13/w mit Adipositas und Konzentrationserhöhung des thyreoidstimulierenden Hormons (TSH), Vorbereitung auf die Facharztprüfung: Fall 88 - Wölfle, Joachim; Gohlke, Bettina (Monatsschrift Kinderheilkunde, 2022)
CRIS-Team Scopus Importer:2022-09-30

23Na MRI Depicts Early Changes in Ion Homeostasis in Skeletal Muscle Tissue of Patients With Duchenne Muscular Dystrophy - Gerhalter, Teresa; Gast, Lena; Marty, Benjamin; Martin, Jan; Trollmann, Regina; Schüssler, Stephanie; Roemer, Frank; Uder, Michael; Schröder, Rolf; Carlier, Pierre G.; Nagel, Armin Michael; Laun, Frederik Bernd (Journal of Magnetic Resonance Imaging, 2019)
BACKGROUND: Duchenne muscular dystrophy (DMD) is a hereditary neuromuscular disease leading to progressive muscle wasting. Since there is a need for MRI variables that serve as early sensitive indicators of response to treatment, several quantitative MRI methods have been suggested for disease monitoring. PURPOSE: To evaluate the potential of sodium (23 Na) and proton (1 H) MRI methods to assess early pathological changes in skeletal muscle of DMD. STUDY TYPE: Prospective clinical study. POPULATION: 23 Na and 1 H MRI of the right leg were performed in 13 patients with DMD (age 7.8 ± 2.4) and 14 healthy boys (age 9.5 ± 2.2). FIELD STRENGTH/SEQUENCE: 3 T including a multiecho-spin-echo sequence, diffusion-weighted sequences, 1 H spectroscopy, 3-pt Dixon, and 23 Na ultrashort echo time sequences. ASSESSMENT: We obtained water T2 maps, fat fraction (FF), pH, and diffusion properties of the skeletal muscle tissue. Moreover, total tissue sodium concentration (TSC) was calculated from the 23 Na sequence. Intracellular-weighted 23 Na signal (ICwS) was derived from 23 Na inversion-recovery imaging. STATISTICAL TESTS: Results from DMD patients and controls were compared using Wilcoxon rank-sum tests and repeated analysis of variance (ANOVA). Spearman-rank correlations and area under the curve (AUC) were calculated to assess the performance of the different MRI methods to distinguish dystrophic from healthy muscle tissue. RESULTS: FF, water T2 , and pH were higher in DMD patients (0.07 ± 0.03, 39.4 ± 0.8 msec, 7.06 ± 0.03, all P < 0.05) than in controls (0.02 ± 0.01, 36.0 ± 0.4 msec, 7.03 ± 0.02). No difference was observed in diffusion properties. TSC (26.0 ± 1.3 mM, P < 0.05) and ICwS (0.69 ± 0.05 a.u., P < 0.05) were elevated in DMD (controls: 16.5 ± 1.3 mM and 0.47 ± 0.04 a.u.). The ICwS was frequently abnormal in DMD even when water T2 , FF, and pH were in the normal range. 23 Na MRI showed higher AUC values in comparison to the 1 H methods. DATA CONCLUSION: Sodium anomalies were regularly observed in patients with DMD compared with controls, and were present even in absence of fatty degenerative changes and water T2 increases. LEVEL OF EVIDENCE: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;50:1103-1113.
CRIS-Team Scopus Importer:2019-09-20
Keywords: Duchenne muscular dystrophy; proton MRI; skeletal muscle; sodium MRI

2-Deoxyglucose induced unfolded protein response enhances efficacy of immunotoxin Moxetumomab pasudotox against lymphoma and leukemia xenografts - Wagner, Franziska; Meier, C.; Krumbholz, Manuela; Metzler, Markus; Mackensen, Andreas; Müller, Fabian (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Aberrant splicing as potential modifier of the phenotype of junctional epidermolysis bullosa - Mittwollen, R.; Wohlfart, S.; Park, J.; Grosch, Ella; Has, C.; Hohenester, E.; Schneider, Holm; Hammersen, Johanna (Journal of the European Academy of Dermatology and Venereology, 2020)
Background: A lack or dysfunction of the anchoring protein laminin-332 in the basement membrane leads to the skin blistering disorder junctional epidermolysis bullosa (JEB). The mutation c.628G>A in the gene LAMB3 encoding the laminin β3-chain is associated with generalized intermediate JEB; it may introduce an amino acid substitution (p.Glu210Lys) or disrupt splicing. Objective: This retrospective study aimed at determining the effects of aberrant splicing on the JEB phenotype. Methods: LAMB3 transcription was analysed in two siblings compound heterozygous for the LAMB3 mutations p.Glu210Lys and p.Arg635* with a diverging JEB phenotype from late childhood on. Laminin-332 levels in skin sections and in cultured keratinocytes were investigated by immunofluorescence staining. Real-time PCR was used to quantify LAMB3 expression in keratinocytes. RNA splice variants were identified by subcloning of a LAMB3 cDNA fraction and subsequent DNA sequencing. Structural models of laminin-332 helped to assess the impact of certain mutations on laminin-332 folding. Results: Both siblings showed diminished LAMB3 expression. Laminin-332 was equally reduced in skin sections obtained during infancy but differed in keratinocytes isolated during adolescence. Although aberrant LAMB3 splicing with 26 variants was detected in both patients, splicing differed significantly: the full-length LAMB3 transcript harbouring the p.Glu210Lys mutation was found more often in the patient affected less severely (14/108 vs. 5/106 clones; P = 0.03). Structural modelling predicted that several deletions in LAMB3, but not the point mutation p.Glu210Lys, have an effect on laminin-332 folding and secretion. Conclusions: Differential LAMB3 mRNA splicing in the patients may explain the disparate JEB phenotype. By elucidating the regulation of laminin-332 gene expression, these findings may contribute to the development of therapeutic strategies for JEB and might help to understand phenotype modification by splice-site mutations in other hereditary diseases.
CRIS-Team Scopus Importer:2020-06-02

A case of severe autosomal recessive spinocerebellar ataxia type 18 with a novel nonsense variant in GRID2 - Hetzelt, Katalin; Kraus, Cornelia; Kusnik, Stefan; Thiel, Christian; Uebe, Steffen; Ekici, Arif Bülent; Trollmann, Regina; Reis, André; Zweier, Christiane (European Journal of Medical Genetics, 2020)
Autosomal-recessive spinocerebellar ataxia type 18 (SCAR18) is a rare neurologic disorder. It is caused by bi-allelic aberrations in the GRID2 gene, encoding an ionotropic glutamate receptor. In total, 20 affected individuals with mainly homozygous/compound heterozygous intragenic deletions/duplications, two different missense variants and one nonsense variant in GRID2 have been reported, so far. SCAR18 is characterized by delayed psychomotor development, intellectual disability, severely impaired gait due to cerebellar ataxia, ocular movement abnormalities, and cerebellar atrophy in brain imaging. By trio exome sequencing, we now identified a novel homozygous nonsense variant (c.568C > T; p.Gln190*) in GRID2 in a four year old female from a consanguineous family who presented with a particularly severe manifestation of SCAR18. The girl was born after an uneventful pregnancy and showed early-onset, profoundly delayed psychomotor development with no achieved psychomotor milestones at age 4 years. Additionally, she presented with severe muscular hypotonia, progressive truncal and appendicular ataxia, binocular vertical nystagmus, central hearing loss and incomplete loss of sight. She was dystrophic, interacted only very little and had behavioral anomalies such as eating hair and bruxism. Brain imaging showed cerebellar hypoplasia, extended cerebrospinal fluid spaces and beginning reduction of cerebral volume. Our findings further delineate the mutational and clinical spectrum of GRID2-associated spinocerebellar ataxia type 18 and indicate that homozygous nonsense variants are possibly associated with the severe end of the SCAR18 phenotypic spectrum.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Ataxia; Autosomal-recessive; Cerebellar hypoplasia; GRID2; Psychomotor development; SCAR18

A Causal Treatment for X-Linked Hypohidrotic Ectodermal Dysplasia: Long-Term Results of Short-Term Perinatal Ectodysplasin A1 Replacement - Schneider, Holm; Schweikl, Christine; Faschingbauer, Florian; Hadj-Rabia, Smail; Schneider, Pascal (International Journal of Molecular Sciences, 2023)
X-linked hypohidrotic ectodermal dysplasia (XLHED), caused by a genetic deficiency of ectodysplasin A1 (EDA1), is a rare developmental disorder of ectodermal derivatives such as hair, sweat glands, and teeth. The absence of sweat glands and perspiration can evoke life-threatening hyperthermia. As molecular genetic findings are not always conclusive, the concentrations of circulating EDA1 may help to distinguish between total and partial EDA1 deficiencies. We previously treated nine male patients with obvious signs of XLHED with a recombinant EDA1 replacement protein, Fc-EDA, either shortly after birth (n = 3) or by prenatal administration in gestational week 26 and beyond (n = 6). Here, we present the long-term follow-up for up to six years. In patients who had received Fc-EDA after birth, neither sweat glands nor sweating ability were detected at the age of 12–60 months. In contrast, prenatal EDA1 replacement resulted in ample sweat gland development and pilocarpine-inducible sweating in all treated subjects, who also attained more permanent teeth than their untreated affected relatives. Normal perspiration has persisted for six years in the two oldest boys treated repeatedly with Fc-EDA in utero. When they had a sauna, adequate thermoregulation was evidenced. Lower sweat production after single prenatal dosing may indicate a dose–response relationship. The absence of circulating EDA1 in five prenatally treated subjects proved that these children would have been unable to perspire if they had been left untreated. The sixth infant was shown to produce an EDA1 molecule that, albeit interacting with its cognate receptor, cannot activate EDA1 signaling. In conclusion, a causal treatment of XLHED before birth is feasible.
CRIS-Team Scopus Importer:2023-05-12
Keywords: AlphaLisa; ectodermal dysplasia; ectodysplasin A; prenatal therapy; protein replacement; sweat glands; tooth development

A Comparison of GFR Estimation Formulae in Pediatric Oncology - Rechenauer, Tobias; Zierk, Jakob; Graefe, Daniel; Rascher, Wolfgang; Rauh, Manfred; Metzler, Markus (Klinische Pädiatrie, 2018)
BACKGROUND: Application of potentially nephrotoxic chemotherapy requires continuous monitoring of renal function for toxicity and dosing. Novel pediatric glomerular filtration rate (GFR) estimating equations including cystatin C have been proposed to enhance the reliability of GFR calculation. MATERIALS AND METHODS: We examined a pediatric oncologic data set with a total of 363 GFR measurements. An analysis of distribution characteristics and comparison of medians was performed to compare creatinine and cystatin C-based GFR estimating formulae. Furthermore, we investigated the clinical impact of different equations in regard to therapeutic consequences. RESULTS: Significant differences in estimated GFR values were calculated depending on the applied formula (range of median GFR from 94.8 to 180.9 mL/min per 1.73 m2) which may result in different therapeutic consequences for the use of potentially nephrotoxic chemotherapeutic agents. Significant correlation for all examined formulae was identified, however there were large fluctuations among the correlation coefficients ranging from 0.254 to 1.0. CONCLUSION: This study compares proposed pediatric GFR estimating equations in a clinical setting. It underlines the current limitations and difficulties of GFR estimation including potential dosing errors. Cystitis C-based equations can be used as alternatives to creatinine-based estimations when the appropriate laboratory method has been applied. A comparative calculator for pediatric GFR estimating equations along with background information is provided at http://gfr.pedz.de and may support clinical decision-making.
EVALuna2:35479

Activation of canonical Wnt signalling is required for TGF-β-mediated fibrosis - Akhmetshina, Alfiya; Palumbo, Katrin; Dees, Clara; Bergmann, Christina; Venalis, Paulius; Zerr, Pawel; Horn, Angelika; Kireva, Trayana; Beyer, Christian; Zwerina, Jochen; Schneider, Holm; Sadowski, Anika; et al. (Nature Communications, 2012)
The transforming growth factor-β (TGF-β) signalling pathway is a key mediator of fibroblast activation that drives the aberrant synthesis of extracellular matrix in fibrotic diseases. Here we demonstrate a novel link between transforming growth factor-β and the canonical Wnt pathway. TGF-β stimulates canonical Wnt signalling in a p38-dependent manner by decreasing the expression of the Wnt antagonist Dickkopf-1. Tissue samples from human fibrotic diseases show enhanced expression of Wnt proteins and decreased expression of Dickkopf-1. Activation of the canonical Wnt pathway stimulates fibroblasts in vitro and induces fibrosis in vivo. Transgenic overexpression of Dickkopf-1 ameliorates skin fibrosis induced by constitutively active TGF-β receptor type I signalling and also prevents fibrosis in other TGF-β-dependent animal models. These findings demonstrate that canonical Wnt signalling is necessary for TGF-β-mediated fibrosis and highlight a key role for the interaction of both pathways in the pathogenesis of fibrotic diseases. © 2012 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2020-07-01

Active visfatin is elevated in serum of maintenance haemodialysis patients and correlates inversely with circulating HDL cholesterol - Nuesken, Kai-Dietrich; Petrasch, Maurice; Rauh, Manfred; Stoehr, Wolfgang; Nuesken, Eva; Schneider, Holm; Dötsch, Jörg (Nephrology Dialysis Transplantation, 2009)
Background. Increased circulating visfatin may be associated both with endothelial damage and with increased mortality in end-stage renal disease (ESRD). HDL cholesterol is an independent, strong inverse predictor of cardiovascular events. However, associations between visfatin and parameters of lipid metabolism are unclear. Moreover, serum concentrations of visfatin measured by an enzyme immuno assay (EIA) are conflicting and do not correlate with ELISA (enzyme-linked immunosorbent assay) data, which predominantly detect enzymatically active visfatin.Methods. A total of 74 haemodialysis (HD) patients and 35 control individuals (C) were studied. All subjects (mean age 62.9 years) provided fasted blood samples (HD patients after 66-69 h without dialysis). Circulating visfatin was measured by the ELISA. Body composition was evaluated using waist circumference, skinfold thickness and body impedance analysis. Results obtained by the ELISA were compared with EIA data.Results. Active serum visfatin was increased in HD (5.58 ± 6.50 ngml) versus C 0.97 ± 1.79 ngml, mean ± SD; P < 0.0001 by multiple regression analysis (MRA) independently of plasma glucose, serum insulin, diabetes, HDL cholesterol and body composition. Within the HD group, only plasma HDL cholesterol (4 lower per additional mgdl HDL; P = 0.001) and insulin-treated diabetes mellitus subgroup of n = 18; 119 higher compared with patients without diabetes (n = 40); P = 0.011 were independently (by MRA) associated with active serum visfatin. Visfatin measured by an EIA showed no correlation with ELISA data.Conclusions. Our study provides reliable data on active visfatin in HD patients using a well-characterized ELISA. Loss of renal function is accompanied by increased circulating active visfatin concentrations in our patients. Furthermore, decreased HDL cholesterol may hint at an increased probability of cardiovascular events in HD patients with elevated serum visfatin.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Body composition; Diabetes; End-stage renal disease; HDL cholesterol; Visfatin

Activin A in perinatal brain injury - Brackmann, Florian; Alzheimer, Christian; Trollmann, Regina (Neuropediatrics, 2015)
Activin A is a multifunctional growth and differentiation factor belonging to the transforming growth factor ? (TGF-?) family. Growing evidence indicates its role as a neurotrophic factor and regulator of synaptic transmission as well as its functional importance in several types of cerebral injury. We recently described age-dependent expression of activin A and its regulation at the mRNA and protein level under different conditions of global hypoxia in the neonatal mouse brain. This review discusses the current knowledge of the function and regulation of activin A from human studies as well as from experimental models of brain injury focusing on acquired lesions of the developing rodent brain during the early stages of brain maturation.
EVALuna2:2466

Adamantinomatous and papillary craniopharyngiomas are characterized by distinct epigenomic as well as mutational and transcriptomic profiles - Hoelsken, Annett; Sill, Martin; Merkle, Jessica; Schweizer, Leonille; Buchfelder, Michael; Flitsch, Joerg; Fahlbusch, Rudolf; Metzler, Markus; Kool, Marcel; Pfister, Stefan M.; Von Deimling, Andreas; Capper, David; et al. (Acta Neuropathologica Communications, 2016)
Craniopharyngiomas (CP) are rare epithelial tumors of the sellar region. Two subtypes, adamantinomatous (adaCP) and papillary CP (papCP), were previously identified based on histomorphological and epidemiological aspects. Recent data indicates that both variants are defined by specific genetic alterations, and influenced by distinct molecular pathways and particular origins. The fact that CP is an uncommon tumor entity renders studies on large cohorts difficult and exceptional. In order to achieve further insights distinguishing CP variants, we conducted whole genome methylation (450 k array) and microarray-based gene expression studies in addition to CTNNB1 and BRAF mutation analysis using a comprehensive cohort of 80 adaCP and 35 papCP.BRAF V600E mutations were solely found in the papCP subgroup and were not detectable in adaCP samples. In contrast, CTNNB1 mutations were exclusively detected in adaCP. The methylome fingerprints assigned DNA specimens to entity-specific groups (papCP (n = 18); adaCP (n = 25)) matching perfectly with histology-based diagnosis, suggesting that they represent truly distinct biological entities. However, we were not able to detect within the adaCP group (including 11 pediatric and 14 adult cases) a significant difference in methylation signature by age. Integrative comparison of the papCP with the adaCP group based on differential gene expression and methylation revealed a distinct upregulation of Wnt- and SHH signaling pathway genes in adaCP.AdaCP and papCP thus represent distinct tumor subtypes that harbor mutually exclusive gene mutations and methylation patterns, further reflected in differences in gene expression. This study demonstrates that DNA methylation analyses are an additional method to classify CP into subtypes, and implicates a role of epigenetic mechanisms in the genesis of the respective CP variants. Detection of tumor-specific signaling pathway activation enables the possibility of target-oriented intervention.
EVALuna2:7314

Adenosine-generating CD39+ plasmablasts predispose to successful infliximab therapy in pediatric IBD - Schnell, Alexander; Schwarz, Benedikt; Schmidt, Hannah; Allabauer, Ida; Schuh, Wolfgang; Regensburger, Adrian; Rauh, Manfred; Wölfle, Joachim; Hörning, André (Life Science Alliance, 2025)
B cells display several immunoregulatory mechanisms including the production of interleukin-10. Ectonucleotidases like CD39 and CD73 influence immune homeostasis by metabolizing eATP and generating immunosuppressive adenosine. The major objective was to examine the expression of those immunoregulatory molecules on B-cell subsets, and, more specifically, to determine their association with an infliximab (IFX) treatment in a pediatric inflammatory bowel disease (IBD) cohort. 42 IBD patients were assessed for IFX response after 12 mo of therapy and compared against 14 healthy controls (HC). Although IL10-producing plas-mablasts were decreased in IFX nonresponders (NRS), we de-tected an up-regulation of CD39 on plasmablasts and increased fractions of CD39/CD73-co-expressing naïve and memory B cells in responding patients (RS). In addition, B cells of responders proved to have superior ATP degradation capacities and aden-osine production before therapy initiation compared with NRS and HC. Moreover, IFX nonresponders had a marked deficiency of α4β7hi plasmablasts, whereas both cohorts had fewer CCR9-expressing plasmablasts. Consequently, CD39+ plasmablasts were decreased in biopsies of inflamed mucosal tissues, espe-cially in IFX nonresponders. Our results highlight the regulatory potential of CD39/CD73-expressing B cells in pediatric IBD and suggest CD39+ plasmablasts as a potential determinant of a successful immunosuppressive therapy with IFX.
CRIS-Team Scopus Importer:2025-05-02

Adrenal crisis in a 14-year-old boy 12 years after hematopoietic stem cell transplantation - Penger, Theresa; Albrecht, Andrea; Marx, Martin; Stachel, Daniel; Metzler, Markus; Dörr, Helmuth-Günther (Endocrinology, Diabetes and Metabolism Case Reports, 2018)
We report on a boy of Albanian descent with the history of juvenile myelomonocytic leukemia (JMML). JMML was diagnosed at the age of 17 months and treated by hematopoietic stem cell transplantation (HSCT). At the age of 14.3 years, about 12 years after HSCT, he was hospitalized with an adrenal crisis. Hormone findings were consistent with primary adrenal insufficiency. Autoimmune adrenalitis was confirmed by positive autoantibodies against 21-hydroxylase and adrenal tissue. Since autoimmune Hashimoto thyroiditis was already known from the age of 9 years, we assume that both diseases are part of the spectrum of autoimmune polyglandular syndrome (APS) type 2. APS type 2 is a rare endocrine disease characterized by Addison's disease along with autoimmune thyroid disease and/or type 1 diabetes. Learning points: Endocrine sequelae after hematopoietic stem cell transplantation (HSCT) are common and can develop over a long period.Primary adrenal insufficiency after HSCT is absolutely rare.The combination of adrenal autoimmune disease and Hashimoto thyroiditis is consistent with autoimmune polyglandular syndrome type 2.
EVALuna2:35483

Adrenarche and pubarche in girls with turner syndrome during growth-promoting therapy with human growth hormone - Dörr, Helmuth-Günther; Penger, Theresa; Marx, Martin; Rauh, Manfred; Oppelt, Patricia; Völkl, Thomas (BMC Endocrine Disorders, 2019)
Background: Data on adrenarche and pubarche in girls with Turner syndrome (TS) are inconsistent in the literature. Methods: The cohort consisted of 94 girls and young women with TS born between 1971 and 2001 (age range: 3.1-23.2 yrs.), who were treated with human growth hormone and regularly presented at our outpatient clinic every 4 to 6 months.The longitudinal data of all patients were ascertained retrospectively from patient charts. The data collection ended in January 2016. Adrenarche was assessed by serum DHEAS levels and pubertal status by Tanner stages. Pubarche was defined as the appearance of pubic hair (PH2), whereas spontaneous puberty was defined as Tanner stage B2. The patients were retrospectively subdivided in two groups with regard to pubertal development: group 1 (n = 21) with spontaneous puberty and group 2 (n = 70) with induced puberty. Since blood samples were not taken at every visit, we generated seven groups according to the age of the children at which the blood samples were taken: 3-5, 5-7, 7-9, 9-11, 11-13, 13-15, and 15-17 yrs. Serum DHEAS and follicle-stimulating hormone (FSH) levels were measured by chemiluminescence immunoassay and compared with those of a control group of healthy girls. Results: Adrenarche started in TS girls between 5 and 7 years. TS girls had higher DHEAS levels than the control group, with statistically significant differences in the age groups 7 to 17 years. No differences were determined between the TS girls with spontaneous puberty and those with POI. TS girls in group 2 reached the Tanner stages PH2 (p < 0.04), PH3 (p < 0.01), PH4 and PH5 (p < 0.001) markedly later than TS girls in group 1. Conclusions: The onset of adrenarche in girls with TS undergoing GH therapy does not differ from that in healthy girls. However, adrenarche is more pronounced in girls with TS. There is no difference in DHEAS levels between the TS girls with spontaneous puberty and the TS girls with primary ovarian insufficiency (POI), while the tempo of pubarche is markedly slower in the girls with POI.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Adrenarche; DHEAS; Primary ovarian insufficiency; Turner syndrome

aEEG Use in Pediatric Critical Care—An Online Survey - Bruns, Nora; Felderhoff-Müser, Ursula; Dohna-Schwake, Christian; Wölfle, Joachim; Müller, Hanna (Frontiers in Pediatrics, 2020)
Background: Evidence supporting continuous EEG monitoring in pediatric intensive care is increasing, but continuous full-channel EEG is a scarce resource. Amplitude-integrated EEG (aEEG) monitors are broadly available in children's hospitals due to their use in neonatology and can easily be applied to older patients. Objective: The aim of this survey was to evaluate the use of amplitude-integrated EEG in German and Swiss pediatric intensive care units (PICUs). Design: An online survey was sent to German and Swiss PICUs that were identified via databases provided by the German Pediatric Association (DGKJ) and the Swiss Society of Intensive Care (SGI). The questionnaire contained 18 multiple choice questions including the PICU size and specialization, indications for aEEG use, perceived benefits from aEEG, and data storage. Main results: Forty-three (26%) PICUs filled out the questionnaire. Two thirds of all interviewed PICUs use aEEG in non-neonates. Main indications were neurological complications or disease and altered mental state. Features assessed were mostly seizures and side differences, less frequently height of amplitude and background pattern. Interpretation of raw EEG also played an important role. All interviewees would appreciate the establishment of reference values for toddlers and children. Conclusions: aEEG is used in a large proportion of the interviewed PICUs. The wide-spread use without validation of data generates the need for further evaluation of this technique and the establishment of reference values for non-neonates.
CRIS-Team Scopus Importer:2020-02-18
Keywords: aEEG; amplitude-integrated EEG; continuous EEG; neuromonitoring; pediatric critical care; survey

Age- and sex-specific dynamics in 22 hematologic and biochemical analytes from birth to adolescence - Zierk, Jakob; Arzideh, Farhad; Rechenauer, Tobias; Haeckel, Rainer; Rascher, Wolfgang; Metzler, Markus; Rauh, Manfred (Clinical Chemistry, 2015)
Pediatric laboratory test results must be interpreted in the context of interindividual variation and age- and sex-dependent dynamics. Reference intervals as presently defined for separate age groups can only approximate the age-related dynamics encountered in pediatrics. Continuous reference intervals from birth to adulthood are not available for most laboratory analytes because of the ethical and practical constraints of defining reference intervals using a population of healthy community children. We applied an indirect method to generate continuous reference intervals for 22 hematologic and biochemical analytes by analyzing clinical laboratory data from blood samples taken during clinical care of patients.We included samples from 32 000 different inpatients and outpatients (167 000 samples per analyte) from a German pediatric tertiary care center. Measurements were performed on a Sysmex-XE 2100 and a Cobas Integra 800 during clinical care over a 6-year period. The distribution of samples considered normal was estimated with an established indirect statistical approach and used for the calculation of reference intervals.We provide continuous reference intervals from birth to adulthood for 9 hematology analytes (hemoglobin, hematocrit, red cell indices, red cell count, red cell distribution width, white cell count, and platelet count) and 13 biochemical analytes (sodium, chloride, potassium, calcium, magnesium, phosphate, creatinine, aspartate transaminase, alanine transaminase, ?-glutamyltransferase, alkaline phosphatase, lactate dehydrogenase, and total protein).Continuous reference intervals capture the population changes in laboratory analytes during pediatric development more accurately than age groups. After local validation, the reference intervals provided should allow a more precise consideration of these dynamics in clinical decision making.
EVALuna2:18920

Age- and sex-specific pediatric reference intervals for neutrophil-to-lymphocyte ratio, lymphocyte-to-monocyte ratio, and platelet-to-lymphocyte ratio - Moosmann, Julia; Krusemark, Anja; Dittrich, Sven; Ammer, Tatjana; Rauh, Manfred; Wölfle, Joachim; Metzler, Markus; Zierk, Jakob (International Journal of Laboratory Hematology, 2021)
Introduction: Neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lymphocyte-to-monocyte ratio (LMR) are emerging biomarkers for systemic inflammation and have been shown to predict morbidity and mortality for several diseases. However, lack of pediatric reference intervals (RIs) prevents their comprehensive use in patient care and medical research. Material and Methods: We calculated reference intervals and corresponding confidence intervals for NLR, PLR, and LMR from birth to 18 years using a data-mining approach: We analyzed 232 746 blood counts from 60 685 patients performed during patient care and excluded patients with elevated C-reactive protein and procalcitonin. Test results were separated according to age and sex, and the distribution of physiological ratios was estimated using an indirect approach (refineR). Additionally, we investigated the ratios’ diagnostic benefit for different inflammatory diseases (acute appendicitis, asthma, Bell's palsy, Henoch-Schonlein purpura, and cystic fibrosis) using the newly obtained reference intervals. Results: We estimated age- and sex-specific reference intervals from birth to adulthood for NLR, PLR, and LMR. Analyses in pediatric inflammatory diseases showed that PLR and LMR were poor markers to detect the examined inflammatory diseases, while NLR was significantly increased in patients with appendicitis and asthma. Conclusion: We provide pediatric reference intervals for NLR, PLR, and LMR to improve the interpretation of these biomarkers in children.
CRIS-Team Scopus Importer:2021-12-03
Keywords: blood components; inflammation; leukocytes; monocytes; neutrophils; platelets

Age of epilepsy onset as modulating factor for naming deficit after epilepsy surgery: a voxel-based lesion-symptom mapping study - Reindl, Caroline; Walther, Katrin; Allgäuer, Anna-Lena; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Schwarz, Michael; Trollmann, Regina; Madzar, Dominik; Knott, Michael; Dörfler, Arnd; et al. (Scientific Reports, 2023)
Age at onset of epilepsy is an important predictor of deterioration in naming ability following epilepsy surgery. In 141 patients with left hemispheric epilepsy and language dominance who received epilepsy surgery at the Epilepsy Centre Erlangen, naming of objects (Boston naming test, BNT) was assessed preoperatively and 6 months postoperatively. Surgical lesions were plotted on postoperative MRI and normalized for statistical analysis using voxel-based lesion-symptom mapping (VBLSM). The correlation between lesion and presence of postoperative naming deterioration was examined varying the considered age range of epilepsy onsets. The VBLSM analysis showed that volumes of cortex areas in the left temporal lobe, which were associated with postoperative decline of naming, increased with each year of later epilepsy onset. In patients with later onset, an increasing left posterior temporobasal area was significantly associated with a postoperative deficit when included in the resection. For late epilepsy onset, the temporomesial expansion also included the left hippocampus. The results underline that early onset of epilepsy is a good prognostic factor for unchanged postoperative naming ability following epilepsy surgery. For later age of epilepsy onset, the extent of the area at risk of postoperative naming deficit at 6 months after surgery included an increasing left temporobasal area which finally also comprised the hippocampus.
CRIS-Team Scopus Importer:2023-09-08

Age-related Differences in Immune Reactions to SARS-CoV-2 Spike and Nucleocapsid Antigens - Morhart, Patrick; Kehl, Sven; Schuh, Wolfgang; Hermes, Katharina; Meltendorf, Stefan; Neubert, Antje; Schneider, Michael; Brunner-Weinzierl, Monika; Schneider, Holm; Lingel, Holger (In Vivo, 2023)
Background/Aim: The manifestation and severity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections show a clear correlation to the age of a patient. The younger a person, the less likely the infection results in significant illness. To explore the immunological characteristics behind this phenomenon, we studied the course of SARS-CoV-2 infections in 11 households, including 8 children and 6 infants/neonates of women who got infected with SARS-CoV-2 during pregnancy. Materials and Methods: We investigated the immune responses of peripheral blood mononuclear cells (PBMCs), umbilical cord blood mononuclear cells (UCBCs), and T cells against spike and nucleocapsid antigens of SARS-COV-2 by flow cytometry and cytokine secretion assays. Results: Upon peptide stimulation, UCBC from neonates showed a strongly reduced IFN-γ production, as well as lower levels of IL-5, IL-13, and TNF-α alongside with decreased frequencies of surface CD137/PD-1 co-expressing CD4+ and CD+8 T cells compared with adult PBMCs. The PBMC response of older children instead was characterized by elevated frequencies of IFN-γ+ CD4+ T cells, but significantly lower levels of multiple cytokines (IL-5, IL-6, IL-9, IL-10, IL-17A, and TNF-α) and a marked shift of the CD4+/CD8+ T-cell ratio towards CD8+ T cells in comparison to adults. Conclusion: The increased severity of SARS-CoV-2 infections in adults could result from the strong cytokine production and lower potential to immunomodulate the excessive inflammation, while the limited IFN-γ production of responding T cells in infants/neonates and the additional higher frequencies of CD8+ T cells in older children may provide advantages during the course of a SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2023-01-13
Keywords: children; COVID-19; immune response; inflammation; neonates; pediatric immunology; SARS-CoV-2; spike protein

A Half-Century of Heterotopic Heart Transplantation in Mice: The Spearhead of Immunology Research - Yin, Decheng; Dewald, Oliver; Peng, Xiangyu; Nie, Wenlong; Rong, Song; Dudziak, Diana; Lehmann, Christian; Hörning, André; Fu, Jian (Transplantology, 2024)
Since the success of solid organ transplants, such as human kidneys, livers and hearts, from the 50s to the 60s in the last century, the field of organ transplantation has progressed rapidly. Mainly due to modifications in surgical operation techniques and improvements in immunosuppressive therapy regimes, organ survival time can now be greatly prolonged. This progress has also been dependent upon the availability of appropriate animal models for organ transplantation. Therefore, the mouse heart transplantation model has developed into an irreplaceable research model for solid organ transplantation, providing indelible contributions to the field. In this review, we will provide an overview of the technical developments in murine heart transplantation, as well as its historical and current role for alloimmune research. Further, we will describe its current fields of application and its scientific achievements before we discuss potential future applications.
CRIS-Team Scopus Importer:2025-02-04
Keywords: heterotopic heart transplantation; immunology; murine transplantation

A high proportion of germline variants in pediatric chronic myeloid leukemia - Krumbholz, Manuela; Dolnik, Anna; Sträng, Eric; Ghete, Tabita; Skambraks, Sabrina; Hutter, Stephan; Simonis, Alfred; Stegelmann, Frank; Suttorp, Meinolf; Horn, Anselm; Sticht, Heinrich; Haferlach, Torsten; et al. (Molecular Cancer, 2024)
Chronic myeloid leukemia (CML) typically occurs in late adulthood. Pediatric CML is a rare form of leukemia. In all age groups, the characteristic genetic driver of the disease is the BCR::ABL1 fusion gene. However, additional genomic events contribute to leukemic transformation, which is not yet well-characterized in pediatric CML. We investigated the mutational landscape of pediatric CML to determine whether predisposing germline variants may play a role in early-age disease development. Whole exome sequencing and targeted sequencing were performed in pediatric and adult CML samples to identify age-related germline and somatic variants in addition to the BCR::ABL1 translocation. Germline variants were detected in about 60% of pediatric patients with CML, with predominantly hematopoietic genes affected, most frequently ASXL1, NOTCH1, KDM6B, and TET2. The number of germline variants was significantly lower in adult patients with CML. If only confirmed pathogenic variants were regarded as cancer-predisposing variants, the occurrence was 10% of pediatric CML, which is comparable to other hematological malignancies and most childhood cancer entities in general. We hypothesize that the interaction with the strong oncogene BCR::ABL1 may also favor the development of leukemia by weaker variants in the same genes. In pediatric patients, the germline variants of genes associated with clonal hematopoiesis may increase the likelihood that an incidental BCR::ABL1 translocation triggers the early manifestation of CML.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Cancer predisposition; Chronic myeloid leukemia; Germline variants; Pediatric CML

ALOX12B and PNPLA1 Have Distinct Roles in Epidermal Lipid Lamellar Organization - Meyer, Jason M.; Vávrová, Kateřina; Radner, Franz P.W.; Schneider, Holm; Dick, Angela; Mauro, Theodora M.; Elias, Peter M. (Journal of Investigative Dermatology, 2022)
CRIS-Team Scopus Importer:2022-12-16

Aloxe3 knockout mice reveal a function of epidermal lipoxygenase-3 as hepoxilin synthase and its pivotal role in barrier formation - Krieg, Peter; Rosenberger, Sabine; De Juanes, Silvia; Latzko, Susanne; Hou, Jin; Dick, Angela; Kloz, Ulrich; Van Der Hoeven, Frank; Hausser, Ingrid; Esposito, Irene; Rauh, Manfred; Schneider, Holm (Journal of Investigative Dermatology, 2013)
Loss-of-function mutations in the lipoxygenase (LOX) genes ALOX12B and ALOXE3 are the second most common cause of autosomal recessive congenital ichthyosis. The encoded proteins, 12R-LOX and epidermal LOX-3 (eLOX-3), act in sequence to convert fatty acid substrates via R-hydroperoxides to specific epoxyalcohol derivatives and have been proposed to operate in the same metabolic pathway during epidermal barrier formation. Here, we show that eLOX-3 deficiency in mice results in early postnatal death, associated with similar but somewhat less severe barrier defects and morphological changes than reported earlier for the 12R-LOX-knockout mice. Skin lipid analysis demonstrated that the severity of barrier failure is related to the loss of covalently bound ceramides in both 12R-LOX- and eLOX-3-null mice, confirming a proposed functional linkage of the LOX pathway to ceramide processing and formation of the corneocyte lipid envelope. Furthermore, analysis of free oxygenated fatty acid metabolites revealed strongly reduced levels of hepoxilin metabolites in eLOX-3-deficient epidermis, indicating an additional function of eLOX-3 in mammalian skin as a hepoxilin synthase linked to the 12S-LOX pathway. © 2013 The Society for Investigative Dermatology.
CRIS-Team Scopus Importer:2020-07-01

Alpha8 Integrin (Itga8) Signalling Attenuates Chronic Renal Interstitial Fibrosis by Reducing Fibroblast Activation, Not by Interfering with Regulation of Cell Turnover - Marek, Ines; Lichtneger, Till-Simon; Cordasic, Nada; Hilgers, Karl Friedrich; Volkert, Gudrun; Fahlbusch, Fabian; Rascher, Wolfgang; Menendez-Castro, Carlos; Hartner, Andrea (PLoS ONE, 2016)
The ?8 integrin (Itga8) chain contributes to the regulation of cell proliferation and apoptosis in renal glomerular cells. In unilateral ureteral obstruction Itga8 is de novo expressed in the tubulointerstitium and a deficiency of Itga8 results in more severe renal fibrosis after unilateral ureteral obstruction. We hypothesized that the increased tubulointerstitial damage after unilateral ureteral obstruction observed in mice deficient for Itga8 is associated with altered tubulointerstitial cell turnover and apoptotic mechanisms resulting from the lack of Itga8 in cells of the tubulointerstitium. Induction of unilateral ureteral obstruction was achieved by ligation of the right ureter in mice lacking Itga8. Unilateral ureteral obstruction increased proliferation and apoptosis rates of tubuloepithelial and interstitial cells, however, no differences were observed in the tubulointerstitium of mice lacking Itga8 and wild type controls regarding fibroblast or proliferating cell numbers as well as markers of endoplasmic reticulum stress and apoptosis after unilateral ureteral obstruction. In contrast, unilateral ureteral obstruction in mice lacking Itga8 led to more pronounced tubulointerstitial cell activation i.e. to the appearance of more phospho-SMAD2/3-positive cells and more ?-smooth muscle actin-positive cells in the tubulointerstitium. Furthermore, a more severe macrophage and T-cell infiltration was observed in these animals compared to controls. Thus, Itga8 seems to attenuate tubulointerstitial fibrosis in unilateral ureteral obstruction not via regulation of cell turnover, but via regulation of TGF-? signalling, fibroblast activation and/or immune cell infiltration.
EVALuna2:3858

A mathematical model of white blood cell dynamics during maintenance therapy of childhood acute lymphoblastic leukemia - Le, Thuy T.T.; Jost, Felix; Raupach, Thomas; Zierk, Jakob; Rauh, Manfred; Suttorp, Meinolf; Stanulla, Martin; Metzler, Markus; Sager, Sebastian (Mathematical Medicine and Biology, 2019)
Acute lymphoblastic leukemia is the most common malignancy in childhood and requires prolonged oral maintenance chemotherapy to prevent disease relapse after remission induction with intensive intravenous chemotherapy. In maintenance therapy, drug doses of 6-mercaptopurine (6-MP) and methotrexate (MTX) are adjusted to achieve sustained antileukemic activity without excessive myelosuppression. However, uncertainty exists regarding timing and extent of drug dose responses and optimal dose adaptation strategies. We propose a novel comprehensive mathematical model for 6-MP and MTX pharmacokinetics, pharmacodynamics and myelosuppression in acute lymphoblastic maintenance therapy. We personalize and cross-validate the mathematical model using clinical data and propose a real-time algorithm to predict chemotherapy responses with a clinical decision support system as a potential future application.
CRIS-Team Scopus Importer:2019-12-24
Keywords: chemotherapy; childhood acute lymphoblastic leukemia; maintenance therapy; ordinary differential equations; parameter estimation; real-time algorithm

A Modified Surgical Technique for Kidney Transplantation in Mice - Yin, Decheng; Fu, Jian; Chen, Rongjun; Shushakova, Nelli; Allabauer, Ida; Wei, Xinyi; Schiffer, Mario; Dudziak, Diana; Rong, Song; Hörning, André (Journal of Visualized Experiments, 2022)
Kidney transplantation in mice is a complicated and challenging surgery procedure. There are very few publications demonstrating the key steps of this operation. Therefore, this article introduces the technique and points out the surgical caveats associated with this operation. In addition, important modifications in comparison to the conventional procedure are demonstrated. Firstly, a patch of the abdominal aorta is cut and prepared so that the proximal bifurcations of the renal artery, including the ureteral artery are transected together with the donor kidney en bloc. This reduces the risk of a ureter necrosis and avoids the development of a urinary tract occlusion. Secondly, a new method of the vascular anastomosis is demonstrated that allows the operator to flexibly increase or decrease the size of the anastomosis after renal transplant reperfusion has already been initiated. This avoids the development of vessel strictures and intraabdominal bleeding. Thirdly, a technique that enables the anastomosis of the delicate donor ureter and the recipient bladder that does not cause a trauma is shown. Adopting this protocol can shorten the operation time and reduces the damage to the recipient's bladder, thereby significantly increasing the operation success rate for the recipient mice.
CRIS-Team Scopus Importer:2022-08-19

A mouse organotypic tissue culture model for autosomal recessive congenital ichthyosis - Rosenberger, S.; Dick, Angela; Latzko, S.; Hausser, I.; Stark, H. -J.; Rauh, Manfred; Schneider, Holm; Krieg, P. (British Journal of Dermatology, 2014)
Autosomal recessive congenital ichthyoses (ARCIs) are keratinization disorders caused by impaired skin barrier function. Mutations in the genes encoding the lipoxygenases 12R-LOX and eLOX-3 are the second most common cause of ARCIs. In recent years, human skin equivalents recapitulating the ARCI phenotype have been established.To develop a murine organotypic tissue culture model for ARCI.Epidermal keratinocytes were isolated from newborn 12R-LOX-deficient mice and cocultivated with mouse dermal fibroblasts embedded in a scaffold of native collagen type I.With this experimental set-up the keratinocytes formed a well-organized multilayered stratified epithelium resembling skin architecture in vivo. All epidermal layers were present and the keratinocytes within showed the characteristic morphological features. Markers for differentiation and maturation indicated regular epidermal morphogenesis. The major components of epidermal structures were expressed, and were obviously processed and assembled properly. In contrast to their wild-type counterparts, 12R-LOX-deficient skin equivalents showed abnormal vesicular structures in the upper epidermal layers correlating with altered lipid composition and increased transepidermal water loss, comparable with 12R-LOX-deficient mice.The mouse skin equivalents faithfully recapitulate the 12R-LOX-deficient phenotype observed in vivo, classifying them as appropriate in vitro models to study molecular mechanisms involved in the development of ARCI and to evaluate novel therapeutic agents. In contrast to existing human three-dimensional skin models, the generation of these murine models is not constrained by a limited supply of material and does not depend on in vitro expansion and/or genetic manipulations that could result in inadvertent genotypic and phenotypic alterations.
EVALuna2:18903

A multicenter, matched case-control analysis comparing burden-of-illness in Dravet syndrome to refractory epilepsy and seizure remission in patients and caregivers in Germany - Strzelczyk, Adam; Schubert-Bast, Susanne; Bast, Thomas; Bettendorf, Ulrich; Fiedler, Barbara; Hamer, Hajo; Herting, Arne; Kalski, Malin; Kay, Lara; Kieslich, Matthias; Klein, Karl Martin; Kluger, Gerhard; et al. (Epilepsia, 2019)
Objective: To compare direct and indirect costs and quality of life (QoL) of pediatric and adult patients with Dravet syndrome (DS), with drug-resistant epilepsy (DRE) and in seizure remission (SR), and their caregivers, in Germany. Methods: Questionnaire responses from 93 DS patients and their caregivers were matched by age and gender with responses from 93 DRE and 93 SR patients collected in independent studies, and were compared across main components of QoL, direct costs (patient visits, medication use, care level, medical equipment, and ancillary treatments), and indirect costs (quitting job, reduced working hours, missed days). Results: Mean total direct costs were highest for DS patients (€4864 [median €3564] vs €3049 [median €1506] for DRE [excluding outliers], P = 0.01; and €1007 [median €311], P < 0.001 for SR). Total lost productivity over 3 months was highest among caregivers of pediatric DS (€4757, median €2841), compared with those of DRE (€1541, P < 0.001; median €0) and SR patients (€891, P < 0.001; median €0). The proportions of caregivers in employment were similar across groups (62% DS, 63% DRE, and 63% SR) but DS caregivers were more likely to experience changes to their working situation, such as quitting their job (40% DS vs 16% DRE and 9% SR, P < 0.001 in both comparisons). KINDL scores were significantly lower for DS patients (62 vs 74 and 72, P < 0.001 in both comparisons), and lower than for the average German population (77). Pediatric caregiver EQ-5D scores across all cohorts were comparable with population norms, but more DS caregivers experienced moderate to severe depressive symptoms (24% vs 11% and 5%). Mean Beck Depression Inventory (BDI-II) score was significantly higher in DS caregivers than either of the other groups (P < 0.001). Significance: This first comparative study of Dravet syndrome to difficult-to-treat epilepsy and to epilepsy patients in seizure remission emphasizes the excess burden of DS in components of QoL and direct costs. The caregivers of DS patients have a greater impairment of their working lives (indirect costs) and increased depression symptoms.
CRIS-Team Scopus Importer:2019-07-09
Keywords: costs; depression; encephalopathy; quality of life; Severe myoclonic epilepsy of infants

A multidisciplinary systematic review of the treatment for chronic idiopathic tinnitus - Zenner, Hans-Peter; Delb, Wolfgang; Kroener-Herwig, Birgit; Jaeger, Burkhard; Peroz, Ingrid; Hesse, Gerhard; Mazurek, Birgit; Goebel, Gerhard; Gerloff, Christian; Trollmann, Regina; Biesinger, Eberhard; Seidler, Harald; et al. (European Archives of Oto-Rhino-Laryngology, 2017)
The majority of tinnitus patients are affected by chronic idiopathic tinnitus, and almost 60 different treatment modalities have been reported. The present study is a multidisciplinary systematic analysis of the evidence for the different forms of treatment for chronic tinnitus. The results are used to form the basis of an S3 guideline. A systematic search was carried out in PubMed and the Cochrane Library. The basis for presenting the level of evidence was the evidence classification of the Oxford Centre of Evidence-based Medicine. Whenever available, randomised controlled trials were given preference for discussing therapeutic issues. All systematic reviews and meta-analyses were assessed for their methodological quality, and effect size was taken into account. As the need for patient counselling is self-evident, specific tinnitus counselling should be performed. Due to the high level of evidence, validated tinnitus-specific, cognitive behavioural therapy is strongly recommended. In addition, auditory therapeutic measures can be recommended for the treatment of concomitant hearing loss and comorbidities; those should also be treated with drugs whenever appropriate. In particular, depression should be treated, with pharmacological support if necessary. If needed, psychiatric treatment should also be given on a case-by-case basis. With simultaneous deafness or hearing loss bordering on deafness, a CI can also be indicated. For auditory therapeutic measures, transcranial magnetic or direct current stimulation and specific forms of acoustic stimulation (noiser/masker, retraining therapy, music, and coordinated reset) for the treatment of chronic tinnitus the currently available evidence is not yet sufficient for supporting their recommendation.
EVALuna2:34026

A mutation of the epithelial sodium channel associated with atypical cystic fibrosis increases channel open probability and reduces Na+ self inhibition - Rauh, Robert; Diakov, Alexei; Tzschoppe, Anja; Korbmacher, Judit; Azad, Abul Kalam; Cuppens, Harry; Cassiman, Jean-Jaques; Dötsch, Jörg; Sticht, Heinrich; Korbmacher, Christoph (The Journal of Physiology, 2010)
Increased activity of the epithelial sodium channel (ENaC) in the respiratory airways contributes to the pathophysiology of cystic fibrosis (CF), a genetic disease caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. In some patients suffering from atypical CF a mutation can be identified in only one CFTR allele. We recently identified in this group of CF patients a heterozygous mutation (W493R) in the α-subunit of ENaC. Here, we investigate the functional effects of this mutation by expressing wild-type αβγENaC or mutant αW493RβγENaC in Xenopus oocytes. The αW493R mutation stimulated amiloride-sensitive whole-cell currents (ΔIami) by ∼4-fold without altering the single-channel conductance or surface expression of ENaC. As these data suggest that the open probability (Po) of the mutant channel is increased, we investigated the proteolytic activation of ENaC by chymotrypsin. Single-channel recordings revealed that chymotrypsin activated near-silent channels in outside-out membrane patches from oocytes expressing wild-type ENaC, but not in membrane patches from oocytes expressing the mutant channel. In addition, the αW493R mutation abolished Na+ self inhibition of ENaC, which might also contribute to its gain-of-function effects. We conclude that the αW493R mutation promotes constitutive activation of ENaC by reducing the inhibitory effect of extracellular Na+ and decreasing the pool of near-silent channels. The resulting gain-of-function phenotype of the mutant channel might contribute to the pathophysiology of CF in patients carrying this mutation. © 2010 The Authors. Journal compilation © 2010 The Physiological Society.
Created from Fastlane, Scopus look-up

An artificial intelligence-assisted clinical framework to facilitate diagnostics and translational discovery in hematologic neoplasia - Tang, Ming; Antić, Željko; Fardzadeh, Pedram; Pietzsch, Stefan; Schröder, Charlotte; Eberhardt, Adrian; van Bömmel, Alena; Escherich, Gabriele; Hofmann, Winfried; Horstmann, Martin A.; Illig, Thomas; McCrary, J. Matt; et al. (EBioMedicine, 2024)
Background: The increasing volume and intricacy of sequencing data, along with other clinical and diagnostic data, like drug responses and measurable residual disease, creates challenges for efficient clinical comprehension and interpretation. Using paediatric B-cell precursor acute lymphoblastic leukaemia (BCP-ALL) as a use case, we present an artificial intelligence (AI)-assisted clinical framework clinALL that integrates genomic and clinical data into a user-friendly interface to support routine diagnostics and reveal translational insights for hematologic neoplasia. Methods: We performed targeted RNA sequencing in 1365 cases with haematological neoplasms, primarily paediatric B-cell precursor acute lymphoblastic leukaemia (BCP-ALL) from the AIEOP-BFM ALL study. We carried out fluorescence in situ hybridization (FISH), karyotyping and arrayCGH as part of the routine diagnostics. The analysis results of these assays as well as additional clinical information were integrated into an interactive web interface using Bokeh, where the main graph is based on Uniform Manifold Approximation and Projection (UMAP) analysis of the gene expression data. At the backend of the clinALL, we built both shallow machine learning models and a deep neural network using Scikit-learn and PyTorch respectively. Findings: By applying clinALL, 78% of undetermined patients under the current diagnostic protocol were stratified, and ambiguous cases were investigated. Translational insights were discovered, including IKZF1plus status dependent subpopulations of BCR::ABL1 positive patients, and a subpopulation within ETV6::RUNX1 positive patients that has a high relapse frequency. Our best machine learning models, LDA and PASNET-like neural network models, achieve F1 scores above 97% in predicting patients’ subgroups. Interpretation: An AI-assisted clinical framework that integrates both genomic and clinical data can take full advantage of the available data, improve point-of-care decision-making and reveal clinically relevant insights promptly. Such a lightweight and easily transferable framework works for both whole transcriptome data as well as the cost-effective targeted RNA-seq, enabling efficient and equitable delivery of personalized medicine in small clinics in developing countries. Funding: German Ministry of Education and Research (BMBF), German Research Foundation (DFG) and Foundation for Polish Science.
CRIS-Team Scopus Importer:2024-06-07
Keywords: Clinical framework; Data integration; Leukaemia; Machine learning

A New Mouse Model of Junctional Epidermolysis Bullosa: The LAMB3 628G > A Knockin Mouse - Hammersen, Johanna; Hou, Jin; Wünsche, Stephanie; Brenner, Sven; Winkler, Thomas; Schneider, Holm (Journal of Investigative Dermatology, 2015)

An isotope dilution-liquid chromatography-tandem mass spectrometry-based candidate reference measurement procedure for the quantification of cortisol in human serum and plasma - Ott, Myriam; Singh, Neeraj; Bauland, Friederike; Köppl, Daniel; Kandler, Kerstin; Gaudl, Alexander; Geistanger, Andrea; Ceglarek, Uta; Rauh, Manfred; Geletneky, Christian; Taibon, Judith (Clinical Chemistry and Laboratory Medicine, 2025)
Accurate measurement of serum cortisol is crucial for the diagnosis and management of adrenal disorders. Thus, we have developed a novel isotope dilution-liquid chromatography-tandem mass spectrometry (ID-LC MS/MS)-based candidate reference measurement procedure (RMP) to quantify cortisol in human serum/plasma, offering higher sensitivity and reliability compared to existing RMPs. Quantitative Nuclear Magnetic Resonance spectroscopic (qNMR) methodology has been utilized to assign the absolute content (g/g) and SI-traceability to the reference materials. A novel two-dimensional heart-cut liquid chromatography (LC) approach was implemented for the LC-MS/MS, combined with a supported liquid extraction (SLE) sample preparation protocol. A multi-day validation experiment assessed precision and accuracy. Reproducibility was assessed by comparing procedure results between two independent laboratories, and measurement uncertainty (MU) was evaluated in compliance with current guidelines. The established RMP exhibited high sensitivity, with a quantification range of 0.800-600 » ng/mL (2.21-1,655 » nmol/L), exceeding the ranges of existing JCTLM-listed RMPs. Intermediate precision was ≤2.6 » %, and repeatability ranged from 0.9 to 1.9 » % across all concentration levels. The relative mean bias ranged from -1.3 to 1.4 » % for all matrices and concentration levels. Measurement uncertainties (MU) for cortisol in single measurements were ≤2.8 » % regardless of the concentration level and sample type. Using the certified International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) reference panel, the equivalence between the candidate RMP and the Joint Committee on Traceability in Laboratory Medicine (JCTLM) listed RMPs (NRMeth 57 and NRMeth 8) was assessed, revealing excellent agreement. This RMP allows for highly sensitive and reproducible determination of cortisol. The performance of the RMP facilitates the standardization of routine assays and ensures traceability in the measurement of individual patient samples.
CRIS-Team Scopus Importer:2025-02-28
Keywords: cortisol; isotope dilution-liquid chromatography-tandem mass spectrometry; qNMR characterization; reference measurement procedure; SI units; traceability

Anorectal malformations - de Blaauw, Ivo; Stenström, Pernilla; Yamataka, Atsuyuki; Miyake, Yuichiro; Reutter, Heiko Martin; Midrio, Paola; Wood, Richard; Grano, Caterina; Pakarinen, Mikko (Nature Reviews Disease Primers, 2024)
Anorectal malformations (ARM) are rare congenital anomalies with an overall prevalence of 3.32 per 10,000 pregnancies. ARM describe a spectrum of anomalies of the anus and rectum ranging from a minimally displaced anal canal to a complete fusion of the anorectum, vagina and urethra with hypoplastic sphincter and pelvic floor muscle. Aberrant septation of the hindgut with anomalous cloacal membrane during weeks 6 to 9 of gestation form the developmental basis for a spectrum of anomalies defined as ARM. Although underlying specific syndromes and occasional familiar occurrence suggest genetic aetiology, most ARM are non-syndromic and their causal genetic mechanisms and non-genetic insults remain unclear. ARM is a clinical diagnosis, generally made early after birth via careful inspection of the perineum. Prenatal detection remains rare, and modern technical developments have added little to prenatal diagnostics. ARM is corrected surgically. Since its introduction in 1982, posterior sagittal anorectoplasty is the most common surgery for ARM reconstruction. Subsequent surgical adaptations focus on minimizing iatrogenic operative injury by limiting surgical invasiveness. They include laparoscopic procedures and shortening of incisions with confined dissection in open surgery. Although outcomes in patients with ARM have evolved throughout the past decades, there is urgent need for further improvements both in functional outcomes and quality of life. The importance of psychosocial experiences of affected patients is increasingly recognized. Continued research is necessary to improve prenatal detection, to elucidate genetic and epigenetic alterations and to refine optimal surgical procedures.
CRIS-Team Scopus Importer:2024-11-29

A novel missense mutation in the gene EDARADD associated with an unusual phenotype of hypohidrotic ectodermal dysplasia - Wohlfart, Sigrun; Söder, Stephan; Smahi, Asma; Schneider, Holm (American Journal of Medical Genetics Part A, 2016)
Hypohidrotic ectodermal dysplasia (HED) is a rare disorder characterized by deficient development of structures derived from the ectoderm including hair, nails, eccrine glands, and teeth. HED forms that are caused by mutations in the genes EDA, EDAR, or EDARADD may show almost identical phenotypes, explained by a common signaling pathway. Proper interaction of the proteins encoded by these three genes is important for the activation of the NF-?B signaling pathway and subsequent transcription of the target genes. Mutations in the gene EDARADD are most rarely implicated in HED. Here we describe a novel missense mutation, c.367G>A (p.Asp123Asn), in this gene which did not appear to influence the interaction between EDAR and EDARADD proteins, but led to an impaired ability to activate NF-?B signaling. Female members of the affected family showed either unilateral or bilateral amazia. In addition, an affected girl developed bilateral ovarian teratomas, possibly associated with her genetic condition.
EVALuna2:6777

A novel mutation of the StAR gene with congenital adrenal hyperplasia and its association with heterochromia iridis: a case report - Splittstösser, Vera; Schreiner, Felix; Gohlke, Bettina; Welzel, Maik; Holterhus, Paul Martin; Wölfle, Joachim (BMC Endocrine Disorders, 2019)
BACKGROUND: We report a novel mutation within the StAR gene, causing congenital adrenal hyperplasia, with the so far unreported association with heterochromia iridis. CASE PRESENTATION: In a now 15-year-old girl (born at 41 + 6 weeks of gestation) adrenal failure was diagnosed in the neonatal period based on the clinical picture with spontaneous hypoglycaemia, hyponatremia and an extremely elevated concentration of ACTH (3381 pmol/l; ref. level 1,1-10,1 pmol/l), elevated renin (836 ng/l; ref. level 5-308 ng/l), and a decreased concentration of aldosterone (410 pmol/l; ref. level 886-3540 pmol/l). In addition to hyperpigmented skin the patient exhibited sectorial heterochromia iridis. Sequence analysis of the steroidogenic acute regulatory protein (StAR) gene showed a novel homozygous mutation (c.652G > A (p.Ala218Thr), which was predicted in-silico to be possibly damaging. Under daily steroid substitution her electrolyte levels are balanced while she became obese. Puberty occurred spontaneously. CONCLUSION: A novel mutation in the StAR gene was identified in a patient with severe adrenal hypoplasia and sectorial heterochromia iridis. We discuss a causal relationship between these two rare phenotypes, i.e. whether very high levels of ACTH and alpha-MSH during early development might have disturbed early differentiation and distribution of uveal melanocytes. If confirmed in additional cases, discolorization of the iris might be considered as an additional phenotypical feature in the differential diagnosis of congenital adrenal insufficiency.
CRIS-Team Scopus Importer:2019-11-12
Keywords: Heterochromia iridis; Lipoid congenital adrenal hyperplasia; StAR

Application of Next-Generation Sequencing to Enterobacter Hormaechei Subspecies Analysis during a Neonatal Intensive Care Unit Outbreak - Morhart, Patrick; Gerlach, Roman; Kunz, Caroline; Held, Jürgen; Valenza, Giuseppe; Wölfle, Joachim; Reutter, Heiko Martin; Hanslik, Gregor J.; Fahlbusch, Fabian B. (Children, 2023)
Introduction: The Enterobacter cloacae complex (ECC) species are potential neonatal pathogens, and ECC strains are among the most commonly encountered Enterobacter spp. associated with nosocomial bloodstream infections. Outbreaks caused by ECC can lead to significant morbidity and mortality in susceptible neonates. At the molecular level, ECC exhibits genomic heterogeneity, with six closely related species and subspecies. Genetic variability poses a challenge in accurately identifying outbreaks by determining the clonality of ECC isolates. This difficulty is further compounded by the limitations of the commonly used molecular typing methods, such as pulsed field gel electrophoresis, which do not provide reliable accuracy in distinguishing between ECC strains and can lead to incorrect conclusions. Next-generation sequencing (NGS) offers superior resolution in determining strain relatedness. Therefore, we investigated the clinical pertinence of incorporating NGS into existing bundle measures to enhance patient management during an outbreak of ECC in a level-3 neonatal intensive care unit (NICU) in Germany. Methods: As the standard of care, all neonates on the NICU received weekly microbiological swabs (nasopharyngeal and rectal) and analysis of endotracheal secretion, where feasible. During the 2.5-month outbreak, colonisation with ECC was detected in n = 10 neonates. The phylogenetic relationship and potential antimicrobial resistance genes as well as mobile genetic elements were identified via bacterial whole-genome sequencing (WGS) using Illumina MiSeq followed by in silico data analysis. Results: Although all ECC isolates exhibited almost identical antimicrobial susceptibility patterns, the WGS data revealed the involvement of four different ECC clones. The isolates could be characterised as Enterobacter hormaechei subspecies steigerwaltii (n = 6, clonal), subsp. hoffmannii (n = 3, two clones) and subsp. oharae (n = 1). Despite the collection of environmental samples, no source of this diffuse outbreak could be identified. A new standardised operating procedure was implemented to enhance the management of neonates colonised with MRGN. This collaborative approach involved both parents and medical professionals and successfully prevented further transmission of ECC. Conclusions: Initially, it was believed that the NICU outbreak was caused by a single ECC clone due to the similarity in antibiotic resistance. However, our findings show that antibiotic susceptibility patterns can be misleading in investigating outbreaks of multi-drug-resistant ECC. In contrast, bacterial WGS accurately identified ECC at the clonal level, which significantly helped to delineate the nature of the observed outbreak.
CRIS-Team Scopus Importer:2023-11-03
Keywords: ECC; Enterobacter; MRGN; NGS; NICU; WGS

A Prevalence Estimation of Exstrophy and Epispadias in Germany From Public Health Insurance Data - Ebert, Anne Karoline; Zwink, Nadine; Reutter, Heiko Martin; Jenetzky, Ekkehart (Frontiers in Pediatrics, 2021)
Introduction: The prevalence of rare diseases is very important for health care research. According to the European Surveillance of Congenital Anomalies (EUROCAT) registers, the live prevalence for exstrophy and/or epispadias (grades 1–3) is reported with 1:23,255 (95% CI: 1:26,316; 1:20,000). A Europe-wide prevalence evaluation based on reports from excellence centers estimates a prevalence for exstrophies of 1:32,200 and for isolated epispadias of 1:96,800 in 2010. However, the frequency of exstrophy [International Statistical Classification of Diseases and Related Health Problems revision 10 (ICD-10): Q64.1] and epispadias (ICD-10: Q64.0) treated in different age groups in Germany remains unclear. Material and Method: Public health insurance data from 71 million people (approximately 87% of the population) were provided by the German Institute for Medical Documentation and Information (DIMDI) in accordance to the German Social Insurance Code for this research purpose. DIMDI analyzed the data source for the ICD diagnoses exstrophy and epispadias between 2009 and 2011. As provided data were robust over the years, averaged data are mentioned. Detailed subgroup analysis of small numbers was forbidden due to privacy protection. Results: Annually, 126 persons of all ages with epispadias and 244 with exstrophy are treated as inpatients. In the observed population, 34 infants (<1 year of age) with epispadias and 19 with exstrophy (58% male) are treated as outpatients each year. This corresponds to an estimated live prevalence of 1:11,000 (95% CI: 1:14,700; 1:8,400) for EEC (exstrophy–epispadias complex), more specifically a prevalence of 1:17,142 for epispadias and of 1:30,675 for exstrophy. The male-to-female ratio for exstrophy is 1.4:1 for infants and 1.6:1 for all minors. In children and adolescents, 349 epispadias and 393 exstrophies (up to the age of 17) are treated annually, whereas adults with exstrophy and even more with epispadias make comparatively less use of medical care. Conclusion: With the help of DIMDI data, the live prevalence of bladder exstrophy and epispadias in Germany could be estimated. The prevalence of epispadias was higher than in previous reports, in which milder epispadias phenotypes (grade 1 or 2) may not have been included. These analyses might enlighten knowledge about nationwide incidence and treatment numbers of rare diseases such as the EEC.
CRIS-Team Scopus Importer:2021-11-19
Keywords: bladder exstrophy; bladder exstrophy epispadias complex (EEC); epispadias; health insurance; prevalence; public health

A role for the alpha-8 integrin chain (itga8) in glomerular homeostasis of the kidney. - Marek, Ines; Hilgers, Karl Friedrich; Rascher, Wolfgang; Wölfle, Joachim; Hartner, Andrea (Molecular and Cellular Pediatrics, 2020)
Glomerulonephritis results in a dysregulation of glomerular cells and may end up in chronic alterations and subsequent loss of renal function. Therefore, understanding mechanisms, which contribute to maintain glomerular integrity, is a pivotal prerequisite for therapeutic interventions. The alpha-8 integrin chain seems to be an important player to maintain glomerular homeostasis by conferring mechanical stability and functional support for the renal capillary tuft.
EVALuna2:383426
Keywords: itga8; Glomerular homeostasis; Mesangial cells; Glomerulonephritis

A single-center observational study on long-term neurodevelopmental outcomes in children with tuberous sclerosis complex - Mammadova, Dilbar; Vecko, Julia; Hofmann, Marlene; Schüssler, Stephanie; Deiters, Ludger; Canda, A.; Wieland, Anna; Gollwitzer, Stephanie; Hamer, Hajo; Trollmann, Regina (Orphanet Journal of Rare Diseases, 2023)
Background: Tuberous sclerosis complex (TSC) is a rare multisystem disorder caused by mutations in the TSC1 or TSC2 gene. More than 90% of patients with TSC develop neurological and/or neuropsychiatric manifestations. The aim of the present study was to determine the developmental and cognitive long-term outcomes of pediatric TSC patients. Methods: This cross-sectional, monocenter study included pediatric TSC patients who received multidisciplinary long-term care with a last visit between 2005 and 2019. Neurological manifestations and cognitive development (BSID, K-ABC) were analyzed in relation to age and type of mutation. Results: Thirty-five patients aged 13.5 ± 7.8 years were included in the study. Diagnosis was confirmed genetically in 65.7% of patients (TSC1, 26.1%; TSC2, 65.2%; NMI, 8.7%). Mean age at diagnosis was 1.3 ± 3.5 years; 74.3% of the patients had been diagnosed within the first year of life due to seizures (62.9%) or/and cardiac rhabdomyomas (28.6%). The most common TSC manifestations included structural brain lesions (cortical tubers, 91.4%; subependymal nodules, 82.9%), epilepsy (85.7%), and cardiac rhabdomyomas (62.9%). Mean age at seizure onset was 1.5 ± 2.3 years, with onset in 80.0% of patients within the first two years of life. Infantile spasms, which were the first seizure type in 23.3% of the patients, developed earlier (0.6 ± 0.4 years) than focal seizures (1.8 ± 2.5 years). Refractory epilepsy was present in 21 (70.0%) patients, mild or severe intellectual impairment in 66.6%, and autism spectrum disorders in 11.4%. Severe cognitive impairment (33.3%) was significantly associated with epilepsy type and age at seizure onset (p < 0.05). Conclusions: The results emphasized the phenotypic variability of pediatric-onset TSC and the high rate of neurological and neuropsychiatric morbidity. Early-onset refractory epilepsy was associated with impaired cognitive development. Children of all ages with TSC require multidisciplinary long-term care and individual early-intervention programs.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Antiseizure medication; Autism; Cognition; Rare disease; Refractory epilepsy; Tuberous sclerosis complex

Assessment of educational and social status of survivors of childhood cancer: Data of a single center late effects clinic - Hahn, B.; Schuster, Sonja; Metzler, Markus; Mackensen, Andreas; Meidenbauer, Norbert (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Assessment of genetic defects, baseline characteristics and adverse events reported in the Increlex (R) registry - Polak, Michel; Bang, Peter; Perrot, Valerie; Sert, Caroline; Storr, Helen L.; Wölfle, Joachim (HORMONE RESEARCH IN PAEDIATRICS, 2021)
CRIS-Team WoS Importer:2021-10-08

Assessment of treatment responses in children and adolescents with Ewing sarcoma with metabolic tumor parameters derived from 18F-FDG-PET/CT and circulating tumor DNA - Schmidkonz, Christian; Krumbholz, Manuela; Atzinger, Armin; Cordes, Michael; Goetz, Theresa Ida; Prante, Olaf; Ritt, Philipp; Schaefer, Christiane; Agaimy, Abbas; Hartmann, Wolfgang; Rössig, Claudia; Fröhlich, Birgit; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2019)
Purpose: The purpose of this study was to perform a prospective integrated analysis of 18F-fluorodeoxyglucose (18F-FDG)-positron emission tomography (PET)/computed tomography (CT) and circulating tumor DNA (ctDNA) to assess responses to multimodal chemotherapy in children and adolescents suffering from Ewing sarcoma (EwS). Methods: A total of 20 patients with histologically confirmed EwS underwent multiple 18F-FDG-PET/CT, performed at the time of each patient’s initial diagnosis and after the second and fifth induction chemotherapy block (EWING2008 treatment protocol, NCT00987636). Additional PET examinations were performed as clinically indicated in some patients, e.g., in patients suspected of having progressive or relapsing disease. All 263 18F-FDG-positive lesions in the field of view suggestive of tumor tissue were assessed quantitatively to calculate PET-derived parameters, including whole-body metabolic tumor volume (wb-MTV) and whole-body total lesion glycolysis (wb-TLG), as well as the following data: standardized uptake value (SUV)max and SUVmean. Tumor-specific ctDNA in patient plasma samples was quantified using digital droplet PCR (ddPCR), and the correlations between ctDNA levels and PET-derived parameters were analyzed. Metabolic responses to multimodal chemotherapy as assessed with PET-parameters were compared to biochemical responses as assessed with changes in ctDNA levels. Results: Twenty patients underwent a total of 87 18F-FDG-PET/CT scans, which detected 263 FDG-positive tumor lesions. Significant correlations between SUVmax, SUVmean, wb-MTV and wb-TLG values, and ctDNA levels were observed (all p < 0.0001). All patients suffering from EwS, with histology serving as gold standard, also presented with a positive corresponding ctDNA sample and a positive 18F-FDG-PET/CT examination before initiation of therapy. There were no false-negative results. Evaluation of treatment response after the fifth block of induction chemotherapy showed that the agreement between the metabolic response and biochemical response was 90%, which was statistically significant (Cohen κ = 0.62; p < 0.05). Non-detectable ctDNA after the second block of induction chemotherapy was associated with complete biochemical and metabolic responses after the fifth block of induction chemotherapy in 16/17 patients (94%). During a median follow-up period of 36 months (range: 8–104 months), four patients had tumor relapses, which, in all cases, were accompanied by an increase in plasma ctDNA levels and a positive 18F-FDG-PET/CT. No false-negative results were observed in the study cohort. Complete biochemical and metabolic responses after the fifth block of induction chemotherapy had a high positive predictive value for disease remission during the follow-up period; specifically, the positive predictive value was 88%. Conclusion: The combination of 18F-FDG-PET/CT and ctDNA quantification is a very promising noninvasive tool for assessing treatment responses and detecting tumor relapses in children and young adolescents suffering from EwS who are undergoing multimodal chemotherapy.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Circulating tumor DNA; Ewing sarcoma; Pediatric oncology; Treatment response

A surrogate cell-based SARS-CoV-2 spike blocking assay - Schuh, Wolfgang; Baus, Lena; Steinmetz, Tobit; Schulz, Sebastian; Weckwerth, Leonie; Roth, Edith; Hauke, Manuela; Krause, Stefan; Morhart, Patrick; Rauh, Manfred; Hoffmann, Markus; Vesper, Niklas; et al. (European Journal of Immunology, 2021)
To monitor infection by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and successful vaccination against coronavirus disease 2019 (COVID-19), the kinetics of neutralizing or blocking anti-SARS-CoV-2 antibody titers need to be assessed. Here, we report the development of a quick and inexpensive surrogate SARS-CoV-2 blocking assay (SUBA) using immobilized recombinant human angiotensin-converting enzyme 2 (hACE2) and human cells expressing the native form of surface SARS-CoV-2 spike protein. Spike protein-expressing cells bound to hACE2 in the absence or presence of blocking antibodies were quantified by measuring the optical density of cell-associated crystal violet in a spectrophotometer. The advantages are that SUBA is a fast and inexpensive assay, which does not require biosafety level 2- or 3-approved laboratories. Most importantly, SUBA detects blocking antibodies against the native trimeric cell-bound SARS-CoV-2 spike protein and can be rapidly adjusted to quickly pre-screen already approved therapeutic antibodies or sera from vaccinated individuals for their ACE2 blocking activities against any emerging SARS-CoV-2 variants.
CRIS-Team Scopus Importer:2021-10-08
Keywords: COVID-19; hACE2; SARS-CoV-2; Spike protein; Surrogate blocking assay

A systematic review of magnetic resonance imaging in patients with an implanted vagus nerve stimulation system - Fetzer, S.; Dibue, M.; Nagel, Armin Michael; Trollmann, Regina (Neuroradiology, 2021)
Purpose Vagus nerve stimulation (VNS) is an effective adjunctive treatment for drug-resistant epilepsy (DRE) and difficult-to-treat depression (DTD). More than 125.000 patients have been implanted with VNS Therapy (R) System (LivaNova PLC) since initial approval. Patients with DRE often require magnetic resonance imaging (MRI) of the brain during the course of their disease. VNS Therapy System devices are labeled to allow MRI under certain conditions; however, there are no published comprehensive articles about the real-world experience using MRI in patients with implanted VNS devices. Methods A systematic review in accordance with PRISMA statement was performed using PubMed database. Full-length articles reporting MRI (1.5 T or 3 T scanner) of patients with implanted VNS for DRE or DTD and published since 2000 were included. The primary endpoint was a positive outcome that was defined as a technically uneventful MRI scan performed in accordance with the VNS Therapy System manufacturer guidelines and completed according to the researchers' planned scanning protocol without harm to the patient. Results Twenty-six articles were eligible with 25 articles referring to the VNS Therapy System, and 216 patients were included in the analysis. No serious adverse events or serious device-related adverse events were reported. MRI scan was prematurely terminated in one patient due to a panic attack. Conclusion This systematic review indicates that cranial MRI of patients with an implanted VNS Therapy System can be completed satisfactorily and is tolerable and safe using 1.5 T and 3 T MRI scanners when performed in adherence to the VNS manufacturer's guidelines.
CRIS-Team WoS Importer:2021-05-07

Ätiologische Konzepte von gastrointestinalen Fehlbildungen/Atresien - Reutter, Heiko Martin (Monatsschrift Kinderheilkunde, 2023)
The causes of gastrointestinal malformations or atresias are heterogeneous. Most atresias occur sporadically. To date, no environmental factor or genetic defect has been identified that alone could causally explain a large proportion of the various malformations. Due to the capabilities of modern array and exome analyses, numerous new disease genes have been identified in the past 10 years. It is known that a small overlap of individual causative genetic risk factors underlies the co-occurrence of malformations of the esophagus and anorectum, and that a large proportion of duodenal atresias occur in the context of an underlying Down syndrome; however, for the vast majority of intestinal atresias the genetic causes remain unclear. The human genetic counselling should consider epidemiological aspects of the observed recurrence risk for the different atresias and the appearance of each atresia (syndromic or non-syndromic, isolated).
CRIS-Team Scopus Importer:2023-05-19
Keywords: Chromosome disorders; DNA copy number variations; Epidemiology; Pathogenesis; Recurrence risk

Attenuation of Mammary Gland Dysplasia and Feeding Difficulties in Tabby Mice by Fetal Therapy - Wahlbuhl, Mandy; Schuepbach-Mallepell, Sonia; Kowalczyk-Quintas, Christine; Dick, Angela; Fahlbusch, Fabian B.; Schneider, Pascal; Schneider, Holm (Journal of Mammary Gland Biology and Neoplasia, 2018)
Hypohidrotic ectodermal dysplasias (HED) are hereditary differentiation disorders of multiple ectodermal structures including the mammary gland. The X-linked form of HED (XLHED) is caused by a lack of the secreted signaling molecule ectodysplasin A1 (EDA1) which is encoded by the gene EDA and belongs to the tumor necrosis factor (TNF) superfamily. Although male patients (hemizygous) are usually more severely affected by XLHED, heterozygous female carriers of an EDA mutation may also suffer from a variety of symptoms, in particular from abnormal development of their breasts. In Tabby mice, a well-studied animal model of XLHED, EDA1 is absent. We investigated the effects of prenatal administration of Fc-EDA, a recombinant EDA1 replacement protein, on mammary gland development in female Tabby mice. Intra-amniotic delivery of Fc-EDA to fetal animals resulted later in improved breastfeeding and thus promoted the growth of their offspring. In detail, such treatment led to a normalization of the nipple shape (protrusion, tapering) that facilitated sucking. Mammary glands of treated female Tabby mice also showed internal changes, including enhanced branching morphogenesis and ductal elongation. Our findings indicate that EDA receptor stimulation during development has a stable impact on later stages of mammary gland differentiation, including lactation, but also show that intra-amniotic administration of an EDA1 replacement protein to fetal Tabby mice partially corrects the mammary gland phenotype in female adult animals.
EVALuna2:35485

Attenuation of Severe Generalized Junctional Epidermolysis Bullosa by Systemic Treatment with Gentamicin - Hammersen, Johanna; Neuner, Andrea; Wild, Florian; Schneider, Holm (Dermatology, 2019)
Severe generalized junctional epidermolysis bullosa (JEB), a lethal genodermatosis, is mainly caused by premature termination codons (PTCs) in one of the three genes encoding the anchoring protein laminin-332. Only symptomatic treatment has been established; overcoming PTCs by aminoglycosides may represent an interesting alternative. This retrospective study aimed at assessing for the first time the clinical effects of systemic gentamicin application in infants with severe generalized JEB. Five patients, homozygous or compound-heterozygous for PTCs in the gene LAMB3, were treated with gentamicin which was administered intravenously or by intramuscular injection at doses of 7.5 mg/kg/d for three weeks. Skin biopsies were investigated by immunofluorescence analyses. Clinical effects of the medication were recorded with a parent questionnaire and by assessing weight-for-age charts. Gentamicin application was well tolerated, long hospitalization was not required. Low levels of laminin-332 could be detected in a skin sample obtained after treatment. Gentamicin had a positive impact on skin fragility and daily life in four patients but did not influence weight gain and failed to reverse the lethal course of the disease. Gentamicin injections should be considered regularly in cases of severe generalized JEB caused by PTCs as they may attenuate JEB symptoms without impeding quality of life.
CRIS-Team Scopus Importer:2019-06-18

Autoimmune Psychosis as a Differential Diagnosis of Primary Schizophreniform Psychosis in Children and Adolescents - Briegel, Wolfgang; Wößner, Rupert; Trollmann, Regina (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2024)
Objective: Autoimmune psychosis (AP), defined as an isolated schizophreniform psychosis with no or only minimal neurological abnormalities stemming from autoantibody-associated cerebral processes, is a very rare and potentially underdiagnosed disorder in children and adolescents. Methods: This article reports the case of a 13-year-old boy who became acutely ill with a psychotic disorder following a respiratory infection. We describe the diagnosis and course of treatment in detail. Results: Following an extensive interdisciplinary workup, a probable glutamic acid decarboxylase (GAD)-associated AP was diagnosed that ultimately remitted completely with treatment. Conclusions: Autoimmune psychoses remain a relatively uncharted territory for the specialty of child and adolescent psychiatry. Good interdisciplinary cooperation is essential for patients with somewhat atypical psychotic symptoms, both in terms of diagnosis and treatment.
CRIS-Team Scopus Importer:2025-02-04

AUTOMATED PUPILLOMETRY FOR PREDICTION OF SPACE-OCCUPYING HEMISPHERIC INFARCTION AFTER ENDOVASCULAR TREATMENT - Köhn, Julia; Kobus, Franca; Kossel, Clara-Sophie; Borutta, Matthias; Kuramatsu, Joji; Schwab, Stefan (JOURNAL OF NEUROTRAUMA, 2022)
CRIS-Team WoS Importer:2022-09-02

Automatic Classification of Neuromuscular Diseases in Children Using Photoacoustic Imaging - Schlereth, Maja; Stromer, Daniel; Breininger, Katharina; Wagner, Alexandra; Tan, Lina; Maier, Andreas; Knieling, Ferdinand (Informatik aktuell, 2022)
Neuromuscular diseases (NMDs) cause a significant burden for both healthcare systems and society. They can lead to severe progressive muscle weakness, muscle degeneration, contracture, deformity and progressive disability. The NMDs evaluated in this study often manifest in early childhood. As subtypes of disease, e.g. Duchenne muscular dystropy (DMD) and spinal muscular atrophy (SMA), are difficult to differentiate at the beginning and worsen quickly, fast and reliable differential diagnosis is crucial. Photoacoustic and ultrasound imaging has shown great potential to visualize and quantify the extent of different diseases. The addition of automatic classification of such image data could further improve standard diagnostic procedures.We compare deep learning-based 2-class and 3-class classifiers based on VGG16 for differentiating healthy from diseased muscular tissue. This work shows promising results with high accuracies above 0.86 for the 3-class problem and can be used as a proof of concept for future approaches for earlier diagnosis and therapeutic monitoring of NMDs.<br
CRIS-Team Scopus Importer:2022-05-06

Automatic recognition of the XLHED phenotype from facial images - Hadj-Rabia, Smail; Schneider, Holm; Navarro, Elena; Klein, Ophir; Kirby, Neil; Huttner, Kenneth; Wolf, Lior; Orin, Melanie; Wohlfart, Sigrun; Bodemer, Christine; Grange, Dorothy K. (American Journal of Medical Genetics Part A, 2017)
X-linked hypohidrotic ectodermal dysplasia (XLHED) is a genetic disorder that affects ectodermal structures and presents with a characteristic facial appearance. The ability of automated facial recognition technology to detect the phenotype from images was assessed . In Phase 1 of this study we examined if the age of male patients affected the technology's recognition. In Phase 2 we investigated how well the technology discriminated affected males cases from female carriers and from individuals with other ectodermal dysplasia syndromes. The system detected XLHED to be the most likely diagnosis in all genetically confirmed affected male patients of all ages, and in 55% of heterozygous females. Interestingly, patients with other ED syndromes were also detected by the XLHED-targeted analysis, consistent with shared developmental features. Thus the automated facial recognition system represents a promising non-invasive technology to screen patients at all ages for a possible diagnosis of ectodermal dysplasia, with greatest sensitivity and specificity for males affected with XLHED.
EVALuna2:34218

BAFF 60-mer, and Differential BAFF 60-mer Dissociating Activities in Human Serum, Cord Blood and Cerebrospinal Fluid - Eslami, Mahya; Meinl, Edgar; Eibel, Hermann; Willen, Laure; Donzé, Olivier; Distl, Ottmar; Schneider, Holm; Speiser, Daniel E.; Tsiantoulas, Dimitrios; Yalkinoglu, Ozkan; Samy, Eileen; Schneider, Pascal (Frontiers in Cell and Developmental Biology, 2020)
B cell activation factor of the TNF family (BAFF/BLyS), an essential B cell survival factor of which circulating levels are elevated in several autoimmune disorders, is targeted in the clinic for the treatment of systemic lupus erythematosus (SLE). The soluble form of BAFF can exist as 3-mer, or as 60-mer that results from the ordered assembly of twenty 3-mers and that can be obtained from naturally cleaved membrane-bound BAFF or made as a recombinant protein. However, which forms of soluble BAFF exist and act in humans is unclear. In this study, BAFF 3-mer and 60-mer in biological fluids were characterized for size, activity and response to specific stimulators or inhibitors of BAFF. Human cerebrospinal fluids (CSF) from patients with multiple sclerosis and adult human sera contained exclusively BAFF 3-mer in these assays, also when BAFF concentrations were moderately SLE or highly (BAFFR-deficient individual) increased. Human sera, but not CSF, contained a high molecular weight, saturable activity that dissociated preformed recombinant BAFF 60-mer into 3-mer. This activity was lower in cord blood. Cord blood displayed BAFF levels 10-fold higher than in adults and consistently contained a fair proportion of active high molecular weight BAFF able to dissociate into 3-mer but not endowed with all properties of recombinant BAFF 60-mer. If BAFF 60-mer is produced in humans, it is dissociated, or at least attenuated in the circulation.
CRIS-Team Scopus Importer:2020-11-27
Keywords: 60-mer; atacicept; B-cell activating factor; belimumab; cerebrospinal fluid; cord blood; serum

BCL10 Deficiency Presenting as Severe Combined Immunodeficiency Escaping Newborn Screening - Salou, Sarah; Völkl, Simon; Keller, Baerbel; Ehl, Stephan; Naumann-Bartsch, Nora (Journal of clinical immunology, 2024)
CRIS-Team Scopus Importer:2024-01-12

BDV Syndrome: An Emerging Syndrome with Profound Obesity and Neurodevelopmental Delay Resembling Prader-Willi Syndrome - Bosch, Elisabeth; Hebebrand, Moritz; Popp, Bernt; Penger, Theresa; Behring, Bettina; Cox, Helen; Towner, Shelley; Kraus, Cornelia; Wilson, William G.; Khan, Shagufta; Krumbiegel, Mandy; Ekici, Arif Bülent; et al. (Journal of Clinical Endocrinology and Metabolism, 2021)
Context: CPE encodes carboxypeptidase E, an enzyme that converts proneuropeptides and propeptide hormones to bioactive forms. It is widely expressed in the endocrine and central nervous system. To date, 4 individuals from 2 families with core clinical features including morbid obesity, neurodevelopmental delay, and hypogonadotropic hypogonadism, harboring biallelic loss-of-function (LoF) CPE variants, have been reported. Objective: We describe 4 affected individuals from 3 unrelated consanguineous families, 2 siblings of Syrian, 1 of Egyptian, and 1 of Pakistani descent, all harboring novel homozygous CPE LoF variants. Methods: After excluding Prader-Willi syndrome (PWS), exome sequencing was performed in both Syrian siblings. The variants identified in the other 2 individuals were reported as research variants in a large-scale exome study and in the ClinVar database. Computational modeling of all possible missense alterations allowed assessing CPE tolerance to missense variants. Results: All affected individuals were severely obese with neurodevelopmental delay and other endocrine anomalies. Three individuals from 2 families shared the same CPE homozygous truncating variant c.361Câ€ >â€ T, p.(Arg121∗), while the fourth carried the c.994del, p.(Ser333Alafs∗22) variant. Comparison of clinical features with previously described cases and standardization according to the Human Phenotype Ontology terms indicated a recognizable clinical phenotype, which we termed Blakemore-Durmaz-Vasileiou (BDV) syndrome. Computational analysis indicated high conservation of CPE domains and intolerance to missense changes. Conclusion: Biallelic truncating CPE variants are associated with BDV syndrome, a clinically recognizable monogenic recessive syndrome with childhood-onset obesity, neurodevelopmental delay, hypogonadotropic hypogonadism, and hypothyroidism. BDV syndrome resembles PWS. Our findings suggest missense variants may also be clinically relevant.
CRIS-Team Scopus Importer:2021-12-24
Keywords: BDV syndrome; carboxypeptidase E; CPE; hypogonadotropic hypogonadism; neurodevelopmental disorder; obesity

Beratung nach pränatalen Diagnosen: Sorgen wir für Informationen aus erster Hand! - Schneider, Holm (Zeitschrift für Geburtshilfe und Neonatologie, 2024)

Betreuung von Kindern und Jugendlichen mit M. Basedow in einem endokrinologischen Zentrum - Penger, Theresa; Albrecht, Andrea; Marx, Martin; Jüngert, Jörg M.; Kuwert, Torsten; Dörr, Helmuth-Günther (Monatsschrift Kinderheilkunde, 2019)
Background: Graves’ disease is rare in childhood and adolescence. While the criteria for diagnosis are clearly defined, there are controversial discussions in the literature regarding the optimal treatment modality. Objective: The aim of the study was to retrospectively analyze the treatment and long-term course of patients with Graves’ disease who were under the care of this outpatient department of pediatric endocrinology between 2000 and 2015. Material and methods: The data of 50 children and adolescents (40 female, 10 male) aged between 4.5 and 17.6 years (median 12.4 years) were evaluated. The patient history, height, weight and laboratory values were documented at the initial presentation and at every outpatient visit. The duration to achievement of euthyroidism (remission), the time until attempted withdrawal, the duration of remission, the time of recurrence and the time and type of a final treatment were also documented. To calculate thyroid volume (SDS) values, the data of Kromeyer-Hauschild et al. were used as references for height and BMI and for the sonographically measured thyroid volume the data of the German National Health Examination Survey for Children and Adolescents (KiGGS) were used. Results (median values): The diagnosis was made 6 months after the onset of symptoms at the age of 12.4 years. Serum thyroid-stimulating hormone (TSH) levels were suppressed, free tri-iodothyronine (fT3, 21.6 pmol/l; normal range 3.5–8.1), free thyroxine (fT4, 48.3 pmol/l; 7.6–17.7), and TSH-receptor antibody (TRAB, 9.4 U/l; <1.5) were elevated. At diagnosis 28 children had goiter (+5.9 SDS) and 15 patients developed a goiter during the further course. All patients primarily received thiamazole (n = 34) or carbimazole (n = 16) and 18 patients a beta blocker. During the course 96% received dual therapy (antithyroid drug plus L‑T4) and 9 patients are still receiving primary treatment. Thus, 41 patients could be assessed with respect to the long-term course. The treatment did not affect the size of the thyroid gland. A withdrawal trial was performed in 33 patients at 32 months, including 6 patients receiving treatment for <24 months and 11 patients receiving treatment for more than 36 months. Thyroidectomy was performed in 8 patients on drug treatment without a withdrawal trial due to the increasing goiter. After the end of the thyrostatic therapy, 17 patients achieved full remission (no recurrence of hyperthyroidism after completion of drug treatment) and 8 patients currently have a remission duration ≥12 months. Recurrence treatment was initiated in 7 patients after the first remission and 9 patients underwent thyroidectomy. Conclusion: The high remission rate was positively correlated with the treatment duration. The dual therapy regimen might also affect the outcome. The size of the thyroid gland was unchanged during treatment. The extent of TRAB levels at the time of the withdrawal trial did not affect the long-term outcome. In all cases with a rapid goiter progression, an early thyroidectomy should be performed.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Hyperthyroidism; Long-term outcome; Single center; Therapeutic options

Biallelic KRT5 mutations in autosomal recessive epidermolysis bullosa simplex, including a complete human keratin 5 “knock-out” - Vahidnezhad, Hassan; Youssefian, Leila; Daneshpazhooh, Maryam; Mahmoudi, Hamidreza; Kariminejad, Ariana; Fischer, Judith; Christiansen, Julie; Schneider, Holm; Guy, Alyson; Liu, Lu; McGrath, John A.; Has, Cristina; et al. (Matrix Biology, 2019)
Epidermolysis bullosa simplex (EBS) is usually inherited as an autosomal dominant disease due to monoallelic gain-of-function mutations in KRT5 or KRT14. Although autosomal recessive forms of EBS have been associated with mutations in at least 10 genes, recessive EBS due to homozygous biallelic KRT5 mutations has not been reported previously; it has been hypothesized that it would result in prenatal lethality. We sought the genetic causes of EB in a cohort of 512 distinct EB families by performing whole exome sequencing (WES) and using an EB-targeting next-generation sequencing (NGS) panel of 21 genes. The pathogenicity and consequences of the mutations were determined by expression profiling and at tissue and ultrastructural levels. Two pathogenic, homozygous missense variants of KRT5 in two patients with generalized EBS and a homozygous null mutation in a patient who died as a neonate from complications of EB were found. The two missense mutations disrupted keratin 5 expression on immunofluorescence microscopy, and the human “knock-out” of KRT5 showed no RNA and protein expression. Collectively, these findings identify biallelic KRT5 mutations with a phenotypic spectrum varying from mild, localized and generalized to perinatal lethal, expanding the genotypic profile of autosomal recessive EBS.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Epidermolysis bullosa simplex; KRT5 homozygosity; Next generation sequencing; Phenotype-genotype correlations

Bilateral posterior persistent hyperplastic primary vitreous - Hohberger, B.; Knorr, H. L.J.; Mardin, Christian Y.; Trollmann, Regina; von Marchtaler, Philipp; Gusek-Schneider, G. ‑C (Ophthalmologe, 2017)
Bilateral persistent hyperplastic primary vitreous (PHPV) represents a rare entity of a congential malformation. This casuistic presents for the first time in the German literature the case of a 4-month-old child with bilateral posterior PHPV.
EVALuna2:21353

Birth Size in Neonates with Congenital Adrenal Hyperplasia due to 21-hydroxylase Deficiency - Dörr, Helmuth-Günther; Penger, Theresa; Albrecht, Andrea; Marx, Martin; Völkl, Thomas (JCRPE Journal of Clinical Research in Pediatric Endocrinology, 2019)
Objective: Classic congenital adrenal hyperplasia (CAH) secondary to 21-hydroxylase deficiency is characterized by increased prenatal adrenal androgen secretion. There are a small number of reports in the literature showing higher birth weight and length in CAH newborns.
CRIS-Team WoS Importer:2019-03-06

Birthweight Differences in Adolescent Monozygotic Twins Influence Androgens, Psychological Morbidity, and Health-Related Quality of Life - Schmitz, Lioba; Schulte, Sandra; Stoffel-Wagner, Birgit; Bartmann, Peter; Plamper, Michaela; Schreiner, Felix; Wölfle, Joachim; Gohlke, Bettina (Hormone Research in Paediatrics, 2021)
Background: Adverse prenatal conditions can exert a long-lasting impact in later life. Patients and Methods: Thirty-eight post-pubertal monozygotic twin pairs (16 female pairs) with divergent birthweight (bw) due to twin-to-twin transfusion syndrome were examined at a median of 15.1 years. Auxological and endocrine parameters were measured. To evaluate effects of intra-twin bw and hormone differences on mental health, adolescents and their parents completed the Strengths and Difficulties Questionnaire (SDQ), identifying psychological problems. Twins answered the questionnaire on health-related quality of life (HrQoL, KIDSCREEN-52). Results: Parents attributed a higher number of psychological challenges to the formerly smaller twins, for example, total difficulties (8.8 vs. 6.5, p = 0.009). Differences in bw were associated with differences in parental evaluation of problems, for example, peer relationship problems (r = -0.57 and p = 0.0001). In contrast, bw differences did not affect subjects' self-assessment of psychological factors but on physical well-being (r = 0.42, p = 0.017). The formerly smaller discordant twins showed significantly lower HrQoL regarding psychological well-being (24.9 vs. 26.6, T1,15 = -2.2, and p = 0.043) and moods and emotions (29.8 vs. 32.0, T1,15 = -2.3, p = 0.039). Higher concentrations of androstenedione were linked to greater psychological well-being (r = 0.39 and p = 0.036) in all twin pairs. Conclusion: Our results show that the prenatal environment leading to bw differences exerts a long-lasting impact on diverging parental evaluation of mental health. Formerly smaller discordant twins showed significantly lower HrQoL regarding psychological well-being and moods and emotions. Higher androstenedione concentrations were linked to greater psychological well-being.
CRIS-Team Scopus Importer:2021-02-26

Blocking counter regulation of unfolded protein response by targeted protein synthesis inhibition produces highly synergistic cell death in several cancer entities - Müller, Fabian; Gsottberger, Franziska; Meier, Clara; Petkovic, S.; Krumbholz, Manuela; Metzler, Markus; Mackensen, Andreas (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Block of Counter-Regulation By Inhibition of Protein Synthesis Sensitizes Cancer Cells to IRE1a-Mediated Apoptosis Following Unfolded Protein Response - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Parker, Scott; Wendland, Kerstin; George, Rebekka; Petkovic, Srdjan; Mellenthin, Lisa; Emmerich, Charlotte; Lutzny-Geier, Gloria; Metzler, Markus; Mackensen, Andreas; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-10

Blood circuit reconstruction in an abdominal mouse heart transplantation model - Yin, Decheng; Fu, Jian; Allabauer, Ida; Witzke, Oliver; Rong, Song; Hörning, André (Journal of Visualized Experiments, 2021)
The surgical technique of heterotopic abdominal heart transplantation in mice is a standard model for research in transplantation immunology. Here, the established technique for a modified blood circuit reconstruction in a heterotopic abdominal heart transplantation model is presented. This method uses the intrathoracic inferior vena cava (IIVC) instead of the pulmonary artery of the donor heart for the anastomosis to the inferior vena cava of the recipient. It is facilitating and improving success rates for abdominal heart transplantation in mice.
CRIS-Team Scopus Importer:2021-07-02

Blood counts in adult and elderly individuals: defining the norms over eight decades of life - Zierk, Jakob; Krebs, Alexander; Rauh, Manfred; Metzler, Markus; Löscher, Astrid; Strasser, Erwin; Krause, Stefan (British Journal of Haematology, 2020)
The blood count is one of the most common tests used for health assessment. In elderly individuals, selection of a ‘healthy’ reference population for laboratory assessment is difficult due to the high prevalence of chronic morbidities, leading to uncertainty regarding appropriate reference intervals. In particular, age-specific lower haemoglobin reference limits to define anaemia are controversial. Here, we applied a data mining approach to a large dataset of 3 029 904 clinical routine samples to establish blood count reference intervals. We excluded samples from units/specialists with a high proportion of abnormal blood counts, samples from patients with an unknown or decreased estimated glomerular filtration rate, and samples with abnormal test results in selected other analytes. After sample exclusion, 566 775–572 060 samples from different individuals aged 20–100 years were available for analysis. We then used an established statistical algorithm to determine the distribution of physiological test results and calculated age- and sex-specific reference intervals. Our results show substantial trends with age in haematology analytes' reference intervals. Most notably, haemoglobin and red cell counts decline in men with advanced age, accompanied by increases in red cell volume in both sexes. These findings were confirmed in an independent dataset, and suggest an at least partly physiologic cause.
CRIS-Team Scopus Importer:2020-02-14
Keywords: anaemia; haematology; laboratory haematology

Blood counts in adults and elderly individuals - Zierk, Jakob; Krebs, A.; Rauh, Manfred; Metzler, Markus; Parsch, H.; Strasser, Erwin; Krause, Stefan (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Blood pressure and kidney function in neonates and young infants with intrauterine growth restriction - Heuchel, Katharina Monika; Ebach, Fabian; Alsat, Ebru Aileen; Reutter, Heiko Martin; Mueller, Andreas; Hilger, Alina Christine (Pediatric Nephrology, 2022)
Background: Intrauterine growth restriction (IUGR) has been associated with changes in kidney anatomy, nephrogenesis and the vascular system, resulting in secondary arterial hypertension and kidney damage in adulthood. Here, we compare routine clinical and metabolic parameters between IUGR and non-IUGR study participants in the neonatal and early infant period. Methods: A total of 39 IUGR and 60 non-IUGR neonates were included during an 18-month study period. We compared blood pressure, serum creatinine (SCr), urea nitrogen (BUN), urinary albumin, α-1-microglobulin, transferrin, immunoglobulin G and total protein excretion in spontaneous urine normalized by urine creatinine level during the hospital stay. Results: There were no significant differences in mean values of blood pressure and urinary protein excretion between cases and controls. SCr and BUN levels were lower in the IUGR group compared to the non-IUGR group. Conclusions: The lower levels of SCr and BUN may be attributed to lower liver and muscle mass in IUGR neonates and young infants. Biomarkers currently used in routine clinical care do not allow early postnatal prediction of higher blood pressure or worse kidney function due to IUGR, so further studies are needed. Graphical abstract: A higher resolution version of the Graphical abstract is available as Supplementary information. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-09-16
Keywords: Blood pressure; Intrauterine growth restriction; Kidney function; Neonates; Proteinuria

Blood Pressure in a Large Cohort of Children and Adolescents With Classic Adrenal Hyperplasia (CAH) Due to 21-Hydroxylase Deficiency - Bonfig, Walter; Roehl, Friedrich-Wilhelm; Riedl, Stefan; Dörr, Helmuth-Günther; Bettendorf, Markus; Braemswig, Juergen; Schoenau, Eckhard; Riepe, Felix; Hauffa, Berthold; Holl, Reinhard W.; Mohnike, Klaus (American Journal of Hypertension, 2016)
BACKGROUND: Data on blood pressure (BP) in children and adolescents with classic congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency are conflicting in the literature. PATIENTS AND METHODS: BP data of n = 716 children and adolescents (aged 3-18 years) from a national CAH database were analyzed. BP data were adjusted for height and compared to contemporary national reference data. A systolic and diastolic BP above the 95th centile was defined as hypertensive. RESULTS: Overall prevalence of hypertension was 12.5%. Prevalence of hypertension was higher in younger children than in adolescents (18.5% vs. 4.9%). Until 8 years of age, fludrocortisone dose/m(2)/day correlated significantly with BP in regression analysis (P < 0.0001). BP correlated significantly with body mass index standard deviation score (BMI-SDS) (P < 0.0001), but not with hydrocortisone dose. In patients with salt-wasting CAH, BMI-SDS and BP were significantly higher compared to patients with simple virilising CAH, P < 0.01. CONCLUSION: Especially young CAH children seem to be at risk for-most likely transient-hypertension, since the prevalence of hypertension decreases with age. In children up to 8 years of age, the used fludrocortisone dose is a significant risk factor for hypertension. Therefore we recommend accurate measurement of BP and careful fludrocortisone dosing in children with CAH.
EVALuna2:34016

Bone Fractures in Children and Young Adults With Type 1 Diabetes: Age Distribution, Fracture Location, and the Role of Glycemic Control - Eckert, Alexander J.; Semler, Oliver; Schnabel, Dirk; Köstner, Katharina; Wurm, Donald; Bechtold-Dalla Pozza, Susanne; Schaaf, Katja; Hörtenhuber, Thomas; Hammersen, Johanna; Holl, Reinhard W. (Journal of Bone and Mineral Research, 2021)
Type 1 diabetes (T1D) is a known risk factor for fractures, but the underlying pathophysiology is still not fully understood. This study aims to define age peaks and frequent fracture sites of children and young adults with T1D. Additionally, associations of fractures with metabolic and lifestyle factors as well as with additional complications in individuals with T1D were analyzed. A total of 750 individuals with T1D aged ≤25 years with fractures were matched to 3750 patients with T1D without fractures by demographics and insulin regimen. Hemoglobin A1c (HbA1c) values were compared using linear regression, and logistic regression was used to calculate odds ratios (OR) for fractures in individuals with acute complications and diseases. Median (Q1–Q3) age was 12.7 (9.9 to 14.9) years in individuals with fractures and 16.3 (12.6 to 17.8) years in the entire control group with 65% versus 53% males. Peak age for fractures was 7 to <15 years in males and 9 to <11 years in females, which is earlier than reported for the general population. HbA1c (%) was significantly higher in individuals with fractures than in controls (difference of estimated means: 0.26%; 95% confidence interval [CI] 0.07–0.46), especially in postpubertal females (0.68; 0.10–1.26). Significantly higher odds for fractures were observed in individuals with severe hypoglycemia (OR = 1.90; 95% CI 1.47–2.47), especially in prepubertal females (OR = 2.81; 1.21–6.52]) and postpubertal males (2.44; 1.11–5.38), celiac disease (2.02; 1.67–2.45), and with a history of smoking (1.38; 1.02–1.88). The age peak of fractures seems to be earlier in T1D than in the general population. Poor glycemic control is related to fractures, even before puberty. Associations of HbA1c and severe hypoglycemia with fractures highly depend on age and sex. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).
CRIS-Team Scopus Importer:2021-10-29
Keywords: CELIAC DISEASE; DISEASES AND DISORDERS OF/RELATED TO BONE; FRACTURE RISK ASSESSMENT; HEALTH SERVICES RESEARCH; HEMOGLOBIN A1c; HYPOGLYCEMIA

Bone marrow niche-derived extracellular matrix-degrading enzymes influence the progression of B-cell acute lymphoblastic leukemia - Verma, Divij; Zanetti, Costanza; Godavarthy, Parimala Sonika; Kumar, Rahul; Minciacchi, Valentina R.; Pfeiffer, Jakob; Metzler, Markus; Lefort, Sylvain; Maguer-Satta, Véronique; Nicolini, Franck E.; Burroni, Barbara; Fontenay, Michaela; et al. (Leukemia, 2020)
Specific and reciprocal interactions with the bone marrow microenvironment (BMM) govern the course of hematological malignancies. Matrix metalloproteinase-9 (MMP-9), secreted by leukemia cells, facilitates tumor progression via remodeling of the extracellular matrix (ECM) of the BMM. Hypothesizing that leukemias may instruct the BMM to degrade the ECM, we show, that MMP-9-deficiency in the BMM prolongs survival of mice with BCR-ABL1-induced B-cell acute lymphoblastic leukemia (B-ALL) compared with controls and reduces leukemia-initiating cells. MMP-9-deficiency in the BMM leads to reduced degradation of proteins of the ECM and reduced invasion of B-ALL. Using various in vivo and in vitro assays, as well as recipient mice deficient for the receptor for tumor necrosis factor (TNF) α (TNFR1) we demonstrate that B-ALL cells induce MMP-9-expression in mesenchymal stem cells (MSC) and possibly other cells of the BMM via a release of TNFα. MMP-9-expression in MSC is mediated by activation of nuclear factor kappa B (NF-κB) downstream of TNFR1. Consistently, knockdown of TNF-α in B-ALL-initiating cells or pharmacological inhibition of MMP-9 led to significant prolongation of survival in mice with B-ALL. In summary, leukemia cell-derived Tnfα induced MMP-9-expression by the BMM promoting B-ALL progression. Inhibition of MMP-9 may act as an adjunct to existing therapies.
CRIS-Team Scopus Importer:2020-01-21

Bosutinib in Resistant and Intolerant Pediatric Patients With Chronic Phase Chronic Myeloid Leukemia: Results From the Phase I Part of Study ITCC054/COG AAML1921. - Brivio, Erica; Pennesi, Edoardo; Willemse, Marieke E.; Huitema, Alwin D.R.; Jiang, Yilin; Van Tinteren, Harm D.R.; Van Der Velden, Vincent H.J.; Beverloo, Berna H.; Den Boer, Monique L.; Rammeloo, Lukas A.J.; Hudson, Chad; Heerema, Nyla; et al. (Journal of Clinical Oncology, 2024)
PURPOSE: Bosutinib is approved for adults with chronic myeloid leukemia (CML): 400 mg once daily in newly diagnosed (ND); 500 mg once daily in resistant/intolerant (R/I) patients. Bosutinib has a different tolerability profile than other tyrosine kinase inhibitors (TKIs) and potentially less impact on growth (preclinical data). The primary objective of this first-in-child trial was to determine the recommended phase II dose (RP2D) for pediatric R/I and ND patients. PATIENTS AND METHODS: In the phase I part of this international, open-label trial (ClinicalTrials.gov identifier: NCT04258943), children age 1-18 years with R/I (per European LeukemiaNet 2013) Ph+ CML were enrolled using a 6 + 4 design, testing 300, 350, and 400 mg/m2 once daily with food. The RP2D was the dose resulting in 0/6 or 1/10 dose-limiting toxicities (DLTs) during the first cycle and achieving adult target AUC levels for the respective indication. As ND participants were only enrolled in phase II, the ND RP2D was selected based on data from R/I patients. RESULTS: Thirty patients were enrolled; 27 were evaluable for DLT: six at 300 mg/m2, 11 at 350 mg/m2 (one DLT), and 10 at 400 mg/m2 (one DLT). The mean AUCs at 300 mg/m2, 350 mg/m2, and 400 mg/m2 were 2.20 μg h/mL, 2.52 μg h/mL, and 2.66 μg h/mL, respectively. The most common adverse event was diarrhea (93%; ≥grade 3: 11%). Seven patients stopped because of intolerance and eight because of insufficient response. Complete cytogenetic and major molecular response to bosutinib appeared comparable with other published phase I/II trials with second-generation TKIs in children. CONCLUSION: Bosutinib was safe and effective. The pediatric RP2D was 400 mg/m2 once daily (max 600 mg/d) with food in R/I patients and 300 mg/m2 once daily (max 500 mg/d) with food in ND patients, which achieved targeted exposures as per adult experience.
EVALuna2:550441

Brain Abnormalities in Patients with Germline Variants in H3F3: Novel Imaging Findings and Neurologic Symptoms Beyond Somatic Variants and Brain Tumors - Alves, C. A.P.F.; Sherbini, O.; D’Arco, F.; Steel, D.; Kurian, M. A.; Radio, F. C.; Ferrero, G. B.; Carli, D.; Tartaglia, M.; Balci, T. B.; Powell-Hamilton, N. N.; Schrier Vergano, S. A.; et al. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Pathogenic somatic variants affecting the genes Histone 3 Family 3A and 3B (H3F3) are extensively linked to the process of oncogenesis, in particular related to central nervous system tumors in children. Recently, H3F3 germline missense variants were described as the cause of a novel pediatric neurodevelopmental disorder. We aimed to investigate patterns of brain MR imaging of individuals carrying H3F3 germline variants. MATERIALS AND METHODS: In this retrospective study, we included individuals with proved H3F3 causative genetic variants and available brain MR imaging scans. Clinical and demographic data were retrieved from available medical records. Molecular genetic testing results were classified using the American College of Medical Genetics criteria for variant curation. Brain MR imaging abnormalities were analyzed according to their location, signal intensity, and associated clinical symptoms. Numeric variables were described according to their distribution, with median and interquartile range. RESULTS: Eighteen individuals (10 males, 56%) with H3F3 germline variants were included. Thirteen of 18 individuals (72%) presented with a small posterior fossa. Six individuals (33%) presented with reduced size and an internal rotational appearance of the heads of the caudate nuclei along with an enlarged and squared appearance of the frontal horns of the lateral ventricles. Five individuals (28%) presented with dysgenesis of the splenium of the corpus callosum. Cortical developmental abnormalities were noted in 8 individuals (44%), with dysgyria and hypoplastic temporal poles being the most frequent presentation. CONCLUSIONS: Imaging phenotypes in germline H3F3-affected individuals are related to brain features, including a small posterior fossa as well as dysgenesis of the corpus callosum, cortical developmental abnormalities, and deformity of lateral ventricles.
CRIS-Team Scopus Importer:2022-08-19

Brainstem biopsy in pediatric diffuse intrinsic pontine glioma in the era of precision medicine: the INFORM study experience - Pfaff, Elke; El Damaty, Ahmed; Balasubramanian, Gnana Prakash; Blattner-Johnson, Mirjam; Worst, Barbara C.; Stark, Sebastian; Witt, Hendrik; Pajtler, Kristian W.; van Tilburg, Cornelis M.; Witt, Ruth; Milde, Till; Jakobs, Martin; et al. (European Journal of Cancer, 2019)
Purpose: Diffuse intrinsic pontine glioma (DIPG) is a highly aggressive paediatric brain tumour with fatal outcome. The Individualised Therapy For Relapsed Malignancies In Childhood (INFORM) registry study offers comprehensive molecular profiling of high-risk tumours to identify target alterations for potential precision therapy. We analysed molecular characteristics and clinical data after brainstem biopsy of all enrolled newly diagnosed DIPGs. Patients and methods: From –February 2015 to February 2018, 21 subsequent primary DIPG cases were enrolled in the nation-wide multicentre INFORM registry study after brainstem biopsy. Whole-genome, whole-exome sequencing and DNA methylation analysis were performed, and RNA-sequencing was added in case of sufficient material. Clinical data were obtained from standardised questionnaires and the INFORM clinical data bank. Results: Tumour material obtained from brainstem biopsy was sufficient for DNA analysis in all cases and RNA analysis in 16 of 21 cases. In 16 of 21 cases (76%), potential targetable alterations were identified including highly relevant MET and NTRK1 fusions as well as an EZH2 alteration not previously described in DIPG. In 5 of 21 cases, molecular information was used for initiation of targeted treatment. The majority of patients (19/21) presented with neurological deficits at diagnosis. Newly arising or worsening of neurological deficits post-biopsy occurred in nine patients. Symptoms were reversible or improved notably in eight cases. Conclusion: In this multicentre study setting, brainstem biopsy of DIPG was feasible and yielded sufficient material for comprehensive molecular profiling. Relevant molecular targets were identified impacting clinical management in a substantial subset. Death or severe bleeding occurred in none of the cases. One of 20 patients experienced unilateral paraesthesia possibly related to biopsy.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Brainstem biopsy; Molecular profiling; Pediatric diffuse intrinsic pons glioma; Targeted therapy

Brittle-Cornea-Syndrom Typ 1 durch Compound-Heterozygotie zweier Mutationen im ZNF469-Gen - Menzel-Severing, Johannes; Meiller, Ralph; Kraus, Cornelia; Trollmann, Regina; Atalay, Deniz (Ophthalmologe, 2019)
We report the case of a 3-year-old boy presenting with bilateral keratoglobus and blue sclera in addition to hallux valgus, arachnodactyly, small joint hypermobility, mitral valve dysfunction and a history of generalized muscular hypotonia in early infancy. Molecular genetics provided evidence of two pathogenic mutations in the ZNF469 gene (compound heterozygosity) leading to the diagnosis of brittle cornea syndrome type 1. In addition to neuropediatric care, spectacles were prescribed to correct refractive error and for ocular protection. Owing to the thin cornea and sclera, eye injuries are the main cause for irreversible visual loss in this disease.
CRIS-Team Scopus Importer:2019-08-20
Keywords: Blue sclera; Connective tissue disease; Hereditary eye disease; Keratoglobus; Pediatric ophthalmology

Burden-of-illness and cost-driving factors in Dravet syndrome patients and carers: A prospective, multicenter study from Germany - Strzelczyk, Adam; Kalski, Malin; Bast, Thomas; Wiemer-Kruel, Adelheid; Bettendorf, Ulrich; Kay, Lara; Kieslich, Matthias; Kluger, Gerhard; Kurlemann, Gerhard; Mayer, Thomas; Neubauer, Bernd A.; Polster, Tilman; et al. (European Journal of Paediatric Neurology, 2019)
Introduction: Dravet syndrome (DS) is a rare developmental and epileptic encephalopathy. This study estimated cost, cost-driving factors and quality of life (QoL) in patients with Dravet syndrome and their caregivers in a prospective, multicenter study in Germany. Methods: A validated 3–12-month retrospective questionnaire and a prospective 3-month diary assessing clinical characteristics, QoL, and direct, indirect and out-of-pocket (OOP) costs were administered to caregivers of patients with DS throughout Germany. Results: Caregivers of 93 patients (mean age 10.1 years, ±7.1, range 15 months–33.7 years) submitted questionnaires and 77 prospective diaries. The majority of patients (95%) experienced at least one seizure during the previous 12 months and 77% a status epilepticus (SE) at least once in their lives. Over 70% of patients had behavioural problems and delayed speech development and over 80% attention deficit symptoms and disturbance of motor skills and movement coordination. Patient QoL was lower than in the general population and 45% of caregivers had some form of depressive symptoms. Direct health care costs per three months were a mean of €6,043 ± €5,825 (median €4054, CI €4935-€7350) per patient. Inpatient costs formed the single most important cost category (28%, €1,702 ± €4,315), followed by care grade benefits (19%, €1,130 ± €805), anti-epileptic drug (AED) costs (15%, €892 ± €1,017) and ancillary treatments (9%, €559 ± €503). Total indirect costs were €4,399 ±€ 4,989 (median €0, CI €3466-€5551) in mothers and €391 ± €1,352 (median €0, CI €195-€841) in fathers. In univariate analysis seizure frequency, experience of SE, nursing care level and severe additional symptoms were found to be associated with total direct healthcare costs. Severe additional symptoms was the single independently significant explanatory factor in a multivariate analysis. Conclusions: This study over a period up to 15 months revealed substantial direct and indirect healthcare costs of DS in Germany and highlights the relatively low patient and caregiver QoL compared with the general population.
CRIS-Team Scopus Importer:2019-05-21
Keywords: Costs; Depression; Epilepsy; Quality of life; Seizure

C1 Esterase Inhibitor Reduces BBB Leakage and Apoptosis in the Hypoxic Developing Mouse Brain - Jung, Susan; Topf, Hans Georg; Boie, Gudrun; Trollmann, Regina (Neuromolecular Medicine, 2019)
Inflammatory pathways involved in blood–brain barrier (BBB) vulnerability and hypoxic brain oedema in models of perinatal brain injury seem to provide putative therapeutic targets. To investigate impacts of C1-esterase inhibitor (C1-INH; 7.5–30 IU/kg, i.p.) on functional BBB properties in the hypoxic developing mouse brain (P7; 8% O2 for 6 h), expression of pro-apoptotic genes (BNIP3, DUSP1), inflammatory markers (IL-1ß, TNF-alpha, IL-6, MMP), and tight junction proteins (ZO-1, occludin, claudin-1, -5), and S100b protein concentrations were analysed after a regeneration period of 24 h. Apoptotic cell death was quantified by CC3 immunohistochemistry and TUNEL staining. In addition to increased apoptosis in the parietal cortex, hippocampus, and subventricular zone, hypoxia significantly enhanced the brain-to-plasma albumin ratio, the cerebral S100b protein levels, BNIP3 and DUSP1 mRNA concentrations as well as mRNA expression of pro-inflammatory cytokines (IL-1ß, TNF-alpha). In response to C1-INH, albumin ratio and S100b concentrations were similar to those of controls. However, the mRNA expression of BNIP3 and DUSP1 and pro-inflammatory cytokines as well as the degree of apoptosis were significantly decreased compared to non-treated controls. In addition, occludin mRNA levels were elevated in response to C1-INH (p < 0.01). Here, we demonstrate for the first time that C1-INH significantly decreased hypoxia-induced BBB leakage and apoptosis in the developing mouse brain, indicating its significance as a promising target for neuroprotective therapy.
CRIS-Team Scopus Importer:2019-08-23
Keywords: BNIP3; DUSP1; Hypoxia; Matrix metalloproteinases; Neonatal brain injury; Neuroprotection; Occludin; S100b protein; Tight junctions

Candidate reference measurement procedure based on isotope dilution-two dimensional-liquid chromatography-tandem mass spectrometry for the quantification of androstenedione in human serum and plasma - Ott, Myriam; Bauland, Friederike; Fischer, Vanessa; Köppl, Daniel; Gaudl, Alexander; Geistanger, Andrea; Ceglarek, Uta; Rauh, Manfred; Taibon, Judith (Clinical Chemistry and Laboratory Medicine, 2025)
Objectives: Androstenedione (ASD) is a biomarker used in the diagnosis of hyperandrogenism and adrenal hyperplasia. Therefore, accurate measurement of serumASD is pivotal in clinical settings. We aimed to develop a novel highly selective reference measurement procedure (RMP) based on isotope dilution-two dimensional-liquid chromatographytandem mass spectrometry (ID-2D-LC-MS/MS) for the quantification of ASD in human serum/plasma. Methods: To achieve high selectivity and sensitivity, a twodimensional heart-cut LC approach for LC-MS/MS and a supported liquid extraction sample preparation protocol were employed. Matrix effects were evaluated through a post-column infusion experiment and comparison of standard line slopes. Precision and accuracy were determined via a multi-day validation experiment. Reproducibility was assessed by comparing results from two independent laboratories, and measurement uncertainty (MU) was evaluated in compliance with current guidelines. Results: Our novel RMP proved effective for measuring ASD concentrations ranging from 0.00800 ng/mL to 12.0 ng/mL (0.0279 nmol/L to 41.9 nmol/L) and demonstrated matrixindependence. The relative mean bias varied between 0.6 and 2.2 %across different matrices and concentration levels. Intermediate precision was observed to be between 1.2 and 1.9 %. The expanded measurement uncertainty for ASD target value assignment ranged from 1.7 to 2.5 %, irrespective of sample concentration. Equivalence to the JCTLMlisted RMP was evaluated through a method comparison study, revealing a high degree of agreement (r≥0.997). Additionally, by comparing results from two independent laboratories, the transferability and reproducibility of the RMP were confirmed. Conclusions: This isotope dilution two-dimensional LC-MS/ MS method can be used for the evaluation and standardization of routine assays and for measuring individual patient samples, ensuring traceability.
CRIS-Team Scopus Importer:2025-06-06
Keywords: androstenedione; isotope dilution-liquid chromatography-tandem mass spectrometry; qNMR characterization; reference measurement procedure; SI units; traceability

Can we starve leukemia? Metabolic needs of MLL - Garcia-Cuellar, Maria-Paz; Lawlor, Jennifer; Böttcher, Martin; Mougiakakos, Dimitrios; Metzler, Markus; Slany, Robert (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-10-23

Cardiomyopathy in Duchenne Muscular Dystrophy: Current Value of Clinical, Electrophysiological and Imaging Findings in Children and Teenagers - Dittrich, Sven; Türk, Matthias; Haaker, G.; Greim, V.; Buchholz, A.; Burkhardt, B.; Fujak, A.; Trollmann, Regina; Schmid, Andrea; Schröder, Rolf (Klinische Pädiatrie, 2015)
Progressive cardiomyopathy (CMP) is one main cause of death in DMD. This cross-sectional assessment of different cardiac diagnostic procedures focusses on preterm diagnosis of cardiac dysfunction.39 male DMD patients aged 6-20 years were included. 6 patients were still ambulatory, 21 patients received corticosteroid therapy.All patients were investigated by ECG, Holter ECG and heart rate variability (HRV), B-type natriuretic peptide (BNP), echocardiography (TTE), tissue Doppler Imaging (TD) and magnetic resonance imaging (MRI) with Late Gadolinium enhancement (LE) and segmental wall motion analysis (WMA).56% of the patients showed repolarization abnormalities and 76% altered HRV. Subnormal ventricular function was found in 25% by TTE and in 34% by MRI. TD differed from normal controls only in the apical septum. In MRI 89% of the patients showed different distribution and intensity of LE and WM restriction. The extent of LE was less in patients after steroid treatment (p<0.05).MRI with segmental LE- and WM-analysis seems to be superior to TTE and TD in exploring regional distribution and severity of damage of the myocardium. ECG and HRV abnormalities are common in DMD-patients but not tightly predictive for segmental and global left ventricular dysfunction. Targeted treatment of CMP in DMD needs prospective evaluation.A timely cardiac MRI is the most sensitive investigation for the identification of early myocardial changes in DMD which is a prerequisite for early interventions and therapeutic strategies.
EVALuna2:7289

Cardiopulmonary function in paediatric post-COVID-19: a controlled clinical trial - Schöffl, Isabelle; Raming, Roman; Tratzky, Jan Philipp; Regensburger, Adrian; Kraus, Calvin; Wällisch, Wolfgang; Trollmann, Regina; Wölfle, Joachim; Dittrich, Sven; Heiß, Rafael; Knieling, Ferdinand; Weigelt, Annika (European Journal of Pediatrics, 2024)
Recently, the importance of post-COVID-19 in children has been recognized in surveys and retrospective chart analysis. However, objective data in the form of cardiopulmonary exercise test as performed in adults suffering from this condition are still lacking. This study aimed to investigate the cardiopulmonary effects of post-COVID-19 on children and adolescents. In this cross-sectional study (the FASCINATE study), children fulfilling the criteria of post-COVID-19 and an age- and sex-matched control group underwent cardiopulmonary exercise testing on a treadmill and completed a questionnaire with regard to physical activity before, during and after the infection with SARS-CoV-2. We were able to recruit 20 children suffering from post-COVID-19 (mean age 12.8 ± 2.4 years, 60% females) and 28 control children (mean age 11.7 ± 3.5 years, 50% females). All participants completed a maximal treadmill test with a significantly lower V ˙ O 2peak in the post-COVID-19 group (37.4 ± 8.8 ml/kg/min vs. 43.0 ± 6.7 ml/kg/min. p = 0.019). This significance did not persist when comparing the achieved percentage of predicted V ˙ O 2peak . There were no significant differences for oxygen pulse, heart rate, minute ventilation or breathing frequency. Conclusion: This is the first study to investigate post-COVID-19 in children using the cardiopulmonary exercise test. Although there was a significantly reduced V ˙ O 2peak in the post-COVID-19 group, this was not true for the percent of predicted values. No pathological findings with respect to cardiac or pulmonary functions could be discerned. Deconditioning was the most plausible cause for the experienced symptoms. Trial registration: clinicaltrials.gov, NCT054445531, Low-field Magnetic Resonance Imaging in Pediatric Post Covid-19—Full Text View—ClinicalTrials.gov. What is Known: • The persistence of symptoms after an infection with SARS-CoV 2, so-called post-COVID-19 exists also in children. • So far little research has been conducted to analyze this entity in the pediatric population. What is New: • This is the first study proving a significantly lower cardiopulmonary function in pediatric patients suffering from post-COVID-19 symptoms. • The cardiac and pulmonary function appear similar between children suffering from post-COVID-19 and those who don’t, but the peripheral muscles seem affected.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Cardiopulmonary exercise testing; Exercise capacity; Fitness; Physical activity; Post-COVID; VO

Cardiovascular Outcome of Pediatric Patients With Bi-Allelic (Homozygous) Familial Hypercholesterolemia Before and After Initiation of Multimodal Lipid Lowering Therapy Including Lipoprotein Apheresis - Taylan, Christina; Driemeyer, Joenna; Schmitt, Claus P.; Pape, Lars; Büscher, Rainer; Galiano, Matthias; König, Jens; Schürfeld, Carsten; Spitthöver, Ralf; Versen, Axel; Koziolek, Michael; Marsen, Tobias A.; et al. (American Journal of Cardiology, 2020)
Twenty-four patients with bi-allelic familial hypercholesterolemia commencing chronic lipoprotein apheresis (LA) at a mean age of 8.5 ± 3.1 years were analysed retrospectively and in part prospectively with a mean follow-up of 17.2 ± 5.6 years. Mean age at diagnosis was 6.3 ± 3.4 years. Untreated mean LDL-C concentrations were 752 mg/dl ± 193 mg/dl (19.5 mmol/l ± 5.0 mmol/l). Multimodal lipid lowering therapy including LA resulted in a mean LDL-C concentration of 184 mg/dl (4.8 mmol/l), which represents a 75.5% mean reduction. Proprotein convertase subtilisin/kexin type 9-antibodies contributed in 3 patients to LDL-C lowering with 5 patients remaining to be tested. After commencing chronic LA, 16 patients (67%) remained clinically stable with only subclinical findings of atherosclerotic cardiovascular disease (ASCVD), and neither cardiovascular events, nor need for vascular interventions or surgery. In 19 patients (79%), pathologic findings were detected at the aortic valve (AV), which in the majority were mild. AV replacement was required in 2 patients. Mean Lipoprotein(a) concentration was 42.4 mg/dl, 38% had >50 mg/dl. There was no overt correlation of AV pathologies with other ASCVD complications, or Lipoprotein(a) concentration. Physicochemical elimination of LDL particles by LA appears indispensable for patients with bi-allelic familial hypercholesterolemia and severe hypercholesterolemia to maximize the reduction of LDL-C. In conclusion, in this rare patient group regular assessment of both the AV, as well as all arteries accessible by ultrasound should be performed to adjust the intensity of multimodal lipid lowering therapy with the goal to prevent ASCVD events and aortic surgery.
CRIS-Team Scopus Importer:2020-11-20

Caring for a Child with Congenital Adrenal Hyperplasia Diagnosed by Newborn Screening: Parental Health-Related Quality of Life, Coping Patterns, and Needs - Rautmann, Laura; Witt, Stefanie; Theiding, Christoph; Odenwald, Birgit; Nennstiel-Ratzel, Uta; Dörr, Helmuth-Günther; Quitmann, Julia Hannah (International Journal of Environmental Research and Public Health, 2023)
Diagnosing a child by newborn screening with classic congenital adrenal hyperplasia due to 21-hydroxylase deficiency (CAH) causes multiple challenges for the affected parents and the whole family. We aimed to examine the health-related Quality of Life (HrQoL), coping, and needs of parents caring for a child with CAH to develop demand-responsive interventions for improving the psychosocial situation of affected families. In a retrospective cross-sectional design, we assessed HrQoL, coping patterns, and the needs of parents caring for a CAH-diagnosed child using specific questionnaires. Data of 59 families with at least one child diagnosed with CAH were analyzed. The results show that mothers and fathers in this study reached significantly higher HrQoL scores compared to reference cohorts. Decisive for the above-average parental HrQoL were effective coping behaviors and the parental needs being met. These findings verify the importance of helpful coping patterns and rapid fulfillment of parental needs for maintaining a good and stable HrQoL of parents with a child diagnosed with CAH. It is crucial to strengthen the parental HrQoL to build a reasonable basis for a healthy upbringing and improve the medical care of CAH-diagnosed children.
CRIS-Team Scopus Importer:2023-03-24
Keywords: 21-hydroxylase deficiency; congenital adrenal hyperplasia; newborn screening; parental coping; parental needs; psychological stress; rare disease

CAR-T cells for the treatment of pediatric chronic myeloid leukemia in repeatedly relapsed lymphoid blast phase - Kramp, Laura Jane; Heydrich-Karsten, Christiane; Sembill, Stephanie; Karow, Axel; Lion, Thomas; Chitadze, Guranda; Suttorp, Meinolf; Cario, Gunnar; Metzler, Markus (Annals of Hematology, 2024)
Chronic myeloid leukemia presenting de novo in the blast phase (CML-BP) is a rare diagnosis among pediatric malignancies. We report on a 16-year-old male who presented with CML-BP lymphoid at diagnosis. He was treated with shortened acute lymphoblastic leukemia induction plus the tyrosine kinase inhibitor (TKI) imatinib followed by dasatinib. After achieving molecular remission (MR), hematopoietic stem cell transplantation (HSCT) was performed early after diagnosis. Despite prophylactic dasatinib, he relapsed 3 months later with the kinase domain mutation T315I. Multiple therapeutic approaches including ponatinib, blinatumomab, a 2nd HSCT from a different donor, donor lymphocyte infusions, and high-dose asciminib all resulted in subsequent relapse. Another molecular response was achieved by combining ponatinib plus asciminib with chemotherapy. In this situation, CD19-directed CAR-T cells (Kymriah®) were administered for compassionate use and tolerated without adverse events. Compared to all prior therapies, CAR T-cells maintained remission. After 12 months of follow-up, complete B-cell aplasia and low numbers of CAR-T cells are detectable in the peripheral blood, potentially mediating long-term disease control.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Blast phase; CD19 CAR-T cells; Chronic myeloid leukemia; Refractory leukemia

CAR T-cell therapy rescues adolescent with rapidly progressive lupus nephritis from haemodialysis - Krickau, Tobias; Naumann-Bartsch, Nora; Aigner, Michael; Kharboutli, Soraya; Kretschmann, Sascha; Spörl, Silvia; Vasova, Ingrid; Völkl, Simon; Wölfle, Joachim; Mackensen, Andreas; Schett, Georg; Metzler, Markus; et al. (Lancet, 2024)
CRIS-Team Scopus Importer:2024-05-03

Cavernous sinus thrombosis as a rare cause of exophthalmos in childhood : A case report - Kamawal, A.; Schmidt, M. A.; Rompel, O.; Gusek-Schneider, G. C.; Mardin, C. Y.; Trollmann, Regina (Ophthalmologe, 2016)
Complications of acute bacterial sinusitis mostly occur in children and adolescents. In particular, intracranial spread of the infection can lead to severe even fatal courses of the disease. This article is a case report about a 13-year-old boy suffering from left-sided headache, meningismus and exophthalmos as presenting symptoms. Cranial magnetic resonance imaging (MRI) showed merely right-sided sphenoid sinusitis; however, the diffusion-weighted MRI sequence indicated a left-sided cavernous sinus thrombosis, which could be confirmed by computed tomography (CT) angiography. Cerebrospinal fluid diagnostics showed significant leukocytosis confirming secondary meningitis. Finally, exophthalmos was explained by parainfectious cavernous sinus thrombosis and periorbital edema. This case report highlights the importance of extended and specific diagnostic imaging in cases of clinically suspected complications in children and adolescents with sinusitis and the diagnostic significance of diffusion-weighted MRI.
EVALuna2:21321

Cell-based resurfacing of large cartilage defects: Long-term evaluation of grafts from autologous transgene-activated periosteal cells in a porcine model of osteoarthritis - Gelse, Koja; Muehle, Christiane; Franke, Oliver; Park, Jung; Jehle, Marc; Durst, Karsten; Göken, Mathias; Hennig, Friedrich; Mark, Klaus; Schneider, Holm (Arthritis & Rheumatism-Arthritis Care & Research, 2008)
WW1::753

Centralization as the key survival benefit in acute neonatal surgery - Besendörfer, Manuel; Günster, Simone; Linz, Katja; Reutter, Heiko Martin; Diez, Sonja (Frontiers in Pediatrics, 2024)
Introduction: Centralization of neonatal surgical care for congenital malformations is already under discussion. Acute care of neonatal emergencies in perinatal centers with affiliated hospitals is not uniformly regulated in Germany. Materials and methods: Analyses are based on acute pediatric surgical care at four affiliated hospitals of a perinatal center. Epidemiologic data and outcome parameters “survival”, “intracerebral hemorrhage”, and “revision of surgical indication” are assessed. Comparison is made between patients receiving surgical treatment at affiliated hospitals (group A) and patients with transfer to the university center for therapy in case of surgical indication for gastrointestinal diseases (group B). Results: 17 group A-patients are compared to 40 group B-patients. Comparison of epidemiological data reveals no significant differences. There is a survival advantage with transfer to the university center (mortality of 29% in group A vs. 2% in group B, p = 0.007). Intracerebral hemorrhage occurred more frequently in externally treated patients (group A 24% vs. group B 2%, p = 0.024). Surgical indication was revised in 30% of group B at the university center (p = 0.011) with consecutive successful conservative treatment. Conclusion: Transfer of patients at the beginning of the acute phase of gastrointestinal diseases is key to optimize the quality of neonatal surgical care. However, larger population studies should confirm the presented results, discuss restricting factors of real care structures and should rule out bias in triage of patients.
CRIS-Team Scopus Importer:2024-04-05
Keywords: centralization; German medical system; neonatal emergency; neonatal surgery; perinatal center

Cerebral MRI and Clinical Findings in Children with PTEN Hamartoma Tumor Syndrome: Can Cerebral MRI Scan Help to Establish an Earlier Diagnosis of PHTS in Children? - Plamper, Michaela; Born, Mark; Gohlke, Bettina; Schreiner, Felix; Schulte, Sandra; Splittstößer, Vera; Wölfle, Joachim (Cells, 2020)
BACKGROUND: PTEN Hamartoma Tumor Syndrome (PHTS) is caused by germline autosomal-dominant mutations of the tumor suppressor gene PTEN. Subjects harbour an increased risk for tumor development, with thyroid carcinoma occurring in young children. Establishing a diagnosis is challenging, since not all children fulfill diagnostic criteria established for adults. Macrocephaly is a common feature in childhood, with cerebral MRI being part of its diagnostic workup. We asked whether distinct cMRI features might facilitate an earlier diagnosis. METHODS: We retrospectively studied radiological and clinical data of pediatric patients who were presented in our hospital between 2013 and 2019 in whom PTEN gene mutations were identified. RESULTS: We included 27 pediatric patients (18 male) in the analysis. All patients were macrocephalic. Of these, 19 patients had received at least one cMRI scan. In 18 subjects variations were detected: enlarged perivascular spaces (EPVS; in 18), white matter abnormalities (in seven) and less frequently additional pathologies. Intellectual ability was variable. Most patients exhibited developmental delay in motor skills, but normal intelligence. CONCLUSION: cMRI elucidates EPVS and white matter abnormalities in a high prevalence in children with PHTS and might therefore aid as a diagnostic feature to establish an earlier diagnosis of PHTS in childhood.
CRIS-Team Scopus Importer:2020-07-24
Keywords: children; cMRI; enlarged perivascular spaces; macrocephaly; PHTS; PTEN; Virchow–Robin spaces; white matter abnormalities

CFAP74-mutations as cause of Primary Ciliary Dyskinesia (PCD): Clinical presentation and diagnostic challenges - Biebach, L.; Cindric, S.; Koenig, J.; Aprea, I.; Dougherty, G.; Raidt, J.; Bracht, D.; Ruppel, Renate; Schreiber, J.; Hjeij, R.; Olbrich, H.; Omran, H. (EUROPEAN RESPIRATORY JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Changes in behavior and quality of life in German young children during the COVID-19 pandemic—results from the COVID kids bavaria study - Schillok, Hannah; Coenen, Michaela; Rehfuess, Eva A.; Kuhlmann, Pia H.; Matl, Stefan; Kindermann, Hannah; Maison, Nicole; Eckert, Jana; von Both, Ulrich; Behrends, Uta; Frühwald, Michael C.; Neubert, Antje; et al. (Frontiers in Pediatrics, 2023)
Introduction: The COVID-19 pandemic with its containment measures such as closures of schools and daycare facilities led to numerous restrictions in daily life, putting developmental opportunities and health-related quality of life in children at risk. However, studies show that not every family was impacted equally by the pandemic and that this exceptional health and societal situation reinforced pre-existing health inequalities among the vulnerable. Our study aimed at analyzing changes in behavior and health-related quality of life of children attending elementary schools and daycare facilities in Bavaria, Germany in spring 2021. We also sought to identify associated factors contributing to inequalities in quality of life. Methods: Data from a multi-center, open cohort study (“COVID Kids Bavaria”) conducted in 101 childcare facilities and 69 elementary schools across all electoral districts of Bavaria were analyzed. Children attending these educational settings (aged 3-10 years) were eligible for participation in a survey on changes in behavior and health-related quality of life. The KINDLR questionnaire (based on children’s self-report and parental report) was administered about one year after the onset of the pandemic (spring 2021). Descriptive and logistic regression analyses and comparisons to pre-pandemic KiGGS (German Health Interview and Examination Survey for Children and Adolescents) data were undertaken. Results: Among respondents, a high percentage of parents reported changes in their children's eating and sleeping behavior, sports and outdoor activities as well as altered screen time. Health-related quality of life in KINDLR analyses compared to pre-pandemic population averages were lower in all age groups (for 3–6-year-old KINDLR-total score: COVID Kids Bavaria MD 74.78 ± 10.57 vs KiGGS data 80.0 ± 8.1; 7-10 years-old KINDLR-total score: COVID Kids Bavaria MD 73.88 ± 12.03 vs KiGGS data 79.30 ± 9.0). No significant differences were detected with regard to associated factors, namely type of institution, sex of the child, migration background, household size and parental education. Conclusion: These findings suggest a relevant impact of the COVID-19 pandemic on children’s behavior and health-related quality of life one year after the onset of the pandemic. Further analyses in large-scale longitudinal studies are needed to determine the effects of specific pandemic or crisis associated factors contributing to health inequalities.
CRIS-Team Scopus Importer:2023-06-02
Keywords: behavior change; COVID-19; health inequalities in children; health-related quality of life (HRQL); mental health—related quality of life; pandemic

Characterization and diagnostic application of genomic NPM-ALK fusion sequences in anaplastic large-cell lymphoma - Krumbholz, Manuela; Woessmann, Wilhelm; Zierk, Jakob; Seniuk, David; Ceppi, Paolo; Zimmermann, Martin; Singh, Vijay Kumar; Metzler, Markus; Damm-Welk, Christine (Oncotarget, 2018)
Nucleophosmin-anaplastic lymphoma kinase (NPM-ALK) fusion genes resulting from the translocation t(2;5)(p23;q35) are present in almost 90% of childhood ALK-positive anaplastic large-cell lymphomas (ALCL). Detection and quantification of minimal disseminated disease (MDD) by measuring NPM-ALK fusion transcript levels in the blood provide independent prognostic parameters. Characterization of the genomic breakpoints provides insights into the pathogenesis of the translocation and allows for DNA-based minimal disease monitoring. We designed a nested multiplex PCR assay for identification and characterization of genomic NPM-ALK fusion sequences in 45 pediatric ALCL-patients, and used the sequences for quantitative MDD monitoring. Breakpoint analysis indicates the involvement of inaccurate non-homologous end joining repair mechanisms in the formation of NPM-ALK fusions. Parallel quantification of RNA and DNA levels in the cellular fraction of 45 blood samples from eight patients with NPM-ALK-positive ALCL correlated, as did cell-free circulating NPM-ALK DNA copies in the plasma fraction of 37 blood samples. With genomic NPM-ALK fusion sequence quantification, plasma samples of ALCL patients become an additional source for MRD-assessment. Parallel quantification of NPM-ALK transcripts and fusion genes in ALCL cell lines treated with the ALK kinase inhibitor crizotinib illustrates the potential value of supplementary DNA-based quantification in particular clinical settings.
EVALuna2:34643

Cherry-red spot in a 13-month-old child - Hohberger, B.; Stenger, Nico; Trollmann, Regina; Mardin, C. Y.; Gusek-Schneider, G-C. (Ophthalmologe, 2016)
EVALuna2:21322

Childhood cancer predisposition syndromes-A concise review and recommendations by the Cancer Predisposition Working Group of the Society for Pediatric Oncology and Hematology - Ripperger, Tim; Bielack, Stefan S.; Borkhardt, Arndt; Brecht, Ines B.; Burkhardt, Birgit; Calaminus, Gabriele; Debatin, Klaus-Michael; Deubzer, Hedwig; Dirksen, Uta; Eckert, Cornelia; Eggert, Angelika; Erlacher, Miriam; et al. (American Journal of Medical Genetics Part A, 2017)
Heritable predisposition is an important cause of cancer in children and adolescents. Although a large number of cancer predisposition genes and their associated syndromes and malignancies have already been described, it appears likely that there are more pediatric cancer patients in whom heritable cancer predisposition syndromes have yet to be recognized. In a consensus meeting in the beginning of 2016, we convened experts in Human Genetics and Pediatric Hematology/Oncology to review the available data, to categorize the large amount of information, and to develop recommendations regarding when a cancer predisposition syndrome should be suspected in a young oncology patient. This review summarizes the current knowledge of cancer predisposition syndromes in pediatric oncology and provides essential information on clinical situations in which a childhood cancer predisposition syndrome should be suspected.
EVALuna2:9370

Choice of basal insulin therapy is associated with weight and height development in type 1 diabetes: A multicenter analysis from the German/Austrian DPV registry in 10 338 children and adolescents - Vollbach, Heike; Auzanneau, Marie; Reinehr, Thomas; Wiegand, Susanna; Schwab, Karl-Otfried; Oeverink, Rudolf; Froehlich-Reiterer, Elke; Wölfle, Joachim; De Beaufort, Carine; Kapellen, Thomas; Gohlke, Bettina; Holl, Reinhard W. (Journal of Diabetes, 2021)
Background Available basal insulin regimes differ in pharmacokinetic profiles, which may be related to subsequent changes in anthropometry in patients with type 1 diabetes. This analysis elucidates the standardized height and body mass index development (height and BMI standard deviation score [height-SDS and BMI-SDS]) in pediatric type 1 diabetes patients depending on the choice of basal insulin. Methods Longitudinal data of 10 338 German/Austrian patients from the Diabetes Prospective Follow-up (DPV, Diabetes Patienten Verlaufsdokumentation) database were analyzed. Patients aged 5.0 to 16.9 years were treated exclusively with neutral protamine Hagedorn (NPH), insulin detemir (IDet), insulin glargine (IGla), or continuous subcutaneous insulin infusion (CSII) for at least 3 years. Population-based German reference data were used to calculate height-SDS and BMI-SDS. Multiple linear regression was conducted. Results BMI-SDS increased significantly in all regimes (NPH P = .0365; IDet P = .0003; IGla P < .0001; and CSII P < .0001). Direct comparison of the therapies revealed a favorable association only for NPH vs IGla. A rise in BMI-SDS was observed for all insulins in females, but only for IGla in males. BMI-SDS increment was not observed before 8 years of age. Initially and at the end of the observation period, mean height was above the 50th percentile of the reference population. Across the cohort, height-SDS declined during the observation period, except for CSII. Apart from the 5.0- to 7.9-year-old subgroup, long-acting insulin analogues were associated with a significant loss of height-SDS. Conclusions Choice of basal insulin regimen might influence height development. CSII appeared to have a favorable effect on growth trajectories. All therapies were associated with an increase of BMI-SDS, most evident in females.
CRIS-Team WoS Importer:2021-07-23

Classic Congenital Adrenal Hyperplasia due to 21-Hydroxylase-Deficiency: 13 Years of Neonatal Screening and Follow-up in Bavaria - Odenwald, B.; Dörr, Helmuth-Günther; Bonfig, W.; Schmidt, H.; Fingerhut, R.; Wildner, M.; Nennstiel-Ratzel, U. (Klinische Pädiatrie, 2015)
21-Hydroxylase deficient (21-OHD) classic congenital adrenal hyperplasia (CAH) is a potentially lethal inherited endocrine disorder. It is included in many neonatal screening programs to prevent morbidity and mortality from salt-wasting and to reduce long-term health problems. This paper presents a population-based evaluation of CAH screening quality and outcome in Bavaria between 1999 and 2011 including long-term follow-up of patients.Screening process quality, clinical complications during the neonatal period, treatment and development of patients up to the age of 4 years were analysed.Among 1 420 102 screened infants, 114 cases of 21-OHD classic CAH were detected (prevalence 1:12 457). Mean age at start of treatment was 7 days. However, in 29 cases (25.4%), age at start of treatment was 12 days or more. The frequency of neonatal salt-wasting increased with age at start of treatment, but all neonatal salt-wasting episodes and crises were managed successfully. Up to the age of 4 years, developmental assessment of the CAH cohort yielded normal results.Epidemiological and screening effectiveness results are in keeping with other publications. For the most part, screening process times were compliant with guidelines. The Bavarian CAH screening and tracking system proved successful, but there were process delays and complications which might have been avoidable. The outcome supports the benefits of CAH screening, but further research is necessary to increase CAH screening effectiveness and to evaluate long-term effects.
EVALuna2:18918

Clean Intermittent Catheterization in Children under 12 Years Does Not Have a Negative Impact on Long-Term Graft Survival following Pediatric Kidney Transplantation - Marcou, Marios; Galiano, Matthias; Tzschoppe, Anja; Sauerstein, Katja; Wach, Sven; Taubert, Helge; Wullich, Bernd; Hirsch-Koch, Karin; Apel, Hendrik (Journal of Clinical Medicine, 2024)
Background: Congenital anomalies of the kidneys and urinary tract (CAKUTs) are one of the most prevalent primary causes of end-stage renal disease (ESRD) in young children, and approximately one-third of these children present with lower urinary tract dysfunction (LUTD). Many children with LUTD require therapy with clean intermittent catheterization (CIC). CIC commonly leads to bacteriuria, and considerations have arisen regarding whether CIC in immunosuppressed children is safe or whether repeated febrile urinary tract infections (UTIs) may lead to the deterioration of kidney graft function. Material and Methods: We retrospectively reviewed all cases of primary kidney transplantation performed in our center between 2001 and 2020 in recipients aged less than twelve years. The number of episodes of febrile UTIs as well as the long-term kidney graft survival of children undergoing CIC were compared to those of children with urological causes of ESRD not undergoing CIC, as well as to those of children with nonurological causes of ESRD. Results: Following successful kidney transplantation in 41 children, CIC was needed in 8 of these patients. These 8 children undergoing CIC had significantly more episodes of febrile UTIs than did the 18 children with a nonurological cause of ESRD (p = 0.04) but not the 15 children with a urological cause of ESRD who did not need to undergo CIC (p = 0.19). Despite being associated with a higher rate of febrile UTIs, CIC was not identified as a risk factor for long-term kidney graft survival, and long-term graft survival did not significantly differ between the three groups at a median follow-up of 124 months. Conclusions: Our study demonstrates that, under regular medical care, CIC following pediatric transplantation is safe and is not associated with a higher rate of long-term graft loss.
CRIS-Team Scopus Importer:2024-01-19
Keywords: CAKUT; catheterization; child; kidney transplantation; LUTD

Clinical characteristics and outcome of 60 pediatric patients with malignant melanoma registered with the German Pediatric Rare Tumor Registry (STEP) - Offenmüller, Sonja; Leiter, Ulrike; Bernbeck, Benedikt; Garbe, Claus; Eigentler, Thomas; Borkhardt, Arndt; Classen, Carl Friedrich; Corbacioglu, Selim; Dirksen, Uta; Ebetsberger-Dachs, Georg; Heinzerling, Lucie; Jorch, Norbert; et al. (Klinische Pädiatrie, 2017)
Background Malignant melanoma (MM) is a common malignancy in adults while it is rare in children. Thus, information on clinical behavior of pediatric MM is incomplete. Patients The German Pediatric Rare Tumor Registry (STEP) presents a prospective analysis of 60 childhood MM cases diagnosed between June 2006 and December 2014. Method Patients' ages ranged between 0 and 17 years at initial diagnosis (median age 9.6 years). Information on patient's and tumor characteristics was obtained by standardized documentation. Three-year overall survival (OS) and event-free survival (EFS) were estimated by the Kaplan-Meier test. Results Follow-up ranged from 0 to 116 months with a median of 36.5 months, however, univariate analysis was performed for 46 cases with a follow-up > 3 months, only. Cases with spitzoid histotype (40%) did not show a significantly different outcome compared to cases with non-spitzoid MM. Breslow thickness ≤ 2.00 mm was identified in 30% of the cases and 18% were Clark level I to III. Adjuvant therapy was used in 45% of cases. OS at 3 years was 100%, EFS 95.2%. Conclusion We present a series of cases with a high number of spitzoid malignant melanoma and advanced pediatric melanoma, but surprisingly good overall survival rates. Spitzoid and non-spitzoid MM do not differ in clinical behavior and survival.
EVALuna2:34327

Clinical Characteristics of the End-of-Life Phase in Children with Life-Limiting Diseases: Retrospective Study from a Single Center for Pediatric Palliative Care - Baumann, Fanni; Hébert, Steven; Rascher, Wolfgang; Wölfle, Joachim; Gravou-Apostolatou, Chara (Children, 2021)
Background: Data on the end-of-life phase of children receiving palliative care are limited. The purpose of this study is to investigate the spectrum of symptoms of terminally ill children, adolescents, and young adults, depending on their underlying disease. Methods: Findings are based on a 4.5-year retrospective study of 89 children who received palliative care before they died, investigating the symptomatology of the last two weeks before death. Results: In this study, the most common clinical symptomatology present in children undergoing end-of-life care includes pain, shortness of breath, anxiety, nausea, and constipation. Out of 89 patients included in this study, 47% suffered from an oncological disease. Oncological patients had a significantly higher symptom burden at the end of life (p < 0.05) compared to other groups, and the intensity of symptoms increased as the underlying disease progressed. The likelihood of experiencing pain and nausea/vomiting was also significantly higher in oncological patients (p = 0.016). Conclusions: We found that the underlying disease is associated with marked differences in the respective leading clinical symptom. Therefore, related to these differences, symptom management has to be adjusted according to the underlying disease, since the underlying disorder seems to exert an influence on the severity of symptoms and thereby on the modality and choice of treatment. This study is intended to aid underlying disease-specific symptom management at the end-of-life care for children, adolescents, and young adults, with a specific focus on end-of-life care in a home environment.
CRIS-Team WoS Importer:2021-07-09

Clinical characteristics, resource utilization, quality of life and care situation for patients with Dravet syndrome in Germany - Kalski, Malin; Schubert-Bast, Susanne; Kieslich, Matthias; Leyer, Anne-Christine; Polster, Tilman; Herting, Arne; Mayer, Thomas; Trollmann, Regina; Neubauer, Bernd A.; Bettendorf, Ulrich; Bast, Thomas; Wiemer-Kruel, Adelheid; et al. (Zeitschrift für Epileptologie, 2019)
Introduction and objective Dravet syndrome (DS) is a rare epileptic and developmental encephalopathy associated with cognitive impairment and delayed development due to genetic mutations predominantly in the SCN1A gene. This multicenter, prospective survey-based study collected data about the clinical characteristics, health care resource utilization, costs and quality of life (QoL) of patients with DS and their caregivers in Germany. Methods A retrospective questionnaire covering the previous 3-12 months was used in addition to a prospective diary over 3 months to confirm the retrospective data and to obtain detailed information about indirect costs, QoL, medication, seizures and health care resource utilization. The questionnaires and the diary were handed out to the parents via Dravet-Syndrome e.& x202f;V. and participating centers. Results The questionnaire and diary were completed by 93 and 77 caregivers of DS patients, respectively. Patient mean age was 10 years (range: 15 months-33.7 years), whereby the time to diagnosis was significantly lower in the last two decades. In the previous 12 months, 95% of patients experienced at least one epileptic seizure. Fever (93.4%), excitement (56%), sleep deprivation (51.6%) and physical exertion (50.5%) were reported as the factors that triggered seizures. The lifetime prevalence of status epilepticus was 77%, with 28% having had at least one episode of status epilepticus within the last year. Patient QoL was lower compared with the general population, with 46% of the parents reporting symptoms of depression. The 3-month direct healthcare costs were 6043 & x202f;euro per patient, the largest components of which were inpatient costs (1702 & x202f;euro) followed by nursing care services (1130 & x202f;euro), anticonvulsant drugs (892 & x202f;euro) and ancillary treatment (559 & x202f;euro). The 3-month total indirect cost for mothers was 4399 & x202f;euro and for fathers 391 & x202f;euro. Conclusion The DS is associated with frequent and often treatment refractory seizures, including status epilepticus as well as various comorbidities. This study shows the substantial associated socioeconomic impact of the disease, with high direct and indirect costs and reduced QoL for patients and the caregivers. In order to achieve an improvement in the QoL for patients with DS and caregivers, new treatment and care concepts are necessary.
CRIS-Team WoS Importer:2019-10-22

Clinical Effectiveness of Newborn Screening for Spinal Muscular Atrophy: A Nonrandomized Controlled Trial - Schwartz, Oliver; Vill, Katharina; Pfaffenlehner, Michelle; Behrens, Max; Weiß, Claudia; Johannsen, Jessika; Friese, Johannes; Hahn, Andreas; Ziegler, Andreas; Illsinger, Sabine; Smitka, Martin; Von Moers, Arpad; et al. (JAMA Pediatrics, 2024)
Importance: There is increasing evidence that early diagnosis and treatment are key for outcomes in infants with spinal muscular atrophy (SMA), and newborn screening programs have been implemented to detect the disease before onset of symptoms. However, data from controlled studies that reliably confirm the benefits of newborn screening are lacking. Objective: To compare data obtained on patients with SMA diagnosed through newborn screening and those diagnosed after clinical symptom onset. Design, Setting, and Participants: This nonrandomized controlled trial used data from the SMARTCARE registry to evaluate all children born between January 2018 and September 2021 with genetically confirmed SMA and up to 3 SMN2 copies. The registry includes data from 70 participating centers in Germany, Austria, and Switzerland. Data analysis was performed in February 2023 so that all patients had a minimal follow-up of 18 months. Exposure: Patients born in 2 federal states in Germany underwent screening in a newborn screening pilot project. All other patients were diagnosed after clinical symptom onset. All patients received standard care within the same health care system. Main Outcomes: The primary end point was the achievement of motor milestones. Results: A total of 234 children (123 [52.6%] female) were identified who met inclusion criteria and were included in the analysis: 44 (18.8%) in the newborn screening cohort and 190 children (81.2%) in the clinical symptom onset cohort. The mean (SD) age at start of treatment with 1 of the approved disease-modifying drugs was 1.3 (2.2) months in the newborn screening cohort and 10.7 (9.1) months in the clinical symptom onset cohort. In the newborn screening cohort, 40 of 44 children (90.9%) gained the ability to sit independently vs 141 of 190 (74.2%) in the clinical symptom onset cohort. For independent ambulation, the ratio was 28 of 40 (63.6%) vs 28 of 190 (14.7%). Conclusions and Relevance: This nonrandomized controlled trial demonstrated effectiveness of newborn screening for infants with SMA in the real-world setting. Functional outcomes and thus the response to treatment were significantly better in the newborn screening cohort compared to the unscreened clinical symptom onset group. Trial Registration: German Clinical Trials Register: DRKS00012699.
CRIS-Team Scopus Importer:2024-04-26

Clinical, Imaging, Genetic, and Disease Course Characteristics in Patients with GM2 Gangliosidosis: Beyond Age of Onset - Kern, Jan; Böhringer, Judith; Timmann, Dagmar; Trollmann, Regina; Stendel, Claudia; Kamm, Cristoph; Röbl, Markus; Santhanakumaran, Vidiyaah; Groeschel, Samuel; Beck-Wödl, Stefanie; Göricke, Sophia; Krägeloh-Mann, Ingeborg; et al. (Neurology, 2024)
Background and ObjectivesGM2 gangliosidoses, a group of autosomal-recessive neurodegenerative lysosomal storage disorders, result from β-hexosaminidase (HEX) deficiency with GM2 ganglioside as its main substrate. Historically, GM2 gangliosidoses have been classified into infantile, juvenile, and late-onset forms. With disease-modifying treatment trials now on the horizon, a more fine-grained understanding of the disease course is needed.MethodsWe aimed to map and stratify the clinical course of GM2 gangliosidoses in a multicenter cohort of pediatric and adult patients. Patients were stratified according to age at onset and age at diagnosis. The 2 resulting GM2 disease clusters were characterized in-depth for respective disease features (detailed standardized clinical, laboratory, and MRI assessments) and disease evolution.ResultsIn 21 patients with GM2 gangliosidosis (17 Tay-Sachs, 2 GM2 activator deficiency, 2 Sandhoff disease), 2 disease clusters were discriminated: an early-onset and early diagnosis cluster (type I; n = 8, including activator deficiency and Sandhoff disease) and a cluster with very variable onset and long interval until diagnosis (type II; n = 13 patients). In type I, rapid onset of developmental stagnation and regression, spasticity, and seizures dominated the clinical picture. Cherry red spot, startle reactions, and elevated AST were only seen in this cluster. In type II, problems with balance or gait, muscle weakness, dysarthria, and psychiatric symptoms were specific and frequent symptoms. Ocular signs were common, including supranuclear vertical gaze palsy in 30%. MRI involvement of basal ganglia and peritrigonal hyperintensity was seen only in type I, whereas predominant infratentorial atrophy (or normal MRI) was characteristic in type II. These types were, at least in part, associated with certain genetic variants.DiscussionAge at onset al.one seems not sufficient to adequately predict different disease courses in GM2 gangliosidosis, as required for upcoming trial planning. We propose an alternative classification based on age at disease onset and dynamics, predicted by clinical features and biomarkers, into type I - an early-onset, rapid progression cluster - and type II - a variable onset, slow progression cluster. Specific diagnostic workup, including GM2 gangliosidosis, should be performed in patients with combined ataxia plus lower motor neuron weakness to identify type II patients.
CRIS-Team Scopus Importer:2024-01-05

Clinical Outcomes in Pediatric Patients With Type 1 Diabetes With Early Versus Late Diagnosis: Analysis From the DPV Registry - Hammersen, Johanna; Tittel, Sascha R.; Kamrath, Clemens; Warncke, Katharina; Galler, Angela; Menzel, Ulrike; Hess, Melanie; Meißner, Thomas; Karges, Beate; Holl, Reinhard W. (Diabetes Care, 2024)
OBJECTIVE This study was conducted to evaluate the effects of early clinical diagnosis of type 1 diabetes by comparison of clinical parameters at diagnosis and during follow-up in patients with pediatric type 1 diabetes with early, intermediate, and late diagnosis. RESEARCH DESIGN AND METHODS In a population-based analysis, data on 14,292 pediatric patients with type 1 diabetes diagnosed between 2015 and 2019 were retrieved from the Diabetes Prospective Documentation (DPV) registry in March 2023. Patients were divided into four groups: one with diabetic ketoacidosis (DKA) at diagnosis and three with early, intermediate, or late diagnosis based on age-dependent HbA1c terciles. Laboratory-measured HbA1c values and those estimated from continuous glucose monitoring were aggregated as a combined glucose indicator (CGI). Insulin dose– adjusted CGI values <9% were defined as partial remission. RESULTS At diagnosis, patients had a median age of 9.8 years (IQR 6.8; 13.0). Three years later, patients with early diagnosis had lower CGI than patients with late diagnosis or DKA (mean [95% CI] 7.46% [7.40; 7.53] vs. 7.81% [7.75; 7.87] or 7.74% [7.68; 7.79], respectively; each P < 0.001). More patients experienced partial remission (12.6% [11.0; 14.4] vs. 9.1% [7.7; 10.7] or 8.6% [7.3; 10.0]; each P < 0.001), and 11.7% [10.2; 13.5] of patients with intermediate diagnosis were in partial remission. CONCLUSIONS Early clinical diagnosis of type 1 diabetes may be beneficial for metabolic control and remission after 3 years of follow-up. Patients diagnosed early may represent a distinct group with better resources or with a different disease biology and slower b-cell destruction, which needs further evaluation.
CRIS-Team Scopus Importer:2024-12-13

Clinical practice guidelines for the care of girls and women with Turner syndrome Proceedings from the 2023 Aarhus International Turner Syndrome Meeting - Gravholt, Claus H.; Andersen, Niels H.; Christin-Maitre, Sophie; Davis, Shanlee M.; Duijnhouwer, Anthonie; Gawlik, Aneta; Maciel-Guerra, Andrea T.; Gutmark-Little, Iris; Fleischer, Kathrin; Hong, David; Klein, Karen O.; Prakash, Siddharth K.; et al. (European Journal of Endocrinology, 2024)
Turner syndrome (TS) affects 50 per 100 000 females. TS affects multiple organs through all stages of life, necessitating multidisciplinary care. This guideline extends previous ones and includes important new advances, within diagnostics and genetics, estrogen treatment, fertility, comorbidities, and neurocognition and neuropsychology. Exploratory meetings were held in 2021 in Europe and United States culminating with a consensus meeting in Aarhus, Denmark in June 2023. Prior to this, eight groups addressed important areas in TS care: (1) diagnosis and genetics, (2) growth, (3) puberty and estrogen treatment, (4) cardiovascular health, (5) transition, (6) fertility assessment, monitoring, and counselling, (7) health surveillance for comorbidities throughout the lifespan, and (8) neurocognition and its implications for mental health and well-being. Each group produced proposals for the present guidelines, which were meticulously discussed by the entire group. Four pertinent questions were submitted for formal GRADE (Grading of Recommendations, Assessment, Development and Evaluation) evaluation with systematic review of the literature. The guidelines project was initiated by the European Society for Endocrinology and the Pediatric Endocrine Society, in collaboration with members from the European Society for Pediatric Endocrinology, the European Society of Human Reproduction and Embryology, the European Reference Network on Rare Endocrine Conditions, the Society for Endocrinology, and the European Society of Cardiology, Japanese Society for Pediatric Endocrinology, Australia and New Zealand Society for Pediatric Endocrinology and Diabetes, Latin American Society for Pediatric Endocrinology, Arab Society for Pediatric Endocrinology and Diabetes, and the Asia Pacific Pediatric Endocrine Society. Advocacy groups appointed representatives for pre-meeting discussions and the consensus meeting.
CRIS-Team Scopus Importer:2024-09-13
Keywords: cardiovascular health; co-morbidity; hypogonadism; infertility; neurocognition; transition; Turner syndrome

Clinical presentation and long-term outcome of patients with KCNJ11/ABCC8 variants: Neonatal diabetes or MODY in the DPV registry from Germany and Austria - Warncke, Katharina; Eckert, Alexander; Kapellen, Thomas; Kummer, Sebastian; Raile, Klemens; Dunstheimer, Desiree; Grulich-Henn, Jurgen; Wölfle, Joachim; Wenzel, Sandra; Hofer, Sabine E.; Dost, Axel; Holl, Reinhard W. (Pediatric Diabetes, 2022)
Objective: To describe clinical presentation/longterm outcomes of patients with ABCC8/KCNJ11 variants in a large cohort of patients with diabetes. Research Design and Methods We analyzed patients in the Diabetes Prospective Follow-up (DPV) registry with diabetes and pathogenic variants in the ABCC8/KCNJ11 genes. For patients with available data at three specific time-points-classification as K+-channel variant, 2-year follow-up and most recent visit-the longitudinal course was evaluated in addition to the cross-sectional examination.
CRIS-Team WoS Importer:2022-08-05

Clustering of genomic breakpoints at the MLL locus in therapy-related acute leukemia with t(4;11)(q21;q23) - Hasan, Syed Khizer; Barba, Gianluca; Metzler, Markus; Divona, Mariadomenica; Ottone, Tiziana; Cicconi, Laura; Falini, Brunangelo; Mecucci, Cristina; Lo-Coco, Francesco (Genes Chromosomes & Cancer, 2014)
Genomic characterization of translocation breakpoints is relevant to identify possible mechanisms underlying their origin. The consistent association of anthracylines (e.g., epirubicin and idarubicin) in inducing therapy-related acute leukemias (t-AL) with mixed lineage leukemia (MLL) gene rearrangement suggests that MLL translocations are causative events for t-AL. Using asymmetric multiplex PCR strategy followed by direct DNA sequencing, we characterized the genomic breakpoints of the MLL and AFF1 genes in two patients who developed t-AL with t(4;11)(q21;q23). Chemotherapeutic treatment of the primary disease in both patients included topoisomerase II (topo II) targeting agents. In one case, the MLL breakpoint was located in intron 9 at nucleotide position chr11:118354284 while the AFF1 breakpoint was in intron 3 at nucleotide position chr4:87992070. The breakpoint junction sequences revealed an insertion of two nucleotides at the MLL-AFF1 junction. In the other patient, the MLL breakpoint was located in intron 11 at nucleotide position chr11:118359130-32 and the AFF1 break was in intron 3 at nucleotide position chr4:87996215-17. The MLL breakpoint found in the latter patient was identical to that of two previously reported cases, strongly suggesting the presence of a preferential site of DNA cleavage in the presence of topo II inhibitor. In addition, microhomologies at the breakpoint junctions were indicative of DNA repair by the non-homologous end joining (NHEJ) pathway. This study further supports the evidence that MLL breakpoints in therapy-related acute leukemia with MLL-AFF1 are clustered in the telomeric half of the breakpoint cluster region that contains topo II recognition sites.
EVALuna2:18880

Collaborative evaluation study on 18 candidate diseases for newborn screening in 1.77 million samples - Maier, Esther M.; Mütze, Ulrike; Janzen, Nils; Steuerwald, Ulrike; Nennstiel, Uta; Odenwald, Birgit; Schuhmann, Elfriede; Lotz-Havla, Amelie S.; Weiss, Katharina J.; Hammersen, Johanna; Weigel, Corina; Thimm, Eva; et al. (Journal of Inherited Metabolic Disease, 2023)
Analytical and therapeutic innovations led to a continuous but variable extension of newborn screening (NBS) programmes worldwide. Every extension requires a careful evaluation of feasibility, diagnostic (process) quality and possible health benefits to balance benefits and limitations. The aim of this study was to evaluate the suitability of 18 candidate diseases for inclusion in NBS programmes. Utilising tandem mass spectrometry as well as establishing specific diagnostic pathways with second-tier analyses, three German NBS centres designed and conducted an evaluation study for 18 candidate diseases, all of them inherited metabolic diseases. In total, 1 777 264 NBS samples were analysed. Overall, 441 positive NBS results were reported resulting in 68 confirmed diagnoses, 373 false-positive cases and an estimated cumulative prevalence of approximately 1 in 26 000 newborns. The positive predictive value ranged from 0.07 (carnitine transporter defect) to 0.67 (HMG-CoA lyase deficiency). Three individuals were missed and 14 individuals (21%) developed symptoms before the positive NBS results were reported. The majority of tested candidate diseases were found to be suitable for inclusion in NBS programmes, while multiple acyl-CoA dehydrogenase deficiency, isolated methylmalonic acidurias, propionic acidemia and malonyl-CoA decarboxylase deficiency showed some and carnitine transporter defect significant limitations. Evaluation studies are an important tool to assess the potential benefits and limitations of expanding NBS programmes to new diseases.
CRIS-Team Scopus Importer:2023-09-22
Keywords: dried blood spot; evaluation study; Germany; inborn errors of metabolism; newborn screening; public health; tandem mass spectrometry

Common variants increase risk for congenital diaphragmatic hernia within the context of de novo variants - Qiao, Lu; Welch, Carrie L.; Hernan, Rebecca; Wynn, Julia; Krishnan, Usha S.; Zalieckas, Jill M.; Buchmiller, Terry; Khlevner, Julie; De, Aliva; Farkouh-Karoleski, Christiana; Wagner, Amy J.; Heydweiller, Andreas; et al. (American Journal of Human Genetics, 2024)
Congenital diaphragmatic hernia (CDH) is a severe congenital anomaly often accompanied by other structural anomalies and/or neurobehavioral manifestations. Rare de novo protein-coding variants and copy-number variations contribute to CDH in the population. However, most individuals with CDH remain genetically undiagnosed. Here, we perform integrated de novo and common-variant analyses using 1,469 CDH individuals, including 1,064 child-parent trios and 6,133 ancestry-matched, unaffected controls for the genome-wide association study. We identify candidate CDH variants in 15 genes, including eight novel genes, through deleterious de novo variants. We further identify two genomic loci contributing to CDH risk through common variants with similar effect sizes among Europeans and Latinx. Both loci are in putative transcriptional regulatory regions of developmental patterning genes. Estimated heritability in common variants is ∼19%. Strikingly, there is no significant difference in estimated polygenic risk scores between isolated and complex CDH or between individuals harboring deleterious de novo variants and individuals without these variants. The data support a polygenic model as part of the CDH genetic architecture.
CRIS-Team Scopus Importer:2024-11-08
Keywords: common variants; congenital diaphragmatic hernia; de novo variants; genome-wide association study; single-nucleotide polymorphism; WNT5A

Comparable Cerebral Blood Flow in Both Hemispheres During Regional Cerebral Perfusion in Infant Aortic Arch Surgery - Rueffer, Andre; Tischer, Philip; Münch, Frank; Purbojo, Ariawan; Toka, Okan; Rascher, Wolfgang; Cesnjevar, Robert; Juengert, Joerg (Annals of Thoracic Surgery, 2017)
Cerebral protection during aortic arch repair can be provided by regional cerebral perfusion (RCP) through the innominate artery. This study addresses the question of an adequate bilateral blood flow in both hemispheres during RCP.Fourteen infants (median age 11 days [range, 3 to 108]; median weight, 3.6 kg [range, 2.8 to 6.0 kg]) undergoing RCP (flow rate 54 to 60 mL · kg(-1) · min(-1)) were prospectively included. Using combined transfontanellar/transtemporal two- and three-dimensional power/color Doppler sonography, cerebral blood flow intensity in the main cerebral vessels was displayed. Mean time average velocities were measured with combined pulse-wave Doppler in the basilar artery, and both sides of the internal carotid, anterior, and medial cerebral arteries. In addition, bifrontal regional cerebral oximetry (rSO2) was assessed. Comparing both hemispheres, measurements were performed at target temperature (28°C) during full-flow total body perfusion (TBP) and RCP.A regular circle of Willis with near-symmetric blood flow intensity to both hemispheres was visualized in all infants during both RCP and TBP. In the left internal carotid artery, blood flow direction was mixed (retrograde, n = 5; antegrade, n = 8) during TBP and retrograde during RCP. Comparison between sides showed comparable cerebral time average velocities and rSO2, except for higher time average velocities in the right internal carotid artery (TBP p = 0.019, RCP p = 0.09). Unilateral comparison between perfusion methods revealed significantly higher rSO2 in the right hemisphere during TBP (82% ± 9%) compared with RCP (74% ± 11%, p = 0.036).Bilateral assessment of cerebral rSO2 and time average velocity in the main great cerebral vessels suggests that RCP is associated with near-symmetric blood flow intensity to both hemispheres. Further neurodevelopmental studies are necessary to verify RCP for neuroprotection during aortic arch repair.
EVALuna2:25812

Comparative Socioeconomic Study Of Patients In Germany With Dravet Syndrome, Refractory Epilepsy Or Epilepsy In Seizure Remission, And Their Caregivers - Strzelczyk, A.; Schubert-Bast, S.; Bast, T.; Bettendorf, U.; Hamer, Hajo; Herting, A.; Kalski, M.; Kay, L.; Kieslich, M.; Klein, K. M.; Kluger, G.; Kurlemann, G.; et al. (EPILEPSIA, 2019)
CRIS-Team WoS Importer:2019-11-15

Compound heterozygous RYR1 mutations in a preterm with arthrogryposis multiplex congenita and prenatal CNS bleeding - Brackmann, Florian; Türk, Matthias; Gratzki, Nils; Rompel, Oliver; Jungbluth, Heinz; Schröder, Rolf; Trollmann, Regina (Neuromuscular Disorders, 2018)
RYR1 mutations, the most common cause of non-dystrophic neuromuscular disorders, are associated with the malignant hyperthermia susceptibility (MHS) trait as well as congenital myopathies with widely variable clinical and histopathological manifestations. Recently, bleeding anomalies have been reported in association with certain RYR1 mutations. Here we report a preterm infant born at 32 weeks gestation with arthrogryposis multiplex congenita due to compound heterozygous, previously MHS-associated RYR1 mutations, with additional signs of prenatal hemorrhage. The patient presented at birth with multiple joint contractures, scoliosis, severe thoracic rigidity and respiratory failure. He continued to depend on mechanical ventilation and tube feeding. Muscle histopathology showed a marked myopathic pattern with eccentric cores. Interestingly, the patient had additional unusual prenatal intraventricular hemorrhage, resulting in post-hemorrhagic hydrocephalus as well as epidural hemorrhage affecting the spinal cord. This report adds to the phenotypic variability associated with RYR1 mutations, and highlights possible bleeding complications in affected individuals.
EVALuna2:34599

Comprehensive assessments and related interventions to enhance the long-term outcomes of child, adolescent and young adult cancer survivors - presentation of the CARE for CAYA-Program study protocol and associated literature review - Salchow, J.; Mann, J.; Koch, B.; von Grundherr, J.; Jensen, W.; Elmers, S.; Straub, L. A.; Vettorazzi, E.; Escherich, G.; Rutkowski, S.; Dwinger, S.; Bergelt, C.; et al. (BMC Cancer, 2020)
BACKGROUND: Improved, multimodal treatment strategies have been shown to increase cure rates in cancer patients. Those who survive cancer as a child, adolescent or young adult (CAYA), are at a higher risk for therapy-, or disease-related, late or long-term effects. The CARE for CAYA-Program has been developed to comprehensively assess any potential future problems, to offer need-based preventative interventions and thus to improve long-term outcomes in this particularly vulnerable population. METHODS: The trial is designed as an adaptive trial with an annual comprehensive assessment followed by needs stratified, modular interventions, currently including physical activity, nutrition and psycho-oncology, all aimed at improving the lifestyle and/or the psychosocial situation of the patients. Patients, aged 15-39 years old, with a prior cancer diagnosis, who have completed tumour therapy and are in follow-up care, and who are tumour free, will be included. At baseline (and subsequently on an annual basis) the current medical and psychosocial situation and lifestyle of the participants will be assessed using a survey compiled of various validated questionnaires (e.g. EORTC QLQ C30, NCCN distress thermometer, PHQ-4, BSA, nutrition protocol) and objective parameters (e.g. BMI, WHR, co-morbidities like hyperlipidaemia, hypertension, diabetes), followed by basic care (psychological and lifestyle consultation). Depending on their needs, CAYAs will be allocated to preventative interventions in the above-mentioned modules over a 12-month period. After 1 year, the assessment will be repeated, and further interventions may be applied as needed. During the initial trial phase, the efficacy of this approach will be compared to standard care (waiting list with intervention in the following year) in a randomized study. During this phase, 530 CAYAs will be included and 320 eligible CAYAs who are willing to participate in the interventions will be randomly allocated to an intervention. Overall, 1500 CAYAs will be included and assessed. The programme is financed by the innovation fund of the German Federal Joint Committee and will be conducted at 14 German sites. Recruitment began in January 2018. DISCUSSION: CAYAs are at high risk for long-term sequelae. Providing structured interventions to improve lifestyle and psychological situation may counteract against these risk factors. The programme serves to establish uniform regular comprehensive assessments and need-based interventions to improve long-term outcome in CAYA survivors. TRIAL REGISTRATION: Registered at the German Clinical Trial Register (ID: DRKS00012504, registration date: 19th January 2018).
CRIS-Team Scopus Importer:2020-01-21
Keywords: AYA; CAYA; Children adolescents and young adults after cancer; Follow-up care; Lifestyle intervention; Long-term side effects; Long-term toxicity; Prevention programme

Comprehensive bone marrow analysis integrating deep learning-based pattern discovery (BMDeep) - Pontones, Martina; Hoefener, H.; Kock, F.; Schwen, L.; Westphal, M.; Dickel, Nicholas; Kunz, Meik; Metzler, Markus (KLINISCHE PADIATRIE, 2022)
Bone marrow morphology forms the basis for the assessment of hematopoiesis. The currently established approach is dependent on manual microscopic counting of a limited number of cells by specially trained personnel, which is inherently associated with substantial intra- and inter-individual variability. The aim of our project is to automatize and improve the evaluation of bone marrow smears and to identify pathological patterns in pediatric leukemia.<br
CRIS-Team WoS Importer:2022-07-08

Computed Tomography-Guided Wire-Marking for Thoracoscopic Resection of Small Lung Nodules in Children - Seitz, Sigurd T.; Schellerer, Vera; Schmid, Axel; Metzler, Markus; Besendörfer, Manuel (Journal of Laparoendoscopic & Advanced Surgical Techniques, 2019)
Introduction: In pediatric patients, thoracoscopic wedge-resection of pulmonary nodules is an established therapy. However, intraoperative localization of small lesions is still challenging. Purpose of this study was to evaluate the efficacy of preoperative computed tomography (CT)-guided wire-marking of small lung nodules. Materials and Methods: Between 2012 and 2017 a total of six cases receiving thoracoscopic resection of CT-marked lung nodules were analyzed. The nodules were preoperatively tagged by a wire, which was attached to the thoracic wall by sterile dressing. Characteristics of interest were stability of wire, complete resection, and prevention of open thoracotomy. Results: Six procedures were performed on five patients, including four men and one woman. Median age at intervention was 16 years (range 11-19 years). All patients had a history of primary malignancies, including osteosarcoma (n = 4) and synovial sarcoma (n = 1). A total of 10 nodules were visualized in CT of which 9 were marked by wire. The median expected size of nodules was 6 mm (range 2-23 mm). Two patients had bilateral, two left-sided and two right-sided lung lesions. There was no wire slippage. In five procedures wedge resection was possible; one case needed a near total lobe resection. In one case a mini-thoracotomy at port insertion site was performed to extract the specimen. There was no conversion to thoracotomy. Histopathology showed R0 resection in all patients. Malignancy was found in all specimens. In one patient postoperative hemorrhagic anemia necessitated transfusion. Conclusions: Preoperative wire-localization of small lung nodules is a safe and effective tool to enable thoracoscopic resection in children and to avoid thoracotomic interventions.
CRIS-Team WoS Importer:2019-04-18

Conditional Alox12b Knockout: Degradation of the Corneocyte Lipid Envelope in a Mouse Model of Autosomal Recessive Congenital Ichthyoses - Krieg, P.; Dick, Angela; Latzko, Susanne; Rosenberger, Sabine; Meyer, J.; Crumrine, D.; Hielscher, Thomas; Elias, Peter M.; Rauh, Manfred; Schneider, Holm (Journal of Investigative Dermatology, 2019)
CRIS-Team Scopus Importer:2019-09-17

Congenital Nail Disorders among Children with Suspected Ectodermal Dysplasias - Maier-Wohlfart, Sigrun; Aicher, Carmen; Willershausen, Ines; Peschel, Nicolai; Meißner, Udo; Gölz, Lina; Schneider, Holm (Genes, 2022)
We report on a cohort of 204 children referred between January 2017 and January 2022 to the German Center for Ectodermal Dysplasias, Erlangen. The most frequent reasons for referral were tooth malformations and lack of multiple teeth leading to the suspicion of an ectodermal dysplasia. Many patients also suffered from being unable to perspire. Nail abnormalities, in contrast, represented a much rarer finding, albeit the impact on some individuals was large. As ectodermal dysplasias are congenital genetic conditions affecting the development and/or homeostasis of two or more ectodermal derivatives, including hair, teeth, nails, and certain glands, we analyzed congenital nail disorders detected in these patients. Dystrophic or otherwise abnormal nails were evident in 17 of 18 subjects with pathogenic WNT10A or GJB6 variants but in none of 161 children with EDA variants underlying X-linked hypohidrotic ectodermal dysplasia. However, 2 of 17 children who carry mutations in EDAR or EDARADD, two other genes involved in the ectodysplasin A signaling pathway, showed nail abnormalities, such as brittle or hypoplastic nails. TP63 variants were regularly associated with nail disorders. In one girl, anonychia congenita caused by a compound heterozygous variant of the R-spondin-4 gene (RSPO4) was diagnosed. Thus, nail dysplasia is rarer among patients with ectodermal dysplasia than commonly thought.
CRIS-Team Scopus Importer:2022-12-09
Keywords: anonychia/hyponychia congenita; congenital nail disorders; ectodermal dysplasia; R-spondin 4 (RSPO4)

Consider further differential diagnoses - Schneider, Holm (Deutsches Ärzteblatt international, 2014)
EVALuna2:18897

CONTINUOUS GLUCOSE MONITORING IN CSII THERAPY IN DIFFERENT AGE GROUPS (0.5- - Van Den Boom, L.; Auzanneau, M.; Wölfle, Joachim; Sindichakis, M.; Herbst, A.; Meraner, D.; Hake, K.; Klinkert, C.; Gohlke, B.; Holl, R. (DIABETES TECHNOLOGY & THERAPEUTICS, 2022)
CRIS-Team WoS Importer:2022-05-20

Continuous monitoring of SARS-CoV-2 seroprevalence in children using residual blood samples from routine clinical chemistry - Wachter, Felix; Regensburger, Adrian; Peter, Antonia Sophia; Knieling, Ferdinand; Wagner, Alexandra; Simon, David; Hörning, André; Wölfle, Joachim; Überla, Klaus; Neubert, Antje; Rauh, Manfred (Clinical Chemistry and Laboratory Medicine, 2022)
Objectives The assessment of SARS-CoV-2 infections in children is still challenging, but essential for appropriate political decisions. The aim of this study was to investigate whether residual blood samples can be used for SARS-CoV-2 seroprevalence monitoring in pediatrics. Methods In this repeated cross-sectional cohort study, anonymous residual blood samples from pediatric patients aged 0-17 years were collected in three time-periods (Oct.-Nov. 2020, April 2021, and June-July 2021) and analyzed for SARS-CoV-2 Spike protein (anti-S) and nucleocapsid (anti-N) antibodies using commercial antibody assays. 28 reactive samples were used to compare antibody levels with a pseudotyped neutralization assay. The results were further compared to the official national COVID-19 surveillance data to calculate the number of unreported cases. Results In total, n=2,626 individual blood samples were analyzed. In this unvaccinated pediatric cohort anti-S and anti-N antibody seroprevalence increased over the three time periods (anti-S: 1.38-9.16%, and 14.59%; anti-N: 1.26%, to 6.19%, and 8.56%). Compared to the national surveillance data this leads to a 3.93-5.66-fold increase in the number of unreported cases. However, a correlation between the cumulative incidence of the individual provinces and our assigned data was found (r=0.74, p=0.0151). In addition, reactive samples with anti-S and anti-N and samples with only anti-S showed neutralization capabilities (11/14 and 8/14, respectively). Anti-S levels were not significantly different between age groups and sexes (all p>0.05). Conclusions The present study suggests that residual blood samples from routine laboratory chemistry could be included in the estimation of the total SARS-CoV-2 seroprevalence in children.
CRIS-Team WoS Importer:2022-03-11
Keywords: COVID-19; pediatrics; prevalence; SARS-CoV-2

Continuous therapy response references for BCR::ABL1 monitoring in pediatric chronic myeloid leukemia - Volz, Christian; Zerjatke, Thomas; Gottschalk, Andrea; Semper, Sabine; Suttorp, Meinolf; Glauche, Ingmar; Krumbholz, Manuela; Metzler, Markus (Scientific Reports, 2023)
Response to tyrosine kinase inhibitor (TKI) therapy in patients with chronic myeloid leukemia (CML) is monitored by quantification of BCR::ABL1 transcript levels. Milestones for assessing optimal treatment response have been defined in adult CML patients and are applied to children and adolescents although it is questionable whether transferability to pediatric patients is appropriate regarding genetic and clinical differences. Therefore, we analyzed the molecular response kinetics to TKI therapy in 129 pediatric CML patients and investigated whether response assessment based on continuous references can support an early individual therapy adjustment. We applied a moving quantiles approach to establish a high-resolution response target curve and contrasted the median responses in all patients with the median of the ideal target curve obtained from a subgroup of optimal responders. The high-resolution response target curve of the optimal responder group presents a valuable tool for continuous therapy monitoring of individual pediatric CML patients in addition to the fixed milestones. By further comparing BCR::ABL1 transcript levels with BCR::ABL1 fusion gene copy numbers, it is also possible to model the differential dynamics of BCR::ABL1 expression and cell number under therapy. The developed methodology can be transferred to other biomarkers for continuous therapy monitoring.
CRIS-Team Scopus Importer:2023-11-03

Contrast-Enhanced Multispectral Optoacoustic Tomography for Functional Assessment of the Gastrointestinal Tract - Paulus, Lars-Philip; Bühler, Adrian; Wagner, Alexandra; Raming, Roman; Jüngert, Jörg; Simon, David; Tascilar, Koray; Schnell, Alexander; Rother, Ulrich; Eckstein, Markus; Lang, Werner; Hörning, André; et al. (Advanced Science, 2023)
Real-time imaging and functional assessment of the intestinal tract and its transit pose a significant challenge to conventional clinical diagnostic methods. Multispectral optoacoustic tomography (MSOT), a molecular-sensitive imaging technology, offers the potential to visualize endogenous and exogenous chromophores in deep tissue. Herein, a novel approach using the orally administered clinical-approved fluorescent dye indocyanine green (ICG) for bedside, non-ionizing evaluation of gastrointestinal passage is presented. The authors are able to show the detectability and stability of ICG in phantom experiments. Furthermore, ten healthy subjects underwent MSOT imaging at multiple time points over eight hours after ingestion of a standardized meal with and without ICG. ICG signals can be visualized and quantified in different intestinal segments, while its excretion is confirmed by fluorescent imaging of stool samples. These findings indicate that contrast-enhanced MSOT (CE-MSOT) provides a translatable real-time imaging approach for functional assessment of the gastrointestinal tract.
CRIS-Team Scopus Importer:2023-06-30
Keywords: indocyanine green; intestine; multispectral optoacoustic tomography; optoacoustics; photoacoustics

Contribution of the ?8 integrin chain to the expression of extracellular matrix components - Volkert, Gudrun; Jahn, Angelika; Dinkel, Christina; Fahlbusch, Fabian; Zuern, Christina; Hilgers, Karl Friedrich; Rascher, Wolfgang; Marek, Ines; Hartner, Andrea (Cell Communication and Adhesion, 2014)
In the kidney, the ?8 integrin chain (itga8) is expressed in mesenchymal cells and is upregulated in fibrotic disease. We hypothesized that itga8 mediates a profibrotic phenotype of renal cells by promoting extracellular matrix and cytokine expression. Genetic itga8 deficiency caused complex changes in matrix expression patterns in mesangial and smooth-muscle cells, with the only concordant effect in both cell types being a reduction of collagen III expression. Silencing of itga8 with siRNA led to a decline of matrix turnover with repression of matrix metalloproteinases and reduction of matrix production. In contrast, de novo expression of itga8 in tubular epithelial cells resulted in reduced collagen synthesis. Overexpression of itga8 in fibroblasts did not change the expression of matrix molecules or regulators of matrix turnover. Thus, the influence of itga8 on the expression of matrix components was not uniform and celltype dependent. Itga8 seems unlikely to exert overall profibrotic effects in renal cells.
EVALuna2:3701

Correction of Vertebral Bone Development in Ectodysplasin A1-Deficient Mice by Prenatal Treatment With a Replacement Protein - Kossel, Clara-Sophie; Wahlbuhl-Becker, Mandy; Schuepbach-Mallepell, Sonia; Park, Jung; Kowalczyk-Quintas, Christine; Seeling, Michaela; von der Mark, Klaus; Schneider, Pascal; Schneider, Holm (Frontiers in Genetics, 2021)
X-linked hypohidrotic ectodermal dysplasia with the cardinal symptoms hypodontia, hypotrichosis and hypohidrosis is caused by a genetic deficiency of ectodysplasin A1 (EDA1). Prenatal EDA1 replacement can rescue the development of skin appendages and teeth. Tabby mice, a natural animal model of EDA1 deficiency, additionally feature a striking kink of the tail, the cause of which has remained unclear. We studied the origin of this phenomenon and its response to prenatal therapy. Alterations in the distal spine could be noticed soon after birth, and kinks were present in all Tabby mice by the age of 4 months. Although their vertebral bones frequently had a disorganized epiphyseal zone possibly predisposing to fractures, cortical bone density was only reduced in vertebrae of older Tabby mice and even increased in their tibiae. Different availability of osteoclasts in the spine, which may affect bone density, was ruled out by osteoclast staining. The absence of hair follicles, a well-known niche of epidermal stem cells, and much lower bromodeoxyuridine uptake in the tail skin of 9-day-old Tabby mice rather suggest the kink being due to a skin proliferation defect that prevents the skin from growing as fast as the skeleton, so that caudal vertebrae may be squeezed and bent by a lack of skin. Early postnatal treatment with EDA1 leading to delayed hair follicle formation attenuated the kink, but did not prevent it. Tabby mice born after prenatal administration of EDA1, however, showed normal tail skin proliferation, no signs of kinking and, interestingly, a normalized vertebral bone density. Thus, our data prove the causal relationship between EDA1 deficiency and kinky tails and indicate that hair follicles are required for murine tail skin to grow fast enough. Disturbed bone development appears to be partially pre-determined in utero and can be counteracted by timely EDA1 replacement, pointing to a role of EDA1 also in osteogenesis.
CRIS-Team Scopus Importer:2021-09-10
Keywords: bone; development; ectodermal dysplasia; ectodysplasin A1; fetal therapy; NF-κB

Correction to: Assessment of treatment responses in children and adolescents with Ewing sarcoma with metabolic tumor parameters derived from 18F-FDG-PET/CT and circulating tumor DNA (European Journal of Nuclear Medicine and Molecular Imaging, (2019), 10.1007/s00259-019-04649-1) - Schmidkonz, Christian; Krumbholz, Manuela; Atzinger, Armin; Cordes, Michael; Götz, Theresa; Prante, Olaf; Ritt, Philipp; Schaefer, Christiane; Agaimy, Abbas; Hartmann, Wolfgang; Roessig, Claudia; Froehlich, Birgit; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2020)
The original version on this paper contained an error. The author names, though correctly appeared in the PDF version, were incorrectly displayed in indexing sites. This error occurred because of the incorrect tagging of their names in themetadata of this article. The purpose of this Erratum is the correction of metadata. Therefore, indexing sites should now reflect their names as Schmidkonz C, Krumbholz M, Atzinger A, Cordes M, Goetz TI, Prante O, Ritt P, Schaefer C, Agaimy A, Hartmann W, Rössig C, Fröhlich B, Bäuerle T, Dirksen U, Kuwert T, Metzler M. The original article has been corrected.
CRIS-Team Scopus Importer:2020-02-25

Correction to: Short-term safety results from compassionate use of risdiplam in patients with spinal muscular atrophy in Germany (Orphanet Journal of Rare Diseases, (2022), 17, 1, (276), 10.1186/s13023-022-02420-8) - Hahn, Andreas; Günther, René; Ludolph, Albert; Schwartz, Oliver; Trollmann, Regina; Weydt, Patrick; Weiler, Markus; Neuland, Kathrin; Schwaderer, Martin Sebastian; Hagenacker, Tim (Orphanet Journal of Rare Diseases, 2022)
Following publication of the original article [1], we have been notified that there is a typographical error in the Fig. 1 text. It should be as per below: Figure 1: “111 patients received ≥ 1 risdiplam dose.
CRIS-Team Scopus Importer:2022-11-04

Corrigendum: Patient-reported long-term outcome following allogeneic hematopoietic stem cell transplantation in pediatric chronic myeloid leukemia. - Schleicher, Oliver; Horndasch, Annkathrin; Krumbholz, Manuela; Sembill, Stephanie; Bremensdorfer, Claudia; Grabow, Desiree; Erdmann, Friederike; Karow, Axel; Metzler, Markus; Suttorp, Meinolf (Frontiers in Oncology, 2022)
[This corrects the article DOI: 10.3389/fonc.2022.963223.].
EVALuna2:517750

Course of renal allograft function after diagnosis and treatment of post-transplant lymphoproliferative disorders in pediatric kidney transplant recipients - Zierhut, Henriette; Kanzelmeyer, Nele; Buescher, Anja; Hoecker, Britta; Mauz-Korholz, Christine; Tonshoff, Burkhard; Metzler, Markus; Pohl, Martin; Pape, Lars; Maecker-Kolhoff, Britta (Pediatric Transplantation, 2021)
Background Post-transplant lymphoproliferative disease (PTLD) is a life-threatening complication in renal transplant recipients. Immunomodulatory and chemotherapeutic treatment potentially affect allograft function. The aim of this study was to evaluate graft function of pediatric kidney transplant recipients following diagnosis and standardized treatment of PTLD.
CRIS-Team WoS Importer:2021-05-28

COVID-19 and increased prevalence of female precocious puberty in Germany - Baehr, Sonja; Schnabel, Dirk; Wölfle, Joachim; Schreiner, Felix; Gohlke, Bettina (HORMONE RESEARCH IN PAEDIATRICS, 2022)
CRIS-Team WoS Importer:2022-10-07

Critical incidents, nocturnal supervision, and caregiver knowledge on SUDEP in patients with Dravet syndrome: A prospective multicenter study in Germany - Maltseva, Margarita; Rosenow, Felix; Schubert-Bast, Susanne; Flege, Silke; Wolff, Markus; von Spiczak, Sarah; Trollmann, Regina; Syrbe, Steffen; Ruf, Susanne; Polster, Tilman; Neubauer, Bernd A.; Mayer, Thomas; et al. (Epilepsia, 2023)
Objective: The aim was to investigate the monitoring, interventions, and occurrence of critical, potentially life-threatening incidents in patients with Dravet syndrome (DS) and caregivers’ knowledge about sudden unexpected death in epilepsy (SUDEP). Methods: This multicenter, cross-sectional study of patients with DS and their caregivers in Germany consisted of a questionnaire and prospective diary querying the disease characteristics and demographic data of patients and caregivers. Results: Our analysis included 108 questionnaires and 82 diaries. Patients with DS were 49.1% male (n = 53), with a mean age of 13.5 (SD ± 10.0 years) and primary caregivers were 92.6% (n = 100) female, with a mean age of 44.7 (SD ± 10.6 years). Monitoring devices were used regularly by 75.9% (n = 82) of caregivers, and most monitored daily/nightly. Frequently used devices were pulse oximeters (64.6%), baby monitors (64.6%), thermometers (24.1%), and Epi-Care (26.8%). Younger caregiver and patient age and history of status epilepticus were associated with increased use of monitoring, and 81% of monitor users reported having avoided a critical incident with nocturnal monitoring. The need for resuscitation due to cardiac or respiratory arrest was reported by 22 caregivers (20.4%), and most cases (72.7%) were associated with a seizure. Caregivers reported frequently performing interventions at night, including oropharyngeal suction, oxygenation, personal hygiene, and change of body position. Most caregivers were well informed about SUDEP (n = 102; 94%) and monitored for a lateral or supine body position; however, only 39.8% reported receiving resuscitation training, whereas 52.8% (n = 57) knew what to do in case the child's breathing or heart activity failed. Significance: Critical incidents and the need for resuscitation are reported frequently by caregivers and may be related to high mortality and SUDEP rates in DS. Resuscitation training is welcomed by caregivers and should be continuously provided. Oxygen monitoring devices are frequently used and considered useful by caregivers.
CRIS-Team Scopus Importer:2023-11-24
Keywords: encephalopathy; epilepsy; near-SUDEP; seizure

CtDNA release mechanisms in a therapeutic Ewing Sarcoma mouse model - Eiblwieser, Johanna; Krumbholz, Manuela; Semper, S.; Frey, Benjamin; Nagel, L.; Bäuerle, Tobias; Metzler, Markus (KLINISCHE PADIATRIE, 2022)
CRIS-Team WoS Importer:2022-07-08

Cullin 7 and Fbxw 8 expression in trophoblastic cells is regulated via oxygen tension: Implications for intrauterine growth restriction - Fahlbusch, Fabian; Dawood, Yousif Louay; Hartner, Andrea; Menendez-Castro, Carlos; Nögel, Stephanie; Tzschoppe, Anja; Schneider, Holm; Strissel, Pamela; Beckmann, Matthias; Schleussner, Ekkehard; Rübner, Matthias; Dörr, Helmuth-Günther; et al. (Journal of Maternal-Fetal & Neonatal Medicine, 2012)
Objective: The F-box protein Fbxw8 is a cofactor of Cullin 7 (Cul7), which regulates protein transfer to the proteasome and cell growth. Cul7 or Fbxw8 deficiency is associated with intrauterine growth restriction (IUGR) due to abnormal placental development leading to poor oxygen supply to the fetus. We studied the role of hypoxia for Fbxw8 and Cul7 expression in trophoblastic cells. Methods: Immunomagnetic bead-separated extravillous trophoblast (EVT) and villous trophoblast (VT) and trophoblast cell lines were incubated with 1 or 8% O2. Fbxw8 and Cul7 expression was determined in IUGR versus matched control placentas. Results: Fbxw8 was expressed uniformly in trophoblasts, whereas Cul7 expression was most prominent in trophoblast cell lines. Hypoxia reduced expression of Cul7 and Fbxw8 in all trophoblastic cells, except for villous trophoblasts. In vivo, Cul7 and Fbxw8 were detected in syncytiotrophoblast cells, VT, and EVT cells. Although no significant changes in expression levels of Fbxw8 or Cul7 were noted in IUGR compared with control placentas, Fbxw8 expression correlated negatively with gestational age in the control, but not in the IUGR group. Conclusion: Fbxw8 and Cul7 expression reveals a complex regulation in trophoblastic cells. Our findings suggest that dysregulation of Cul7 and Fbxw8 expression might affect trophoblast turnover in IUGR. © 2012 Informa UK, Ltd.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Cul7; Fbxw8; IUGR; Oxygen; Placenta; Trophoblast

Current clinical practice of prenatal dexamethasone treatment in at risk pregnancies for classic 21-hydroxylase deficiency in Europe - Nowotny, Hanna F.; Neumann, Uta; Tardy-Guidollet, Veronique; Ahmed, S. Faisal; Baronio, Federico; Battelino, Tadej; Bertherat, Jerome; Blankenstein, Oliver; Bonomi, Marco; Bouvattier, Claire; De La Perriere, Aude Brac; Brucker, Sara; et al. (HORMONE RESEARCH IN PAEDIATRICS, 2021)
CRIS-Team WoS Importer:2021-10-08

Current Role of Monoclonal Antibody Therapy in Pediatric IBD: A Special Focus on Therapeutic Drug Monitoring and Treat-to-Target Strategies - Claßen, Merle; Hörning, André (Children, 2023)
In the last two decades, biologicals have become essential in treating children and adolescents with inflammatory bowel disease. TNF-α inhibitors (infliximab, adalimumab and golimumab) are preferentially used. Recent studies suggest that early application of TNF-α inhibitors is beneficial to inducing disease remission and preventing complications such as development of penetrating ulcers and fistulas. However, treatment failure occurs in about one third of pediatric patients. Particularly, children and adolescents differ in drug clearance, emphasizing the importance of pharmacokinetic drug monitoring in the pediatric setting. Here, current data on the choice and effectiveness of biologicals and therapeutic drug monitoring strategies are reviewed.
CRIS-Team Scopus Importer:2023-05-05
Keywords: biologics; Crohn’s disease; treatment optimization; trough levels; ulcerative colitis

CXCR4 blockade reduces the severity of murine heart allograft rejection by plasmacytoid dendritic cell-mediated immune regulation - Fu, Jian; Lehmann, Christian; Wang, Xinning; Wahlbuhl, Mandy; Allabauer, Ida; Wilde, Benjamin; Amon, Lukas; Dolff, Sebastian; Cesnjevar, Robert; Kribben, Andreas; Wölfle, Joachim; Rascher, Wolfgang; et al. (Scientific Reports, 2021)
Allograft-specific regulatory T cells (Treg cells) are crucial for long-term graft acceptance after transplantation. Although adoptive Treg cell transfer has been proposed, major challenges include graft-specificity and stability. Thus, there is an unmet need for the direct induction of graft-specific Treg cells. We hypothesized a synergism of the immunotolerogenic effects of rapamycin (mTOR inhibition) and plerixafor (CXCR4 antagonist) for Treg cell induction. Thus, we performed fully-mismatched heart transplantations and found combination treatment to result in prolonged allograft survival. Moreover, fibrosis and myocyte lesions were reduced. Although less CD3+ T cell infiltrated, higher Treg cell numbers were observed. Noteworthy, this was accompanied by a plerixafor-dependent plasmacytoid dendritic cells-(pDCs)-mobilization. Furthermore, in vivo pDC-depletion abrogated the plerixafor-mediated Treg cell number increase and reduced allograft survival. Our pharmacological approach allowed to increase Treg cell numbers due to pDC-mediated immune regulation. Therefore pDCs can be an attractive immunotherapeutic target in addition to plerixafor treatment.
CRIS-Team Scopus Importer:2021-12-24

Das nicht klassische adrenogenitale Syndrom mit 21-Hydroxylase-Defekt bei Kindern und Jugendlichen - Dörr, Helmuth-Günther; Schulze, Nadja (Pädiatrische Praxis, 2020)
Non-classical AGS with 21-hydroxylase defect is a common monogenetic disorder that is often not diagnosed or diagnosed too late. The leading clinical symptom in girls is the premature pubarche before the 8th birthday. For diagnostic purposes, 17-OHP should be measured in serum in the morning for children in the first step and in the follicular phase for menstruating girls. The gold standard in diagnostics is the ACTH test, whereby cortisol should also be determined in the serum in addition to 17-OHP. The laboratory chemical diagnosis should in any case be confirmed by molecular genetic analysis. Drug therapy in children with hydrocortisone is carried out in a low dose if the clinical symptoms are progressive and, above all, there is a poor prognosis of the final size due to the acceleration of bone age. If a therapy with glucocorticoids is carried out, then an emergency ID card should also be issued.
CRIS-Team Scopus Importer:2021-04-19
Keywords: 17-OHP; ACTH test; Cortisol; CYP21A2; Premature pubarche

Das nicht klassische Adrenogenitale Syndrom mit 21-Hydroxylase-Defekt bei Kindern und Jugendlichen - Dörr, Helmuth-Günther; Schulze, Nadja (gynäkologische praxis, 2021)
Non-classical AGS with 21-hydroxylase defect is a common monogenetic disorder that is often not diagnosed or diagnosed too late. The leading clinical symptom in girls is the premature pubarche before the 8th birthday. For diagnostic purposes, 17-OHP should be measured in serum in the morning for children in the first step and in the follicular phase for menstruating girls. The gold standard in diagnostics is the ACTH test, whereby cortisol should also be determined in the serum in addition to 17-OHP. The laboratory chemical diagnosis should in any case be confirmed by molecular genetic analysis. Drug therapy in children with hydrocortisone is carried out in a low dose if the clinical symptoms are progressive and, above all, there is a poor prognosis of the final size due to the acceleration of bone age. If a therapy with glucocorticoids is carried out, then an emergency ID card should also be issued.
CRIS-Team Scopus Importer:2024-12-16
Keywords: 17-OHP; ACTH test; cortisol; CYP21A2; premature pubarche

Data mining of pediatric reference intervals - Zierk, Jakob; Metzler, Markus; Rauh, Manfred (Journal of Laboratory Medicine, 2021)
Laboratory tests are essential to assess the health status and to guide patient care in individuals of all ages. The interpretation of quantitative test results requires availability of appropriate reference intervals, and reference intervals in children have to account for the extensive physiological dynamics with age in many biomarkers. Creation of reference intervals using conventional approaches requires the sampling of healthy individuals, which is opposed by ethical and practical considerations in children, due to the need for a large number of blood samples from healthy children of all ages, including neonates and young infants. This limits the availability and quality of pediatric reference intervals, and ultimately negatively impacts pediatric clinical decision-making. Data mining approaches use laboratory test results and clinical information from hospital information systems to create reference intervals. The extensive number of available test results from laboratory information systems and advanced statistical methods enable the creation of pediatric reference intervals with an unprecedented age-related accuracy for children of all ages. Ongoing developments regarding the availability and standardization of electronic medical records and of indirect statistical methods will further improve the benefit of data mining for pediatric reference intervals.
CRIS-Team Scopus Importer:2021-10-29
Keywords: data mining; indirect methods; pediatric reference intervals

Data mining of reference intervals for coagulation screening tests in adult patients - Zierk, Jakob; Ganslandt, Thomas; Rauh, Manfred; Metzler, Markus; Strasser, Erwin (Clinica Chimica Acta, 2019)
Background: Appropriate reference intervals are essential when evaluating laboratory test results. However, establishment of reference intervals is challenging, especially for coagulation screening tests, and uncertainty exists regarding age- and sex-dependency of test results. Data mining of laboratory information systems is an emerging approach to reference interval determination, and we evaluated its applicability to coagulation tests. Methods: We analyzed measurements of activated partial thromboplastin time (aPTT), prothrombin time (PT), international normalized ratio (INR), thrombin time (TT), and fibrinogen performed during clinical care in the University Hospital Erlangen, Germany (1,778,738 samples from 116,754 adult patients, 45,577-509,859 samples per analyte). We identified the proportion of samples from healthy individuals using an established statistical approach (Reference Limit Estimator), in which the distribution of physiological test results is approximated using a parametrical function, and used for the calculation of reference intervals. Results: We established age- and sex specific reference intervals for aPTT, PT, INR, TT, and fibrinogen, and created batch- and reagent-specific aPTT-reference intervals. Additionally, we evaluated the sensitivity of the established aPTT reference intervals for the detection of factor VIII, IX, XI, XII deficiencies. Conclusion: Data mining of laboratory test results allows the creation of age- and sex-reference intervals for coagulation tests that are specific to the examined population, analytical framework, and reagent. This approach can complement conventional methods when establishing reference intervals and improve clinical decision-making based on coagulation tests. The reference intervals established in this study show only minor variation with sex and age, supporting the practice of providing a common reference interval for adult women and men.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Coagulation screening tests; Data mining; Reference intervals

Deficiency of ECHS1 causes mitochondrial encephalopathy with cardiac involvement - Haack, Tobias B.; Jackson, Christopher B.; Murayama, Kei; Kremer, Laura S.; Schaller, Andre; Kotzaeridou, Urania; De Vries, Maaike C.; Schottmann, Gudrun; Santra, Saikat; Buechner, Boriana; Wieland, Thomas; Graf, Elisabeth; et al. (Annals of Clinical and Translational Neurology, 2015)
Short-chain enoyl-CoA hydratase (ECHS1) is a multifunctional mitochondrial matrix enzyme that is involved in the oxidation of fatty acids and essential amino acids such as valine. Here, we describe the broad phenotypic spectrum and pathobiochemistry of individuals with autosomal-recessive ECHS1 deficiency.Using exome sequencing, we identified ten unrelated individuals carrying compound heterozygous or homozygous mutations in ECHS1. Functional investigations in patient-derived fibroblast cell lines included immunoblotting, enzyme activity measurement, and a palmitate loading assay.Patients showed a heterogeneous phenotype with disease onset in the first year of life and course ranging from neonatal death to survival into adulthood. The most prominent clinical features were encephalopathy (10/10), deafness (9/9), epilepsy (6/9), optic atrophy (6/10), and cardiomyopathy (4/10). Serum lactate was elevated and brain magnetic resonance imaging showed white matter changes or a Leigh-like pattern resembling disorders of mitochondrial energy metabolism. Analysis of patients' fibroblast cell lines (6/10) provided further evidence for the pathogenicity of the respective mutations by showing reduced ECHS1 protein levels and reduced 2-enoyl-CoA hydratase activity. While serum acylcarnitine profiles were largely normal, in vitro palmitate loading of patient fibroblasts revealed increased butyrylcarnitine, unmasking the functional defect in mitochondrial ?-oxidation of short-chain fatty acids. Urinary excretion of 2-methyl-2,3-dihydroxybutyrate - a potential derivative of acryloyl-CoA in the valine catabolic pathway - was significantly increased, indicating impaired valine oxidation.In conclusion, we define the phenotypic spectrum of a new syndrome caused by ECHS1 deficiency. We speculate that both the ?-oxidation defect and the block in l-valine metabolism, with accumulation of toxic methacrylyl-CoA and acryloyl-CoA, contribute to the disorder that may be amenable to metabolic treatment approaches.
EVALuna2:18926

Deficiency of Fhl2 leads to delayed neuronal cell migration and premature astrocyte differentiation - Kim, Soung Yung; Ludwig, Stephan; Schneider, Holm; Wixler, Viktor; Park, Jung; Völkl, Simon (Journal of Cell Science, 2019)
The four and a half LIM domains protein 2 (Fhl2) is an adaptor protein capable of mediating protein-protein interactions. Here, we report for the first time phenotypic changes in the brain of Fhl2-deficient mice. We showed that Fhl2 is expressed in neural stem cells, precursors and mature cells of neuronal lineage. Moreover, Fhl2 deficiency leads to delayed neuroblast migration in vivo, premature astroglial differentiation of neural stem cells (NSCs) in vitro, and a gliosis-like accumulation of glial fibrillary acidic protein (GFAP)-positive astrocytes in vivo that substantially increases with age. Collectively, Fhl2-deficiency in the brain interrupts the maintenance and the balanced differentiation of adult NSCs, resulting in preferentially glial differentiation and early exhaustion of the NSC pool required for adult neurogenesis.
CRIS-Team WoS Importer:2019-04-12

Definition, diagnosis and clinical management of non-obstructive kidney dysplasia: a consensus statement by the ERKNet Working Group on Kidney Malformations - Kohl, Stefan; Avni, Fred E.; Boor, Peter; Capone, Valentina; Clapp, William L.; De Palma, Diego; Harris, Tess; Heidet, Laurence; Hilger, Alina Christine; Liapis, Helen; Lilien, Marc; Manzoni, Gianantonio; et al. (Nephrology Dialysis Transplantation, 2022)
Kidney dysplasia is one of the most frequent causes of chronic kidney failure in children. While dysplasia is a histological diagnosis, the term 'kidney dysplasia' is frequently used in daily clinical life without histopathological confirmation. Clinical parameters of kidney dysplasia have not been clearly defined, leading to imprecise communication amongst healthcare professionals and patients. This lack of consensus hampers precise disease understanding and the development of specific therapies. Based on a structured literature search, we here suggest a common basis for clinical, imaging, genetic, pathological and basic science aspects of non-obstructive kidney dysplasia associated with functional kidney impairment. We propose to accept hallmark sonographic findings as surrogate parameters defining a clinical diagnosis of dysplastic kidneys. We suggest differentiated clinical follow-up plans for children with kidney dysplasia and summarize established monogenic causes for non-obstructive kidney dysplasia. Finally, we point out and discuss research gaps in the field.
CRIS-Team WoS Importer:2022-09-16

Definition, epidemiology, pathophysiology, and essential criteria for diagnosis of pediatric chronic myeloid leukemia - Suttorp, Meinolf; Sembill, Stephanie; Deutsch, Hélène; Metzler, Markus; Millot, Frederic (Cancers, 2021)
Depending on the analytical tool applied, the hallmarks of chronic myeloid leukemia (CML) are the Philadelphia Chromosome and the resulting mRNA fusion transcript BCR-ABL1. With an incidence of 1 per 1 million of children this malignancy is very rare in the first 20 years of life. This article aims to; (i) define the disease based on the WHO nomenclature, the appropriate ICD 11 code and to unify the terminology, (ii) delineate features of epidemiology, etiology, and pathophysiology that are shared, but also differing between adult and pediatric patients with CML, iii) give a short summary on the diseases to be considered as a differential diagnosis of pediatric CML, (iv) to describe the morphological, histopathological and immunophenotypical findings of CML in pediatric patients, (v) illustrate rare but classical complications resulting from rheological problems observed at diagnosis, (vi) list essential and desirable diagnostic criteria, which hopefully in the future will help to unify the attempts when approaching this rare pediatric malignancy.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Diagnostic essential criteria; Epidemiology; Pathophysiology; Pediatric CML

Delineation of the clinical phenotype caused by de novo CLTC variants - Sa, M. J. Nabais; Venselaar, H.; Wiel, L.; Trimouille, A.; Lasseaux, E.; Naudion, S.; Lacombe, D.; Piton, A.; Vincent-Delorme, C.; Zweier, Christiane; Wiesmann da Silva Reis, André; Trollmann, Regina; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2019)
CRIS-Team WoS Importer:2019-10-25

De novo CLTC variants are associated with a variable phenotype from mild to severe intellectual disability, microcephaly, hypoplasia of the corpus callosum, and epilepsy - Nabais Sá, Maria J.; Venselaar, Hanka; Wiel, Laurens; Trimouille, Aurélien; Lasseaux, Eulalie; Naudion, Sophie; Lacombe, Didier; Piton, Amélie; Vincent-Delorme, Catherine; Zweier, Christiane; Reis, André; Trollmann, Regina; et al. (Genetics in Medicine, 2019)
Purpose: To delineate the genotype–phenotype correlation in individuals with likely pathogenic variants in the CLTC gene. Methods: We describe 13 individuals with de novo CLTC variants. Causality of variants was determined by using the tolerance landscape of CLTC and computer-assisted molecular modeling where applicable. Phenotypic abnormalities observed in the individuals identified with missense and in-frame variants were compared with those with nonsense or frameshift variants in CLTC. Results: All de novo variants were judged to be causal. Combining our data with that of 14 previously reported affected individuals (n = 27), all had intellectual disability (ID), ranging from mild to moderate/severe, with or without additional neurologic, behavioral, craniofacial, ophthalmologic, and gastrointestinal features. Microcephaly, hypoplasia of the corpus callosum, and epilepsy were more frequently observed in individuals with missense and in-frame variants than in those with nonsense and frameshift variants. However, this difference was not significant. Conclusions: The wide phenotypic variability associated with likely pathogenic CLTC variants seems to be associated with allelic heterogeneity. The detailed clinical characterization of a larger cohort of individuals with pathogenic CLTC variants is warranted to support the hypothesis that missense and in-frame variants exert a dominant-negative effect, whereas the nonsense and frameshift variants would result in haploinsufficiency.
CRIS-Team Scopus Importer:2019-12-10
Keywords: CLTC; intellectual disability; neurodevelopmental disorder

Detection of collagens by multispectral optoacoustic tomography as an imaging biomarker for Duchenne muscular dystrophy - Regensburger, Adrian; Fonteyne, Lina M.; Jüngert, Jörg; Wagner, Anna; Gerhalter, Teresa; Nagel, Armin Michael; Heiß, Rafael; Flenkenthaler, Florian; Qurashi, Matthias; Neurath, Markus; Klymiuk, Nikolai; Kemter, Elisabeth; et al. (Nature Medicine, 2019)
Biomarkers for monitoring of disease progression and response to therapy are lacking for muscle diseases such as Duchenne muscular dystrophy. Noninvasive in vivo molecular imaging with multispectral optoacoustic tomography (MSOT) uses pulsed laser light to induce acoustic pressure waves, enabling the visualization of endogenous chromophores. Here we describe an application of MSOT, in which illumination in the near- and extended near-infrared ranges from 680–1,100 nm enables the visualization and quantification of collagen content. We first demonstrated the feasibility of this approach to noninvasive quantification of tissue fibrosis in longitudinal studies in a large-animal Duchenne muscular dystrophy model in pigs, and then applied this approach to pediatric patients. MSOT-derived collagen content measurements in skeletal muscle were highly correlated to the functional status of the patients and provided additional information on molecular features as compared to magnetic resonance imaging. This study highlights the potential of MSOT imaging as a noninvasive, age-independent biomarker for the implementation and monitoring of newly developed therapies in muscular diseases.
CRIS-Team Scopus Importer:2019-12-17

Detection of expressional changes induced by intrauterine growth restriction in the developing rat mammary gland via exploratory pathways analysis - Beinder, Lea; Fährmann, Nina; Wachtveitl, Rainer; Winterfeld, Ilona; Hartner, Andrea; Menendez-Castro, Carlos; Rauh, Manfred; Ruebner, Matthias; Hübner, Hanna; Nögel, Stephanie; Dörr, Helmuth-Günther; Rascher, Wolfgang; et al. (PLoS ONE, 2014)
Intrauterine growth restriction (IUGR) is thought to lead to fetal programming that in turn contributes to developmental changes of many organs postnatally. There is evidence that IUGR is a risk factor for the development of metabolic and cardiovascular disease later in life. A higher incidence of breast cancer was also observed after IUGR. This could be due to changes in mammary gland developmental pathways. We sought to characterise IUGR-induced alterations of the complex pathways of mammary development at the level of the transcriptome in a rat model of IUGR, using pathways analysis bioinformatics.We analysed the mammary glands of Wistar rats with IUGR induced by maternal low protein (LP) diet at the beginning (d21) and the end (d28) of pubertal ductal morphogenesis. Mammary glands of the LP group were smaller in size at d28, however did not show morphologic changes. We identified multiple differentially expressed genes in the mammary gland using Agilent SurePrint arrays at d21 and d28. In silico analysis was carried out using Ingenuity Pathways Analysis. In mammary gland tissue of LP rats at d21 of life a prominent upregulation of WT1 and CDKN1A (p21) expression was observed. Differentially regulated genes were associated with the extracellular regulated kinase (ERK)-1/-2 pathway. Western Blot analysis showed reduced levels of phosphorylated ERK-1/-2 in the mammary glands of the LP group at d21. To identify possible changes in circulating steroid levels, serum LC-Tandem mass-spectrometry was performed. LP rats showed higher serum progesterone levels and an increased corticosterone/dehydrocorticosterone-ratio at d28.Our data obtained from gene array analysis support the hypothesis that IUGR influences pubertal development of the rat mammary gland. We identified prominent differential regulation of genes and pathways for factors regulating cell cycle and growth. Moreover, we detected new pathways which appear to be programmed by IUGR.
EVALuna2:17429

Detection of signature double-negative T cells is a predictive marker to identify autoimmune lymphoproliferative syndrome associated with FAS loss of function - Eisenhauer, Nina; Miano, Maurizio; Naumann-Bartsch, Nora; Leyh, Jörg; Dell'Orso, Gianluca; Aigner, Michael; Fecker, Gisela; Hinze, Claas; Wittkowski, Helmut; Bruns, Heiko; Zierk, Jakob; Metzler, Markus; et al. (American Journal of Hematology, 2024)
CRIS-Team Scopus Importer:2024-03-29

Detection of Signature Double-Negative T Cells Is a Reliable Marker for ALPS Associated with FAS Mutation - Eisenhauer, Nina; Miano, Maurizio; Naumann-Bartsch, Nora; Leyh, Jörg; Terranova, Paola; Hinze, Claas; Aigner, Michael; Wittkowski, Helmut; Bruns, Heiko; Ehl, Stephan; Metzler, Markus; Arkwright, Peter; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-17

Development and Usability Analysis of a Multimedia eConsent Solution - Schneiderheinze, Hauke; Prokosch, Hans-Ulrich; Apel, Hendrik; Bellut, Laura; Wullich, Bernd; Trollmann, Regina; Schüttler, Christina (German Medical Data Sciences: Shaping Change – Creative Solutions for Innovative Medicine, 2019)
BACKGROUND: More and more medical data is being stored digitally in routine care. The secondary use of patient data is only possible to a limited extent for data protection reasons. In order to enable a long-term and far-reaching use of secondary data, a possible approach is to obtain "broad consent" from patients, e.g. on research projects whose purpose is still unknown at the time of consent. OBJECTIVE: To develop and evaluate an interactive eConsent prototype that presents the extensive contents of the "broad consent" in multimedia form for the purpose of a successful and resource-efficient information and consent process. METHODS: The eConsent prototype was designed on basis of a literature review and in accordance with the goals of the German medical informatics initiative. User tests and subsequent questionnaire surveys using the System Usability Scale (SUS) were carried out with patients from a university hospital to assess the prototype's usability. The study was conducted in a quasi-experimental, one-group posttest-only design. RESULTS: The created interactive prototype can present the contents acoustically and visually and offers the possibility to retrieve additional information. With a SUS score of 84,1/100 the results indicate a very good usability of the prototype. CONCLUSION: The next steps will include further refinements of the prototype based on the feedback received and a subsequent study with a broader user group aimed at introducing an eConsent tool as part of a patient portal.
CRIS-Team Scopus Importer:2019-09-24
Keywords: Informed consent; multimedia; patient participation; patient portals

Diagnosis and treatment of Guillain-Barré Syndrome in childhood and adolescence: An evidence- and consensus-based guideline - Korinthenberg, R.; Trollmann, Regina; Felderhoff-Müser, U.; Bernert, G.; Hackenberg, A.; Hufnagel, M.; Pohl, M.; Hahn, G.; Mentzel, H. J.; Sommer, C.; Lambeck, J.; Mecher, F.; et al. (European Journal of Paediatric Neurology, 2020)
This evidence- and consensus-based practical guideline for the diagnosis and treatment of Guillain-Barré Syndrome (GBS) in childhood and adolescence has been developed by a group of delegates from relevant specialist societies and organisations; it is the result of an initiative by the German-Speaking Society of Neuropediatrics (GNP), and is supported by the Association of Scientific Medical Societies (AWMF, Arbeitsgemeinschaft der Wissenschaftlichen Medizinischen Fachgesellschaften). A systematic analysis of the literature revealed that only a few adequately-controlled studies exist for this particular age group, while none carries a low risk of bias. For this reason, the diagnostic and therapeutic recommendations largely rely on findings in adult patients with GBS, for which there are a higher number of suitable studies available. Consensus was established using a written, multi-step Delphi process. A high level of consensus could be reached for the crucial steps in diagnosis and treatment. We recommend basing the diagnostic approach on the clinical criteria of GBS and deriving support from CSF and electrophysiological findings. Repetition of invasive procedures that yield ambiguous results is only recommended if the diagnosis cannot be ascertained from the other criteria. For severe or persistently-progressive GBS treatment with intravenous immunoglobulin (IVIG) is recommended, whereas in cases of IVIG intolerance or inefficacy we recommended treatment with plasmapheresis. Corticosteroids are ineffective for GBS but can be considered when acute onset chronic inflammatory demyelinating polyneuropathy (A-CIDP) is suspected due to a prolonged disease course. The full German version of the Guideline is available on the AWMF website (https://www.awmf.org/leitlinien/detail/ll/022-008.html).
CRIS-Team Scopus Importer:2020-01-21
Keywords: Children; Diagnosis; Guillain-barré syndrome; Intravenous immunoglobulin; Plasmapheresis/plasma exchange; Supportive care

Diagnosis of X-Linked Hypohidrotic Ectodermal Dysplasia by Meibography and Infrared Thermography of the Eye - Kärcher, Thomas; Dietz, Jasna; Jacobi, Christina; Berz, Reinhold; Schneider, Holm (Current Eye Research, 2015)
X-linked hypohidrotic ectodermal dysplasia (XLHED) is the most common form of ectodermal dysplasia. Clinical characteristics include meibomian gland disorder and the resulting hyperevaporative dry eye. In this study, we evaluated meibography and ocular infrared thermography as novel methods to diagnose XLHED.Eight infants, 12 boys and 14 male adults with XLHED and 12 healthy control subjects were subjected to a panel of tests including the ocular surface disease index (OSDI), meibography and infrared thermography, non-invasive measurement of tear film break-up time (NIBUT) and osmolarity, Schirmer's test, lissamine green staining and fluorescein staining. Sensitivity and specificity were determined for single tests and selected test combinations.Meibography had 100% sensitivity and specificity for identifying XLHED. Infrared thermography, a completely non-invasive procedure, revealed a typical pattern for male subjects with XLHED. It was, however, less sensitive (86% for adults and 67% for children) than meibography or a combination of established routine tests. In adults, OSDI and NIBUT were the best single routine tests (sensitivity of 86% and 71%, respectively), whereas increased tear osmolarity appeared as a rather unspecific ophthalmic symptom. In children, NIBUT was the most convincing routine test (sensitivity of 91%).Meibography is the most reliable ophthalmic examination to establish a clinical diagnosis in individuals with suspected hypohidrotic ectodermal dysplasia, even before genetic test results are available. Tear film tests and ocular surface staining are less sensitive in children, but very helpful for estimating the severity of ocular surface disease in individuals with known XLHED.
EVALuna2:18886

Diagnostic Utility of Interleukin-6 in Early-Onset Sepsis among Term Newborns: Impact of Maternal Risk Factors and CRP Evaluation. - Schleier, Maria; Lubig, Julia; Kehl, Sven; Hébert, Steven; Wölfle, Joachim; van der Donk, Adriana; Bär, Alisa; Reutter, Heiko Martin; Hepp, Tobias; Morhart, Patrick (Children, 2023)
(1) Background: Interleukin-6 (IL-6) levels act as an early infection marker preceding C-reactive protein (CRP) elevation. This study seeks to analyze IL-6 behavior in suspected early-onset sepsis (EOS) cases among term newborns, comparing it to that of CRP and evaluating IL-6's diagnostic utility. We also aim to assess the impact of maternal risk factors on EOS in term newborns, quantifying their influence for informed decision making. (2) Methods: The retrospective data analysis included 533 term newborns who were admitted to our hospital because of suspected EOS. IL-6, CRP, and the impact of maternal risk factors were analyzed in the context of EOS using binomial test, Chi-squared test, logistic and linear regression. (3) Results: In the cases of EOS, both IL-6 and CRP were elevated. The increase in CRP can be predicted by the initial increase in IL-6 levels. Among the assessed risk factors, intrapartum maternal fever (adjusted odds ratio 18.1; 95% CI (1.7-4.1)) was identified as the only risk factor significantly associated with EOS. (4) Conclusions: Employing IL-6 as an early infection marker enhanced EOS diagnostic precision due to its detectable early rise. However, caution is required, as elevations in IL-6 and CRP levels do not exclusively indicate EOS. Increased CRP levels in healthy newborns with maternal risk factors may be attributed to dynamics of vaginal labor.
EVALuna2:549522

Differences between capillary and venous blood counts in children-A data mining approach - Becker, Mathias; Gscheidmeier, Thomas; Gross, Hans-Juergen; Cario, Holger; Wölfle, Joachim; Rauh, Manfred; Metzler, Markus; Zierk, Jakob (International Journal of Laboratory Hematology, 2022)
Background Capillary sampling of blood counts is a well-established alternative to venipuncture in paediatrics. However, the sampling method has to be considered when interpreting test results, as measurements differ. Ethical and practical considerations prevent simultaneous venous and capillary sample acquisition in comprehensive paediatric cohorts that span all ages for the purpose of a direct method comparison, resulting in uncertainty regarding the interpretation of capillary test results. Methods We applied a data mining method to calculate the differences between capillary and venous blood count analytes using laboratory data collected during patient care. We examined 486 401 blood counts performed between 2010 and 2017 in two German paediatric tertiary care centers in children from birth to 18 years analysed on SYSMEX XE-2100 and SYSMEX XE-5000 devices, and analysed the differences between capillary and venous test results in 15 218 paired samples performed within 24 h. Results We identified the mean systematic differences between capillary and venous (capillary-venous) test results for haemoglobin (+6.5 g/L), haematocrit (+2.38%), platelet count (-7.01 x 10(9)/l), red cell count (+0.18 x 10(12)/L), white cell count (-0.64 x 10(9)/L), mean corpuscular cell volume (+2.07 fl), mean corpuscular haemoglobin (+0.33 pg), mean corpuscular haemoglobin concentration (-4.4 g/L) and red cell distribution width (+0.40%). The effect of age on these mean deltas is negligible, while the levels of test results influence the difference between capillary and venous test results in most analytes. Conclusions Our results improve guidance regarding the interpretation of capillary test results for children of all ages and in both physiological and pathological ranges.
CRIS-Team WoS Importer:2022-05-13

Differential Coassembly of α1-GABAARs Associated with Epileptic Encephalopathy - Hannan, Saad; Affandi, Aida H. B.; Minere, Marielle; Jones, Charlotte; Goh, Pollyanna; Warnes, Gary; Popp, Bernt; Trollmann, Regina; Nizetic, Dean; Smart, Trevor G. (The Journal of Neuroscience, 2020)
GABAA receptors (GABAARs) are profoundly important for controlling neuronal excitability. Spontaneous and familial mutations to these receptors feature prominently in excitability disorders and neurodevelopmental deficits following disruption to GABA-mediated inhibition. Recent genotyping of an individual with severe epilepsy and Williams-Beuren syndrome identified a frameshifting de novo variant in a major GABAAR gene, GABRA1 This truncated the α1 subunit between the third and fourth transmembrane domains and introduced 24 new residues forming the mature protein, α1Lys374Serfs*25 Cell surface expression of mutant murine GABAARs is severely impaired compared with WT, due to retention in the endoplasmic reticulum. Mutant receptors were differentially coexpressed with β3, but not with β2, subunits in mammalian cells. Reduced surface expression was reflected by smaller IPSCs, which may underlie the induction of seizures. The mutant does not have a dominant-negative effect on native neuronal GABAAR expression since GABA current density was unaffected in hippocampal neurons, although mutant receptors exhibited limited GABA sensitivity. To date, the underlying mechanism is unique for epileptogenic variants and involves differential β subunit expression of GABAAR populations, which profoundly affected receptor function and synaptic inhibition.SIGNIFICANCE STATEMENT GABAARs are critical for controlling neural network excitability. They are ubiquitously distributed throughout the brain, and their dysfunction underlies many neurologic disorders, especially epilepsy. Here we report the characterization of an α1-GABAAR variant that results in severe epilepsy. The underlying mechanism is structurally unusual, with the loss of part of the α1 subunit transmembrane domain and part-replacement with nonsense residues. This led to compromised and differential α1 subunit cell surface expression with β subunits resulting in severely reduced synaptic inhibition. Our study reveals that disease-inducing variants can affect GABAAR structure, and consequently subunit assembly and cell surface expression, critically impacting on the efficacy of synaptic inhibition, a property that will orchestrate the extent and duration of neuronal excitability.
CRIS-Team Scopus Importer:2020-07-31
Keywords: epilepsy; GABA-A receptor; inhibition; synaptic transmission; α subunit variant

Differential Diagnosis of Acquired and Hereditary Neuropathies in Children and Adolescents-Consensus-Based Practice Guidelines - Korinthenberg, Rudolf; Trollmann, Regina; Plecko, Barbara; Stettner, Georg M.; Blankenburg, Markus; Weis, Joachim; Schoser, Benedikt; Mueller-Felber, Wolfgang; Lochbuehler, Nina; Hahn, Gabriele; Rudnik-Schoeneborn, Sabine (Children, 2021)
Disorders of the peripheral nerves can be caused by a broad spectrum of acquired or hereditary aetiologies. The objective of these practice guidelines is to provide the reader with information about the differential diagnostic workup for a target-oriented diagnosis. Following an initiative of the German-speaking Society of Neuropaediatrics, delegates from 10 German societies dedicated to neuroscience worked in close co-operation to write this guideline. Applying the Delphi methodology, the authors carried out a formal consensus process to develop practice recommendations. These covered the important diagnostic steps both for acquired neuropathies (traumatic, infectious, inflammatory) and the spectrum of hereditary Charcot-Marie-Tooth (CMT) diseases. Some of our most important recommendations are that: (i) The indication for further diagnostics must be based on the patient's history and clinical findings; (ii) Potential toxic neuropathy also has to be considered; (iii) For focal and regional neuropathies of unknown aetiology, nerve sonography and MRI should be performed; and (iv) For demyelinated hereditary neuropathy, genetic diagnostics should first address PMP22 gene deletion: once that has been excluded, massive parallel sequencing including an analysis of relevant CMT-genes should be performed. This article contains a short version of the guidelines. The full-length text (in German) can be found at the Website of the "Arbeitsgemeinschaft der Wissenschftlichen Medizinischen Fachgesellschaften e.V. (AWMF), Germany.
CRIS-Team WoS Importer:2021-09-03

Differential effects of low birthweight and intrauterine growth restriction on umbilical cord blood insulin-like growth factor concentrations - Tzschoppe, Anja; Riedel, Christina; Von Kries, Ruediger; Struwe, Ellen; Rascher, Wolfgang; Dörr, Helmuth-Günther; Beckmann, Matthias; Schild, Ralf L.; Goecke, Tamme W.; Flyvbjerg, Allan; Frystyk, Jan; Doetsch, Joerg (Clinical Endocrinology, 2015)
Alterations in the growth hormone-insulin-like growth factor (IGF) axis have been considered as a causal factor for intrauterine growth restriction (IUGR) and for the increased risk of metabolic disease in later life. We compared members of the IGF axis in umbilical cord blood between IUGR neonates, small for gestational age without foetal restriction (SGA) and appropriate for gestational age (AGA) neonates.Prospective controlled multicenter study.Sixteen ultrasound-proven IUGR, 8 SGA and 40 AGA neonates.Concentrations of total IGF-I and total IGF-II by immunoassays, bioactive IGF by cell-based bioassay and IGFBP-I in mixed venous and arterial umbilical cord blood samples at birth. Auxological parameters at birth.IGF-I concentrations in IUGR [17·7 ?g/l (CI 13·8;21·6)] were clearly below those in AGA [48·3 ?g/l (CI 43·7;52·9)] and SGA neonates [36·0 ?g/l (CI 26·6;45·4)]. IGF-II levels were significantly reduced in IUGR [201·4 ?g/l (CI 190·2;212·6)] compared to AGA neonates [231·2 ?g/l (CI 220·6;241·9)]. A trend for lower IGF-II concentrations was observed in IUGR when compared to SGA neonates [232·0 ?g/l (CI 207·2;256·8)]. These differences could not be explained by confounding. For IGFBP-1, a trend towards higher values in IUGR was observed.Low IGF-I cord blood concentrations in hypotrophic neonates after IUGR might not only result from low birthweight per se, but also reflect prenatal placental environment. Alterations of the IGF axis could be in the causal pathway of IUGR and thus constitute a potential surrogate marker for IUGR in the assessment of foetal programming.
EVALuna2:17440

Diffuse Encephalopathy Associated with Isolated Cerebral Langerhans Cell Histiocytosis - Rompel, Oliver; Buslei, Rolf; Hammon, Matthias; Dörr, Helmuth-Günther; Chada, Martin; Nikkhah, Guido; Uder, Michael; Trollmann, Regina (Pediatric Neurology, 2016)
Langerhans cell histiocytosis is a rare disease of the monocyte-macrophage system. Abnormalities of the hypothalamic-pituitary region are common in individuals with central nervous system involvement.This six-year-old boy developed rapidly progressive aggressive behavior, central diabetes insipidus, and repeated complex partial seizures. Magnetic resonance imaging revealed a diffuse leukoencephalopathy-like pattern and numerous infratentorial and supratentorial granulomatous nodules in the brain parenchyma along with infundibular and hypothalamic mass lesions. Stereotactic serial biopsies enabled histopathologic and immunohistochemical diagnosis of Langerhans cell histiocytosis.Similar MRI findings have rarely been described in the literature. These findings represent part of the broad neuroradiological spectrum of Langerhans cell histiocytosis of the nervous system in children.
EVALuna2:7341

Digital Workout Versus Team Training: The Impact of the COVID-19 Pandemic on Athletes. - Schneider, Friedemann; Runer, Armin; Burkert, Francesco; Und Aspang, Jesse Seilern; Reider, Simone; Schneider, Holm; Pocecco, Elena (Sports Medicine International Open, 2022)
The aim of the study was to assess the effects of the COVID-19 pandemic on sport practice and to identify measures adopted by individuals and sports organizations to allow a safe return to community sports. An electronic survey was launched worldwide in June 2020 in the German and English languages. The questionnaire collected anonymous data on sporting activity before, during, and after pandemic-induced confinement. Participants classified themselves as either recreational, competitive, or professional sports level athletes. A total of 1336 adults (30.5±11.7 years; 54.0% women) participated in the survey; 68.5% were active athletes, 10.1% coaches, 2.1% officials and 4.3% related medical staff, 3.6% had another function, and 11.4% indicated no regular sports activity. Most participants practiced their sport in Europe (93.8%); the majority (61.0%) was amateur athletes. During confinement, 15.7% could perform their main sport unrestricted, 43.5% stated a reduced amount of time spent on sporting activities, 46.4% a reduced intensity level. Most participants (77.5%) were neither aware of screening measures nor of guidelines for dealing with infected athletes (80.0%) or for return to sports after a coronavirus infection (88.6%). Preventive measures mentioned included basic hygiene, measures to reduce personal contacts or virus transmission, or to improve traceability of infections. During confinement, a higher age (p=0.004) and training in a club setting (p<0.001) were associated with reduced sporting activity, while the availability of online training (p=0.030 ) was linked to both increased extent and intensity levels. A lower age (p=0.001) and recreational sports level (p=0.005) were associated with decreased activity after confinement. Although isolation can be necessary to protect public health, it alters the amount and intensity of physical activity.
EVALuna2:514670

Diminished protein-bound ω-hydroxylated ceramides in the skin of patients with ichthyosis with 12R-lipoxygenase (LOX) or eLOX-3 deficiency - Dick, A.; Tantcheva-Poor, I. .; Oji, V.; Giehl, K. A.; Fischer, J. .; Krieg, P.; Schneider, Holm; Rauh, Manfred (British Journal of Dermatology, 2017)
EVALuna2:34217

Direct and indirect costs and cost drivers of Tuberous sclerosis complex in children, adolescents, and caregivers: A multicenter cohort study - Zoellner, Johann Philipp; Grau, Janina; Schubert-Bast, Susanne; Kurlemann, Gerhard; Hertzberg, Christoph; Wiemer-Kruel, Adelheid; Bast, Thomas; Bertsche, Astrid; Bettendorf, Ulrich; Fiedler, Barbara; Hahn, Andreas; Hartmann, Hans; et al. (Epilepsia, 2021)
CRIS-Team WoS Importer:2021-11-26

Direct and indirect costs and cost-driving factors of Tuberous sclerosis complex in children, adolescents, and caregivers: a multicenter cohort study - Grau, Janina; Zollner, Johann Philipp; Schubert-Bast, Susanne; Kurlemann, Gerhard; Hertzberg, Christoph; Wiemer-Kruel, Adelheid; Bast, Thomas; Bertsche, Astrid; Bettendorf, Ulrich; Fiedler, Barbara; Hahn, Andreas; Hartmann, Hans; et al. (Orphanet Journal of Rare Diseases, 2021)
Background Tuberous sclerosis complex (TSC), a multisystem genetic disorder, affects many organs and systems, characterized by benign growths. This German multicenter study estimated the disease-specific costs and cost-driving factors associated with various organ manifestations in TSC patients. Methods A validated, three-month, retrospective questionnaire was administered to assess the sociodemographic and clinical characteristics, organ manifestations, direct, indirect, out-of-pocket, and nursing care-level costs, completed by caregivers of patients with TSC throughout Germany. Results The caregivers of 184 patients (mean age 9.8 +/- 5.3 years, range 0.7-21.8 years) submitted questionnaires. The reported TSC disease manifestations included epilepsy (92%), skin disorders (86%), structural brain disorders (83%), heart and circulatory system disorders (67%), kidney and urinary tract disorders (53%), and psychiatric disorders (51%). Genetic variations in TSC2 were reported in 46% of patients, whereas 14% were reported in TSC1. Mean total direct health care costs were EUR 4949 [95% confidence interval (95% CI) EUR 4088-5863, median EUR 2062] per patient over three months. Medication costs represented the largest direct cost category (54% of total direct costs, mean EUR 2658), with mechanistic target of rapamycin (mTOR) inhibitors representing the largest share (47%, EUR 2309). The cost of anti-seizure drugs (ASDs) accounted for a mean of only EUR 260 (5%). Inpatient costs (21%, EUR 1027) and ancillary therapy costs (8%, EUR 407) were also important direct cost components. The mean nursing care-level costs were EUR 1163 (95% CI EUR 1027-1314, median EUR 1635) over three months. Total indirect costs totaled a mean of EUR 2813 (95% CI EUR 2221-3394, median EUR 215) for mothers and EUR 372 (95% CI EUR 193-586, median EUR 0) for fathers. Multiple regression analyses revealed polytherapy with two or more ASDs and the use of mTOR inhibitors as independent cost-driving factors of total direct costs. Disability and psychiatric disease were independent cost-driving factors for total indirect costs as well as for nursing care-level costs. Conclusions This study revealed substantial direct (including medication), nursing care-level, and indirect costs associated with TSC over three months, highlighting the spectrum of organ manifestations and their treatment needs in the German healthcare setting. Trial registration: DRKS, DRKS00016045. Registered 01 March 2019,
CRIS-Team WoS Importer:2021-07-09

Disability Rating in Children and Adolescents with Chronic Myeloid Leukemia - Suttorp, Meinolf; Sembill, Stephanie; Metzler, Markus (Klinische Pädiatrie, 2020)
Background CML comprises only 2-3 % of all diagnosed pediatric leukemias. Mostly diagnosed in chronic phase (CML-CP), the disease progresses without treatment to accelerated phase (CML-AP) and finally to life-limiting blastic phase (CML-BP). Contrasting the therapy of other leukemia types, CML-CP is not treated by intense chemotherapy but with oral drugs - termed tyrosine kinase inhibitors (TKI)- for an unlimited duration. This therapy may be associated with general and developmental-specific side effects. The rarity of pediatric-CML is limiting the experience in assessment of the disability rating (DR) as an administrative health authority procedure.
CRIS-Team WoS Importer:2020-10-30

Distinct pathways for genetic and epigenetic predisposition in familial and bilateral Wilms tumor - Wegert, Jenny; Appenzeller, Silke; Treger, Taryn D.; Streitenberger, Heike; Ziegler, Barbara; Bausenwein, Sabrina; Vokuhl, Christian; Parks, Conor; Jüttner, Eva; Gramlich, Susanne; Ernestus, Karen; Warman, Steven W.; et al. (Genome Medicine, 2025)
Background: Genetic predisposition is particularly common in children with the kidney cancer, Wilms tumor. In 10% of these children, this manifests as a family history of Wilms tumor or bilateral disease. The frequency and spectrum of underlying changes have not been systematically investigated. Methods: We analyzed 129 children with suspected Wilms tumor predisposition, 20 familial cases, and 109 children with bilateral disease, enrolled over 30 years in the German SIOP93-01/GPOH and SIOP2001 studies. We used whole exome, whole genome, and targeted DNA sequencing, together with MLPA and targeted methylation assays on tumor, blood, and normal kidney to determine predisposing changes. Results: Predisposing variants were identified in 117/129 children, comprising DNA variants (57%) and epigenetic changes (34%). Most children had predisposition variants in genes previously implicated in Wilms tumor: most prominently WT1 (n = 35) and less frequently TRIM28, REST, DIS3L2, CTR9, DICER1, CDC73, and NONO. Nine children carried germline mutations in cancer predisposition genes not considered Wilms tumor predisposition genes, such as CHEK2, CDKN2A, BLM, BRCA2, STK11, and FMN2. Predisposition via epigenetic BWS-IC1 alterations occurred as early somatic events, reflected by partial (mosaic) loss of imprinting or loss of heterozygosity at the IGF2/H19 locus in normal kidney or blood. These patients rarely had a clinical diagnosis of Beckwith-Wiedemann syndrome (BWS). Especially WT1-driven tumors follow a stereotypical pathway of germline WT1 mutations becoming homozygous in renal precursor lesions through 11p LOH, which concomitantly activates imprinted IGF2 expression, with subsequent WNT pathway activation leading to tumor growth. There is a high rate of multicentric tumors, which may have previously been missed in unilateral tumors. While Wilms tumor predisposition genes relied on somatic inactivation of the second allele, this was different for general cancer predisposition genes. The latter cases were often associated with additional oncogenic alterations, similar to tumors with epigenetic predisposition. Conclusions: We identified two main mechanisms of Wilms tumor predisposition: either germline genetic alterations of Wilms tumor and, less frequently, general cancer genes; or postzygotic mosaic imprinting defects activating IGF2. These findings inform future genetic screening and risk assessment of affected children and lend support to liquid biopsy screening for enhanced therapeutic stratification.
CRIS-Team Scopus Importer:2025-05-16
Keywords: BWS; Cancer predisposition; Genomic imprinting; Hereditary cancer; Multicentric tumors; Nephroblastoma; Pediatric cancer; Wilms tumor; WT1

Distinct pattern of genomic breakpoints in CML and BCR::ABL1-positive ALL: analysis of 971 patients - Hovorkova, Lenka; Winkowska, Lucie; Skorepova, Justina; Krumbholz, Manuela; Benesova, Adela; Polivkova, Vaclava; Alten, Julia; Bardini, Michela; Meyer, Claus; Kim, Rathana; Trahair, Toby N.; Clappier, Emmanuelle; et al. (Molecular Cancer, 2024)
Background: The BCR::ABL1 is a hallmark of chronic myeloid leukemia (CML) and is also found in acute lymphoblastic leukemia (ALL). Most genomic breaks on the BCR side occur in two regions - Major and minor - leading to p210 and p190 fusion proteins, respectively. Methods: By multiplex long-distance PCR or next-generation sequencing technology we characterized the BCR::ABL1 genomic fusion in 971 patients (adults and children, with CML and ALL: pediatric ALL: n = 353; pediatric CML: n = 197; adult ALL: n = 166; adult CML: n = 255 patients) and designed “Break-App” web tool to allow visualization and various analyses of the breakpoints. Pearson’s Chi-Squared test, Kolmogorov-Smirnov test and logistic regression were used for statistical analyses. Results: Detailed analysis showed a non-random distribution of breaks in both BCR regions, whereas ABL1 breaks were distributed more evenly. However, we found a significant difference in the distribution of breaks between CML and ALL. We found no association of breakpoints with any type of interspersed repeats or DNA motifs. With a few exceptions, the primary structure of the fusions suggests non-homologous end joining being responsible for the BCR and ABL1 gene fusions. Analysis of reciprocal ABL1::BCR fusions in 453 patients showed mostly balanced translocations without major deletions or duplications. Conclusions: Taken together, our data suggest that physical colocalization and chromatin accessibility, which change with the developmental stage of the cell (hence the difference between ALL and CML), are more critical factors influencing breakpoint localization than presence of specific DNA motifs.
CRIS-Team Scopus Importer:2024-07-12
Keywords: ABL1; Acute lymphoblastic leukemia; BCR; Chronic myeloid leukemia; Genomic breakpoints

Distribution and Cytokine Profile of Peripheral B Cell Subsets Is Perturbed in Pediatric IBD and Partially Restored during a Successful IFX Therapy - Schnell, Alexander; Schwarz, Benedikt; Wahlbuhl, Mandy; Allabauer, Ida; Hess, Merlin; Weber, Simone; Werner, Felix; Schmidt, Hannah; Rechenauer, Tobias; Siebenlist, Gregor; Kaspar, Sonja; Ehrsam, Christoph; et al. (Inflammatory Bowel Diseases, 2021)
Background: The role of B cells in inflammatory bowel disease (IBD) is ambiguous, as B cells may have both pathogenic and protective functions in IBD. We studied B cell subsets before and after initiation of an anti-tumor necrosis factor alpha (anti-TNFα) therapy in pediatric IBD. The aim of the study was to examine the behavior of B cells in pediatric IBD patients undergoing an anti-TNFα therapy and, more specifically, to clarify their association with a successful or an unsuccessful infliximab (IFX) treatment. Methods: A total of N = 42 pediatric IBD patients (Crohn disease, n = 30; ulcerative colitis, n = 12) for whom an anti-TNFα therapy with and without a concomitant azathioprine (AZA) medication was administered were recruited. Fourteen healthy age-matched children served as control patients. Blood samples were collected before initiation of the anti-TNFα therapy, before the fourth infusion at the end of the induction phase, and after 6 and 12 months under therapy maintenance. Flow cytometry (CD20, CD27, CD38, CD138) and intracellular staining (interleukin 10 [IL10], TNFα, granzyme B) were performed. Responders to successful IFX therapy were classified exhibiting a fecal calprotectin level of below 100 μg/g or achieving levels of <10% of the baseline value at initiation than at the end of the 12-month follow-up period. Results: Before initiation of anti-TNFα therapy, flow cytometry revealed increased percentages of naïve B cells whereas transitional B cells were reduced compared with those in the healthy control patients. The IL10-producing B cells of both ulcerative colitis and Crohn disease patients were reduced at the initiation of IFX therapy, whereas TNFα-producing transitional CD24hiCD38hi B cells in ulcerative colitis patients were increased compared with those in healthy control patients. After 12 months of therapy, we detected a significant increase of IL10-producing transitional B cells in responding patients. The IFX trough levels in the responding patients showed a significant increase until 6 months after IFX initiation, attaining mean values of 9.9 μg/mL, whereas the IFX dosage was significantly lower than that in the nonresponding patients. The IFX trough levels in AZA-treated patients reached earlier therapeutic levels than in patients without AZA comedication, whereas during the course of the IFX therapy, comedication with AZA had no significant effect on the outcome. Conclusions: Attaining a normalization of IL10 production among CD24hiCD38hi B cells after 12 months of therapy may represent additional information about the reconstitution of a patient's immune system in responding patients. The achievement of an IFX trough level of 10 μg/mL at 6 months of treatment is associated with a successful anti-TNFα therapy. In addition, AZA comedication supports an earlier achievement of therapeutic IFX trough levels.
CRIS-Team Scopus Importer:2021-02-26
Keywords: children; Crohn disease; TNFα inhibitor; transitional B cells; ulcerative colitis

Distribution of BCR::ABL1 Transcript Types and Response to Therapy in Pediatric Patients with Chronic Myeloid Leukemia - Seiser, Esra; Behrens, Yvonne L.; Lukat, Sabine; Sembill, Stephanie; Karow, Axel; Suttorp, Meinolf; Metzler, Markus; Krumbholz, Manuela (Journal of Molecular Diagnostics, 2025)
Achieving a stable deep molecular response with the option to discontinue tyrosine kinase inhibitor treatment is the new therapeutic goal for patients with chronic myeloid leukemia (CML). Several studies have shown that individuals expressing the BCR::ABL1 e14a2 transcript achieve a major molecular response more rapidly than those with the e13a2 transcript. However, technical issues may have confounded these observations, and data for pediatric patients are limited. This study analyzed the distribution of BCR::ABL1 transcript types and their association with baseline hematologic parameters and tyrosine kinase inhibitor treatment response in 102 pediatric patients with CML. Subgroups were compared on the basis of results from routine multiplex PCR and droplet digital PCR (ddPCR). The dynamics of the transcript types under therapy were evaluated in detail in patients and a CML cell line co-expressing e13a2 + e14a2. ddPCR has identified significantly more patients co-expressing e13a2 + e14a2 than classified on the basis of routine diagnostics. This has implications for the categorization of individual subgroups. Comparing transcript dynamics in individuals or a cell line expressing both variants simultaneously revealed no differences in treatment response. When analyzing clinical data based on the transcript classification of patients, it is important to use methods that detect both variants with equal sensitivity. In ddPCR, the transcript variants' ratio is accurately shown because there is no competitive template amplification, as seen in multiplex and quantitative real-time PCR.
CRIS-Team Scopus Importer:2025-02-28

Diving into the Digital Landscape: Assessing the Quality of Online Information on Neonatal Jaundice for Parents - Baumgartner, Michael; Behr, Anna Lena; Garbe, Anne Christina; Quatember, Christoph; Reutter, Heiko Martin; Wölfle, Joachim; Fahlbusch, Fabian Benedikt; Hanslik, Gregor (Children, 2024)
Background: Hyperbilirubinemia is a common condition in newborns. While mild cases of jaundice are common and typically resolve spontaneously, severe hyperbilirubinemia can lead to serious neurologic complications if left untreated. With the constant adaptation of guidelines, clinical management has significantly improved, and treatment has become routine for pediatricians. However, for parents of affected children, managing the condition is not routine. In today’s digital age, parents often seek additional information by accessing a wide range of medical resources on the internet. While this can be empowering, it also presents challenges, as the quality and accuracy of online medical information can vary widely. Therefore, we analyzed the current quality of information on jaundice found on the internet by parents. Methods: A simulated internet search (using the Google search engine) was conducted from a layperson’s perspective using German (“Neugeborenes Gelbsucht”, “Baby Gelbsucht”) and English (“jaundice newborn”, “jaundice baby”) search terms. Subsequently, the quality of the search results was assessed by two independent neonatologists based on the DISCERN Plus Score, HONcode certification, and the JAMA criteria. Results: Websites targeting non-medical laypersons exhibited significant variability in quality. Notably, the content of English websites was superior to that of websites in the German language. The majority of English sites were predominantly institutional, whereas most German sites were commercially oriented. Conclusions: Although information on jaundice is readily accessible online for non-medical individuals, there were notable differences in quality based on language and significant variability in the quality of information warranting attention from healthcare professionals. Furthermore, German websites providing information on jaundice were often hosted by commercial organizations. We propose that pediatric societies engage in developing and maintaining organization-based medical information to improve online resources for parents.
CRIS-Team Scopus Importer:2024-08-02
Keywords: jaundice; neonatal care; online information

DMBT1 expression and neutrophil-to-lymphocyte ratio during necrotizing enterocolitis are influenced by impaired perfusion due to cardiac anomalies. - Diez, Sonja; Besendörfer, Manuel; Weyerer, Veronika; Hartmann, Arndt; Moosmann, Julia; Weiss, Christel; Renner, Marcus; Müller, Hanna (Molecular and Cellular Pediatrics, 2022)
BACKGROUND: Deleted in malignant brain tumors 1 (DMBT1) is involved in innate immunity and epithelial differentiation. It has been proven to play a role in various states of inflammation or hypoxia of fetal gastrointestinal and pulmonary diseases. Discrimination of pathogenesis in necrotizing enterocolitis (NEC) based on cardiac status improves the understanding of NEC in different patient subgroups. We aimed at examining DMBT1 expressions regarding their association with cardiac status leading to impaired intestinal perfusion, intraoperative bacteria proof, and a fulminant course of NEC. METHODS: Twenty-eight patients with NEC were treated surgically between 2010 and 2019 at our institution. DMBT1 expression was examined in intestinal sections using immunohistochemistry to detect DMBT1 protein. Associations of clinical parameters and DMBT1 expression were analyzed. RESULTS: We examined DMBT1 levels in 10 patients without cardiac defects and 18 patients with persisting ductus arteriosus (PDA) and congenital heart defects (CHD). Compared to patients without cardiac malformations, DMBT1 levels tended to score higher in patients with PDA/CHD (p = 0.2113) and were negatively correlated with C-reactive protein in these infants (p = 0.0172; r = - 0.5533). The number of DMBT1-expressing macrophages was elevated in the PDA/CHD-subgroup (p = 0.0399). Ratios of neutrophils and monocytes to lymphocytes were significantly higher in infants with PDA/CHD (p = 0.0319 and 0.0493). DMBT1 expression was significantly associated with positive bacterial culture of intraoperative swabs (p = 0.0252) and DMBT1 expression of the serosa was associated with a fulminant course of NEC (p = 0.0239). CONCLUSIONS: This study demonstrates that DMBT1 expression may be influenced by cardiac anomalies with an impaired intestinal perfusion in the neonatal intestine. NEC in PDA/CHD infants is associated with more DMBT1-positive macrophages and a significantly elevated neutrophil-to-lymphocyte ratio.
EVALuna2:497662
Keywords: DMBT1; Deleted in malignant brain tumors 1; Necrotizing enterocolitis; Congenital heart disease; Neutrophil-to-lymphocyte ratio; Monocyte-to-lymphocyte ratio

DNA copy number alterations mark disease progression in paediatric chronic myeloid leukaemia - Van Der Sligte, Naomi E.; Krumbholz, Manuela; Pastorczak, Agata; Scheijen, Blanca; Tauer, Josephine T.; Nowasz, Christina; Sonneveld, Edwin; De Bock, Geertruida H.; Meeuwsen-De Boer, Tiny G. J.; Van Reijmersdal, Simon; Kuiper, Roland P.; Bradtke, Jutta; et al. (British Journal of Haematology, 2014)
Early recognition of children with chronic phase chronic myeloid leukaemia (CML-CP) at risk for developing a lymphoid blast crisis (LyBC) is desirable, because therapy options in CML-LyBC are limited. We used Multiplex Ligation-dependent Probe Amplification to determine whether B-cell lymphoid leukaemia-specific copy number alterations (CNAs) (e.g. IKZF1, PAX5, CDKN2A deletions) could be detected in CML-CP and may be used to predict disease progression to LyBC. CNAs were detected in all patients with CML-LyBC, but in none of the 77 patients with CML-CP. Based on this study we conclude that CNAs remain a hallmark of disease progression.
EVALuna2:18891

Do the exome: A case of Williams-Beuren syndrome with severe epilepsy due to a truncating de novo variant in GABRA1 - Popp, Bernt; Trollmann, Regina; Büttner, Christian; Caliebe, Almuth; Thiel, Christian; Hüffmeier, Ulrike; Reis, André; Zweier, Christiane (European Journal of Medical Genetics, 2016)
Williams-Beuren syndrome (WBS) is a relatively common, clinically recognizable microdeletion syndrome. In most cases the typical heterozygous deletion of 1.5 Mb on chromosome 7q11.23 spanning about 26 genes can be identified. Also some larger or smaller atypical deletions have been reported and associated with additional or atypical phenotypic aspects. We report on an individual with typical WBS due to the common deletion and with refractory infantile spasms. Using trio-exome sequencing, we identified a de novo truncating variant c.1200del, p (Lys401Serfs*25) in GABRA1 as the likely cause of the early onset epilepsy. This unique case not only allows to further define the phenotypic spectrum of infantile epileptic encephalopathy associated with rare de novo GABRA1 variants but exemplifies the need for a sensitive review of unclear associations in clinically defined syndromes and for extended diagnostic work-up in individuals with unusual presentations of a genetically confirmed diagnosis.
EVALuna2:9310

Drug utilisation on a preterm and neonatal intensive care unit in Germany: A prospective, cohort-based analysis - Neubert, Antje; Lukas, Kristin; Leis, Thomas; Dormann, Harald; Brune, Kay; Rascher, Wolfgang (European Journal of Clinical Pharmacology, 2010)
Purpose: This study aims to describe the drug use on a Neonatal Intensive Care Unit (NICU) at a University Children's Hospital in Germany, to investigate the licensing status of the drugs used and to conclude critical areas in neonatal intensive care to support prioritisation of future research. Methods: An 11-month, prospective cohort study was conducted on the NICU at the University Children's Hospital Erlangen, Germany. All products prescribed during the study period were analysed whether or not the SPC contains information on term and preterm neonates. Results: A total of 183 patients (102 male) with a mean gestational age of 33.6 weeks (minimum=24, maximum=42) were included. The mean length of hospitalisation was 19.4 days (minimum=2, maximum=167). On average, patients received 11.1 drugs (minimum=0, maximum=46). The majority of prescriptions were accounted for by antibiotics (n=515), which were received by 90% of all patients, followed by CNS drugs (n=448) and respiratory drugs (n=306). Of all the different drugs prescribed (n=102) only 38% had information regarding their use in patients aged less than 1 month in their SPC. Analgesics and cardiovascular drugs were prescribed frequently, but without having information for use in neonates. Seventy percent of all patients and 100% of very preterm infants received at least one of these drugs. Conclusions: Treatment strategies on a preterm intensive care unit are complex and little information is available for the drugs used. Analgesics and cardiovascular drugs are of major concern. Efforts will have to be made to conduct well-designed and powered studies in this vulnerable population. © 2009 Springer-Verlag.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Drug utilisation; Neonatal intensive care unit; Neonates; Off-label; Preterm; Unlicensed

Dual pathways to endochondral osteoblasts: a novel chondrocyte-derived osteoprogenitor cell identified in hypertrophic cartilage - Park, Jung; Gebhardt, Matthias; Golovchenko, Svitlana; Perez-Branguli, Francesc; Hattori, Takako; Hartmann, Christine; Zhou, Xin; Decrombrugghe, Benoit; Stock, Michael; Schneider, Holm; Mark, Klaus (Biology Open, 2015)
According to the general understanding, the chondrocyte lineage terminates with the elimination of late hypertrophic cells by apoptosis in the growth plate. However, recent cell tracking studies have shown that murine hypertrophic chondrocytes can survive beyond "terminal" differentiation and give rise to a progeny of osteoblasts participating in endochondral bone formation. The question how chondrocytes convert into osteoblasts, however, remained open. Following the cell fate of hypertrophic chondrocytes by genetic lineage tracing using BACCol10;Cre induced YFP-reporter gene expression we show that a progeny of Col10Cre-reporter labelled osteoprogenitor cells and osteoblasts appears in the primary spongiosa and participates - depending on the developmental stage - substantially in trabecular, endosteal, and cortical bone formation. YFP(+) trabecular and endosteal cells isolated by FACS expressed Col1a1, osteocalcin and runx2, thus confirming their osteogenic phenotype. In searching for transitory cells between hypertrophic chondrocytes and trabecular osteoblasts we identified by confocal microscopy a novel, small YFP(+)Osx(+) cell type with mitotic activity in the lower hypertrophic zone at the chondro-osseous junction. When isolated from growth plates by fractional enzymatic digestion, these cells termed CDOP (chondrocyte-derived osteoprogenitor) cells expressed bone typical genes and differentiated into osteoblasts in vitro. We propose the Col10Cre-labeled CDOP cells mark the initiation point of a second pathway giving rise to endochondral osteoblasts, alternative to perichondrium derived osteoprogenitor cells. These findings add to current concepts of chondrocyte-osteocyte lineages and give new insight into the complex cartilage-bone transition process in the growth plate.
EVALuna2:10200

Dual-source computed tomography of the lung with spectral shaping and advanced iterative reconstruction: potential for maximum radiation dose reduction - Wetzl, Matthias; May, Matthias; Weinmann, Daniel; Hammon, Matthias; Treutlein, Christoph; Zeilinger, Martin; Kiefer, Alexander; Trollmann, Regina; Wölfle, Joachim; Uder, Michael; Rompel, Oliver (Pediatric Radiology, 2020)
Background: Radiation dose at CT should be as low as possible without compromising diagnostic quality. Objective: To assess the potential for maximum dose reduction of pediatric lung dual-source CT with spectral shaping and advanced iterative reconstruction (ADMIRE). Materials and methods: We retrospectively analyzed dual-source CT acquisitions in a full-dose group (FD: 100 kV, 64 reference mAs) and in three groups with spectral shaping and differing reference mAs values (Sn: 100 kV, 96/64/32 reference mAs), each group consisting of 16 patients (age mean 11.5 years, standard deviation 4.8 years, median 12.8 years, range 1.3–18 years). Advanced iterative reconstruction of images was performed with different strengths (FD: ADMIRE Level 2; Sn: ADMIRE Levels 2, 3 and 4). We analyzed dose parameters and measured noise. Diagnostic confidence and detectability of lung lesions as well as anatomical structures were assessed using a Likert scale (from 1 [unacceptable] to 4 [fully acceptable]). Results: Compared to full dose, effective dose was reduced to 16.7% in the Sn 96 group, 11.1% in Sn64, and 5.5% in Sn32 (P<0.001). Noise values of Sn64ADM4 did not statistically differ from those in FDADM2 (45.7 vs. 38.9 Hounsfield units [HU]; P=0.132), whereas noise was significantly higher in Sn32ADM4 compared to Sn64ADM4 (61.5 HU; P<0.001). A Likert score >3 was reached in Sn64ADM4 regarding diagnostic confidence (3.2) and detectability of lung lesions (3.3). For detectability of most anatomical structures, no significant differences were found between FDAM2 and Sn64ADM4 (P≥0.05). Conclusion: In pediatric lung dual-source CT, spectral shaping together with ADMIRE 4 enable radiation dose reduction to about 10% of a full-dose protocol while maintaining an acceptable diagnostic quality.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Adolescents; Advanced iterative reconstruction; Children; Dual-source computed tomography; Lung; Radiation dose reduction; Spectral shaping; Tin prefiltration

DYNC2LI1 mutations broaden the clinical spectrum of dynein-2 defects - Keßler, Kristin; Wunderlich, Ina; Uebe, Steffen; Falk, Nathalie; Gießl, Andreas; Brandstätter, Johann Helmut; Popp, Bernt; Klinger, Patricia; Ekici, Arif Bülent; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Scientific Reports, 2015)
Skeletal ciliopathies are a heterogeneous group of autosomal recessive osteochondrodysplasias caused by defects in formation, maintenance and function of the primary cilium. Mutations in the underlying genes affect the molecular motors, intraflagellar transport complexes (IFT), or the basal body. The more severe phenotypes are caused by defects of genes of the dynein-2 complex, where mutations in DYNC2H1, WDR34 and WDR60 have been identified. In a patient with a Jeune-like phenotype we performed exome sequencing and identified compound heterozygous missense and nonsense mutations in DYNC2LI1 segregating with the phenotype. DYNC2LI1 is ubiquitously expressed and interacts with DYNC2H1 to form the dynein-2 complex important for retrograde IFT. Using DYNC2LI1 siRNA knockdown in fibroblasts we identified a significantly reduced cilia length proposed to affect cilia function. In addition, depletion of DYNC2LI1 induced altered cilia morphology with broadened ciliary tips and accumulation of IFT-B complex proteins in accordance with retrograde IFT defects. Our results expand the clinical spectrum of ciliopathies caused by defects of the dynein-2 complex.
EVALuna2:9281

Early start of growth hormone is associated with positive effects on auxology and metabolism in Prader-Willi-syndrome - Magill, Lucy; Laemmer, Constanze; Wölfle, Joachim; Fimmers, Rolf; Gohlke, Bettina (Orphanet Journal of Rare Diseases, 2020)
Background: Prader-Willi-Syndrome (PWS) is characterized by hypothalamic-pituitary dysfunction. Recent research suggests starting growth hormone-treatment (GHT) as soon as possible. The aim of this study is to analyze possible differences in auxological parameters, carbohydrate and lipid metabolism between two groups of children with PWS that started GHT either during or after their first year of life. Study design: Retrospective longitudinal study of 62 children (31 males) with genetically confirmed PWS. Upon diagnosis all children were offered GHT, some started immediately, others commenced later. Cohort A (n = 21; 11 males) started GHT at 0.3-0.99 yrs. (mean 0.72 yrs) and Cohort B (n = 41; 20 males) commenced GHT at 1.02-2.54 yrs. (mean 1.42 yrs) of age. Fasting morning blood samples and auxological parameters were obtained before the start of therapy and semi-annually thereafter. Differences between the two cohorts were estimated with a linear mixed-effect model. Results: Mean length/height-SDSPWS differed significantly between the groups [1 yr: A: 0.37 (±0.83) vs B: 0.05 (±0.56); 5 yrs.: A: 0.81 (±0.67) vs B: 0.54 (±0.64); p = 0.012]. No significant differences were found in BMI, lean body mass or body fat. Low-density cholesterol was significantly lower in A than in B [LDL: 1 yr: A: 79 (±20) mg/dl vs B: 90 (±19) mg/dl; 5 yrs.: A: 91(±18) mg/dl vs 104 (±26) mg/dl; p = 0.024]. We found significant differences in the glucose homeostasis between the groups [fasting insulin: p = 0.012; HOMA-IR: p = 0.006; HbA1c: p < 0.001; blood glucose: p = 0.022]. Conclusions: An early start of GHT during the first year of life seems to have a favorable effect on height-SDS and metabolic parameters.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Carbohydrate and lipid metabolism; Growth hormone therapy; Insulin-like growth factor-I; Prader-Willi-syndrome

Ectodermal dysplasias: Classification and organization by phenotype, genotype and molecular pathway - Wright, John Timothy; Fete, Mary; Schneider, Holm; Zinser, Madelaine; Koster, Maranke I.; Clarke, Angus J.; Hadj-Rabia, Smail; Tadini, Gianluca; Pagnan, Nina; Visinoni, Atila F.; Bergendal, Birgitta; Abbott, Becky; et al. (American Journal of Medical Genetics Part A, 2019)
An international advisory group met at the National Institutes of Health in Bethesda, Maryland in 2017, to discuss a new classification system for the ectodermal dysplasias (EDs) that would integrate both clinical and molecular information. We propose the following, a working definition of the EDs building on previous classification systems and incorporating current approaches to diagnosis: EDs are genetic conditions affecting the development and/or homeostasis of two or more ectodermal derivatives, including hair, teeth, nails, and certain glands. Genetic variations in genes known to be associated with EDs that affect only one derivative of the ectoderm (attenuated phenotype) will be grouped as non-syndromic traits of the causative gene (e.g., non-syndromic hypodontia or missing teeth associated with pathogenic variants of EDA "ectodysplasin"). Information for categorization and cataloging includes the phenotypic features, Online Mendelian Inheritance in Man number, mode of inheritance, genetic alteration, major developmental pathways involved (e.g., EDA, WNT "wingless-type," TP63 "tumor protein p63") or the components of complex molecular structures (e.g., connexins, keratins, cadherins).
CRIS-Team WoS Importer:2019-02-27

Ectodermal dysplasias: New perspectives on the treatment of so far immedicable genetic disorders - Schneider, Holm (Frontiers in Genetics, 2022)
The past decade has witnessed an expansion of molecular approaches facilitating the differential diagnosis of ectodermal dysplasias, a group of genetic diseases characterized by the lack or malformation of hair, teeth, nails, and certain eccrine glands. Moreover, advances in translational research have increased the therapeutic opportunities for such rare diseases, and new dental, surgical, and ophthalmic treatment options are likely to offer relief to many individuals affected by ectodermal dysplasias. In X-linked hypohidrotic ectodermal dysplasia (XLHED), the genetic deficiency of the signaling molecule ectodysplasin A1 (EDA1) may even be overcome before birth by administration of a recombinant replacement protein. This has been shown at least for the key problem of male subjects with XLHED, the nearly complete absence of sweat glands and perspiration which can lead to life-threatening hyperthermia. Prenatal treatment of six boys by injection of an EDA1 replacement protein into the amniotic fluid consistently induced the development of functional sweat glands. Normal ability to sweat has so far persisted for > 5 years in the two oldest boys treated in utero. Thus, timely replacement of a missing protein appears to be a promising therapeutic strategy for the most frequent ectodermal dysplasia and possibly additional congenital disorders.
CRIS-Team WoS Importer:2022-09-30

Ectodysplasin A1 Deficiency Leads to Osteopetrosis-like Changes in Bones of the Skull Associated with Diminished Osteoclastic Activity - Schweikl, Christine; Maier-Wohlfart, Sigrun; Schneider, Holm; Park, Jung (International Journal of Molecular Sciences, 2022)
Pathogenic variants of the gene Eda cause X-linked hypohidrotic ectodermal dysplasia (XLHED), which is characterized by structural abnormalities or lack of ectodermal appendages. Signs of dysplasia are not restricted to derivatives of the ectodermal layer, but mesodermal abnormalities, such as craniofacial dysmorphism, are also frequently observed, suggesting close reciprocal interactions between the ectoderm and mesoderm; however, a causal link has remained unsubstantiated. We investigated the functional impact of defective ectodysplasin A1 (Eda1) signaling on postnatal bone homeostasis in Eda1-deficient Tabby mice. Interestingly, Eda1 was detected in wild-type mouse calvariae throughout postnatal lifetime. In calvariae, bone-lining Osterix (Osx)+ osteoblasts stained positive for Eda1, and osteoclasts were revealed as Eda receptor (Edar)-positive. Moreover, adult Eda1-deficient calvarial bone showed osteopetrosis-like changes with significantly diminished marrow space, which was maintained during adulthood. Concomitantly with osteopetrosis-like changes, Tabby calvarial bone and Tabby bone marrow-derived osteoclasts had far less osteoclastic activity-associated co-enzymes including cathepsin K, Mmp9, Trap, and Tcirg1 (V-type proton ATPase a3 subunit) compared with wild-type calvariae in vivo or osteoclasts in vitro, indicating that Eda1 deficiency may affect the activity of osteoclasts. Finally, we confirmed that nuclear Nfatc1-positive osteoclasts were strongly diminished during mature osteoclastic differentiation under M-CSF and RANKL in the Tabby model, while Fc-EDA treatment of Tabby-derived osteoclasts significantly increased nuclear translocation of Nfatc1. Furthermore, we identified enhanced Nfatc1 and NF-κB transcriptional activity following Fc-EDA treatment in vitro using luciferase assays. Overall, the results indicate that diminished expressions of osteoclastic activity-associated co-enzymes may lead to disturbed bone homeostasis in Tabby calvariae postnatally.
CRIS-Team Scopus Importer:2022-11-04
Keywords: bone; ectodermal dysplasia; ectodysplasin A1; NF-κB; NFAT; osteoclast differentiation; osteopetrosis

Ectodysplasin A in Biological Fluids and Diagnosis of Ectodermal Dysplasia - Podzus, J.; Kowalczyk-Quintas, C.; Schuepbach-Mallepell, S.; Willen, L.; Staehlin, G.; Vigolo, M.; Tardivel, A.; Headon, D.; Kirby, N.; Mikkola, M. L.; Schneider, Holm; Schneider, P. (Journal of Dental Research, 2017)
The tumor necrosis factor (TNF) family ligand ectodysplasin A (EDA) is produced as 2 full-length splice variants, EDA1 and EDA2, that bind to EDA receptor (EDAR) and X-linked EDA receptor (XEDAR/EDA2R), respectively. Inactivating mutations in Eda or Edar cause hypohidrotic ectodermal dysplasia (HED), a condition characterized by malformations of the teeth, hair and glands, with milder deficiencies affecting only the teeth. EDA acts early during the development of ectodermal appendages-as early as the embryonic placode stage-and plays a role in adult appendage function. In this study, the authors measured EDA in serum, saliva and dried blood spots. The authors detected 3- to 4-fold higher levels of circulating EDA in cord blood than in adult sera. A receptor binding-competent form of EDA1 was the main form of EDA but a minor fraction of EDA2 was also found in fetal bovine serum. Sera of EDA-deficient patients contained either background EDA levels or low levels of EDA that could not bind to recombinant EDAR. The serum of a patient with a V262F missense mutation in Eda, which caused a milder form of X-linked HED (XLHED), contained low levels of EDA capable of binding to EDAR. In 2 mildly affected carriers, intermediate levels of EDA were detected, whereas a severely affected carrier had no active EDA in the serum. Small amounts of EDA were also detectable in normal adult saliva. Finally, EDA could be measured in spots of wild-type adult or cord blood dried onto filter paper at levels significantly higher than that measured in EDA-deficient blood. Measurement of EDA levels combined with receptor-binding assays might be of relevance to aid in the diagnosis of total or partial EDA deficiencies.
EVALuna2:34220

Editorial: Gene, Cell and Protein Replacement Therapy for Genetic Muscle, Bone and Skin Disorders - Schneider, Holm; De Luca, Michele (Frontiers in Genetics, 2021)
CRIS-Team Scopus Importer:2021-11-12
Keywords: duchenne muscular dystrophy (DMD); ectodermal dysplasia; epidermolysis bullosa; gene therapy; myogenic cell transplantation; protein replacement

Effect and safety of treatment with ACE-inhibitor Enalapril and β-blocker metoprolol on the onset of left ventricular dysfunction in Duchenne muscular dystrophy - A randomized, double-blind, placebo-controlled trial - Dittrich, Sven; Graf, Erika; Trollmann, Regina; Neudorf, Ulrich; Schara, Ulrike; Heilmann, Antje; Von Der Hagen, Maja; Stiller, Brigitte; Kirschner, Janbernd; Pozza, Robert Dalla; Müller-Felber, Wolfgang; Weiss, Katja; et al. (Orphanet Journal of Rare Diseases, 2019)
Background: X-linked Duchenne muscular dystrophy (DMD), the most frequent human hereditary skeletal muscle myopathy, inevitably leads to progressive dilated cardiomyopathy. We assessed the effect and safety of a combined treatment with the ACE-inhibitor enalapril and the β-blocker metoprolol in a German cohort of infantile and juvenile DMD patients with preserved left ventricular function. Methods Trial design: Sixteen weeks single-arm open run-in therapy with enalapril and metoprolol followed by a two-arm 1:1 randomized double-blind placebo-controlled treatment in a multicenter setting. Inclusion criteria: DMD boys aged 10-14 years with left ventricular fractional shortening [LV-FS] ≥ 30% in echocardiography. Primary endpoint: time from randomization to first occurrence of LV-FS < 28%. Secondary: changes of a) LV-FS from baseline, b) blood pressure, c), heart rate and autonomic function in ECG and Holter-ECG, e) cardiac biomarkers and neurohumeral serum parameters, f) quality of life, and g) adverse events. Results: From 3/2010 to 12/2013, 38 patients from 10 sites were centrally randomized after run-in, with 21 patients continuing enalapril and metoprolol medication and 17 patients receiving placebo. Until end of study 12/2015, LV-FS < 28% was reached in 6/21 versus 7/17 patients. Cox regression adjusted for LV-FS after run-in showed a statistically non-significant benefit for medication over placebo (hazard ratio: 0.38; 95% confidence interval: 0.12 to 1.22; p = 0.10). Analysis of secondary outcome measures revealed a time-dependent deterioration of LV-FS with no statistically significant differences between the two study arms. Blood pressure, maximal heart rate and mean-NN values were significantly lower at the end of open run-in treatment compared to baseline. Outcome analysis 19 months after randomization displayed significantly lower maximum heart rate and higher noradrenalin and renin values in the intervention group. No difference between treatments was seen for quality of life. As a single, yet important adverse event, the reversible deterioration of walking abilities of one DMD patient during the run-in period was observed. Conclusions: Our analysis of enalapril and metoprolol treatment in DMD patients with preserved left ventricular function is suggestive to delay the progression of the intrinsic cardiomyopathy to left ventricular failure, but did not reach statistical significance, probably due to insufficient sample size. Clinical trial registration: DRKS-number 00000115, EudraCT-number 2009-009871-36.
CRIS-Team Scopus Importer:2019-05-21
Keywords: ACE-inhibitors; Cardiomyopathy; Duchenne muscular dystrophy; ß-blockers

Effectiveness and safety of rhIGF1 therapy in patients with or without Laron syndrome - Bang, Peter; Wölfle, Joachim; Perrot, Valerie; Sert, Caroline; Polak, Michel (European Journal of Endocrinology, 2021)
Objective: The European Increlex® Growth Forum Database Registry monitors the effectiveness and safety of recombinant human insulin-like growth factor-1 (rhIGF1; mecasermin, Increlex®) therapy in patients with severe primary IGF1 deficiency (SPIGFD). We present data from patients with and without a reported genetic diagnosis of Laron syndrome (LS). Design: Ongoing, open-label, observational registry (NCT00903110). Methods: Children and adolescents receiving rhIGF1 therapy from 10 European countries were enrolled in 2008-2017 (n = 242). The treatment-naïve/prepubertal (NPP) cohort (n = 138) was divided into subgroups based on reported genetic diagnosis of LS (n = 21) or non-LS (n = 117). Multivariate analysis of the NPP-non-LS subgroup was conducted to identify factors predictive of growth response (first-year-height standard deviation score (SDS) gain ≥ 0.3). Assessments included change in height and weight over 5 years and adverse events (AEs). Results: Height SDS gain from baseline was greater in the NPP-LS than the NPP-non-LS subgroup after 1 years' treatment (P < 0.05). In the NPP-non-LS subgroup, 56% were responders; young age at baseline was a positive independent predictive factor (P < 0.001). NPP-non-LS-responders and the NPP-LS subgroup had a similar mean age (6.07 years vs 7.00 years) at baseline and height SDS gain in year 1 (0.64 vs 0.70), although NPP-non-LS-responders were taller (P < 0.001) at baseline. BMI SDS changes did not differ across subgroups. Treatment-emergent AEs were experienced by 65.3% of patients; hypoglycaemia was most common. Conclusions: In most NPP children with SPIGFD, with or without LS, rhIGF1 therapy promotes linear growth. The safety profile was consistent with previous studies.
CRIS-Team Scopus Importer:2021-02-05

Effectiveness of structured, multidisciplinary long-term care for pediatric cancer survivors: protocol of the multicenter, randomized-controlled AELKI study - Schmidt, Hannah; Baust, Katja; Calaminus, Gabriele; Hohls, Lisa; Tetzner, Katharina; Griech, Nicole; Haugke, Henrike; Baltus, Hannah; Elsner, Susanne; Katalinic, Alexander; Becker, Hera; Cytera, Chirine; et al. (Trials, 2024)
Background: In Germany, around 2.250 children and adolescents are diagnosed with cancer each year. Despite generally positive long-term survival rates, many patients must cope with late effects of the disease and its treatment. This highlights the need for a well-structured, long-term approach addressing both physical and mental health issues. Currently, the German healthcare system lacks such comprehensive structures. Our study aims to evaluate the effectiveness of a structured, multidisciplinary long-term approach compared to conventional “treatment as usual” (TAU). Methods: A prospective, multicenter study with ten pediatric university clinics in Germany will be conducted. The cluster-randomization takes place at the clinic level. Children and adolescents who completed their cancer treatment at least five years ago and their parents will be eligible to participate. While the control group (CG) receives TAU, the intervention group (IG) participates in a structured program. This program includes risk-based medical treatment and psychosocial interventions tailored to each patient’s individual needs within a two-month timeframe. The primary outcome is the improvement of self-efficacy. Secondary outcomes are satisfaction with health care, improvement of health-related quality of life (HRQoL), reduction of mental health problems, and improvement of transition readiness. Discussion: This approach has the potential to optimize the health care for individuals who survived cancer during childhood or adolescence. It addresses the challenges of overuse, underuse, and misuse of health care resources. By considering both medical and psychosocial factors and promoting increased self-efficacy, independent from parental involvement, it may facilitate a smoother transition to adult medicine and enhance adherence to lifelong aftercare. If proven successful, this approach will contribute to the integration of multidisciplinary strategies into standard healthcare practice. Trial registration: German Clinical Trials Register DRKS00029269. Registered on December 23, 2022.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Cancer; Children and adolescent; Long-term care; Multidisciplinary; Psychosocial

Effect of nusinersen on motor, respiratory and bulbar function in early-onset spinal muscular atrophy - Pechmann, Astrid; Behrens, Max; Doernbrack, Katharina; Tassoni, Adrian; Stein, Sabine; Vogt, Sibylle; Zoeller, Daniela; Bernert, Gunther; Hagenacker, Tim; Schara-Schmidt, Ulrike; Schwersenz, Inge; Walter, Maggie C.; et al. (Brain, 2022)
5q-associated spinal muscular atrophy is a rare neuromuscular disorder with the leading symptom of a proximal muscle weakness. Three different drugs have been approved by the European Medicines Agency and Food and Drug Administration for the treatment of spinal muscular atrophy patients, however, long-term experience is still scarce. In contrast to clinical trial data with restricted patient populations and short observation periods, we report here real-world evidence on a broad spectrum of patients with early-onset spinal muscular atrophy treated with nusinersen focusing on effects regarding motor milestones, and respiratory and bulbar insufficiency during the first years of treatment. Within the SMArtCARE registry, all patients under treatment with nusinersen who never had the ability to sit independently before the start of treatment were identified for data analysis. The primary outcome of this analysis was the change in motor function evaluated with the Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders and motor milestones considering World Health Organization criteria. Further, we evaluated data on the need for ventilator support and tube feeding, and mortality. In total, 143 patients with early-onset spinal muscular atrophy were included in the data analysis with a follow-up period of up to 38 months. We observed major improvements in motor function evaluated with the Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders. Improvements were greater in children >2 years of age at start of treatment than in older children. 24.5% of children gained the ability to sit independently. Major improvements were observed during the first 14 months of treatment. The need for intermittent ventilator support and tube feeding increased despite treatment with nusinersen. Our findings confirm the increasing real-world evidence that treatment with nusinersen has a dramatic influence on disease progression and survival in patients with early-onset spinal muscular atrophy. Major improvements in motor function are seen in children younger than 2 years at the start of treatment. Bulbar and respiratory function needs to be closely monitored, as these functions do not improve equivalent to motor function.
CRIS-Team WoS Importer:2023-01-27

Effect of Psychosocial Factors on Growth - Gohlke, Bettina C.; Bettendorf, Markus; Binder, Gerhard; Hauffa, Berthold; Reinehr, Thomas; Dörr, Helmuth-Günther; Wölfle, Joachim (Klinische Pädiatrie, 2021)
Background Genes, hormones and factors such as nutrition and psychosocial environment affect growth. Objective What is the significance of various psychosocial factors on growth? Methods Evaluation of results of a working meeting of paediatric endocrinologist with current literature research. Results Psychosocial deprivation in children can be associated with growth hormone deficiency (GHD) and short stature. GHD can be reversed by a change of environment and psychosocial support. War and migration are often associated with underweight, growth disturbances and poor health care. These factors can improve after the end of conflicts, but children often remain too short. Consumption of alcohol or opiates during pregnancy are associated with lower birth weight and increased risk of early and small for gestational age (SGA) childbirth. Children with attention deficit hyperactivity disorder show a slight slowdown in growth after they started stimulant therapy. However, they reach normal adult height. Conclusions In children with idiopathic short stature, psychosocial causes should be taken into account in the differential diagnosis. Notably there is an increased risk of growth disturbances in children from conflict regions or after prenatal drug exposure.
CRIS-Team WoS Importer:2021-12-24

Effects of Levetiracetam and Sulthiame on EEG in benign epilepsy with centrotemporal spikes: A randomized controlled trial - Tacke, Moritz; Borggraefe, Ingo; Gerstl, Lucia; Heinen, Florian; Vill, Katharina; Bonfert, Michaela; Bast, Thomas; Neubauer, Bernd Axel; Baumeister, Friedrich; Baethmann, Martina; Bentele, Karl; Blank, Christian; et al. (Seizure-European Journal of Epilepsy, 2018)
PURPOSE: BECTS (benign childhood epilepsy with centrotemporal spikes) is associated with characteristic EEG findings. This study examines the influence of anti-convulsive treatment on the EEG. METHODS: In a randomized controlled trial including 43 children with BECTS, EEGs were performed prior to treatment with either Sulthiame or Levetiracetam as well as three times under treatment. Using the spike-wave-index, the degree of EEG pathology was quantified. The EEG before and after initiation of treatment was analyzed. Both treatment arms were compared and the EEG of the children that were to develop recurrent seizures was compared with those that were successfully treated. RESULTS: Regardless of the treatment agent, the spike-wave-index was reduced significantly under treatment. There were no differences between the two treatment groups. In an additional analysis, the EEG characteristics of the children with recurrent seizures differed statistically significant from those that did not have any further seizures. CONCLUSION: Both Sulthiame and Levetiracetam influence the EEG of children with BECTS. Persistent EEG pathologies are associated with treatment failures.
EVALuna2:35718

Effects of the STAMP-inhibitor asciminib on T cell activation and metabolic fitness compared to tyrosine kinase inhibition by imatinib, dasatinib, and nilotinib - Häselbarth, Lukas; Karow, Axel; Mentz, Kristin; Böttcher, Martin; Roche-Lancaster, Oisin; Krumbholz, Manuela; Jitschin, Regina; Mougiakakos, Dimitrios; Metzler, Markus (Cancer Immunology, Immunotherapy, 2023)
T cell function is central to immune reconstitution and control of residual chronic myeloid leukemia (CML) cells after treatment initiation and is associated with achieving deep molecular response as a prerequisite for treatment-free remission, the ultimate therapeutic goal in CML. ATP-pocket-binding tyrosine kinase inhibitors (TKIs) like imatinib, dasatinib, and nilotinib are widely used for treating CML, but they have shown to inhibit T cell function as an “off-target” effect. Therefore, we tested asciminib, the first-in-class BCR::ABL1 fusion protein inhibitor specifically targeting the ABL myristoyl pocket (STAMP) and compared its effects on T cell function with imatinib, dasatinib, and nilotinib. Whereas all four TKIs inhibited the expression of the co-stimulatory protein CD28, the amino acid transporter CD98, proliferation, and secretion of pro-inflammatory cytokines IFNγ, IL-6, and IL-17A upon T cell stimulation, asciminib had less impact on PD-1, activation markers, and IL-2 secretion. T cells treated with asciminib and the other TKIs maintained their ability to mobilize their respiratory capacity and glycolytic reserve, which is an important surrogate for metabolic fitness and flexibility. Overall, we found milder inhibitory effects of asciminib on T cell activation, which might be beneficial for the immunological control of residual CML cells.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Activity; Asciminib; CML; Metabolism; T cell; TKI

Efficacy and safety of gene therapy with onasemnogene abeparvovec in children with spinal muscular atrophy in the D-A-CH-region: a population-based observational study - Weiß, Claudia; Becker, Lena Luise; Friese, Johannes; Blaschek, Astrid; Hahn, Andreas; Illsinger, Sabine; Schwartz, Oliver; Bernert, Günther; Hagen, Maja von der; Husain, Ralf A.; Goldhahn, Klaus; Kirschner, Janbernd; et al. (The Lancet Regional Health - Europe, 2024)
Background: Real-world data on gene addition therapy (GAT) with onasemnogene abeparvovec (OA), including all age groups and with or without symptoms of the disease before treatment are needed to provide families with evidence-based advice and realistic therapeutic goals. Aim of this study is therefore a population-based analysis of all patients with SMA treated with OA across Germany, Austria and Switzerland (D-A-CH). Methods: This observational study included individuals with Spinal Muscular Atrophy (SMA) treated with OA in 29 specialized neuromuscular centers in the D-A-CH-region. A standardized data set including WHO gross motor milestones, SMA validated motor assessments, need for nutritional and respiratory support, and adverse events was collected using the SMArtCARE registry and the Swiss-Reg-NMD. Outcome data were analyzed using a prespecified statistical analysis plan including potential predictors such as age at GAT, SMN2 copy number, past treatment, and symptom status. Findings: 343 individuals with SMA (46% male, 54% female) with a mean age at OA of 14.0 months (range 0–90, IQR 20.0 months) were included in the analysis. 79 (23%) patients were clinically presymptomatic at the time of treatment. 172 (50%) patients received SMN2 splice-modifying drugs prior to GAT (risdiplam: n = 16, nusinersen: n = 154, both: n = 2). Functional motor improvement correlated with lower age at GAT, with the best motor outcome in those younger than 6 weeks, carrying 3 SMN2 copies, and being clinically presymptomatic at time of treatment. The likelihood of requiring ventilation or nutritional support showed a significantly increase with older age at the time of GAT and remained stable thereafter. Pre-treatment had no effect on disease trajectories. Liver-related adverse events occurred significantly less frequently up to 8 months of age. All other adverse events showed an even distribution across all age and weight groups. Interpretation: Overall, motor, respiratory, and nutritional outcome were dependent on timing of GAT and initial symptom status. It was best in presymptomatic children treated within the first six weeks of life, but functional motor scores also increased significantly after treatment in all age groups up to 24 months. Additionally, OA was best tolerated when administered at a young age. Our study therefore highlights the need for SMA newborn screening and immediate treatment to achieve the best possible benefit-risk ratio. Funding: The SMArtCARE and Swiss-Reg-NMD registries are funded by different sources (see acknowledgements).
CRIS-Team Scopus Importer:2024-10-18
Keywords: Gene addition therapy; Gene therapy; Onasemnogene abeparvovec; SMA; Spinal muscular atrophy; Zolgensma

Efficacy, Retention and Tolerability of Everolimus in Patients with Tuberous Sclerosis Complex: A Survey-Based Study on Patients' Perspectives - Willems, Laurent M.; Rosenow, Felix; Schubert-Bast, Susanne; Kurlemann, Gerhard; Zoellner, Johann Philipp; Bast, Thomas; Bertsche, Astrid; Bettendorf, Ulrich; Ebrahimi-Fakhari, Daniel; Grau, Janina; Hahn, Andreas; Hartmann, Hans; et al. (Cns Drugs, 2021)
Background The approval of everolimus (EVE) for the treatment of angiomyolipoma (2013), subependymal giant cell astrocytoma (2013) and drug-refractory epilepsy (2017) in patients with tuberous sclerosis complex (TSC) represents the first disease-modifying treatment option available for this rare and complex genetic disorder. Objective The objective of this study was to analyse the use, efficacy, tolerability and treatment retention of EVE in patients with TSC in Germany from the patient's perspective. Methods A structured cross-age survey was conducted at 26 specialised TSC centres in Germany and by the German TSC patient advocacy group between February and July 2019, enrolling children, adolescents and adult patients with TSC. Results Of 365 participants, 36.7% (n = 134) reported the current or past intake of EVE, including 31.5% (n = 115) who were taking EVE at study entry. The mean EVE dosage was 6.1 +/- 2.9 mg/m(2) (median: 5.6 mg/m(2), range 2.0-15.1 mg/m(2)) in children and adolescents and 4 +/- 2.1 mg/m(2) (median: 3.7 mg/m(2), range 0.8-10.1 mg/m(2)) in adult patients. An early diagnosis of TSC, the presence of angiomyolipoma, drug-refractory epilepsy, neuropsychiatric manifestations, subependymal giant cell astrocytoma, cardiac rhabdomyoma and overall multi-organ involvement were associated with the use of EVE as a disease-modifying treatment. The reported efficacy was 64.0% for angiomyolipoma (75% in adult patients), 66.2% for drug-refractory epilepsy, and 54.4% for subependymal giant cell astrocytoma. The overall retention rate for EVE was 85.8%. The retention rates after 12 months of EVE therapy were higher among adults (93.7%) than among children and adolescents (88.7%; 90.5% vs 77.4% after 24 months; 87.3% vs 77.4% after 36 months). Tolerability was acceptable, with 70.9% of patients overall reporting adverse events, including stomatitis (47.0%), acne-like rash (7.7%), increased susceptibility to common infections and lymphoedema (each 6.0%), which were the most frequently reported symptoms. With a total score of 41.7 compared with 36.8 among patients not taking EVE, patients currently being treated with EVE showed an increased Liverpool Adverse Event Profile. Noticeable deviations in the sub-items 'tiredness', 'skin problems' and 'mouth/gum problems', which are likely related to EVE-typical adverse effects, were more frequently reported among patients taking EVE. Conclusions From the patients' perspective, EVE is an effective and relatively well-tolerated disease-modifying treatment option for children, adolescents and adults with TSC, associated with a high long-term retention rate that can be individually considered for each patient. Everolimus therapy should ideally be supervised by a centre experienced in the use of mechanistic target of rapamycin inhibitors, and adverse effects should be monitored on a regular basis.
CRIS-Team WoS Importer:2021-07-30

Efficacy, tolerability, and retention of fenfluramine for the treatment of seizures in patients with Dravet syndrome: Compassionate use program in Germany - Strzelczyk, Adam; Pringsheim, Milka; Mayer, Thomas; Polster, Tilman; Klotz, Kerstin A.; Muhle, Hiltrud; Alber, Michael; Trollmann, Regina; Spors, Hartwig; Kluger, Gerhard; Kurlemann, Gerhard; Schubert-Bast, Susanne (Epilepsia, 2021)
Objective: Dravet syndrome (DS) is a rare but severe drug-resistant epilepsy. Before the approval of fenfluramine (FFA) for the treatment of seizures in DS, patients in Germany could receive treatment under a compassionate use program (CUP). Methods: We conducted a multicenter, retrospective, observational study to describe the efficacy, tolerability, and retention of FFA within the CUP. Patients received add-on therapy with oral FFA gradually titrated to a target dose between.13 and.7 mg/kg/day. Results: Overall, 78 patients with DS (median age = 8.0 years, range = 2.1–46.0; 53% female, median concomitant antiseizure medications [ASMs] = 3) were treated with FFA for a median duration of 255.5 days (range = 31–572). Responder rates (a ≥50% reduction; n = 78) and seizure-freedom rates at 3 months were 68% and 14% for total seizures, respectively, and 67% and 23% for generalized tonic–clonic seizures. Responder rates were consistent at 6 and 12 months (n = 66 and n = 43, respectively). Median seizure days per month significantly decreased from 10.0 (range =.5–30) to 3.0 (range = 0–30) in the 3-month period before and after FFA treatment (p <.001). Significantly fewer patients reported at least one episode of status epilepticus (28% vs. 14% patients before and after FFA initiation, p =.005). During FFA treatment, 35 (45%) patients were able to discontinue a concomitant ASM. At the last follow-up date, 66 (85%) patients remained on treatment with FFA. The most common adverse events were somnolence (36%), decreased appetite (22%), and ataxia (8%). Forty-eight (62%) patients were reported as having a meaningful global clinical improvement. Significance: In a large cohort of patients, FFA demonstrated efficacy across a range of outcomes including clinically significant reductions in convulsive seizures, and was well tolerated, providing valuable information for real-world practice.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Clinical Global Impression of Change; convulsive seizures; Dravet syndrome; fenfluramine; real-world; status epilepticus

Efficiency of translation termination in humans is highly dependent upon nucleotides in the neighbourhood of a (premature) termination codon - Pacho, Frederic; Zambruno, Giovanna; Calabresi, Valentina; Kiritsi, Dimitra; Schneider, Holm (Journal of Medical Genetics, 2011)
Background Spontaneous read-through of a premature termination codon (PTC) has so far not been observed in patients carrying nonsense mutations. This report describes a patient with junctional epidermolysis bullosa who was expected to die because of compound heterozygous nonsense mutations in the gene LAMA3 (R943X/R1159X), but was rescued by spontaneous readthrough of the R943X allele. Results and conclusion FACS analysis of cells carrying various PTCs surrounded by their natural neighbouring codons revealed significant reporter gene expression despite the PTC only for this patient's genetic context. Gene expression could be abolished by replacing the first or third nucleotide before, or one of the two nucleotides following the PTC. Site-directed mutagenesis was used to identify genotypes allowing PTC read-through. The genetic context of the LAMA3 mutation R943X is close to a hypothetical consensus sequence for maximum PTC read-through. Bioinformatic analysis showed that this consensus sequence is present in four sequences from the NCBI reference database, each of which contains another in-frame termination codon three or four codons apart. This indicates strong selective pressure against leaky termination codons in the human genome. This patient's mutated full length mRNA escaped nonsensemediated decay, leading to LAMA3 mRNA levels similar to those of a healthy control, and full length laminin a3 could be detected in culture supernatant of the patient's keratinocytes. Immunofluorescence analyses of skin biopsies and continuous clinical improvement of the patient's condition suggested accumulation of intact laminin-332 in the epidermal basement membrane. These findings provide important clues for the prediction of PTC read-through in human genetic disease.
CRIS-Team Scopus Importer:2020-07-01

Einstufung des Grades der Schwerbehinderung bei Kindern und Jugendlichen mit Chronischer Myeloischer Leukämie - Suttorp, Meinolf; Sembill, Stephanie; Metzler, Markus (TumorDiagnostik & Therapie, 2021)
Background CML comprises only 2-3% of all diagnosed pediatric leukemias. Mostly diagnosed in chronic phase (CML-CP), the disease progresses without treatment to accelerated phase (CML-AP) and finally to life-limiting blastic phase (CML-BP). Contrasting the therapy of other leukemia types, CML-CP is not treated by intense chemotherapy but with oral drugs -termed tyrosine kinase inhibitors (TKI)- for an unlimited duration. This therapy may be associated with general and developmentalspecific side effects. The rarity of pediatric-CML is limiting the experience in assessment of the disability rating (DR) as an administrative health authority procedure. Methods A questionnaire was sent out evaluating the procedures and results associated with the application of a disabled person's pass. Results 34 out of 70 patients (49%; median age 11 yrs., range 3-17 yrs.; CML-CP/-AP/-BP: N=28/3/3) replied to the questionnaire. Median duration of TKI therapy was 33 months (range 4-163) and associated in 71% (24/34) of the patients with side effects. 5/34 (15%) patients did not apply for a pass. DR 100 was assigned to all patients with CML-BP and to 2/3 patients with CML-AP; the 3rd patient was assigned DR 60. In the 21 patients with CML-CP the assigned DR varied from 20-100; 9/28 patients (32%) were assigned to DR 50. Special identifier label H (helpless) was assigned to 5/28 patients (18%) with CML-CP. Conclusion Compared to other pediatric malignancies, the broad range of DR in CML-CP points to unsureness when assessing the limitations exerted by the disease and its therapy. Guidelines for adults with CML offer little orientation only as pediatric patients frequently suffer from developmental-specific side effects.
Created from Fastlane, Scopus look-up
Keywords: Chronic Myeloid Leukemia; disability rating; Pediatric CML; TKI side Effects

Ektope Lage einer Schilddrüse im Zungengrund – Zufallsdiagnose bei einem 6‑jährigen Mädchen - Albrecht, Andrea; Penger, Theresa; Marx, Martin; Jüngert, Jörg M.; Kuwert, Torsten; Dörr, Helmuth-Günther (Monatsschrift Kinderheilkunde, 2020)
Background: An ectopic thyroid gland is a rare anomaly due to the incomplete descent of the thyroid gland during the embryonic developmental migration process. The ectopic thyroid tissue is normally located in the area from the tongue to the diaphragm but lingual and sublingual locations preferentially occur. In a child with congenital hypothyroidism, which was detected during neonatal screening, the ectopic gland could be diagnosed during the further clarification. Case report: This article reports on the case of a girl who was presented to the pediatrician for clarification of chronic abdominal pain at the age of 6 years and 3 months. As an incidental finding the pediatrician diagnosed a subclinical hypothyroidism (serum TSH 23.3 mU/l, fT3 and fT4 normal) and initiated treatment with L‑thyroxine (L-T4). The psychomotor, growth and weight development had always been age-appropriate. At the initial presentation in this outpatient department the girl was 6 years and 5 months old, was clinically and biochemically euthyroid, and the body measurements were normal. The thyroid autoantibodies were inconspicuous. The ultrasound scan revealed a small lingual thyroid-like tissue (volume 0.9 ml) with no thyroid tissue in the typical site. A thyroid scintigraphy confirmed the diagnosis. Under the weight-adapted medication with L‑thyroxine the patient never developed symptoms of hypothyroidism and the volume of the lingual thyroid did not increase. The patient is currently 11 years and 8 months old (height 146.9 cm, weight 33.3 kg, Tanner stage B 2) and attends a grammar school. Conclusion: A thyroid gland at the base of the tongue is a rare cause of latent hypothyroidism and is difficult to diagnose when there is a lack of clinical symptoms. It can be detected at any age as an incidental finding.
CRIS-Team Scopus Importer:2020-05-05
Keywords: Ectopic lingual thyroid; Incidental finding; Rare disease; Subclinical hypothyroidism; Thyroid ultrasound

Electric Field-Induced Osteogenic Differentiation on TiO2 Nanotubular Layer - Park, Jung Hyun; Mazare, Anca Valentina; Schneider, Holm; Mark, Klaus; Fischer, Michael; Schmuki, Patrik (Tissue Engineering - Part C: Methods, 2016)
On biocompatible implant surfaces, cellular behavior and fate of stem cells are determined not only by microenvironmental signals but also by electrochemical signals. The potential of electric fields (EFs) to stimulate bone growth and bone healing has been widely demonstrated, but the molecular mechanism linking EFs to osteogenic differentiation has remained elusive. Here we show that constant EFs triggered osteogenic induction of mesenchymal stem cells (MSCs) on a defined nanotubular TiO2 substrate. EFs stimulate the formation of plasma membrane protrusions and the transport of connexin 43 to these protrusions. Connexin 43 is required for the EF-induced lasting intracellular calcium increase, which rapidly propagates to neighboring cells by gap junctions. This enables simultaneous osteogenic induction following downstream calcineurin/CAMKII/NFAT signaling. We propose that connexin 43-mediated, EF-induced osteogenic differentiation of MSCs on a defined nanotubular titanium oxide surface may give new insight on therapeutic interventions for bone regeneration and tissue engineering approaches.
EVALuna2:10221

Elexacaftor – Tezacaftor – Ivacaftor treatment improves systemic infection parameters and Pseudomonas aeruginosa colonization rate in patients with cystic fibrosis a monocentric observational study - Schnell, Alexander; Hober, Hannah; Kaiser, Natalie; Ruppel, Renate; Geppert, Annika; Tremel, Christina; Sobel, Julia; Plattner, Erika; Wölfle, Joachim; Hörning, André (Heliyon, 2023)
Background & aims: The CFTR-modulating therapy Elexaftor – Tezacaftor - Ivacaftor (ETI) has been widely prescribed since its approval in 2020 in the European Union. The aim of this study was to methodically evaluate the effects of an ETI treatment on clinical, biochemical data and Pseudomonas colonization in order to demonstrate its efficacy. Methods: This prospective monocentric study comprised 69 patients diagnosed with cystic fibrosis aged at least 12 years and treated with ETI between September 2020 and November 2021. Clinical and laboratory data of each patient and study visit were collected before and after 24 weeks of ETI treatment. Follow-up status of Pseudomonas aeruginosa (PsA) colonization was assessed after one year of therapy by regularly determined sputum or throat swab samples. Results: Marked improvements biochemical markers of systemic inflammation as white blood cell count, levels of immunoglobulins A, G and M and albumin within 24 weeks of therapy were observed. ETI treatment proved to be effective as seen by amelioration of lung function and sweat chloride concentration. Assessment of PsA colonization status revealed a conversion from a positive to negative detection in 36% of the cases after one year of therapy. Conclusions: ETI treatment effectively improves systemic inflammation parameters and shows promising results in PsA status conversion.
CRIS-Team Scopus Importer:2023-06-02
Keywords: CFTR modulator; Clinical data; Cystic fibrosis; Elexacaftor; ETI; Inflammation markers; Ivacaftor; Kaftrio; Tezacaftor

ENGRAFTMENT, DIFFERENTIATION AND BIOLOGICAL EFFECTS OF CORD BLOOD-DERIVED CLONAL CELLS ADMINISTERED INTRAVENOUSLY TO NEWBORN RATS WITH HYPOXIC-ISCHEMIC BRAIN INJURY - Yang, Xiaojun; Griesmaier, E.; Wegleiter, K.; Schlager, G. W.; Weisbach, Volker Günter; Keller, M.; Park, J.; Schneider, Holm (2016)
EVALuna2:34012

Epidemiology of inherited epidermolysis bullosa in Germany - Has, Cristina; Hess, Moritz; Anemueller, Waltraud; Blume-Peytavi, Ulrike; Emmert, Steffen; Foelster-Holst, Regina; Frank, Jorge; Giehl, Kathrin; Guenther, Claudia; Hammersen, Johanna; Hillmann, Kathrin; Hoeflein, Bettina; et al. (Journal of the European Academy of Dermatology and Venereology, 2022)
Background Epidermolysis bullosa (EB) is a rare genetic disorder manifesting with skin and mucosal membrane blistering in different degrees of severity. Objective Epidemiological data from different countries have been published, but none are available from Germany. Methods In this population-based cross-sectional study, people living with EB in Germany were identified using the following sources: academic hospitals, diagnostic laboratories and patient organization. Results Our study indicates an overall EB incidence of 45 per million live births in Germany. With 14.23 per million live births for junctional EB, the incidence is higher than in other countries, possibly reflecting the availability of early molecular genetic diagnostics in severely affected neonates. Dystrophic EB was assessed at 15.58 cases per million live births. The relatively low incidence found for EB simplex, 14.93 per million live births, could be explained by late or missed diagnosis, but also by 33% of cases remaining not otherwise specified. Using log-linear models, we estimated a prevalence of 54 per million for all EB types, 2.44 for junctional EB, 12.16 for dystrophic EB and 28.44 per million for EB simplex. These figures are comparable to previously reported data from other countries. Conclusions Altogether, there are at least 2000 patients with EB in the German population. These results should support national policies and pharmaceutical companies in decision-making, allow more precise planning of drug development and clinical trials, and aid patient advocacy groups in their effort to improve quality of life of people with this orphan disease.
CRIS-Team WoS Importer:2022-11-11

Epidemiology of inherited Epidermolysis bullosa in Germany - Has, Cristina; Hess, Moritz; Anemueller, Waltraud; Blume-Peytavi, Ulrike; Emmert, Steffen; Foelster-Holst, Regina; Frank, Jorge; Giehl, Kathrin; Günther, Claudia; Hammersen, Johanna; Hillmann, Kathrin; Hoeflein, Bettina; et al. (Journal of the European Academy of Dermatology and Venereology, 2023)

Equal cerebral perfusion during extended aortic coarctation repair - Rüffer, André; Knieling, Ferdinand; Cesnjevar, Robert; Regensburger, Adrian; Purbojo, Ariawan; Dittrich, Sven; Münch, Frank; Wölfle, Joachim; Jüngert, Jörg M. (European Journal of Cardio-Thoracic Surgery, 2021)
OBJECTIVES: Aortic coarctation with distal aortic arch hypoplasia can be effectively addressed by coarctation resection with extended end-to-end-anastomosis (REEEA). Particularly, when unilateral cerebral perfusion (UCP) is established by clamping of left-sided supra-aortic vessels, the extent of cerebral blood flow distribution during repair remains undetermined, so far. Transfontanellar contrast-enhanced ultrasound (T-CEUS) can be utilized for real-time visualization and quantitative evaluation of cerebral blood flow. This study quantitatively evaluates cerebral perfusion during REEEA by using intraoperative T-CEUS. METHODS: In a prospective study, 9 infants with open fontanelle undergoing REEEA [median age: 13 days (range 1-34) and median weight 3.1 kg (range 2.2-4.4)] were intraoperatively examined with T-CEUS at 3 consecutive time-points: before skin incision, during UCP and after skin suture. A software-based analysis of 11 parameters was used for data evaluation. Absolute and relative blood flow in contralateral hemispheres was measured in side-by-side comparison, and referenced to baseline measurements. RESULTS: No side-depend absolute or relative cerebral perfusion differences were found during REEEA, except for an increased relative 'wash-out-rate' (P = 0.0013) in favour of the right hemisphere after surgery. Compared to ipsilateral baseline levels, 'rise time' was transiently increased in right (P = 0.0277) and 'time-to-peak' in both hemispheres (right: P = 0.0403 and left: P = 0.0286), all during UCP. CONCLUSIONS: The use of T-CEUS provided evidence for homogenous distribution of contrast agent in both hemispheres during UCP. T-CEUS can be utilized for the postprocedural evaluation of cerebral perfusion during congenital cardiac surgery. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov Unique, Identifier: NCT03215628.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Aortic coarctation; Cerebral perfusion; Extended end-to-end-anastomosis

Erratum: Zahn et al. Manipulation of medicinal products for oral administration to paediatric patients at a german university hospital: An observational study. Pharmaceutics 2020, 12, 583 - Zahn, Julia; Hörning, André; Trollmann, Regina; Rascher, Wolfgang; Neubert, Antje (Pharmaceutics, 2021)
The authors wish to make the following corrections to the affiliation and acknowledgments part [1]. The affiliation of all of the authors of “Department of Paediatrics and Adolescent Medicine, Universitätsklinikum Erlangen, 91054 Erlangen, Germany”, should be “Department of Paediatrics and Adolescent Medicine, Universitätsklinikum Erlangen, Friedrich-Alexander-Universität Erlangen-Nürnberg (FAU), 91054 Erlangen, Germany”. The updated “Acknowledgments” section is as follows “The authors would like to thank the nursing staff for a valuable exchange on the subject of manipulation and the opportunity to observe dispensing of medicines in clinical practice. The present work was performed in (partial) fulfilment of the requirements for obtaining the degree Dr. rer. biol. hum.”. The authors would like to apologize for any inconvenience caused to the readers by these changes.
CRIS-Team Scopus Importer:2021-08-06

Erster epileptischer Anfall und Epilepsien im Erwachsenenalter: Kurzfassung S2k-Leitlinie der Deutschen Gesellschaft für Neurologie in Zusammenarbeit mit der Deutschen Gesellschaft für Epileptologie - Holtkamp, Martin; May, Theodor W.; Berkenfeld, Ralf; Bien, Christian G.; Coban, Ingrid; Knake, Susanne; Michaelis, Rosa; Rémi, Jan; Seeck, Margitta; Surges, Rainer; Weber, Yvonne; Baum, Petra; et al. (Clinical Epileptology, 2024)
The new S2k guideline “First epileptic seizure and epilepsies in adulthood” provides recommendations on clinically relevant issues in five major topics: management of first epileptic seizures, pharmacotherapy, epilepsy surgery, complementary and supportive treatment, and psychosocial aspects. For the topic management of first epileptic seizures, the guideline provides recommendations on identifying the two major differential diagnoses, syncope and psychogenic non-epileptic seizure. The importance of additional examinations such as EEG, MRI and cerebrospinal fluid for syndromic classification and etiological allocation is discussed. Recommendations on neuropsychological and psychiatric screening tests are also given. The topic pharmacotherapy issues recommendations on antiseizure medication in monotherapy for focal, generalized and unclassified epilepsies; patient groups with special challenges such as the aged, women of childbearing potential and people with mental retardation are emphasized. Further issues are indications for measuring serum concentrations of antiseizure medication and possible risks of switching manufacturers. In the topic epilepsy surgery, indications for presurgical assessment and the multiple therapeutic approaches, such as resection, laser ablation, and neurostimulation are presented. Recommendations on postoperative management of patients, including rehabilitation and psychosocial counselling, are given. The topic complementary and supportive therapeutic approaches comprises recommendations on the diagnostics and treatment of common psychiatric comorbidities of epilepsy, such as anxiety disorder, depression and psychosis. Another important issue is the management of psychogenic non-epileptic seizures as a neuropsychiatric differential diagnosis or comorbidity of epileptic seizures. Furthermore, recommendations on the potential role of ketogenic diet and on acupuncture, homeopathy and other complementary approaches are made. The recommendations on psychosocial aspects comprise practical issues, such as fitness to drive a car, training and occupation, medical rehabilitation, sport, transition, patients’ self-help, education programs for patients and next of kin, adherence, advise on SUDEP.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Consensus; Epilepsy surgery; Pharmacotherapy; Psychosocial aspects; Recommendations

Erythroderma and Hypernatraemic Dehydration in Newborn - A Case report of Netherton Syndrome - Anneser, Verena; Mueller, Fabian; Wild, Florian; Metze, Dieter; Schneider, Holm; Steinhoff, Martin; Seeliger, Stephan (Klinische Pädiatrie, 2020)
Netherton syndrome (NS) is a rare, severe, autosomal recessive form of congenital ichthyosis, associated with a characteristic defect in the hair shaft (Trichorrhexis invaginata), erythroderma, and a pronounced atopic disposition due to an altered immune system. Its incidence is about 1:100,000 to 1: 200,000. The disease is caused by mutations in the gene SPINK5 (5q31-q32) which codes for the serine protease inhibitor LEKTI. Affected newborns show a non-uniform picture of generalized erythroderma with scaling of the skin and sometimes even present as Collodion babys. A serious complication during early infancy is hypernatremic dehydration resulting from the inadequate barrier function of the skin. The mucocutaneous barrier dysfunction also leads to recurrent infections, atopy, diarrhea, and intestinal malabsorption with concomitant failure to thrive.
CRIS-Team WoS Importer:2020-06-05

Etiology, Risk Factors and Diagnosis of Back Pain in Children and Adolescents: Evidence-and Consensus-Based Interdisciplinary Recommendations - Frosch, Michael; Mauritz, Maximilian D.; Bielack, Stefan; Blödt, Susanne; Dirksen, Uta; Dobe, Michael; Geiger, Florian; Häfner, Renate; Höfel, Lea; Hübner-Möhler, Bettina; von Kalle, Thekla; Lawrenz, Burkhard; et al. (Children, 2022)
Using a structured approach and expert consensus, we developed an evidence-based guideline on the diagnosis of back pain and the treatment of non-specific back pain in children and adolescents. The first part comprises etiology, risk factors, and diagnosis. The second part, published in the same issue, includes treatment and prevention. A comprehensive and systematic literature search was conducted to identify relevant guidelines and studies. Based on the findings of this literature search, recommendations on risk factors and diagnosis were formulated and voted on by experts in a structured consensus-building process. Notable red flags for specific back pain and evidence-based risk factors for non-specific back pain in children and adolescents were identified. Only three evidence-based recommendations could be formulated for causes, red flags, and risk factors for back pain, while two recommendations are based on expert consensus. Regarding diagnostics, eight expert consensus recommendations and one evidence-based recommendation could be provided. Despite the importance of adequate diagnosis for the treatment of back pain in children and adolescents, results of this work confirm the deficit in research investment in this area.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Adolescents; Back pain; Children; Diagnosis; Etiology; Evidence-based; Guideline; Risk factors

Evaluating the Use of Neonatal Colonization Screening for Empiric Antibiotic Therapy of Sepsis and Pneumonia - Bär, Alisa; Schmitt-Grohé, Sabina; Held, Jürgen; Lubig, Julia; Hanslik, Gregor; Fahlbusch, Fabian; Reutter, Heiko Martin; Wölfle, Joachim; van der Donk, Adriana; Schleier, Maria; Hepp, Tobias; Morhart, Patrick (Antibiotics, 2023)
(1) Background: Since 2013, weekly screening for multidrug-resistant Gram-negative (MDRGN) bacteria has been performed in German neonatal intensive care units (NICU). National guidelines recommend considering these colonization analyses for antibiotic treatment regimens. Our retrospective single center study provides insight into the clinical dichotomy of bacterial colonization and infection rates in neonates. (2) Methods: We analyzed microbiological data of neonates admitted to our tertiary level NICU over nine years. Colonization with MDRGN/Serratia marcescens (SERMA) was compared to microbiological findings in sepsis and pneumonia. (3) Results: We analyzed 917 blood and 1799 tracheal aspirate samples. After applying criteria from the Nosocomial Infection Surveillance for Neonates (NEO-KISS), we included 52 and 55 cases of sepsis and pneumonia, respectively; 19.2% of sepsis patients and 34.5% of pneumonia patients had a prior colonization with MDRGN bacteria or SERMA. In these patients, sepsis was not attributable to MDRGN bacteria yet one SERMA, while in pneumonias, ten MDRGN bacteria and one SERMA were identified. We identified late-onset pneumonia and cesarean section as risk factors for MDRGN/SERMA acquisition. (4) Conclusions: Colonization screening is a useful tool for hygiene surveillance. However, our data suggest that consideration of colonization with MDRGN/SERMA might promote extensive use of last resort antibiotics in neonates.
CRIS-Team Scopus Importer:2023-03-10
Keywords: colonization; MDR; MDRGN; multidrug-resistant bacteria; multidrug-resistant Gram-negative bacteria; neonatal infection; neonates; pneumonia; screening; sepsis

Evaluation of an Interactive Visualization Tool for the Interpretation of Pediatric Laboratory Test Results - Hirschmann, Johannes; Sedlmayr, Brita; Zierk, Jakob; Rauh, Manfred; Metzler, Markus; Prokosch, Hans-Ulrich; Toddenroth, Dennis (Studies in health technology and informatics, 2017)
The physiological age-related development of pediatric laboratory results interferes with pathological derangements, which can complicate the interpretation of test results. Recently proposed continuous reference intervals (RIs) promise to be beneficial, although their clinical use may depend on graphical presentations. To estimate the clinical utility of continuous RIs, we developed and evaluated an interactive visualization tool, and examined the differentiation of hemoglobinopathies that is attainable based on the underlying innovative RI model. The implemented web application allows users to easily enter laboratory test results, and displays various visualizations in conjunction with the corresponding RIs, such as charts and personalized Z-scores. To evaluate the usability of the visualization tool, we conducted concurrent think-aloud sessions with four physicians, who were prompted to solve a set of typical interpretation tasks, and acquired additional information through a questionnaire including the System Usability Scale (SUS). We used 85 de-identified clinical cases for an exemplified assessment of how well model-based interpretations of blood count parameters reproduced previously diagnosed hemoglobinopathies. Usability tests as well as questionnaire responses indicated that the developed tool was well received by the physicians. Results from the think-aloud evaluation revealed only minor problems and the tool reached an average SUS score of 86.9, suggesting good usability. Hemoglobinopathy discrimination depended on the considered subtype, although the overall performance of the novel method rivaled the one of the conventional approach. The interactive visualization of innovative continuous reference intervals demonstrated promising results, which justifies further testing on the path towards clinical routine.
EVALuna2:193

Every CFTR variant counts – Target-capture based next-generation-sequencing for molecular diagnosis in the German CF Registry - Ahting, Simone; Nährlich, Lutz; Held, Inka; Henn, Constance; Krill, Angelika; Landwehr, Kerstin; Meister, Jochen; Nährig, Susanne; Nolde, Anna; Remke, Katharina; Ruppel, Renate; Sauer-Heilborn, Annette; et al. (Journal of Cystic Fibrosis, 2023)
Background: In times of genotype guided therapy options, a total of 3.2 % of people with CF (pwCF) in the German CF Registry[1] only have one or no CFTR-variant detected after genetic analysis. Additionally, genetic data in the Registry can be documented as free text and can therefore be prone to error. In order to allow the greatest possible amount of pwCF access to modern therapies, we conducted a re-evaluation of free text entries and established a custom-whole-CFTR-locus NGS-approach for all pwCF who remained without genetic confirmation afterwards. Methods: To this end, we assembled 731 free text variants of 655 pwCF in the German CF Registry. All variants were evaluated using ClinVar, HGMD and CFTR1/2, corrected in the Registries’ database and uploaded to ClinVar. PwCF whose diagnosis remained uncertain as well as additional pwCF or pwCFTR-RD that were assembled through a nationwide call for testing of unclear cases were offered genetic analysis. Samples were analysed using a target-capture based NGS-custom-design-panel covering the entire CFTR-locus. Results: Evaluation of free text variants led to the discovery of 43 variants not formerly reported in the context of CF. The Registries’ dropdown list was extended by 497 variants and over 500 pwCF were provided with their most up-to-date genotype. Samples of 47 pwCF/pwCFTR-RD were sequenced via NGS with an overall success rate of 61.7 %, resulting in implementation of entire CFTR-genotyping into routine diagnostics. Conclusion: Entire CFTR-genotyping can greatly increase the genetic diagnostic rate of pwCF/pwCFTR-RD and should be considered after inconspicuous CFTR screening panels in CFTR-diagnostics.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Cystic fibrosis; Diagnostics; Genetics; Genotyping; Next-generation-sequencing

Evolving pituitary hormone deficits in primarily isolated GHD: a review and experts' consensus. - Binder, Gerhard; Schnabel, Dirk; Reinehr, Thomas; Pfaeffle, Roland; Dörr, Helmuth-Günther; Bettendorf, Markus; Hauffa, Berthold P.; Wölfle, Joachim (Molecular and Cellular Pediatrics, 2020)
Isolated growth hormone deficiency (GHD) is defined by growth failure in combination with retarded bone age, low serum insulin-like growth factor-1, and insufficient GH peaks in two independent GH stimulation tests. Congenital GHD can present at any age and can be associated with significant malformations of the pituitary-hypothalamic region or the midline of the brain. In rare instances, genetic analysis reveals germline mutations of transcription factors involved in embryogenesis of the pituitary gland and the hypothalamus. Acquired GHD is caused by radiation, inflammation, or tumor growth. In contrast to organic GHD, idiopathic forms are more frequent and remain unexplained.There is a risk of progression from isolated GHD to combined pituitary hormone deficiency (> 5% for the total group), which is clearly increased in children with organic GHD, especially with significant malformation of the pituitary gland. Therefore, it is prudent to exclude additional pituitary hormone deficiencies in the follow-up of children with isolated GHD by clinical and radiological observations and endocrine baseline tests. In contrast to primary disorders of endocrine glands, secondary deficiency is frequently milder in its clinical manifestation. The pituitary hormone deficiencies can develop over time from mild insufficiency to severe deficiency. This review summarizes the current knowledge on diagnostics and therapy of additional pituitary hormone deficits occurring during rhGH treatment in children initially diagnosed with isolated GHD. Although risk factors are known, there are no absolute criteria enabling exclusion of children without any risk of progress to combined pituitary hormone deficiency. Lifelong monitoring of the endocrine function of the pituitary gland is recommended in humans with organic GHD. This paper is the essence of a workshop of pediatric endocrinologists who screened the literature for evidence with respect to evolving pituitary deficits in initially isolated GHD, their diagnosis and treatment.
EVALuna2:385043
Keywords: Isolated GHD; Combined pituitary hormone deficiency; Organic GHD; Pituitary gland malformation; Acquired GHD

Ewing Sarcoma-Diagnosis, Treatment, Clinical Challenges and Future Perspectives - Zoellner, Stefan K.; Amatruda, James E.; Bauer, Sebastian; Collaud, Stephane; De Alava, Enrique; Dubois, Steven G.; Hardes, Jendrik; Hartmann, Wolfgang; Kovar, Heinrich; Metzler, Markus; Shulman, David S.; Streitbuerger, Arne; et al. (Journal of Clinical Medicine, 2021)
Ewing sarcoma, a highly aggressive bone and soft-tissue cancer, is considered a prime example of the paradigms of a translocation-positive sarcoma: a genetically rather simple disease with a specific and neomorphic-potential therapeutic target, whose oncogenic role was irrefutably defined decades ago. This is a disease that by definition has micrometastatic disease at diagnosis and a dismal prognosis for patients with macrometastatic or recurrent disease. International collaborations have defined the current standard of care in prospective studies, delivering multiple cycles of systemic therapy combined with local treatment; both are associated with significant morbidity that may result in strong psychological and physical burden for survivors. Nevertheless, the combination of non-directed chemotherapeutics and ever-evolving local modalities nowadays achieve a realistic chance of cure for the majority of patients with Ewing sarcoma. In this review, we focus on the current standard of diagnosis and treatment while attempting to answer some of the most pressing questions in clinical practice. In addition, this review provides scientific answers to clinical phenomena and occasionally defines the resulting translational studies needed to overcome the hurdle of treatment-associated morbidities and, most importantly, non-survival.
CRIS-Team WoS Importer:2021-05-21

Exhausted Lag-3+ CD4+ T cells are increased in pediatric Inflammatory Bowel Disease. - Schnell, Alexander; Aicher, Carmen; Schnegelsberg, Philipp; Schwarz, Benedikt; Schmidt, Hannah; Allabauer, Ida; Rueckel, Aline; Regensburger, Adrian; Wölfle, Joachim; Hörning, André (Clinical and Experimental Immunology, 2025)
T cells are one of the main drivers of inflammatory bowel diseases (IBD). Infliximab (IFX) is used in the treatment of IBD as an anti-inflammatory drug to induce remission by neutralizing TNFα. We determined the individual chemokine/homing receptor and cytokine profile in pediatric IBD patients before and during IFX therapy to identify predictive biomarkers for therapy success. Peripheral blood CD4+ cells from pediatric patients with IBD were immunomagnetically isolated and either directly analyzed by FACS for cell distribution and chemokine/homing receptor expression or evaluated for cytokine production after in-vitro-stimulation. Twenty-one responders (RS) and 21 non-responders (NRS) were recruited. Before IFX therapy, flow cytometry revealed decreased percentages of naïve conventional T cells in pediatric IBD patients. The proportions of CD62-L+ T cells were decreased in both CD and UC therapy responders. The cytokine profile of T cells was highly altered in IBD patients compared to healthy controls (HC). During IFX therapy, the frequencies of conventional memory and regulatory memory T cells expanded in both cohorts. IFX response was marked by a decrease of α4β7+ and IFNγ+ memory T cells in both CD and UC. In contrast, frequencies of Lag-3+ T cells proved to be significantly increased in NRS. These observations were irrespective of the underlying disease. T cells of pediatric IBD patients display an activated and rather Th1/Th17-shifted phenotype. The increased expression of the checkpoint molecule Lag-3 on T cells of NRS resembles a more exhausted phenotype than in RS and HC which appeared to be a relevant predictive marker for therapy failure.
EVALuna2:582625

Exome sequencing implicates a novel heterozygous missense variant in DSTYK in autosomal dominant lower urinary tract dysfunction and mild hereditary spastic paraparesis. - Vidic, Clara; Zaniew, Marcin; Jurga, Szymon; Thiele, Holger; Reutter, Heiko Martin; Hilger, Alina C. (Molecular and Cellular Pediatrics, 2021)
INTRODUCTION: DSTYK encodes dual serine/threonine and tyrosine protein kinase. DSTYK has been associated with autosomal-dominant congenital anomalies of the kidney and urinary tract and with autosomal-recessive hereditary spastic paraplegia type 23. Here, we report a father and his two dizygotic twin sons carrying a novel heterozygous missense variant in DSTYK, presenting with early onset lower urinary tract dysfunction due to dysfunctional voiding. Moreover, in the later course of the disease, both sons presented with bilateral spasticity in their lower limbs, brisk reflexes, and absence seizures. MATERIALS AND METHODS: Exome sequencing in the affected father and his affected sons was performed. The sons presented clinically with urinary hesitancy, dysfunctional voiding, and night incontinence till adolescence, while the father reported difficulty in voiding. In the sons, cystoscopy excluded urethral valves and revealed hypertrophy of the bladder neck and trabeculated bladder. Additionally, both sons were diagnosed with absence epilepsy in early childhood. Filtering of exome data focused on rare (MAF < 0.01%), autosomal-dominant variants, predicted to be deleterious, residing in highly conserved regions of the exome. RESULTS: Exome analysis identified a novel, heterozygous missense variant (c.271C>A (p.Leu91Met)) in DSTYK segregating with the disease. In silico prediction analyses uniformly rated the variant to be deleterious suggesting the variant to be disease-causing in the family. CONCLUSION: To the best of our knowledge, this is the first report of early onset dysfunctional voiding, seizures, and bilateral spasticity of the lower limbs associated with a novel heterozygous dominant missense variant in DSTYK.
EVALuna2:490519
Keywords: DSTYK; Functional urinary bladder disturbance; HSP23; Hereditary spastic paraparesis; Epilepsy; CAKUT

Exome Survey and Candidate Gene Re-Sequencing Identifies Novel Exstrophy Candidate Genes and Implicates LZTR1 in Disease Formation - Köllges, Ricarda; Stegmann, Jil; Schneider, Sophia; Waffenschmidt, Lea; Fazaal, Julia; Breuer, Katinka; Hilger, Alina Christine; Dworschak, Gabriel C.; Mingardo, Enrico; Rösch, Wolfgang; Hofmann, Aybike; Neissner, Claudia; et al. (Biomolecules, 2023)
Background: The bladder exstrophy-epispadias complex (BEEC) is a spectrum of congenital abnormalities that involves the abdominal wall, the bony pelvis, the urinary tract, the external genitalia, and, in severe cases, the gastrointestinal tract as well. Methods: Herein, we performed an exome analysis of case-parent trios with cloacal exstrophy (CE), the most severe form of the BEEC. Furthermore, we surveyed the exome of a sib-pair presenting with classic bladder exstrophy (CBE) and epispadias (E) only. Moreover, we performed large-scale re-sequencing of CBE individuals for novel candidate genes that were derived from the current exome analysis, as well as for previously reported candidate genes within the CBE phenocritical region, 22q11.2. Results: The exome survey in the CE case-parent trios identified two candidate genes harboring de novo variants (NR1H2, GKAP1), four candidate genes with autosomal-recessive biallelic variants (AKR1B10, CLSTN3, NDST4, PLEKHB1) and one candidate gene with suggestive uniparental disomy (SVEP1). However, re-sequencing did not identify any additional variant carriers in these candidate genes. Analysis of the affected sib-pair revealed no candidate gene. Re-sequencing of the genes within the 22q11.2 CBE phenocritical region identified two highly conserved frameshift variants that led to early termination in two independent CBE males, in LZTR1 (c.978_985del, p.Ser327fster6) and in SLC7A4 (c.1087delC, p.Arg363fster68). Conclusions: According to previous studies, our study further implicates LZTR1 in CBE formation. Exome analysis-derived candidate genes from CE individuals may not represent a frequent indicator for other BEEC phenotypes and warrant molecular analysis before their involvement in disease formation can be assumed.
CRIS-Team Scopus Importer:2023-08-11
Keywords: cloacal exstrophy; exome analysis; exstrophy; molecular inversion probe

Expanding the spectrum of WDR62 mutations : description of new cases - Ruaud, L.; Drunat, S.; Ernault, A.; Capri, Y.; Van Maldergem, L.; Engel, C.; Altuzarra, C.; Bayat, A.; Moortgart, S.; Maystadt, I.; Abramowicz, M.; Zweier, Christiane; et al. (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Expertenempfehlung: Therapie nichtgehfähiger Patienten mit Muskeldystrophie Duchenne - Bernert, Guenther; Hahn, Andreas; Köhler, Cornelia; Meyer, Sascha; Schara, Ulrike; Schlachter, Kurt; Trollmann, Regina; Walter, Maggie C. (Der Nervenarzt, 2020)
Background: Duchenne muscular dystrophy (DMD) is the most frequent genetic neuromuscular disease in childhood with loss of ambulation usually occurring around the age of 9–11 years. Objective, material and methods: Based on current guidelines and clinical trials, neuropediatric and neurological experts developed recommendations for the treatment of nonambulatory DMD patients focusing on drug treatment of adults. This advisory board was sponsored by PTC Therapeutics, the distributers of the substance ataluren. Results and conclusion: Loss of ambulation is heterogeneously defined across clinical trials. Among others, the need of a wheelchair, ambulation without mobility aids or maximum walking distance can be suitable parameters for assessment. Treatment of DMD patients at any stage of the disease is based on supportive and symptomatic measures, which should be continued after loss of ambulation. In addition, disease-modifying drugs are available for the treatment of DMD and glucocorticoids are the usual standard of care treatment even beyond the loss of ambulation. Ataluren, a potentially dystrophin restorative, disease-modifying treatment, has been approved for patients with DMD due to a nonsense mutation (nmDMD), which applies to approximately 13% of DMD patients and is usually combined with steroids. Clinical data from the STRIDE registry demonstrated a delayed disease progression even after loss of ambulation. Currently, no reliable data are available for exon skipping approaches in adult DMD patients. The antioxidant idebenone could be an option in nonambulant adolescent patients not treated with glucocorticoids and without other therapeutic options. A combination treatment of idebenone and glucocorticoids is currently being investigated in a clinical trial. Add-on treatment with idebenone in addition to ataluren may be considered for nonambulant nmDMD patients. Some of the discussed treatment options are still in clinical trials or there are not enough data for older DMD patients; therefore, these expert recommendations correspond to evidence class IV.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Ataluren; Duchenne muscular dystrophy; Exon skipping; Glucocorticoids; Idebenone; Pharmacological therapy

Expertenempfehlung zur Magnetresonanztomographie bei Muskelerkrankungen - Zeng, Rachel; Schlaeger, Sarah; Türk, Matthias; Baum, Thomas; Deschauer, Marcus; Janka, Rolf Matthias; Karampinos, Dimitrios; Kassubek, Jan; Keller-Yamamura, Sarah; Kornblum, Cornelia; Lehmann, Helmar; Lichtenstein, Thorsten; et al. (Der Nervenarzt, 2024)
Background: Magnetic resonance (MRI) imaging of the skeletal muscles (muscle MRI for short) is increasingly being used in clinical routine for diagnosis and longitudinal assessment of muscle disorders. However, cross-centre standards for measurement protocol and radiological assessment are still lacking. Objectives: The aim of this expert recommendation is to present standards for the application and interpretation of muscle MRI in hereditary and inflammatory muscle disorders. Methods: This work was developed in collaboration between neurologists, neuroradiologists, radiologists, neuropaediatricians, neuroscientists and MR physicists from different university hospitals in Germany. The recommendations are based on expert knowledge and a focused literature search. Results: The indications for muscle MRI are explained, including the detection and monitoring of structural tissue changes and oedema in the muscle, as well as the identification of a suitable biopsy site. Recommendations for the examination procedure and selection of appropriate MRI sequences are given. Finally, steps for a structured radiological assessment are presented. Conclusions: The present work provides concrete recommendations for the indication, implementation and interpretation of muscle MRI in muscle disorders. Furthermore, it provides a possible basis for the standardisation of the measurement protocols at all clinical centres in Germany.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Diagnostics; Muscle MRI; Myopathy; Myositis; Semi-quantitative assessment scales

Expertenempfehlung zur Magnetresonanztomographie bei Muskelerkrankungen - Zeng, Rachel; Schlaeger, Sarah; Türk, Matthias; Baum, Thomas; Deschauer, Marcus; Janka, Rolf Matthias; Karampinos, Dimitrios; Kassubek, Jan; Keller-Yamamura, Sarah; Kornblum, Cornelia; Lehmann, Helmar; Lichtenstein, Thorsten; et al. (Die Radiologie, 2024)
BACKGROUND: Magnetic resonance (MRI) imaging of the skeletal muscles (muscle MRI for short) is increasingly being used in clinical routine for diagnosis and longitudinal assessment of muscle disorders. However, cross-centre standards for measurement protocol and radiological assessment are still lacking. OBJECTIVES: The aim of this expert recommendation is to present standards for the application and interpretation of muscle MRI in hereditary and inflammatory muscle disorders. METHODS: This work was developed in collaboration between neurologists, neuroradiologists, radiologists, neuropaediatricians, neuroscientists and MR physicists from different university hospitals in Germany. The recommendations are based on expert knowledge and a focused literature search. RESULTS: The indications for muscle MRI are explained, including the detection and monitoring of structural tissue changes and oedema in the muscle, as well as the identification of a suitable biopsy site. Recommendations for the examination procedure and selection of appropriate MRI sequences are given. Finally, steps for a structured radiological assessment are presented. CONCLUSIONS: The present work provides concrete recommendations for the indication, implementation and interpretation of muscle MRI in muscle disorders. Furthermore, it provides a possible basis for the standardisation of the measurement protocols at all clinical centres in Germany.
EVALuna2:566089

Exploitable metabolic dependencies in MLL-ENL-induced leukemia - Garcia-Cuellar, Maria-Paz; Lawlor, Jennifer; Böttcher, Martin; Mougiakakos, Dimitrios; Metzler, Markus; Slany, Robert (Blood Advances, 2020)
Mixed-lineage leukemia (MLL) fusions are transcriptional activators that induce leukemia, with a dismal prognosis that mandates further elucidation of their transformation mechanism. In this study, knockdown of the direct MLL-ENL target gene polypyrimidine tract binding protein-1 (PTBP1) was rate limiting for cell proliferation and caused a metabolic phenotype associated with reduced glucose consumption and lactate production. This effect was accompanied by a reduction of splice isoform-2 of pyruvate kinase M (PKM2). Because PKM2 restricts glycolytic outflow to provide anabolic intermediates, we tested the consequences of glucose, energy, and Ser/Gly starvation for cell physiology. Administration of deoxyglucose, energetic decoupling with rotenone, and inhibition of Ser biosynthesis by CBR5884 had a significantly stronger influence on self-renewal and survival of transformed cells than on normal controls. In particular, inhibition of Ser synthesis, which branches off glycolysis caused accumulation of reactive oxygen species, DNA damage, and apoptosis, predominantly in leukemic cells. Depletion of exogenous Ser/Gly affected proliferation and self-renewal of murine and human leukemia samples, even though they are classified as nonessential amino acids. Response to Ser/Gly starvation correlated with glucose transport, but did not involve activation of the AMPK energy homeostasis system. Finally, survival times in transplantation experiments were significantly extended by feeding recipients a Ser/Gly-free diet. These results suggest selective starvation as an option for supportive leukemia treatment.
CRIS-Team WoS Importer:2020-09-04

Exploring the complex etiology of oncogenic fusions in childhood cancer - Anderson, Nathaniel D.; De Borja, Richard; Young, Matthew D.; Fuligni, Fabio; Rosic, Andrej; Roberts, Nicola D.; Pillay, Nischalan; Toretsky, Jeffrey A.; Akihiko, Yoshida; Shibata, Tatsuhiro; Metzler, Markus; Somers, Gino; et al. (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22

Exploring the relationships between composite scores of disease severity, seizure-freedom and quality of life in Dravet syndrome. - Strzelczyk, Adam; Kurlemann, Gerhard; Bast, Thomas; Bettendorf, Ulrich; Kluger, Gerhard; Mayer, Thomas; Neubauer, Bernd A.; Polster, Tilman; von Spiczak, Sarah; Trollmann, Regina; Wolff, Markus; Toward, Toby; et al. (Neurological Research and Practice, 2022)
BACKGROUND: In Dravet syndrome (DS), a rare epileptic and developmental encephalopathy, the effectiveness of a new treatment is predominantly measured in terms of seizure frequency. However, this may not fully capture the impact of a treatment on the broader aspects of the syndrome and patients' health-related quality of life (HRQoL). Using a previously published survey which collected data from DS patients and their carers on the broader manifestations of their syndrome, their HRQoL, and their experience of seizures, this study created composite measures of symptom severity to offer new perspectives on the multifaceted aspects of this rare condition. METHODS: Survey responses on the severity of physical and psychosocial symptoms were combined with independent assessments of disability and care need, to generate three composite symptom scores assessing the manifestations of DS (physical, psychosocial and care requirements). Variation in HRQoL was investigated in multiple regression analyses to assess the strength of association between each of these composite measures and three forms of seizure measures (seizure frequency, days with no seizures and longest interval without seizures), as experienced over a 4- and 12-week period. RESULTS: Composite scores were calculated for a cohort of 75 primarily paediatric patients who were enrolled in the study. Strong associations were found between each of the three composite symptom scores and each of the three seizure measures, with the regression coefficient on symptom score highly significant (p ≤ 0.001) in all nine comparisons. Separate regressions using predictors of HRQoL (Kiddy KINDL and Kid KINDL) as the dependent variable were inconclusive, identifying only behavioural/attention problems and status epilepticus as significant predictors of HRQoL. CONCLUSIONS: These results allow the development of a composite score that may be useful in developing a clinical understanding of the severity of DS for an individual patient and establishing their treatment goals. Where measurement of long-term sequalae of disease is not feasible, such as clinical trials, correlation of the composite score with experience of seizures and seizure-free periods may allow a better contextualisation of the results of short-term assessments. TRIAL REGISTRATION: German Clinical Trials Register (DRKS), DRKS00011894. Registered 16 March 2017, http://www.drks.de/ DRKS00011894.
EVALuna2:516469

EZH2 specifically regulates ISL1 during embryonic urinary tract formation - Mingardo, Enrico; Kalanithy, Jeshurun C.; Dworschak, Gabriel; Ishorst, Nina; Yilmaz, Öznur; Lindenberg, Tobias; Hollstein, Ronja; Felger, Tim; Angrand, Pierre-Olivier; Reutter, Heiko M.; Reutter, Heiko Martin; Odermatt, Benjamin (Scientific Reports, 2024)
Isl1 has been described as an embryonic master control gene expressed in the pericloacal mesenchyme. Deletion of Isl1 from the genital mesenchyme in mice leads to an ectopic urethral opening and epispadias-like phenotype. Using genome wide association methods, we identified ISL1 as the key susceptibility gene for classic bladder exstrophy (CBE), comprising epispadias and exstrophy of the urinary bladder. The most significant marker (rs6874700) identified in our recent GWAS meta-analysis achieved a p value of 1.48 × 10- 24 within the ISL1 region. In silico analysis of rs6874700 and all other genome-wide significant markers in Linkage Disequilibrium (LD) with rs6874700 (D' = 1.0; R2 > 0.90) revealed marker rs2303751 (p value 8.12 × 10- 20) as the marker with the highest regulatory effect predicted. Here, we describe a novel 1.2 kb intragenic promoter residing between 6.2 and 7.4 kb downstream of the ISL1 transcription starting site, which is located in the reverse DNA strand and harbors a binding site for EZH2 at the exact region of marker rs2303751. We show, that EZH2 silencing in HEK cells reduces ISL1 expression. We show that ezh2-/- knockout (KO) zebrafish larvae display tissues specificity of ISL1 regulation with reduced expression of Isl1 in the pronephric region of zebrafish larvae. In addition, a shorter and malformed nephric duct is observed in ezh2-/- ko zebrafish Tg(wt1ß:eGFP) reporter lines. Our study shows, that Ezh2 is a key regulator of Isl1 during urinary tract formation and suggests tissue specific ISL1 dysregulation as an underlying mechanism for CBE formation.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Classic bladder exstrophy; EZH2; Gene regulation; HEK293; ISL1; Promoter; Zebrafish

Familial congenital lower urinary tract obstruction (LUTO) suggested by screening for lower urinary tract dysfunction in parents of patients: A descriptive study - Ebach, Fabian; Wagner, Pauline; Stein, Raimund; Dolscheid-Pommerich, Ramona; Reutter, Heiko Martin; Hilger, Alina Christine (Health Science Reports, 2024)
Background: Congenital lower urinary tract obstruction (LUTO) describes a heterogeneous group of congenital malformations. Posterior urethral valves (PUV) represent the most common entity. Familial occurrence has been described, suggestive of underlying genetic factors. LUTO can occur in various degrees of severity. In severe forms, oligohydramnios, pulmonary hypoplasia, and renal damage can occur resulting in high pre- and postnatal mortality. On the contrary, mild forms may become apparent through recurrent urinary tract infections. Such high phenotypic variability has been described even within the same family. Here, we systematically screened parents of affected children for symptoms of LUTO. Methods: The study population consisted of parents of LUTO patients. Fathers over 50 years of age were excluded, to avoid inclusion of male phenocopies due to early prostatic hypertrophy. Uroflowmetry, ultrasonography for residual urine and hydronephrosis, and laboratory examination of standard renal retention parameters were assessed, and a detailed patient history was taken, including the assessment of the International Prostate Symptom Score. Results: Twenty-nine of 42 LUTO families enrolled were found eligible for the present study. Of these, we identified five families in which the father had already been diagnosed with infravesical obstruction (17%). Of the remaining families, nine agreed to participate in our study. Of these nine families, eight families had a child affected with PUV and one family had a child with urethral stenosis. Here, we found two fathers and one mother with symptoms of LUTO suggestive of mild LUTO and one family, in which the unborn male fetal brother of the affected index patient was also diagnosed prenatally with LUTO. Conclusion: Our observations suggest that LUTOs have a higher heritability than previously thought and that first-degree relatives of the affected should be clinically assessed for symptoms of LUTO.
CRIS-Team Scopus Importer:2024-04-05
Keywords: familial LUTO; IPSS; LUTO; obstructive uropathy; postvoid residual volume; PUV; uroflowmetry

Fatigue and depression predict health-related quality of life in patients with pediatric-onset multiple sclerosis - Gravesande, Karin Storm Van'S; Blaschek, Astrid; Calabrese, Pasquale; Rostasy, Kevin; Huppke, Peter; Kessler, Josef J.; Kalbe, Elke; Mall, Volker; Kraus,; Dornfeld, E.; Elpers, C.; Lohmann, H.; et al. (Multiple Sclerosis and Related Disorders, 2019)
Background: Fatigue, depression and loss in health-related quality of life (HRQoL) have been reported to occur in a substantial amount of patients with pediatric-onset MS (POMS). This study aims to evaluate depression, fatigue and HRQoL and its relationship in a cohort of patients with POMS and matched healthy controls (HCs).
CRIS-Team WoS Importer:2019-12-27

Feasibility and Satisfaction of Young Cancer Survivors Participating in Preventive Interventions. A Subgroup Analysis of the Care for CAYA Program (CFC-P) - Elmers, Simon; Beitzen-Heineke, Antonia; Von Grundherr, Julia; Jensen, Wiebke; Koch, Barbara; Mann, Julia; Salchow, Jannike; Sinn, Marianne; Straub, Lesley-Ann; Wegert, Luisa; Vettorazzi, Elk; Bergelt, Corinna; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Feasibility of VECOPA, a dose-intensive chemotherapy regimen for children and adolescents with intermediate and advanced stage Hodgkin lymphoma: results of the GPOH-HD-2002/VECOPA pilot trial - Mauz-Koerholz, Christine; Hasenclever, Dirk; Holzendorf, Volker; Bernstaedt, Matthias; Juergens, Heribert; Burdach, Stefan; Eggert, Angelika; Berthold, Frank; Mueller, Hermann L.; Fruehwald, Michael C.; Klingebiel, Thomas; Metzler, Markus; et al. (Leukemia & Lymphoma, 2015)
The GPOH-HD (Gesellschaft für Pädiatrische Onkologie und Hämatologie-Hodgkin Disease) strategy for children and adolescents with intermediate and advanced stage Hodgkin lymphoma is based on two induction cycles of OEPA (vincristine, etoposide, prednisone, doxorubicin) followed by COPP (cyclophosphamide, vincristine, procarbazine, prednisone) or COPDAC (cyclophosphamide, vincristine, prednisone, dacarbazine) consolidation. The feasibility and efficacy of an intensified procarbazine-free consolidation regimen VECOPA (vinblastine, etoposide, cyclophosphamide, vincristine, prednisone, doxorubicin) were investigated. Following two OEPA and one or two VECOPA cycles, involved field radiotherapy was applied. The main endpoint was feasibility. Secondary endpoints were toxicity, proportion of delayed cycles, granulocyte-colony stimulating factor use, and event-free and overall survival. The regimen was well tolerated with mostly hematotoxicity exceeding Common Toxicity Criteria grade 2. In most patients with advanced stage the second VECOPA cycle was delayed despite hematopoietic recovery and absence of serious adverse events. Event-free survival at 36 months was 0.86 (95% confidence interval 0.70-1). The VECOPA regimen is effective and tolerable. However, its time-intensification was not fully exploited within this trial.
EVALuna2:18931

Fecal calprotectin and platelet count predict histologic disease activity in pediatric ulcerative colitis: results from a projection-predictive feature selection. - Schiller, B.; Wirthgen, E.; Weber, F.; Schiller, S.; Radke, M.; Claßen, Merle; Däbritz, J. (European Journal of Pediatrics, 2024)
Especially for pediatric patients, proxies of mucosal inflammation are needed. The Pediatric Ulcerative Colitis Activity Index (PUCAI) has been established to predict clinical and endoscopic disease activity. However, histologic inflammation might persist. We applied a special variable selection technique to predict histologic healing in pediatric ulcerative colitis (UC) as parsimoniously (but still as precisely) as possible. The retrospective analysis included data from two study cohorts, comprising 91 visits from 59 pediatric patients with UC. A Bayesian ordinal regression model was used in combination with a projection-predictive feature selection (PPFS) to identify a minimal subset of clinical and laboratory parameters sufficient for the prediction of histologic disease activity. Following the PPFS, CEDATA-GPGE patient registry data were analyzed to investigate the relevance of the selected predictors in relation to PUCAI and Physician Global Assessment (PGA) in up to 6697 patient visits. Fecal calprotectin (FC) and platelet count were identified as the minimal subset of predictors sufficient for prediction of histologic disease activity in pediatric UC. FC and platelet count also appeared to be associated with increasing disease activity as measured by PUCAI and PGA in the CEDATA-GPGE registry. Based on the selected model, predictions can be performed with a Shiny web app. Conclusion: Our statistical approach constitutes a reproducible and objective tool to select a minimal subset of the most informative parameters to predict histologic inflammation in pediatric UC. A Shiny app shows how physicians may predict the histologic activity in a user-friendly way using FC and platelet count. To generalize the findings, further prospective studies will be needed. What is Known: • Histologic healing is a major endpoint in the therapy of ulcerative colitis (UC). • The PUCAI score has been established to predict disease activity in pediatric UC but is not suitable for the prediction of histologic healing. What is New: • Our Bayesian ordinal regression model in combination with a projection-predictive feature selection is a reproducible and objective tool to select the minimal subset of clinical and laboratory parameters to predict histologic inflammation in pediatric UC. • Histologic inflammation in pediatric UC can be non-invasively predicted based on the combination of fecal calprotectin levels and platelet count.
EVALuna2:568617

Fetal and Maternal Safety Considerations for In Utero Therapy Clinical Trials: iFeTiS Consensus Statement - Sagar, Rachel; Almeida-Porada, Graça; Blakemore, Karin; Chan, Jerry K.Y.; Choolani, Mahesh; Götherström, Cecilia; Jaulent, Agnes; MacKenzie, Tippi C.; Mattar, Citra; Porada, Christopher D.; Peranteau, William H.; Schneider, Holm; et al. (Molecular Therapy, 2020)
CRIS-Team Scopus Importer:2020-11-06
Keywords: adverse event; clinical trial; fetal; fetal therapy; In utero stem cell transplantation; maternal; safety

Fetal programming of gene expression in growth-restricted rats depends on the cause of low birth weight - Nuesken, Kai-Dietrich; Schneider, Holm; Plank, Christian Georg; Trollmann, Regina; Nuesken, Eva; Rascher, Wolfgang; Doetsch, Joerg (Endocrinology, 2011)
Low birth weight and intrauterine growth restriction (IUGR) can be caused by numerous different conditions. In many experimental settings, however, these different causes are not accounted for. This study aimed at comparing the impact of two frequent causes of IUGR (low utero-placental blood flow vs. malnutrition) on fetal programming of gene expression. We studied offspring of dams treated by uterine artery ligation or sham operation compared with untreated controls and offspring of dams that were fed either a low protein or normal protein diet. After Cesarean section at term, placental and fetal hepatic expression of key "metabolic" and "vasoregulative" genes was investigated by quantitative RT-PCR. Ligation neonates showed IUGR, reduced expression of placental leptin, placental and hepatic IGF-I, hepatic inducible nitric oxide synthase, and increased expression of placental IGF binding protein 1, hepatic IGF-II receptor and erythropoietin (EPO).Low protein offspring also showed IUGR but increased expression of placental leptin; IGF-I; placental and hepatic inducible nitric oxide synthase; hepatic insulin, IGF-I, and IGF-II receptors; and reduced expression of placental IGF binding protein 1, IGF-II, leptin-receptor type A, placental and hepatic leptin receptor type B, and EPO. Expression was independent of sex, birth weight, fetal intrauterine position, and EPO expression. In conclusion, the impact of IUGR on fetal and placental gene expression depends on the cause of low birth weight. Therefore, morbidity after IUGR should be analyzed referring to its pathophysiological cause rather than referring to low birth weight itself. Fetal hypoxia as estimated by hepatic EPO expression does not seem to be a key regulator of transcriptional activity in our models. Copyright © 2011 by The Endocrine Society.
CRIS-Team Scopus Importer:2020-07-01

Fibrillin-1 and alpha8 integrin are co-expressed in the glomerulus and interact to convey adhesion of mesangial cells - Marek, Ines; Volkert, Gudrun; Hilgers, Karl Friedrich; Bieritz, Beate; Rascher, Wolfgang; Reinhardt, Dieter P.; Hartner, Andrea (Cell Adhesion and Migration, 2014)
Fibrillin-1 is a microfibrillar extracellular matrix protein that was described to be a ligand for ?8 integrin. ?8 integrin is a matrix receptor specifically expressed in mesangial and smooth muscle cells of the kidney. In previous studies we detected glomerular expression of fibrillin-1. Moreover, fibrillin-1 promoted adhesion, migration, and proliferation of mesangial cells. We hypothesized that fibrillin-1 and ?8 integrin might interact in the glomerulus, and thus, regulate mesangial cell properties. Our studies showed that fibrillin-1 and ?8 integrin colocalize in the glomerular mesangium. Induction of experimental glomerulonephritis led to an increase of both fibrillin-1 and ?8 integrin expression. In vitro studies revealed that mesangial cells deficient for ?8 integrin adhere weaker to fibrillin-1 and migrate more easily on fibrillin-1 than wild-type mesangial cells. Baseline proliferation on fibrillin-1 is higher in ?8 integrin-deficient mesangial cells, but the induction of proliferation is not different in ?8 integrin-deficient and wild-type mesangial cells. We conclude that fibrillin-1 and ?8 integrin interact, and thus, regulate mesangial cell adhesion and migration. The concomitant induction of both fibrillin-1 and ?8 integrin in a self-limited model of glomerular injury points to a protective role of the interaction of fibrillin-1 with ?8 integrin in the glomerulus resulting in reduced damage of the glomerular tuft as a consequence of firm adhesion of mesangial cells.
EVALuna2:3751

Finding a balance in reduced toxicity hematopoietic stem cell transplantation for thalassemia: role of infused CD3+ cell count and immunosuppression - Meissner, Barbara; Lang, Peter; Bader, Peter; Hoenig, Manfred; Müller, Ingo; Meisel, Roland; Greil, Johann; Sauer, Martin G.; Metzler, Markus; Corbacioglu, Selim; Burkhardt, Birgit; Wölfl, Matthias; et al. (Bone Marrow Transplantation, 2024)
We performed a retrospective analysis on 124 patients with transfusion-dependent thalassemia who were registered in the German pediatric registry for stem cell transplantation. All patients underwent first allogeneic hematopoietic stem cell transplantation (HSCT) between 2011 and 2020 and belonged mainly to Pesaro risk class 1–2. Four-year overall (OS) and thalassemia-free survival (TFS) were 94.5% ± 2.9% and 88.0% ± 3.4% after treosulfan-fludarabine-thiotepa- and 96.9% ± 3.1% (P = 0.763) and 96.9% ± 3.1% (P = 0.155) after busulfan-fludarabine-based conditioning. Mixed chimerism below 75% occurred predominantly in treosulfan-based regimens (27.5% versus 6.2%). OS and TFS did not differ significantly between matched sibling, other matched family and matched unrelated donor (UD) HSCTs (OS: 100.0%, 100.0%, 96.3% ± 3.6%; TFS: 96.5% ± 2.4%, 90.0% ± 9.5%, 88.9% ± 6.0%). However, mismatched UD-HSCTs performed less favorable (OS: 84.7% ± 7.3% (P = 0.029); TFS: 79.9% ± 7.4% (P = 0.082)). We generated a scoring system reflecting the risk to develop mixed chimerism in our cohort. The main risk-reducing factors were a high CD3+ cell count (≥6 × 107/kg) in the graft, busulfan-conditioning, pre-conditioning therapy and low-targeted ciclosporin A trough levels. Acute GvHD grade III-IV in treosulfan-based concepts predominantly occurred in patients with UD and reduced GvHD prophylaxis but not in the context of high CD3+ cell doses. Taken together, this information might be used to develop more risk-adapted HSCT regimens for thalassemia patients.
CRIS-Team Scopus Importer:2024-02-16

First epileptic seizure and epilepsies in adulthood: Abridged version of the S2k guideline of the German Society for Neurology in cooperation with the German Society for Epileptology. English Version - Holtkamp, Martin; May, Theodor W.; Berkenfeld, Ralf; Bien, Christian G.; Coban, Ingrid; Knake, Susanne; Michaelis, Rosa; Rémi, Jan; Seeck, Margitta; Surges, Rainer; Weber, Yvonne; Baum, Petra; et al. (Clinical Epileptology, 2024)
The new S2k guideline “First epileptic seizure and epilepsies in adulthood” provides recommendations on clinically relevant issues in five major topics: management of first epileptic seizures, pharmacotherapy, epilepsy surgery, complementary and supportive treatment, and psychosocial aspects. For the topic management of first epileptic seizures, the guideline provides recommendations on identifying the two major differential diagnoses, syncope and psychogenic non-epileptic seizure. The importance of additional examinations such as EEG, MRI and cerebrospinal fluid for syndromic classification and etiological allocation is discussed. Recommendations on neuropsychological and psychiatric screening tests are also given. The topic pharmacotherapy issues recommendations on antiseizure medication in monotherapy for focal, generalized and unclassified epilepsies; patient groups with special challenges such as the aged, women of childbearing potential and people with intellectual disability are emphasized. Further issues are indications for measuring serum concentrations of antiseizure medication and possible risks of switching manufacturers. In the topic epilepsy surgery, indications for presurgical assessment and the multiple therapeutic approaches, such as resection, laser ablation, and neurostimulation are presented. Recommendations on postoperative management of patients, including rehabilitation and psychosocial counselling, are given. The topic complementary and supportive therapeutic approaches comprises recommendations on the diagnostics and treatment of common psychiatric comorbidities of epilepsy, such as anxiety disorder, depression and psychosis. Another important issue is the management of psychogenic non-epileptic seizures as a neuropsychiatric differential diagnosis or comorbidity of epileptic seizures. Furthermore, recommendations on the potential role of ketogenic diet and on acupuncture, homeopathy and other complementary approaches are made. The recommendations on psychosocial aspects comprise practical issues, such as fitness to drive a car, training and occupation, medical rehabilitation, sport, transition, patients’ self-help, education programs for patients and next of kin, adherence, advise on SUDEP.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Consensus; Epilepsy surgery; Pharmacotherapy; Psychosocial aspects; Recommendations

First postnatal lactate blood levels on day 1 and outcome of preterm infants with gestational age <29 weeks - Zipf, Stephanie; Fortmann, Ingmar; Härtel, Christoph; Andres, Oliver; Frieauff, Eric; Paul, Pia; Häfke, Anna; Reutter, Heiko Martin; Morhart, Patrick; Weller, Ursula; Welp, Amrei; Kipke, Henry; et al. (Frontiers in Pediatrics, 2024)
Background: Serum lactate levels are used as biomarkers for perinatal asphyxia, while their value for outcome prediction in preterm infants is uncertain. It was the aim of this observational study to determine the association of the first postnatal serum-lactate levels on day 1 of life and short-term outcome in preterm infants less than 29 gestational weeks. Methods: We analysed data in a population-based cohort of German Neonatal Network (GNN) preterm infants with available first postnatal lactate levels enrolled at 22–28 weeks of gestational age (GA) between 1st of April 2009 and 31st December 2020. We hypothesized that high lactate levels as measured in mmol/L increase the risk of intraventricular haemorrhage (IVH) and bronchopulmonary dysplasia (BPD) in infants with VLBW regardless of small-for-gestational-age (SGA) status. Hypotheses were evaluated in univariate analyses and multiple logistic regression models. Results: First postnatal lactate levels were available in 2499 infants. The study population had a median GA of 26.7 [IQR 25.2–27.9] weeks and birth weight of 840 g [IQR 665–995]. Infants with short-term complications such as IVH and BPD had higher initial lactate levels than non-affected infants. The positive predictive value of a lactate cut-off of 4 mmol/L was 0.28 for IVH and 0.30 for BPD. After adjustment for known confounding variables, each 1 mmol/L increase of day 1 lactate levels was associated with a modestly increased risk of IVH (OR 1.18; 95% CI 1.03–1.37; p = 0.002) and BPD (OR 1.23; 95% CI 1.06–1.43; p = 0.005) but not with sepsis or mortality. Notably, SGA was associated with lower risk of any grade and severe IVH (OR 0.70; 95% CI 0.54–0.85; p = 0.001). Conclusions: In our observational cohort study higher initial lactate levels were associated with adverse outcome regardless of SGA status. However, the predictive value of lactate cut-off levels such as 4 mmol/L is low.
CRIS-Team Scopus Importer:2024-11-01
Keywords: all-cause mortality; bronchopulmonary dysplasia; extremely preterm infants; intraventricular haemorrhage; lactate levels; small for gestational age

First-year predictors of health-related quality of life changes in short-statured children treated with human growth hormone - Quitmann, J.; Bloemeke, J.; Dörr, Helmuth-Günther; Bullinger, M.; Witt, S.; Silva, N. (Journal of Endocrinological Investigation, 2019)
Purpose: Little attention has been directed towards examining the impact of predictors on change in health-related quality of life (HRQOL) within the course of growth hormone (GH) treatment in pediatric short stature. We aimed to assess changes in HRQOL and its sociodemographic, clinical and psychosocial predictors in children and adolescents diagnosed with growth hormone deficiency (GHD), and born short for gestational age (SGA) before and 12-month after start of GH treatment from the parents’ perspective. Results were compared with an untreated group with idiopathic short stature (ISS). In this prospective multicenter study, 152 parents of children/adolescents (aged 4–18 years) provided data on their children’s HRQOL at baseline and at 12-month follow-up. Method: Repeated-measures multivariate analyses of covariance were performed to examine parent-reported HRQOL changes from baseline to 1-year after treatment and hierarchical linear regressions to identify the predictors of HRQOL changes. Results: Results showed that parents of children that were treated with GH report an increase in their children’s HRQOL after 1 year. Changes in HRQOL were mostly explained by psychosocial predictors followed by sociodemographic and clinical variables. Specifically, the diagnosis SGA significantly predicted a greater increase in parent-reported HRQOL. Furthermore, a lower caregiving burden significantly predicted a decrease in parent-reported HRQOL. Conclusion: In conclusion, a substantial percentage of explained variance in HRQOL relates to psychosocial and sociodemographic predictors. However, there appears to be other important factors that are predictors of HRQOL, which need to be determined in large, population-based samples.
CRIS-Team Scopus Importer:2019-08-23
Keywords: Children and adolescents; Growth hormone treatment; HRQOL; Predictors of change; Short stature

Frequency and impact of enteric hyperoxaluria in pediatric short bowel syndrome: a retrospective single centre study - Schaefer, Jan Thomas; Schulz-Heise, Susanne; Rueckel, Aline; Rauh, Manfred; Jüngert, Jörg; Galiano, Matthias; Meier, Norbert; Wölfle, Joachim; Schiffer, Mario; Hörning, André (Frontiers in Pediatrics, 2023)
Objectives: The survival of pediatric patients with short bowel syndrome has improved in recent years. Enteric hyperoxaluria as a pathophysiological consequence has been hardly addressed so far. It can be associated with nephrolithiasis, nephrocalcinosis or even renal insufficiency. We assessed the prevalence of hyperoxaluria and its pathogenic consequences in a retrospective single centre study over the last 12 years. Methods: We conducted an internal database search for all pediatric patients suffering from short bowel syndrome treated from 2010 to 2022 in the department of pediatric gastroenterology as well as the pediatric nephrology and dialysis unit. Out of 56 patients identified, 26 patients were analysed for etiology of short bowel syndrome, renal excretion of oxalate (24/26), remaining short bowel and large intestinal length as well as further clinical parameters such as eGFR, nephrocalcinosis/urinary stone formation or stool frequency. Results: Hyperoxaluria was detected in 14/26 patients (54%). Nephrocalcinosis was present in four patients. Out of these four patients, hyperoxaluria could be proven (21% of all hyperoxaluric patients) in three cases, one hyperoxaluric patient had nephrolithiasis (7%). In one patient hyperoxaluria lead to end stage renal disease. We found that 80% of patients with volvulus developed enteric hyperoxaluria. None of the investigated factors had an effect on oxalate excretion. Conclusion: Enteric hyperoxaluria is a relevant pathophysiological finding in patients with short bowel syndrome occurring in about 50% of our cohort with multiple pathogenic complications. Regular screening for hyperoxaluria may be implemented in medical care for patients with short bowel syndrome. If necessary, prophylaxis, e.g., dietary advice or metaphylaxis should be initiated.
CRIS-Team Scopus Importer:2023-08-11
Keywords: enteric hyperoxaluria; hyperoxaluria; intestinal failure; kidney stone; nephrolithiasis; pediatric; short bowel syndrome

Frequency and Predictive Factors of Hypoglycemia in Patients Treated With rhIGF-1: Data From the Eu-IGFD Registry. - Bang, Peter; Polak, Michel; Bossowski, Artur; Maghnie, Mohamad; Argente, Jesús; Ramon-Krauel, Marta; Sert, Caroline; Perrot, Valerie; Mazain, Sarah; Wölfle, Joachim (Journal of Clinical Endocrinology and Metabolism, 2023)
CONTEXT: The European Increlex® Growth Forum Database (Eu-IGFD) is an ongoing surveillance registry (NCT00903110) established to collect long-term safety and effectiveness data on the use of recombinant human insulin-like growth factor-1 (rhIGF-1, mecasermin, Increlex) for the treatment of children/adolescents with severe primary insulin-like growth factor-1 deficiency (SPIGFD). OBJECTIVE: This analysis of Eu-IGFD data aimed to identify the frequency and predictive factors for hypoglycemia adverse events (AEs) in children treated with rhIGF-1. METHODS: Data were collected from December 2008 to May 2021. Logistic regression was performed to identify predictive risk factors for treatment-induced hypoglycemia AEs. Odds ratios (ORs) are presented with 95% CIs for each factor. RESULTS: In total, 306 patients were enrolled in the registry; 84.6% were diagnosed with SPIGFD. Patients who experienced ≥ 1 hypoglycemia AE (n = 80) compared with those with no hypoglycemia AEs (n = 224) had a lower mean age at treatment start (8.7 years vs 9.8 years), a more frequent diagnosis of Laron syndrome (27.5% vs 10.3%), and a history of hypoglycemia (18.8% vs 4.5%). Prior history of hypoglycemia (OR 0.25; 95% CI: [0.11; 0.61]; P = .002) and Laron syndrome diagnosis (OR 0.36; 95% CI: [0.18; 0.72]; P = .004) predicted future hypoglycemia AEs. Total hypoglycemia AEs per patient per treatment year was 0.11 and total serious hypoglycemia AEs per patient per treatment year was 0.01. CONCLUSION: Hypoglycemia occurs more frequently in patients with prior history of hypoglycemia and/or Laron syndrome compared with patients without these risk factors, and these patients should be carefully monitored for this AE throughout treatment.
EVALuna2:548565

Frequent and sex-biased deletion of SLX4IP by illegitimate V(D)J-mediated recombination in childhood acute lymphoblastic leukemia - Meissner, Barbara; Bartram, Thies; Eckert, Cornelia; Trka, Jan; Panzer-Grümayer, Renate; Hermanova, Ivana; Ellinghaus, Eva; Franke, Andre; Möricke, Anja; Schrauder, Andre; Teigler-Schlegel, Andrea; Dörge, Petra; et al. (Human Molecular Genetics, 2014)
Acute lymphoblastic leukemia (ALL) accounts for 25% of pediatric malignancies. Of interest, the incidence of ALL is observed 20% higher in males relative to females. The mechanism behind the phenomenon of sex-specific differences is presently not understood. Employing genome-wide genetic aberration screening in 19 ALL samples, one of the most recurrent lesions identified was monoallelic deletion of the 5' region of SLX4IP. We characterized this deletion by conventional molecular genetic techniques and analyzed its interrelationships with biological and clinical characteristics using specimens and data from 993 pediatric patients enrolled into trial AIEOP-BFM ALL 2000. Deletion of SLX4IP was detected in 30% of patients. Breakpoints within SLX4IP were defined to recurrent positions and revealed junctions with typical characteristics of illegitimate V(D)J-mediated recombination. In initial and validation analyses, SLX4IP deletions were significantly associated with male gender and ETV6/RUNX1-rearranged ALL (both overall P < 0.0001). For mechanistic validation, a second recurrent deletion affecting TAL1 and caused by the same molecular mechanism was analyzed in 1149 T-cell ALL patients. Validating a differential role by sex of illegitimate V(D)J-mediated recombination at the TAL1 locus, 128 out of 1149 T-cell ALL samples bore a deletion and males were significantly more often affected (P = 0.002). The repeatedly detected association of SLX4IP deletion with male sex and the extension of the sex bias to deletion of the TAL1 locus suggest that differential illegitimate V(D)J-mediated recombination events at specific loci may contribute to the consistent observation of higher incidence rates of childhood ALL in boys compared with girls.
EVALuna2:18859

From initiation to eradication: The lifespan of an MLL-rearranged therapy-related paediatric AML - Krumbholz, Manuela; Bradtke, J.; Stachel, D.; Peters, O.; Hero, B.; Holter, Wolfgang; Slany, Robert; Metzler, Markus (Bone Marrow Transplantation, 2015)

Front-line imatinib treatment in children and adolescents with chronic myeloid leukemia: results from a phase III trial - Suttorp, Meinolf; Schulze, Philipp; Glauche, Ingmar; Goehring, Gudrun; Von Neuhoff, Nils; Metzler, Markus; Sedlacek, Petr; De Bont, Eveline S. J. M.; Balduzzi, Adriana; Lausen, Birgitte; Aleinikova, Olga; Sufliarska, Sabina; et al. (Leukemia, 2018)
A total of 156 patients (age range 1.3-18.0 years, median 13.2 years; 91 (58.3%) male) with newly diagnosed CML (N = 146 chronic phase (CML-CP), N = 3 accelerated phase (CML-AP), N = 7 blastic phase (CML-BP)) received imatinib up-front (300, 400, 500 mg/m2, respectively) within a prospective phase III trial. Therapy response, progression-free survival, causes of treatment failure, and side effects were analyzed in 148 children and adolescents with complete data. Event-free survival rate by 18 months for patients in CML-CP (median follow-up time 25 months, range: 1-120) was 97% (95% CI, 94.2-99.9%). According to the 2006 ELN-criteria complete hematologic response by month 3, complete cytogenetic response (CCyR) by month 12, and major molecular response (MMR) by month 18 were achieved in 98, 63, and 59% of the patients, respectively. By month 36, 86% of the patients achieved CCyR and 74% achieved MMR. Thirty-eight patients (27%) experienced imatinib failure because of unsatisfactory response or intolerance (N = 9). In all, 28/148 patients (19%) underwent stem cell transplantation (SCT). In the SCT sub-cohort 2/23 patients diagnosed in CML-CP, 0/1 in CML-AP, and 2/4 in CML-BP, respectively, died of relapse (N = 3) or SCT-related complications (N = 2). This large pediatric trial extends and confirms data from smaller series that first-line imatinib in children is highly effective.
EVALuna2:35826

Functional and clinical analysis of five EDA variants associated with ectodermal dysplasia but with a hard-to-predict significance - Goekdere, Sare; Schneider, Holm; Hehr, Ute; Willen, Laure; Schneider, Pascal; Maier-Wohlfart, Sigrun (Frontiers in Genetics, 2022)
Deficiency of ectodysplasin A1 (EDA1) due to variants of the gene EDA causes X-linked hypohidrotic ectodermal dysplasia (XLHED), a rare genetic condition characterized by abnormal development of ectodermal structures. XLHED is defined by the triad of hypotrichosis, hypo- or anhidrosis, and hypo- or anodontia. Anhidrosis may lead to life-threatening hyperthermia. A definite genetic diagnosis is, thus, important for the patients' management and amenability to a novel prenatal treatment option. Here, we describe five familial EDA variants segregating with the disease in three families, for which different prediction tools yielded discordant results with respect to their significance. Functional properties in vitro and levels of circulating serum EDA were compared with phenotypic data on skin, hair, eyes, teeth, and sweat glands. EDA1-Gly176Val, although associated with relevant hypohidrosis, still bound to the EDA receptor (EDAR). Subjects with EDA1-Pro389LeufsX27, -Ter392GlnfsX30, -Ser125Cys, and an EDA1 splice variant (c.924+7A > G) showed complete absence of pilocarpine-induced sweating. EDA1-Pro389LeufsX27 was incapable of binding to EDAR and undetectable in serum. EDA1-Ter392GlnfsX30, produced in much lower amounts than wild-type EDA1, could still bind to EDAR, and so did EDA1-Ser125Cys that was, however, undetectable in serum. The EDA splice variant c.924+7A > G resulted experimentally in a mix of wild-type EDA1 and EDA molecules truncated in the middle of the receptor-binding domain, with reduced EDA serum concentration. Thus, in vitro assays reflected the clinical phenotype in two of these difficult cases, but underestimated it in three others. Absence of circulating EDA seems to predict the full-blown phenotype of XLHED, while residual EDA levels may also be found in anhidrotic patients. This indicates that unborn subjects carrying variants of uncertain significance could benefit from an upcoming prenatal medical treatment even if circulating EDA levels or tests in vitro suggest residual EDA1 activity.
CRIS-Team WoS Importer:2022-08-12

Functional characterization of a novel CFTR mutation P67S identified in a patient with atypical cystic fibrosis - Kraus, Cornelia; Reis, André; Naehrlich, Lutz; Dötsch, Jörg; Korbmacher, Christoph; Rauh, Robert (Cellular Physiology and Biochemistry, 2007)
Cystic fibrosis (CF) is caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. CFTR serves as a cAMP-stimulated chloride channel in a wide range of epithelial tissues and its dysfunction is a hallmark of CF. Over 1400 mutations in the CFTR gene are known, but functional data exist only for a minority of the mutant channels. The aim of the present study was to functionally characterize a novel CFTR mutation identified in a patient with atypical CF. Full length sequencing of the patient's CFTR gene revealed a homozygous C to T transition at nucleotide position 331 (CCT>TCT), which results in a P67S amino acid substitution. Mutant and wild-type CFTR were heterologously expressed in Xenopus laevis oocytes. CFTR whole-cell currents were studied using the two-electrode voltage-clamp technique. Channel surface expression was assessed by a chemiluminescence assay. Expression of P67S-CFTR resulted in functional CFTR chloride channels. However, the CFTR chloride conductance observed in oocytes expressing the mutant channel averaged only 24% of that in oocytes expressing wild-type CFTR. Similarly, surface expression of the mutant channel was reduced. In contrast, the mutation did not alter the anion selectivity of the channel, and Western blot analysis indicated a similar protein expression level of mutant and wild-type CFTR. Our findings indicate that the P67S mutation reduces CFTR chloride channel function by reducing channel surface expression. The mild disease phenotype of the patient indicates that the residual function of the mutant channel is sufficient to prevent the development of severe CF symptoms. Copyright © 2007 S. Karger AG.
UnivIS-Import:2015-04-14:Pub.2007.med.IPK.LPVP.functi
Keywords: CFTR; Chloride channel; Cystic fibrosis; Electrophysiology; P67S mutation; Pancreatic insufficiency; Surface expression; Xenopus laevis oocytes

Further Evidence of Neuroprotective Effects of Recombinant Human Erythropoietin and Growth Hormone in Hypoxic Brain Injury in Neonatal Mice - Klepper, Simon; Jung, Susan; Dittmann, Lara; Geppert, Carol-Immanuel; Hartmann, Arndt; Beier, Nicole; Trollmann, Regina (International Journal of Molecular Sciences, 2022)
Experimental in vivo data have recently shown complementary neuroprotective actions of rhEPO and growth hormone (rhGH) in a neonatal murine model of hypoxic brain injury. Here, we hypothesized that rhGH and rhEPO mediate stabilization of the blood-brain barrier (BBB) and regenerative vascular effects in hypoxic injury to the developing brain. Using an established model of neonatal hypoxia, neonatal mice (P7) were treated i.p. with rhGH (4000 mu g/kg) or rhEPO (5000 IU/kg) 0/12/24 h after hypoxic exposure. After a regeneration period of 48 h or 7 d, cerebral mRNA expression of Vegf-A, its receptors and co-receptors, and selected tight junction proteins were determined using qRT-PCR and ELISA. Vessel structures were assessed by Pecam-1 and occludin (Ocln) IHC. While Vegf-A expression increased significantly with rhGH treatment (p < 0.01), expression of the Vegfr and TEK receptor tyrosine kinase (Tie-2) system remained unchanged. RhEPO increased Vegf-A (p < 0.05) and Angpt-2 (p < 0.05) expression. While hypoxia reduced the mean vessel area in the parietal cortex compared to controls (p < 0.05), rhGH and rhEPO prevented this reduction after 48 h of regeneration. Hypoxia significantly reduced the Ocln(+) fraction of cortical vascular endothelial cells. Ocln signal intensity increased in the cortex in response to rhGH (p < 0.05) and in the cortex and hippocampus in response to rhEPO (p < 0.05). Our data indicate that rhGH and rhEPO have protective effects on hypoxia-induced BBB disruption and regenerative vascular effects during the post-hypoxic period in the developing brain.
CRIS-Team WoS Importer:2022-08-26

General Anesthesia in the First 36 Months of Life. - Schüttler, Christina; Münster, Tino; Gall, Christine; Trollmann, Regina; Schüttler, Jürgen (Deutsches Ärzteblatt international, 2021)
BACKGROUND: Experimental data have shown that the developing brain is especially vulnerable to exogenous noxious substances. The potential effects of anesthetic drugs on brain growth and development are a matter of concern. Clinical studies of children who underwent general anesthesia in their earliest years can make a major contribution to our understanding of the effects of anesthetic drugs on infants and toddlers (i.e., children under age 5). METHODS: Children born at term during the years 2007-2011 who were exposed to general anesthesia before their third birthday were included in the study. Data on general anesthesia were retrospectively evaluated, and the overall intelligence quotient (IQ) was determined prospectively as the primary target parameter. Children who had not been exposed to general anesthesia were recruited as a control group. The non-inferiority threshold was set at a difference of 5 IQ points out of a consideration of clinical relevance. RESULTS: 430 complete data sets were available from exposed children and 67 from members of the control group. The exposed group achieved a mean IQ score of 108.2, with a 95% confidence interval of [107; 109.4]; the corresponding values in the control group were 113 [110; 116.1]. Both groups achieved a mean score that was higher than the expected 100 points. After adjustment for age, socioeconomic status, and sex, the difference between the two groups was 2.9 points [0.2; 5.6], indicating a significantly better outcome in the control group than in the exposed group. The non-inferiority threshold of 5 IQ points was within the confidence interval; thus, non-inferiority was not demonstrated. CONCLUSION: The fact that both groups achieved a higher IQ score than the expected 100 points may be attributable, at least in part, to the restriction of the study to children born at term. The results indicate that general anesthesia in early childhood is not associated with markedly reduced intelligence in later years, although noninferiority could not be demonstrated.
EVALuna2:491351

Generation and characterization of function-blocking anti-ectodysplasin A (EDA) monoclonal antibodies that induce ectodermal dysplasia - Kowalczyk-Quintas, Christine; Willen, Laure; Anh Thu Dang,; Sarrasin, Heidi; Tardivel, Aubry; Hermes, Katharina; Schneider, Holm; Gaide, Olivier; Donze, Olivier; Kirby, Neil; Headon, Denis J.; Schneider, Pascal (Journal of Biological Chemistry, 2014)
Development of ectodermal appendages, such as hair, teeth, sweat glands, sebaceous glands, and mammary glands, requires the action of the TNF family ligand ectodysplasin A (EDA). Mutations of the X-linked EDA gene cause reduction or absence of many ectodermal appendages and have been identified as a cause of ectodermal dysplasia in humans, mice, dogs, and cattle. We have generated blocking antibodies, raised in Eda-deficient mice, against the conserved, receptor-binding domain of EDA. These antibodies recognize epitopes overlapping the receptor-binding site and prevent EDA from binding and activating EDAR at close to stoichiometric ratios in in vitro binding and activity assays. The antibodies block EDA1 and EDA2 of both mammalian and avian origin and, in vivo, suppress the ability of recombinant Fc-EDA1 to rescue ectodermal dysplasia in Eda-deficient Tabby mice. Moreover, administration of EDA blocking antibodies to pregnant wild type mice induced in developing wild type fetuses a marked and permanent ectodermal dysplasia. These function-blocking anti-EDA antibodies with wide cross-species reactivity will enable study of the developmental and postdevelopmental roles of EDA in a variety of organisms and open the route to therapeutic intervention in conditions in which EDA may be implicated.
EVALuna2:18884

Gene replacement therapy with onasemnogene abeparvovec in children with spinal muscular atrophy aged 24 months or younger and bodyweight up to 15 kg: an observational cohort study - Weiß, Claudia; Ziegler, Andreas; Becker, Lena Luise; Johannsen, Jessika; Brennenstuhl, Heiko; Schreiber, Gudrun; Flotats-Bastardas, Marina; Stoltenburg, Corinna; Hartmann, Hans; Illsinger, Sabine; Denecke, Jonas; Pechmann, Astrid; et al. (The Lancet Child & Adolescent Health, 2022)
Background: Given the novelty of gene replacement therapy with onasemnogene abeparvovec in spinal muscular atrophy, efficacy and safety data are limited, especially for children older than 24 months, those weighing more than 8·5 kg, and those who have received nusinersen. We aimed to provide real-world data on motor function and safety after gene replacement therapy in different patient subgroups. Methods: We did a protocol-based, multicentre prospective observational study between Sept 21, 2019, and April 20, 2021, in 18 paediatric neuromuscular centres in Germany and Austria. All children with spinal muscular atrophy types 1 and 2 receiving onasemnogene abeparvovec were included in our cohort, and there were no specific exclusion criteria. Motor function was assessed at the time of gene replacement therapy and 6 months afterwards, using the Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders (CHOP INTEND) and Hammersmith Functional Motor Scale-Expanded (HFMSE) scores. Additionally, in children pretreated with nusinersen, motor function was assessed before and after treatment switch. Off-target adverse events were analysed with a focus on liver function, thrombocytopaenia, and potential cardiotoxicity. Findings: 76 children (58 pretreated with nusinersen and 18 who were nusinersen naive) with spinal muscular atrophy were treated with onasemnogene abeparvovec at a mean age of 16·8 months (range 0·8–59·0, IQR 9–23) and a mean weight of 9·1 kg (range 4·0–15·0, IQR 7·4–10·6). In 60 patients with available data, 49 had a significant improvement on the CHOP-INTEND score (≥4 points) and HFMSE score (≥3 points). Mean CHOP INTEND scores increased significantly in the 6 months after therapy in children younger than 8 months (n=16; mean change 13·8 [SD 8·5]; p<0·0001) and children aged between 8 and 24 months (n=34; 7·7 [SD 5·2]; p<0·0001), but not in children older than 24 months (n=6; 2·5 [SD 5·2]; p=1·00). In the 45 children pretreated with nusinersen and had available data, CHOP INTEND score increased by 8·8 points (p=0·0003) at 6 months after gene replacement therapy. No acute complications occurred during infusion of onasemnogene abeparvovec, but 56 (74%) patients had treatment-related side-effects. Serious adverse events occurred in eight (11%) children. Liver enzyme elevation significantly increased with age and weight at treatment. Six (8%) patients developed acute liver dysfunction. Other adverse events included pyrexia (n=47 [62%]), vomiting or loss of appetite (41 [54%]), and thrombocytopenia (n=59 [78%]). Prednisolone treatment was significantly prolonged with a mean duration of 15·7 weeks (IQR 9–19), mainly due to liver enzyme elevation. Cardiac adverse events were rare; only two patients had abnormal echocardiogram and echocardiography findings. Interpretation: This study provides class IV evidence that children with spinal muscular atrophy aged 24 months or younger and patients pretreated with nusinersen significantly benefit from gene replacement therapy, but adverse events can be severe and need to be closely monitored. Funding: None. Translation: For the German translation of the abstract see Supplementary Materials section.
CRIS-Team Scopus Importer:2021-12-24

Generic formulations of imatinib for treatment of Philadelphia chromosome-positive leukemia in pediatric patients - Suttorp, Meinolf; Metzler, Markus; Shimada, Hiroyuki; Bansal, Deepak; Gunes, Adalet Meral; Kalwak, Krzysztof; Sedlacek, Petr; Baruchel, Andre; Biondi, Andrea; Hijiya, Nobuko; Schultz, Kirk R.; Schrappe, Martin; et al. (Pediatric Blood & Cancer, 2018)
Since the patent for imatinib has expired, the role of generic imatinib (GI) in the management of Philadelphia chromosome-positive (Ph+) leukemia in pediatric patients has had ongoing discussion. Some studies in adults demonstrated that equivalent doses of GI and branded imatinib (BI) result in comparable plasma concentrations and clinical efficacy. However, other studies found that GI users are more likely to stop imatinib, with intolerance and decreased persistence as the main causes. Economic factors also heavily influence GI selection. This article aims to review the present knowledge to support further discussion on the role of GI in the management of pediatric Ph+ leukemia.
EVALuna2:35822

Genetic Counseling for Birth Defects - Reutter, Heiko Martin (European Journal of Pediatric Surgery, 2021)
CRIS-Team WoS Importer:2021-12-31

Genetic Counseling for Bladder Exstrophy-Epispadias Complex - Reutter, Heiko Martin; Holmdahl, Gundela (European Journal of Pediatric Surgery, 2021)
Bladder exstrophy-epispadias complex (BEEC) represents the severe end of the uro-rectal malformation spectrum and has profound impact on continence, sexual, and renal function. Treatment of BEEC is primarily surgical, and the main goals are safe closure of the abdominal wall, urinary continence while preserving renal function, and adequate cosmetic and functional genital reconstruction. Psychosocial and psychosexual outcomes and adequate health-related quality of life depend on long-term multidisciplinary care. The overall outcome is now considered very positive and affected individuals usually lead self-determined and independent lives with the desire to start their own families later in life. Certainty about the risk of recurrence and the provision of information about the current state of knowledge about the identified genetic causes with high penetrance will have an impact on family planning for healthy parents with an affected child and for affected individuals themselves. This review addresses this information and presents the current state of knowledge.
CRIS-Team WoS Importer:2021-12-31

Genetic modifiers of fetal hemoglobin affect the course of sickle cell disease in patients treated with hydroxyurea - Allard, Pierre; Alhaj, Nareen; Lobitz, Stephan; Cario, Holger; Jarisch, Andreas; Grosse, Regine; Oevermann, Lena; Hakimeh, Dani; Tagliaferri, Laura; Kohne, Elisabeth; Kopp-Schneider, Annette; Kulozik, Andreas E.; et al. (Haematologica, 2022)
The course of sickle cell disease (SCD) is modified by polymorphisms boosting fetal hemoglobin (HbF) synthesis. However, it has remained an open question how these polymorphisms affect patients who are treated with the HbF-inducing drug hydroxyurea/hydroxycarbamide. The German SCD registry offers the opportunity to answer this question, because >90% of patients are treated according to national guidelines recommending the use of hydroxyurea in all patients above 2 years of age. We analyzed the modifying effect of HbF-related genetic polymorphisms in 417 patients with homozygous SCD >2 years old who received hydroxyurea. HbF levels were correlated with higher total hemoglobin levels, lower rates of hemolysis, a lower frequency of painful crises and of red blood cell transfusions. The minor alleles of the polymorphisms in the γ-globin promoter (rs7482144), BCL11A (rs1427407) and HMIP (rs66650371) were strongly associated with increased HbF levels. However, these associations did not translate into lower frequencies of vaso-occlusive events which did not differ between patients either carrying or not carrying the HMIP and BCL11A polymorphisms. Patients on hydroxyurea carrying the γ-globin promoter polymorphism demonstrated substantially higher hemoglobin levels (P<10-4) but also higher frequencies of painful crises and hospitalizations (P<0.01) when compared to patients without this polymorphism. Taken together, these data indicate that the γ-globin, HMIP and BCL11A polymorphisms correlate with increased HbF in SCD patients on hydroxyurea. While HbF is negatively correlated with the frequency of painful crises and hospitalizations, this was not observed for the presence of known HbF-boosting alleles.
CRIS-Team Scopus Importer:2022-07-15

Genetic screening confirms heterozygous mutations in ACAN as a major cause of idiopathic short stature - Hauer, Nadine; Sticht, Heinrich; Boppudi, Sangamitra; Büttner, Christian; Kraus, Cornelia; Trautmann, Udo; Zenker, Martin; Zweier, Christiane; Wiesener, Antje; Abou Jamra, Rami; Wieczorek, Dagmar; Kelkel, Jaqueline; et al. (Scientific Reports, 2017)
Short stature is a common pediatric disorder affecting 3% of the population. However, the clinical variability and genetic heterogeneity prevents the identification of the underlying cause in about 80% of the patients. Recently, heterozygous mutations in the ACAN gene coding for the proteoglycan aggrecan, a main component of the cartilage matrix, were associated with idiopathic short stature. To ascertain the prevalence of ACAN mutations and broaden the phenotypic spectrum in patients with idiopathic short stature we performed sequence analyses in 428 families. We identified heterozygous nonsense mutations in four and potentially disease-causing missense variants in two families (1.4%). These patients presented with a mean of -3.2 SDS and some suggestive clinical characteristics. The results suggest heterozygous mutations in ACAN as a common cause of isolated as well as inherited idiopathic short stature.
EVALuna2:9379

GENETICS IN ENDOCRINOLOGY: Gain and loss of function mutations of the calcium-sensing receptor and associated proteins: current treatment concepts - Mayr, Bernhard; Schnabel, Dirk; Dörr, Helmuth-Günther; Schöfl, Christof (European Journal of Endocrinology, 2016)
The calcium-sensing receptor (CASR) is the main calcium sensor in the maintenance of calcium metabolism. Mutations of the CASR, the G protein alpha 11 (GNA11) and the adaptor-related protein complex 2 sigma 1 subunit (AP2S1) genes can shift the set point for calcium sensing causing hyper- or hypo-calcemic disorders. Therapeutic concepts for these rare diseases range from general therapies of hyper- and hypo-calcemic conditions to more pathophysiology oriented approaches such as parathyroid hormone (PTH) substitution and allosteric CASR modulators. Cinacalcet is a calcimimetic that enhances receptor function and has gained approval for the treatment of hyperparathyroidism. Calcilytics in turn attenuate CASR activity and are currently under investigation for the treatment of various diseases. We conducted a literature search for reports about treatment of patients harboring inactivating or activating CASR, GNA11 or AP2S1 mutants and about in vitro effects of allosteric CASR modulators on mutated CASR. The therapeutic concepts for patients with familial hypocalciuric hypercalcemia (FHH), neonatal hyperparathyroidism (NHPT), neonatal severe hyperparathyroidism (NSHPT) and autosomal dominant hypocalcemia (ADH) are reviewed. FHH is usually benign, but symptomatic patients benefit from cinacalcet. In NSHPT patients pamidronate effectively lowers serum calcium, but most patients require parathyroidectomy. In some patients cinacalcet can obviate the need for surgery, particularly in heterozygous NHPT. Symptomatic ADH patients respond to vitamin D and calcium supplementation but this may increase calciuria and renal complications. PTH treatment can reduce relative hypercalciuria. None of the currently available therapies for ADH, however, prevent tissue calcifications and complications, which may become possible with calcilytics that correct the underlying pathophysiologic defect.
EVALuna2:2068

Genetic testing and surveillance in infantile myofibromatosis: a report from the SIOPE Host Genome Working Group - Hettmer, Simone; Dachy, Guillaume; Seitz, Guido; Agaimy, Abbas; Duncan, Catriona; Jongmans, Marjolijn; Hirsch, Steffen; Kventsel, Iris; Kordes, Uwe; De Krijger, Ronald R.; Metzler, Markus; Michaeli, Orli; et al. (Familial Cancer, 2020)
Infantile myofibromatosis (IM), which is typically diagnosed in young children, comprises a wide clinical spectrum ranging from inconspicuous solitary soft tissue nodules to multiple disseminated tumors resulting in life-threatening complications. Familial IM follows an autosomal dominant mode of inheritance and is linked to PDGFRB germline variants. Somatic PDGFRB variants were also detected in solitary and multifocal IM lesions. PDGFRB variants associated with IM constitutively activate PDGFRB kinase activity in the absence of its ligand. Germline variants have lower activating capabilities than somatic variants and, thus, require a second cis-acting hit for full receptor activation. Typically, these mutant receptors remain sensitive to tyrosine kinase inhibitors such as imatinib. The SIOPE Host Genome Working Group, consisting of pediatric oncologists, clinical geneticists and scientists, met in January 2020 to discuss recommendations for genetic testing and surveillance for patients who are diagnosed with IM or have a family history of IM/PDGFRB germline variants. This report provides a brief review of the clinical manifestations and genetics of IM and summarizes our interdisciplinary recommendations.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Genetic counseling; Infantile myofibromatosis; PDGFRB variants; Surveillance

Genome-wide association study identifies multiple new loci associated with Ewing sarcoma susceptibility - Machiela, Mitchell J.; Gruenewald, Thomas G. P.; Surdez, Didier; Reynaud, Stephanie; Mirabeau, Olivier; Karlins, Eric; Rubio, Rebeca Alba; Zaidi, Sakina; Grossetete-Lalami, Sandrine; Ballet, Stelly; Lapouble, Eve; Laurence, Valerie; et al. (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-04

Genome-wide association study identifies multiple new loci associated with Ewing sarcoma susceptibility - Machiela, Mitchell J.; Grunewald, Thomas G. P.; Surdez, Didier; Reynaud, Stephanie; Mirabeau, Olivier; Karlins, Eric; Rubio, Rebeca Alba; Zaidi, Sakina; Grossetete-Lalami, Sandrine; Ballet, Stelly; Lapouble, Eve; Laurence, Valerie; et al. (Nature Communications, 2018)
Ewing sarcoma (EWS) is a pediatric cancer characterized by the EWSR1-FLI1 fusion. We performed a genome-wide association study of 733 EWS cases and 1346 unaffected individuals of European ancestry. Our study replicates previously reported susceptibility loci at 1p36.22, 10q21.3 and 15q15.1, and identifies new loci at 6p25.1, 20p11.22 and 20p11.23. Effect estimates exhibit odds ratios in excess of 1.7, which is high for cancer GWAS, and striking in light of the rarity of EWS cases in familial cancer syndromes. Expression quantitative trait locus (eQTL) analyses identify candidate genes at 6p25.1 (RREB1) and 20p11.23 (KIZ). The 20p11.22 locus is near NKX2-2, a highly overexpressed gene in EWS. Interestingly, most loci reside near GGAA repeat sequences and may disrupt binding of the EWSR1-FLI1 fusion protein. The high locus to case discovery ratio from 733 EWS cases suggests a genetic architecture in which moderate risk SNPs constitute a significant fraction of risk.
EVALuna2:35825

GENOME-WIDE ASSOCIATION STUDY IN PATIENTS WITH ANATOMICAL OBSTRUCTIONS OF THE LOWER URINARY TRACT - Van Der Zanden, Loes F. M.; Maj, Carlo; Borisov, Oleg; Van Rooij, Iris A. L. M.; Quaedackers, Josine S. L. T.; Steffens, Martijn; Schierbaum, Luca; Schneider, Sophia; Waffenschmidt, Lea; Kiemeney, Lambert A. L. M.; De Wall, Liesbeth; Heilmann, Stefanie; et al. (PEDIATRIC NEPHROLOGY, 2022)
CRIS-Team WoS Importer:2022-09-30

Genome-wide association study in patients with posterior urethral valves - van der Zanden, Loes F.M.; Maj, Carlo; Borisov, Oleg; van Rooij, Iris A.L.M.; Quaedackers, Josine S.L.T.; Steffens, Martijn; Schierbaum, Luca; Schneider, Sophia; Waffenschmidt, Lea; Kiemeney, Lambertus A.L.M.; de Wall, Liesbeth L.L.; Heilmann, Stefanie; et al. (Frontiers in Pediatrics, 2022)
Congenital lower urinary tract obstructions (LUTO) are most often caused by posterior urethral valves (PUV), a male limited anatomical obstruction of the urethra affecting 1 in 4,000 male live births. Little is known about the genetic background of PUV. Here, we report the largest genome-wide association study (GWAS) for PUV in 4 cohorts of patients and controls. The final meta-analysis included 756 patients and 4,823 ethnicity matched controls and comprised 5,754,208 variants that were genotyped or imputed and passed quality control in all 4 cohorts. No genome-wide significant locus was identified, but 33 variants showed suggestive significance (P < 1 × 10−5). When considering only loci with multiple variants residing within < 10 kB of each other showing suggestive significance and with the same effect direction in all 4 cohorts, 3 loci comprising a total of 9 variants remained. These loci resided on chromosomes 13, 16, and 20. The present GWAS and meta-analysis is the largest genetic study on PUV performed to date. The fact that no genome-wide significant locus was identified, can be explained by lack of power or may indicate that common variants do not play a major role in the etiology of PUV. Nevertheless, future studies are warranted to replicate and validate the 3 loci that yielded suggestive associations.
CRIS-Team Scopus Importer:2022-10-28
Keywords: BMP7; genome wide association study; lower urinary tract obstruction; obstructive uropathy; PCDH9; posterior urethral valves; SALL1

Genome-wide identification of disease-causing copy number variations in 450 individuals with anorectal malformations - Fabian, Julia; Dworschak, Gabriel C.; Waffenschmidt, Lea; Schierbaum, Luca; Bendixen, Charlotte; Heilmann-Heimbach, Stefanie; Sivalingam, Sugirthan; Buness, Andreas; Schwarzer, Nicole; Boemers, Thomas M.; Schmiedeke, Eberhard; Neser, Jorg; et al. (European Journal of Human Genetics, 2022)
Anorectal malformations (ARM) represent a spectrum of rare malformations originating from a perturbated development of the embryonic hindgut. Approximately 60% occur as a part of a defined genetic syndrome or within the spectrum of additional congenital anomalies. Rare copy number variations (CNVs) have been associated with both syndromic and non-syndromic forms. The present study represents the largest study to date to explore the contribution of CNVs to the expression of ARMs. SNP-array-based molecular karyotyping was applied in 450 individuals with ARM and 4392 healthy controls. CNVs were identified from raw intensity data using PennCNV. Overlapping CNVs between cases and controls were discarded. Remaining CNVs were filtered using a stringent filter algorithm of nine filter steps. Prioritized CNVs were confirmed using qPCR. Filtering prioritized and qPCR confirmed four microscopic chromosomal anomalies and nine submicroscopic CNVs comprising seven microdeletions (del2p13.2, del4p16.2, del7q31.33, del9p24.1, del16q12.1, del18q32, del22q11.21) and two microduplications (dup2p13.2, dup17q12) in 14 individuals (12 singletons and one affected sib-pair). Within these CNVs, based on their embryonic expression data and function, we suggest FOXK2, LPP, and SALL3 as putative candidate genes. Overall, our CNV analysis identified putative microscopic and submicroscopic chromosomal rearrangements in 3% of cases. Functional characterization and re-sequencing of suggested candidate genes is warranted.
CRIS-Team Scopus Importer:2022-11-18

Genome-Wide Survey for Microdeletions or -Duplications in 155 Patients with Lower Urinary Tract Obstructions (LUTO) - Schierbaum, Luca M.; Schneider, Sophia; Herms, Stefan; Sivalingam, Sugirthan; Fabian, Julia; Reutter, Heiko Martin; Weber, Stefanie; Merz, Waltraut M.; Tkaczyk, Marcin; Miklaszewska, Monika; Sikora, Przemyslaw; Szmigielska, Agnieszka; et al. (Genes, 2021)
Lower urinary tract obstruction (LUTO) is, in most cases, caused by anatomical blockage of the bladder outlet. The most common form are posterior urethral valves (PUVs), a male-limited phenotype. Here, we surveyed the genome of 155 LUTO patients to identify disease-causing CNVs. Raw intensity data were collected for CNVs detected in LUTO patients and 4.392 healthy controls using CNVPartition, QuantiSNP and PennCNV. Overlapping CNVs between patients and controls were discarded. Additional filtering implicated CNV frequency in the database of genomic variants, gene content and final visual inspection detecting 37 ultra-rare CNVs. After, prioritization qPCR analysis confirmed 3 microduplications, all detected in PUV patients. One microduplication (5q23.2) occurred de novo in the two remaining microduplications found on chromosome 1p36.21 and 10q23.31. Parental DNA was not available for segregation analysis. All three duplications comprised 11 coding genes: four human specific lncRNA and one microRNA. Three coding genes (FBLIM1, SLC16A12, SNCAIP) and the microRNA MIR107 have previously been shown to be expressed in the developing urinary tract of mouse embryos. We propose that duplications, rare or de novo, contribute to PUV formation, a male-limited phenotype.
CRIS-Team WoS Importer:2021-10-08

Genomic EWSR1 Fusion Sequence as Highly Sensitive and Dynamic Plasma Tumor Marker in Ewing Sarcoma - Krumbholz, Manuela; Hellberg, Julia; Steif, Benedikt; Bäuerle, Tobias; Gillmann, Clarissa; Fritscher, Torsten; Agaimy, Abbas; Frey, Benjamin; Juengert, Joerg; Wardelmann, Eva; Hartmann, Wolfgang; Juergens, Heribert; et al. (Clinical Cancer Research, 2016)
The application of the tumor-specific genomic fusion sequence as noninvasive biomarker for therapy monitoring in Ewing sarcoma (EwS) has been evaluated.EwS xenograft mouse models were used to explore detectability in small plasma volumes and correlation of genomic EWSR1-FLI1 copy numbers with tumor burden. Furthermore, 234 blood samples from 20 EwS patients were analyzed before and during multimodal treatment. EWSR1 fusion sequence levels in patients' plasma were quantified using droplet digital PCR and compared with tumor volumes calculated from MRI or CT imaging studies.Kinetics of EWSR1 fusion sequence copy numbers in the plasma are correlated with changes of the tumor volume in patients with localized and metastatic disease. The majority of patients showed a fast reduction of cell-free tumor DNA (ctDNA) during initial chemotherapy. Recurrence of increasing ctDNA levels signalized relapse development.Genomic fusion sequences represent promising noninvasive biomarkers for improved therapy monitoring in EwS. Until now, response assessment is largely based on MRI and CT imaging, implying restrictions on closely repeated performance and limitations on the differentiation between vital tumor and reactive stromal tissue. Particularly in patients with prognostic unfavorable disseminated disease, ctDNA is a valuable addition for the assessment of therapy response. Clin Cancer Res; 22(17); 4356-65. ©2016 AACR.
EVALuna2:6851

Genotype, Clinical Course, and Therapeutic Decision Making in 76 Infants with Severe Generalized Junctional Epidermolysis Bullosa - Hammersen, Johanna; Has, Cristina; Naumann-Bartsch, Nora; Stachel, Daniel; Kiritsi, Dimitra; Söder, Stephan; Tardieu, Mathilde; Metzler, Markus; Bruckner-Tuderman, Leena; Schneider, Holm (Journal of Investigative Dermatology, 2016)
Severe generalized junctional epidermolysis bullosa, a lethal hereditary blistering disorder, is usually treated by palliative care. Allogeneic stem cell transplantation (SCT) has been proposed as a therapeutic approach, yet without clinical evidence. Decision making was evaluated retrospectively in 76 patients with severe generalized junctional epidermolysis bullosa born in the years 2000-2015. The diagnosis was based on the absence of laminin-332 in skin biopsies. With an incidence of 1 of 150,000, severe generalized junctional epidermolysis bullosa occurred more often than published previously. Eleven as yet unreported mutations in the laminin-332 genes were detected. Although patients homozygous for the LAMB3 mutation c.1903C>T lived longer than the others, life expectancy was greatly diminished (10.8 vs. 4.6 months). Most patients failed to thrive. In two patients with initially normal weight gain, the decision for SCT from haploidentical bone marrow or peripheral blood was made. Despite transiently increasing skin erosions, the clinical status of both subjects stabilized for several weeks after SCT, but finally deteriorated. Graft cells, but no laminin-332, were detected in skin biopsies. The patients died 96 and 129 days after SCT, respectively, one of them after receiving additional skin grafts. Treatment of severe generalized junctional epidermolysis bullosa by SCT is a last-ditch attempt still lacking proof of efficacy.
EVALuna2:6828

Genotype-phenotype correlation in boys with X-linked hypohidrotic ectodermal dysplasia - Burger, Kristin; Schneider, Anne-Theres; Wohlfart, Sigrun; Kiesewetter, Franklin; Huttner, Kenneth; Johnson, Ramsey; Schneider, Holm (American Journal of Medical Genetics Part A, 2014)
X-linked hypohidrotic ectodermal dysplasia (XLHED), the most frequent form of ectodermal dysplasia, is a genetic disorder of ectoderm development characterized by malformation of multiple ectodermal structures such as skin, hair, sweat and sebaceous glands, and teeth. The disease is caused by a broad spectrum of mutations in the gene EDA. Although XLHED symptoms show inter-familial and intra-familial variability, genotype-phenotype correlation has been demonstrated with respect to sweat gland function. In this study, we investigated to which extent the EDA genotype correlates with the severity of XLHED-related skin and hair signs. Nineteen male children with XLHED (age range 3-14 years) and seven controls (aged 6-14 years) were examined by confocal microscopy of the skin, quantification of pilocarpine-induced sweating, semi-quantitative evaluation of full facial photographs with respect to XLHED-related skin issues, and phototrichogram analysis. All eight boys with known hypomorphic EDA mutations were able to produce at least some sweat and showed less severe cutaneous signs of XLHED than the anhidrotic XLHED patients (e.g., perioral and periorbital eczema or hyperpigmentation, regional hyperkeratosis, characteristic wrinkles under the eyes). As expected, individuals with XLHED had significantly less and thinner hair than healthy controls. However, there were also significant differences in hair number, diameter, and other hair characteristics between the group with hypomorphic EDA mutations and the anhidrotic patients. In summary, this study indicated a remarkable genotype-phenotype correlation of skin and hair findings in prepubescent males with XLHED.
EVALuna2:18885

Genotype/phenotype correlations in 538 congenital adrenal hyperplasia patients from Germany and Austria: discordances in milder genotypes and in screened versus prescreening patients - Riedl, Stefan; Roehl, Friedrich-Wilhelm; Bonfig, Walter; Braemswig, Juergen; Richter-Unruh, Annette; Fricke-Otto, Susanne; Bettendorf, Markus; Riepe, Felix; Kriegshaeuser, Gernot; Schoenau, Eckhard; Even, Gertrud; Hauffa, Berthold; et al. (Endocrine Connections, 2019)
Congenital adrenal hyperplasia (CAH) due to CYP21A2 gene mutations is associated with a variety of clinical phenotypes (salt wasting, SW; simple virilizing, SV; nonclassical, NC) depending on residual 21-hydroxylase activity. Phenotypes and genotypes correlate well in 80-90% of cases. We set out to test the predictive value of CAH phenotype assignment based on genotype classification in a large multicenter cohort. A retrospective evaluation of genetic data from 538 CAH patients (195 screened) collected from 28 tertiary centers as part of a German quality control program was performed. Genotypes were classified according to residual 21-hydroxylase activity (null, A, B, C) and assigned clinical phenotypes correlated with predicted phenotypes, including analysis of Prader stages. Ultimately, concordance of genotypes with clinical phenotypes was compared in patients diagnosed before or after the introduction of nationwide CAH-newborn screening. Severe genotypes (null and A) correlated well with the expected phenotype (SW in 97 and 91%, respectively), whereas less severe genotypes (B and C) correlated poorly (SV in 45% and NC in 57%, respectively). This was underlined by a high degree of virilization in girls with C genotypes (Prader stage >1 in 28%). SW was diagnosed in 90% of screening-positive babies with classical CAH compared with 74% of prescreening patients. In our CAH series, assigned phenotypes were more severe than expected in milder genotypes and in screened vs prescreening patients. Diagnostic discrimination between phenotypes based on genotypes may prove overcome due to the overlap in their clinical presentations.
CRIS-Team WoS Importer:2019-03-20

Genotype-phenotype correlations in children and adolescents with nonclassical congenital adrenal hyperplasia due to 21-hydroxylase deficiency. - Dörr, Helmuth-Günther; Schulze, Nadja; Bettendorf, Markus; Binder, Gerhard; Bonfig, Walter; Denzer, Christian; Dunstheimer, Desirée; Salzgeber, Kirsten; Schmidt, Heinrich; Schwab, Karl-Otfried; Voss, Egbert; Wabitsch, Martin; et al. (Molecular and Cellular Pediatrics, 2020)
BACKGROUND: Nonclassical congenital adrenal hyperplasia due to 21-hydroxylase deficiency is caused by mutations in the active 21-hydroxylase gene (CYP21A2). The clinical symptoms can vary greatly. To date, no systematic studies have been undertaken in Germany. AIMS: Description of the phenotype, evaluation of the diagnostics and genotype-phenotype correlation PATIENTS AND METHODOLOGY: Retrospective analysis of the data of 134 patients (age range 0.1-18.6 years) in a multicentre study covering 10 paediatric endocrinology centres in Bavaria and Baden-Württemberg. The data was gathered on site from the medical records. Two hundred and thirty-three alleles with a mutation of the CYP21A2 gene were identified in 126 patients. A genotype-phenotype correlation of the mutation findings was undertaken (C1, severe/mild; C2, mild/mild). Individuals with a heterozygous mutation of the CYP21A2 were also included (C3). The data was collected with the approval of the ethics committee of the University Hospital of Erlangen during the period of 2014 and 2015. RESULTS (MW ± SD): One hundred and seventeen out of 134 patients (115 f, 29 m) were symptomatic. The chronological age (CA) at diagnosis was 7.1 ± 4.4 years. The most frequent symptom (73.5%) was premature pubarche. The height-SDS on diagnosis was 0.8 ± 1.3 and the BMI-SDS was 0.8 ± 1.2. Bone age (BA) was ascertained in 82.9% of the symptomatic patients. The difference between BA and CA was 1.9 ± 1.4 years. Basal 17OHP concentrations were 14.5 ± 19.1 ng/ml (18 patients < 2 ng/ml). In total, 58.1% mild and 34.7% severe mutations were found. The most common mutation was p.Val281Leu (39.1%); 65.8% of the patients could be allocated to group C1. No phenotypical differences were found between the 3 mutation groups. The 17OHP levels (basal and after ACTH) in the standard ACTH stimulation test were highest in group C1 and also significantly higher in group C2 as in C3, the ACTH-stimulated cortisol levels (ng/ml) were significantly lower in groups C1 (192.1 ± 62.5) and C2 (218 ± 50) than in C3 (297.3 ± 98.7). CONCLUSION: Most of the patients have symptoms of mild androgenisation. Male patients are underdiagnosed. Diagnostics are not standardised. Differences between the types of mutations are found in the hormone concentrations but not in phenotype. We speculate that further, as yet not clearly defined, factors are responsible for the development of the respective phenotypes.
EVALuna2:385044

Genotyping circulating tumor DNA of pediatric Hodgkin lymphoma - Desch, Ann Kathrin; Hartung, Kristin; Botzen, Ante; Brobeil, Alexander; Rummel, Mathias; Kurch, Lars; Georgi, Thomas; Jox, Theresa; Bielack, Stefan; Burdach, Stefan; Classen, Carl Friedrich; Claviez, Alexander; et al. (Leukemia, 2019)
We used hybrid capture-targeted next-generation sequencing of circulating cell-free DNA (ccfDNA) of pediatric Hodgkin lymphoma (PHL) patients to determine pathogenic mechanisms and assess the clinical utility of this method. Hodgkin-Reed/Sternberg (HRS) cell-derived single nucleotide variants, insertions/deletions, translocations and VH-DH-JH rearrangements were detected in pretherapy ccfDNA of 72 of 96 patients. Number of variants per patient ranged from 1 to 21 with allele frequencies from 0.6 to 42%. Nine translocation breakpoints were detected. Genes involved in JAK/STAT, NFkB and PI3K signaling and antigen presentation were most frequently affected. SOCS1 variants, mainly deletions, were found in most circulating tumor (ct) DNAs, and seven of the nine translocation breakpoints involved SOCS1. Analysis of VH-DH-JH rearrangements revealed an origin of PHL HRS cells from partially selected germinal center B cells. Amounts of pretherapy ctDNA were correlated with metabolic tumor volumes. Furthermore, in all ccfDNA samples of 43 patients with early response assessment quantitative qPET < 3, indicative of a favorable clinical course, ctDNA was not detectable. In contrast, in five of six patients with qPET > 3, indicative of an unfavorable clinical course, ctDNA remained detectable. ccfDNA analysis of PHL is thus a suitable approach to determine pathogenic mechanisms and monitor therapy response.
CRIS-Team Scopus Importer:2019-08-27

Genotyp-Phänotyp-Korrelation bei Zwillingsmädchen mit nichtklassischem adrenogenitalem Syndrom und 21-Hydroxylase-Defekt - Dörr, Helmuth-Günther; Oppelt, Patricia (Gynakologische Endokrinologie, 2020)
CRIS-Team Scopus Importer:2020-03-06

Genotyp-Phänotyp-Korrelationen bei Kindern und Jugendlichen mit nichtklassischem adrenogenitalen Syndrom mit 21-Hydroxylase-Defekt - Dörr, Helmuth-Günther; Schulze, Nadja; Bettendorf, M.; Binder, G.; Bonfig, W.; Denzer, C.; Dunstheimer, D.; Salzgeber, K.; Schmidt, H.; Schwab, K. O.; Voss, E.; Wabitsch, M.; et al. (Monatsschrift Kinderheilkunde, 2020)
Background: Nonclassical congenital adrenal hyperplasia due to 21-hydroxylase deficiency (NCCAH) is caused by mutations in the active 21-hydroxylase gene (CYP21A2). The clinical symptoms can vary greatly. To date, no systematic studies have been undertaken in Germany. Objective: Description of the phenotype, evaluation of the diagnostics, genotype-phenotype correlation. Patients and methodology: Retrospective analysis of the data of 134 patients (age range 0.1–18.6 years) in a multicenter study covering 10 pediatric endocrinology centers in Bavaria and Baden-Württemberg. The data were collected on site from the medical records. In 126 patients 233 alleles with a mutation of the CYP21A2 gene were identified. A genotype-phenotype correlation of the mutation findings was undertaken (C1: severe/mild, C2: mild/mild). Individuals with a heterozygote mutation (C3) were also included in the analysis. The data were collected with the approval of the ethics committee of the University Hospital of Erlangen during the time period of 2014 and 2015. Results (MW ± SD): Out of 134 patients (115 female, 29 male) 117 were symptomatic. The chronological age (CA) at diagnosis was 7.1 ± 4.4 years. The most frequent symptom (73.5%) was premature pubarche. The height-standard deviation score (SDS) on diagnosis was 0.8 ± 1.3 and the body mass index (BMI)-SDS was 0.8 ± 1.2. Bone age (BA) was ascertained in 82.9% of the symptomatic patients. The difference between BA and CA was 1.9 ± 1.4 years. Basal 17-hydroxyprogesterone (17-OHP) concentrations were 14.5 ± 19.1 ng/ml (18 patients <2 ng/ml). In total 58.1% mild and 34.7% severe mutations were found. The most common mutation (39.1%) was p.Val281Leu and 65.8% of the patients could be allocated to group C1. No phenotypical differences were found between the three mutation groups. The 17-OHP levels (basal and after ACTH) in the ACTH test were highest in group C1 and also significantly higher in group C2 than in group C3. The ACTH-stimulated cortisol levels (ng/ml) were significantly lower in groups C1 (192.1 ± 62.5) and C2 (218 ± 50) than in C3 (297.3 ± 98.7). Conclusion: Most of the patients had symptoms of mild androgenization. Male patients were underdiagnosed. The diagnostics were not standardized. Differences between the types of mutations were found in the hormone concentrations but not in the phenotype. We speculate that further, as yet not clearly defined, factors are responsible for the development of the respective phenotypes.
CRIS-Team Scopus Importer:2020-07-24
Keywords: 17-OHP; ACTH stimulation test; Androgenisation; CYP21A2 gene mutations; Premature pubarche

Graves’ disease in children with Down syndrome - Cebeci, Ayse Nurcan; Schempp, Vera; Förtsch, Katharina; Gohlke, Bettina; Marx, Martin; Dörr, Helmuth-Günther; Wölfle, Joachim (Endocrine Connections, 2024)
While subclinical or overt hypothyroidism are common in Down syndrome (DS); Graves’ disease (GD) is rare (ranges 0.6–3%). We aimed to evaluate the clinical features, course, and treatment of GD in children with DS and compare them with those without DS. Among 161 children with GD, 13 (8 female, 5 male) had DS (8%). Data were collected retrospectively from patients’ medical records. The mean age at diagnosis was 10.6 ± 4.5 years, with a female-to-male ratio 1.6:1. The main symptoms were weight loss (n = 6), increased irritability (n = 3), and increased sweating (n = 3). None had orbitopathy. Seven of 11 patients with a thyroid ultrasound at diagnosis had a goitre. On admission, all had thyroid-stimulating hormone (TSH) <0.01 mU/L (normal range (NR): 0.51–4.30), free triiodothyronine, free thyroxine (mean ± s.d.), and thyrotrophin receptor antibodies (median, range) were 22.2 ± 10.2 pmol/L (NR: 3.5–8.1), 50.2 ± 18.7 pmol/L (NR 12.6–20.9), and 17.0 (2.89–159.0) U/L (NR <1), respectively. Patients were treated either with methimazole (n = 10) or carbimazole (n = 3), a dose of 0.54 ± 0.36 mg/kg/day. The treatment was ‘block and replace’ in ten patients and ‘dose titration’ in three patients, with a mean duration of 43.4 ± 11.0 months. Of 13 patients, four are still receiving primary treatment, three are in remission, one patient had two medically treated recurrences, three underwent surgery without complications, and two patients were lost to follow-up. Our data show that the clinical course of GD in patients with DS was similar to those without DS and suggest that a prolonged medical therapy should be the preferred option.
CRIS-Team Scopus Importer:2024-06-28
Keywords: anti-thyroid drug medication; autoimmune thyroiditis; Down syndrome; Graves’ disease; hyperthyroidism

Größenwachstum und Knochengesundheit bei Erkrankungen der Wachstumsfuge und des Knochens: Möglichkeiten und Grenzen einer GH-Therapie - Wölfle, Joachim; Bettendorf, M.; Bechtold-Dalla Pozza, S.; Binder, G.; Grasemann, C.; Reinehr, T.; Semler, O.; Dörr, Helmuth-Günther (Monatsschrift Kinderheilkunde, 2020)
Background: Genetic, paracrine and endocrine factors influence longitudinal growth in the area of the epiphyseal plates and bone mineralization. Objective: The aim was to review the spontaneous longitudinal growth and bone health in patients with rare bone diseases. Can growth hormone (GH) treatment improve growth and bone health in these diseases? Material and methods: Findings of an expert workshop including literature search on bone health in bone disorders associated with stunted growth and the treatment options. Results: Most patients with osteogenesis imperfecta are of short stature. Additional administration of GH has no influence on adult height and is currently not used. Pseudohypoparathyroidism (PHP) patients with insufficient longitudinal growth and confirmed GH deficiency can be treated with GH and can benefit from the treatment. Children with X‑linked hereditary hypophosphatemic rickets show progressive disproportionate short stature under the current treatment with phosphate and calcitriol. Randomized GH treatment studies resulted in a temporary improvement in body height but not in a significant improvement of adult height. The use of GH is approved for treatment of SHOX-deficient children and is comparably effective as in girls with Turner’s syndrome (TS). Observational studies also suggest that GH treatment can lower the risk of bone fractures, known to be increased in TS. Inflammation, reduced physical activity and malnutrition can result in impaired growth with loss of muscle and bone mass in patients with juvenile idiopathic arthritis (JIA). Studies could demonstrate a positive impact of GH on longitudinal growth, density and geometry of bones and on bone metabolism as well as on muscular mass; however, GH treatment is not approved for patients with JIA. Conclusion: Regarding the various bone diseases mentioned above, all growth disorders have to be considered individually. Apart from longitudinal growth GH can have a positive impact on metabolism, bone mineral content and bone density depending on the indications. The only approved indications for GH treatment are GH deficiency in PHP and children born small for gestational age (SGA) and TS/SHOX deficiency. Apart from increased growth, improvements in bone health in children and adolescents should be discussed as an outcome measure for GH treatment.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Bone; Bone health; Growth; Growth hormone (GH); Growth plate

Guided Multispectral Optoacoustic Tomography for 3D Imaging of the Murine Colon - Knieling, Ferdinand; Brown, Emma L.; Eckstein, Markus; Thoma, Oana-Maria; Wachter, Felix; Mandelbaum, Henriette; Ludwig, Petra; Claßen, Merle; Oraiopoulou, Mariam Eleni; Rother, Ulrich; Neurath, Markus; Wölfle, Joachim; et al. (Advanced Science, 2025)
Multispectral optoacoustic tomography is a promising medical imaging modality that combines light and sound to provide molecular imaging information at depths of several centimeters, based on the optical absorption of endogenous chromophores, such as hemoglobin. Assessment of inflammatory bowel disease has emerged as a promising clinical application of optoacoustic tomography. In this context, preclinical studies in animal models are essential to identify novel disease-specific imaging biomarkers and understand findings from emerging clinical pilot studies, however to-date, these studies have been limited by the precise identification of the bowel wall. Herein, a transrectal-absorber guide is applied, serving as a high-contrast landmark for 3D optoacoustic tomography of the colon. This study shows that guided multispectral optoacoustic tomography is able to measure changes in blood oxygenation status over the course of acute, chemically-induced colitis in mice and correlates with standard disease activity scores. This novel approach depicts intestinal hemoglobin composition non-invasively during murine inflammation. These results underscore the potential for optoacoustic imaging in translational inflammatory bowel disease research.
CRIS-Team Scopus Importer:2025-01-31
Keywords: dextran sodium sulfate induced colitis; inflammatory bowel disease; multispectral optoacoustic tomography; murine acute colitis; optoacoustic imaging; photoacoustic imaging

Guideline Adherence and Registry Recruitment of Congenital Primary Hypothyroidism: Data from the German Registry for Congenital Hypothyroidism (HypoDok) - Thomann, Julia; Tittel, Sascha R.; Voss, Egbert; Oeverink, Rudolf; Palm, Katja; Fricke-Otto, Susanne; Kapelari, Klaus; Holl, Reinhard W.; Wölfle, Joachim; Bettendorf, Markus (International Journal of Neonatal Screening, 2021)
Neonatal screening for congenital primary hypothyroidism (CH) is mandatory in Germany but medical care thereafter remains inconsistent. Therefore, the registry HypoDok of the German Society of Pediatric Endocrinology and Diabetology (DGKED) was analyzed to evaluate the implementation of evidence-based guidelines and to assess the number of included patients. Inclusion criteria were (i) date of birth between 10/2001 and 05/2020 and (ii) increased thyroid-stimulating hormone (TSH) at screening and/or confirmation. The cohort was divided into before (A) and after (B) guideline publication in 02/2011, to assess the guideline's influence on medical care. A total of 659 patients were analyzed as group A (n = 327) and group B (n = 332) representing 17.5% and 10.3% of CH patients identified in the German and Austrian neonatal screening program during the respective time period. Treatment start and thyroxine doses were similar in both groups and consistent with recommendations. Regular follow-ups were documented. In the first three years of life, less than half of the patients underwent audiometry; developmental assessment was performed in 49.3% (A) and 24.8% (B) (p < 0.01). Documentation of CH patient care by pediatric endocrinologists seemed to be established, however, it reflected only a minority of the affected patients. Therefore, comprehensive documentation as an important instrument of quality assurance and evidence-based medicine should be legally enforced and officially funded in order to record, comprehend, and optimize care and outcome in patients with rare diseases such as CH.
CRIS-Team WoS Importer:2021-04-16

Haematological characteristics and spontaneous haematological recovery in Pearson syndrome - Yoshimi, Ayami; Gruenert, Sarah C.; Cario, Holger; Fisch, Aron; Gross-Wieltsch, Ute; Timmermann, Kirsten; Kontny, Udo; Lobitz, Stephan; Odenthal, Helen S.; Schmid, Irene; Uetz, Barbara; Hoell, Tanja; et al. (British Journal of Haematology, 2021)
CRIS-Team Scopus Importer:2021-04-23
Keywords: hematological recovery; mitochondrial disease; Pearson syndrome; single large-scale mitochondrial DNA deletion

Handlungsempfehlung nach der AWMF-S1-Leitlinie Fieberkrämpfe im Kindesalter - Trollmann, Regina (Monatsschrift Kinderheilkunde, 2024)
CRIS-Team Scopus Importer:2024-10-04

Health Problems and Quality of Life of Young Cancer Survivors in the Comprehensive Care for CAYA Program - Elmers, Simon; Beitzen-Heineke, Antonia; Von Grundherr, Julia; Jensen, Wiebke; Koch, Barbara; Mann, Julia; Salchow, Jannike; Sinn, Marianne; Straub, Lesley-Ann; Wegert, Luisa; Vettorazzi, Eik; Bergelt, Corinna; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Health-related quality of life in children and adolescents with tuberous sclerosis complex and their caregivers: A multicentre cohort study from Germany - Willems, Laurent M.; Schubert-Bast, Susanne; Grau, Janina; Hertzberg, Christoph; Kurlemann, Gerhard; Wiemer-Kruel, Adelheid; Bast, Thomas; Bertsche, Astrid; Bettendorf, Ulrich; Fiedler, Barbara; Hahn, Andreas; Hartmann, Hans; et al. (European Journal of Paediatric Neurology, 2021)
Objective: This study aimed to measure health-related quality of life (HRQOL) in children and adolescents with tuberous sclerosis complex (TSC) and quality of life (QOL) and depressive symptoms among caregivers. Methods: Adequate metrics were used to assess HRQOL in children and adolescents with TSC (4–18 years, KINDLR) as well as QOL (EQ-5D) and symptoms of depression (BDI-II) among caregivers. Predictors for reduced HRQOL and depressive symptoms were identified by variance analysis, ordinal regression, and bivariate correlation. Results: The mean HRQOL score was 67.9 ± 12.7, and significantly lower values were associated with increasing age, attending special needs education, TSC-associated psychiatric symptoms, and drug-related adverse events. The mean QOL of caregivers was 85.4 ± 15.7, and caregiver's sex, TSC mutation locus, familial TSC clustering, special needs education, degree of disability, care dependency, presence of TSC-associated psychiatric symptoms, and TSC severity were significant predictors of lower QOL. Depressive symptoms were identified in 45.7% of caregivers, associated with female sex of the caregiver, familial TSC clustering, special needs education, and presence of TSC-associated psychiatric symptoms of the child. Multivariate regression analysis revealed adolescence and drug-related adverse events as significant predictors for lower HRQOL in TSC children, and TSC2 variants predicted lower QOL and depressive symptoms in caregivers. Conclusion: Compared with other chronic diseases, such as headache, diabetes or obesity, children with TSC have significantly lower HRQOL, which further decreases during adolescence. A decreased HRQOL of patients correlates with a lower QOL and increased symptoms of depression of their caregivers. These results may improve the comprehensive therapy and care of children and adolescents with TSC and their families and caregivers. Trial registration: DRKS, DRKS00016045. Registered 01 March 2019, http://www.drks.de/DRKS00016045.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Angiomyolipoma; Depression; Epilepsy; Seizure; TSC

Hemoglobin A1c patterns of youth with type 1 diabetes 10 years post diagnosis from 3 continents - Sherr, Jennifer L.; Schwandt, Anke; Phelan, Helen; Clements, Mark A.; Holl, Reinhard W.; Benitez-Aguirre, Paul Z.; Miller, Kellee M.; Wölfle, Joachim; Dover, Thomas; Maahs, David M.; Fröhlich-Reiterer, Elke; Craig, Maria E. (Pediatrics, 2021)
Objectives: Distinct hemoglobin A1c (HbA1c) trajectories during puberty are identified in youth with established type 1 diabetes (T1D). We used data from 3 international registries to evaluate whether distinct HbA1c trajectories occur from T1D onset. Methods: Participants were <18 years old at diagnosis with at least 1 HbA1c measured within 12 months post diagnosis, along with ≥3 duration-year-aggregated HbA1c values over 10 years of follow-up. Participants from the Australasian Diabetes Data Network (n = 7292), the German-Austrian-Luxembourgian-Swiss diabetes prospective follow-up initiative (Diabetes Patienten Verlaufsdokumentation) (n = 39 226) and the US-based Type 1 Diabetes Exchange Clinic Registry (n = 3704) were included. With group-based trajectory modeling, we identified unique HbA1c patterns from the onset of T1D. Results: Five distinct trajectories occurred in all 3 registries, with similar patterns of proportions by group. More than 50% had stable HbA1c categorized as being either low stable or intermediate stable. Conversely, ∼15% in each registry were characterized by stable HbA1c >8.0% (high stable), and ∼11% had values that began at or near the target but then increased (target increase). Only ∼5% of youth were above the target from diagnosis, with an increasing HbA1c trajectory over time (high increase). This group differed from others, with higher rates of minority status and an older age at diagnosis across all 3 registries (P ≤ .001). Conclusions: Similar postdiagnostic HbA1c patterns were observed across 3 international registries. Identifying the youth at the greatest risk for deterioration in HbA1c over time may allow clinicians to intervene early, and more aggressively, to avert increasing HbA1c.
CRIS-Team Scopus Importer:2021-09-10

HIBCH deficiency in a patient with phenotypic characteristics of mitochondrial disorders - Reuter, Miriam; Sass, Joern Oliver; Leis, Thomas; Koehler, Julia; Mayr, Johannes A.; Feichtinger, Rene G.; Rauh, Manfred; Schanze, Ina; Baehr, Luzy; Trollmann, Regina; Uebe, Steffen; Ekici, Arif Bülent; et al. (American Journal of Medical Genetics Part A, 2014)
HIBCH (3-hydroxyisobutyryl-CoA hydrolase) deficiency (MIM #250620) is a rare autosomal recessive inborn error of metabolism, leading to a block in the catabolic pathway of the amino acid valine and presumably to accumulation of toxic valine metabolites in mitochondria. Only three families with HIBCH deficiency and biallelic HIBCH mutations have been described. We report on a further patient, first child of healthy consanguineous parents, with severe developmental delay, seizures, hyperintensities of the basal ganglia on magnetic resonance imaging (MRI), progressive brain atrophy, optic nerve atrophy, repeatedly elevated blood lactate, and respiratory chain complexes I, I + III and cytochrome c oxidase deficiencies with borderline depletion of mitochondrial DNA in muscle tissue. Laboratory findings in blood and skeletal muscle were inconsistent and did not allow a definite diagnosis, but supported the hypothesis of mitochondrial dysfunction. Homozygosity mapping and whole-exome sequencing revealed a homozygous one-base pair insertion in HIBCH. Deficiency of enzyme activity was confirmed in cultured fibroblasts. Although relatively unspecific, the clinical features were similar to those of the previously reported cases. Given the clinical variability and large number of differential diagnoses, the prevalence of HIBCH deficiency is probably underestimated. Next-generation sequencing approaches are an effective tool for identifying the underlying genetic basis in patients suspected of mitochondrial disorders. © 2014 Wiley Periodicals, Inc.
EVALuna2:9220

High-Dose Treosulfan and Melphalan as Consolidation Therapy Versus Standard Therapy for High-Risk (Metastatic) Ewing Sarcoma - Koch, Raphael; Gelderblom, Hans; Haveman, Lianne; Brichard, Benedicte; Jürgens, Heribert; Cyprova, Sona; Van Den Berg, Henk; Hassenpflug, Wolf; Raciborska, Anna; Ek, Torben; Baumhoer, Daniel; Egerer, Gerlinde; et al. (Journal of Clinical Oncology, 2022)
PURPOSEEwing 2008R3 was conducted in 12 countries and evaluated the effect of treosulfan and melphalan high-dose chemotherapy (TreoMel-HDT) followed by reinfusion of autologous hematopoietic stem cells on event-free survival (EFS) and overall survival in high-risk Ewing sarcoma (EWS).METHODSPhase III, open-label, prospective, multicenter, randomized controlled clinical trial. Eligible patients had disseminated EWS with metastases to bone and/or other sites, excluding patients with only pulmonary metastases. Patients received six cycles of vincristine, ifosfamide, doxorubicin, and etoposide induction and eight cycles of vincristine, actinomycin D, and cyclophosphamide consolidation therapy. Patients were randomly assigned to receive additional TreoMel-HDT or no further treatment (control). The random assignment was stratified by number of bone metastases (1, 2-5, and > 5). The one-sided adaptive-inverse-normal-4-stage-design was changed after the first interim analysis via Müller-Schäfer method.RESULTSBetween 2009 and 2018, 109 patients were randomly assigned, and 55 received TreoMel-HDT. With a median follow-up of 3.3 years, there was no significant difference in EFS between TreoMel-HDT and control in the adaptive design (hazard ratio [HR] 0.85; 95% CI, 0.55 to 1.32, intention-to-treat). Three-year EFS was 20.9% (95% CI, 11.5 to 37.9) in TreoMel-HDT and 19.2% (95% CI, 10.8 to 34.4) in control patients. The results were similar in the per-protocol collective. Males treated with TreoMel-HDT had better EFS compared with controls: median 1.0 years (95% CI, 0.8 to 2.2) versus 0.6 years (95% CI, 0.5 to 0.9); P =.035; HR 0.52 (0.28 to 0.97). Patients age < 14 years benefited from TreoMel-HDT with a 3-years EFS of 39.3% (95% CI, 20.4 to 75.8%) versus 9% (95% CI, 2.4 to 34); P =.016; HR 0.40 (0.19 to 0.87). These effects were similar in the per-protocol collective. This observation is supported by comparable results from the nonrandomized trial EE99R3.CONCLUSIONIn patients with very high-risk EWS, additional TreoMel-HDT was of no benefit for the entire cohort of patients. TreoMel-HDT may be of benefit for children age < 14 years.
CRIS-Team Scopus Importer:2022-06-10

High molecular diagnostic yields and novel phenotypic expansions involving syndromic anorectal malformations - Reutter, Heiko Martin (European Journal of Human Genetics, 2023)
CRIS-Team Scopus Importer:2023-01-13

High Platelet Counts, Thrombosis, Bleeding Signs, and Acquired Von Willebrand Syndrome at Diagnosis of Pediatric Chronic Myeloid Leukemia - Suttorp, Meinolf; Knoefler, Ralf; Deutsch, Helene; Paul, Franziska; Tiebel, Oliver; Metzler, Markus; Millot, Frederic (BLOOD, 2019)
CRIS-Team WoS Importer:2021-10-18

High-resolution label-free mapping of murine kidney vasculature by raster-scanning optoacoustic mesoscopy: an ex vivo study - Goebel, Colin A.; Brown, Emma; Fahlbusch, Fabian; Wagner, Alexandra; Buehler, Adrian; Raupach, Thomas; Hohmann, Martin; Späth, Moritz; Burton, Neal; Wölfle, Joachim; Schmidt, Michael; Hartner, Andrea; et al. (Molecular and Cellular Pediatrics, 2022)
Background: Chronic kidney disease (CKD) is a global burden affecting both children and adults. Novel imaging modalities hold great promise to visualize and quantify structural, functional, and molecular organ damage. The aim of the study was to visualize and quantify murine renal vasculature using label-free raster scanning optoacoustic mesoscopy (RSOM) in explanted organs from mice with renal injury. Material and methods: For the experiments, freshly bisected kidneys of alpha 8 integrin knock-out (KO) and wildtype mice (WT) were used. A total of n=7 female (n=4 KO, n=3 WT) and n=6 male animals (n=2 KO, n=4 WT) aged 6 weeks were examined with RSOM optoacoustic imaging systems (RSOM Explorer P50 at SWL 532nm and/or ms-P50 imaging system at 532 nm, 555 nm, 579 nm, and 606 nm). Images were reconstructed using a dedicated software, analyzed for size and vascular area and compared to standard histologic sections. Results: RSOM enabled mapping of murine kidney size and vascular area, revealing differences between kidney sizes of male (m) and female (f) mice (merged frequencies (MF) f vs. m: 52.42±6.24 mm2 vs. 69.18±15.96 mm2, p=0.0156) and absolute vascular area (MF f vs. m: 35.67±4.22 mm2 vs. 49.07±13.48 mm2, p=0.0036). Without respect to sex, the absolute kidney area was found to be smaller in knock-out (KO) than in wildtype (WT) mice (WT vs. KO: MF: p=0.0255) and showed a similar trend for the relative vessel area (WT vs. KO: MF p=0.0031). Also the absolute vessel areas of KO compared to WT were found significantly different (MF p=0.0089). A significant decrease in absolute vessel area was found in KO compared to WT male mice (MF WT vs. KO: 54.37±9.35 mm2 vs. 34.93±13.82 mm2, p=0.0232). In addition, multispectral RSOM allowed visualization of oxygenated and deoxygenated parenchymal regions by spectral unmixing. Conclusion: This study demonstrates the capability of RSOM for label-free visualization of differences in vascular morphology in ex vivo murine renal tissue at high resolution. Due to its scalability optoacoustic imaging provides an emerging modality with potential for further preclinical and clinical imaging applications.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Chronic kidney disease; Ex vivo kidney imaging; msRSOM; Optoacoustic; Photoacoustic; Raster scanning optoacoustic mesoscopy; RSOM

High-resolution pediatric reference intervals for 15 biochemical analytes described using fractional polynomials - Zierk, Jakob; Baum, Hannsjörg; Bertram, Alexander; Boeker, Martin; Buchwald, Armin; Cario, Holger; Christoph, Jürgen; Frühwald, Michael C.; Groß, Hans Jürgen; Groening, Arndt; Gscheidmeier, Thomas; Hoff, Torsten; et al. (Clinical Chemistry and Laboratory Medicine, 2021)
Assessment of children's laboratory test results requires consideration of the extensive changes that occur during physiological development and result in pronounced sex- and age-specific dynamics in many biochemical analytes. Pediatric reference intervals have to account for these dynamics, but ethical and practical challenges limit the availability of appropriate pediatric reference intervals that cover children from birth to adulthood. We have therefore initiated the multi-center data-driven PEDREF project (Next-Generation Pediatric Reference Intervals) to create pediatric reference intervals using data from laboratory information systems. We analyzed laboratory test results from 638,683 patients (217,883-982,548 samples per analyte, a median of 603,745 test results per analyte, and 10,298,067 test results in total) performed during patient care in 13 German centers. Test results from children with repeat measurements were discarded, and we estimated the distribution of physiological test results using a validated statistical approach (kosmic). We report continuous pediatric reference intervals and percentile charts for alanine transaminase, aspartate transaminase, lactate dehydrogenase, alkaline phosphatase, γ-glutamyl-transferase, total protein, albumin, creatinine, urea, sodium, potassium, calcium, chloride, anorganic phosphate, and magnesium. Reference intervals are provided as tables and fractional polynomial functions (i.e., mathematical equations) that can be integrated into laboratory information systems. Additionally, Z-scores and percentiles enable the normalization of test results by age and sex to facilitate their interpretation across age groups. The provided reference intervals and percentile charts enable precise assessment of laboratory test results in children from birth to adulthood. Our findings highlight the pronounced dynamics in many biochemical analytes in neonates, which require particular consideration in reference intervals to support clinical decision making most effectively.
CRIS-Team Scopus Importer:2021-03-05
Keywords: continuous reference intervals; data mining; indirect reference intervals; pediatric reference intervals; percentile charts

High sensitivity and clonal stability of the genomic fusion as single marker for response monitoring in ETV6-RUNX1-positive acute lymphoblastic leukemia - Hoffmann, Jana; Krumbholz, Manuela; Gutiérrez, Helia Pimentel; Fillies, Marion; Szymansky, Annabell; Bleckmann, Kirsten; zur Stadt, Udo; Köhler, Rolf; Kuiper, Roland P.; Horstmann, Martin; von Stackelberg, Arend; Eckert, Cornelia; et al. (Pediatric Blood & Cancer, 2019)
Background: Assessment of minimal residual disease (MRD) is an integral component for response monitoring and treatment stratification in acute lymphoblastic leukemia (ALL). We aimed to evaluate the genomic ETV6-RUNX1 fusion sites as a single marker for MRD quantification. Procedure: In a representative, uniformly treated cohort of pediatric relapsed ALL patients (n = 52), ETV6-RUNX1 fusion sites were compared to the current gold standard, immunoglobulin/T-cell receptor (Ig/TCR) gene rearrangements. Results: Primer/probe sets designed to ETV6-RUNX1 fusions achieved significantly more frequent a sensitivity and a quantitative range of at least 10 –4 compared to the gold standard with 100% and 73% versus 76% and 47%, respectively. The breakpoint sequence was identical at diagnosis and relapse in all tested cases. There was a high degree of concordance between quantitative MRD results assessed using ETV6-RUNX1 and the highest Ig/TCR marker (Spearman's 0.899, P <.01) with differences >½ log-step in only 6% of patients. A high proportion of ETV6-RUNX1-positive ALL relapses (40%) in our cohort showed a poor response to induction treatment at relapse, and therefore had an indication for hematopoietic stem cell transplantation, demonstrating the need of accurate identification of this subgroup. Conclusions: ETV6-RUNX1 fusion sites are highly sensitive and reliable MRD markers. Our data confirm that they are unaffected by clonal evolution and selection during front-line and second-line chemotherapy in contrast to Ig/TCR rearrangements, which require several markers per patient to compensate for the observed loss of target clones. In future studies, the genomic ETV6-RUNX1 fusion can be used as single MRD marker.
CRIS-Team Scopus Importer:2019-05-17
Keywords: acute lymphoblastic leukemia; fusion gene; genomic breakpoint; minimal residual disease; response monitoring

Histopathological proof of the pathogenicity of a rare GFAP mutation in a patient with flaccid paraparesis - Brackmann, Florian; Coras, Roland; Rössler, Karl; Kraus, Cornelia; Rompel, Oliver; Trollmann, Regina (Brain & Development, 2017)
Infantile Alexander disease is a rare progressive leukodystrophy caused by autosomal dominant mutations in the (GFAP) gene typically presenting with psychomotor retardation, progressive macrocephaly and refractory epilepsy. Neuroradiological hallmarks are extensive white matter lesions with frontal preponderance as well as signal intensity changes of basal ganglia and medulla oblongata with variable contrast enhancement. Here, we report an atypical manifestation in a 21-month-old boy presenting with flaccid paraparesis and areflexia. Cognitive, visual as well as fine motor skills and muscular strength of the upper extremities were appropriate for age. Weight and height as well as head circumference were within normal range. Clinical or electroencephalographic signs of seizures were absent. Cranial MRI demonstrated bifrontal cystic tumorous lesions with partial contrast rims, as well as space-occupying focal lesions of the caudate nuclei. Spinal MRI revealed swelling of the lumbar and cervical spinal cord. CSF and blood chemistry showed normal results. Histopathology of a subcortical lesion showed large amounts of Rosenthal fibers and protein droplets characteristic of Alexander disease. Sequencing detected a heterozygous mutation of the GFAP gene (c.205G > A; p.(Glu69Lys)) that has been reported before as probably pathogenetic in another case of lower spinal involvement. This well documented case draws attention to atypical spinal manifestations of Alexander disease and gives histopathological proof of the pathogenetic role of a rare GFAP mutation with marked spinal involvement.
EVALuna2:9396

Hodgkin lymphoma: hypodense lesions in mediastinal masses - Damek, Adrian; Kurch, Lars; Franke, Friedrich Christian; Attarbaschi, Andishe; Beishuizen, Auke; Cepelova, Michaela; Ceppi, Francesco; Daw, Stephen; Dieckmann, Karin; Fernández-Teijeiro, Ana; Feuchtinger, Tobias; Flerlage, Jamie E.; et al. (Scientific Reports, 2024)
Hypodense volumes (HDV) in mediastinal masses can be visualized in a computed tomography scan in Hodgkin lymphoma. We analyzed staging CT scans of 1178 patients with mediastinal involvement from the EuroNet-PHL-C1 trial and explored correlations of HDV with patient characteristics, mediastinal tumor volume and progression-free survival. HDV occurred in 350 of 1178 patients (29.7%), typically in larger mediastinal volumes. There were different patterns in appearance with single lesions found in 243 patients (69.4%), multiple lesions in 107 patients (30.6%). Well delineated lesions were found in 248 cases (70.1%), diffuse lesions were seen in 102 cases (29.1%). Clinically, B symptoms occurred more often in patients with HDV (47.7% compared to 35.0% without HDV (p = 0.039)) and patients with HDV tended to be in higher risk groups. Inadequate overall early-18F-FDG-PET-response was strongly correlated with the occurrence of hypodense lesions (p < 0.001). Patients with total HDV > 40 ml (n = 80) had a 5 year PFS of 79.6% compared to 89.7% (p = 0.01) in patients with HDV < 40 ml or no HDV. This difference in PFS is not caused by treatment group alone. HDV is a common phenomenon in HL with mediastinal involvement.
CRIS-Team Scopus Importer:2024-07-05
Keywords: Hodgkin lymphoma; Hypodense lesion; Thymic cyst; Tomography; X-ray computed

Hologene 5: A Phase II/III Clinical Trial of Combined Cell and Gene Therapy of Junctional Epidermolysis Bullosa - De Rosa, Laura; Enzo, Elena; Zardi, Giulia; Bodemer, Christine; Magnoni, Cristina; Schneider, Holm; De Luca, Michele (Frontiers in Genetics, 2021)
Epidermolysis bullosa (EB) is a group of devastating genetic diseases characterized by skin and mucosal fragility and formation of blisters, which develop either spontaneously or in response to minor mechanical trauma. There is no definitive therapy for any form of EB. Intermediate junctional EB (JEB) caused by mutations in the gene LAMB3 has been the first genetic skin disease successfully tackled by ex vivo gene therapy. Here, we present a multicenter, open-label, uncontrolled phase II/III study that aims at confirming the efficacy of Hologene 5, a graft consisting of cultured transgenic keratinocytes and epidermal stem cells and meant to combine cell and gene therapy for the treatment of LAMB3-related JEB. Autologous clonogenic keratinocytes will be isolated from patients’ skin biopsies, genetically corrected with a gamma-retroviral vector (γRV) carrying the full-length human LAMB3 cDNA and plated onto a fibrin support (144cm2). The transgenic epidermis will be transplanted onto surgically prepared selected skin areas of at least six JEB patients (four pediatric and two adults). Evaluation of clinical efficacy will include, as primary endpoint, a combination of clinical parameters, such as percentage of re-epithelialization, cellular, molecular, and functional parameters, mechanical stress tests, and patient-reported outcome (PRO), up to 12months after transplantation. Safety and further efficacy endpoints will also be assessed during the clinical trial and for additional 15years in an interventional non-pharmacological follow-up study. If successful, this clinical trial would provide a therapeutic option for skin lesions of JEB patients with LAMB3 mutations and pave the way to a combined cell and gene therapy platform tackling other forms of EB and different genodermatoses. Clinical Trial Registration: EudraCT Number: 2018-000261-36.
CRIS-Team Scopus Importer:2021-10-01
Keywords: cell and gene therapy; clinical trial; epidermal stem cell; epidermolysis bullosa; genodermatoses; skin

Homozygous Biallelic KRT5 Mutations in Epidermolysis Bullosa Simplex, Including a Complete Human Keratin 5 "Knock-Out", in Families with Extensive Consanguinity - Vahidnezhad, H.; Youssefian, L.; Daneshpazhooh, M.; Mahmoudi, H.; Kariminejad, A.; Fischer, J.; Christiansen, J.; Schneider, Holm; Guy, A.; Liu, L.; Mcgrath, J. A.; Has, C.; et al. (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2019)
CRIS-Team WoS Importer:2019-09-27

Homozygous familial hypercholesterolemia with severe involvement of the aortic valve—A sibling-controlled case study on the efficacy of lipoprotein apheresis - Galiano, Matthias; Hammersen, Johanna; Sauerstein, Katja; Blessing, Holger; Rümmele, Petra; Purbojo, Ariawan; Schöber, Martin; Moosmann, Julia; Raffelsbauer, Gunter; Heibges, Andreas; Klingel, Reinhard (Journal of Clinical Apheresis, 2020)
Background: Homozygous familial hypercholesterolemia (hoFH) can cause severe atherosclerotic cardiovascular disease (ASCVD) in early infancy. Diagnosis and initiation of effective lipid-lowering therapy (LLT) are recommended as early as possible to prevent ASCVD-related morbidity and mortality. Methods: The clinical courses of a pair of siblings with an identical hoFH genotype, who exhibited major similarities of their clinical phenotype were analyzed in a case-control fashion including the family. Results: The older sibling was diagnosed with hoFH at the age of 4. Untreated LDL-cholesterol (LDL-C) was 17 mmol/L (660 mg/dL). LLT including lipoprotein apheresis (LA) was initiated and has been successful for 8 years now. A reduction of estimated cholesterol burden by 74% was achieved by LA and combined drug therapy including statins and ezetimibe. The efficacy of escalation of drug therapy was limited because the underlying LDL receptor (LDLR) mutation in the family resulted in substantially reduced receptor function. Treatment with proprotein convertase subtilisin-kexin type 9 (PCSK9)-antibodies failed. His younger brother died at the age of 2 years shortly after the hoFH diagnosis of the elder sibling. Postmortem examination revealed advanced aortic root atheroma and aortic valve stenosis. In the older sibling, aortic valve stenosis and insufficiency were treated at the age of 9 years with mechanical aortic valve replacement. Conclusions: LLT including LA should be initiated as early as possible following the diagnosis of hoFH with very high LDL-C levels. With the same genotype, the phenotype of hoFH can exhibit similar patterns but outcome is substantially related to treatment.
CRIS-Team Scopus Importer:2020-03-27
Keywords: aortic valve stenosis; children; familial hypercholesterolemia; LDL-cholesterol; lipoprotein apheresis; prevention

Horn of plenty: Value of the international registry for pediatric chronic myeloid leukemia - Suttorp, Meinolf; Metzler, Markus; Millot, Frederic (World Journal of Clinical Oncology, 2020)
Chronic myeloid leukemia (CML) in minors is a rare disease which can be effectively treated by tyrosine kinase inhibitors (TKIs) since the year 2000. A majority of pediatricians will encounter one or two CML patients in the course of their careers and will typically have to rely on written information along with their own intuition to provide care. Knowledge of response to TKIs and of age-specific side effects has an impact on the design of pediatric CML trials in many ways aiming to contribute toward greater predictability of clinical improvements. Information from a registry on a rare disease like CML offers the enormous benefit of enabling treating physicians to interact and share their collective experience. The International Registry on Pediatric CML (IR-PCML) was founded at Poitiers/France almost 10 years ago. Since then, the number of collaboration centers and in parallel of registered patients continuously increased (> 550 patients as of December 2019). Ideally, from a given treatment center in a country data are transferred to a national coordinator who interacts with the IR-PCML. In the sense of quality assurance, the registry can offer dissemination of knowledge on state-of-the-art diagnostics (including reference appraisal), optimal treatment approaches, and follow-up procedures within a network that is exerting its strength via participation. With continuous growth during the recent years, very rare subgroups of patients could be identified (e.g., CML diagnosed at age < 3 years, children presenting with specific problems at diagnosis or during course of treatment) which had not been described before. Publications coming from the IR-PCML disseminated this useful information derived from patients who robustly participate and share information about their disease, among themselves and with their caregivers and clinicians. Patient input driving the collection of data on this rare leukemia is the basis for the considerable success of bringing new therapeutics into clinical use.
CRIS-Team WoS Importer:2020-08-28

How to administer near-infrared spectroscopy in critically ill neonates, infants, and children - Bruns, Nora; Moosmann, Julia; Münch, Frank; Dohna-Schwake, Christian; Wölfle, Joachim; Cesnjevar, Robert; Dittrich, Sven; Felderhoff-Müser, Ursula; Müller, Hanna (Journal of Visualized Experiments, 2020)
Near infrared spectroscopy (NIRS) calculates regional tissue oxygenation (rSO2) using the different absorption spectra of oxygenated and deoxygenated hemoglobin molecules. A probe placed on the skin emits light that is absorbed, scattered, and reflected by the underlying tissue. Detectors in the probe sense the amount of reflected light: this reflects the organ-specific ratio of oxygen supply and consumption-independent of pulsatile flow. Modern devices enable the simultaneous monitoring at different body sites. A rise or dip in the rSO2 curve visualizes changes in oxygen supply or demand before vital signs indicate them. The evolution of rSO2 values in relation to the starting point is more important for interpretation than are absolute values. A routine clinical application of NIRS is the surveillance of somatic and cerebral oxygenation during and after cardiac surgery. It is also administered in preterm infants at risk for necrotizing enterocolitis, newborns with hypoxic ischemic encephalopathy and a potential risk of impaired tissue oxygenation. In the future, NIRS could be increasingly used in multimodal neuromonitoring, or applied to monitor patients with other conditions (e.g., after resuscitation or traumatic brain injury).
CRIS-Team Scopus Importer:2020-09-18

HRV-based Monitoring of Neonatal Seizures with Machine Learning - Lu, Hui; Kusnik, Stefan; Mammadova, Dilbar; Trollmann, Regina; Koelpin, Alexander (2024 46th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2024)
With the rapid development of machine learning (ML) in biomedical signal processing, ML-based neonatal seizure detection using heart rate variability (HRV) parameters extracted from the electrocardiogram (ECG) has gained increasing interest. In this paper, we present a benchmarking of various ML classifiers for HRV-based neonatal seizure monitoring. We extract the HRV parameter in time-domain, frequency-domain, and nonlinear-domain from segments with duration ranging from 30 to 180 s and perform the feature selection with minimum redundancy and maximum relevance (mRmR). In the next step, we evaluate the performance using nested cross-validation on a dataset collected from 16 preterm and term newborns with neonatal seizures with a total duration of over 35 hours. The best-performing classifier was the support vector machine (SVM) with a linear kernel using HRV parameters from the 180 s segment, achieving an area under the operator characteristic operating curve (AUC) score of 0.627, 89.7% sensitivity, 34.6% specificity, and 92.3% good detection rate.
CRIS-Team Scopus Importer:2025-02-04
Keywords: ECG; HRV; machine learning; nested cross-validation; newborns; seizure monitoring

Humans with inherited MyD88 and IRAK-4 deficiencies are predisposed to hypoxemic COVID-19 pneumonia - Garcia-Garcia, Ana; De Diego, Rebeca Perez; Flores, Carlos; Rinchai, Darawan; Sole-Violan, Jordi; Deya-Martinez, Angela; Garcia-Solis, Blanca; Lorenzo-Salazar, Jose M.; Hernandez-Brito, Elisa; Lanz, Anna-Lisa; Moens, Leen; Bucciol, Giorgia; et al. (Journal of Experimental Medicine, 2023)
X-linked recessive deficiency of TLR7, a MyD88- and IRAK-4-dependent endosomal ssRNA sensor, impairs SARS-CoV-2 recognition and type I IFN production in plasmacytoid dendritic cells (pDCs), thereby underlying hypoxemic COVID-19 pneumonia with high penetrance. We report 22 unvaccinated patients with autosomal recessive MyD88 or IRAK-4 deficiency infected with SARS-CoV-2 (mean age: 10.9 yr; 2 mo to 24 yr), originating from 17 kindreds from eight countries on three continents. 16 patients were hospitalized: six with moderate, four with severe, and six with critical pneumonia, one of whom died. The risk of hypoxemic pneumonia increased with age. The risk of invasive mechanical ventilation was also much greater than in age-matched controls from the general population (OR: 74.7, 95% CI: 26.8-207.8, P < 0.001). The patients' susceptibility to SARS-CoV-2 can be attributed to impaired TLR7-dependent type I IFN production by pDCs, which do not sense SARS-CoV-2 correctly. Patients with inherited MyD88 or IRAK-4 deficiency were long thought to be selectively vulnerable to pyogenic bacteria, but also have a high risk of hypoxemic COVID-19 pneumonia.
CRIS-Team WoS Importer:2023-04-21

Hybrid reflected-ultrasound computed tomography versus B-mode-ultrasound for muscle scoring in spinal muscular atrophy - Danko, Vera; Jüngert, Jörg M.; Schüssler, Stephanie; Bühler, Adrian; Klett, Daniel; Federle, Anna; Roos, Andreas; Lochmüller, Hanns; Neurath, Markus; Wölfle, Joachim; Trollmann, Regina; Waldner, Maximilian; et al. (Journal of Neuroimaging, 2023)
Background and Purpose: Novel light- and sound-based technologies like multispectral optoacoustic tomography (MSOT) with co-registered reflected-ultrasound computed tomography (RUCT) could add additional value to conventional ultrasound (US) for disease phenotyping in pediatric spinal muscular atrophy (SMA). The aim of this study was to investigate the quality of RUCT compared to US for qualitative and quantitative assessment of imaging neuromuscular disorders. Methods: Subanalyzing the MSOT SMA study, 288 RUCT and 276 US images from 10 SMA patients (mean age 9.0 ± 3.7) and 10 gender- and age-matched healthy volunteers (HV; mean age 8.7 ± 4.3) were analyzed for quantitative (grayscale levels [GSLs]) and qualitative (echogenicity, distribution pattern, Heckmatt scale, and muscle texture) muscle changes. RUCT and US measures were further correlated with clinical standard motor outcomes. Results: Quantitative agreement using GSLs revealed significantly higher GSLs in muscles of SMA patients compared to healthy muscles in both techniques (US mean GSL [SD] SMA vs. HV: 110.70 [27.8] vs. 68.85 [19.2], p <.0001; RUCT mean GSL [SD] SMA vs. HV: 91.81 [21.8] vs. 59.86 [8.2], p <.0001) with good correlation with motor outcome tests, respectively. Qualitative agreement between methods for muscle composition was excellent for differentiation of pathological versus healthy muscles, echogenicity, and distribution pattern, moderate for Heckmatt scale, and poor for muscle texture. Conclusions: The data suggest that RUCT may allow the assessment of basic qualitative and quantitative measures for muscular diseases with comparable results to conventional US.
CRIS-Team Scopus Importer:2023-01-20
Keywords: neuromuscular disorders; optoacoustics; photoacoustics; spinal muscular atrophy; ultrasound

Hybrid ultrasound and single wavelength optoacoustic imaging reveals muscle degeneration in peripheral artery disease - Träger, Anna P.; Günther, Josefine; Raming, Roman; Paulus, Lars-Philip; Lang, Werner; Meyer, Alexander; Kempf, Julius; Caranovic, Milenko; Li, Yi; Wagner, Alexandra; Tan, Lina; Danko, Vera; et al. (Photoacoustics, 2024)
Peripheral arterial disease (PAD) leads to chronic vascular occlusion and results in end organ damage in critically perfused limbs. There are currently no clinical methods available to determine the muscular damage induced by chronic mal-perfusion. This monocentric prospective cross-sectional study investigated n = 193 adults, healthy to severe PAD, in order to quantify the degree of calf muscle degeneration caused by PAD using a non-invasive hybrid ultrasound and single wavelength optoacoustic imaging (US/SWL-OAI) approach. While US provides morphologic information, SWL-OAI visualizes the absorption of pulsed laser light and the resulting sound waves from molecules undergoing thermoelastic expansion. US/SWL-OAI was compared to multispectral data, clinical disease severity, angiographic findings, phantom experiments, and histological examinations from calf muscle biopsies. We were able to show that synergistic use of US/SWL-OAI is most likely to map clinical degeneration of the muscle and progressive PAD.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Muscle degeneration; Muscle imaging; Optoacoustics; Peripheral artery disease; Photoacoustics

Hydrocortisone dosing in children with classic congenital adrenal hyperplasia: Results of the german/austrian registry - Hoyer-Kuhn, Heike; Huebner, Angela; Richter-Unruh, Anette; Bettendorf, Markus; Rohrer, Tilman; Kapelari, Klaus; Riedl, Stefan; Mohnike, Klaus; Dörr, Helmuth-Günther; Roehl, Friedrich Wilhelm; Fink, Katharina; Holl, Reinhard W.; et al. (Endocrine Connections, 2021)
Objective: Treatment of classic congenital adrenal hyperplasia (CAH) is necessary to compensate for glucocorticoid/mineralocorticoid deficiencies and to suppress androgen excess. Hydrocortisone (HC) is preferred in growing children with classic CAH but recommendations regarding dosage/administration are inconsistent. The aim of this study was to evaluate HC dosing in children with CAH in relation to chronological age, sex, and phenotype based on a multicenter CAH registry. Design: The CAH registry was initiated in 1997 by the AQUAPE in Germany. On December 31st 2018, data from 1571 patients were included. Methods: A custom-made electronic health record software is used at the participating centers. Pseudonymized data are transferred for central analysis. Parameters were selected based on current guidelines. Descriptive analyses and linear regression models were implemented with SAS 9.4. Results: We identified 1288 patients on exclusive treatment with hydrocortisone three times daily (604 boys; median age 7.2 years; 817 salt-wasting phenotype, 471 simple-virilizing phenotype). The mean (lower-upper quartiles) daily HC dose (mg/m² body surface area) was 19.4 (18.9–19.8) for patients <3 months (n = 329), 15.0 (14.6–15.3) for age ≥3–12 months (n = 463), 14.0 (13.7–14.3) for age 1–5.9 years (n = 745), 14.2 (14.0–14.5) for age 6 years to puberty entry (n = 669), and 14.9 (14.6–15.2) during puberty to 18 years (n = 801). Fludrocortisone was administered in 74.1% of patients with a median daily dosage of 88.8 µg. Conclusion: Our analyses showed that still a high proportion of children are treated with HC doses higher than recommended. This evaluation provides comprehensive information on nationwide hydrocortisone substitution dosages in children with CAH underlining the benefit of systematic data within a registry to assess daily practice.
CRIS-Team Scopus Importer:2021-06-11
Keywords: CYP21A2; fludrocortisone; glucocorticoids; treatment

Hyperactive mTOR pathway promotes lymphoproliferation and abnormal differentiation in autoimmune lymphoproliferative syndrome - Voelkl, Simon; Rensing-Ehl, Anne; Allgäuer, Andrea; Schreiner, Elisabeth; Lorenz, Myriam Ricarda; Rohr, Jan; Klemann, Christian; Fuchs, Ilka; Schuster, Volker; Von Bueren, Andre O.; Naumann-Bartsch, Nora; Gambineri, Eleonora; et al. (Blood, 2016)
Autoimmune lymphoproliferative syndrome (ALPS) is a human disorder characterized by defective Fas signaling, resulting in chronic benign lymphoproliferation and accumulation of TCR??(+) CD4(-) CD8(-) double-negative T (DNT) cells. Although their phenotype resembles that of terminally differentiated or exhausted T cells, lack of KLRG1, high eomesodermin, and marginal T-bet expression point instead to a long-lived memory state with potent proliferative capacity. Here we show that despite their terminally differentiated phenotype, human ALPS DNT cells exhibit substantial mitotic activity in vivo. Notably, hyperproliferation of ALPS DNT cells is associated with increased basal and activation-induced phosphorylation of serine-threonine kinases Akt and mechanistic target of rapamycin (mTOR). The mTOR inhibitor rapamycin abrogated survival and proliferation of ALPS DNT cells, but not of CD4(+) or CD8(+) T cells in vitro. In vivo, mTOR inhibition reduced proliferation and abnormal differentiation by DNT cells. Importantly, increased mitotic activity and hyperactive mTOR signaling was also observed in recently defined CD4(+) or CD8(+) precursor DNT cells, and mTOR inhibition specifically reduced these cells in vivo, indicating abnormal programming of Fas-deficient T cells before the DNT stage. Thus, our results identify the mTOR pathway as a major regulator of lymphoproliferation and aberrant differentiation in ALPS.
EVALuna2:25746

Hypohidrotic Ectodermal Dysplasia: Breastfeeding Complications Due to Impaired Breast Development - Wahlbuhl-Becker, Mandy; Faschingbauer, Florian; Beckmann, Matthias; Schneider, Holm (Geburtshilfe und Frauenheilkunde, 2017)
Background X-linked hypohidrotic ectodermal dysplasia (XLHED), the most common form of ectodermal dysplasia, is caused by mutations in the gene EDA. While only affected men develop the full-blown clinical picture, females who are heterozygous for an EDA mutation often also show symptoms such as hypodontia, hypotrichosis and hypohidrosis. These women may also suffer from malformations of the mammary gland which represent not just a cosmetic problem but can limit their breastfeeding capability. This paper summarizes the findings of the first systematic study on the impact of hypohidrotic ectodermal dysplasia on breastfeeding. Patients Thirty-eight adult female members of the German-Swiss-Austrian ectodermal dysplasia patient support group participated in a structured interview; most of them also agreed to a photodocumentation of their mammary region. Thirty-one women carried mutations in EDA (Group A) and seven were affected by other forms of hypohidrotic ectodermal dysplasia (Group B). Results 39 % of the women of Group A reported that their breasts were of different size or entirely absent on one side. In Group B, 86 % of the women reported differently sized or even absent breasts; two of these women lacked both breasts entirely. Most women described their nipples as exceptionally flat. 10 % of the women of Group A had more than two nipples. The high percentage of deviations from the norm was confirmed in the photodocumentation. Both groups had few or no sebaceous glands of Montgomery in the areolar region. Around 80 % of interviewed women had children and had attempted to breastfeed their first child. 67 % of the mothers in Group A had had difficulty in breastfeeding their infants and generally attributed this difficulty to their flat nipples. All of the mothers in Group B reported difficulties in breastfeeding; 60 % had not been able to breastfeed their first child. Conclusion Mothers with hypohidrotic ectodermal dysplasia very often have difficulty in breastfeeding because of their impaired breast development. This causal relationship needs to be taken into account in lactation counseling.
EVALuna2:34219

Hypoxia Potentiates LPS-Mediated Cytotoxicity of BV2 Microglial Cells In Vitro by Synergistic Effects on Glial Cytokine and Nitric Oxide System - Frey, Daniel; Jung, Susan; Brackmann, Florian; Richter-Kraus, Mandy; Trollmann, Regina (Neuropediatrics, 2015)
Microglial activation due to a variety of stimuli induces secretion of neurotoxic substances including inflammatory cytokines and nitric oxide (NO). Clinical studies indicate a cross-link between inflammatory and hypoxia-regulated pathways suggesting that bacterial infections markedly sensitize the immature brain to hypoxic injury.The impact of inflammation and hypoxia on interleukin (IL)-1?, IL-6, tumor necrosis factor ? (TNF-?), and NO secretion and microglia-induced cytotoxicity was investigated exposing BV2 cells to lipopolysaccharides (LPS) and hypoxia (1% O2). Cytotoxicity, NO, and cytokine release was quantified by MTS and Griess assays and by enzyme-linked immunosorbent assays, respectively.LPS exposure of BV2 cells induced a significant, persistent production of NO, IL-1?, IL-6, and TNF-?. Even after LPS removal, ongoing NO and cytokine secretion was observed. Hypoxia mediated exclusively a significant, short-term IL-1? increase, but enhanced LPS-induced cytokine and NO secretion significantly. In addition, LPS-induced supernatants exhibited a stronger cytotoxic effect in glial and neuronal cells than LPS exposition (p < 0.001). Hypoxia potentiated LPS-induced cytotoxicity.Present data prove that LPS-induced soluble factors rather than LPS exposure mediate microglial toxicity under conditions of hypoxia in vitro. Apart from potential protective effects of the hypoxia-inducible transcription factor (HIF)-1? system, activation of proinflammatory pathways may markedly sensitize microglial cells to promote hypoxia-induced injuries of the developing brain.
EVALuna2:18925

IGF-I in cord blood is predictive of final height in monozygotic twins with intra-twin birth weight differences - Kasner, Charlotte; Schulte, Sandra; Schreiner, Felix; Fimmers, Rolf; Stoffel-Wagner, Birgit; Bartmann, Peter; Wölfle, Joachim; Gohlke, Bettina (Clinical Endocrinology, 2020)
Objective: Adverse prenatal conditions can exert a long-lasting impact on growth up to final height (FH). Due to different prenatal nutrient availability, monozygotic twin pairs with discordant birth weight (bw) provide an excellent model to examine the impact of genes and environment and to analyse the predictive value of bw, birth length (bl) and cord blood (cb) concentration of IGF-I on FH. Patients and Methods: Twenty eight monozygotic twin pairs with intra-twin bw-/bl-differences were studied at birth and longitudinally until FH. Intra-twin bw difference >1 SDS was defined “discordant” (n = 10 pairs). IGF-I was analysed in cord blood in all twins. Intra-twin differences (∆) in bw, bl and cord blood IGF-I were correlated with ∆FH. Results: Throughout growth and up until FH intra-twin length/height differences remained for all but two (26/28) twins and for all (10/10) discordant twins. In the discordant group, a highly significant intra-twin difference for FH-SDS was found with a mean intra-twin Δheight- SDS of 1.23 (range, 0.29-2.34). This corresponds to a mean Δintra-twin difference at FH of 7.9 cm (3.1 inch; range, 2-15 cm [0.79-5.9 inch]). Correlation coefficients were calculated to identify factors predicting FH: ∆bw (r =.678; P =.0005), ∆bl (r =.333; P =.0002) and ∆IGF-I in cb (r =.418; P =.0023). Interaction terms showed that IGF-I is an additional factor to the auxological data, leading to an improvement of the ∆FH modelling. Conclusion: Prenatal environment leading to bw-/bl- and cbIGF-I differences in monozygotic twins had a long-lasting impact on growth until FH. Both, anthropometric data at birth and cbIGF-I are predictive of FH.
CRIS-Team Scopus Importer:2020-06-19
Keywords: birth length; birth weight; final height; foetal programming; growth; IGF-I

Imatinib treatment and longitudinal growth in pediatric patients with chronic myeloid leukemia: influence of demographic, pharmacological, and genetic factors in the German CML-PAED cohort - Stiehler, Sophie; Sembill, Stephanie; Schleicher, Oliver; Marx, Martin; Rauh, Manfred; Krumbholz, Manuela; Karow, Axel; Suttorp, Meinolf; Wölfle, Joachim; Maj, Carlo; Metzler, Markus (Haematologica, 2024)
In children and adolescents, impaired growth due to tyrosine kinase inhibitor therapy remains an insufficiently studied adverse effect. This study examines demographic, pharmacological, and genetic factors associated with impaired longitudinal growth in a uniform pediatric cohort treated with imatinib. We analyzed 94 pediatric patients with chronic myeloid leukemia (CML) diagnosed in the chronic phase and treated with imatinib for >12 months who participated in the Germany-wide CML-PAEDII study between February 2006 and February 2021 (clinicaltrials gov. Identifier: NCT00445822). During imatinib treatment, significant height reduction occurred, with medians of -0.35 standard deviation score (SDS) at 12 months and -0.76 SDS at 24 months. Cumulative height SDS change (Δ height SDS) showed a more pronounced effect in prepubertal patients during the first year but were similar between prepubertal and pubertal subgroups by the second year (-0.55 vs. -0.50). From months 12 to 18 on imatinib, only 18% patients achieved individually longitudinal growth adequate to the growth standard (Δ height SDS ≥0). When patients were divided into two subgroups based on median Δ height SDS (classifier Δ height SDS > or ≤-0.37) after 1 year on imatinib therapy, cohort 1 (Δ height SDS ≤-0.37) showed younger age at diagnosis, a higher proportion of prepubertal children, but also better treatment response and higher imatinib serum levels. Exploring the association of growth parameters with pharmacokinetically relevant single nucleotide polymorphisms, known for affecting imatinib response, showed no correlation. This retrospective study provides new insights into imatinib-related growth impairment. We emphasize the importance of optimizing treatment strategies for pediatric patients to realize their maximum growth potential.
CRIS-Team Scopus Importer:2024-08-16

Impact of a computerized physician order entry system on medication safety in pediatrics-The AVOID study - Wimmer, Stefan; Toni, Irmgard; Botzenhardt, Sebastian; Trollmann, Regina; Rascher, Wolfgang; Neubert, Antje (Pharmacology Research and Perspectives, 2023)
BACKGROUND: One of the most critical steps in the medication process on pediatric wards is the medical prescription. This study aims to investigate the impact of a computerized physician order entry (CPOE) system on Adverse Drug Events (ADEs) and potentially harmful ADEs (pot ADEs) in comparison with paper-based documentation in a general pediatric ward at a German University hospital. METHODS: A prospective pre-post study was conducted. All patients aged 17 years or younger were observed during the study periods (5 months pre- and postimplementation). Issues Regarding Medication (IRM) were identified by intensive chart review. Events were assessed regarding causality (WHO), severity (WHO; Dean & Barber for MEs), and preventability (Shumock) and classified into (pot) ADEs, (pot) Medication errors (ME), Adverse drug Reactions (ADR), and Other incidents (OI) accordingly. RESULTS: Total of 333 patients with medication were included in the paper-based prescribing cohort (phase I) and 320 patients with medication in the electronic prescribing cohort (phase II). In each cohort, patients received a median number of four different drugs (IQR 5 and IQR 4). A total of 3966 IRM was observed. During the hospitalization, 2.7% (n = 9) patients in phase I and 2.8% (n = 9) in phase II experienced an ADE. Potentially harmful MEs were less often observed in the cohort with electronic prescribing (n = 228 vs. n = 562). The mean number per patient significantly decreased from 1.69 to 0.71 (p < .01). CONCLUSION: The implementation of a CPOE system resulted in a reduction of issues regarding medication, particularly MEs with the potential to harm patients decreased significantly.
CRIS-Team Scopus Importer:2023-06-02
Keywords: adverse drug event; adverse drug reaction; computerized physician order entry; electronic prescribing; medication error; medication safety; pediatrics

Impact of age on safety of Busulfan-Melphalan followed by autologous hematopoietic stem-cell transplantation versus standard chemotherapy in the patients of the EURO-E.W.I.N.G. 99 and Ewing 2008 clinical trials - Choderlos de Laclos, Xavier; Risbourg, Séverine; Marec-Bérard, Perrine; Cécile Le Deley, Marie; Tabone, Marie Dominique; Bertucci, François; Gaspar, Nathalie; Gandemer, Virginie; Brennan, Bernadette; Strauss, Sandra; McCabe, Martin G.; Windsor, Rachael; et al. (European Journal of Cancer, 2024)
Introduction: Ewing sarcoma (ES), is a rare cancer affecting children, adolescents and adults. After VIDE (vincristine-ifosfamide-doxorobucin-etoposide) induction chemotherapy, Busulfan-Melphalan (BuMel) high-dose chemotherapy followed by autologous hematopoietic stem cells transplantation improved outcomes in unfavourable localized ES, but with more toxicities than conventional chemotherapy (VAI: Vincristine-dactinomycin-Ifosfamide). We evaluated whether the risk of acute toxicity associated with BuMel compared to VAI varied according to age in patients recruited in the R2Loc and R2Pulm randomised trials of the Euro-E.W.I.N.G.99 and Ewing-2008 trials. Methods: We included patients with a localized high-risk disease, or pulmonary or pleural metastasis. We analysed the risk of severe toxicity according to randomised treatment group (VAI versus BuMel) and age group (<12 years, 12–17 years, 18–24 years, ≥25 years). We evaluated the heterogeneity of treatment effects by age group using interaction terms in logistic multivariable models. Results: The analysis included 243 patients treated with VAI and 205 with BuMel. Overall, BuMel was associated with a higher risk of severe acute toxicity than VAI particularly haematological, gastrointestinal, liver, sinusoidal occlusive syndrome, and infections. Severe haematological toxicity and lower general condition were significantly more frequent in younger patients, whatever treatment. We did not observe any significant heterogeneity in terms of the excess risk of severe toxicities associated with BuMel compared to VAI according to age group. Conclusion: The excess of acute toxicity associated with BuMel compared to VAI does not vary significantly with age, suggesting the feasibility of BuMel across all age groups.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Autologous hematopoietic stem cells transplantation; Ewing sarcoma (ES); High dose chemotherapy; Safety

Impact of COVID-19 infection on lung function and nutritional status amongst individuals with cystic fibrosis: A global cohort study - Semenchuk, Julie; Naito, Yumi; Charman, Susan C.; Carr, Siobhán B.; Cheng, Stephanie Y.; Marshall, Bruce C.; Faro, Albert; Elbert, Alexander; Gutierrez, Hector H.; Goss, Christopher H.; Karadag, Bulent; Burgel, Pierre Régis; et al. (Journal of Cystic Fibrosis, 2024)
Background: Factors associated with severe COVID-19 infection have been identified; however, the impact of infection on longer-term outcomes is unclear. The objective of this study was to examine the impact of COVID-19 infection on the trajectory of lung function and nutritional status in people with cystic fibrosis (pwCF). Methods: This is a retrospective global cohort study of pwCF who had confirmed COVID-19 infection diagnosed between January 1, 2020 and December 31, 2021. Forced expiratory volume in one second percent predicted (ppFEV1) and body mass index (BMI) twelve months prior to and following a diagnosis of COVID-19 were recorded. Change in mean ppFEV1 and BMI were compared using a t-test. A linear mixed-effects model was used to estimate change over time and to compare the rate of change before and after infection. Results: A total of 6,500 cases of COVID-19 in pwCF from 33 countries were included for analysis. The mean difference in ppFEV1 pre- and post-infection was 1.4 %, (95 % CI 1.1, 1.7). In those not on modulators, the difference in rate of change pre- and post-infection was 1.34 %, (95 % CI -0.88, 3.56) per year (p = 0.24) and -0.74 % (-1.89, 0.41) per year (p = 0.21) for those on elexacaftor/tezacaftor/ivacaftor. No clinically significant change was noted in BMI or BMI percentile before and after COVID-19 infection. Conclusions: No clinically meaningful impact on lung function and BMI trajectory in the year following infection with COVID-19 was identified. This work highlights the ability of the global CF community to unify and address critical issues facing pwCF.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Coronavirus; COVID-19; Cystic fibrosis

Impact of Newborn Screening on Adult Height in Patients With Congenital Adrenal Hyperplasia (CAH) - Hoyer-Kuhn, Heike; Eckert, Alexander J.; Binder, Gerhard; Bonfig, Walter; Dübbers, Angelika; Riedl, Stefan; Wölfle, Joachim; Dörr, Helmuth-Günther; Holl, Reinhard W. (Journal of Clinical Endocrinology and Metabolism, 2023)
CONTEXT: Treatment of children with classical congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency is challenging. Linear growth and adult height are compromised according to recent publications. However, most of these data were obtained in the era before CAH newborn screening. DESIGN: Body height of patients with classical CAH diagnosed before and after the establishment of newborn screening were analyzed retrospectively. PATIENTS AND METHODS: We identified 600 patients with classical CAH (227 male) with data on near-adult height (NAH), target height (TH), and information on newborn screening from the electronic German CAH registry (German Society for Paediatric Endocrinology and Diabetology). Newborn screening was performed in 101 (16.8%) patients. All patients received hydrocortisone with or without fludrocortisone.To assess the effects of newborn screening, a linear regression model adjusted/stratified for sex and phenotype was used (SAS 9.4). RESULTS: TH corrected NAH (mean; 95% confidence interval) was closer to 0 in patients with CAH and newborn screening [-0.25 standard deviation score (SDS); -0.44 to -0.06] than in patients without newborn screening (-0.44 SDS; -0.52 to -0.36) (P = .069). Screening had no effect on NAH in female patients. In male patients, NAH was significantly better (P = .033) with screening than without screening. After stratifying for CAH phenotype, screening did not affect the NAH of patients with salt-wasting CAH. Patients with simple-virilizing CAH had a significantly better cNAH (P = .034) with screening (0.15 SDS; -0.28-0.59) than without screening (-0.35 SDS; -0.52 to -0.18). CONCLUSIONS: Our data suggest that newborn screening might be associated with improved NAH in male CAH patients and in patients with simple-virilizing CAH.
CRIS-Team Scopus Importer:2023-11-03
Keywords: congenital adrenal hyperplasia; CYP21A2; near adult height; newborn screening

Impact of regional SARS-CoV-2 proceedings on changes in diagnoses of pediatric malignancies in Bavaria during the COVID-19 pandemic - Reger, Mira; Manz, Kirsi; Kaeuferle, Theresa; Coffey, Ramona; Wotschofsky, Zofia; von Luettichau, Irene; Schlegel, Paul Gerhardt; Frühwald, Michael C.; Corbacioglu, Selim; Metzler, Markus; Feuchtinger, Tobias (Pediatric Hematology and Oncology, 2024)
The COVID-19 pandemic affected daily life significantly and had massive consequences for healthcare systems with tremendous regional differences. This retrospective study aimed to investigate whether the pandemic and resulting societal changes impacted the diagnosis of pediatric malignancies in a distinct region. Pediatric cancer cases in Bavaria (2016–2021) and SARS-CoV-2 proceedings during the peak phase of the pandemic (2020–2021) were retrospectively analyzed. All new diagnoses of pediatric malignancies reported from cancer centers in Bavaria were included. Clinical data from pre-pandemic years was compared to diagnoses made during the pandemic. Official SARS-CoV-2 reports were received from the Bavarian Health and Food Safety Authority and data on regional pandemic measures were obtained from the Healthcare Data Platform. With this design, a comprehensive analysis of the pandemic proceedings was performed. We found significantly decreased incidence-rate ratios for pediatric cancer diagnosis during the early spring peak of SARS-CoV-2 as it was observed in May during the pandemic, followed by non-significantly increased metastatic cancer diagnosis two months later. Additionally, the time-to-diagnosis of pediatric malignancies was significantly prolonged during the pandemic, and outpatient contacts were significantly reduced, although the availability of consultations remained the same. From our findings, we may hypothesize that there have been effects on pediatric cancer diagnosis during the COVID-19 pandemic at vulnerable times. Interpretation of changes remains speculative with potential causes from behavior patterns, such as hesitation, concerns, and potential societal changes during phases of public restrictions, rather than overwhelmed medical capacities. Nevertheless, specific awareness is needed to protect this patient population during potential future pandemics.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Incidence; pandemic; pediatric malignancies; SARS-CoV-2; time-to-diagnosis

Impaired myocardial performance in a normotensive rat model of intrauterine growth restriction - Menendez-Castro, Carlos; Toka, Okan; Fahlbusch, Fabian; Cordasic, Nada; Wachtveitl, Rainer; Hilgers, Karl Friedrich; Rascher, Wolfgang; Hartner, Andrea (Pediatric Research, 2014)
Intrauterine growth restriction (IUGR) is an important risk factor for cardiovascular disease. Previous studies revealed altered myocardial matrix composition after IUGR. We hypothesized that IUGR is accompanied by compromised myocardial performance independently from arterial hypertension.IUGR was induced in Wistar rats by maternal protein restriction, and hearts of male offspring were studied using echocardiography, immunohistochemistry, real-time PCR, and western blot analysis.At day 70 of life, in the absence of arterial hypertension (mean arterial blood pressure: 101.3 ± 7.1 mmHg in IUGR vs. 105.3 ± 4.6 mmHg in controls, not significant (NS)), echocardiography showed a reduced contractility (ejection fraction: 65.4 ± 1.8% in IUGR vs. 82.2 ± 1.5% in controls, P < 0.001) of a more distensible myocardium in IUGR rats. Altered expression patterns of myosin chains and titin isoforms and increased expression levels of atrial natriuretic peptide, Na/K-ATPase, and ?-adrenergic receptor 1 were detected. A higher number of cardiac fibroblasts and vascular cross-sections were observed in IUGR rats, accompanied by elevated expression of hypoxia inducible factor 1 target genes, such as vascular endothelial growth factor and its receptors.We observed a blood pressure-independent impairment of myocardial function after IUGR, which possibly favors cardiovascular disease later in life. Some IUGR-induced myocardial changes (e.g., sarcomeric components) may partly explain the compromised cardiac performance, whereas others (e.g., elevated vascular supply) reflect compensatory mechanisms.
EVALuna2:3704

Improved upper limb function in non-ambulant children with SMA type 2 and 3 during nusinersen treatment: a prospective 3-years SMArtCARE registry study - Pechmann, Astrid; Behrens, Max; Dörnbrack, Katharina; Tassoni, Adrian; Wenzel, Franziska; Stein, Sabine; Vogt, Sibylle; Zöller, Daniela; Bernert, Günther; Hagenacker, Tim; Schara-Schmidt, Ulrike; Walter, Maggie C.; et al. (Orphanet Journal of Rare Diseases, 2022)
Background: The development and approval of disease modifying treatments have dramatically changed disease progression in patients with spinal muscular atrophy (SMA). Nusinersen was approved in Europe in 2017 for the treatment of SMA patients irrespective of age and disease severity. Most data on therapeutic efficacy are available for the infantile-onset SMA. For patients with SMA type 2 and type 3, there is still a lack of sufficient evidence and long-term experience for nusinersen treatment. Here, we report data from the SMArtCARE registry of non-ambulant children with SMA type 2 and typen 3 under nusinersen treatment with a follow-up period of up to 38 months. Methods: SMArtCARE is a disease-specific registry with data on patients with SMA irrespective of age, treatment regime or disease severity. Data are collected during routine patient visits as real-world outcome data. This analysis included all non-ambulant patients with SMA type 2 or 3 below 18 years of age before initiation of treatment. Primary outcomes were changes in motor function evaluated with the Hammersmith Functional Motor Scale Expanded (HFMSE) and the Revised Upper Limb Module (RULM). Results: Data from 256 non-ambulant, pediatric patients with SMA were included in the data analysis. Improvements in motor function were more prominent in upper limb: 32.4% of patients experienced clinically meaningful improvements in RULM and 24.6% in HFMSE. 8.6% of patients gained a new motor milestone, whereas no motor milestones were lost. Only 4.3% of patients showed a clinically meaningful worsening in HFMSE and 1.2% in RULM score. Conclusion: Our results demonstrate clinically meaningful improvements or stabilization of disease progression in non-ambulant, pediatric patients with SMA under nusinersen treatment. Changes were most evident in upper limb function and were observed continuously over the follow-up period. Our data confirm clinical trial data, while providing longer follow-up, an increased number of treated patients, and a wider range of age and disease severity.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Later-onset; Nusinersen; Sitter; SMArtCARE; Spinal muscular atrophy

Improvements in Walking Distance during Nusinersen Treatment - A Prospective 3-year SMArtCARE Registry Study - Pechmann, Astrid; Behrens, Max; Dörnbrack, Katharina; Tassoni, Adrian; Wenzel, Franziska; Stein, Sabine; Vogt, Sibylle; Zöller, Daniela; Bernert, Günther; Hagenacker, Tim; Schara-Schmidt, Ulrike; Walter, Maggie C.; et al. (Journal of Neuromuscular Diseases, 2023)
BACKGROUND AND OBJECTIVES: Disease progression in patients with spinal muscular atrophy (SMA) has changed dramatically within the past years due to the approval of three different disease-modifying treatments. Nusinersen was the first drug to be approved for the treatment of SMA patients. Clinical trials provided data from infants with SMA type 1 and children with SMA type 2, but there is still insufficient evidence and only scarcely reported long-term experience for nusinersen treatment in ambulant patients. Here, we report data from the SMArtCARE registry of ambulant patients under nusinersen treatment with a follow-up period of up to 38 months. METHODS: SMArtCARE is a disease-specific registry in Germany, Austria and Switzerland. Data are collected as real-world data during routine patient visits. Our analysis included all patients under treatment with nusinersen able to walk independently before start of treatment with focus on changes in motor function. RESULTS: Data from 231 ambulant patients were included in the analysis. During the observation period, 31 pediatric walkers (27.2%) and 31 adult walkers (26.5%) experienced a clinically meaningful improvement of≥30 m in the 6-Minute-Walk-Test. In contrast, only five adult walkers (7.7%) showed a decline in walking distance≥30 m, and two pediatric walkers (1.8%) lost the ability to walk unassisted under treatment with nusinersen. HFMSE and RULM scores improved in pediatric and remained stable in adult patients. CONCLUSION: Our data demonstrate a positive effect of nusinersen treatment in most ambulant pediatric and adult SMA patients. We not only observed a stabilization of disease progression or lack of deterioration, but clinically meaningful improvements in walking distance.
CRIS-Team Scopus Importer:2023-01-20
Keywords: ambulant; nusinersen; SMArtCARE; Spinal muscular atrophy; walker

Increased Rat Placental Fatty Acid, but Decreased Amino Acid and Glucose Transporters Potentially Modify Intrauterine Programming - Nuesken, Eva; Gellhaus, Alexandra; Kuehnel, Elisabeth; Swoboda, Isabelle; Wohlfarth, Maria; Vohlen, Christina; Schneider, Holm; Doetsch, Joerg; Nuesken, Kai-Dietrich (Journal of Cellular Biochemistry, 2016)
Regulation of placental nutrient transport significantly affects fetal development and may modify intrauterine growth restriction (IUGR) and fetal programming. We hypothesized that placental nutrient transporters are differentially affected both by utero-placental insufficiency and prenatal surgical stress. Pregnant rats underwent bilateral uterine artery and vein ligation (LIG), sham operation (SOP) or no operation (controls, C) on gestational day E19. Placentas were obtained by caesarean section 4 h (LIG, n=20 placentas; SOP, n=24; C, n=12), 24 h (LIG, n=28; SOP, n=20; C, n=12) and 72 h (LIG, n=20; SOP, n=20; C, n=24) after surgery. Gene and protein expression of placental nutrient transporters for fatty acids (h-FABP, CD36), amino acids (SNAT1, SNAT2) and glucose (GLUT-1, Connexin 26) were examined by qRT-PCR, western blot and immunohistochemistry. Interestingly, the mean protein expression of h-FABP was doubled in placentas of LIG and SOP animals 4, 24 (SOP significant) and 72 h (SOP significant) after surgery. CD36 protein was significantly increased in LIG after 72 h. SNAT1 and SNAT2 protein and gene expressions were significantly reduced in LIG and SOP after 24 h. Further significantly reduced proteins were GLUT-1 in LIG (4 h, 72 h) and SOP (24 h), and Connexin 26 in LIG (72 h). In conclusion, placental nutrient transporters are differentially affected both by reduced blood flow and stress, probably modifying the already disturbed intrauterine milieu and contributing to IUGR and fetal programming. Increased fatty acid transport capacity may affect energy metabolism and could be a compensatory reaction with positive effects on brain development. J. Cell. Biochem. 117: 1594-1603, 2016. © 2015 Wiley Periodicals, Inc.
EVALuna2:33879

Increased risk of chronic fatigue and hair loss following COVID-19 in individuals with hypohidrotic ectodermal dysplasia - Hennig, Verena; Schuh, Wolfgang; Neubert, Antje; Mielenz, Dirk; Jäck, Hans-Martin; Schneider, Holm (Orphanet Journal of Rare Diseases, 2021)
Background: Hypohidrotic ectodermal dysplasia (HED) is a group of genodermatoses in which deficient ectodysplasin A signalling leads to maldevelopment of skin appendages, various eccrine glands, and teeth. Individuals with HED often have disrupted epithelial barriers and, therefore, were suspected to be more susceptible to coronavirus infection. Methods: 56 households with at least one member who had coronavirus disease of 2019 (COVID-19) were enrolled in a longitudinal study to compare the course of illness, immune responses, and long-term consequences of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) infection in HED patients (n = 15, age 9–52 years) and control subjects of the same age group (n = 149). Results: In 14 HED patients, mild or moderate typical COVID-19 symptoms were observed that lasted for 4–45 days. Fever during the first days sometimes required external cooling measures. The course of COVID-19 was similar to that in control subjects if patients developed antibodies blocking the SARS-CoV-2 spike protein. Five out of six HED patients with completely abrogated ectodysplasin A signalling (83%) suffered from chronic, in two cases very severe fatigue following COVID-19, while only 25% of HED patients with residual activity of this pathway and 21% of control subjects recovering from COVID-19 experienced postinfectious fatigue. Hair loss after COVID-19 was also more frequent among HED patients (64%) than in the control group (13%). Conclusions: HED appears to be associated with an increased risk of long-term consequences of a SARS-CoV-2 infection. Preventive vaccination against COVID-19 should be recommended for individuals affected by this rare genetic disorder.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Chronic fatigue; COVID-19; Hair loss; Hypohidrotic ectodermal dysplasia; SARS-CoV-2

Increase of liver stiffness and altered bile acid metabolism after triple CFTR modulator initiation in children and young adults with cystic fibrosis - Schnell, Alexander; Jüngert, Jörg M.; Klett, Daniel; Hober, Hannah; Kaiser, Natalie; Ruppel, Renate; Geppert, Annika; Tremel, Christina; Sobel, Julia; Plattner, Erika; Schmitt-Grohe, Sabina; Zirlik, Sabine; et al. (Liver International, 2023)
Background: Novel cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapies (elexacaftor/tezacaftor/ivacaftor—ETI) promise clinically significant and sustained improvements for patients with cystic fibrosis (CF). In this study, we investigated the impact of ETI therapy on liver stiffness and bile acid metabolism in a cohort of children and young adults with CF. Methods: A prospective observational study (NCT05576324) was conducted from September 2020 to November 2021 enrolling CF patients naive to ETI. Standard laboratory chemistry, sweat test, lung function, share wave velocity (SWV) derived by acoustic radiation force impulse imaging (ARFI) and serum bile acid profiles were assessed before and 6 months after induction of ETI therapy. Results: A total of 20 patients (10 aged <20 years) completed the study. While lung function and BMI improved after ETI therapy, ARFI SWV increased in CF patients <20 years of age (from 1.27 to 1.43 m/s, p = 0.023). Bile acid (BA) profiles revealed a decrease in unconjugated (5.75 vs 1.46, p = 0.007) and increase in glycine-conjugated derivatives (GCDCA) (4.79 vs 6.64 p = 0.016). There was a positive correlation between ARFI SWV values and GCDCA (r = 0.80, p < 0.0001). Glycine-conjugated BA provided high diagnostic accuracy to predict increased ARFI measurements (AUC 0.90) and clinical (Colombo) CFLD grading (AUC 0.97). Conclusions: ARFI SWV and bile acid profiles provide evidence for early increase in liver stiffness and altered bile acid metabolism in young CF patients after initiation of ETI and may serve as synergistic measures for detection of hepatic complications during ETI therapy.
CRIS-Team Scopus Importer:2023-03-17
Keywords: ARFI; bile acids; CFLD; cystic fibrosis

Indirect determination of hematology reference intervals in adult patients on Beckman Coulter UniCell DxH 800 and Abbott CELL-DYN Sapphire devices - Zierk, Jakob; Arzideh, Farhad; Haeckel, Rainer; Rauh, Manfred; Metzler, Markus; Ganslandt, Thomas; Krause, Stefan (Clinical Chemistry and Laboratory Medicine, 2018)
Background Conventional establishment of reference intervals for hematological analytes is challenging due to the need to recruit healthy persons. Indirect methods address this by deriving reference intervals from clinical laboratory databases which contain large datasets of both physiological and pathological test results. Methods We used the "Reference Limit Estimator" (RLE) to establish reference intervals for common hematology analytes in adults aged 18-60 years. One hundred and ninety-five samples from 44,519 patients, measured on two different devices in a tertiary care center were analyzed. We examined the influence of patient cohorts with an increasing proportion of abnormal test results, compared sample selection strategies, explored inter-device differences, and analyzed the stability of reference intervals in simulated datasets with varying overlap of pathological and physiological test results. Results Reference intervals for hemoglobin, hematocrit, red cell count and platelet count remained stable, even if large numbers of pathological samples were included. Reference intervals for red cell indices, red cell distribution width and leukocyte count were sufficiently stable, if patient cohorts with the highest fraction of pathological samples were excluded. In simulated datasets, estimated reference limits shifted, if the pathological dataset contributed more than 15%-20% of total samples and approximated the physiological distribution. Advanced sample selection techniques did not improve the algorithm's performance. Inter-device differences were small except for red cell distribution width. Conclusions The RLE is well-suited to create reference intervals from clinical laboratory databases even in the challenging setting of a adult tertiary care center. The procedure can be used as a complement for reference interval determination where conventional approaches are limited.
EVALuna2:34837

INFANTS AND NEWBORNS WITH ATYPICAL TERATOID/RHABDOID TUMORS (ATRT) AND EXTRACRANIAL MALIGNANT RHABDOID TUMORS: A UNIQUE AND CHALLENGING POPULATION - Nemes, Karolina; Johann, Pascal D.; Steinbuegl, Mona; Gruhle, Miriam; Bens, Susanne; Kachanov, Denis; Teleshova, Margarita; Peter, Hauser; Simon, Thorsten; Tippelt, Stephan; Eberl, Wolfgang; Chada, Martin; et al. (NEURO-ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-09-02

Influence of labor on direct and indirect determinants of placental 11beta-hydroxysteroid dehydrogenase activity - Hübner, Hanna; Heussner, Kirsten; Rübner, Matthias; Schmid, Matthias; Nadal, Jennifer; Wölfle, Joachim; Hartner, Andrea; Menendez-Castro, Carlos; Rauh, Manfred; Beckmann, Matthias; Kehl, Sven; Fahlbusch, Fabian (Archives of Gynecology and Obstetrics, 2020)
Purpose: Labor is a complex process involving multiple para-, auto- and endocrine cascades. The interaction of cortisol, corticotropin-releasing hormone (CRH) and progesterone is essential. The action of cortisol on the human feto-placental unit is regulated by 11beta-hydroxysteroid dehydrogenase type 2 (11β-HSD2/HSD11B2) that converts cortisol into inactive cortisone. The majority of studies on the assessment of placental 11β-HSD2 function determined indirect activity parameters. It remains elusive if indirect measurements correlate with enzymatic function and if these parameters are affected by potential confounders (e.g., mode of delivery). Thus, we compared determinants of indirect 11β-HSD2 tissue activity with its direct enzymatic turnover rate in placental samples from spontaneous births and cesarean (C)-sections. Methods: Using LC–MS/MS, we determined CRH, cortisol, cortisone, progesterone and 17-hydroxy(OH)-progesterone in human term placentas (spontaneous birth vs. C-section, n = 5 each) and measured the enzymatic glucocorticoid conversion rates in placental microsomes. Expression of HSD11B1, 2 and CRH was determined via qRT-PCR in the same samples. Results: Cortisol–cortisone ratio correlated with direct microsomal enzymatic turnover. While this observation seemed independent of sampling site, a strong influence of mode of delivery on tissue steroids was observed. The mRNA expression of HSD11B2 correlated with indirect and direct cortisol turnover rates in C-section placentas only. In contrast to C-sections, CRH, cortisol and cortisone levels were significantly increased in placental samples following spontaneous birth. Conclusion: Labor involves a series of complex hormonal processes including activation of placental CRH and glucocorticoid metabolism. This has to be taken into account when selecting human cohorts for comparative analysis of placental steroids.
CRIS-Team Scopus Importer:2020-09-11
Keywords: 11beta-hydroxysteroid dehydrogenase; CRH; LC–MS/MS; Mode of delivery; Placenta

Influence of prenatal environment and genetic background on glucocorticoid steroid metabolism in monozygotic twins with intra-twin birthweightdifferences - Schulte, Sandra; Schreiner, Felix; Plamper, Michaela; Kasner, Charlotte; Gruenewald, Mathias; Bartmann, Peter Bartmann; Fimmers, Rolf; Hartmann, Michaela F.; Wudy, Stefan A.; Wölfle, Joachim; Gohlke, Bettina (HORMONE RESEARCH IN PAEDIATRICS, 2022)
CRIS-Team WoS Importer:2022-10-07

Influence of Prenatal Environment on Androgen Steroid Metabolism In Monozygotic Twins With Birthweight Differences - Schulte, Sandra; Schreiner, Felix; Plamper, Michaela; Kasner, Charlotte; Gruenewald, Mathias; Bartmann, Peter; Fimmers, Rolf; Hartmann, Michaela F.; Wudy, Stefan A.; Stoffel-Wagner, Birgit; Wölfle, Joachim; Gohlke, Bettina (Journal of Clinical Endocrinology and Metabolism, 2020)
OBJECTIVE: Although low birthweight (bw) and unfavorable intrauterine conditions have been associated with metabolic sequelae in later life, little is known about their impact on steroid metabolism. We studied genetically identical twins with intra-twin bw-differences from birth to adolescence to analyze the long-term impact of bw on steroid metabolism. METHODS: 68 monozygotic twin pairs with a bw-difference of <1 standard deviation score (SDS; concordant; n = 41) and ≥1 SDS (discordant; n = 27) were recruited. At 14.9 years (mean age), morning urine samples were collected and analyzed with gas chromatography-mass-spectrometry. RESULTS: No significant differences were detected in the concordant group. In contrast, in the smaller twins of the discordant group, we found significantly higher concentrations not only of the dehydroepiandrosterone sulfate (DHEAS) metabolite 16α-OH-DHEA (P = 0.001, 656.11 vs 465.82 µg/g creatinine) but also of cumulative dehydroepiandrosterone and downstream metabolites (P = 0.001, 1650.22 vs 1131.92 µg/g creatinine). Relative adrenal (P = 0.002, 0.25 vs 0.18) and overall androgen production (P = 0.001, 0.79 vs 0.65) were significantly higher in the formerly smaller discordant twins. All twin pairs exhibited significant intra-twin correlations for all individual steroid metabolites, sums of metabolites, indicators of androgen production, and enzyme activities. Multiple regression analyses of the smaller twins showed that individual steroid concentrations of the larger co-twin were the strongest influencing factor among nearly all parameters analyzed. CONCLUSION: In monozygotic twin pairs with greater intra-twin bw-differences (≥1 SDS), we found that bw had a long-lasting impact on steroid metabolism, with significant differences regarding DHEAS metabolites and relative androgen production. However, most parameters showed significant intra-twin correlations, suggesting a consistent interrelationship between prenatal environment, genetic background, and steroid metabolism.
CRIS-Team Scopus Importer:2020-09-04
Keywords: androgens; androgen production; fetal programming; low birthweight; steroid hormones; twin-to-twin transfusion syndrome

Influence of the autotaxin-lysophosphatidic acid axis on cellular function and cytokine expression in different breast cancer cell lines - Hauck, Theresa; Kadam, Sheetal; Heinz, Katharina; Garcia Peraza, Maria; Schmid, Rafael; Kremer, Andreas; Wolf, Katharina; Bauer, Alina; Horch, Raymund E.; Arkudas, Andreas; Kengelbach-Weigand, Annika (Scientific Reports, 2022)
Previous studies provide high evidence that autotaxin (ATX)-lysophosphatidic acid (LPA) signaling through LPA receptors (LPAR) plays an important role in breast cancer initiation, progression, and invasion. However, its specific role in different breast cancer cell lines remains to be fully elucidated to offer improvements in targeted therapies. Within this study, we analyzed in vitro the effect of LPA 18:1 and the LPAR1, LPAR3 (and LPAR2) inhibitor Ki16425 on cellular functions of different human breast cancer cell lines (MDA-MB-231, MDA-MB-468, MCF-7, BT-474, SKBR-3) and the human breast epithelial cell line MCF-10A, as well as Interleukin 8 (IL-8), Interleukin 6 (IL-6) and tumor necrosis factor (TNF)-alpha cytokine secretion after LPA-incubation. ATX-LPA signaling showed a dose-dependent stimulatory effect especially on cellular functions of triple-negative and luminal A breast cancer cell lines. Ki16425 inhibited the LPA-induced stimulation of triple-negative breast cancer and luminal A cell lines in variable intensity depending on the functional assay, indicating the interplay of different LPAR in those assays. IL-8, IL-6 and TNF-alpha secretion was induced by LPA in MDA-MB-468 cells. This study provides further evidence about the role of the ATX-LPA axis in different breast cancer cell lines and might contribute to identify subtypes suitable for a future targeted therapy of the ATX-LPA axis.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Cancer; Medical research; Molecular medicine

Influence of Timing of Antenatal Corticosteroid Administration on Morbidity of Preterm Neonates - Morhart, Patrick; Gärtner, Janis; Weiss, Christel; Stumpfe, Florian; Dammer, Ulf; Faschingbauer, Florian; Fahlbusch, Fabian; Beckmann, Matthias; Kehl, Sven (In Vivo, 2022)
Background/Aim: We investigated the impact of the timing of antenatal corticosteroid (ACS) administration on the clinical outcome of preterm infants. Patients and Methods: Two hundred and fifty-five preterm infants between 28+0 and 34+0 weeks of gestation were retrospectively assigned to one of two groups: In the first group, ACS was given within 7 days before birth; the second group, did not receive ACS during that period. The primary outcome parameter was respiratory failure (defined by need for continuous positive airway pressure or mechanical ventilation) due to grade 1-4 respiratory distress syndrome (RDS). Secondary outcomes included the rates of intraventricular hemorrhage (IVH), periventricular leukomalacia, and necrotizing enterocolitis. Results: The rate of RDS was significantly higher in the no ACS group (40% vs. 62%, p=0.0009), especially of the more severe grades 24 (n=37 vs. n=48, p=0.0121). In addition, IVH (1% vs. 9%, p=0.0041) and neonatal infections (72% vs. 89%, p=0.0025) were significantly increased. Univariable and multivariable regression analyses showed a lower likelihood of RDS in the ACS group [odds ratio (OR)=0.295] in infants born closer to term (OR=0.907) and following preterm onset of labor (OR=0.495). Similarly, we observed a lower probability of IVH in the ACS group (OR=0.098), with a higher probability of occurrence of IVH in pre-eclampsia/HELLP syndrome (hemolysis, elevated liver enzyme levels, low platelet count) (OR=7.914). Conclusion: ACS treatment within the last 7 days before birth significantly reduced the risk of RDS and IVH in preterm. These data emphasize that the timing of ACS administration determines its success.
CRIS-Team WoS Importer:2022-07-15

Influence of Turkish origin on hematology reference intervals in the German population - Mayr, Franz Xaver; Bertram, Alexander; Cario, Holger; Frühwald, Michael C.; Groß, Hans Jürgen; Groening, Arndt; Grützner, Stefanie; Gscheidmeier, Thomas; Hoffmann, Reinhard; Krebs, Alexander; Ruf, Hans Georg; Torge, Antje; et al. (Scientific Reports, 2021)
Reference intervals for laboratory test results have to be appropriate for the population in which they are used to be clinically useful. While sex and age are established partitioning criteria, patients’ origin also influences laboratory test results, but is not commonly considered when creating or applying reference intervals. In the German population, stratification for ethnicity is rarely performed, and no ethnicity-specific hematology reference intervals have been reported yet. In this retrospective study, we investigated whether specific reference intervals are warranted for the numerically largest group of non-German descent, individuals originating from Turkey. To this end, we analyzed 1,314,754 test results from 167,294 patients from six German centers. Using a name-based algorithm, 1.9% of patients were identified as originating from Turkey, in line with census data and the algorithm’s sensitivity. Reference intervals and their confidence intervals were calculated using an indirect data mining approach, and Turkish and non-Turkish reference limits overlapped completely or partially in nearly all analytes, regardless of age and sex, and only 5/144 (3.5%) subgroups’ reference limits showed no overlap. We therefore conclude that the current practice of using common reference intervals is appropriate and allows correct clinical decision-making in patients originating from Turkey.
CRIS-Team Scopus Importer:2021-11-05

Inhibition of activator protein 1 signaling abrogates transforming growth factor β-mediated activation of fibroblasts and prevents experimental fibrosis - Avouac, Jerome; Palumbo, Katrin; Tomcik, Michal; Zerr, Pawel; Dees, Clara; Horn, Angelika; Maurer, Britta; Akhmetshina, Alfiya; Beyer, Christian; Sadowski, Anika; Schneider, Holm; Shiozawa, Shunichi; et al. (Arthritis and Rheumatism, 2012)
Objective To investigate whether c-Jun and c-Fos contribute to the pathologic activation of fibroblasts in systemic sclerosis (SSc) and to evaluate the antifibrotic potential of selective activator protein 1 (AP-1) inhibition. Methods Expression of c-Jun and c-Fos was determined by real-time polymerase chain reaction (PCR) and immunohistochemical analysis. Fibroblasts were stimulated with transforming growth factor β (TGFβ) and incubated with T-5224, a small-molecule inhibitor of AP-1, or were transfected with small interfering RNA (siRNA) duplexes against c-Jun and c-Fos. Collagen synthesis was quantified by real-time PCR and hydroxyproline assay. Differentiation of resting fibroblasts into myofibroblasts was assessed by staining for α-smooth muscle actin and stress fibers. The antifibrotic potential of T-5224 was evaluated in mouse models of dermal fibrosis induced by bleomycin or by adenoviral overexpression of a constitutively active TGFβ receptor type I. Results Up-regulation of c-Jun and c-Fos was detected in mouse models of SSc and in the skin and dermal fibroblasts of patients with SSc. Stimulation of healthy fibroblasts with TGFβ induced the expression of c-Jun and c-Fos. Treatment with T-5224 or nucleofection with siRNA directed against c-Jun and c-Fos abrogated the profibrotic effects of TGFβ. T-5224 decreased the release of collagen selectively in SSc fibroblasts. T-5224 was well tolerated and prevented dermal fibrosis induced by bleomycin or by adenoviral activation of TGFβ signaling. Conclusion AP-1 is up-regulated in a TGFβ-dependent manner in SSc. The selective AP-1 inhibitor T-5224 reduced collagen synthesis selectively in SSc fibroblasts and efficiently prevented the development of experimental dermal fibrosis. Thus, AP-1 might be a promising new molecular target for the treatment of SSc. Copyright © 2012 by the American College of Rheumatology.
CRIS-Team Scopus Importer:2020-07-01

Inhibition of sumoylation prevents experimental fibrosis - Khodzhigorova, Aisa; Distler, Alfiya; Lang, Veronika; Dees, Clara; Schneider, Holm; Beyer, Christian; Gelse, Kolja; Distler, Oliver; Schett, Georg; Distler, Jörg (Annals of the Rheumatic Diseases, 2012)
Objectives: Fibrosis is a predominant cause of death in systemic sclerosis (SSc). First epigenetic modifications have recently been shown to contribute to activation of SSc fibroblasts. Here, we investigated inhibition of sumoylation as a novel antifibrotic approach. Methods: Sumoylation was inhibited by siRNA-mediated knockdown of the Small Ubiquitin-like MOdifiers (SUMO) E2-conjugating enzyme Ubc9, which is essential for sumoylation. The effects of knockdown of Ubc9 were analysed in bleomycin-induced dermal fibrosis, and in the model of fibrosis induced by overexpression of a constitutively active TGF-beta receptor type I (TBR). SUMO-1 and phosphorylated Smad3 were detected by immunohistochemistry. Results: Increased staining for SUMO-1 was detected in patients with SSc and in experimental fibrosis. Inhibition of sumoylation exerted potent antifibrotic effects and prevented dermal thickening, myofibroblast differentiation and accumulation of collagen induced by bleomycin, or by overexpression of constitutively active TBR. Moreover, knockdown of Ubc9 reduced the accumulation of phosphorylated Smad3 in experimental fibrosis indicating that inhibition of sumoylation may normalise canonical TGF-β signalling in vivo. Conclusions: We demonstrate that inhibition of sumoylation reduces canonical TGF-β signalling and prevents experimental fibrosis in different preclinical models. These data provide first evidence that targeting of aberrant sumoylation may be a novel therapeutic approach for fibrotic diseases.
CRIS-Team Scopus Importer:2020-07-01

Inhibition of tgf-β signaling and decreased apoptosis in iugr-associated lung disease in rats - Alcazar, Miguel Angel Alejandre; Morty, Rory E.; Lendzian, Lisa; Vohlen, Christina; Oestreicher, Iris; Plank, Christian Georg; Schneider, Holm; Doetsch, Joerg (PLoS ONE, 2011)
Intrauterine growth restriction is associated with impaired lung function in adulthood. It is unknown whether such impairment of lung function is linked to the transforming growth factor (TGF)-β system in the lung. Therefore, we investigated the effects of IUGR on lung function, expression of extracellular matrix (ECM) components and TGF-β signaling in rats. IUGR was induced in rats by isocaloric protein restriction during gestation. Lung function was assessed with direct plethysmography at postnatal day (P) 70. Pulmonary activity of the TGF-β system was determined at P1 and P70. TGF-β signaling was blocked in vitro using adenovirus-delivered Smad7. At P70, respiratory airway compliance was significantly impaired after IUGR. These changes were accompanied by decreased expression of TGF-β1 at P1 and P70 and a consistently dampened phosphorylation of Smad2 and Smad3. Furthermore, the mRNA expression levels of inhibitors of TGF-β signaling (Smad7 and Smurf2) were reduced, and the expression of TGF-β-regulated ECM components (e.g. collagen I) was decreased in the lungs of IUGR animals at P1; whereas elastin and tenascin N expression was significantly upregulated. In vitro inhibition of TGF-β signaling in NIH/3T3, MLE 12 and endothelial cells by adenovirus-delivered Smad7 demonstrated a direct effect on the expression of ECM components. Taken together, these data demonstrate a significant impact of IUGR on lung development and function and suggest that attenuated TGF-β signaling may contribute to the pathological processes of IUGR-associated lung disease. © 2011 Alejandre Alcázar et al.
CRIS-Team Scopus Importer:2020-07-01

Insights into the infiltrative behavior of adamantinomatous craniopharyngioma in a new xenotransplant mouse model - Stache, Christina; Hoelsken, Annett; Schlaffer, Sven-Martin; Heß, Andreas; Metzler, Markus; Frey, Benjamin; Fahlbusch, Rudolf; Flitsch, Joerg; Buchfelder, Michael; Buslei, Rolf (Brain Pathology, 2015)
Adamantinomatous craniopharyngiomas (adaCP) cause hypothalamic pituitary dysfunction. Elucidation of pathomechanisms underlying tumor progression is essential for the development of targeted chemotherapeutic treatment options. In order to study the mechanisms of tumor outgrowth, we implanted human primary adaCP tissue from three different surgical specimens stereotactically into the brain of immunodeficient mice (n = 20). Three months after tumor inoculation, magnetic resonance imaging and histology confirmed tumor engraftment in all 20 mice (100%) that obtained tissue transplants. The lesions invaded adjoining brain tissue with micro finger-shaped protrusions. Immunohistochemical comparison of the primary tumor and xenotransplants revealed a similar amount of proliferation (Mib-1) and cytokeratin expression pattern (KL-1). Whole tumor reconstruction using serial sections confirmed whirl-like cell clusters with nuclear ?-catenin accumulations at the tumor brain border. These whirls were surrounded by a belt of Claudin-1 expressing cells, showed an activated epidermal growth factor receptor (EGFR) and distinct CD133 as well as p21(WAF1/Cip1) positivity, indicating a tumor stem cell phenotype. Consistent with our previous in vitro studies, intracranial xenotransplants of adaCP confirmed cells with nuclear ?-catenin and activated EGFR being the driving force of tumor outgrowth. This model provides the possibility to study in vivo tumor cell migration and to test novel treatment regimens targeting this tumor stem cell niche.
EVALuna2:7210

Intrafamilial neurological phenotypic variability due to either biallelic or monoallelic pathogenic variants in CACNA1A - Mammadova, Dilbar; Kraus, Cornelia; Leis, Thomas; Popp, Bernt; Zweier, Christiane; Reis, André; Trollmann, Regina (Frontiers in Neurology, 2024)
Pathogenic heterozygous variants in CACNA1A are associated with familial hemiplegic migraine, episodic ataxia type 2 and spinocerebellar ataxia type 6, and more recently, neurodevelopmental disorders. We describe a severe, early-onset phenotype including severe muscular hypotonia, early-onset epileptic seizures, apnoea, optic atrophy and dysphagia in three siblings carrying compound heterozygous frameshift variants in CACNA1A. Two male patients died at the age of 5 or 14 months of suspected SIDS or severe developmental epileptic encephalopathy (DEE) with refractory seizures and apnoea. A male child (index patient) developed severe early-onset DEE including seizures and ictal apnoea at the age of 4 weeks. Another male child developed generalized epilepsy and mild intellectual impairment in late infancy, and his mother and his maternal uncle were identified as carriers of a known CACNA1A pathogenic variant [c.2602delG heterozygous, p. (Ala868Profs*24)] with a diagnosis of episodic ataxia type 2. This maternal pathogenic variant c.2602delG was detected in the index patient and child 2. Trio-Exome sequencing identified an additional heterozygous pathogenic variant in the CACNA1A gene, c.5476delC, p.(His1826Thrfs*30) in the index patient and child 2, which was inherited from the asymptomatic father. In conclusion, the novel compound heterozygosity for two frameshift pathogenic variants, maternally [c.2602delG, p.(Ala868Profs*24)] and paternally [c.5476delC, p.(His1826Thrfs*3)] is associated with a severe phenotype of early-onset DEE. This observation highlights the necessity of additional analyses to clarify unusual phenotypes even if a pathogenic variant has already been identified, and expands the clinical spectrum of CACNA1A-related disorders.
CRIS-Team Scopus Importer:2024-10-25
Keywords: apneic spells; burst suppression; developmental epileptic encephalopathy; early-onset epileptic encephalopathy; generalized epilepsy; optic nerve atrophy

Investigating significant health trends in growth hormone treatments registry: rationale, aims and design of a nationwide prospective registry (study protocol) - Schnabel, Dirk; Kreitschmann-Andermahr, Ilonka J.; Strasburger, Christian; Pittrow, David; Pausch, Christine; Wölfle, Joachim; Nsights-Ght Study Grp, (Orphanet Journal of Rare Diseases, 2023)
Background: Somatropin treatment is indicated in a variety of disorders including growth hormone (GH) deficiency, Prader–Willi and Turner syndrome, chronic renal insufficiency and others. To date, almost all studies have been limited to single GH products, and no independent registry across indications and somatropin products was ever established. Aim: The present investigator-initiated registry named INSIGHTS-GHT aims to provide comprehensive information on various aspects of somatropin treatment in Germany in approved indications within routine clinical practice: drug utilization, effectiveness (including real final height, body composition), tolerability, quality of life, other patient related outcomes (PRO), and health economic variables. Methods: Registry (prospective observational study) in specialised pediatric and adult endocrinology centres in Germany. Patients of any age are eligible for documentation, if they are on ongoing or newly initiated treatment with any approved somatropin or somatropin-related product within the labelling, available for long term follow-up documentation, and if they provided informed consent. Subjects may switch, discontinue/interrupt or initiate somatropin products at any time. They are followed up for at least 3 years (minimal study duration). Documentation is planned once or twice per year to record somatropin utilisation (product, dosing), other medications, laboratory status (glucose, lipids, GH function including stimulation tests, IGF-I, IGFBP3), if applicable, pubertal development, auxological parameters, body composition and bone age. Patient reported outcome (PRO) measures include, but are not limited to, Short Form 12 in adults and adolescents aged 14 years and over. Safety reporting includes adverse events. Conclusions: The registry documents children and adults in one joint registry, includes, at present, patients in Germany and allows documentation of patients on all approved somatropin and other growth hormone preparations. It will allow to describe the transition of subjects from adolescence to adulthood (treatment and height), to describe switches between somatotropin preparations, to perform responder analyses, and to analyse differences and similarities of somatropin utilization (by age group, sex, setting, and PRO instrument). INSIGHTS-GHT offers a broad, comprehensive research platform to assess multiple relevant aspects of somatropin treatment and outcomes (including the transition of subjects from adolescence to adulthood), allows the documentation of all GH products including long-acting GH preparations after their introduction, and will evaluate the data independently of funders. Trial registration BfArM Nr. NIS7492, DRKS registry DRKS00027394.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Adults; Children; Growth hormone deficiency; Human growth hormone; Observational; Somatropin

In Vivo Assessment of Deep Vascular Patterns in Murine Colitis Using Optoacoustic Mesoscopic Imaging - Bühler, Adrian; Brown, Emma L.; Nedoschill, Emmanuel; Eckstein, Markus; Ludwig, Petra; Wachter, Felix; Mandelbaum, Henriette; Raming, Roman; Oraiopoulou, Mariam Eleni; Paulus, Lars-Philip; Rother, Ulrich; Friedrich, Oliver; et al. (Advanced Science, 2024)
The analysis of vascular morphology and functionality enables the assessment of disease activity and therapeutic effects in various pathologies. Raster-scanning optoacoustic mesoscopy (RSOM) is an imaging modality that enables the visualization of superficial vascular networks in vivo. In murine models of colitis, deep vascular networks in the colon wall can be visualized by transrectal absorber guide raster-scanning optoacoustic mesoscopy (TAG-RSOM). In order to accelerate the implementation of this technology in translational studies of inflammatory bowel disease, an image-processing pipeline for TAG-RSOM data has been developed. Using optoacoustic data from a murine model of chemically-induced colitis, different image segmentation methods are compared for visualization and quantification of deep vascular patterns in terms of vascular network length and complexity, blood volume, and vessel diameter. The presented image-processing pipeline for TAG-RSOM enables label-free in vivo assessment of changes in the vascular network in murine colitis with broad applications for inflammatory bowel disease research.
CRIS-Team Scopus Importer:2024-11-01
Keywords: dextran sodium sulfate induced colitis; inflammatory bowel disease; murine acute colitis; optoacoustic imaging; photoacoustic imaging; raster-scanning optoacoustic mesoscopy; vessel morphology analysis

In vivo evaluation of gene transfer into mesenchymal cells (in view of cartilage repair). - Gelse, Kolja; Schneider, Holm (Methods in Molecular Biology, 2011)
Gene transfer of specific growth factors is suitable for inducing chondrogenic differentiation of -mesenchymal cells to be used for cartilage regeneration. However, extent and quality of repair tissue formation also depend on biomechanical and metabolic influences that can only be studied in vivo. We describe three methods to evaluate viral gene transfer into mesenchymal cells in animal models of articular cartilage defects, e.g., mouse, rat and miniature pig models, focussing on the repair of hyaline cartilage tissue.
CRIS-Team Scopus Importer:2020-07-01

Kann die Ketoacidose bei pädiatrischen Patienten mit Manifestation eines Diabetes mellitus Typ 1 vermieden werden? Lehren aus der COVID-19-Pandemie - Mönkemöller, Kirsten; Kamrath, Clemens; Hammersen, Johanna; Biester, Torben; Warncke, Katharina; Pappa, Angeliki; Fink, Katharina; Raile, Klemens; Rohrer, Tilman R.; Holl, Reinhard W. (Monatsschrift Kinderheilkunde, 2021)
Background: Diabetic ketoacidosis (DKA) is a life-threatening emergency in children and adolescents with manifestation of type 1 diabetes mellitus (DM1) and often associated with delayed diagnosis or previous diagnostic errors. During the coronavirus disease 2019 (COVID-19) lockdown period in Germany, less patients presented at emergency departments and private practices. Objective: The aim of this study was to investigate the DKA risk in children and adolescents with DM1 manifestation during the COVID-19 lockdown and associated risk factors. Material and methods: The frequency of DKA at DM1 onset in patients <18 years between 13 March and 13 May 2020 in pediatric diabetes centers was analyzed. The centers also documented their assessment, if the presentation was delayed or the diagnosis was not made on the first medical consultation. In order to analyze the influence of the risk factors on the frequency of DKA, the data from 2020 were compared with the same periods in 2018 and 2019 using multivariable linear and logistic regression. Results: The data of 532 patients from 216 diabetes centers showed that the risk for DKA increased by 84.7% and the risk for severe DKA increased by 45.3% compared to the years 2018/2019. Children <6 years had the highest risk with an 141.6% increase for DKA and 97.0% for severe DKA compared to the previous years. Migration background was a risk factor independent of COVID-19. Of the patients 31% had either a delayed presentation or a missed diagnosis. Conclusion: During the COVID-19 lockdown the frequency of DKA and severe DKA at DM1 onset was significantly increased for children and adolescents in Germany. Age <6 years, migration background and delayed diagnosis were the main risk factors.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Children < 6 years; COVID-19 lockdown; Delayed presentation; Migration background; Missed diagnosis

Klinische Ethikkomitees Chancen, Risiken und Nebenwirkungen - Frewer, Andreas; Fahr, Uwe; Rascher, Wolfgang (Königshausen & Neumann, 2008)
UnivIS-Import:2019-03-25:Pub.2008.sonste.verbun.fbzhl.philos

Lang wirksames Wachstumshormon – eine neue Therapieoption für Kinder mit Wachstumshormonmangel: Status 2024 - Dörr, Helmuth-Günther; Bettendorf, Markus; Wölfle, Joachim; Saenger, Paul; Ranke, Michael B. (Monatsschrift Kinderheilkunde, 2024)
Until recently, daily singular subcutaneous injections of recombinant human growth hormone (rhGH) was the treatment of choice in short-statured children with growth hormone deficiency (GHD). This concept has been effective and safe for almost four decades; however, with this practice of replacement therapy approximately 10–20% of the children did not reach an adult height within the target range of the parents. Among the various factors involved, insufficient adherence, as the consequence of the necessary but inconvenient daily injections has been identified as a particularly important factor. This prompted the development of long-acting growth hormone (LAGH). At the end of 2023 there were three approved LAGH preparations available in Germany for the treatment of children older than 3 years with GHD due to an insufficient secretion of GH. All approved LAGH formulations use different technologies to prolong the half-life of rhGH. The LAGH as well as rhGH bind to the GH receptor and initiate the signal cascade that leads to the activation of growth and metabolism. In phase 3 studies LAGH showed non-inferiority to daily rhGH injections in terms of increasing height as well as comparability in the safety profiles. Thus, the treatment with LAGH offers a new option for children and adolescents with GHD; however, the long-term efficacy and safety need further systematic evaluation. Parents and patients need to be informed about all relevant aspects of the new treatment. This review article discusses the currently approved LAGH preparations in Germany together with the published data from a pediatric perspective.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Adherence; Lonapegsomatropin; Somapacitan; Somatrogon

Large amplicon droplet digital PCR for DNA-based monitoring of pediatric chronic myeloid leukaemia - Krumbholz, Manuela; Görlitz, Katharina; Albert, Christian; Lawlor, Jennifer; Suttorp, Meinolf; Metzler, Markus (Journal of Cellular and Molecular Medicine, 2019)
Quantification of tumour-specific molecular markers at the RNA and DNA level for treatment response monitoring is crucial for risk-adapted stratification and guidance of individualized therapy in leukaemia and other malignancies. Most pediatric leukaemias and solid tumours of mesenchymal origin are characterized by a relatively low mutation burden at the single nucleotide level and the presence of recurrent chromosomal translocations. The genomic fusion sites resulting from translocations are stable molecular tumour markers; however, repeat-rich DNA sequences flanking intronic breakpoints limit the design of high sensitivity PCR assays for minimal residual disease (MRD) monitoring. Here, we quantitatively evaluated the impact of repeat elements on assay selection and the feasibility of using extended amplicons (≤1330 bp) amplified by droplet digital PCR to monitor pediatric chronic myeloid leukaemia (CML). Molecular characterization of 178 genomic BCR-ABL1 fusion sites showed that 64% were located within sequence repeat elements, impeding optimal primer/probe design. Comparative quantification of DNA and RNA BCR-ABL1 copy numbers in 687 specimens from 55 pediatric patients revealed that their levels were highly correlated. The combination of droplet digital PCR, double quenched probes and extended amplicons represents a valuable tool for sensitive MRD assessment in CML and may be adapted to other translocation-positive tumours.
CRIS-Team Scopus Importer:2019-08-06
Keywords: BCR-ABL1 fusion; biomarkers; chronic myeloid leukaemia CML; digital PCR; disease monitoring; genomic fusion sequences; pediatric oncology; translocation

Latent class distributional regression for the estimation of non-linear reference limits from contaminated data sources - Hepp, Tobias; Zierk, Jakob; Rauh, Manfred; Metzler, Markus; Mayr, Andreas (BMC Bioinformatics, 2020)
Background: Medical decision making based on quantitative test results depends on reliable reference intervals, which represent the range of physiological test results in a healthy population. Current methods for the estimation of reference limits focus either on modelling the age-dependent dynamics of different analytes directly in a prospective setting or the extraction of independent distributions from contaminated data sources, e.g. data with latent heterogeneity due to unlabeled pathologic cases. In this article, we propose a new method to estimate indirect reference limits with non-linear dependencies on covariates from contaminated datasets by combining the framework of mixture models and distributional regression. Results: Simulation results based on mixtures of Gaussian and gamma distributions suggest accurate approximation of the true quantiles that improves with increasing sample size and decreasing overlap between the mixture components. Due to the high flexibility of the framework, initialization of the algorithm requires careful considerations regarding appropriate starting weights. Estimated quantiles from the extracted distribution of healthy hemoglobin concentration in boys and girls provide clinically useful pediatric reference limits similar to solutions obtained using different approaches which require more samples and are computationally more expensive. Conclusions: Latent class distributional regression models represent the first method to estimate indirect non-linear reference limits from a single model fit, but the general scope of applications can be extended to other scenarios with latent heterogeneity.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Distributional regression; Finite mixture models; Latent class regression; Reference limits

Lebenssituation von jungen Frauen mit Ullrich-Turner-Syndrom nach dem Ende der Wachstumshormontherapie: Ergebnisse einer Umfrage in Deutschland - Dörr, Helmuth-Günther; Bettendorf, Markus; Binder, Gerhard; Brämswig, Jürgen; Hauffa, Berthold P.; Holterhus, Paul Martin; Mohnike, Klaus; Schmidt, Heinrich; Stalla, Günter K.; Wabitsch, Martin; Wölfle, Joachim (Deutsche Medizinische Wochenschrift, 2019)
Introduction Psychosocial problems such as anxious personality, low self-esteem, late separation from home and/or late sexual experience have been described in girls and women with Turner syndrome (TS). Methods The study was performed in 2015 based on a questionnaire that was sent out to 779 women with TS aged 25 years (median). The questionnaire was devised by a French team and used with their permission. In all, 130 questionnaires (16.7%) could be evaluated. The questions from the individual topics were not always completely answered. Results (mean ± SD). 116 women (89.9%) were not married; 52 women (40%) lived in their parents' home. 47.6% had a high-school/technical diploma or university degree. 60 women (46%) had a job; 51 women (39%) had not completed vocational training. Puberty was induced at the age of 14.2± 2.1 years in 78% of the women. 80% of the women received hormone replacement therapy at the time of the questionnaire survey. 66 of 93 women (71%) found that the disease had a negative influence on emotional life. Love life and sexual relationship was the topic mentioned most frequently by 44 women (66.6%). 116 women answered questions on sexuality. Here, 77% had the first French kiss at the age of 16.4± 3.6 years and 62.4% had sexual intercourse for the first time at the age of 19.0±3.4 years. 81% of the women stated that they had a partner relationship for more than 6 months (94 women had a male partner and 5 had a female partner). The question as to the wish to have children was answered in the affirmative by 89 of 124 women (71.8%); 38.2% desired spontaneous pregnancy and 44.9% had considered in vitro fertilization or adoption. Discussion The women's answers show that care needs to be improved. There are deficits in the topics of family, emotional life, relationships, sexuality, fertility and pregnancy. Therefore, the medical team should also include psychologists and social workers.
CRIS-Team Scopus Importer:2019-07-26
Keywords: emotional life; fertility; questionnaire; sexuality

Letter: Enhancing Predictive Models for Paediatric Ulcerative Colitis—Addressing Socioeconomic, Environmental and Clinical Factors. Authors' Reply - Claßen, Merle; Schiller, Benjamin; Däbritz, Jan (Alimentary Pharmacology & Therapeutics, 2024)
CRIS-Team Scopus Importer:2024-12-06

Levothyroxine Treatment of Euthyroid Children with Autoimmune Hashimoto Thyroiditis: Results of a Multicenter, Randomized, Controlled Trial - Dörr, Helmuth-Günther; Bettendorf, Markus; Binder, Gerhard; Karges, Beate; Kneppo, Carolin; Schmidt, Heinrich; Voss, Egbert; Wabitsch, Martin; Doetsch, Joerg (Hormone Research in Paediatrics, 2015)
Levothyroxine (L-T4) treatment of euthyroid children with Hashimoto thyroiditis (HT) is a controversial issue.We conducted a prospective, randomized, controlled clinical trial. Out of 79 identified euthyroid patients, 59 started the study; 25 patients (21 female, 4 male; age: 11.8 ± 2.3 years) received L-T4 at a mean dose of 1.6 µg/kg (SD, 0.8) daily, and 34 (27 female, 7 male; age: 12.6 ± 1.2 years) were not treated. Patients developing subclinical hypothyroidism during follow-up (n = 13) were treated with L-T4 and removed from the observation group. As the main outcome measures, thyroid gland volume (determined by ultrasound) as well as serum levels of TSH, free T4, and antibodies against thyroid peroxidase and thyroglobulin were assessed every 6 months for 36 months.At the start, the mean thyroid volume (standard deviation score, SDS) was 2.5 in the treatment group and 1.6 in the observation group. There was a constant decline in mean thyroid volume (SDS) from 2.13 (month 12) to 1.12 (month 30) in the treated group, with a delta thyroid volume of -1.01 SDS. In the observation group, the mean delta thyroid volume increased to +0.27 SDS. The change of the delta thyroid volume was statistically significantly different between both groups during the 12- and 30-month time points (p < 0.05). L-T4 had no effect on thyroid function and serum thyroid antibodies.L-T4 treatment can decrease the thyroid volume in euthyroid children with HT, but the effect is limited to a definite time period.
EVALuna2:18916

Life Situation of Young women with Turner Syndrome: Results of a Questionnaire-based Study in Germany - Dörr, Helmuth-Günther; Bettendorf, Markus; Binder, Gerhard; Braemswig, Juergen; Hauffa, Berthold P.; Holterhus, Paul-Martin; Mohnike, Klaus; Schmidt, Heinrich; Stalla, Gunter K.; Wabitsch, Martin; Woelfle, Joachim (Deutsche Medizinische Wochenschrift, 2019)
INTRODUCTION: Psychosocial problems such as anxious personality, low self-esteem, late separation from home and/or late sexual experience have been described in girls and women with Turner syndrome (TS). METHODS: The study was performed in 2015 based on a questionnaire that was sent out to 779 women with TS aged 25 years (median). The questionnaire was devised by a French team and used with their permission. In all, 130 questionnaires (16.7 %) could be evaluated. The questions from the individual topics were not always completely answered. RESULTS: (mean ± SD).: 116 women (89.9 %) were not married; 52 women (40 %) lived in their parents' home. 47.6 % had a high-school/technical diploma or university degree. 60 women (46 %) had a job; 51 women (39 %) had not completed vocational training. Puberty was induced at the age of 14.2 ± 2.1 years in 78 % of the women. 80 % of the women received hormone replacement therapy at the time of the questionnaire survey. 66 of 93 women (71 %) found that the disease had a negative influence on emotional life. "Love life and sexual relationship" was the topic mentioned most frequently by 44 women (66.6 %). 116 women answered questions on sexuality. Here, 77 % had the first French kiss at the age of 16.4 ± 3.6 years and 62.4 % had sexual intercourse for the first time at the age of 19.0 ± 3.4 years. 81 % of the women stated that they had a partner relationship for more than 6 months (94 women had a male partner and 5 had a female partner). The question as to the wish to have children was answered in the affirmative by 89 of 124 women (71.8 %); 38.2 % desired spontaneous pregnancy and 44.9 % had considered in vitro fertilization or adoption. DISCUSSION: The women's answers show that care needs to be improved. There are deficits in the topics of family, emotional life, relationships, sexuality, fertility and pregnancy. Therefore, the medical team should also include psychologists and social workers.
EVALuna2:202757

Liquid Biopsies in Ewing Sarcoma - Krumbholz, Manuela; Metzler, Markus (Ewing Sarcoma, 2021)
Liquid biopsies enable noninvasive therapy monitoring in patients with solid tumors. Specific serum markers such as proteins, hormones, or enzymes released from tumor cells or in response to tumor growth can be used for quantification of the tumor burden. However, only a fraction of pediatric tumors has none of these serum markers, but tumor-specific genetic alterations represent reliable alternatives. Here we describe a method for using genomic fusion sequences as liquid biopsy markers in Ewing sarcoma patients.
CRIS-Team Scopus Importer:2021-01-01
Keywords: Cell-free circulating DNA; Double-quenched probes; Droplet digital PCR; Ewing sarcoma; Genomic fusion sequences; Liquid biopsy; Serum marker

Long-Acting Growth Hormone Therapy in Pediatric Growth Hormone Deficiency: A Consensus Statement. - Maniatis, Aristides; Cutfield, Wayne; Dattani, Mehul; Deal, Cheri; Collett-Solberg, Paulo Ferrez; Horikawa, Reiko; Maghnie, Mohamad; Miller, Bradley S.; Polak, Michel; Sävendahl, Lars; Wölfle, Joachim (Journal of Clinical Endocrinology and Metabolism, 2025)
CONTEXT: Several long-acting growth hormone (LAGH) therapies have recently become available, but guidance on their usage in children with growth hormone (GH) deficiency is limited. METHODS: International experts in pediatric endocrinology were invited to join a consensus group based on their expertise in treating children with daily GH and LAGH. The group comprised 11 experts from 10 countries across the world. Online group meetings were held in February to March 2024 followed by a 1-day in-person meeting in May 2024 to finalize the consensus recommendations. A targeted literature search approach was used to identify and share evidence ahead of the meetings. Formulations considered were limited to those with international populations in phase III pivotal trials and regulatory approvals in multiple countries. EVIDENCE SYNTHESIS: Topics covered include patient selection and preference, dose adjustment, initiating and switching therapies, administration, adherence and missed doses, practical considerations, and knowledge gaps. LAGH formulations offer a potential advantage over daily GH injections for children with GH deficiency in terms of reduced injection frequency and treatment burden; this may also be associated with improved adherence and treatment outcomes over time. However, data on LAGH in pediatric GH deficiency are mostly limited to clinical trials, and long-term, real-world data are currently lacking. CONCLUSION: This article provides an international consensus on the use of LAGH therapy in children with GH deficiency to guide practitioners when considering these new treatment options for their patients. Long-term data are needed to fill current data gaps and allow the creation of comprehensive evidence-based recommendations.
EVALuna2:586369

Long-term outcomes of very-low-birth-weight and low-birth-weight preterm newborns with neonatal seizures: A single-center perspective - Schüssler, Stephanie; Schmidt, Martina; Deiters, Ludger; Candova, A.; Fahlbusch, Fabian; Trollmann, Regina (European Journal of Paediatric Neurology, 2022)
Objective: Newborn seizures are frequent in preterm newborns and indicate brain lesions in many cases. The objective of this observational study was to investigate the long-term outcome of very-low-birth-weight (VLBW) and low-birth-weight (LBW) preterm infants with neonatal seizures. Methods: We examined 54 preterm infants (40 VLBW and 14 LBW cases) born between 2008 and 2011 with clinical seizures during the neonatal period confirmed by interictal or ictal electroencephalography recordings in a retrospective single-center study. Neurodevelopmental follow-up included an expert neurological examination and cognitive testing (Kaufman Assessment Battery for Children) at a mean age of six years. Results: The (mean ± standard deviation) gestational ages of the VLBW and LBW infants were 27.2 ± 1.9 weeks and 33.4 ± 1.7 weeks, respectively, and the postnatal age at seizure onset was 13 ± 11 days in VLBW infants and 9 ± 8 days in LBW infants, with a wide range of one to 62 days. LBW infants more frequently developed non-motor seizures (50.0%) than VLBW infants did (25.0%), and higher-grade intracranial hemorrhage was the predominant etiology in the VLBW group (18.0%), while the etiology in the LBW group was more heterogeneous and included central nervous system malformations and genetic syndromes. At the mean age of 6.2 ± 2.0, years, 25/54 patients were assessed and 44.4% of the VLBW group and 71.4% of the LBW group showed intellectual impairment. Infantile cerebral palsy was present in 22% of VLBW and 42.9% of LBW infants, respectively. Significance: The present analysis of long-term neurodevelopmental outcomes of preterm neonates who experienced seizures shows that the risk for intellectual impairment is not limited only to VLBW infants but may significantly affect LBW infants as well. The etiological spectrum differs in relation to gestational age.
CRIS-Team Scopus Importer:2022-01-14
Keywords: Cognitive development; Neonatal EEG; Neurodevelopmental outcome; Preterm; Prognosis

Long-term positive and negative psychosocial outcomes in young childhood cancer survivors, type 1 diabetics and their healthy peers - Kremer, Anna-Lena; Schieber, Katharina; Metzler, Markus; Schuster, Sonja; Erim, Yesim (International Journal of Adolescent Medicine and Health, 2016)
EVALuna2:18942

Long-term Surveillance of Children with Congenital Hypothyroidism: Data from the German Registry for Congenital Hypothyroidism (AQUAPE "Hypo Dok") - Ellerbroek, V. L.; Bonfig, W.; Dörr, Helmuth-Günther; Bettendorf, M.; Hauffa, B.; Fricke-Otto, S.; Rohrer, T.; Reschke, F.; Schoenau, E.; Schwab, K. O.; Kapelari, K.; Roehl, F. -W.; et al. (Klinische Pädiatrie, 2015)
The German study group for quality assurance in pediatric endocrinology and the University of Ulm have established a software ("Hypo Dok") for the documentation of longitudinal data of patients with congenital primary hypothyroidism (CH). Aim of this study was to analyse the long-term follow-up of patients with CH and to compare treatment with current guidelines.Anonymised data of 1,080 patients from 46 centres were statistically analysed.Newborn screening result was available at a mean age of 7.3 days. Confirmation of the diagnosis was established at 8.4 days and therapy was started at 11 days. The average screening TSH was 180.0 mIU/L. During the first 3 months mean levothyroxine (LT4) dose was 10.7 µg/kg/day or 186.0 µg/m²/day. Weight-, BMI- and height-SDS did not differ significantly from the normal population. Only 25% of the patients (n=262) underwent formal EQ/IQ-testing. Their average IQ was 98.8 ± 13.2 points.In Germany screening, confirmation and start of treatment of CH are within the recommended time frame of 14 days. Initial LT4-doses are adequate. The auxological longterm outcome of young CH patients is normal. The implementation of standardized IQ testing has to be improved in routine patient care.Longitudinal data of patients with CH was analysed and compared to current guidelines. Confirmation and start of treatment are according to the recommendations. However standardised IQ testing requires improvement.
EVALuna2:18917

Low-frequency variation near common germline susceptibility loci are associated with risk of Ewing sarcoma - Lin, Shu Hong; Sampson, Joshua N.; Grünewald, Thomas G.P.; Surdez, Didier; Reynaud, Stephanie; Mirabeau, Olivier; Karlins, Eric; Rubio, Rebeca Alba; Zaidi, Sakina; Grossetête-Lalami, Sandrine; Ballet, Stelly; Lapouble, Eve; et al. (PLoS ONE, 2020)
Background Ewing sarcoma (EwS) is a rare, aggressive solid tumor of childhood, adolescence and young adulthood associated with pathognomonic EWSR1-ETS fusion oncoproteins altering transcriptional regulation. Genome-wide association studies (GWAS) have identified 6 common germline susceptibility loci but have not investigated low-frequency inherited variants with minor allele frequencies below 5% due to limited genotyped cases of this rare tumor. Methods We investigated the contribution of rare and low-frequency variation to EwS susceptibility in the largest EwS genome-wide association study to date (733 EwS cases and 1,346 unaffected controls of European ancestry). Results We identified two low-frequency variants, rs112837127 and rs2296730, on chromosome 20 that were associated with EwS risk (OR = 0.186 and 2.038, respectively; P-value < 5×10−8) and located near previously reported common susceptibility loci. After adjusting for the most associated common variant at the locus, only rs112837127 remained a statistically significant independent signal (OR = 0.200, P-value = 5.84×10−8). Conclusions These findings suggest rare variation residing on common haplotypes are important contributors to EwS risk. Impact Motivate future targeted sequencing studies for a comprehensive evaluation of low-frequency and rare variation around common EwS susceptibility loci.
CRIS-Team Scopus Importer:2020-09-18

Low incidence of symptomatic osteonecrosis after allogeneic HSCT in children with high-risk or relapsed ALL - results of the ALL-SCT 2003 trial - Kuhlen, Michaela; Bader, Peter; Sauer, Martin; Albert, Michael H.; Gruhn, Bernd; Gungor, Tayfun; Kropshofer, Gabriele; Lang, Peter; Lawitschka, Anita; Metzler, Markus; Pentek, Falk; Rossig, Claudia; et al. (British Journal of Haematology, 2018)
Osteonecrosis (ON) was prospectively assessed in 557 children and adolescents in the Berlin-Frankfurt-Münster Stem Cell Transplantation in children with acute lymphoblastic leukaemia 2003 trial. Median age at haematopoietic stem cell transplantation (HSCT) was 10·3 years (range 0·5-26). Cumulative incidence of symptomatic ON (sON) was 9% at 5 years (standard deviation 1%), median time from HSCT to diagnosis of sON was 12·4 months (range 1-126). Multivariate analysis identified age at HSCT [10-15 years vs. <10 years: hazard ratio (HR) 3·73, P = 0·009; >15 years vs. <10 years: HR 5·46, P = 0·001], diagnosis of sON prior to HSCT and chronic graft-versus-host disease (yes versus no: HR 2·696, P = 0·015) as significant independent risk factors for the development of sON.
EVALuna2:35823

Machine Learning-Supported Diagnosis of Small Blue Round Cell Sarcomas Using Targeted RNA Sequencing. - Schlieben, Lea D.; Carta, Maria Giulia; Moskalev, Evgeny; Stöhr, Robert; Metzler, Markus; Besendörfer, Manuel; Meidenbauer, Norbert; Semrau, Sabine; Janka, Rolf Matthias; Grützmann, Robert; Wiemann, Stefan; Hartmann, Arndt; et al. (Journal of Molecular Diagnostics, 2024)
Small blue round cell sarcomas (SBRCSs) are a heterogeneous group of tumors with overlapping morphologic features but markedly varying prognosis. They are characterized by distinct chromosomal alterations, particularly rearrangements leading to gene fusions, whose detection currently represents the most reliable diagnostic marker. Ewing sarcomas are the most common SBRCSs, defined by gene fusions involving EWSR1 and transcription factors of the ETS family, and the most frequent non-EWSR1-rearranged SBRCSs harbor a CIC rearrangement. Unfortunately, currently the identification of CIC::DUX4 translocation events, the most common CIC rearrangement, is challenging. Here, we present a machine-learning approach to support SBRCS diagnosis that relies on gene expression profiles measured via targeted sequencing. The analyses on a curated cohort of 69 soft-tissue tumors showed markedly distinct expression patterns for SBRCS subgroups. A random forest classifier trained on Ewing sarcoma and CIC-rearranged cases predicted probabilities of being CIC-rearranged >0.9 for CIC-rearranged-like sarcomas and <0.6 for other SBRCSs. Testing on a retrospective cohort of 1335 routine diagnostic cases identified 15 candidate CIC-rearranged tumors with a probability >0.75, all of which were supported by expert histopathologic reassessment. Furthermore, the multigene random forest classifier appeared advantageous over using high ETV4 expression alone, previously proposed as a surrogate to identify CIC rearrangement. Taken together, the expression-based classifier can offer valuable support for SBRCS pathologic diagnosis.
EVALuna2:565265

Macrophage‐like Cells Are Responsive to Titania Nanotube Intertube Spacing—An In Vitro Study - Necula, Madalina Georgiana; Mazare, Anca Valentina; Negrescu, Andreea Mariana; Mitran, Valentina; Özkan, Selda; Trusca, Roxana; Park, Jung; Schmuki, Patrik; Cimpean, Anisoara (International Journal of Molecular Sciences, 2022)
With the introduction of a new interdisciplinary field, osteoimmunology, today, it is well acknowledged that biomaterial‐induced inflammation is modulated by immune cells, primarily macrophages, and can be controlled by nanotopographical cues. Recent studies have investigated the effect of surface properties in modulating the immune reaction, and literature data indicate that various surface cues can dictate both the immune response and bone tissue repair. In this context, the purpose of the present study was to investigate the effects of titanium dioxide nanotube (TNT) interspacing on the response of the macrophage‐like cell line RAW 264.7. The cells were maintained in contact with the surfaces of flat titanium (Ti) and anodic TNTs with an intertube spacing of 20 nm (TNT20) and 80 nm (TNT80), under standard or pro‐inflammatory conditions. The results revealed that nanotube interspacing can influence macrophage response in terms of cell survival and proliferation, cellular morphology and polarization, cytokine/chemokine expression, and foreign body reaction. While the nanostructured topography did not tune the macrophages’ differentiation into osteoclasts, this behavior was significantly reduced as compared to flat Ti surface. Overall, this study provides a new insight into how nanotubes’ morphological features, particularly intertube spacing, could affect macrophage behavior.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Cytokines; Inflammation; Intertube spacing; Macrophage; Osteoclastogenesis; TiO2 nanotubes

Malignant epithelioid peripheral nerve sheath tumor with prominent reticular/microcystic pattern in a child: a low-grade neoplasm with 18-years follow-up - Agaimy, Abbas; Stachel, Daniel; Jüngert, Jörg; Radkow, Tanja; Carbon, Roman; Metzler, Markus; Holter, Wolfgang (Applied Immunohistochemistry & Molecular Morphology, 2014)
Malignant peripheral nerve sheath tumors (MPNSTs) constitute <2% of soft tissue neoplasms in children and display a wide histologic spectrum including low-grade and epithelioid variants, although most are high-grade spindle cell sarcomas. Here, we describe an unusual case of a large retroperitoneal epithelioid MPNST diagnosed in a 7-year-old girl without family history or clinical features of neurofibromatosis type 1. The patient was treated by repeated surgical interventions, polychemotherapy, autologous stem cell transplantation, and irradiation therapy. Over the years, she developed multiple disseminated abdominal recurrences but is currently alive with very slowly progressing disseminated intra-abdominal disease 18 years from initial diagnosis. Histologically, the tumor was composed of medium-sized polygonal and ovoid-to-spindled cells set within a copious myxoid matrix with a prominent reticular and microcystic pattern reminiscent of the recently described reticular/microcystic schwannoma. Immunohistochemistry revealed strong and diffuse expression of S100, CD56, CD57, collagen IV, and neuron-specific enolase, with negativity for perineurial cell markers (claudin-1, epithelial membrane antigen, and glucose transporter-1) and other lineage-specific mesenchymal and epithelial antigens. This unusual variant of low-grade MPNST must be differentiated from a variety of other entities, in particular benign perineurioma, myxoid neurofibroma, and benign reticular/microcystic schwannoma. Confinement of the recurrent disease to the abdominal cavity emphasizes the necessity of primary curative wide excision of this highly recurring but nonmetastasizing low-grade neoplasm.
EVALuna2:6527

Malignant teratoid tumor of the thyroid gland: an aggressive primitive multiphenotypic malignancy showing organotypical elements and frequent DICER1 alterations—is the term “thyroblastoma” more appropriate? - Agaimy, Abbas; Witkowski, Leora; Stöhr, Robert; Cuenca, Joseph Christopher Castillo; González-Muller, Carlos Alberto; Brütting, Alfred; Bährle, Markus; Mantsopoulos, Konstantinos; Amin, Randa M.S.; Hartmann, Arndt; Metzler, Markus; Amr, Samir S.; et al. (Virchows Archiv, 2020)
Primary thyroid teratomas are exceedingly rare. Mature and immature variants recapitulate their gonadal counterparts (predilection for infants/children, triphasic germ layer differentiation, and favorable outcome). On the other hand, the so-called malignant teratomas affect predominantly adults and elderly, are highly aggressive, and, according to a few published cases, harbor DICER1 mutations. We describe three highly aggressive sporadic malignant teratoid thyroid tumors in 2 females (17 and 45 years) and one male (17 years). Histology showed triphasic neoplasms composed of solid nests of small primitive monomorphic cells embedded in a cellular stroma with primitive immature rhabdomyosarcoma-like (2) or pleomorphic sarcoma-like (1) phenotype. The third component was represented by TTF1+/PAX8+ primitive teratoid epithelial tubules reminiscent of primitive thyroid follicles and/or Wilms tumor, admixed with scattered respiratory- or enteric-type tubules, neuroepithelial rosettes, and fetal-type squamoid nests. Foci of cartilage were seen in two cases, but none contained mature organoid adult-type tissue or skin adnexa. SALL4 was expressed in the small cell (2) and stromal (1) component. Other germ cell markers were negative. Molecular testing revealed a known “hotspot” pathogenic DICER1 mutation in two cases. In addition, case 1 had a missense TP53 variant. This type of thyroid malignancy is distinct from genuine teratomas. The immunoprofile suggests primitive thyroid- or branchial cleft-like differentiation. Given that “blastoma” is a well-accepted terminology in the spectrum of DICER1-associated malignancies, the term “thyroblastoma” might be more convenient for these malignant teratoid tumors of the thyroid gland. Relationship of thyroblastoma to the DICER1 syndrome remains to be addressed.
CRIS-Team Scopus Importer:2020-06-16
Keywords: DICER1; Germ cell tumor; Head and neck; Malignant teratoma; Rhabdomyosarcoma; Teratocarcinosarcoma; Thyroblastoma; Thyroid

Management of children and adolescents with chronic myeloid leukemia in blast phase: International pediatric CML expert panel recommendations - Sembill, Stephanie; Ampatzidou, Maria; Chaudhury, Sonali; Dworzak, Michael; Kalwak, Krzysztof; Karow, Axel; Kiani, Alexander; Krumbholz, Manuela; Luesink, Maaike; Naumann-Bartsch, Nora; De Moerloose, Barbara; Osborn, Michael; et al. (Leukemia, 2023)
Treatment of chronic myeloid leukemia has improved significantly with the introduction of tyrosine kinase inhibitors (TKIs), and treatment guidelines based on numerous clinical trials are available for chronic phase disease. However for CML in the blast phase (CML-BP), prognosis remains poor and treatment options are much more limited. The spectrum of treatment strategies for children and adolescents with CML-BP has largely evolved empirically and includes treatment principles derived from adult CML-BP and pediatric acute leukemia. Given this heterogeneity of treatment approaches, we formed an international panel of pediatric CML experts to develop recommendations for consistent therapy in children and adolescents with this high-risk disease based on the current literature and national standards. Recommendations include detailed information on initial diagnosis and treatment monitoring, differentiation from Philadelphia-positive acute leukemia, subtype-specific selection of induction therapy, and combination with tyrosine kinase inhibitors. Given that allogeneic hematopoietic stem cell transplantation currently remains the primary curative intervention for CML-BP, we also provide recommendations for the timing of transplantation, donor and graft selection, selection of a conditioning regimen and prophylaxis for graft-versus-host disease, post-transplant TKI therapy, and management of molecular relapse. Management according to the treatment recommendations presented here is intended to provide the basis for the design of future prospective clinical trials to improve outcomes for this challenging disease.
CRIS-Team WoS Importer:2023-02-24

Management of children and adolescents with chronic myeloid leukemia in chronic phase: International pediatric chronic myeloid leukemia expert panel recommendations: CHRONIC MYELOGENOUS LEUKEMIA - Millot, Frédéric; Ampatzidou, Mirella; Moulik, Nirmalya Roy; Tewari, Sanjay; Elhaddad, Alaa; Hammad, Mahmoud; Pichler, Herbert; Lion, Thomas; Tragiannidis, Athanasios; Shima, Haruko; An, Wenbin; Yang, Wenyu; et al. (Leukemia, 2025)
The treatment strategy for children and adolescents with chronic myeloid leukemia in the chronic phase (CML-CP) has evolved from allogeneic hematopoietic stem cell transplantation (HSCT) to tyrosine kinase inhibitors (TKIs). With the advent of next-generation TKIs and new targeted therapies in the CML field, an international pediatric CML expert panel provides recommendations based on the medical literature (including previous pediatric guidelines), national standards, and treatment principles used in adults with CML-CP. Recommendations include diagnosis of the disease and details on managing the initial steps of care of children and adolescents with newly diagnosed CML-CP, including complications such as leukostasis. The treatment recommendations are based on the initiation of therapy with a first- or second-generation TKI according to the allocated European Treatment and Outcome Study (EUTOS) long-term survival score risk group of the patient. The subsequent steps are based on the results of recommended monitoring which can justify a switch to another TKI or a drug in development if there is resistance or toxicity. The panel also provides recommendations regarding the discontinuation criteria for TKIs in children and adolescents in sustained deep molecular response. Allogeneic HSCT is not recommended as the first-line of treatment for children with CML-CP but is to be considered in case of progression to the advanced phase or failure of several lines of treatment. The present treatment and management recommendations are intended to provide advice to clinicians in view of optimizing the care and the outcome of children and adolescents with CML-CP.
CRIS-Team Scopus Importer:2025-03-21

Manipulation of medicinal products for oral administration to paediatric patients at a german university hospital: An observational study - Zahn, Julia; Hörning, André; Trollmann, Regina; Rascher, Wolfgang; Neubert, Antje (Pharmaceutics, 2020)
Pharmacotherapy in children requires medicinal products in age-appropriate dosage forms and flexible dose strengths. Healthcare professionals often encounter a lack of licensed and commercially available formulations, which results in the need for manipulation. This study aimed to investigate the nature, frequency and preventability of the manipulation of medicinal products before oral drug administration to paediatric inpatients in Germany. A prospective, direct observational approach was used. Two thousand and three medication preparation processes (MPP) in 193 patients were included in the analysis. Medicines were manipulated in 37% of oral administrations, affecting 57% of the patients. The percentage of manipulations was highest in infants/toddlers (42%) and lowest in adolescents (31%). Antiepileptics were most frequently manipulated (27%), followed by vitamins (20%) and drugs for acid-related disorders (13%). Fifty-six per cent of all manipulations were off-label. In 71% of these, no alternative appropriate medicinal product was commercially available. These results demonstrate that the manipulation of medicinal products before oral administration is common in paediatric wards in Germany. About half of the manipulations were off-label, indicating that no suitable formulation was available. Evidence-based guidelines for manipulations are required, with the overall aim of improving the safety of paediatric drug therapy.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Age-appropriate formulation; Drug manipulation; Hospital; Off-label use/manipulation; Oral drug administration; Paediatrics

Manufacturer switch of anti-seizure drugs may not increase the risk of seizure recurrence in Children: A nationwide study of prescription data in Germany - Lang, Johannes; Kostev, Karel; Reindl, Caroline; Müller, Tamara; Stritzelberger, Jenny; Gollwitzer, Stephanie; Westermayer, Vivien; Trollmann, Regina; Hamer, Hajo (Epilepsy & Behavior, 2021)
Objective: Several publications on the exchangeability of antiepileptic drugs in clinical settings revealed an increased risk for seizure recurrence after changing the manufacturer of anti-seizure drugs (ASD) in adults, possibly due to a decline of adherence. It is unclear whether this holds true in children and adolescents. Methods: Patient data of children and adolescents (<18 years) were collected anonymously from 236 German pediatricians and pediatric neurologists between January 2011 and December 2018 using the IMS® Disease Analyzer database (IQVIA, Frankfurt, Germany). Patients with epilepsy were included if at least 2 prescriptions within 360 days and 1 within 180 days prior to the index date were available. The cohort was separated into a seizure group and seizure-free controls. Both groups were matched 1:1 according to age, gender, insurance status, and treating pediatrician. The risk for seizure recurrence after a manufacturer switch of the same ASD at the last prescription before the index date was analyzed using a multivariate regression model. Results: A total of 678 children and adolescents with epilepsy were included (each group: n = 339; age: 9.6 ± 4.4 years). Comparing both groups, the risk for seizures recurrence was not increased after a manufacturer switch had occurred. Albeit changes during the last prescription before the index date had occurred more often in the seizure-free group, neither change of branded and generic products nor substances reached significance. Only change of ASD strength showed a significantly reduced odds ratio for seizures (OR 0.40, 95% CI 0.24–0.65, p < 0.001). Significance: In contrast to the available evidence in adults, changing the manufacturer did not appear to increase the risk for seizure recurrence in previously seizure-free children and adolescents with epilepsy.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Anti-seizure drugs; Manufacturer changes; Relapse seizures

MAP2K1-MUTATED ECD/RDD-OVERLAP NON-LANGERHANS CELL HISTIOCYTOSIS RESPONDING TO COBIMETINIB - Classen, Carl Friedrich; Leyh, Jörg; Rümmele, Petra; Rosenwald, Andreas; Metzler, Markus (PEDIATRIC BLOOD & CANCER, 2021)
CRIS-Team WoS Importer:2020-12-18

MAP4-dependent regulation of microtubule formation affects centrosome, cilia, and golgi architecture as a central mechanism in growth regulation - Zahnleiter, Diana; Hauer, Nadine; Keßler, Kristin; Uebe, Steffen; Sugano, Yuya; Neuhauss, Stephan C. F.; Gießl, Andreas; Ekici, Arif Bülent; Blessing, Holger; Sticht, Heinrich; Dörr, Helmuth-Günther; Reis, André; et al. (Human Mutation, 2015)
Numerous genes are involved in human growth regulation. Recently, autosomal-recessive inherited variants in centrosomal proteins have been identified in Seckel syndrome, primary microcephaly, or microcephalic osteodysplastic primary dwarfism. Common hallmarks of these syndromic forms are severe short stature and microcephaly. In a consanguineous family with two affected children with severe growth retardation and normocephaly, we used homozygosity mapping and next-generation sequencing to identify a homozygous MAP4 variant. MAP4 is a major protein for microtubule assembly during mitosis. High-expression levels in the somite boundaries of zebrafish suggested a role in growth and body segment patterning. The identified variant affects binding sites of kinases necessary for dynamic instability of microtubule formation. We found centrosome amplifications in mitotic fibroblast cells in vivo and in vitro. These numeric centrosomal aberrations were also present during interphase resulting in aberrant ciliogenesis. Furthermore, affected cells showed a dysfunction of the microtubule-dependent assembly of the Golgi apparatus, indicated by a significant lack of compactness of Golgi membranes. These observations demonstrated that MAP4 mutations contribute to the clinical spectrum of centrosomal defects and confirmed the complex role of a centrosomal protein in centrosomal, ciliary, and Golgi regulation associated with severe short stature.
EVALuna2:9244

Maternal SARS-CoV-2 infection during pregnancy: possible impact on the infant - Morhart, Patrick; Mardin, Christian; Rauh, Manfred; Juengert, Joerg; Hammersen, Johanna; Kehl, Sven; Schuh, Wolfgang; Maier-Wohlfart, Sigrun; Hermes, Katharina; Neubert, Antje; Schneider, Michael; Hein, Alexander; et al. (European Journal of Pediatrics, 2021)
The risk and potential consequences of mother-to-child transmission of severe acute respiratory syndrome-coronavirus type 2 (SARS-CoV-2) during pregnancy are still a matter of debate. We studied the impact of SARS-CoV-2 infection on 56 complete households, including 27 newborns whose mothers were pregnant when exposed to the virus. Two PCR-confirmed perinatal SARS-CoV-2 transmissions with mild symptoms in affected neonates were recorded. In addition, we observed a severe eye malformation (unilateral microphthalmia, optic nerve hypoplasia, and congenital retinopathy) associated with maternal SARS-CoV-2 infection in weeks 5 and 6 of embryonic development. This embryopathy could not be explained by other infectious agents, genetic factors, drug use, or maternal disease during pregnancy. Eight other women with a history of SARS-CoV-2 infection prior to gestational week 12, however, delivered healthy infants. Conclusion: The repeated occurrence of mother-to-child transmission in our cohort with risks that remain incompletely understood, such as long-term effects and the possibility of an embryopathy, should sensitize researchers and stimulate further studies as well as support COVID-19 vaccination recommendations for pregnant women. Trial registration number: NCT04741412. Date of registration: November 18, 2020What is Known:•Materno-fetal transmission of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) during pregnancy has rarely been reported so far, but was demonstrated in isolated cases.What is New:•In a study of complete households with documented SARS-CoV-2 infection, including a cohort of pregnant women, we observed perinatal coronavirus transmission at a higher frequency than expected.•We also describe a newborn boy with an eye malformation reminiscent of rubella embryopathy but associated with early gestation SARS-CoV-2 infection of his mother.•A coronavirus-related embryopathy, reported here for the first time, is a finding that requires further investigation.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Case report; Coronavirus; Embryopathy; Malformation; Materno-fetal transmission

Measurement of amniotic fluid steroids of midgestation via LC-MS/MS - Fahlbusch, Fabian B.; Heussner, Kirsten; Schmid, Matthias; Schild, Ralf; Rübner, Matthias; Hübner, Hanna; Rascher, Wolfgang; Dörr, Helmuth-Günther; Rauh, Manfred (Journal of Steroid Biochemistry and Molecular Biology, 2015)
Analysis of steroids by mass spectrometry (MS) has evolved into a reliable tool for the simultaneous detection of multiple steroids. As amniotic fluid (AF) and fetal serum composition of early pregnancy are closely related, the analysis of AF can yield information on the physiological status of the developing fetus. We evaluated the use of liquid-chromatography tandem mass spectrometry (LC-MS/MS) for AF steroid analysis, including the analysis of its sensitivity and accuracy for gender verification in healthy subjects.AF of 78 male and 94 female healthy newborns was analyzed by LC-MS/MS at 16 weeks of gestation. The levels of androstenedione, corticosterone, cortisol, cortisone, deoxycorticosterone, 11-deoxycortisol, dehydroepiandrosterone (DHEA), dehydroepiandrosterone-sulfate (DHEA-S), 17-hydroxyprogesterone, progesterone (17-OHP) and testosterone were measured. Steroid levels were compared to RIA and GC-MS levels of midgestation from the literature. Cross-validated logistic regression was used to obtain statistical predictions of gender at birth from testosterone and the above steroids.LC-MS/MS analysis of AF steroids yielded comparable results with published GC-MS data. Gender specific differences were found for androstenedione and testosterone concentrations with higher levels in the male fetus. In contrast to published RIA data no gender specific differences were observed for 17-hydroxyprogesterone and dehydroepiandrosterone AF concentrations. Testosterone concentrations yielded highly accurate predictions for male gender at birth. Additional analysis of further steroids did neither increase the accuracy, sensitivity nor specificity of this prediction. The estimated optimal cut-off value for amniotic testosterone level was 0.074 ?g/L for healthy male newborns.LC-MS/MS is a reliable method for the determination of steroids in amniotic fluid. The determination of testosterone in amniotic fluid by LC-MS/MS in early pregnancy of healthy subjects can be used to offer a reliable prediction of fetal gender at birth.
EVALuna2:17444

MECOM-associated syndrome: a heterogeneous inherited bone marrow failure syndrome with amegakaryocytic thrombocytopenia - Germeshausen, Manuela; Ancliff, Phil; Estrada, Jaime; Metzler, Markus; Ponstingl, Eva; Ruetschle, Horst; Schwabe, Dirk; Scott, Richard H.; Unal, Sule; Wawer, Angela; Zeller, Bernward; Ballmaier, Matthias (Blood Advances, 2018)
Heterozygous mutations in MECOM (MDS1 and EVI1 complex locus) have been reported to be causative of a rare association of congenital amegakaryocytic thrombocytopenia and radioulnar synostosis. Here we report on 12 patients with congenital hypomegakaryocytic thrombocytopenia caused by MECOM mutations (including 10 novel mutations). The mutations affected different functional domains of the EVI1 protein. The spectrum of phenotypes was much broader than initially reported for the first 3 patients; we found familial as well as sporadic cases, and the clinical spectrum ranged from isolated radioulnar synostosis with no or mild hematological involvement to severe bone marrow failure without obvious skeletal abnormality. The clinical picture included radioulnar synostosis, bone marrow failure, clinodactyly, cardiac and renal malformations, B-cell deficiency, and presenile hearing loss. No single clinical manifestation was detected in all patients affected by MECOM mutations. Radioulnar synostosis and B-cell deficiency were observed only in patients with mutations affecting a short region in the C-terminal zinc finger domain of EVI1. We propose the term MECOM-associated syndrome for this heterogeneous hereditary disease and inclusion of MECOM sequencing in the diagnostic workup of congenital bone marrow failure.
EVALuna2:35827

Medication safety with oral antitumour therapeutics in paediatrics (youngAMBORA): A mixed-methods approach towards a tailored care program. - Lensker, Phyllis; Cuba, Lisa; Geßner, Katja; Fromm, Martin; Dörje, Frank; Metzler, Markus (PLoS ONE, 2024)
OBJECTIVE: Oral antitumour therapeutics (OAT) are increasingly used due to improvements in outcomes and their convenient application. However, complex intake regimens pose several challenges. The randomised AMBORA trial (Medication Safety With Oral Antitumour Drugs) demonstrated highly positive outcomes of a clinical pharmacological/pharmaceutical care program for adults treated with numerous OAT, but comparable concepts in paediatrics are lacking so far. METHODS: We used a parallel mixed-methods approach to develop a tailored pharmacological/pharmaceutical care program for OAT in paediatrics (youngAMBORA). We combined a quantitative analysis of tumour entities and used OAT in a paediatric cancer centre with a qualitative survey for patients, caregivers, and healthcare professionals to identify particular demands and educational needs (e.g., application problems, side effects). RESULTS: Leukaemia (77/315) and antimetabolites (95/151) were the most frequently observed entity and OAT, respectively. Of 22 surveyed patients, 81.8% wanted to be involved in oral medication education. Compared to caregivers, significantly more healthcare professionals graded the three most common application problems to be challenging ('Smell/taste': 32/36 vs. 23/42, p = 0.001; 'Refusal of intake': 31/36 vs. 16/42, p<0.001; 'Swallowing problems': 28/36 vs. 21/42, p = 0.011). We identified nine relevant side effects, of which two ('Skin dryness', 'Taste changes') were not included in 15 previously published core side effects of the Common Terminology Criteria of Adverse Events (CTCAE) item library. CONCLUSION: Based on the present findings, the tailored youngAMBORA care program will include: 1) counselling sessions for classic and targeted OAT, 2) child-friendly support with drug application, and 3) systematic evaluation of 17 relevant side effects from patients' and caregivers' points of view including age-appropriate information material.
EVALuna2:583325

Memorandum on the use of information technology to improve medication safety - Ammenwerth, E.; Aly, A. -F.; Bürkle, Thomas; Christ, P.; Dormann, H.; Friesdorf, W.; Haas, C.; Haefeli, W. E.; Jeske, M.; Kaltschmidt, J.; Menges, K.; Moeller, H.; et al. (Methods of Information in Medicine, 2014)
Information technology in health care has a clear potential to improve the quality and efficiency of health care, especially in the area of medication processes. On the other hand, existing studies show possible adverse effects on patient safety when IT for medication-related processes is developed, introduced or used inappropriately.To summarize definitions and observations on IT usage in pharmacotherapy and to derive recommendations and future research priorities for decision makers and domain experts.This memorandum was developed in a consensus-based iterative process that included workshops and e-mail discussions among 21 experts coordinated by the Drug Information Systems Working Group of the German Society for Medical Informatics, Biometry and Epidemiology (GMDS).The recommendations address, among other things, a stepwise and comprehensive strategy for IT usage in medication processes, the integration of contextual information for alert generation, the involvement of patients, the semantic integration of information resources, usability and adaptability of IT solutions, and the need for their continuous evaluation.Information technology can help to improve medication safety. However, challenges remain regarding access to information, quality of information, and measurable benefits.
EVALuna2:131

Metabolic control during the first two years of the COVID-19 pandemic in pediatric patients with type 1 diabetes: results from the German DPV initiative - Hammersen, Johanna; Tittel, Sascha R.; Khodaverdi, Semik; Reschke, Felix; Flury, Monika; Menzel, Ulrike; Mönkemöller, Kirsten; Meissner, Thomas; Karges, Beate; Holl, Reinhard W. (Acta Diabetologica, 2023)
Aim: To assess effects of the SARS-CoV2 pandemic on metabolic control in youth with type 1 diabetes (T1D) in Germany in a population-based analysis. Methods: Data from 33,372 pediatric T1D patients from the Diabetes Prospective Follow-up (DPV) registry, with face-to-face visits or telemedicine contacts in the years 2019–2021, were available. Datasets from eight time periods between March 15, 2020, and December 31, 2021, according to SARS-CoV2 incidence waves, were compared to those from five control time periods. Parameters of metabolic control were assessed with adjustment for sex, age, diabetes duration, and repeated measurements. Laboratory-measured HbA1c values and those estimated from CGM were aggregated into a combined glucose indicator (CGI). Results: There was no clinically relevant difference in metabolic control between pandemic and control time periods with adjusted CGI values ranging from 7.61% [7.60–7.63] (mean [95% confidence interval (CI)]) in the third quarter of 2019 to 7.83% [7.82–7.85] in the time period from January 1 to March 15 2020, in the other control periods, and during the pandemic, CGI values lay between these values. BMI-SDS rose during the pandemic from 0.29 [0.28–0.30] (mean [95% CI]) in the third quarter of 2019 to 0.40 [0.39–0.41] during the fourth wave. Adjusted insulin dose rose during the pandemic. Event rates for hypoglycemic coma and diabetic ketoacidosis remained unchanged. Conclusions: We found no clinically relevant change of glycemic control or incidence of acute diabetes complications during the pandemic. The observed BMI increase may represent an important health risk for youth with T1D.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Lockdown; Metabolic control; Pediatric diabetes; SARS-CoV2 pandemic

Metamizole Use in Children: Analysis of Drug Utilisation and Adverse Drug Reactions at a German University Hospital between 2015 and 2020 - Zahn, Julia; Eberl, Sonja; Rödle, Wolfgang; Rascher, Wolfgang; Neubert, Antje; Toni, Irmgard (Paediatric Drugs, 2021)
Background: Metamizole use is controversially discussed due to its potentially serious adverse drug reactions (ADRs). In Germany, however, it remains a popular analgesic and antipyretic drug. Objective: The aim of this study was to discuss the safety profile of metamizole in children by analysing the inpatient prescription patterns and presenting the metamizole-related ADRs at a paediatric hospital between 2015 and 2020. Methods: Metamizole utilisation data were retrospectively analysed from electronic medical records. ADRs were prospectively recorded via the hospital’s stimulated reporting system and analysed accordingly. Patients aged < 18 years admitted to one of the general wards of the department of paediatrics and adolescent medicine of a German university hospital between June 2015 and May 2020 who received at least one drug therapy within their inpatient stay were included in the analysis. Causality of ADRs was rated according to the World Health Organisation causality assessment. Results: In 31.7% (3759/11,857) of the inpatient stays of 7809 patients, metamizole was administered. Metamizole exposure was highest in adolescents (37.9%) and lowest in newborns (9.9%). Overall, metamizole was administered parenterally in about 90%. Three cases of agranulocytosis, one allergic shock and one rash with possible or higher causality to metamizole treatment were reported. Three of these occurred prior to hospitalisation. All patients recovered without remaining harm. Discussion: Metamizole is commonly used in paediatric inpatients in Germany. Serious ADRs occur but rarely. Continuous monitoring of drug therapy through, for example, stimulated reporting systems ensures that serious ADRs are detected, and appropriate interventions can be introduced.
CRIS-Team Scopus Importer:2021-12-17

Methods for the Administration of EDAR Pathway Modulators in Mice - Schuepbach-Mallepell, Sonia; Kowalczyk-Quintas, Christine; Dick, Angela; Eslami, Mahya; Vigolo, Michele; Headon, Denis J.; Cheeseman, Michael; Schneider, Holm; Schneider, Pascal (The TNF Superfamily, 2021)
Genetic deficiency of ectodysplasin A (EDA) causes X-linked hypohidrotic ectodermal dysplasia, a congenital condition characterized by the absence or abnormal formation of sweat glands, teeth, and several skin appendages. Stimulation of the EDA receptor (EDAR) with agonists in the form of recombinant EDA or anti-EDAR antibodies can compensate for the absence of Eda in a mouse model of Eda deficiency, provided that agonists are administered in a timely manner during fetal development. Here we provide detailed protocols for the administration of EDAR agonists or antagonists, or other proteins, by the intravenous, intraperitoneal, and intra-amniotic routes as well as protocols to collect blood, to visualize sweat gland function, and to prepare skulls in mice.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Amniotic fluid; Ectodermal dysplasia; EDAR signaling; Protein replacement therapy; Route of administration

Miscarriages in families with an offspring that have classic congenital adrenal hyperplasia and 21-hydroxylase deficiency - Dörr, Helmuth-Günther; Hess, Johannes; Penger, Theresa; Marx, Martin; Oppelt, Patricia (BMC Pregnancy and Childbirth, 2018)
BACKGROUND: The most common form of congenital adrenal hyperplasia is 21-hydroxylase deficiency (CAH). Both men and women with classic CAH have lower fertility rates than the general population, and an increased rate of miscarriages has been reported in affected women. There are no data on the incidence rate of miscarriages in families with an offspring that have classic CAH. METHODS: We studied families with a history of classic CAH. The families came from different parts of Germany and attended the annual meeting of the German CAH support group for parents and patients which was held in Hamburg in September 2014. The data was collected anonymously by a paper-based questionnaire which was completed by the families at home. The families also accepted the responsibility to address this question to their siblings. In all, the data of 50 families with at least one child with classic CAH, and the data of 164 parental siblings were available for evaluation. Miscarriage rates were calculated in relation to the reported pregnancies. RESULTS: Twenty-two miscarriages were reported from 19 families. At least one miscarriage occurred in 38% of the families, three families experienced two miscarriages and 16 families had one miscarriage each. The mean miscarriage rate was 15.8%. The heterozygous mothers had a total of 90 siblings (41 m, 49 f), while 74 siblings (33 m, 41 f) were reported from the heterozygous fathers. The miscarriage rate was 10.1% in the families of the mothers` siblings, and 11.4% in the families of the fathers` siblings. The genotype was known in all parents that have an offspring with classic CAH, but not defined in 82% of the maternal siblings, and in 86% of the paternal siblings. No child with classic CAH has been diagnosed in any of the sibling's families to date. CONCLUSION: Our data show that the miscarriage rate in German families with a child with classic CAH is not elevated.
EVALuna2:35501

Mixture density networks for the indirect estimation of reference intervals - Hepp, Tobias; Zierk, Jakob; Rauh, Manfred; Metzler, Markus; Seitz, Sarem (BMC Bioinformatics, 2022)
Background: Reference intervals represent the expected range of physiological test results in a healthy population and are essential to support medical decision making. Particularly in the context of pediatric reference intervals, where recruitment regulations make prospective studies challenging to conduct, indirect estimation strategies are becoming increasingly important. Established indirect methods enable robust identification of the distribution of “healthy” samples from laboratory databases, which include unlabeled pathologic cases, but are currently severely limited when adjusting for essential patient characteristics such as age. Here, we propose the use of mixture density networks (MDN) to overcome this problem and model all parameters of the mixture distribution in a single step. Results: Estimated reference intervals from varying settings with simulated data demonstrate the ability to accurately estimate latent distributions from unlabeled data using different implementations of MDNs. Comparing the performance with alternative estimation approaches further highlights the importance of modeling the mixture component weights as a function of the input in order to avoid biased estimates for all other parameters and the resulting reference intervals. We also provide a strategy to generate partially customized starting weights to improve proper identification of the latent components. Finally, the application on real-world hemoglobin samples provides results in line with current gold standard approaches, but also suggests further investigations with respect to adequate regularization strategies in order to prevent overfitting the data. Conclusions: Mixture density networks provide a promising approach capable of extracting the distribution of healthy samples from unlabeled laboratory databases while simultaneously and explicitly estimating all parameters and component weights as non-linear functions of the covariate(s), thereby allowing the estimation of age-dependent reference intervals in a single step. Further studies on model regularization and asymmetric component distributions are warranted to consolidate our findings and expand the scope of applications.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Distributional regression; Latent class regression; Mixture density networks; Reference intervals

Model-Based Simulation of Maintenance Therapy of Childhood Acute Lymphoblastic Leukemia - Jost, Felix; Zierk, Jakob; Le, Thuy T.T.; Raupach, Thomas; Rauh, Manfred; Suttorp, Meinolf; Stanulla, Martin; Metzler, Markus; Sager, Sebastian (Frontiers in Physiology, 2020)
Acute lymphoblastic leukemia is the most common malignancy in childhood. Successful treatment requires initial high-intensity chemotherapy, followed by low-intensity oral maintenance therapy with oral 6-mercaptopurine (6MP) and methotrexate (MTX) until 2–3 years after disease onset. However, intra- and inter-individual variability in the pharmacokinetics (PK) and pharmacodynamics (PD) of 6MP and MTX make it challenging to balance the desired antileukemic effects with undesired excessive myelosuppression during maintenance therapy. A model to simulate the dynamics of different cell types, especially neutrophils, would be a valuable contribution to improving treatment protocols (6MP and MTX dosing regimens) and a further step to understanding the heterogeneity in treatment efficacy and toxicity. We applied and modified a recently developed semi-mechanistic PK/PD model to neutrophils and analyzed their behavior using a non-linear mixed-effects modeling approach and clinical data obtained from 116 patients. The PK model of 6MP influenced the accuracy of absolute neutrophil count (ANC) predictions, whereas the PD effect of MTX did not. Predictions based on ANC were more accurate than those based on white blood cell counts. Using the new cross-validated mathematical model, simulations of different treatment protocols showed a linear dose-effect relationship and reduced ANC variability for constant dosages. Advanced modeling allows the identification of optimized control criteria and the weighting of specific influencing factors for protocol design and individually adapted therapy to exploit the optimal effect of maintenance therapy on survival.
CRIS-Team Scopus Importer:2020-04-14
Keywords: 6-mercaptopurine; childhood acute lymphoblastic leukemia; maintenance therapy; methotrexate; neutropenia; non-linear mixed-effects modeling; population pharmacokinetics/pharmacodynamics

Modelling human lower urinary tract malformations in zebrafish - Kolvenbach, Caroline M.; Dworschak, Gabriel C.; Rieke, Johanna M.; Woolf, Adrian S.; Reutter, Heiko Martin; Odermatt, Benjamin; Hilger, Alina Christine (Molecular and Cellular Pediatrics, 2023)
Advances in molecular biology are improving our understanding of the genetic causes underlying human congenital lower urinary tract (i.e., bladder and urethral) malformations. This has recently led to the identification of the first disease-causing variants in the gene BNC2 for isolated lower urinary tract anatomical obstruction (LUTO), and of WNT3 and SLC20A1 as genes implicated in the pathogenesis of the group of conditions called bladder-exstrophy-epispadias complex (BEEC). Implicating candidate genes from human genetic data requires evidence of their influence on lower urinary tract development and evidence of the found genetic variants’ pathogenicity. The zebrafish (Danio rerio) has many advantages for use as a vertebrate model organism for the lower urinary tract. Rapid reproduction with numerous offspring, comparable anatomical kidney and lower urinary tract homology, and easy genetic manipulability by Morpholino®-based knockdown or CRISPR/Cas editing are among its advantages. In addition, established marker staining for well-known molecules involved in urinary tract development using whole-mount in situ hybridization (WISH) and the usage of transgenic lines expressing fluorescent protein under a tissue-specific promoter allow easy visualization of phenotypic abnormalities of genetically modified zebrafish. Assays to examine the functionality of the excretory organs can also be modeled in vivo with the zebrafish. The approach of using these multiple techniques in zebrafish not only enables rapid and efficient investigation of candidate genes for lower urinary tract malformations derived from human data, but also cautiously allows transferability of causality from a non-mammalian vertebrate to humans.
CRIS-Team Scopus Importer:2023-04-14

Models for the marrow: A comprehensive review of AI-based cell classification methods and malignancy detection in bone marrow aspirate smears. - Ghete, Tabita; Kock, Farina; Pontones, Martina; Pfrang, David; Westphal, Max; Höfener, Henning; Metzler, Markus (HemaSphere, 2024)
Given the high prevalence of artificial intelligence (AI) research in medicine, the development of deep learning (DL) algorithms based on image recognition, such as the analysis of bone marrow aspirate (BMA) smears, is rapidly increasing in the field of hematology and oncology. The models are trained to identify the optimal regions of the BMA smear for differential cell count and subsequently detect and classify a number of cell types, which can ultimately be utilized for diagnostic purposes. Moreover, AI is capable of identifying genetic mutations phenotypically. This pipeline has the potential to offer an accurate and rapid preliminary analysis of the bone marrow in the clinical routine. However, the intrinsic complexity of hematological diseases presents several challenges for the automatic morphological assessment. To ensure general applicability across multiple medical centers and to deliver high accuracy on prospective clinical data, AI models would require highly heterogeneous training datasets. This review presents a systematic analysis of models for cell classification and detection of hematological malignancies published in the last 5 years (2019-2024). It provides insight into the challenges and opportunities of these DL-assisted tasks.
EVALuna2:583328

Molecular Composition of Genomic TMPRSS2-ERG Rearrangements in Prostate Cancer - Krumbholz, Manuela; Agaimy, Abbas; Stöhr, Robert; Burger, Maximilian; Wach, Sven; Taubert, Helge; Wullich, Bernd; Hartmann, Arndt; Metzler, Markus (Disease Markers, 2019)
There is increasing interest in the use of cell-free circulating tumor DNA (ctDNA) as a serum marker for therapy assessment in prostate cancer patients. Prostate cancer is characterized by relatively low numbers of mutations, and, in contrast to many other common epithelial cancers, commercially available single nucleotide mutation assays for quantification of ctDNA are insufficient for therapy assessment in this disease. However, prostate cancer shares some similarity with translocation-affected mesenchymal tumors (e.g., leukemia and Ewing sarcoma), which are common in pediatric oncology, where chromosomal translocations are used as biomarkers for quantification of the tumor burden. Approximately 50% of prostate cancers carry a chromosomal translocation resulting in generation of the TMPRSS2-ERG fusion gene, which is unique to the tumor cells of each individual patient because of variability in the fusion breakpoint sites. In the present study, we examined the structural preconditions for TMPRSS2-ERG fusion sites in comparison with mesenchymal tumors in pediatric patients to determine whether the sequence composition is suitable for the establishment of tumor-specific quantification assays in prostate cancer patients. Genomic repeat elements represent potential obstacles to establishment of quantification assays, and we found similar proportions of repeat elements at fusion sites in prostate cancer to those reported for mesenchymal tumors, where genomic fusion sequences are established as biomarkers. Our data support the development of the TMPRSS2-ERG fusion gene as a noninvasive tumor marker for therapy assessment, risk stratification, and relapse detection to improve personalized therapy strategies for patients with prostate cancer.
CRIS-Team WoS Importer:2020-01-07

Molecular Pathway-Based Classification of Ectodermal Dysplasias: First Five-Yearly Update - Peschel, Nicolai; Wright, John T.; Koster, Maranke I.; Clarke, Angus J.; Tadini, Gianluca; Fete, Mary; Hadj-Rabia, Smail; Sybert, Virginia P.; Norderyd, Johanna; Maier-Wohlfart, Sigrun; Fete, Timothy J.; Pagnan, Nina; et al. (Genes, 2022)
To keep pace with the rapid advancements in molecular genetics and rare diseases research, we have updated the list of ectodermal dysplasias based on the latest classification approach that was adopted in 2017 by an international panel of experts. For this purpose, we searched the databases PubMed and OMIM for the term "ectodermal dysplasia", referring mainly to changes in the last 5 years. We also tried to obtain information about those diseases on which the last scientific report appeared more than 15 years ago by contacting the authors of the most recent publication. A group of experts, composed of researchers who attended the 8th International Conference on Ectodermal Dysplasias and additional members of the previous classification panel, reviewed the proposed amendments and agreed on a final table listing all 49 currently known ectodermal dysplasias for which the molecular genetic basis has been clarified, including 15 new entities. A newly reported ectodermal dysplasia, linked to the gene LRP6, is described here in more detail. These ectodermal dysplasias, in the strict sense, should be distinguished from syndromes with features of ectodermal dysplasia that are related to genes extraneous to the currently known pathways involved in ectodermal development. The latter group consists of 34 syndromes which had been placed on the previous list of ectodermal dysplasias, but most if not all of them could actually be classified elsewhere. This update should streamline the classification of ectodermal dysplasias, provide guidance to the correct diagnosis of rare disease entities, and facilitate the identification of individuals who could benefit from novel treatment options.
CRIS-Team WoS Importer:2023-01-06

Molecular Therapies - Schneider, Holm; Schneider, Pascal (Springer Nature, 2025)
This chapter describes the development of molecular therapies for X-linked hypohidrotic ectodermal dysplasia (XLHED), the most common ectodermal dysplasia syndrome, and for the cutaneous and ocular manifestations of p63-associated syndromes. Large parts of the text are based on the following previously published journal article by Holm Schneider: “Ectodermal dysplasias: New perspectives on the treatment of so far immedicable genetic disorders”, Front Genet. 13:1000744, doi: 10.3389/fgene.2022.1000744; available under the terms of the Creative Commons Attribution License (CC BY).
CRIS-Team Scopus Importer:2025-05-02
Keywords: Ectodysplasin A; Molecular therapy; Neonatal Fc receptor; P63 PRIMA-1MET

Molekulare Tumortherapie: Phase-I/II-Netzwerkstruktur der Gesellschaft für Pädiatrische Onkologie und Hämatologie - Nesper-Brock, Martina; Metzler, Markus; Wotschofsky, Zofia; Reinhardt, Dirk; Fischer, Matthias; Rutkowski, Stefan; Kratz, Christian; Thorwarth, Anne; Graf Einsiedel, Hagen; Schrappe, Martin; Mauz-Körholz, Christine; Witt, Olaf (Onkologe, 2021)
Background: To enable the rapid and efficient implementation of early clinical trials for pediatric patients and provide comprehensive access to novel treatment options for pediatric relapse or high-risk patients, five regional phase I/II trial networks have been established under the auspices of the Society for Pediatric Oncology and Hematology (GPOH). The network structure secures, bundles and organizes required competencies and resources and has established processes to optimize operational trial efficiency. The INFORM study is a population-based molecular diagnostic study for children and adolescents with recurrent cancer in Germany and 11 other countries. Preliminary data show that precision medicine in pediatric oncology is possible in an international multicenter setting, provides clinical benefit for subgroups of patients and helps to identify hereditary predispositions, to refine diagnoses and to match patients in suitable phase I/II clinical trials. Conclusions: The portfolio of innovative biomarker driven phase I/II clinical trials for children and adolescents with recurrent tumor diseases in Germany is currently limited. Therefore, the development of innovative, targeted therapy concepts and combination therapies is an important task in the coming years.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Clinical trial; phase I as topic; Clinical trial; phase II as topic; Molecular diagnostic techniques; Molecular targeted therapy; Precision medicine

Monitoring spinal muscular atrophy with three-dimensional optoacoustic imaging - Nedoschill, Emmanuel; Wagner, Alexandra L.; Danko, Vera; Bühler, Adrian; Raming, Roman; Jüngert, Jörg M.; Neurath, Markus; Waldner, Maximilian; Rother, Ulrich; Wölfle, Joachim; Trollmann, Regina; Knieling, Ferdinand; et al. (Med, 2024)
Background: Spinal muscular atrophy is a progressive neuromuscular disorder and among the most frequent genetic causes of infant mortality. While recent advancements in gene therapy provide the potential to ameliorate the disease severity, there is currently no modality in clinical use to visualize dynamic pathophysiological changes in disease progression and regression after therapy. Methods: In this prospective diagnostic clinical study, ten pediatric patients with spinal muscular atrophy and ten age- and sex-matched controls have been examined with three-dimensional optoacoustic imaging and clinical standard examinations to compare the spectral profile of muscle tissue and correlate it with motor function (ClinicalTrials.gov: NCT04115475). Findings: We observed a reduced optoacoustic signal in muscle tissue of pediatric patients with spinal muscular atrophy. The reduction in signal intensity correlated with disease severity as assessed by grayscale ultrasound and standard motor function tests. In a cohort of patients who received disease-modifying therapy prior to the study, the optoacoustic signal intensity was similar to healthy controls. Conclusions: This translational study provides early evidence that three-dimensional optoacoustic imaging could have clinical implications in monitoring disease activity in spinal muscular atrophy. By visualizing and quantifying molecular changes in muscle tissue, disease progression and effects of gene therapy can be assessed in real time. Funding: The project was funded by ELAN Fonds (P055) at the University Hospital of the Friedrich-Alexander-Universität (FAU) Erlangen-Nurnberg to A.P.R.
CRIS-Team Scopus Importer:2024-05-03
Keywords: gene therapy; non-invasive imaging; optoacoustic imaging; pediatric spinal muscular atrophy; photoacoustic imaging; spinal muscular atrophy; Translation to patients

MRI in LARS1 deficiency—Spectrum, patterns, and correlation with acute neurological deterioration - Hammann, Nicole; Lenz, Dominic; Bianzano, Alyssa; Husain, Ralf A.; Forman, Eva; Bernstein, Jonathan A.; Dattner, Tal; Engelen, Marc; Hanson-Kahn, Andrea K.; Isidor, Bertrand; Kotzaeridou, Urania; Tietze, Anna; et al. (Journal of Inherited Metabolic Disease, 2024)
Leucine aminoacyl tRNA-synthetase 1 (LARS1)-deficiency (infantile liver failure syndrome type 1 (ILFS1)) has a multisystemic phenotype including fever-associated acute liver failure (ALF), chronic neurologic abnormalities, and encephalopathic episodes. In order to better characterize encephalopathic episodes and MRI changes, 35 cranial MRIs from 13 individuals with LARS1 deficiency were systematically assessed and neurological phenotype was analyzed. All individuals had developmental delay and 10/13 had seizures. Encephalopathic episodes in 8/13 were typically associated with infections, presented with seizures and reduced consciousness, mostly accompanied by hepatic dysfunction, and recovery in 17/19 episodes. Encephalopathy without hepatic dysfunction occurred in one individual after liver transplantation. On MRI, 5/7 individuals with MRI during acute encephalopathy had deep gray matter and brainstem changes. Supratentorial cortex involvement (6/13) and cerebellar watershed injury (4/13) occurred with seizures and/or encephalopathy. Abnormal brainstem contour on sagittal images (8/13), atrophy (8/13), and myelination delay (8/13) were not clearly associated with encephalopathy. The pattern of deep gray matter and brainstem changes are apparently characteristic of encephalopathy in LARS1-deficiency, differing from patterns of hepatic encephalopathy or metabolic stroke in organic acidurias and mitochondrial diseases. While the pathomechanism remains unclear, fever and energy deficit during infections might be causative; thus, sufficient glucose and protein intake along with pro-active fever management is suggested. As severe episodes were observed during influenza infections, we strongly recommend seasonal vaccination.
CRIS-Team Scopus Importer:2024-07-19
Keywords: acute liver failure; aminoacyl-tRNA synthetase deficiencies; cerebellar watershed; encephalopathy; ILFS1; LARS1; metabolic stroke; MRI; thalamus

Mucosal Mast Cell Distribution in the Gastrointestinal Tract of Children: A Preliminary Study for Establishing Reference Values - Ehrsam, Christoph; Rechenauer, Tobias; Allabauer, Ida; Siebenlist, Gregor; Kaspar, Sonja; Rieger, Daniel; Schmid, Margit; Ruckel, Aline; Wölfle, Joachim; Hartmann, Arndt; Rieker, Ralf; Raithel, Martin; et al. (Journal of Pediatric Gastroenterology and Nutrition, 2022)
Objectives: The physiological number and distribution of mast cells (MCs) in the pediatric gastrointestinal (GI) tract is not well defined and reference values of normality are missing. To define a physiological and disease defining cut-off, a systematic histological exploration of MC distribution from the esophagus to the rectum in healthy as well as in patients with gastrointestinal food allergies (GFA) was performed. Methods: Nine pediatric subjects that exhibited unremarkable histopathological evaluations or underwent endoscopy for surveillance reasons after a previous polypectomy of single colonic juvenile polyps served as reference cohort. In all of these subjects, a chronic inflammatory disease (eg, inflammatory bowel disease, celiac disease) or allergy was excluded. In addition, a group of 15 patients with gastrointestinal complaints suspected to be caused by a GFA were investigated. Immunohistochemistry was performed from all biopsies using CD117 (c-Kit) as a reliable marker to identify MCs in the lamina propria. Results: There were distinct differences of MC counts in all parts of the pediatric GI tract. The highest counts of MCs in both symptomatic patients and control cohort, were found in the duodenum, terminal ileum, cecum and ascending colon. The lowest counts were found in the esophagus. Significant disparities between GFA and healthy subjects were found in the gastric corpus (22.1 +/- 4.0/ high power field [HPF] vs 32.0 +/- 10.1/HPF; P = 0.034) and ascending colon (44.8 +/- 10.4/HPF vs 60.4 +/- 24.3/HPF; P = 0.047). Conclusions: Mucosal MC counts in the pediatric GI tract are higher than previously reported, with a considerable overlap between healthy and GFA patients. These results provide detailed information on distribution and numbers of MCs in pediatric allergic patients while allowing estimates of physiological values in childhood for the first time. With regard to diagnostic procedures in GFA further laboratory parameters have to be integrated.
CRIS-Team WoS Importer:2022-01-07

Multidisciplinary Approach to Ectodermal Dysplasia - Tadini, Gianluca; Wright, John Timothy; Hadj-Rabia, Smail; Schneider, Holm (Springer Nature, 2025)

Multidisciplinary Late Effects Clinics for Childhood Cancer Survivors in Germany - a Two-Center Study - Gebauer, Judith; Rieken, Sarah; Schuster, Sonja; Hahn, Birgit; Gebauer, Niklas; Meidenbauer, Norbert; Brabant, Georg; Metzler, Markus; Langer, Thorsten (Oncology Research and Treatment, 2018)
EVALuna2:34277

Multimodal analysis of cell-free DNA whole-genome sequencing for pediatric cancers with low mutational burden - Peneder, Peter; Stütz, Adrian M.; Surdez, Didier; Krumbholz, Manuela; Semper, Sabine; Chicard, Mathieu; Sheffield, Nathan C.; Pierron, Gaelle; Lapouble, Eve; Tötzl, Marcus; Ergüner, Bekir; Barreca, Daniele; et al. (Nature Communications, 2021)
Sequencing of cell-free DNA in the blood of cancer patients (liquid biopsy) provides attractive opportunities for early diagnosis, assessment of treatment response, and minimally invasive disease monitoring. To unlock liquid biopsy analysis for pediatric tumors with few genetic aberrations, we introduce an integrated genetic/epigenetic analysis method and demonstrate its utility on 241 deep whole-genome sequencing profiles of 95 patients with Ewing sarcoma and 31 patients with other pediatric sarcomas. Our method achieves sensitive detection and classification of circulating tumor DNA in peripheral blood independent of any genetic alterations. Moreover, we benchmark different metrics for cell-free DNA fragmentation analysis, and we introduce the LIQUORICE algorithm for detecting circulating tumor DNA based on cancer-specific chromatin signatures. Finally, we combine several fragmentation-based metrics into an integrated machine learning classifier for liquid biopsy analysis that exploits widespread epigenetic deregulation and is tailored to cancers with low mutation rates. Clinical associations highlight the potential value of cfDNA fragmentation patterns as prognostic biomarkers in Ewing sarcoma. In summary, our study provides a comprehensive analysis of circulating tumor DNA beyond recurrent genetic aberrations, and it renders the benefits of liquid biopsy more readily accessible for childhood cancers.
CRIS-Team Scopus Importer:2021-06-11

Multiple new susceptibility loci identified in genome-wide association study of Ewing sarcoma - Machiela, Mitchell J.; Gruenewald, Thomas G.; Surdez, Didier; Reynaud, Stephanie; Mirabeau, Olivier; Karlins, Eric; Rubio, Rebeca Alba; Zaidi, Sakina; Grossetete-Lalami, Sandrine; Ballet, Stelly; Lapouble, Eve; Laurence, Valerie; et al. (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-18

Multispectral optoacoustic tomography enables assessment of disease activity in paediatric inflammatory bowel disease - Regensburger, Adrian; Eckstein, Markus; Wetzl, Matthias; Raming, Roman; Paulus, Lars-Philip; Bühler, Adrian; Nedoschill, Emmanuel; Danko, Vera; Jüngert, Jörg; Wagner, Alexandra; Schnell, Alexander; Rückel, Aline; et al. (Photoacoustics, 2024)
Multispectral optoacoustic tomography (MSOT) allows non-invasive molecular disease activity assessment in adults with inflammatory bowel disease (IBD). In this prospective pilot-study, we investigated, whether increased levels of MSOT haemoglobin parameters corresponded to inflammatory activity in paediatric IBD patients, too. 23 children with suspected IBD underwent MSOT of the terminal ileum and sigmoid colon with standard validation (e.g. endoscopy). In Crohn‘s disease (CD) and ulcerative colitis (UC) patients with endoscopically confirmed disease activity, MSOT total haemoglobin (HbT) signals were increased in the terminal ileum of CD (72.1 ± 13.0 a.u. vs. 32.9 ± 15.4 a.u., p = 0.0049) and in the sigmoid colon of UC patients (62.9 ± 13.8 a.u. vs. 35.1 ± 16.3 a.u., p = 0.0311) as compared to controls, respectively. Furthermore, MSOT haemoglobin parameters correlated well with standard disease activity assessment (e.g. SES-CD and MSOT HbT (rs =0.69, p = 0.0075). Summarizing, MSOT is a novel technology for non-invasive molecular disease activity assessment in paediatric patients with inflammatory bowel disease.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Multispectral optoacoustic tomography; Optoacoustic imaging; Paediatric inflammatory bowel disease

Multispectral Optoacoustic Tomography for Assessment of Crohn's Disease Activity - Knieling, Ferdinand; Neufert, Clemens; Hartmann, Arndt; Claussen, Jing; Urich, Alexander; Egger, Cornelia; Vetter, Marcel; Fischer, Sarah; Pfeifer, Lukas; Hagel, Alexander; Kielisch, Christian; Görtz, Rüdiger; et al. (New England Journal of Medicine, 2017)
EVALuna2:33821

Multispectral optoacoustic tomography for non-invasive disease phenotyping in pediatric spinal muscular atrophy patients - Regensburger, Adrian; Wagner, Alexandra; Danko, Vera; Jüngert, Jörg M.; Federle, Anna; Klett, Daniel; Schüssler, Stephanie; Buehler, Adrian; Neurath, Markus; Roos, Andreas; Lochmüller, Hanns; Wölfle, Joachim; et al. (Photoacoustics, 2022)
Proximal spinal muscular atrophy (SMA) is a rare progressive, life limiting genetic motor neuron disease. While promising causal therapies are available, meaningful prognostic biomarkers for therapeutic monitoring are missing. We demonstrate handheld Multispectral Optoacoustic Tomography (MSOT) as a novel non-invasive imaging approach to visualize and quantify muscle wasting in pediatric SMA. While MSOT signals were distributed homogeneously in muscles of healthy volunteers (HVs), SMA patients showed moth-eaten optoacoustic signal patterns. Further signal quantification revealed greatest differences between groups at the isosbestic point for hemoglobin (SWL 800 nm). The SWL 800 nm signal intensities further correlated with clinical phenotype tested by standard motor outcome measures. Therefore, handheld MSOT could enable non-invasive assessment of disease burden in SMA patients.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Multispectral optoacoustic tomography; Optoacoustics; Photoacoustics; Spinal muscular atrophie

Multispectral optoacoustic tomography of the human intestine – temporal precision and the influence of postprandial gastrointestinal blood flow - Paulus, Lars-Philip; Wagner, Alexandra; Buehler, Adrian; Raming, Roman; Jüngert, Jörg; Simon, David; Tascilar, Koray; Schnell, Alexander; Günther, Josefine; Rother, Ulrich; Lang, Werner; Hörning, André; et al. (Photoacoustics, 2023)
Multispectral optoacoustic tomography (MSOT) holds great promise as a non-invasive diagnostic tool for inflammatory bowel diseases. Yet, reliability and the impact of physiological processes during fasting and after food intake on optoacoustic signals have not been studied. In the present investigator initiated trial (NCT05160077) the intestines of ten healthy subjects were examined by MSOT at eight timepoints on two days, one fasting and one after food intake. While within-timepoint and within-day reproducibility were good for single wavelength 800 nm and total hemoglobin (ICC 0.722–0.956), between-day reproducibility was inferior (ICC −0.137 to 0.438). However, temporal variability was smaller than variation between individuals (coefficients of variation 8.9%−33.7% vs. 17.0%−48.5%). After food intake and consecutive increased intestinal circulation, indicated by reduced resistance index of simultaneous Doppler ultrasound, optoacoustic signals did not alter significantly. In summary, this study demonstrates high reliability and temporal stability of MSOT for imaging the human intestine during fasting and after food intake.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Gut; Inflammatory bowel disease; Intestinal blood flow; Multispectral optoacoustic imaging; Optoacoustic; Photoacoustic; Postprandial; Reliability; Reproducibility

"Multisystem Inflammatory Syndrome in Children"-Like Disease after COVID-19 Vaccination (MIS-V) with Potential Significance of Functional Active Autoantibodies Targeting G-Protein-Coupled Receptors (GPCR-fAAb) for Pathophysiology and Therapy. - Schmidt, Marius; Hébert, Steven; Wallukat, Gerd; Ponader, Rolf; Krickau, Tobias; Galiano, Matthias; Reutter, Heiko Martin; Wölfle, Joachim; Agaimy, Abbas; Mardin, Christian; Hörning, André; Hohberger, Bettina (Children, 2023)
BACKGROUND: An infection with SARS-CoV-2 can trigger a systemic disorder by pathological autoimmune processes. A certain type of this dysregulation is known as Multisystemic inflammatory syndrome in children (MIS-C). However, similar symptoms may occur and have been described as Multisystemic inflammatory syndrome after SARS-CoV-2 Vaccination (MIS-V) following vaccination against SARS-CoV-2. We report the case of a 12-year-old boy who was identified with MIS-C symptoms without previous SARS-CoV-2 infection after receiving two doses of the Pfizer-BioNTech COVID-19 vaccine approximately one month prior to the onset of symptoms. He showed polyserositis, severe gastrointestinal symptoms and, consequently, a manifestation of a multiorgan failure. IgG antibodies against spike proteins of SARS-CoV-2 were detected, indicating a successful vaccination, while SARS-CoV-2 Nucleocapsid protein antibodies and SARS-CoV-2 PCR were not detected. Several functional, active autoantibodies against G-protein-coupled receptors (GPCR-fAAb), previously associated with Long COVID disease, were detected in a cardiomyocyte bioassay. Immunosuppression with steroids was initiated. Due to side effects, treatment with steroids and later interleukin 1 receptor antagonists had to be terminated. Instead, immunoadsorption was performed and continued with tacrolimus and mycophenolic acid therapy, leading to improvement and discharge after 79 days. GPCR-fAAb decreased during therapy and remained negative after clinical curing and under continued immunosuppressive therapy with tacrolimus and mycophenolic acid. Follow-up of the patient showed him in good condition after one year. CONCLUSIONS: Infection with SARS-CoV-2 shows a broad and severe variety of symptoms, partly due to autoimmune dysregulation, which, in some instances, can lead to multiorgan failure. Despite its rarity, post-vaccine MIS-C-like disease may develop into a serious condition triggered by autoimmune dysregulation. The evidence of circulating GPCR-fAAb and their disappearance after therapy suggests a link of GPCR-fAAb to the clinical manifestations. Thus, we hypothesize a potential role of GPCR-fAAb in pathophysiology and their potential importance for the therapy of MIS-C or MIS-V. However, this observation needs further investigation to prove a causative correlation.
EVALuna2:547545

“Multisystem Inflammatory Syndrome in Children” (MIS-C) after COVID-19 Infection in the Metropolitan Area of Nuremberg-Erlangen, Germany—Expectations and Results of a Two-Year Period - Hébert, Steven; Schmidt, Marius; Topf, Georg; Rieger, Daniel; Klinge, Jens; Vermehren, Jan; Fusch, Christoph; Grillhösl, Christian; Schroth, Michael; Toni, Irmgard; Reutter, Heiko Martin; Morhart, Patrick; et al. (Children, 2023)
Background: Multisystemic Inflammatory Syndrome in children (MIS-C) is a rare autoimmune disorder occurring after a latency period following acute SARS-CoV-2 infection. The therapeutic regime of MIS-C is adapted to the therapy of the Kawasaki disease, as clinical symptoms are similar. Since the Kawasaki disease can potentially result in severe symptoms, which may even affect long-term health, it is essential to gain further knowledge about MIS-C. Thus, we aimed to investigate the incidence, symptoms, therapeutical procedure and outcome of MIS-C patients in the metropolitan area of Nuremberg-Erlangen during the SARS-CoV2 pandemic. Material and Methods: Retrospective analysis of clinical charts of MIS-C patients was carried out at three children’s hospitals covering the medical care of the metropolitan area of Nuremberg-Erlangen in Germany. Demographic characteristics and symptoms at first visit, their clinical course, therapeutic regime and outcome were recorded within the time period January 2021–December 2022. Results: Analysis of 10 patients (5 male, 5 female) with MIS-C resulting in an incidence of 2.14/100.000 children. The median time between COVID-19 infection and admission to hospital was 5 weeks. The median age was 7 years. Symptoms comprised fever (100%), rash (70%), bilateral non-purulent conjunctivitis (70%) and urticaria (20%). At the time of presentation, diagnosis-defining inflammation parameters were increased and the range for C-reactive protein was 4.13 mg/dL to 28 mg/dL, with a median of 24.7 mg/dL. Procalcitonin was initially determined in six patients (1.92 ng/mL to 21.5 ng/mL) with a median value of 5.5 pg/mL. Two patients displayed leukocytosis and two displayed leukopenia. None of the patients presented coronary pathologies. Nine of the ten patients received intravenous immunoglobulin (IVIG) therapy. In addition, patients received intravenous steroids (80%) and acetylsalicylic acid (80%). Conclusion: SARS-CoV virus may rarely exert multiorgan manifestations due to hyperinflammatory immunological processes. Within two years of the COVID-19 pandemic, we identified ten patients with COVID-induced MIS-C in the metropolitan area Nuremberg-Erlangen. In the description of the patient collective, we can confirm that MIS-C is distinguished from the Kawasaki disease by the lack of coronary manifestations. Interestingly, although having monitored all pediatric facilities in the investigated area, we find lower incidences of MIS-C compared to findings in the literature. In conclusion, an overestimation of incidences in the upcoming MIS-C during the pandemic needs to be considered.
CRIS-Team Scopus Importer:2023-09-08
Keywords: COVID-19; intravenous immunoglobulins; IVIG; mAbs; MIS-C; monoclonal antibodies; Multisystem Inflammatory Syndrome in children

Mutational spectrum in 101 patients with hypohidrotic ectodermal dysplasia and breakpoint mapping in independent cases of rare genomic rearrangements - Wohlfart, Sigrun; Hammersen, Johanna; Schneider, Holm (Journal of Human Genetics, 2016)
Hypohidrotic ectodermal dysplasia (HED), a rare and heterogeneous hereditary disorder, is characterized by deficient development of multiple ectodermal structures including hair, sweat glands and teeth. If caused by mutations in the genes EDA, EDA1R or EDARADD, phenotypes are often very similar as the result of a common signaling pathway. Single-nucleotide polymorphisms (SNPs) affecting any gene product in this pathway may cause inter- and intrafamilial variability. In a cohort of 124 HED patients, genotyping was attempted by Sanger sequencing of EDA, EDA1R, EDARADD, TRAF6 and EDA2R and by multiplex ligation-dependent probe amplification (MLPA). Pathogenic mutations were detected in 101 subjects with HED, affecting EDA, EDA1R and EDARADD in 88%, 9% and 3% of the cases, respectively, and including 23 novel mutations. MLPA revealed exon copy-number variations in five unrelated HED families (two deletions and three duplications). In four of them, the genomic breakpoints could be localized. The EDA1R variant rs3827760 (p.Val370Ala), known to lessen HED-related symptoms, was found only in a single individual of Asian origin, but in none of the 123 European patients. Another SNP, rs1385699 (p.Arg57Lys) in EDA2R, however, appeared to have some impact on the hair phenotype of European subjects with EDA mutations.
EVALuna2:33878

Mutations in CFAP74 as a cause of primary ciliary dyskinesia (PCD) with normal nasal NO production rate and normal ciliary ultrastructure - Biebach, L.; Cindric, S.; Koenig, J.; Aprea,; Dougherty, G.; Raidt, J.; Bracht, D.; Ruppel, Renate; Schreiber, J.; Hieij, R.; Olbrich, H.; Omran, H. (KLINISCHE PADIATRIE, 2022)
Einleitung Die PCD ist eine seltene genetische Erkrankung deren respiratorischer Phänotyp langfristig durch eine destruktive, bronchiektasenbildende Lungenerkrankung charakterisiert ist. Mutationen in CFAP74 (Cilia and Flagella Associated Protein 74) wurden kürzlich als Ursache für MMAF (multiple morphological abnormalities of sperm flagella) bei zwei unfruchtbaren Männern veröffentlicht. Respiratorische Zilien wurden nicht untersucht, so dass CFAP74, welches ein central pair (CP)-assoziiertes Protein kodiert, als PCD-Ursache bislang nicht etabliert wurde. Methoden Patienten mit PCD-Verdacht wurden per genetischer Paneldiagnostik auf das Vorliegen von CFAP74-Mutationen untersucht und gefundene Mutationen mittels Sanger-Sequenzierung bestätigt. Neben Anamnese und klinischer Untersuchung erfolgten nasale NO-Messung, Hochfrequenz-Videomikroskopie-Analyse (HVMA), Immunfluoreszenz (IF) und Transmissions-Elektronenmikroskopie (TEM) als PCD-Diagnostik. Die mukoziläre Clearance wurde anhand von particle tracking auf ALI-Kulturen untersucht. Western Blot Analysen erfolgten zur Untersuchung der Proteinexpression. Ergebnisse Wir berichten über drei Betroffene aus zwei Familien mit biallelischen compound heterozygoten Loss-of-Function-Mutationen in CFAP74. Alle Patienten litten an rezidivierenden Atemwegsinfektionen. Interessanterweise waren sowohl die nasalen NO-Produktionsraten, als auch die Ultrastruktur in der TEM normal. Die HVMA wiederum identifizierte milde Anomalien des Zilienschlags. Die mukoziliäre Clearance war beeinträchtigt. Western-Blot-Analysen bewiesen die fehlende Expression von CFAP74. Schlussfolgerungen Mutationen in CFAP74 können PCD mit normaler NO-Produktionsrate, normaler Ultrastruktur und subtilem Zilienschlagdefekt verursachen. Um diese Patienten im diagnostischen Prozess dennoch identifizieren zu können, ist eine genetische Testung entscheidend. Wir empfehlen bei allen Patienten mit PCD-Verdacht eine genetische Untersuchung, die auch CFAP74 beinhalte
CRIS-Team WoS Importer:2023-01-27

Myelin Oligodendrocyte Glycoprotein Antibody-Associated Neuromyelitis Optica Spectrum Disorder in a 6-Year-Old Boy - Kamawal, Ariana; Hörning, Susanne; Galiano, Matthias; Rompel, Oliver; Trollmann, Regina (Klinische Pädiatrie, 2019)
CRIS-Team Scopus Importer:2019-07-26

Nanoscale Topography of Anodic TiO2 Nanostructures Is Crucial for Cell-Surface Interactions - Park, Jung; Tesler, Alexander; Gongadze, Ekaterina; Iglič, Aleš; Schmuki, Patrik; Mazare, Anca Valentina (ACS Applied Materials and Interfaces, 2024)
Anodic titanium dioxide (TiO2) nanostructures, i.e., obtained by electrochemical anodization, have excellent control over the nanoscale morphology and have been extensively investigated in biomedical applications owing to their sub-100 nm nanoscale topography range and beneficial effects on biocompatibility and cell interactions. Herein, we obtain TiO2 nanopores (NPs) and nanotubes (NTs) with similar morphologies, namely, 15 nm diameter and 500 nm length, and investigate their characteristics and impact on stem cell adhesion. We show that the transition of TiO2 NPs to NTs occurs via a pore/wall splitting mechanism and the removal of the fluoride-rich layer. Furthermore, in contrast to the case of NPs, we observe increased cell adhesion and proliferation on nanotubes. The enhanced mesenchymal stem cell adhesion/proliferation seems to be related to a 3-fold increase in activated integrin clustering, as confirmed by immunogold labeling with β1 integrin antibody on the nanostructured layers. Moreover, computations of the electric field and surface charge density show increased values at the inner and outer sharp edges of the top surfaces of the NTs, which in turn can influence cell adhesion by increasing the bridging interactions mediated by proteins and molecules in the environment. Collectively, our results indicate that the nanoscale surface architecture of the lateral spacing topography can greatly influence stem cell adhesion on substrates for biomedical applications.
CRIS-Team Scopus Importer:2024-02-23
Keywords: anodization; integrin; stem cells; surface topography; TiO2 nanopores; TiO2 nanotubes

National survey of referrals for precocious puberty in Germany - Baehr, Sonja; Schnabel, Dirk; Wölfle, Joachim; Schreiner, Felix; Gohlke, Bettina (BMJ Paediatrics Open, 2023)
An unusual high number of girls were referred to our paediatric endocrine clinic with suspected precocious puberty (PP) since the beginning of the COVID-19 pandemic. We analysed our data and initiated a survey among German paediatric endocrinologists. At our centre, less than 10 patients were diagnosed of PP annually between 2015 and 2019. This increased to n=23 (2020) and n=30 (2021). A German survey confirmed this observation: Out of 44 centres which completed the questionnaire, 30/44 (68%) reported an increase of PP. Above this, 32/44 (72%) stated an increase in girls diagnosed with 'early normal puberty' since the beginning of the COVID-19 pandemic.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Adolescent Health; COVID-19; Endocrinology

Natural history and clinical outcome of junctional epidermolysis bullosa generalized intermediate due to a LAMA3 mutation - Reimer, A.; Schwieger-Briel, A.; He, Y.; Leppert, J.; Schauer, F.; Kiritsi, D.; Schneider, Holm; Ott, H.; Bruckner-Tuderman, L.; Has, C. (British Journal of Dermatology, 2018)
EVALuna2:35487

Natural history of X-linked hypohidrotic ectodermal dysplasia: a 5-year follow-up study - Wohlfart, Sigrun; Meiller, Ralph; Hammersen, Johanna; Park, Jung; Menzel-Severing, Johannes; Melichar, Volker O.; Huttner, Kenneth; Johnson, Ramsey; Porte, Florence; Schneider, Holm (Orphanet Journal of Rare Diseases, 2020)
BACKGROUND: X-linked hypohidrotic ectodermal dysplasia (XLHED) is caused by pathogenic variants of the gene EDA disrupting the prenatal development of ectodermal derivatives. Cardinal symptoms are hypotrichosis, lack of teeth, and hypo- or anhidrosis, but the disease may also evoke other clinical problems. This study aimed at investigating the clinical course of XLHED in early childhood as the basis for an evaluation of the efficacy of potential treatments. METHODS: 25 children (19 boys and 6 girls between 11 and 35 months of age) with genetically confirmed XLHED were enrolled in a long-term natural history study. Clinical data were collected both retrospectively using parent questionnaires and medical records (pregnancy, birth, infancy) and prospectively until the age of 60 months. General development, dentition, sweating ability, ocular, respiratory, and skin involvement were assessed by standardized clinical examination and yearly quantitative surveys. RESULTS: All male subjects suffered from persistent anhidrosis and heat intolerance, although a few sweat ducts were detected in some patients. Sweating ability of girls with XLHED ranged from strongly reduced to almost normal. In the male subjects, 1-12 deciduous teeth erupted and 0-8 tooth germs of the permanent dentition became detectable. Tooth numbers were higher but variable in the female group. Most affected boys had no more than three if any Meibomian glands per eyelid, most girls had fewer than 10. Many male subjects developed additional, sometimes severe health issues, such as obstructive airway conditions, chronic eczema, or dry eye disease. Adverse events included various XLHED-related infections, unexplained fever, allergic reactions, and retardation of psychomotor development. CONCLUSIONS: This first comprehensive study of the course of XLHED confirmed the early involvement of multiple organs, pointing to the need of early therapeutic intervention.
CRIS-Team Scopus Importer:2020-01-21
Keywords: Dry eye; Ectodysplasin A; Heat intolerance; Hypohidrotic ectodermal dysplasia; Natural history; Oligodontia

Near final height in 62 twin pairs with twin-to-twin transfusion syndrome is not associated with the GHRd3 genotype - Schreiner, Felix; Schulte, Sandra; Kasner, Charlotte; Bartmann, Peter; Wölfle, Joachim; Gohlke, Bettina (HORMONE RESEARCH IN PAEDIATRICS, 2022)
CRIS-Team WoS Importer:2022-10-07

Neonatal nephron loss during active nephrogenesis results in altered expression of renal developmental genes and markers of kidney injury - Raming, Roman; Cordasic, Nada; Kirchner, Philipp; Ekici, Arif Bülent; Fahlbusch, Fabian; Wölfle, Joachim; Hilgers, Karl Friedrich; Hartner, Andrea; Menendez-Castro, Carlos (Physiological Genomics, 2021)
Preterm neonates are at a high risk for nephron loss under adverse clinical conditions. Renal damage potentially collides with postnatal nephrogenesis. Recent animal studies suggest that nephron loss within this vulnerable phase leads to renal damage later in life. Nephrogenic pathways are commonly reactivated after kidney injury supporting renal regeneration. We hypothesized that nephron loss during nephrogenesis affects renal development, which, in turn, impairs tissue repair after secondary injury. Neonates prior to 36 wk of gestation show an active nephrogenesis. In rats, nephrogenesis is ongoing until day 10 after birth. Mimicking the situation of severe nephron loss during nephrogenesis, male pups were uninephrectomized at day 1 of life (UNXd1). A second group of males was uninephrectomized at postnatal day 14 (UNXd14), after terminated nephrogenesis. Agematched controls were sham operated. Three days after uninephrectomy transcriptional changes in the right kidney were analyzed by RNA-sequencing, followed by functional pathway analysis. In UNXd1, 1,182 genes were differentially regulated, but only 143 genes showed a regulation both in UNXd1 and UNXd14. The functional groups “renal development” and “kidney injury” were among the most differentially regulated groups and revealed distinctive alterations. Reduced expression of candidate genes concerning renal development (Bmp7, Gdnf, Pdgf-B, Wt1) and injury (nephrin, podocin, Tgf-b 1) were detected. The downregulation of Bmp7 and Gdnf persisted until day 28. In UNXd14, Six2 was upregulated and Pax2 was downregulated. We conclude that nephron loss during nephrogenesis affects renal development and induces a specific regulation of genes that might hinder tissue repair after secondary kidney injury.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Neonatal nephron loss; Neonatal uninephrectomy; Nephrogenesis; Renal regeneration; RNA-sequencing

Neurogenic bladder function disorders in patients with meningomyelocele: S2k guidelines on diagnostics and therapy - Stein, R.; Assion, C.; Beetz, R.; Buerst, M.; Cremer, R.; Ermert, A.; Goepel, M.; Kuwertz-Broeking, E.; Ludwikowski, B.; Michael, T.; Pannek, J.; Peters, H.; et al. (Urologe, 2015)
The treatment of children and adolescents with meningomyelocele has experienced a clear change in the last 30 years. The establishment of pharmacotherapy, clean intermittent catheterization (CIC) and infection prophylaxis have improved the prognosis for patients and have led to new therapeutic strategies. The interdisciplinary cooperation between neonatologists, neurosurgeons, pediatric neurologists, pediatric urologists, pediatric nephrologists, pediatric orthopedists and pediatric surgeons leads to optimization of individualized therapy. These guidelines present definitions and classifications, investigations and timing which are described in detail. The conservative and operative therapy options for neurogenic bladder function disorders are described and discussed with reference to the current literature. The brief overview provides in each case assistance for the treating physician in the care of this patient group and facilitates the interdisciplinary cooperatio
EVALuna2:18927

Neuromonitoring in Neonatal-Onset Epileptic Encephalopathies - Trollmann, Regina (Frontiers in Neurology, 2021)
Considering the wide spectrum of etiologies of neonatal-onset epileptic encephalopathies (EE) and their unfavorable consequences for neurodevelopmental prognoses, neuromonitoring at-risk neonates is increasingly important. EEG is highly sensitive for early identification of electrographic seizures and abnormal background activity. Amplitude-integrated EEG (aEEG) is recommended as a useful bedside monitoring method but as a complementary tool because of methodical limitations. It is of special significance in monitoring neonates with acute symptomatic as well as structural, metabolic and genetic neonatal-onset EE, being at high risk of electrographic-only and prolonged seizures. EEG/aEEG monitoring is established as an adjunctive tool to confirm perinatal hypoxic-ischemic encephalopathy (HIE). In neonates with HIE undergoing therapeutic hypothermia, burst suppression pattern is associated with good outcomes in about 40% of the patients. The prognostic specificity of EEG/aEEG is lower compared to cMRI. As infants with HIE may develop seizures after cessation of hypothermia, recording for at least 24 h after the last seizure is recommended. Progress in the identification of genetic etiology of neonatal EE constantly increases. However, presently, no specific EEG changes indicative of a genetic variant have been characterized, except for individual variants associated with typical EEG patterns (e.g., KCNQ2, KCNT1). Long-term monitoring studies are necessary to define and classify electro-clinical patterns of neonatal-onset EE.
CRIS-Team Scopus Importer:2021-03-05
Keywords: electroencephalopgraphy; genetic epilepsy; metabolic epilepsy; neonatal brain; suppression burst

Neuromonitoring in neonatal seizures-significance and challenges Neuromonitoring bei zerebralen Anfällen im Neugeborenenalter-Chancen und Herausforderungen - Trollmann, Regina (Klinische Neurophysiologie, 2021)
Neonatal EEG-monitoring including amplitude-integrated EEG (aEEG) is a valuable bedside tool for diagnosis of epileptic seizures and neonatal epileptic encephalopathies, as well as for continuous treatment monitoring. Because of methodical limitations of aEEG monitoring, the combinatory use of aEEG and conventional EEG is recommended as the gold standard. Especially physiological EEG maturation patterns and epileptic discharges (e. g. discharges<10 s, electrographic seizures in very preterm neonates) are exclusively identified by conventional EEG. Long-term EEG/aEEG monitoring is of special significance in neonates at risk of electrographic-only or subtle seizures. EEG/aEEG is an important additional tool for monitoring neonates with HIE undergoing therapeutic hypothermia. Rarely, typical EEG changes indicative of a genetic variant have been characterized. Further studies are necessary on the role of EEG/aEEG as biomarker of neurodevelopmental outcome in neonates with seizures of various etiology.
CRIS-Team Scopus Importer:2021-09-24
Keywords: amplitude-integrated EEG; genetic early-onset epileptic encephalopathy; hypoxic-ischemic encephalopathy; KCNQ2; KCNT1; maturational patterns; neonatal stroke

Neuropathy in paediatric type 1 diabetes mellitus - Clinical characterization and analysis of risk factors in the diabetes prospective follow-up registry DPV (Diabetes-Patienten-Verlaufsdokumentation)-registry - Pappa, Angeliki; Haeusler, Martin G.; Tittel, Sascha R.; Boettcher, Claudia; Hilgard, Doerte; Knauer-Fischer, Sabine; Pavel, Marianne Ellen; Wölfle, Joachim; Holl, Reinhard W. (Journal of Pediatric Endocrinology & Metabolism, 2023)
Objectives: Data on the prevalence, clinical features and risk factors associated with paediatric diabetic neuropathy (DN) are scarce. Methods: We retrospectively analysed data from the DPV registry, including patients under 20years of age, treated for type 1 diabetes mellitus (T1D) between 2005 and 2021. Patients with non-diabetic neuropathy were excluded. Data came from centres in Austria, Germany, Luxembourg and Switzerland. Results: 1,121 of the 84,390 patients included had been diagnosed with DN. Univariate analysis showed patients with DN to be older and predominantly female, with a longer duration of T1D, higher insulin dosages per kg and day, lower rates of insulin pump therapy, higher postprandial glucose-, higher HbA1c-and higher cholesterol levels, and higher diastolic and systolic blood pressure values. There was also a larger proportion of smokers and higher prevalence of diabetic retinopathy. Median duration of diabetes at diagnosis of DN was 8.3years. Multivariable analysis, adjusted for demographics revealed an increased risk for DN among female patients and those who were older, underweight (BMI-SDS), smoked cigarettes or had a longer duration of T1D or higher levels of HbA1c and postprandial blood glucose. The presence of retinopathy and higher cholesterol levels were also linked to increased risk while not-using insulin pump therapy was not. Conclusions: DN can develop after just a short duration of T1D. Prevention may be achieved by a lowering of HbA1c-and postprandial glucose levels through improved glycaemic control. This warrants further investigation. The slight female predominance suggests further hormonal and genetic etiological factors.
CRIS-Team Scopus Importer:2023-07-07
Keywords: autonomic dysfunction; childhood diabetes; diabetic neuropathy; DPV; small fiber neuropathy; type 1 diabetes mellitus

Newbornscreening SMA - From Pilot Project to Nationwide Screening in Germany - Müller-Felber, Wolfgang; Blaschek, Astrid; Schwartz, Oliver; Gläser, Dieter; Nennstiel, Uta; Brockow, Inken; Wirth, Brunhilde; Burggraf, Siegfried; Röschinger, Wulf; Becker, Marc; Durner, Jürgen; Eggermann, Katja; et al. (Journal of Neuromuscular Diseases, 2023)
Now that targeted therapies for spinal muscular atrophy are available, attempts are being made worldwide to include screening for spinal muscular atrophy in general newborn screening. In Germany, after pilot projects from 2018-2021, it was included in the general newborn screening from October 2021. To ensure a smooth transition, criteria for follow-up were developed together with key stakeholders. At the beginning of the transition to nationwide screening, false positive findings were reported in 3 patients. After optimization of the screening method in the laboratories concerned, all findings have been subsequently confirmed. On average, the first presentation to a neuromuscular center occurred on day 12 of life, and in patients with 2 or 3 SMN2 copies, therapy started on day 26 of life. Compared with the pilot project, there was no significant delay in timing.
CRIS-Team Scopus Importer:2023-01-20
Keywords: 5q-SMA; newborn screening; SMA treatment; Spinal muscular atrophy

NEXT-GENERATION REFERENCE INTERVALS FOR PEDIATRIC HEMATOLOGY - Zierk, Jakob; Hirschmann, J.; Toddenroth, Dennis; Arzideh, F.; Streichert, T.; Haeckel, R.; Prokosch, Hans-Ulrich; Rauh, Manfred; Metzler, Markus (2017)
EVALuna2:32792

Next-generation reference intervals for pediatric hematology - Zierk, Jakob; Hirschmann, Johannes; Toddenroth, Dennis; Arzideh, Farhad; Haeckel, Rainer; Bertram, Alexander; Cario, Holger; Frühwald, Michael C.; Groß, Hans Jürgen; Groening, Arndt; Grützner, Stefanie; Gscheidmeier, Thomas; et al. (Clinical Chemistry and Laboratory Medicine, 2019)
Interpreting hematology analytes in children is challenging due to the extensive changes in hematopoiesis that accompany physiological development and lead to pronounced sex- and age-specific dynamics. Continuous percentile charts from birth to adulthood allow accurate consideration of these dynamics. However, the ethical and practical challenges unique to pediatric reference intervals have restricted the creation of such percentile charts, and limitations in current approaches to laboratory test result displays restrict their use when guiding clinical decisions. We employed an improved data-driven approach to create percentile charts from laboratory data collected during patient care in 10 German centers (9,576,910 samples from 358,292 patients, 412,905-1,278,987 samples per analyte). We demonstrate visualization of hematology test results using percentile charts and z-scores (www.pedref.org/hematology) and assess the potential of percentiles and z-scores to support diagnosis of different hematological diseases. We created percentile charts for hemoglobin, hematocrit, red cell indices, red cell count, red cell distribution width, white cell count and platelet count in girls and boys from birth to 18 years of age. Comparison of pediatricians evaluating complex clinical scenarios using percentile charts versus conventional/tabular representations shows that percentile charts can enhance physician assessment in selected example cases. Age-specific percentiles and z-scores, compared with absolute test results, improve the identification of children with blood count abnormalities and the discrimination between different hematological diseases. The provided reference intervals enable precise assessment of pediatric hematology test results. Representation of test results using percentiles and z-scores facilitates their interpretation and demonstrates the potential of digital approaches to improve clinical decision-making.
CRIS-Team Scopus Importer:2019-05-09
Keywords: hematology; laboratory test result display; pediatric reference intervals

No evidence for preferential X-chromosome inactivation as the main cause of divergent phenotypes in sisters with X-linked hypohidrotic ectodermal dysplasia - Körber, Laura; Schneider, Holm; Fleischer, Nicole; Maier-Wohlfart, Sigrun (Orphanet Journal of Rare Diseases, 2021)
Background: X-linked hypohidrotic ectodermal dysplasia (XLHED), a rare genetic disorder, affects the normal development of ectodermal derivatives, such as hair, skin, teeth, and sweat glands. It is caused by pathogenic variants of the gene EDA and defined by a triad of hypotrichosis, hypo- or anodontia, and hypo- or anhidrosis which may lead to life-threatening hyperthermia. Although female carriers are less severely affected than male patients, they display symptoms, too, with high phenotypic variability. This study aimed to elucidate whether phenotypic differences in female XLHED patients with identical EDA genotypes might be explained by deviating X-chromosome inactivation (XI) patterns. Methods: Six families, each consisting of two sisters with the same EDA variant and their parents (with either mother or father being carrier of the variant), participated in this study. XLHED-related data like sweating ability, dental status, facial dysmorphism, and skin issues were assessed. We determined the women`s individual XI patterns in peripheral blood leukocytes by the human androgen receptor assay and collated the results with phenotypic features. Results: The surprisingly large inter- and intrafamilial variability of symptoms in affected females was not explicable by the pathogenic variants. Our cohort showed no higher rate of nonrandom XI in peripheral blood leukocytes than the general female population. Furthermore, skewed XI patterns in favour of the mutated alleles were not associated with more severe phenotypes. Conclusions: We found no evidence for preferential XI in female XLHED patients and no distinct correlation between XLHED-related phenotypic features and XI patterns. Phenotypic variability seems to be evoked by other genetic or epigenetic factors.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Ectodysplasin A; Female carriers; Genotype–phenotype correlation; X-chromosome inactivation; X-linked hypohidrotic ectodermal dysplasia

No evidence of the unfolded protein response in the placenta of two rodent models of preeclampsia and intrauterine growth restriction - Denkl, Barbara; Cordasic, Nada; Hübner, Hanna; Menendez-Castro, Carlos; Schmidt, Marius; Mocker, Alexander; Wölfle, Joachim; Hartner, Andrea; Fahlbusch, Fabian (Biology of Reproduction, 2021)
In humans, intrauterine growth restriction (IUGR) and preeclampsia (PE) are associated with induction of the unfolded protein response (UPR) and increased placental endoplasmic reticulum (ER) stress. Especially in PE, oxidative stress occurs relative to the severity of maternal vascular underperfusion (MVU) of the placental bed. On the premise that understanding the mechanisms of placental dysfunction could lead to targeted therapeutic options for human IUGR and PE, we investigated the roles of the placental UPR and oxidative stress in two rodent models of these human gestational pathologies. We employed a rat IUGR model of gestational maternal protein restriction, as well as an endothelial nitric oxide synthase knockout mouse model (eNOS-/-) of PE/IUGR. Placental expression of UPR members was analyzed via qRT-PCR (Grp78, Calnexin, Perk, Chop, Atf6, and Ern1), immunohistochemistry, and Western blotting (Calnexin, ATF6, GRP78, CHOP, phospho-eIF2α, and phospho-IRE1). Oxidative stress was determined via Western blotting (3-nitrotyrosine and 4-hydroxy-2-nonenal). Both animal models showed a significant reduction of fetal and placental weight. These effects did not induce placental UPR. In contrast to human data, results from our rodent models suggest retention of placental plasticity in the setting of ER stress under an adverse gestational environment. Oxidative stress was significantly increased only in female IUGR rat placentas, suggesting a sexually dimorphic response to maternal malnutrition. Our study advances understanding of the involvement of the placental UPR in IUGR and PE. Moreover, it emphasizes the appropriate choice of animal models researching various aspects of these pregnancy complications.
CRIS-Team Scopus Importer:2021-08-27
Keywords: eNOS; ER stress; IUGR; oxidative stress; placenta; preeclampsia

No juvenile arterial hypertension in sheep multiples despite reduced nephron numbers - Muehle, Anja; Mühle, Christiane; Amann, Kerstin Ute; Dötsch, Jörg; Nuesken, Kai-Dietrich; Boltze, Johannes; Schneider, Holm (Pediatric Nephrology, 2010)
Low birth weight is associated with an increased risk of metabolic dysfunction and arterial hypertension in later life. Because of their reduced birth weight twins have been used repeatedly as a natural model to investigate prenatal programming of hypertension. To reveal an early impact of lower nephron endowment on blood pressure, we performed a longitudinal study on lambs from single, twin and triplet pregnancies. The lambs were studied from birth until adulthood, including regular blood analyses, measurements of body weight and blood pressure and post-mortem estimation of glomerular numbers. Relative weight differences between multiples and singletons at birth were -28% for twins and -44% for triplets, respectively. Some lambs showed rapid catch-up growth. Total nephron number of twins and triplets was reduced by 21 and 37% with respect to that of singletons (p∈<∈0.01). However, multiples did not show increased blood pressure within the time frame of this study. No gender-specific effect was observed. Plasma concentrations of creatinine, urea, electrolytes or osmolality also did not differ. Our data indicate that the previously reported postnatal blood pressure differences between sheep multiples and singletons are a time-limited phenomenon. During infancy and adolescence, a reduced nephron number in sheep multiples is neither associated with increased blood pressure nor reflected by plasma parameters. © 2010 IPNA.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Blood pressure; Nephron number; Prenatal programming

NON-INVASIVE IN VIVO METABOLIC PROFILING OF INFLAMMATION IN JOINTS AND ENTHESES BY OPTOACOUSTIC IMAGING - Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Bayat, Sara; Heidemann, Robert; Steiger, F.; Krönke, Gerhard; Bohr, D.; Ramming, Andreas; Hartmann, F.; Klett, Daniel; Federle, Anna; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Non-invasive metabolic profiling of inflammation in joints and entheses by multispectral optoacoustic tomography - Tascilar, Koray; Fagni, Filippo; Kleyer, Arnd; Bayat, Sara; Heidemann, Robert; Steiger, Florian; Krönke, Gerhard; Bohr, Daniela; Ramming, Andreas; Hartmann, Fabian; Klett, Daniel; Federle, Anna; et al. (Rheumatology, 2022)
Objective To explore the metabolic characteristics of arthritis and enthesitis using multispectral opto-acoustic tomography (MSOT), a technology using near-infrared multispectral laser to stimulate tissues and detect the emitted acoustic energy, enabling non-invasive quantification of tissue components in vivo based on differential absorbance at multiple wavelengths. Methods We performed a cross-sectional study in patients with RA or PsA and healthy controls (HCs). Participants underwent clinical, ultrasonographic and MSOT examination of MCP and wrist joints as well as the entheses of the common extensor tendon at the lateral humeral epicondyles and of the patellar, quadriceps and Achilles tendon. MSOT-measured haemoglobin (Hb), oxygen saturation, collagen and lipid levels were quantified and scaled mean differences between affected and unaffected joints and entheses were calculated as defined by clinical examination or ultrasonography using linear mixed effects models. Results We obtained 1535 MSOT and 982 ultrasonography scans from 87 participants (34 PsA, 17 RA, 36 HCs). Entheseal tenderness was not associated with significant metabolic changes, whereas enthesitis-related sonographic changes were associated with increased total Hb, oxygen saturation and collagen content. In contrast, the presence of arthritis-related clinical and sonographic findings showed increased Hb levels, reduced oxygen saturation and reduced collagen content. Synovial hypertrophy was associated with increased lipid content in the joints. Conclusion MSOT allows determination of distinct metabolic differences between arthritis and enthesitis in a non-invasive setting in humans in vivo.
CRIS-Team WoS Importer:2022-07-22

Non-invasive optoacoustic imaging of glycogen-storage and muscle degeneration in late-onset Pompe disease. - Tan, Lina; Zschüntzsch, Jana; Meyer, Stefanie; Stobbe, Alica; Bruex, Hannah; Regensburger, Adrian; Claßen, Merle; Alves, Frauke; Jüngert, Jörg; Rother, Ulrich; Li, Yi; Danko, Vera; et al. (Nature Communications, 2024)
Pompe disease (PD) is a rare autosomal recessive glycogen storage disorder that causes proximal muscle weakness and loss of respiratory function. While enzyme replacement therapy (ERT) is the only effective treatment, biomarkers for disease monitoring are scarce. Following ex vivo biomarker validation in phantom studies, we apply multispectral optoacoustic tomography (MSOT), a laser- and ultrasound-based non-invasive imaging approach, in a clinical trial (NCT05083806) to image the biceps muscles of 10 late-onset PD (LOPD) patients and 10 matched healthy controls. MSOT is compared with muscle magnetic resonance imaging (MRI), ultrasound, spirometry, muscle testing and quality of life scores. Next, results are validated in an independent LOPD patient cohort from a second clinical site. Our study demonstrates that MSOT enables imaging of subcellular disease pathology with increases in glycogen/water, collagen and lipid signals, providing higher sensitivity in detecting muscle degeneration than current methods. This translational approach suggests implementation in the complex care of these rare disease patients.
EVALuna2:571098

Noninvasive Prenatal Diagnosis of Hypohidrotic Ectodermal Dysplasia by Tooth Germ Sonography - Wuensche, S.; Juengert, J.; Faschingbauer, Florian; Mommsen, H.; Goecke, T.; Schwanitz, K.; Stepan, H.; Schneider, Holm (Ultraschall in der Medizin, 2015)
Hypohidrotic ectodermal dysplasia, a potentially life-threatening heritable disorder, may be recognized already in utero by characteristic features such as oligodontia and mandibular hypoplasia. As therapeutic options and prognosis depend on the time point of diagnosis, early recognition was attempted during routine prenatal ultrasound examinations.Fetuses of nine pregnant women (one triplet and eight singleton pregnancies) with family histories of hypohidrotic ectodermal dysplasia were investigated by sonography between the 20th and 24th week of gestation.In 4 male and 2 female fetuses reduced amounts of tooth germs were detected, whereas 5 fetal subjects showed the normal amount. Three-dimensional ultrasound evaluation revealed mandibular hypoplasia in 5 of the 6 fetuses with oligodontia. Molecular genetic analysis and/or clinical findings after birth confirmed the prenatal sonographic diagnosis in each subject.In subjects with a family history of hypohidrotic ectodermal dysplasia, the diagnosis of this rare condition can be established noninvasively by sonography in the second trimester of pregnancy. Early recognition of the disorder may help to prevent dangerous hyperthermic episodes in infancy and may allow timely therapeutic intervention
EVALuna2:17430

Non-Syndromic and Syndromic Defects in Children with Extracranial Germ Cell Tumors: Data of 2610 Children Registered with the German MAKEI 96/MAHO 98 Registry Compared to the General Population - Schultewolter, Judit H.; Rissmann, Anke; von Schweinitz, Dietrich; Frühwald, Michael; Blattmann, Claudia; Fischer, Lars; Lange, Björn Sönke; Wessalowski, Rüdiger; Fröhlich, Birgit; Behnisch, Wolfgang; Schmid, Irene; Reinhard, Harald; et al. (Cancers, 2024)
GCTs are developmental tumors and are likely to reflect ontogenetic and teratogenetic determinants. The objective of this study was to identify syndromes with or without congenital anomalies and non-syndromic defects as potential risk factors. Patients with extracranial GCTs (eGCTs) registered in MAKEI 96/MAHO 98 between 1996 and 2017 were included. According to Teilum’s holistic concept, malignant and benign teratomas were registered. We used a case–control study design with Orphanet as a reference group for syndromic defects and the Mainz birth registry (EUROCAT) for congenital anomalies at birth. Co-occurring genetic syndromes and/or congenital anomalies were assessed accordingly. Odds ratios and 95% confidence intervals were calculated and p-values for Fisher’s exact test with Bonferroni correction if needed. A strong association was confirmed for Swyer (OR 338.6, 95% CI 43.7–2623.6) and Currarino syndrome (OR 34.2, 95% CI 13.2–88.6). We additionally found 16 isolated cases of eGCT with a wide range of syndromes. However, these were not found to be significantly associated following Bonferroni correction. Most of these cases pertained to girls. Regarding non-syndromic defects, no association with eGCTs could be identified. In our study, we confirmed a strong association for Swyer and Currarino syndromes with additional congenital anomalies.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Currarino syndrome; developmental tumor; germ cell tumor; MAKEI 96/MAHO 98; non-syndromic defect; Swyer syndrome; syndrome

Nonurgent Visits to the Pediatric Emergency Department before and during the First Peak of the COVID-19 Pandemic - Guckert, Laura; Reutter, Heiko Martin; Saleh, Nadia; Ganschow, Rainer; Müller, Andreas; Ebach, Fabian (International Journal of Pediatrics, 2022)
Background. Nonurgent visits in pediatric Emergency Departments are a growing burden. In order to find predictors for those nonurgent visits, we performed a retrospective analysis of unscheduled visits at the Pediatric Emergency Department of the University Hospital of Bonn, Germany, in the year 2017. Additionally, we compared these findings to unscheduled visits during the first peak of the worldwide pandemic of the Coronavirus disease 2019, to see if there would be an effect on nonurgent pediatric Emergency Department attendances. Methods. For our retrospective cohort study, we analyzed more than 5.000 visits at the pediatric Emergency Department of the University Hospital of Bonn, Germany, before and during the first peak of the ongoing worldwide pandemic of the Coronavirus disease 2019, particularly with regard to their urgency. Data included gender, age, zip code, urgency, and preexisting conditions. Results. Our study shows that more than half of unscheduled pediatric Emergency Department visits (69%) at the University Hospital in Bonn are for nonurgent reasons, with short living distance being a factor to present children to a pediatric Emergency Department, even with minor complaints. During the first peak of the pandemic of the Coronavirus disease 2019, nonurgent visits decreased significantly, potentially due to hesitation to attend a pediatric Emergency Department with minor issues, fearing an infection with SARS-CoV-2 at the hospital. Conclusion. Many people use pediatric Emergency Departments for nonemergency complaints. In order to address the reasons for nonurgent visits to pediatric Emergency Departments and to prevent parents from doing so, further studies and targeted education concepts for parents are needed.
CRIS-Team Scopus Importer:2022-04-01

Oligoclonal bands predict multiple sclerosis in children with optic neuritis - Heussinger, Nicole; Kontopantelis, Evangelos; Gburek-Augustat, Janina; Jenke, Andreas; Vollrath, Gesa; Korinthenberg, Rudolf; Hofstetter, Peter; Meyer, Sascha; Brecht, Isabel; Kornek, Barbara; Herkenrath, Peter; Schimmel, Mareike; et al. (Annals of Neurology, 2015)
We retrospectively evaluated predictors of conversion to multiple sclerosis (MS) in 357 children with isolated optic neuritis (ON) as a first demyelinating event who had a median follow-up of 4.0 years. Multiple Cox proportional-hazards regressions revealed abnormal cranial magnet resonance imaging (cMRI; hazard ratio [HR] = 5.94, 95% confidence interval [CI] = 3.39-10.39, p < 0.001), presence of cerebrospinal fluid immunoglobulin G oligoclonal bands (OCB; HR = 3.69, 95% CI = 2.32-5.86, p < 0.001), and age (HR = 1.08 per year of age, 95% CI = 1.02-1.13, p = 0.003) as independent predictors of conversion, whereas sex and laterality (unilateral vs bilateral) had no influence. Combined cMRI and OCB positivity indicated a 26.84-fold higher HR for developing MS compared to double negativity (95% CI = 12.26-58.74, p < 0.001). Accordingly, cerebrospinal fluid analysis may supplement cMRI to determine the risk of MS in children with isolated ON.
EVALuna2:18923

On the interdisciplinary S3 guidelines for the treatment of chronic idiopathic tinnitus - Zenner, H. -P.; Delb, W.; Kroener-Herwig, B.; Jaeger, B.; Peroz, I.; Hesse, G.; Mazurek, B.; Goebel, G.; Gerloff, C.; Trollmann, Regina; Biesinger, E.; Seidler, H.; et al. (HNO, 2015)
Tinnitus is a frequent symptom, which, particularly in combination with comorbidities, can result in a severe disease-related burden. Chronic idiopathic tinnitus (CIT) is the most frequent type of tinnitus. A considerable number of treatment strategies are used to treat CIT-for many of which there is no evidence of efficacy. In order to enable scientific evidence-based treatment of CIT, German interdisciplinary S3 guidelines have recently been constructed for the first time. Here we present a short form of these S3 guidelines.The guidelines were constructed based on a meta-analysis of the treatment of chronic tinnitus performed by the authors. Additionally, a systematic literature search was performed in the PubMed and Cochrane Library databases. Furthermore, a systematic search for international guidelines was performed in Google, as well as in the Guidelines International Network and National Guideline Clearinghouse (USA) database. Evidence was classified according to the Oxford Centre for Evidence-Based Medicine system.According to the guidelines, alongside counselling, manualized structured tinnitus-specific cognitive behavioral therapy (tCBT) with a validated treatment manual is available as evidence-based therapy. In addition, the guidelines recommend concurrent treatment of comorbidities, including drug-based treatment, where appropriate. Particularly important is treatment of anxiety and depression. Where a psychic or psychiatric comorbidity is suspected, further diagnosis and treatment should be performed by an appropriately qualified specialist (psychiatrist, neurologist, psychosomatic medicine consultant) or psychological psychotherapist. In cases accompanied by deafness or hearing loss bordering on deafness, cochlear implants may be indicated.No recommendations can be made for drug-based treatment of CIT, audiotherapy, transcranial magnetic or electrical stimulation, specific forms of acoustic stimulation or music therapy; or such recommendations must remain open due to the lack of available evidence. Polypragmatic tinnitus treatment with therapeutic strategies for which there is no evidence of efficacy from controlled studies is to be refused.
EVALuna2:18924

Orthotic Care Based on the Ferrari Concept for Children and Adults with Meningomyelocele - Schmid, Tim; Strehl, Elisabeth; Trollmann, Regina; Forst, Raimund; Fujak, Albert (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Background Even today, myelomeningocele (MMC) is still encountered in clinical medicine and its incidence has not decreased over the last 20 years despite a known reduction in risk due to the use of folic acid supplements. The spectrum of clinical symptoms is extremely broad and, depending on the level of the defect, varies from mild to severe. Subject to the degree of paralysis, patients are reliant on the use of orthopaedic aids and orthoses for the treatment of primary contractures and deformities and the prevention of secondary ones. This forms the basis for attaining or maintaining mobility in many patients. The objective of the study was to determine the practical application of the proposed Ferrari concept for the provision of orthoses for children and adults. Patients and Material The retrospective study comprised medical records of 180 patients (97 m) with an average age of 19.44 years (3-52 years, SD 9.3) at the time of investigation. The average duration of treatment was 15.34 years (1-38 years, SD 8.96). Data relating to deformities of the vertebral column and lower limbs, provision of hydrocephalus shunts and orthoses, and patient mobility was evaluated. Results Most patients were given systematic treatment with orthoses at an early stage. In 58,9% of cases, it was possible to implement the proposed concept for providing patients with dynamic orthoses, whereby the treatment concept was more difficult to implement with high lumbar lesions than with lower lesions. Moreover, a decrease in the patients' mobility with increasing age was noticeable. Some 42.3% of adult patients were able to walk with marked variations in mobility in relation to the different levels of lesions. Conclusion Taking into consideration the complexity of both the clinical picture and therefore the provision of orthopaedic devices, the result of the implementation of the proposed orthotic concept can be considered positive. Similarly, early commencement of provision of orthoses and hence the possibility of achieving a positive influence on later mobility can be considered a success. The need for individual concepts and further development in order to increase mobility particularly in the case of patients with thoracic or high lumbar lesions is evident. A more comprehensive provision of information to patients regarding orthotic treatment options and their consequences for prophylaxis and quality of life should be an important component of interdisciplinary long-term patient care.
CRIS-Team Scopus Importer:2019-12-13
Keywords: MMC; mobility; orthopaedic treatment concept; orthotics

Osteosarcoma and causes of death: A report of 1520 deceased patients from the Cooperative Osteosarcoma Study Group (COSS) - Bielack, Stefan S.; Blattmann, Claudia; Borkhardt, Arndt; Csóka, Monika; Hassenpflug, Wolf; Kabíčková, Edita; Kager, Leo; Kessler, Thorsten; Kratz, Christian; Kühne, Thomas; Kevric, Matthias; Lehrnbecher, Thomas; et al. (European Journal of Cancer, 2022)
Purpose: Most aspects of osteosarcoma have been addressed in detail, but there is no comprehensive analysis of deceased patients and causes of death. Methods: The database of the Cooperative Osteosarcoma Study Group COSS (1980-03/31/2021; 4475 registered high-grade central osteosarcoma patients) was searched deaths from any cause. Affected patients were analyzed for demographic and baseline variables and disease-status at the time of demise. Deaths from causes other than osteosarcoma were analyzed in detail. Results: A total of 1520 deceased patients were identified (median age (range) at osteosarcoma diagnosis 16 (2–78) years; 908 (59.7%) male, 612 (40.3%) female; primary tumor: extremities 1263 (83.1%), trunk 208 (13.7%), craniofacial 47 (3.1%) (site unknown 2); metastases at registration: absent 1.051 (69.1%), present 466 (30.7%) (3 no data). The median time from diagnosis to death was 2.22 (0.08–32.02) years. 1286 (84.6%) patients succumbed to osteosarcoma (370 without achieving complete remission, 488 first, 428 more than one recurrences), 146 (9.6%) to other, 88 (5.8%) to unknown causes. Chemotherapy-related infections (40), secondary malignancies (39), and perioperative complications (19) were among the most frequent potentially treatment-related causes, and high-dose methotrexate (19), doxorubicin (17), and ifosfamide (15) were the drugs most commonly held responsible. Patients with unknown causes of death had an unusually long median follow-up. Conclusion: The major cause of death of patients after osteosarcoma is this malignancy, mostly from one of its multiple relapses. However, almost 10% of fatalities are due to other documented causes. Some of these deaths may be preventable with the knowledge gained from comprehensive analyses such as this.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Adolescent; Adult; Child; Osteosarcoma; Survival

Osteosarcomas in retinoblastoma-survivors. A report of 28 affected patients from the Cooperative Osteosarcoma Study Group (COSS) - Bielack, Stefan S.; Baumhoer, Daniel; Hecker-Nolting, Stefanie; Hettmer, Simone; Kager, Leo; Ketteler, Petra; Kevric, Matthias; Kratz, Christian P.; Kühne, Thomas; Mettmann, Vanessa; Metzler, Markus; Reinhardt, Dirk; et al. (EJC Pediatric Oncology, 2024)
Purpose: Many publications address the epidemiology of secondary osteosarcomas following retinoblastoma. Treatment- and outcome-related information is, however, scarce. We used a large cooperative group's database to study this issue. Patients and methods: The database Cooperative Osteosarcoma Study Group COSS was searched for patients with osteosarcoma following a previous retinoblastoma. Patients were then analyzed for demographic factors, local/systemic treatments received, and outcomes. Results: 28 eligible patients were identified. Median age at retinoblastoma was.5 years, 89% occurred bilaterally. Retinoblastoma-therapy was by surgery in 26/27, radiotherapy in 26/27, chemotherapy in 10/26 (rest unknown). Osteosarcoma was diagnosed after 13.7 (3.1 – 36.1) years, extremities and head/neck affected in 14/28, each. Four/28 patients had primary metastases. Osteosarcoma treatment included chemotherapy in all cases, local therapy surgery in 27/28. Histological response was good in 9/16 evaluable cases. Surgery of all sites was macroscopically complete in 23/27 operated tumors and microscopically complete in 17/26 (1 unknown). Radiotherapy was administered to 3 craniofacial tumors. Median follow-up was 3.5 (.4 – 30.1) years from osteosarcoma diagnosis, 8/28 patients remaining event-free. Altogether, five patients suffered further secondary malignancies. Actuarial overall and event-free survival at 2 and 5 years from osteosarcoma were 73% (standard error: 8%) / 50% (10%) and 47% (10%) / 22% (9%), respectively. Conclusion: This comparatively large cohort of osteosarcomas after retinoblastoma proves that the latter may be treated curatively. While their prognosis is far worse than that of primary osteosarcomas, partly due to a predilection for craniofacial involvement, selected patients may still become long-term survivors with appropriate therapies.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Chemotherapy; Osteosarcoma; Prognosis; Radiotherapy; Retinoblastoma; Surgery

Oxygen-sensitive regulation and neuroprotective effects of growth hormone-dependent growth factors during early postnatal development - Jung, Susan; Boie, Gudrun; Dörr, Helmuth-Günther; Trollmann, Regina (American Journal of Physiology-Regulatory Integrative and Comparative Physiology, 2017)
Perinatal hypoxia severely disrupts metabolic and somatotrophic development, as well as cerebral maturational programs. Hypoxia-inducible transcription factors (HIFs) represent the most important endogenous adaptive mechanisms to hypoxia, activating a broad spectrum of growth factors that contribute to cell survival and energy homeostasis. To analyze effects of systemic hypoxia and growth hormone (GH) therapy (rhGH) on HIF-dependent growth factors during early postnatal development, we compared protein (using ELISA) and mRNA (using quantitative RT PCR) levels of growth factors in plasma and brain between normoxic and hypoxic mice (8% O2, 6 h; postnatal day 7, P7) at P14. Exposure to hypoxia led to reduced body weight (P < 0.001) and length (P < 0.04) compared with controls and was associated with significantly reduced plasma levels of mouse GH (P < 0.01) and IGF-1 (P < 0.01). RhGH abrogated these hypoxia-induced changes of the GH/IGF-1 axis associated with normalization of weight and length gain until P14 compared with controls. In addition, rhGH treatment increased cerebral IGF-1, IGF-2, IGFBP-2, and erythropoietin mRNA levels, resulting in significantly reduced apoptotic cell death in the hypoxic, developing mouse brain. These data indicate that rhGH may functionally restore hypoxia-induced systemic dysregulation of the GH/IGF-1 axis and induce upregulation of neuroprotective, HIF-dependent growth factors in the hypoxic developing brain.
EVALuna2:34028

Pädiatrische epileptische Enzephalopathien mit Manifestation oberhalb des Neugeborenenalters: ein Up-date - Trollmann, Regina; Borggräfe, Ingo; Müller-Felber, Wolfgang; Brandl, Ulrich (Klinische Neurophysiologie, 2021)
Developmental and epileptic encephalopathies represent complex and neurodegenerative disorders characterized by onset of refractory seizures usually in the first year of life and associated with motor and intellectual disability. The new ILAE classification of seizures and epilepsies proposed a revised definition of epileptic encephalopathies including electro-clinical phenotype as well as etiological spectrum and associated comorbidities. Modern genetic techniques led to the identification of a precise genotype in several electro-clinical syndromes such as West syndrome and Dravet syndrome. EEG continues to play a specific role as an additional tool in diagnosis and management of epileptic encephalopathies with special focus on the diagnosis of complications such as subclinical seizures and status epilepticus as well as treatment monitoring. This article reviews current aspects of complex pediatric epileptic encephalopathies and the significance of EEG monitoring.
CRIS-Team Scopus Importer:2021-09-24
Keywords: CSWS; Dravet syndrome; Landau-Kleffner syndrome; Lennox-Gastaut syndrome; West syndrome

Paediatric and adult soft tissue sarcomas with NTRK1 gene fusions: a subset of spindle cell sarcomas unified by a prominent myopericytic/haemangiopericytic pattern - Haller, Florian; Knopf, Jasmin; Ackermann, Andreas; Bieg, Matthias; Kleinheinz, Kortine; Schlesner, Matthias; Moskalev, Evgeny; Will, Rainer; Satir, Ali Abdel; Abdelmagid, Ibtihalat E.; Giedl, Josef; Carbon, Roman; et al. (Journal of Pathology, 2016)
Neoplasms with a myopericytomatous pattern represent a morphological spectrum of lesions encompassing myopericytoma of the skin and soft tissue, angioleiomyoma, myofibromatosis/infantile haemangiopericytoma and putative neoplasms reported as malignant myopericytoma. Lack of reproducible phenotypic and genetic features of malignant myopericytic neoplasms have prevented the establishment of myopericytic sarcoma as an acceptable diagnostic category. Following detection of a LMNA-NTRK1 gene fusion in an index case of paediatric haemangiopericytoma-like sarcoma by combined whole-genome and RNA sequencing, we identified three additional sarcomas harbouring NTRK1 gene fusions, termed 'spindle cell sarcoma, NOS with myo/haemangiopericytic growth pattern'. The patients were two children aged 11 months and 2 years and two adults aged 51 and 80 years. While the tumours of the adults were strikingly myopericytoma-like, but with clear-cut atypical features, the paediatric cases were more akin to infantile myofibromatosis/haemangiopericytoma. All cases contained numerous thick-walled dysplastic-like vessels with segmental or diffuse nodular myxohyaline myo-intimal proliferations of smooth muscle actin-positive cells, occasionally associated with thrombosis. Immunohistochemistry showed variable expression of smooth muscle actin and CD34, but other mesenchymal markers, including STAT6, were negative. This study showed a novel variant of myo/haemangiopericytic sarcoma with recurrent NTRK1 gene fusions. Given the recent introduction of a novel therapeutic approach targeting NTRK fusion-positive neoplasms, recognition of this rare but likely under-reported sarcoma variant is strongly encouraged.
EVALuna2:6792

Paediatric chronic myeloid leukaemia presenting in de novo or secondary blast phase - a comparison of clinical and genetic characteristics - Sembill, Stephanie; Goehring, Gudrun; Schirmer, Elke; Lutterloh, Friederike; Suttorp, Meinolf; Metzler, Markus; Karow, Axel (British Journal of Haematology, 2021)
Additional data on blast phase (BP) chronic myeloid leukaemia (CML) in children and adolescents is essential for improving diagnostic and therapeutic approaches of this rare but serious condition. Here, we describe distinct clinical and genetic characteristics of 18 paediatric patients with de novo (n = 10) and secondary (n = 8) BP CML enrolled in the CML-PAED-II trial and registry. Our findings suggest that paediatric patients exhibit a diverse cytogenetic profile compared to adults with BP CML. In addition, patients with de novo BP CML in this cohort presented at a younger age, whereas patients with secondary BP CML more often harboured complex karyotypes.
CRIS-Team Scopus Importer:2021-03-19
Keywords: ABL1 kinase domain mutations; blast phase; chemotherapy regimen; Chronic myeloid leukemia; cytogenetic aberrations; hematopoietic stem cell transplantation; pediatric chronic myeloid leukemia; tyrosine kinase inhibitor

Papilledema and Echographically Detectable Retro-orbital Dilatation of the Sub-arachnoidal Space with open Fontanelle - Six Case Reports - Gusek-Schneider, G. C.; Mardin, Christian Y.; Trollmann, Regina; Eyüpoglu, Ilker Yasin; Ganslandt, Oliver Thomas (Klinische Monatsblätter für Augenheilkunde, 2011)
This paper analyses the case reports for three children in which a papilledema occurred before the age of one year. Furthermore, an analysis is also given of three further case reports for children aged less than one year in which, in spite of open fontanelle, no papilledema was found, however, a dilatation of the sub-arachnoidal space was demonstrated echographically. Even in children less than one year of age in which an open fontanelle still exists and in whom a neuro-paediatric clarification of internal hydrocepalus is made, in spite of opththalmoscopically inconspicuous findings for the papilla an echography is indispensable for the evaluation of the sub-arachnoidal space. Here, the early recognition of a dilatation of the retro-bulbar sub-arachnoidal space can possibly prevent the occurrence of a consecutive optic atrophy. At the present time, the data available do not allow the recommendation of an upper age limit for an echographic examination.
EVALuna2:21040

Parecoxib does not suppress thromboxane synthesis in newborn piglets with group B streptococcal sepsis - Nögel, Stephanie; Chada, Martin; Schmidt, Ariana; Bosselmann, Stephan; Kandler, Michael; Schweer, Horst; Watzer, Bernhard; Schneider, Holm; Gessner, André; Rascher, Wolfgang (Prostaglandins & Other Lipid Mediators, 2009)
Group B streptococci (GBS) cause fatal sepsis in newborns. Strong activation of thromboxane synthesis is assumed to correlate with severe pulmonary hypertension. In this study we compared the impact of indomethacin versus parecoxib on hemodynamics and outcome and investigated the pharmacological effects on thromboxane synthesis and EP-3 receptor gene expression. Whereas both parecoxib and indometacin reduced expression of thromboxane synthase and EP-3 receptor in infected lung tissue, parecoxib did not suppress urine levels of thromboxane like indometacin. We presume that COX-2 inhibition in GBS sepsis is associated with enhanced thrombogenicity. © 2009 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Group b streptococcal sepsis; Parecoxib; Thromboxane

Partial homonymous hemianopia of traumatic origin after riding a high-speed amusement ride - Hohberger, B.; Trollmann, Regina; Rompel, O.; Gölitz, Philipp; Gusek-Schneider, G. C. (Ophthalmologe, 2016)
Amusement park injuries have become more common in recent years. Especially neurological symptoms dominate clinical findings. In this article, the case of a 15-year-old child with homonymous hemianopia due to an atypical intracranial bleeding with subdural hematoma after a giant swing ride is described for the first time.
EVALuna2:21326

Pathway to assess severe primary IGF-1 deficiency diagnosis in a real-life setting: data from the Global Increlex (R) Registry - Bang, Peter; Polak, Michel; Bossowski, Artur; De Schepper, Jean; Sert, Caroline; Perrot, Valerie; Wölfle, Joachim (HORMONE RESEARCH IN PAEDIATRICS, 2022)
CRIS-Team WoS Importer:2022-10-07

Patient-reported health-related quality of life (HRQOL) following allogeneic stem cell transplantation (SCT) performed early after diagnosis of pediatric chronic myeloid leukemia (CML) - Schleicher, O.; Horndasch, A.; Krumbholz, Manuela; Sembill, S.; Karow, A.; Bremensdorfer, C.; Grabow, D.; Metzler, Markus; Suttorp, M. (BONE MARROW TRANSPLANTATION, 2022)
CRIS-Team WoS Importer:2022-11-25

Patient-reported long-term outcome following allogeneic hematopoietic stem cell transplantation in pediatric chronic myeloid leukemia - Schleicher, Oliver; Horndasch, Annkathrin; Krumbholz, Manuela; Sembill, Stephanie; Bremensdorfer, Claudia; Grabow, Desiree; Erdmann, Friederike; Karow, Axel; Metzler, Markus; Suttorp, Meinolf (Frontiers in Oncology, 2022)
BackgroundPediatric CML is very rare. Before the introduction of tyrosine kinase inhibitors (TKIs), allogeneic hematopoietic stem cell transplantation (HSCT) from a donor -if available- was the standard cure attempt. Data on the long-term outcome and health-related quality of life (HRQOL) in former pediatric CML patients undergoing HSCT are lacking. Study questionWe investigated long-term survivors' self-reporting to a questionnaire sent out to patients formerly enrolled in pediatric CML-HSCT trials. MethodsIndividuals with CML transplanted at age <18 years were identified from the German Childhood Cancer Registry database. Long-term survivors received a questionnaire based on the SF-36 and FACT-BMT asking them to self-report HRQOL issues. (Ethical vote #541_20 B, Medical Faculty, University of Erlangen-Nurnberg). Results111/171 (64.9%) individuals survived HSCT long-term and 86/111 (77.5%) fulfilled all inclusion criteria and received the questionnaire. 37/86 (43%) participants (24 female, 13 male, median age at HSCT 12 years [range 2-18], median age at the time of the survey 29 years [range 18-43]) responded after a median follow-up period of 19 years (range 4-27) after HSCT. 10/37 (27%) participants underwent no regular medical follow-up examinations. Self-reported symptoms like chronic graft-versus-host disease (cGvHD)-associated organ impairments and conditioning regimen consequences could causatively not sharply be separated in each case. Complains comprised hypothyroidism (N=11, 30%), infertility (N=9, 24%), lung problems, dry eyes (each N=7, 19%), skin alterations (N=6, 17%), hair problems (N=4, 11%), and sexual dysfunction (N=3, 9%). 10 (27%) participants experienced 13 CML relapses after a median interval from HSCT of 31 months (range 2-93). Only one patient underwent 2nd SCT after failure of relapse treatment with TKIs. Six secondary malignancies (dysplastic melanocytic nevus and ALL, basal cell carcinoma (N=2), rhabdomyosarcoma, and thyroid carcinoma developed in 5 (13%) participants. As assessed by the SF-36 questionnaire, impaired physical health was mainly associated with cGvHD. The mental component summary score showed that also participants without cGvHD scored significantly lower than the general population. When assessed by the FACT-BMT, participants with cGvHD scored significantly lower while participants without cGvHD scored even 5 points higher than the data from controls. 18 (49%) participants considered the sequelae of HSCT an obstacle to education. Out of the total cohort, N=20 (54%), N=7 (19%), N=5 (14%), and N=4 (11%) participants worked full time, part-time, were unemployed, or had not yet finalized their education, respectively. 20 (54%) participants lived as singles, 8 (22%) lived in a partnership, 6 (16%) were married, and 3 (8%) had been divorced. Four (11%) participants reported a total number of 7 children. ConclusionThis first assessment of HRQOL in former pediatric patients with CML surviving HSCT for more than two decades demonstrates self-reported satisfactory well-being only in the absence of cGvHD. Research-based on self-reported outcomes sheds light on former patients' perspectives and provides an additional layer of valuable knowledge for pediatric and adult hematologists. Regular follow-up examinations are mandatory helping to avoid that late secondary neoplasias, CML-relapse, and disorders forming the broad range of possible long-term consequences of HSCT are not detected too late.
CRIS-Team WoS Importer:2022-11-04

Pediatric Buried Bumper Syndrome: Diagnostic Validity of Transabdominal Ultrasound and Artificial Intelligence - Aguilar, Caroline; Regensburger, Adrian; Knieling, Ferdinand; Wagner, Alexandra; Siebenlist, Gregor; Wölfle, Joachim; Koehler, Henrik; Hörning, André; Jüngert, Jörg M. (Ultraschall in der Medizin, 2021)
Zusammenfassung
CRIS-Team WoS Importer:2021-06-04

Pediatric chronic myeloid leukemia is a unique disease that requires a different approach - Hijiya, Nobuko; Schultz, Kirk R.; Metzler, Markus; Millot, Frederic; Suttorp, Meinolf (Blood, 2016)
Chronic myelogenous leukemia (CML) in children is relatively rare. Because of a lack of robust clinical study evidence, management of CML in children is not standardized and often follows guidelines developed for adults. Children and young adults tend to have a more aggressive clinical presentation than older adults, and prognostic scores for adult CML do not apply to children. CML in children has been considered to have the same biology as in adults, but recent data indicate that some genetic differences exist in pediatric and adult CML. Because children with CML may receive tyrosine kinase inhibitor (TKI) therapy for many decades, and are exposed to TKIs during a period of active growth, morbidities in children with CML may be distinct from those in adults and require careful monitoring. Aggressive strategies, such as eradication of CML stem cells with limited duration and intensive regimens of chemotherapy and TKIs, may be more advantageous in children as a way to avoid lifelong exposure to TKIs and their associated adverse effects. Blood and marrow transplantation in pediatric CML is currently indicated only for recurrent progressive disease, and the acute and long-term toxicities of this option should be carefully evaluated against the complications associated with lifelong use of TKIs.
EVALuna2:33877

Pediatric Colorectal Carcinoma is Associated With Excellent Outcome in the Context of Cancer Predisposition Syndromes - Weber, Marie; Schneider, Dominik T.; Offenmüller, Sonja; Kaatsch, Peter; Einsiedel, Hagen Graf; Benesch, Martin; Claviez, Alexander; Ebinger, Martin; Kramm, Christof; Kratz, Christian; Lawlor, Jennifer; Leuschner, Ivo; et al. (Pediatric Blood & Cancer, 2016)
Colorectal carcinoma (CRC) is the second most common adult cancer in Germany, however, it is extremely rare in children and adolescents. In these patients, previous literature describes aggressive behavior and diagnosis at advanced stage.Thirty-one patients with CRC age <= 18 years and treated between 1990 and 2012 have been identified through the structures and registries of the German Society for Pediatric Oncology and Hematology.The age range was 9-18 years (median 13.5 years); the median follow-up time was 43.9 months (range 1-124 months). Twenty-six patients (84%) were tested for a genetic tumor syndrome (GTS); of these, 11 patients (35% of all patients) tested positive (eight cases of Lynch syndrome, one patient with familial adenomatous polyposis, two patients with constitutional mismatch repair deficiency). An unfavorable histology was reported in 55% of the records (n = 17), a poor differentiation (grade III) in 68% of carcinoma (n = 21). Overall survival (OS) and event-free survival at 5 years was 52.0% and 65.6%, respectively. Five-year survival according to stage was 100% in stage II (n = 2), 100% in stage III (n = 13), and 12.9% in stage IV (n = 15; P < 0.001). Five-year OS in patients with and without a defined GTS was 100% and 36.5% (P = 0.019), respectively.Children and adolescents with CRC are frequently diagnosed in advanced stages and have an unfavorable prognosis. In this study, a high percentage of pediatric CRC patients presented with a tumor predisposition syndrome and showed an especially favorable OS.
EVALuna2:15175

Pediatric Mesothelioma With ALK Fusions: A Molecular and Pathologic Study of 5 Cases - Argani, Pedram; Lian, Derrick W.Q.; Agaimy, Abbas; Metzler, Markus; Wobker, Sara E.; Matoso, Andres; Epstein, Jonathan I.; Sung, Yun Shao; Zhang, Lei; Antonescu, Cristina R. (American Journal of Surgical Pathology, 2021)
Pediatric mesotheliomas are rare and their pathogenesis remains undefined. In this study, we report 5 cases of malignant mesothelioma in children, characterized by fusions involving the anaplastic lymphoma kinase (ALK) gene. Four cases occurred in females involving the abdominal cavity and were characterized by a pure epithelioid morphology. The fifth arose in the tunica vaginalis of a 15-year-old male and displayed a biphasic epithelioid-sarcomatoid phenotype. All cases demonstrated the classic morphologic and immunohistochemical features of malignant mesothelioma, including tubulopapillary architecture and cuboidal epithelioid cells with eosinophilic cytoplasm and uniform nuclei with vesicular chromatin. Immunohistochemically, all cases showed labeling for ALK, cytokeratins, WT1, and calretinin, while lacking expression of adenocarcinoma immunomarkers. Four cases demonstrated weak-moderate labeling for PAX8 protein, which resulted in diagnostic challenges with primary peritoneal serous carcinoma. The ALK genetic abnormalities were investigated by a combination of molecular methods. Archer FusionPlex was performed in 2 cases, showing fusions between ALK with either STRN or TPM1 genes, resulting in a transcript that retained the ALK kinase domain. One case was further studied by DNA targeted sequencing, but no additional genetic alterations were observed. In 1 case, cytogenetic analysis showed the presence of a t(2;15)(p23;q22) and fluorescence in situ hybridization confirmed the ALK gene break-apart. In the remaining 2 cases, ALK gene rearrangements were demonstrated by fluorescence in situ hybridization. Unlike adult mesotheliomas, which are tightly linked to asbestos exposure, often show loss of BAP1 expression and have complex karyotypes, ALK-rearranged mesothelioma appears to be similar to other fusion-positive mesotheliomas, such as those harboring EWSR1/FUS-ATF1 fusions, sharing significant morphologic overlap, occurring in young patients and displaying a simple, translocation-driven genetic profile.
CRIS-Team Scopus Importer:2021-04-23

Pediatric reference intervals for alkaline phosphatase - Zierk, Jakob; Arzideh, Farhad; Haeckel, Rainer; Cario, Holger; Fruehwald, Michael C.; Gross, Hans-Juergen; Gscheidmeier, Thomas; Hoffmann, Reinhard; Krebs, Alexander; Lichtinghagen, Ralf; Neumann, Michael; Ruf, Hans-Georg; et al. (Clinical Chemistry and Laboratory Medicine, 2017)
BACKGROUND: Interpretation of alkaline phosphatase activity in children is challenging due to extensive changes with growth and puberty leading to distinct sex- and age-specific dynamics. Continuous percentile charts from birth to adulthood allow accurate consideration of these dynamics and seem reasonable for an analyte as closely linked to growth as alkaline phosphatase. However, the ethical and practical challenges unique to pediatric reference intervals have restricted the creation of such percentile charts, resulting in limitations when clinical decisions are based on alkaline phosphatase activity. METHODS: We applied an indirect method to generate percentile charts for alkaline phosphatase activity using clinical laboratory data collected during the clinical care of patients. A total of 361,405 samples from 124,440 patients from six German tertiary care centers and one German laboratory service provider measured between January 2004 and June 2015 were analyzed. Measurement of alkaline phosphatase activity was performed on Roche Cobas analyzers using the IFCC's photometric method. RESULTS: We created percentile charts for alkaline phosphatase activity in girls and boys from birth to 18 years which can be used as reference intervals. Additionally, data tables of age- and sex-specific percentile values allow the incorporation of these results into laboratory information systems. CONCLUSIONS: The percentile charts provided enable the appropriate differential diagnosis of changes in alkaline phosphatase activity due to disease and changes due to physiological development. After local validation, integration of the provided percentile charts into result reporting facilitates precise assessment of alkaline phosphatase dynamics in pediatrics.
EVALuna2:34216

Permissive hypercapnia in extremely low birthweight infants (PHELBI): a randomised controlled multicentre trial - Thome, Ulrich H.; Genzel-Boroviczeny, Orsolya; Bohnhorst, Bettina; Schmid, Manuel; Fuchs, Hans; Rohde, Oliver; Avenarius, Stefan; Topf, Hans-Georg; Zimmermann, Andrea; Faas, Dirk; Timme, Katharina; Kleinlein, Barbara; et al. (The Lancet Respiratory Medicine, 2015)
Tolerating higher partial pressure of carbon dioxide (pCO2) in mechanically ventilated, extremely low birthweight infants might reduce ventilator-induced lung injury and bronchopulmonary dysplasia. We aimed to test the hypothesis that higher target ranges for pCO2 decrease the rate of bronchopulmonary dysplasia or death.In this randomised multicentre trial, we recruited infants from 16 tertiary care perinatal centres in Germany with birthweight between 400 g and 1000 g and gestational age 23-28 weeks plus 6 days, who needed endotracheal intubation and mechanical ventilation within 24 h of birth. Infants were randomly assigned to either a high target or control group. The high target group aimed at pCO2 values of 55-65 mm Hg on postnatal days 1-3, 60-70 mm Hg on days 4-6, and 65-75 mm Hg on days 7-14, and the control target at pCO2 40-50 mmHg on days 1-3, 45-55 mm Hg on days 4-6, and 50-60 mm Hg on days 7-14. The primary outcome was death or moderate to severe bronchopulmonary dysplasia, defined as need for mechanical pressure support or supplemental oxygen at 36 weeks postmenstrual age. Cranial ultrasonograms were assessed centrally by a masked paediatric radiologist. This trial is registered with the ISRCTN registry, number ISRCTN56143743.Between March 1, 2008, and July 31, 2012, we recruited 362 patients of whom three dropped out, leaving 179 patients in the high target and 180 in the control group. The trial was stopped after an interim analysis (n=359). The rate of bronchopulmonary dysplasia or death in the high target group (65/179 [36%]) did not differ significantly from the control group (54/180 [30%]; p=0·18). Mortality was 25 (14%) in the high target group and 19 (11%; p=0·32) in the control group, grade 3-4 intraventricular haemorrhage was 26 (15%) and 21 (12%; p=0·30), and the rate of severe retinopathy recorded was 20 (11%) and 26 (14%; p=0·36).Targeting a higher pCO2 did not decrease the rate of bronchopulmonary dysplasia or death in ventilated preterm infants. The rates of mortality, intraventricular haemorrhage, and retinopathy did not differ between groups. These results suggest that higher pCO2 targets than in the slightly hypercapnic control group do not confer increased benefits such as lung protection.Deutsche Forschungsgemeinschaft.
EVALuna2:18882

Pharmacodynamic Effect of mTOR Inhibition-based Immunosuppressive Therapy on T- and B-cell Subsets After Renal Transplantation - Wei, Xinyi; Weber, Sabine; Yin, Decheng; Allabauer, Ida; Jobst-Schwan, Tilman; Wiesener, Michael; Schiffer, Mario; Dudziak, Diana; Lehmann, Christian; Wölfle, Joachim; Hörning, André (Transplantation Direct, 2024)
Background. The mammalian target of rapamycin inhibitor (mTORi) therapy after kidney transplantation is solely monitored pharmacokinetically, not necessarily reflecting PI3K-Akt-mTOR pathway blockade efficacy leading to potential under- or overimmunosuppression. Methods. In this cross-sectional study, phosphoflow cytometry was used to determine the efficacy of mTOR inhibition in peripheral T- and B-lymphocyte subsets by assessing p70S6 kinase (p70S6K) phosphorylation in renal transplant recipients upon treatment with a combination of either mTORi and calcineurin inhibitors (n = 18), or mTORi with mycophenolic acid (n = 9). Nine dialysis patients with end-stage renal disease and 17 healthy age-matched volunteers served as controls. Results. mTORi treatment reduced p70S6K phosphorylation in CD4+, CD8+ T, and CD19+ B cells compared with healthy controls (HCs). Subpopulation analysis of CD4+ T cells and CD19+ B cells revealed a significant reduction of p70S6K phosphorylation in CD4+CD45RA−CD25− Th cells (P < 0.05), CD24hiCD38hi transitional B cells (P < 0.001), CD24+CD38− memory B cells (P < 0.001), and CD24intCD38int-naive B cells (P < 0.05) upon mTORi treatment, whereas CD4+CD45RA−CD25++CD127− regulatory T cells and CD24−CD38hi plasmablasts were not affected. Compared with mTORi + mycophenolic acid therapy, mTORi + calcineurin inhibitor treatment exhibited an even stronger inhibition of p70S6K phosphorylation in CD4+CD45RA−CD25− Th cells and CD8+ T cells. However, trough levels of mTORi did not correlate with p70S6K phosphorylation. Conclusions. mTORi selectively inhibited p70S6K phosphorylation in select lymphocyte subtypes. Assessing p70S6K phosphorylation by phosphoflow cytometry may serve as an approach to understand cell subset specific effects of mTORi providing detailed pharmacodynamic information for individualizing immunosuppression.
CRIS-Team Scopus Importer:2024-07-19

Pharmacokinetic–pharmacodynamic modeling of maintenance therapy for childhood acute lymphoblastic leukemia - Gebhard, Anna; Lilienthal, Patrick; Metzler, Markus; Rauh, Manfred; Sager, Sebastian; Schmiegelow, Kjeld; Toksvang, Linea Natalie; Zierk, Jakob (Scientific Reports, 2023)
In the treatment of childhood acute lymphoblastic leukemia (ALL), current protocols combine initial high-dose multiagent chemotherapy with prolonged oral therapy with 6-mercaptopurine (6MP) and low-dose methotrexate (MTX) maintenance therapy. Decades of research on ALL treatment have resulted in survival rates of approximately 90%. However, dose-response relationships vary widely between patients and insight into the influencing factors, that would allow for improved personalized treatment management, is insufficient. We use a detailed data set with measurements of thioguanine nucleotides and MTX in red blood cells and absolute neutrophil count (ANC) to develop pharmacokinetic models for 6MP and MTX, as well as a pharmacokinetic–pharmacodynamic (PKPD) model capable of predicting individual ANC levels and thus contributing to the development of personalized treatment strategies. Here, we show that integrating metabolite measurements in red blood cells into the full PKPD model improves results when less data is available, but that model predictions are comparable to those of a fixed pharmacokinetic model when data availability is not limited, providing further evidence of the quality of existing models. With this comprehensive model development leading to dynamics similar to simpler models, we validate the suitability of this model structure and provide a foundation for further exploration of maintenance therapy strategies through simulation and optimization.
CRIS-Team Scopus Importer:2023-09-08

Pharmacologic stabilization of hypoxia-inducible transcription factors protects developing mouse brain from hypoxia-induced apoptotic cell death - Trollmann, Regina; Richter, Markus; Jung, Susan; Walkinshaw, G.; Brackmann, Florian (Neuroscience, 2014)
Accumulation of hypoxia-inducible transcription factors (HIFs) by prolyl-4-hydroxylase inhibitors (PHI) has been suggested to induce neuroprotection in the ischemic rodent brain. We aimed to investigate in vivo effects of a novel PHI on HIF-regulated neurotrophic and pro-apoptotic factors in the developing normoxic and hypoxic mouse brain.Neonatal mice (P7) were treated with PHI FG-4497 (30-100mg/kg, i.p.) followed by exposure to systemic hypoxia (8% O2, 6h) 4h later. Cerebral expression of HIF?-subunits, specific neurotrophic and vasoactive target genes (vascular endothelial growth factor (VEGF), adrenomedullin (ADM), erythropoietin (EPO), inducible nitric oxide synthase (iNOS)) as well as pro-apoptotic (BCL2/adenovirus E1B 19-kDa protein-interacting protein 3 gene (BNIP3), immediate early response 3 (IER3)) and migratory factors (chemokine receptor 4 (CXCR4), stromal cell-derived factor 1 (SDF-1)) was determined (quantitative real-time (RT)., Western blot analysis) in comparison to controls. Apoptotic cell death was analyzed by terminal desoxynucleotidyl transferase-mediated dUTP-biotin nick end labeling (TUNEL) and cleaved caspase 3 (CC3) staining.Under normoxic conditions, FG-4497 treatment significantly induced the accumulation of both HIF-1? and HIF-2? isoforms in developing mouse brain. In addition, there was a significant up-regulation of HIF target genes (VEGF, ADM, EPO, CXCR4, p<0.01) with FG-4497 treatment compared to controls supporting functional activation of the HIF proteins. Under hypoxia, differential target gene activation was observed in the developing brain including additive effects of FG-4497 and hypoxia on mRNA expression of VEGF and ADM as well as a dose-dependent down-regulation of iNOS. BNIP3 but not IER3 mRNA levels significantly increased in hypoxic brains pre-treated with high-dose FG-4497 compared to controls. Of special interest, FG-4497 treatment significantly diminished apoptotic cell death, quantified by TUNEL and CC3-positive cells, in hypoxic developing brains compared to controls.PHI treatment modulates neurotrophic factors known to be crucially involved in hypoxia-induced cerebral adaptive mechanisms as well as early brain maturation. Pre-treatment with FG-4497 seems to protect the developing brain from hypoxia-induced apoptosis. Present observations provide basic information for further evaluation of neuroprotective properties of PHI treatment in hypoxic injury of the developing brain. However, potential effects on maturational processes need special attention in experimental research targeting HIF-dependent neuroprotective interventions during the very early stage of brain development.
EVALuna2:18900

Pharmacology and pharmacokinetics of imatinib in pediatric patients - Suttorp, Meinolf; Bornhaeuser, Martin; Metzler, Markus; Schleyer, Eberhard; Millot, Frederic (Expert Review of Clinical Pharmacology, 2018)
INTRODUCTION: The tyrosine kinase inhibitor (TKI) imatinib was rationally designed to target BCR-ABL1 which is constitutively activated in chronic myeloid leukemia (CML). Following the tremendous success in adults, imatinib also became licensed for treatment of CML in minors. The rarity of pediatric CML hampers the conduction of formal trials. Thus, imatinib is still the single TKI approved for CML treatment in childhood. Areas covered: This review attempts to provide an overview of the literature on pharmacology, pharmacokinetic, and pharmacogenetic of imatinib concerning pediatric CML treatment. Articles were identified through a PubMed search and by reviewing abstracts from relevant hematology congresses. Additional information was provided from the authors' libraries and expertise and from our own measurements of imatinib trough plasma levels in children. Pharmacokinetic variables (e.g. alpha 1-acid glycoprotein binding, drug-drug/food-drug interactions via cytochrome P450 3A4/5, cellular uptake mediated via OCT-1-influx variations and P-glycoprotein-mediated drug efflux) still await to be addressed in pediatric patients systematically. Expert commentary: TKI response rates vary among different individuals and pharmacokinetic variables all can influence CML treatment success. Adherence to imatinib intake may be the most prominent factor influencing treatment outcome in teenagers thus pointing towards the potential benefits of regular drug monitoring.
EVALuna2:34299

Phenylbutyrate Treatment in a Boy With MCT8 Deficiency: Improvement of Thyroid Function Tests and Possible Hepatotoxicity. - Schreiner, Felix; Vollbach, Heike; Sonntag, Niklas; Schempp, Vera; Gohlke, Bettina; Friese, Johannes; Wölfle, Joachim; Braun, Doreen; Schweizer, Ulrich (Journal of Clinical Endocrinology and Metabolism, 2025)
CONTEXT: Monocarboxylate transporter 8 (MCT8) deficiency is a rare X-chromosomal inherited disease leading to severe cognitive impairment, muscular hypotonia, and symptoms of peripheral thyrotoxicosis. Experimental approaches aiming to functionally rescue mutant MCT8 activity by the chemical chaperone phenylbutyrate (PB) demonstrated promising effects in vitro for several MCT8 missense mutations. OBJECTIVE: The objective was to evaluate biochemical and clinical effects of PB in doses equivalent to those approved for the treatment of urea cycle disorders in a boy with MCT8 deficiency due to a novel MCT8 missense mutation c.703G>T (p.V235L). RESULTS: During a treatment period of 13 months, PB led to a significant decrease of elevated thyrotropin and triiodothyronine (T3) serum concentrations, while free thyroxine (fT4) increased. The weight z-score of the toddler remained remarkably stable during the treatment period. Neurodevelopmental assessments (BSID-III) revealed a slight increase of gross motor skills from developmental age 4 to 6 months. However, increasing liver enzyme serum activities and accumulation of phenylacetate in urine led to treatment interruptions and dose alterations. In vitro analyses in MDCK1 cells confirmed the pathogenicity of MCT8 p.V235L. However, while PB increased expression of the mutant protein, it did not rescue T3 transport, suggesting a PB effect on thyroid function tests independent of restoring MCT8 activity. CONCLUSION: In a clinical attempt of PB treatment in MCT8 deficiency we observed a significant improvement of thyroid hormone function tests, tendencies toward body weight stabilization and slight neurodevelopmental improvement. Hepatotoxicity of PB may be a limiting factor in MCT8 deficiency and requires further investigation.
EVALuna2:586368

Phosphate Intoxication after Application of Enema - a Life-threatening Iatrogenic Complication - Marek, I.; Benz, Kerstin; Kusnik, Stefan; Morhart, P.; Botzenhardt, S.; Toni, I.; Rascher, Wolfgang (Klinische Pädiatrie, 2015)
Enemas are used in pediatric patients with constipation. Retention of phosphate containing enemas with prolonged resorption or reduced renal elimination of phosphate can result in life-threatening hyperphosphatemia with subsequent lethal hypocalcemia and acidosis.We report the case of a 6-month-old child who received phosphate-containing enema to treat acute aggravation of constipation. The used enema here was not licensed for this age group. Phosphate intoxication resulted (phosphate 19.87 mmol/l) and presented like a sepsis. Hyperphosphatemia was treated by hemodialysis. A non-diagnosed Hirschsprung disease had led to prolonged resorption of phosphate containing enema and to an ileus and toxic megacolon that had to be operated.Insufficient elimination of phosphate containing enema can result in lethal or life threatening hyperphosphatemia, hypocalcemia and metabolic acidosis. These can be treated efficaciously by hemodialysis. Because of the high risk of intoxication in using enemas containing phosphate in infants or in patients with gastrointestinal or renal comorbidities, physicians treating constipation should choose enemas without phosphate but with ingredients with lower risk like glycerol or sorbitol in this age group.
EVALuna2:18933

Postnatal management of preterm infants with spinal muscular atrophy: experience from German newborn screening - Trollmann, Regina; Johannsen, Jessika; Vill, Katharina; Köhler, Cornelia; Hahn, Andreas; Illsinger, Sabine; Pechmann, Astrid; Hagen, Maja von der; Müller-Felber, Wolfgang (Orphanet Journal of Rare Diseases, 2024)
Background: The introduction of newborn screening (NBS) for spinal muscular atrophy (SMA) has increased the early diagnosis of 5q-associated SMA in presymptomatic and symptomatic preterm infants. National and international recommendations for treating preterms and newborns < 38 weeks of gestational age are unavailable. Our retrospective multicentre study aimed to evaluate the postnatal clinical course of preterm infants with 5q-associated SMA diagnosed since the implementation of NBS in Germany in 2021 and to summarize the German experience regarding the decision-making process for available treatment regimens for preterm infants with ≤ 3 survival of motor neuron 2 (SMN2) copies. Results: Twelve preterm infants with 5q-associated SMA and a mean gestational age of 34.0 weeks (range: 26.1–36.8) and birth weight of 2022 g (range: 645–3370) were reported from 8/20 German SMA NBS follow-up centers using a pseudonymized questionnaire. Confirmatory diagnosis, including SMN2 copy number, was completed on average on postnatal day 13. All patients had a biallelic deletion of exon 7 or exons 7 and 8 of the survival of motor neuron 1 (SMN1) gene, with SMN2 copy numbers of two in 10 patients and three in two patients. The neonatal course was complicated by respiratory distress due to prematurity (n = 2), sepsis (n = 2), and jaundice (n = 2). At birth, 11 preterm infants (91.6%) were presymptomatic. However, the neurological status of one patient deteriorated at five weeks of age (postconceptional age of 41.8 weeks) prior to the start of treatment. Disease-modifying treatments were initiated in all patients at a mean postconceptional age of 38.8 weeks, with the majority receiving onasemnogene abeparvovec (83.3%, including 2 patients with prior risdiplam bridge therapy). Notably, consensus among participating experts from German neuromuscular centers resulted in 83.3% of patients receiving disease-modifying treatment at term. Conclusions: Premature infants with SMA require interdisciplinary care in close collaboration with the neuromuscular center. SMA NBS facilitates early initiation of disease-modifying therapy, ideally during the presymptomatic phase, which significantly influences the prognosis of the newborn.
CRIS-Team Scopus Importer:2024-10-04
Keywords: 5q-SMA; Newborn screening; Nusinersen; Onasemnogene Abeparvovec; Preterm infants; Risdiplam; SMA treatment; Spinal muscular atrophy

Postoperative pain in small-for-gestational age infants after hernia repair, orchidopexy and urethral reconstruction surgery: A pilot study - Schüssler, Stephanie C.; Kußmann, Franziska; Fahlbusch, Fabian B.; Münster, Tino; Hirsch, Karin; Carbon, Roman; Albrecht, Sven; Dötsch, Jörg; Rascher, Wolfgang (Early Human Development, 2019)
Background: Small-for-gestational-age (SGA) birth bears an enhanced risk of developing hypertension, obesity, insulin resistance and mental health disorders in later life as a consequence of adaptive processes in utero. Only a small number of studies on pain perception in SGA infants exist. These are indicative of a blunted stress response to pain in SGA newborns. Aim: We initiated a pilot study investigating differences in postoperative pain perception between SGA and appropriate-for-gestational-age (AGA) infants. Methods: Pain and alertness levels of 10 formerly SGA and 14 AGA infants at the age 0.5–2 years were evaluated by the FLACC scale, Steward and Aldrete Scores following hernia repair, reconstructive surgery of hypospadia and orchidopexy. In addition, the postoperative consumption of non-steroidal anti-inflammatory drugs was compared between SGA and AGA. Results: Postoperative pain and alertness levels were not significantly different in SGA and AGA children. We did not observe significant group differences regarding the consumption of non-steroidal anti-inflammatory drugs. Conclusion: While previous studies were suggestive of a suppressed stress response to pain in SGA newborns, these findings did not fully translate into an altered response to pain beyond the newborn age. Further studies in a larger cohort seem necessary to verify this finding.
CRIS-Team Scopus Importer:2019-07-16

Potential for Radiation Dose Reduction in Dual-Source Computed Tomography of the Lung in the Pediatric and Adolescent Population Compared to Digital Radiography - Wetzl, Matthias; May, Matthias; Weinmann, Daniel; Hammon, Matthias; Kopp, Markus; Ruppel, Renate; Trollmann, Regina; Wölfle, Joachim; Uder, Michael; Rompel, Oliver (Diagnostics, 2021)
Low-dose dual-source computed tomography (DSCT) protocols for the evaluation of lung diseases in children and adolescents are of importance since this age group is particularly prone to radiation damage. The aim of this study was to evaluate image quality of low-dose DSCT of the lung and to assess the potential of radiation dose reduction compared to digital radiographs (DR). Three groups, each consisting of 19 patients, were examined with different DSCT protocols using tin prefiltration (Sn96/64/32 ref. mAs at 100 kV). Different strengths of iterative reconstruction were applied (ADMIRE 2/3/4). DSCT groups were compared to 19 matched patients examined with posterior-anterior DR. Diagnostic confidence, detectability of anatomical structures and small lung lesions were evaluated on a 4-point Likert scale (LS 1 = unacceptable, 4 = fully acceptable; a value >= 3 was considered acceptable). Effective dose (ED) was 31-/21-/9-fold higher in Sn96/Sn64/Sn32 compared to DR. Diagnostic confidence was sufficient in Sn96/Sn64 (LS 3.4/3.2), reduced in Sn32 (LS 2.7) and the worst in DR (LS 2.4). In DSCT, detectability of small anatomical structures was always superior to DR (p < 0.05). Mean lesion size ranged from 5.1-7 mm; detectability was acceptable in all DSCT groups (LS 3.0-3.4) and superior to DR (LS 1.9; p < 0.05). Substantial dose lowering in DSCT of the pediatric lung enables acceptable detectability of small lung lesions with a radiation dose being about 10-fold higher compared to DR.
CRIS-Team WoS Importer:2021-03-12

Precision of handheld multispectral optoacoustic tomography for muscle imaging - Wagner, Anna; Danko, Vera; Federle, Anna; Klett, Daniel; Simon, David; Heiß, Rafael; Jüngert, Jörg M.; Uder, Michael; Schett, Georg; Neurath, Markus; Wölfle, Joachim; Waldner, Maximilian; et al. (Photoacoustics, 2021)
Photo-or optoacoustic imaging (OAI) allows quantitative imaging of target tissues. Using multi-wavelength illumination with subsequent ultrasound detection, it may visualize a variety of different chromophores at centimeter depth. Despite its non-invasive, label-free advantages, the precision of repeated measurements for clinical applications is still elusive. We present a multilayer analysis of n = 1920 imaging datasets obtained from a prospective clinical trial (NCT03979157) in n = 10 healthy adult volunteers. All datasets were analyzed for 13 single wavelengths (SWL) between 660 nm–1210 nm and five MSOT-parameters (deoxygenated/oxygenated/total hemoglobin, collagen and lipid) by a semi-automated batch mode software. Intraclass correlation coefficients (ICC) were good to excellent for intrarater (SWL: 0.82–0.92; MSOT-parameter: 0.72−0.92) and interrater reproducibility (SWL: 0.79−0.87; MSOT-parameter: 0.78−0.86), with the exception for MSOT-parameter lipid (interrater ICC: 0.56). Results were stable over time, but exercise-related effects as well as inter-and intramuscular variability were observed. The findings of this study provide a framework for further clinical OAI implementation.
CRIS-Team Scopus Importer:2020-12-25
Keywords: MSOT; Multispectral optoacoustic tomography; Muscle imaging; Optoacoustics; Photoacoustics

Predicting complications in paediatric ulcerative colitis: A longitudinal multicentre cohort study - Claßen, Merle; Schiller, Benjamin; Däbritz, Jan; Buderus, Stephan; Bufler, Philip; Claßen, Martin; Dammann, Söhnke; de Laffolie, Jan; Friedt, Michael; Hauer, Almuthe Christina; Keller, Klaus Michael; Krahl, Andreas; et al. (Alimentary Pharmacology & Therapeutics, 2024)
Background: To prevent complications of paediatric ulcerative colitis (UC), it is critical to understand their predictors. The Paediatric Inflammatory Bowel Disease Ahead (PIBD Ahead) program identified the relevant outcomes and their potential predictors. However, external validation of these results in larger cohorts is required. Aims: The aim of this study is to investigate these outcomes and their predictors. Methods: We included 743 patients aged under 18 years with UC from the multicentre German-Austrian CEDATA-GPGE registry. We performed Cox regressions, Kaplan–Meier estimator, and receiver operating characteristics curve analyses to analyse predictors of poor outcomes. Results: Older age at diagnosis was associated with relapse, hospitalisation, the use of immunomodulators, use of biologics, and therapy escalation. Higher disease activity, as in acute severe colitis in the first 3 months, was significantly associated with further acute severe colitis and the need for biologics. Upper gastrointestinal tract involvement was a risk factor for the need of intravenous corticosteroids and biologics. A faecal calprotectin of >685 μg/g was associated with a higher risk of subsequent acute severe colitis with a sensitivity of 79.0% and a specificity of 59.1%. A lower haematocrit at diagnosis was predictive of the use of biologics. Colectomy was rare. Conclusions: This study validates predictors of poor outcomes in paediatric patients with UC. Our results might help physicians to anticipate poor outcomes and initiate appropriate treatment strategies at an early stage.
CRIS-Team Scopus Importer:2024-09-20

Prediction of phenotypes by secretory biomarkers and machine learning in patients with chronic rhinosinusitis - Becker, Mathias; Kist, A. M.; Wendler, O.; Pesold, V. V.; Bleier, B. S.; Mueller, S. K. (European Review for Medical and Pharmacological Sciences, 2025)
OBJECTIVE: Chronic rhinosinusitis (CRS) has traditionally been classified phenotypically according to the presence (CRSwNP) or absence (CRSsNP) of nasal polyps. However, the phenotypic dichotomy does not represent the complexity of the disease. Current research thus focuses on identifying underlying inflammatory mechanisms and distinguishing different endotypes. The objectives of this study were 1) to identify maximally predictive non-invasive biomarkers from nasal mucus, 2) to apply machine learning algorithms to use mucus-derived biomarkers to classify phenotype, and 3) to determine the feature importance of each mucus biomarker to phenotypes. PATIENTS AND METHODS: This is an IRB-approved study of 103 CRS patients (37 CRSsNP, 66 CRSwNP). Nasal mucus was collected using merocele sponges after a 3-week steroid washout period. The nasal mucus was then examined for twelve cytokines/inflammatory protein biomarkers, including interferon (IFN)-γ, interleukin (IL)-4, -5, -17A, -22, immunoglobulin (Ig) E, cystatin-SA (CST-2), eosinophilic cationic protein (ECP), matrix metalloproteinase-9 (MMP-9), pappalysin-A (PAPP-A), periostin, and serpin E1. Protein concentrations were determined by ELISAs and Luminex assays. For phenotype classification, different artificial intelligence algorithms in increasing complexity, including t-distributed stochastic neighbor embedding (t-SNE), Adaboost, and XGBoost, were applied to the data from the biomarker analysis. RESULTS: TThe analysis showed that IL-5 is a non-invasive marker to distinguish between the two phenotypic clusters. This was true for immune cell-derived proteins, and all proteins were analyzed conjointly. Periostin and CST-2 showed the highest feature importance for the epithelial- and tissue-derived proteins. The combination of IL-5, IgE, IL-17, and periostin showed the highest accuracy for prediction. CONCLUSIONS: Nasal mucus can predict phenotypes similar to tissue, with IL-5 as the main trigger for clustering. Periostin and CST-2 may be part of important targetable pathways. Future efforts will be directed at determining how these markers may be used to guide therapeutic choices and individualize treatment.
CRIS-Team Scopus Importer:2025-02-28

Predictors of transient congenital primary hypothyroidism: data from the German registry for congenital hypothyroidism (AQUAPE “HypoDok”) - Matejek, Nicola; Tittel, Sascha R.; Haberland, Holger; Rohrer, Tilman; Busemann, Eva-Maria; Jorch, Norbert; Schwab, Karl-Otfried; Wölfle, Joachim; Holl, Reinhard W.; Bettendorf, Markus (European Journal of Pediatrics, 2021)
Neonatal screening for congenital primary hypothyroidism (CH) may not distinguish between transient (TCH) and permanent dysfunction (PCH), causing potential overtreatment and concerns in affected families. To specify the indication for interruption of therapy, we analysed the German registry “HypoDok” for infants with CH, which oversees 1625 patients from 49 participating centres in Germany and Austria from 1997 until today. A total of 357 patients with a thyroid gland in loco typico were identified and retrospectively grouped according to cessation (TCH, n = 24) or continuation (PCH, n = 333) of l-thyroxine (l-T4) treatment at 2 years of age. The receiver operating characteristic (ROC) analysis was performed to identify cutoffs predicting TCH by screening TSH concentrations and l-T4 dosages. Gestational ages, birth weights and prevalence of associated malformations were comparable in both groups. The cutoff screening TSH concentration was 73 mU/L. The cutoff daily l-T4 dosage at 1 year was 3.1 μg/kg (90% sensitivity, 63% specificity; 36 μg/day) and at 2 years of age 2.95 μg/kg (91% sensitivity, 59% specificity; 40 μg/day). At 2 years of age, specificity (71%) increased when both of these parameters were considered together. Conclusion: The decision to continue or cease l-T4 treatment at 2 years of age in CH patients diagnosed in neonatal screening may be based on their screening TSH concentrations and individual l-T4 dosages at 1 and 2 years of age. Thus, TCH and PCH may be distinguished; overtreatment avoided; and affected families reassured.What is Known:• The course of congenital primary hypothyroidism may be transient, causing potential overtreatment.• The dose ofl-thyroxine at 1 or 2 years of age may predict a transient course of primary congenital hypothyroidism.What is New:• TSH screening concentration andl-thyroxine dosages at 1 and 2 years of age represent reliable predictors for transient congenital primary hypothyroidism with higher sensitivity and specificity when considered together in order to select eligible patients who qualify for treatment withdrawal.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Congenital primary hypothyroidism; Permanent congenital primary hypothyroidism; Prediction; Transient congenital primary hypothyroidism

Premature birth associated with a favorable course in gestational alloimmune liver disease (GALD): A case report - Mulzer, Linda-Marie; Reutter, Heiko Martin; Jüngert, Jörg M.; Knisely, A. S.; Schmid, Margit; Hörning, André; Morhart, Patrick (Frontiers in Pediatrics, 2023)
Gestational alloimmune liver disease (GALD) is a rare neonatal disorder with high mortality and morbidity. The patients come to caregivers' attention aged a few hours or days. The disease manifests as acute liver failure with or without siderosis. The differential diagnosis of neonatal acute liver failure (NALF) is broad, including mainly immunologic, infectious, metabolic and toxic disorders. The most common cause, however, is GALD followed by herpes simplex virus (HSV) infection. The best suited pathophysiological paradigm of GALD is that of a maternofetal alloimmune disorder. State of the art treatment combines intravenously administered immunoglobulin (IVIG) with exchange transfusion (ET). We report an infant born at 35 + 2 weeks' gestation in whom GALD had a favorable course, of interest because premature birth in our patient may have exerted protective aspects and lessened morbidity in that intrauterine exposure to maternal complement-fixing antibodies was shortened. The diagnosis of GALD was challenging and difficult. We suggest a modified diagnostic algorithm combining clinical findings with histopathologic findings in liver and lip mucosa and, if available, on abdominal magnetic resonance imaging-study focusing on the liver, spleen, and pancreas. This diagnostic workup must be followed by ET and subsequent administration of IVIG without delay.
CRIS-Team WoS Importer:2023-04-14

Prenatal Correction of X-Linked Hypohidrotic Ectodermal Dysplasia - Schneider, Holm; Faschingbauer, Florian; Schuepbach-Mallepell, Sonia; Koerber, Iris; Wohlfart, Sigrun; Dick, Angela; Wahlbuhl, Mandy; Kowalczyk-Quintas, Christine; Vigolo, Michele; Kirby, Neil; Tannert, Corinna; Rompel, Oliver; et al. (New England Journal of Medicine, 2018)
Genetic deficiency of ectodysplasin A (EDA) causes X-linked hypohidrotic ectodermal dysplasia (XLHED), in which the development of sweat glands is irreversibly impaired, an condition that can lead to life-threatening hyperthermia. We observed normal development of mouse fetuses with Eda mutations after they had been exposed in utero to a recombinant protein that includes the receptor-binding domain of EDA. We administered this protein intraamniotically to two affected human twins at gestational weeks 26 and 31 and to a single affected human fetus at gestational week 26; the infants, born in week 33 (twins) and week 39 (singleton), were able to sweat normally, and XLHED-related illness had not developed by 14 to 22 months of age. (Funded by Edimer Pharmaceuticals and others.).
EVALuna2:35486

Prenatal dexamethasone treatment for classic 21-hydroxylase deficiency in Europe - Nowotny, Hanna; Neumann, Uta; Tardy-Guidollet, Veronique; Faisal Ahmed, S.; Baronio, Federico; Battelino, Tadej; Bertherat, Jerome; Blankenstein, Oliver; Bonomi, Marco; Bouvattier, Claire; De la Perrière, Aude Brac; Brucker, Sara; et al. (European Journal of Endocrinology, 2022)
Objective: To assess the current medical practice in Europe regarding prenatal dexamethasone (Pdex) treatment of congenital adrenal hyperplasia (CAH) due to 21-hydroxylase defic iency. Design and methods: A questionnaire was designed and distributed, including 17 questions collecting quantitative and qualitative data. Thirty-six medical centres from 14 European countries responded and 30 out of 36 centres were reference centres of the European Reference Network on Rare Endocrine Conditions, EndoERN. Results: Pdex treatment is currently provided by 36% of the surveyed ce ntres. The treatment is initiated by different specialties, that is paediatricians, endocrinologists, gynaecologists or geneticists. Regarding the starting point of Pdex, 23% stated to initiate therapy at 4-5 weeks postconception (wpc), 31% at 6 wpc and 46 % as early as pregnancy is confirmed and before 7 wpc at the latest. A dose of 20 μg/kg/day is used. Dose distribution among the centres varies from once to thrice daily. Prenatal diagnostics for treated cases are conducted in 72% of the responding centres. Cases treated per country and year vary between 0.5 and 8.25. Registries for long-term follow-up are only available at 46% of the centres that are using Pdex treatment. National registries are only available in Sweden and France. Conclusions: This study reveals a high international variability and discrepancy in the use of Pdex treatment across Europe. It highlights the importance of a European cooperation initiative for a joint international prospective trial to establish evidence-based guidelines on prenatal diagnostics, treatment and follow-up of pregnancies at risk for CAH.
CRIS-Team Scopus Importer:2022-04-29

Prenatal diagnosis of HNF1B-associated renal cysts: Is there a need to differentiate intragenic variants from 17q12 microdeletion syndrome? - Vasileiou, Georgia; Hoyer, Juliane; Thiel, Christian; Schaefer, Jan Thomas; Zapke, Maren; Krumbiegel, Mandy; Kraus, Cornelia; Zweier, Markus; Uebe, Steffen; Ekici, Arif Bülent; Schneider, Michael; Wiesener, Michael; et al. (Prenatal Diagnosis, 2019)
Objective 17q12 microdeletions containing HNF1B and intragenic variants within this gene are associated with variable developmental, endocrine, and renal anomalies, often already noted prenatally as hyperechogenic/cystic kidneys. Here, we describe prenatal and postnatal phenotypes of seven individuals with HNF1B aberrations and compare their clinical and genetic data to those of previous studies. Methods Prenatal sequencing and postnatal chromosomal microarray analysis were performed in seven individuals with renal and/or neurodevelopmental phenotypes. We evaluated HNF1B-related clinical features from 82 studies and reclassified 192 reported intragenic HNF1B variants. Results In a prenatal case, we identified a novel in-frame deletion p.(Gly239del) within the HNF1B DNA-binding domain, a mutational hot spot as demonstrated by spatial clustering analysis and high computational prediction scores. The six postnatally diagnosed individuals harbored 17q12 microdeletions. Literature screening revealed variable reporting of HNF1B-associated clinical traits. Overall, both mutation groups showed a high phenotypic heterogeneity. The reclassification of all previously reported intragenic HNF1B variants provided an up-to-date overview of the mutational spectrum. Conclusions We highlight the value of prenatal HNF1B screening in renal developmental diseases. Standardized clinical reporting and systematic classification of HNF1B variants are necessary for a more accurate risk quantification of prenatal and postnatal clinical features, improving genetic counseling and prenatal decision making.
CRIS-Team WoS Importer:2019-11-08

Prenatal therapy in developmental disorders: drug targeting via intra-amniotic injection to treat X-linked hypohidrotic ectodermal dysplasia - Hermes, Katharina; Schneider, Pascal; Krieg, Peter; Anh Thu Dang,; Huttner, Kenneth; Schneider, Holm (Journal of Investigative Dermatology, 2014)
EVALuna2:18898

Prenatal treatment of X-linked hypohidrotic ectodermal dysplasia using recombinant ectodysplasin in a canine model - Margolis, Carol A.; Schneider, Pascal; Huttner, Kenneth; Kirby, Neil; Houser, Timothy P.; Wildman, Lee; Grove, Gary L.; Schneider, Holm; Casal, Margret L. (Journal of Pharmacology and Experimental Therapeutics, 2019)
X-linked hypohidrotic ectodermal dysplasia (XLHED) is caused by defects in the EDA gene that inactivate the function of ectodysplasin A1 (EDA1). This leads to abnormal development of eccrine glands, hair follicles, and teeth, and to frequent respiratory infections. Previous studies in the naturally occurring dog model demonstrated partial prevention of the XLHED phenotype by postnatal administration of recombinant EDA1. The results suggested that a single or two temporally spaced injections of EDI200 prenatally might improve the clinical outcome in the dog model. Fetuses received ultrasound-guided EDI200 intra-amniotically at gestational days 32 and 45, or 45 or 55 alone (of a 65-day pregnancy). Growth rates, lacrimation, hair growth, meibomian glands, sweating, dentition, and mucociliary clearance were compared in treated and untreated XLHED-affected dogs, and in heterozygous and wild-type control dogs. Improved phenotypic outcomes were noted in the earlier and more frequently treated animals. All animals treated prenatally showed positive responses compared with untreated dogs with XLHED, most notably in the transfer of moisture through paw pads, suggesting improved onset of sweating ability and restored meibomian gland development. These results exemplify the feasibility of ultrasound-guided intra-amniotic injections for the treatment of developmental disorders, with improved formation of specific EDA1-dependent structures in dogs with XLHED.
CRIS-Team Scopus Importer:2019-09-17

Prescription patterns of antiseizure drugs in tuberous sclerosis complex (TSC)-associated epilepsy: a multicenter cohort study from Germany and review of the literature - Strzelczyk, Adam; Grau, Janina; Bast, Thomas; Bertsche, Astrid; Bettendorf, Ulrich; Hahn, Andreas; Hartmann, Hans; Hertzberg, Christoph; Hornemann, Frauke; Immisch, Ilka; Jacobs, Julia; Klotz, Kerstin A.; et al. (Expert Review of Clinical Pharmacology, 2021)
Objective Seizures are a primary and early disease manifestation of Tuberous Sclerosis Complex (TSC). We aimed to describe the age-stratified patterns of antiseizure drug (ASD) treatments among children, adolescents, and adults with TSC in Germany. Additionally, we reviewed real-world and clinical study evidence regarding ASD utilization in patients with TSC. Methods We evaluated the pattern of routine ASD use and everolimus prescriptions based on a 2019 multicenter survey of 268 individuals with TSC-associated epilepsy. We contextualized the results with a structured review of real-world and clinical study evidence. Results TSC-associated epilepsy treatment comprises a wide variety of ASDs. In this German sample, the majority of patients were treated with polytherapy, and lamotrigine (34.7%), valproate (32.8%), oxcarbazepine (28.7%), vigabatrin (19.0%), and levetiracetam (17.9%) were identified as the most-commonly used ASDs. In addition, everolimus was used by 32.5% of patients. In adherence to current TSC guidelines, the disease-modifying ASD vigabatrin was widely used in children (58% below the age of 5 years), whereas treatment in adults did not necessarily reflect guideline preference for (partial) GABAergic ASDs. Conclusions The selection of ASDs for patients with TSC-associated epilepsy follows well-evaluated recommendations, including the guidelines regarding vigabatrin use in children. Several characteristics, such as the comparatively high frequency of valproate use and polytherapy, reflect the severity of TSC-associated epilepsy.
CRIS-Team WoS Importer:2021-06-11

Preterm small-for-gestational age children: Predictive role of gestational age for mental development at the age of 2 years - Nögel, Stephanie; Deiters, Ludger; Stemmler, Mark; Rascher, Wolfgang; Trollmann, Regina (Brain & Development, 2015)
AIM: The aim of the study was to compare the cognitive development of very low birth weight (VLBW) preterm SGA children and preterm AGA children at the age of 2 years. The hypothesis was that SGA children are at an additional risk for deficits in cognitive function. Additionally, the impact of neonatal risk factors and the parents' profession on the early cognitive development was analysed. METHODS: Cognitive function of 107 preterm infants with a gestational age of 24-35 weeks was assessed with the Mental Bayley Scales of Infant Development at the age of 2 years (mean±SEM). The results of SGA (n=38) and AGA (n=69) children were compared as well as neonatal risk factors and parental education. RESULTS: There was a linear regression between the Mental Bayley Scales result and gestational age for preterm infants with a gestational age of 24-32 weeks. SGA and AGA children did not differ significantly in their cognitive function at the age of 2 years. A strong association was found between the parents' profession and cognitive development. Among the neonatal risk factors, bronchopulmonary dysplasia was a strong predictor of mental development. INTERPRETATION: Cognitive development of two-year-old preterm children with a gestational age of 24-32 weeks was mainly related to their gestational age. Being born preterm and small for gestational age was not additionally associated with cognitive deficits at the age of 2 years. The parents' profession had a significant impact on the cognitive development. The role of the parents' profession on the early development of preterm infants should be elucidated in further studies. Copyright © 2014 The Japanese Society of Child Neurology. Published by Elsevier B.V. All rights reserved.
Keywords: Gestational age; Mental development; Parental profession; Preterm infants

Prevalence and prevention of severe complications of hypohidrotic ectodermal dysplasia in infancy - Blueschke, Gert; Nuesken, Kai-Dietrich; Schneider, Holm (Early Human Development, 2010)
Objective: To re-evaluate the mortality of hypohidrotic ectodermal dysplasia (HED) and the prevalence of hyperpyrexia and possible neurological sequelae in affected infants. Study design: A cross-sectional postal survey was conducted among parents of 100 children with ectodermal dysplasia who had been registered with the German-Swiss-Austrian patient support group at any time point within the past 10. years. Detailed questionnaires referring to the first year of life were evaluated statistically. Results: 63% of parents returned completed surveys, identifying 57% of children as patients with X-linked HED and 20% as patients with autosomal HED or HED of unknown origin. Of those two groups, 17 infants had been placed in an incubator after birth, where body temperature recording proved to be of utmost importance. In 94% of all HED patients, episodes of unexplained fever were observed during the first year of life. X-linked HED was associated with frequent airway infections. Febrile seizures occurred in 5.9% of infants with X-linked HED and in 17% of the other HED patients. Developmental retardation was reported for 15% and 25%, respectively. Prognosis depended on the type of genetic defect and the time point of diagnosis. Except for one all patients survived infancy. Early recognition of the disease was aided by vigilant neonatal care and consulting a dermatologist or geneticist. Adequate instruction of the parents and networking with patient support groups also reduced the risks associated with HED. Conclusions: Today, mortality of HED and the risk of hyperthermic brain damage are still increased, but lower than reported previously. © 2010 Elsevier Ltd.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Ectodermal dysplasia; Febrile seizure; Hyperthermia; Sudden infant death

Prevalence of SARS-CoV-2 in Pregnant Women Assessed by RT-PCR in Franconia, Germany: First Results of the SCENARIO Study (SARS-CoV-2 prEvalence in pregNAncy and at biRth In FrancOnia) - Hein, Alexander; Kehl, Sven; Häberle, Lothar; Tiemann, Carsten; Peuker, Rebecca; Mereutanu, Denise; Stumpfe, Florian; Faschingbauer, Florian; Meyer-Schlinkmann, Kirstin; Koch, Martin C.; Kainer, Franz; Dammer, Ulf; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Purpose Detection of SARS-CoV-2-infected pregnant women admitted to maternity units during a pandemic is crucial. In addition to the fact that pregnancy is a risk factor for severe COVID-19 and that medical surveillance has to be adjusted in infected women and their offspring, knowledge about infection status can provide the opportunity to protect other patients and healthcare workers against virus transmission. The aim of this prospective observational study was to determine the prevalence of SARS-CoV-2 infection among pregnant women in the hospital setting. Material and Methods All eligible pregnant women admitted to the nine participating hospitals in Franconia, Germany, from 2 June 2020 to 24 January 2021 were included. COVID-19-related symptoms, secondary diseases and pregnancy abnormalities were documented. SARS-CoV-2 RNA was detected by RT-PCR from nasopharyngeal swabs. The prevalence of acute SARS-CoV-2 infection was estimated by correcting the positive rate using the Rogan-Gladen method. The risk of infection for healthcare workers during delivery was estimated using a risk calculator. Results Of 2414 recruited pregnant women, six were newly diagnosed RT-PCR positive for SARS-CoV-2, which yielded a prevalence of SARS-CoV-2 infection of 0.26% (95% CI, 0.10-0.57%). Combining active room ventilation and wearing FFP2 masks showed an estimated reduction of risk of infection for healthcare workers in the delivery room to < 1%. Conclusions The prevalence of newly diagnosed SARS-CoV-2 infection during pregnancy in this study is low. Nevertheless, a systematic screening in maternity units during pandemic situations is important to adjust hygienic and medical management. An adequate hygienic setting can minimise the calculated infection risk for medical healthcare workers during patients' labour.
CRIS-Team Scopus Importer:2022-02-25
Keywords: COVID-19; infection; pregnancy; prevalence; SARS-CoV-2

Previous diabetic ketoacidosis as a risk factor for recurrence in a large prospective contemporary pediatric cohort: Results from the DPV initiative - Hammersen, Johanna; Tittel, Sascha R.; Warncke, Katharina; Fritsch, Maria; Placzek, Kerstin; Pacaud, Danièle; Karges, Beate; Wölfle, Joachim; Holl, Reinhard W. (Pediatric Diabetes, 2021)
Objective: To assess the role of previous episodes of diabetic ketoacidosis (DKA) and their time-lag as risk factors for recurring DKA in youth with type 1 diabetes (T1D). Research Design and Methods: In a population-based analysis, data from 29,325 children and adolescents with T1D and at least 5 years of continuous follow-up were retrieved from the “Diabetes Prospective Follow-up” (DPV) multi-center registry in March 2020. Statistical analyses included unadjusted comparisons, logistic and negative binomial regression models. Results: Among 29,325 patients with T1D, 86.0% (n = 25,219) reported no DKA, 9.7% (n = 2,833) one, and 4.3% (n = 1,273) more than one episode, corresponding to a DKA rate of 4.4 [95% CI: 4.3–4.6] per 100 patient-years. Female sex, migratory background, higher HbA1c values, higher daily insulin doses, a lower glucose monitoring frequency, and less CGM usage were associated with DKA. In patients with a previous episode, the DKA rate in the most recent year was significantly higher than in patients with no DKA (17.6 [15.9–19.5] vs. 2.8 [2.7–3.1] per 100 patient-years; p < 0.001). Multiple DKAs further increased the recurrence rate. The risk for DKA in the most recent year was higher in patients with an episode in the preceding year than in patients with no previous DKA (OR: 10.0 [95% CI: 8.6–11.8]), and remained significantly elevated 4 years after an episode (OR: 2.3 [1.6–3.1]; p < 0.001). Conclusions: Each episode of DKA is an independent risk factor for recurrence, even 4 years after an event, underlining the importance of a close follow-up after each episode.
CRIS-Team Scopus Importer:2021-03-05

Priapism at Diagnosis of Pediatric Chronic Myeloid Leukemia: Data Derived from a Large Cohort of Children and Teenagers and a Narrative Review on Priapism Management - Suttorp, Meinolf; Sembill, Stephanie; Kalwak, Krzysztof; Metzler, Markus; Millot, Frederic (Journal of Clinical Medicine, 2023)
Pediatric chronic myeloid leukemia (CML) is a very rare malignancy (age-related incidence 0.1/100,000) typically presenting with leucocyte counts >100,000/µL. However, clinical signs of leukostasis are observed at diagnosis in only approximately 10% of all cases and among these, priapism is infrequent. Here, we analyze data from pediatric CML registries on the occurrence of priapism heralding diagnosis of CML in 16/491 (3.2%) boys (median age 13.5 years, range 4–18) with pediatric CML. In the cohort investigated, duration of priapism resulting in a diagnosis of CML was not reported in 5 patients, and in the remaining 11 patients, occurred as stuttering priapism over 3 months (n = 1), over 6 weeks (n = 1), over 1–2 weeks (n = 2), over several days (n = 2), or 24 h (n = 1), while the remaining 4 boys reported continuous erection lasting over 11–12 h. All patients exhibited splenomegaly and massive leukocytosis (median WBC 470,000/µL, range 236,700–899,000). Interventions to treat priapism were unknown in 5 patients, and in the remaining cohort, comprised intravenous fluids ± heparin (n = 2), penile puncture (n = 5) ± injection of sympathomimetics (n = 4) ± intracavernous shunt operation (n = 1) paralleled by leukocyte-reductive measures. Management without penile puncture by leukapheresis or exchange transfusion was performed in 3 boys. In total, 7 out 15 (47%) long-term survivors (median age 20 years, range 19–25) responded to a questionnaire. All had maintained full erectile function; however, 5/7 had presented with stuttering priapism while in the remaining 2 patients priapism had lasted <12 h until intervention. At its extreme, low-flow priapism lasting for longer than 24 h may result in partial or total impotence by erectile dysfunction. This physical disability can exert a large psychological impact on patients’ lives. In a narrative review fashion, we analyzed the literature on priapism in boys with CML which is by categorization stuttering or persisting as mostly painful, ischemic (low-flow) priapism. Details on the pathophysiology are discussed on the background of the different blood rheology of hyperleukocytosis in acute and chronic leukemias. In addition to the data collected, instructive case vignettes demonstrate the diagnostic and treatment approaches and the outcome of boys presenting with priapism. An algorithm for management of priapism in a stepwise fashion is presented. All approaches must be performed in parallel with cytoreductive treatment of leukostasis in CML which comprises leukapheresis and exchange transfusions ± cytotoxic chemotherapy.
CRIS-Team Scopus Importer:2023-08-11
Keywords: chronic myeloid leukemia; exchange transfusion; hyperleukocytosis; leukapheresis; leukostasis; pediatric CML; pediatric CML registry; penile puncture; priapism

Prospective Newborn Screening for SCID in Germany: A First Analysis by the Pediatric Immunology Working Group (API) - Speckmann, Carsten; Nennstiel, Uta; Hoenig, Manfred; Albert, Michael H.; Ghosh, Sujal; Schuetz, Catharina; Brockow, Inken; Hoerster, Friederike; Niehues, Tim; Ehl, Stephan; Wahn, Volker; Borte, Stephan; et al. (Journal of Clinical Immunology, 2023)
Background: T-cell receptor excision circle (TREC)-based newborn screening (NBS) for severe combined immunodeficiencies (SCID) was introduced in Germany in August 2019. Methods: Children with abnormal TREC-NBS were referred to a newly established network of Combined Immunodeficiency (CID) Clinics and Centers. The Working Group for Pediatric Immunology (API) and German Society for Newborn Screening (DGNS) performed 6-monthly surveys to assess the TREC-NBS process after 2.5 years. Results: Among 1.9 million screened newborns, 88 patients with congenital T-cell lymphocytopenia were identified (25 SCID, 17 leaky SCID/Omenn syndrome (OS)/idiopathic T-cell lymphocytopenia, and 46 syndromic disorders). A genetic diagnosis was established in 88%. Twenty-six patients underwent hematopoietic stem cell transplantation (HSCT), 23/26 within 4 months of life. Of these, 25/26 (96%) were alive at last follow-up. Two patients presented with in utero onset OS and died after birth. Five patients with syndromic disorders underwent thymus transplantation. Eight syndromic patients deceased, all from non-immunological complications. TREC-NBS missed one patient, who later presented clinically, and one tracking failure occurred after an inconclusive screening result. Conclusion: The German TREC-NBS represents the largest European SCID screening at this point. The incidence of SCID/leaky SCID/OS in Germany is approximately 1:54,000, very similar to previous observations from North American and European regions and countries where TREC-NBS was implemented. The newly founded API-CID network facilitates tracking and treatment of identified patients. Short-term HSCT outcome was excellent, but NBS and transplant registries will remain essential to evaluate the long-term outcome and to compare results across the rising numbers of TREC-NBS programs across Europe.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Hematopoietic stem cell transplantation; HSCT; NBS; Newborn screening; SCID; Severe combined immunodeficiency; T cell receptor excision circles; Thymus transplantation; TREC

Protocol for the Phase 2 EDELIFE Trial Investigating the Efficacy and Safety of Intra-Amniotic ER004 Administration to Male Subjects with X-Linked Hypohidrotic Ectodermal Dysplasia - Schneider, Holm; Hadj-Rabia, Smail; Faschingbauer, Florian; Bodemer, Christine; Grange, Dorothy K.; Norton, Mary E.; Cavalli, Riccardo; Tadini, Gianluca; Stepan, Holger; Clarke, Angus; Guillén-Navarro, Encarna; Maier-Wohlfart, Sigrun; et al. (Genes, 2023)
X-linked hypohidrotic ectodermal dysplasia (XLHED) is a rare genetic disorder characte-rised by abnormal development of the skin and its appendages, such as hair and sweat glands, the teeth, and mucous glands of the airways, resulting in serious, sometimes life-threatening complications like hyperthermia or recurrent respiratory infections. It is caused by pathogenic variants of the ectodysplasin A gene (EDA). Most affected males are hemizygous for EDA null mutations that lead to the absence or inactivity of the signalling protein ectodysplasin A1 (EDA1) and, thus, to the full-blown phenotype with inability to perspire and few if any teeth. There are currently no long-term treatment options for XLHED. ER004 represents a first-in-class protein replacement molecule designed for specific, high-affinity binding to the endogenous EDA1 receptor (EDAR). Its proposed mechanism of action is the replacement of missing EDA1 in yet unborn patients with XLHED. Once bound to EDAR, ER004 activates the EDA/NFκB signalling pathway, which triggers the transcription of genes involved in the normal development of multiple tissues. Following preclinical studies, named-patient use cases demonstrated significant potential of ER004 in affected males treated in utero during the late second and third trimesters of pregnancy. In order to confirm these results, we started the EDELIFE trial, a prospective, open-label, genotype-match controlled, multicentre clinical study to investigate the efficacy and safety of intra-amniotic ER004 administration as a prenatal treatment for male subjects with XLHED. This article summarises the rationale, the study protocol, ethical issues of the trial, and potential pitfalls.
CRIS-Team Scopus Importer:2023-02-24
Keywords: anhidrosis; clinical trial; ectodermal dysplasia; ectodysplasin A; fetal therapy; protein replacement; sweat glands

PTEN hamartoma tumor syndrome in childhood and adolescence-a comprehensive review and presentation of the German pediatric guideline. - Plamper, Michaela; Gohlke, Bettina; Wölfle, Joachim (Molecular and Cellular Pediatrics, 2022)
BACKGROUND: The PTEN hamartoma tumor syndrome (PHTS) encompasses several different syndromes, which are linked to an autosomal-dominant mutation of the tumor suppressor PTEN gene on chromosome 10. Loss of PTEN activity leads to an increased phosphorylation of different cell proteins, which may have an influence on growth, migration, and apoptosis. Excessive activity of the PI3K/AKT/mTOR pathway due to PTEN deficiency may lead to the development of benign and malignant tumors and overgrowth. Diagnosis of PHTS in childhood can be even more challenging than in adulthood because of a lack of well-defined diagnostic criteria. So far, there are no official recommendations for cancer surveillance in affected children and adolescents. MAIN BODY: All individuals with PHTS are at high risk for tumor development and thus might benefit from cancer surveillance strategies. In childhood, macrocephaly may be the only evident symptom, but developmental delay, behavioral problems, dermatological features (e.g., penile freckling), vascular anomalies, lipoma, or enlarged perivascular spaces in cerebral magnetic resonance imaging (cMRI) may help to establish the diagnosis. Regular psychomotor assessment and assistance in subjects with neurological impairment play an important role in the management of affected children. Already in early childhood, affected patients bear a high risk to develop thyroid pathologies. For that reason, monitoring of thyroid morphology and function should be established right after diagnosis. We present a detailed description of affected organ systems, tools for initiation of molecular diagnostic and screening recommendations for patients < 18 years of age. CONCLUSION: Affected families frequently experience a long way until the correct diagnosis for their child's peculiarity is made. Even after diagnosis, it is not easy to find a physician who is familiar with this rare group of diseases. Because of a still-limited database, it is not easy to establish evidence-based (cancer) surveillance recommendations. The presented screening recommendation should thus be revised regularly according to the current state of knowledge.
EVALuna2:519679

Pubertal Timing and Growth Dynamics in Children With Severe Primary IGF-1 Deficiency: Results From the European Increlex® Growth Forum Database Registry - Bang, Peter; Polak, Michel; Perrot, Valérie; Sert, Caroline; Shaikh, Haris; Wölfle, Joachim (Frontiers in Endocrinology, 2022)
Background: Puberty is delayed in untreated children and adolescents with severe primary IGF-1 deficiency (SPIGFD); to date, it has not been reported whether recombinant human insulin-like growth factor-1 mecasermin (rhIGF-1) treatment affects this. Pubertal growth outcomes were extracted from the European Increlex® Growth Forum Database (Eu-IGFD) Registry (NCT00903110). Methods: The Eu-IGFD Registry includes children and adolescents aged 2 to 18 years with growth failure associated with SPIGFD who are treated with rhIGF-1. Reported outcomes include: age at last registration of Tanner stage 1 and first registration of Tanner stage 2-5 (T2-T5; based on breast development for girls and genital development for boys, respectively); maximum height velocity during each Tanner stage; and pubertal peak height velocity (PPHV). Data cut-off was 13 May 2019. Results: This analysis included 213 patients (132 boys and 81 girls). Mean (SD) age at last registration of T1 and first registration of T5 was 13.0 (2.0) and 16.3 (1.6) years, respectively, in boys and 11.6 (1.8) and 14.7 (1.5) years, respectively, in girls. Among patients reaching the end of puberty (25 boys and 11 girls), mean (SD) height SDS increased from -3.7 (1.4) at baseline in the Eu-IGFD Registry to -2.6 (1.4) at T5 in boys and from -3.1 (1.1) to -2.3 (1.5) in girls. Maximum height velocity was observed during T2 in girls and T3 in boys. Median (range) PPHV was 8.0 (0.3–13.0) cm/year in boys and 6.8 (1.3–9.6) cm/year in girls and occurred most frequently during T2. Overall, the adverse events seen in this analysis were in line with the known safety profile of rhIGF-1. Conclusion: Children and adolescents treated with rhIGF-1 for SPIGFD with growth failure experienced an increase in height SDS in prepubertal years compared with baseline. Despite 1.5 years delay in pubertal start and a delayed and slightly lower PPHV, height SDS gain during puberty was maintained.
CRIS-Team Scopus Importer:2022-03-18
Keywords: Eu-IGFD Registry; growth retardation; mecasermin; puberty; severe primary insulin-like growth factor-1 deficiency

Pulmonary Dysfunction after Pediatric COVID-19 - Heiß, Rafael; Tan, Lina; Schmidt, Sandy; Regensburger, Adrian; Ewert, Franziska; Mammadova, Dilbar; Bühler, Adrian; Vogel-Claussen, Jens; Voskrebenzev, Andreas; Rauh, Manfred; Rompel, Oliver; Nagel, Armin Michael; et al. (Radiology, 2022)
Background Long COVID occurs in lower frequency in children and adolescents than in adults. Morphologic and free-breathing phase-resolved functional low-field MRI may identify persistent pulmonary manifestations after SARS-CoV-2 infection. Purpose To characterize both morphologic and functional changes of lung parenchyma on low-field MRI in children and adolescents with post COVID-19 compared with healthy controls. Materials and Methods Between August and December 2021, a cross-sectional, prospective clinical trial using low-field MRI was performed in children and adolescents from a single academic medical center. The primary outcome was the frequency of morphologic changes on MRI. Secondary outcomes included MRI-derived functional proton ventilation and perfusion parameters. Clinical symptoms, the duration from positive RT-PCR test and serological parameters were compared with imaging results. Nonparametric tests for pairwise and corrected tests for groupwise comparisons were applied to assess differences in healthy controls, recovered participants and with long COVID. Results A total of 54 participants post COVID-19 infection (mean age, 11 years ±3 [SD], 56 males) and 9 healthy controls (mean age, 10 years ±3 [SD], 70 males) were included: 29 (54%) in the COVID-19 group had recovered from infection and 25 (46%) were classified as having long COVID on the day of enrollment. Morphologic abnormality was identified in one recovered participant. Both ventilated and perfused lung parenchyma (V/Q match) was reduced from 81±6.1% in healthy controls to 62±19% (P =.006) in the recovered group and 60±20% (P=.003) in the long COVID group. V/Q match was lower in post COVID patients with infection less than 180 days (63±20%, P=.03), 180 to 360 days (63±18%, P=0.03) and 360 days ago (41±12%, P<.001) as compared with the never-infected healthy controls (81±6.1%). Conclusion Low-field MRI showed persistent pulmonary dysfunction in both children and adolescents recovered from COVID-19 and with long COVI

Pupillometry in the follow-up of patients undergoing EVT - prediction of space-occupying hemispheric infarction - Kossel, Clara-Sophie; Kobus, Franca; Borutta, Matthias; Kärtner, Maximilian; Kuramatsu, Joji; Engelhorn, Tobias; Schwab, Stefan; Köhn, Julia (Journal of Neurology, 2023)
Background: Despite benefits of endovascular treatment (EVT) for large vessel occlusion (LVO) ischemic stroke, space-occupying brain edema (BE) represents a detrimental complication. In critical-care settings, CT-imaging is needed for monitoring these patients. Yet, bed-side techniques with the potential to predict whether patients develop BE or not would facilitate a time- and cost-efficient patient care. We assessed clinical significance of automated pupillometry in the follow-up of patients undergoing EVT. Methods: From 10/2018 to 10/2021, neurocritical-care-unit patients were retrospectively enrolled after EVT of anterior circulation LVO. We monitored parameters of pupillary reactivity [light-reflex-latency (Lat), constriction- and redilation-velocities (CV, DV), percentage-change-of-apertures (per-change); NeurOptics-pupilometer®] up to every hour on day 1–3 of ICU stay. BE was defined as midline shift ≥ 5 mm on follow-up imaging 3–5 days after EVT. We calculated mean values of intra-individual differences between successive pairs of parameters (mean-deltas), determined best discriminative cut-off values for BE development (ROC-analyses), and evaluated prognostic performance of pupillometry for BE development (sensitivity/specificity/positive-/negative-predictive-values). Results: 3241 pupillary assessments of 122 patients [67 women, 73 years (61.0–85.0)] were included. 13/122 patients developed BE. Patients with BE had significantly lower CVs, DVs, and smaller per-changes than patients without BE. On day 1 after EVT mean-deltas of CV, DV, and per-changes were significantly lower in patients with than without BE. Positive-predictive-values of calculated thresholds to discriminate both groups were considerably low, yet, we found high negative-predictive-values for CV, DV, per-changes, and mean-deltas (max.: 98.4%). Conclusion: Our data suggest associations between noninvasively detected changes in pupillary reactivity and BE early after LVO-EVT. Pupillometry may identify patients who are unlikely to develop BE and may not need repetitive follow-up-imaging or rescue-therapy.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Automated pupillometry; Endovascular treatment; Ischemic stroke; Large vessel occlusion; Pupillary reactivity

Quality of life of short-statured children born small for gestational age or idiopathic growth hormone deficiency within one year of growth hormone treatment - Quitmann, Julia; Bloemeke, Janika; Silva, Neuza; Bullinger, Monika; Witt, Stefanie; Akkurt, Ilker; Dunstheimer, Desirée; Vogel, Christian; Böttcher, Volker; Krahl, Ursula Kuhnle; Bettendorf, Markus; Schönau, Eckhard; et al. (Frontiers in Pediatrics, 2019)
Aside from clinical endpoints like height gain, health-related quality of life has also become an important outcome indicator in the medical field. However, the data on short stature and health-related quality of life is inconsistent. Therefore, we examined changes in health-related quality of life in German children with idiopathic growth hormone deficiency or children born small for gestational age before and after 12 months of human growth hormone treatment. Children with idiopathic short stature without treatment served as a comparison group. At baseline, health-related quality of life data of 154 patients with idiopathic growth hormone deficiency (n = 65), born small for gestational age (n = 58) and idiopathic short stature (n = 31) and one parent each was collected. Of these, 130 completed health-related quality of life assessments after 1-year of human growth hormone treatment. Outcome measures included the Quality of Life in Short Stature Youth questionnaire, as well as clinical and sociodemographic data. Our results showed that the physical, social, and emotional health-related quality of life of children treated with human growth hormone significantly increased, while untreated patients with idiopathic short stature reported a decrease in these domains. Along with this, a statistically significant increase in height in the treated group can be observed, while the slight increase in the untreated group was not significant. In conclusion, the results showed that human growth hormone treatment may have a positive effect not only on height but also in improving patient-reported health-related quality of life of children with idiopathic growth hormone deficiency and children born small for gestational age.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Growth hormone treatment; Health-related quality of life; IGHD; ISS; QoLISSY; Short stature

Quality of life of young adults after a growth hormone therapy with childhood onset - Quitmann, J. H.; Rohenkohl, A. C.; Kammerer, U.; Schöfl, Christof; Bullinger, M.; Dörr, Helmuth-Günther (Deutsche Medizinische Wochenschrift, 2014)
Little is known about the health-related quality of life of young adults with childhood onset idiopathic growth hormone deficiency or neurosecretory dysfunction of growth hormone secretion, who have been treated with recombinant human growth hormone (GH).Patients were diagnosed and treated with human growth hormone at the University Children´s Hospital in Erlangen (n=85). The data of both groups were merged for analysis, because no difference between idiopathic growth hormone deficiency and neurosecretory dysfunction of growth hormone secretion in auxological. Data were found. Health-related quality of life was cross- sectionally assessed after the end of growth hormone therapy with the Short Form-36 Health Survey and the Nottingham Health Profiles for which population based norm data are available.At the time of the survey, the patients (53 m, 32 f) were 23.5 ± 4.6 years old. At start of GH therapy, age was 10.5 ± 2.8 and at the end 16.3 ± 1,4 years. At start, height SDS was -3.20 ± 1.06. GH dose was 0,026 ± 0,012 mg/kg/d (daily s. c.-injections). The increase in height SDS after the end of GH therapy was 1.69 ± 1.22. Compared to the reference population, patients reported significantly lower scores on the scales energy level, vitality, social functioning, indicating a greater social isolation, a stronger emotional reaction, an increased loss of mobility and a worse psychological state.Young adults report specific impairments after completion of GH therapy.
EVALuna2:1888

Quality of Survival and Growth in Children and Young Adults in the PNET4 European Controlled Trial of Hyperfractionated Versus Conventional Radiation Therapy for Standard-Risk Medulloblastoma - Kennedy, Colin; Bull, Kim; Chevignard, Mathilde; Culliford, David; Dörr, Helmuth-Günther; Doz, Francois; Kortmann, Rolf-Dieter; Lannering, Birgitta; Massimino, Maura; Navajas Gutierrez, Aurora; Rutkowski, Stefan; Spoudeas, Helen A.; et al. (International Journal of Radiation Oncology Biology Physics, 2014)
To compare quality of survival in "standard-risk" medulloblastoma after hyperfractionated radiation therapy of the central nervous system with that after standard radiation therapy, combined with a chemotherapy regimen common to both treatment arms, in the PNET4 randomised controlled trial.Participants in the PNET4 trial and their parents/caregivers in 7 participating anonymized countries completed standardized questionnaires in their own language on executive function, health status, behavior, health-related quality of life, and medical, educational, employment, and social information. Pre- and postoperative neurologic status and serial heights and weights were also recorded.Data were provided by 151 of 244 eligible survivors (62%) at a median age at assessment of 15.2 years and median interval from diagnosis of 5.8 years. Compared with standard radiation therapy, hyperfractionated radiation therapy was associated with lower (ie, better) z-scores for executive function in all participants (mean intergroup difference 0.48 SDs, 95% confidence interval 0.16-0.81, P=.004), but health status, behavioral difficulties, and health-related quality of life z-scores were similar in the 2 treatment arms. Data on hearing impairment were equivocal. Hyperfractionated radiation therapy was also associated with greater decrement in height z-scores (mean intergroup difference 0.43 SDs, 95% confidence interval 0.10-0.76, P=.011).Hyperfractionated radiation therapy was associated with better executive function and worse growth but without accompanying change in health status, behavior, or quality of life.
EVALuna2:18860

Quantification of translocation-specific ctDNA provides an integrating parameter for early assessment of treatment response and risk stratification in ewing sarcoma - Krumbholz, Manuela; Eiblwieser, Johanna; Ranft, Andreas; Zierk, Jakob; Schmidkonz, Christian; Stuetz, Adrian M.; Peneder, Peter; Tomazou, Eleni M.; Agaimy, Abbas; Bäuerle, Tobias; Hartmann, Wolfgang; Dirksen, Uta; et al. (Clinical Cancer Research, 2021)
Purpose: We evaluated the predictive and prognostic value of circulating tumor DNA (ctDNA) in patients with Ewing sarcoma (EWS) treated in the EWING2008 trial. Experimental Design: Plasma samples from 102 patients with EWS enrolled in the EWING2008 trial were obtained before and during induction chemotherapy. Genomic EWSR1 fusion sequence spanning primers and probes were used for highly specific and sensitive quantification of the levels of ctDNA by digital droplet PCR. ctDNA levels were correlated to established clinical risk factors and outcome parameters. Results: Pretreatment ctDNA copy numbers were correlated with event-free and overall survival. The reduction in ctDNA levels below the detection limit was observed in most cases after only two blocks of vincristine, ifosfamide, doxorubicin, and etoposide (VIDE) induction chemotherapy. The persistence of ctDNA after two VIDE blocks was a strong predictor of poor outcomes. ctDNA levels correlated well with most established clinical risk factors; an inverse correlation was found only for the histologic response to induction therapy. ctDNA levels did not provide simple representations of tumor volume, but integrated information from various tumor characteristics represented an independent EWS tumor marker with predictive and prognostic value. Conclusions: ctDNA copy number in the plasma of patients with EWS is a quantifiable parameter for early risk stratification and can be used as a dynamic noninvasive biomarker for early prediction of treatment response and outcome of patients.
CRIS-Team Scopus Importer:2021-11-26

Rare intronic mutation between Exon 62 and 63 (c.9225–285A>G) of the dystrophin gene associated with atypical BMD phenotype - Schüssler, S. C.; Gerhalter, T.; Abicht, A.; Müller-Felber, W.; Nagel, Armin Michael; Trollmann, Regina (Neuromuscular Disorders, 2020)
Dystrophinopathies are predominantly caused by deletions, duplications and point mutations in the coding regions of the dystrophin gene with less than 1% of all pathogenic mutations identified within intronic sequences. We describe a 17-year-old male with a Becker muscular dystrophy diagnosis and mental disability due to an intron mutation that led to aberrant splicing and formation of an additional exon. Histopathological analysis of muscle tissue revealed signs of muscular dystrophy and reduced signal for dystrophin, alpha-sarcoglycan, and alpha-dystroglycan. Multiplex ligation-dependent probe amplification screening and total sequencing of the dystrophin gene did not identify a mutation in the coding regions. However, next generation sequencing revealed an intron mutation between exons 62 and 63 of the dystrophin gene known for pseudoexon formation and disruption of the reading frame. We report a functional consequence of this mutation as an increased intracellular-weighted sodium signal (assessed by 23Na-magnetic resonance imaging) in leg muscles.
CRIS-Team Scopus Importer:2020-08-28
Keywords: 23Na-MRI; Aberrant splicing; Becker muscular dystrophy; Dystrophin; Intracellular-weighted sodium signal; Next generation sequencing

Rare pediatric tumors in Germany – not as rare as expected: a study based on data from the Bavarian Cancer Registry and the German Childhood Cancer Registry - Achajew, Aisana; Brecht, Ines B.; Radespiel-Troeger, Martin; Meyer, Martin; Metzler, Markus; Bremensdorfer, Claudia; Spix, Claudia; Erdmann, Friederike; Schneider, Dominik T.; Abele, Michael (European Journal of Pediatrics, 2022)
Very rare pediatric tumors (VRTs) pose a challenge for treating physicians as little is known about the best diagnostic assessment and therapeutic decision-making in these malignancies. A large proportion of these cancers occur in adolescence. Therefore, the established structures of pediatric oncology including cancer registration may partly be circumvented. This may lead to an underregistration in clinical cancer registries of yet unclear extent. The aim of this study is to increase the knowledge on the occurrence of VRTs in pediatric patients in Germany. Pseudonymized data of cases recorded in the Bavarian Cancer Registry (BCR) between 2002 and 2014 were retrieved. VRTs according to the definition of the European Cooperative Study Group for Pediatric Rare Tumors were identified using the ICD and ICD-O classification. The numbers of registered patients were compared to those reported to the German Childhood Cancer Registry (GCCR). 6.3% (n = 290) of all malignancies (n = 4615) in the age below 18 years were classified as VRTs. Median age at diagnosis was 15 years (range 0–17 years). The most common tumor types included malignant melanoma, skin carcinoma, and gonadal tumors. During the same period, 49 pediatric patients from Bavaria with matchable VRTs were reported to the GCCR, accounting for 17% of cases reported to the BCR. Conclusions: The frequency of VRTs in Germany is underestimated in the national GCCR. With this study, we present population-based data on the incidence of VRTs in Germany for the first time. In order to gain additional knowledge about these malignancies, registration of VRTs must be improved through enhanced data exchange between the GCCR, the public cancer registries, and the clinical Registry for Rare Pediatric Tumors (STEP).What is Known:• Rare pediatric tumors pose a challenge for treating physicians as limited knowledge is available on these malignancies for diagnostic and therapeutic decision-making.• Little is known about the frequency of these rare tumors in pediatric patients.What is New:• The frequency of rare pediatric tumors in Germany is distinctly underestimated in the German Childhood Cancer Registry.• We present population-based data on the incidence of these rare pediatric cancers for the first time.
CRIS-Team Scopus Importer:2022-06-17
Keywords: Bavaria; Cancer registry; Germany; Incidence; Pediatric cancers; Rare tumors

Rare Variant of GM2 Gangliosidosis through Activator-Protein Deficiency - Brackmann, Florian; Kehrer, Christiane; Kustermann, Wibke; Boehringer, Judith; Kraegeloh-Mann, Ingeborg; Trollmann, Regina (Neuropediatrics, 2017)
GM2 gangliosidosis, AB variant, is a very rare form of GM2 gangliosidosis due to a deficiency of GM2 activator protein. We report on two patients with typical clinical features suggestive of GM2 gangliosidosis, but normal results for hexosaminidase A and hexosaminidase B as well as their corresponding genes. Genetic analysis of the gene encoding the activator protein, the GM2A gene, elucidated the cause of the disease, adding a novel mutation to the spectrum of GM2 AB variant. This report points out that in typical clinical constellations with normal enzyme results, genetic diagnostic for activator protein defects should be performed.
EVALuna2:34027

Ratiometric luminescence 2D in vivo imaging and monitoring of mouse skin oxygenation - Hofmann, Julian; Meier, Robert J.; Mahnke, Alexander; Schatz, Valentin; Brackmann, Florian; Trollmann, Regina; Bogdan, Christian; Liebsch, Gregor; Wang, Xu Dong; Wolfbeis, Otto S.; Jantsch, Jonathan (Methods and Applications in Fluorescence, 2013)
Tissue oxygenation plays a critical role in the pathogenesis of various diseases, but non-invasive, robust and user-friendly methods for its measurement in vivo still need to be established. Here, we are presenting an in vivo oxygen-detection system that uses ratiometric luminescence imaging (RLI) as a readout scheme to determine the skin oxygen tension of mouse hind footpads via side-by-side comparison with more established techniques including luminescence-lifetime imaging using planar sensor films and the polarographic electrode as the gold standard. We also demonstrate that this technology allows the detection of changes in mouse skin tissue oxygenation induced by subjecting mice to systemic hypoxia. The data demonstrate oxygen imaging based on RLI to be a most useful tool for reliably and easily analyzing and monitoring skin tissue oxygenation in vivo. This technology will advance our understanding of local regulation of skin tissue oxygenation in various disease conditions.
CRIS-Team Scopus Importer:2024-02-26

Real-world data in children with achondroplasia after licensing of Vosoritide - Palm, Katja; Bechthold-Dalla Pozza, Susanne; Gausche, Ruth; Hoegler, Wolfgang; Hoyer-Kuhn, Heike; Huebner, Angela; Keller, Alexandra; Mirante, Alice; Mohnike, Klaus; Muschol, Nicole; Nader, Sean; Pfaeffle, Roland; et al. (HORMONE RESEARCH IN PAEDIATRICS, 2022)
CRIS-Team WoS Importer:2022-10-07

Rearrangement bursts generate canonical gene fusions in bone and soft tissue tumors - Anderson, Nathaniel D.; De Borja, Richard; Young, Matthew D.; Fuligni, Fabio; Rosic, Andrej; Roberts, Nicola D.; Hajjar, Simon; Layeghifard, Mehdi; Novokmet, Ana; Kowalski, Paul E.; Anaka, Matthew; Davidson, Scott; et al. (Science, 2018)
Sarcomas are cancers of the bone and soft tissue often defined by gene fusions. Ewing sarcoma involves fusions between EWSR1, a gene encoding an RNA binding protein, and E26 transformation-specific (ETS) transcription factors. We explored how and when EWSR1-ETS fusions arise by studying the whole genomes of Ewing sarcomas. In 52 of 124 (42%) of tumors, the fusion gene arises by a sudden burst of complex, loop-like rearrangements, a process called chromoplexy, rather than by simple reciprocal translocations. These loops always contained the disease-defining fusion at the center, but they disrupted multiple additional genes. The loops occurred preferentially in early replicating and transcriptionally active genomic regions. Similar loops forming canonical fusions were found in three other sarcoma types. Chromoplexy-generated fusions appear to be associated with an aggressive form of Ewing sarcoma. These loops arise early, giving rise to both primary and relapse Ewing sarcoma tumors, which can continue to evolve in parallel.
EVALuna2:35824

Recessive Mutations in CFAP74 Cause Primary Ciliary Dyskinesia with Normal Ciliary Ultrastructure - Biebach, Luisa; Cindrić, Sandra; Koenig, Julia; Aprea, Isabella; Dougherty, Gerard W.; Raidt, Johanna; Bracht, Diana; Ruppel, Renate; Schreiber, Jens; Hjeij, Rim; Olbrich, Heike; Omran, Heymut (American journal of respiratory cell and molecular biology, 2022)
CRIS-Team Scopus Importer:2022-09-16

Recombinant Human Growth Hormone Activates Neuroprotective Growth Factors in Hypoxic Brain Injury in Neonatal Mice - Jung, Susan; Terörde, Klara; Dörr, Helmuth-Günther; Trollmann, Regina (Endocrinology, 2021)
Perinatal hypoxia severely disrupts cerebral metabolic and maturational programs beyond apoptotic cell death. Antiapoptotic treatments such as erythropoietin are suggested to improve outcomes in hypoxic brain injury; however, the results are controversial. We analyzed the neuroprotective effects of recombinant human growth hormone (rhGH) on regenerative mechanisms in the hypoxic developing mouse brain in comparison to controls. Using an established model of neonatal acute hypoxia (8% O2, 6 hours), P7 mice were treated intraperitoneally with rhGH (4000 µg/kg) 0, 12, and 24 hours after hypoxic exposure. After a regeneration period of 48 hours, expression of hypoxia-inducible neurotrophic factors (erythropoietin [EPO], vascular endothelial growth factor A [VEGF-A], insulin-like growth factors 1 and 2 [IGF-1/-2], IGF binding proteins) and proinflammatory markers was analyzed. In vitro experiments were performed using primary mouse cortical neurons (E14, DIV6). rhGH increased neuronal gene expression of EPO, IGF-1, and VEGF (P < .05) in vitro and diminished apoptosis of hypoxic neurons in a dose-dependent manner. In the developing brain, rhGH treatment led to a notable reduction of apoptosis in the subventricular zone and hippocampus (P < .05), abolished hypoxia-induced downregulation of IGF-1/IGF-2 expression (P < .05), and led to a significant accumulation of endogenous EPO protein and anti-inflammatory effects through modulation of interleukin-1β and tumor necrosis factor α signaling as well as upregulation of cerebral phosphorylated extracellularly regulated kinase 1/2 levels (ERK1/2). Indicating stabilizing effects on the blood-brain barrier (BBB), rhGH significantly modified cerebrovascular occludin expression. Thus, we conclude that rhGH mediates neuroprotective effects by the activation of endogenous neurotrophic growth factors and BBB stabilization. In addition, the modification of ERK1/2 pathways is involved in neuroprotective actions of rhGH. The present study adds further evidence that pharmacologic activation of neurotrophic growth factors may be a promising target for neonatal neuroprotection.
CRIS-Team Scopus Importer:2021-03-05
Keywords: apoptosis; BBB; IGF binding proteins; IGF-1; IGF-2; interleukin-1β; neuroprotection; occludin; pERK 1/2; TNF-α; VEGF

Recommendations of the AGG (Working Group for Obstetrics, Department of Maternal Diseases) on How to Treat Thyroid Function Disorders in Pregnancy. - Hamza, Amr; Schlembach, Dietmar; Schild, Ralf Lothar; Groten, Tanja; Wölfle, Joachim; Battefeld, Wilgard; Kehl, Sven; Schneider, Michael (Geburtshilfe und Frauenheilkunde, 2023)
Objective These recommendations from the AGG (Committee for Obstetrics, Department of Maternal Diseases) on how to treat thyroid function disorder during pregnancy aim to improve the diagnosis and management of thyroid anomalies during pregnancy. Methods Based on the current literature, the task force members have developed the following recommendations and statements. These recommendations were adopted after a consensus by the members of the working group. Recommendations The following manuscript gives an insight into physiological and pathophysiological thyroid changes during pregnancy, recommendations for clinical and subclinical hypo- and hyperthyroidism, as well as fetal and neonatal diagnostic and management strategies.
EVALuna2:548561

Recurrent Somatic PDGFRB Mutations in Sporadic Infantile/Solitary Adult Myofibromas But Not in Angioleiomyomas and Myopericytomas - Agaimy, Abbas; Bieg, Matthias; Michal, Michael; Geddert, Helene; Maerkl, Bruno; Seitz, Jan; Moskalev, Evgeny; Schlesner, Matthias; Metzler, Markus; Hartmann, Arndt; Wiemann, Stefan; Michal, Michal; et al. (American Journal of Surgical Pathology, 2017)
Infantile myofibroma (MF) is an uncommon benign myofibroblastic tumor of infancy and childhood. Solitary adult MF shares similar features with infantile MF. The lesions occur in 3 clinicopathologic settings: solitary, multicentric, and generalized and can be either sporadic or familial. Traditionally, infantile MF has been included in the spectrum of infantile hemangiopericytoma. The recent World Health Organization classification listed MF, angioleiomyoma, and myopericytoma under the general heading of perivascular tumors in the sense of a morphologic spectrum of perivascular myoid cell neoplasms. Although activating germline PDGFRB mutations have recently been linked to familial infantile MF, the molecular pathogenesis of sporadic infantile and adult solitary MF remained unclear. In this study, we analyzed 25 solitary MFs without evidence of familial disease (9 infantile and 16 adult MFs) to address the question whether somatic PDGFRB mutations might be responsible for the sporadic form of the disease. Given the presumed histogenetic link of MF to myopericytoma and angioleiomyoma, we additionally analyzed a control group of 6 myopericytomas and 9 angioleiomyomas for PDGFRB mutations. We detected PDGFRB mutations in 6/8 (75%) analyzable infantile and in 11/16 (69%) adult MFs but in none of the angioleiomyomas or myopericytomas. In 2 infantile MFs, additional sequencing of the germline confirmed the somatic nature of PDGFRB mutations. To our knowledge, this is the first study reporting apparently somatic recurrent PDGFRB mutations as molecular driver events in the majority of sporadic infantile and adult solitary MFs. Our results suggest molecular distinctness of MF as compared with angioleiomyoma/myopericytoma. Investigation of more cases including those with atypical and worrisome features, as well as other mimickers in the heterogenous morphologic spectrum of MF, is mandatory for validating the potential diagnostic value of PDGFRB mutation testing as a possible surrogate in difficult-to-classify lesions.
EVALuna2:6839

Reduced Perinatal Leptin Availability May Contribute to Adverse Metabolic Programming in a Rat Model of Uteroplacental Insufficiency - Nuesken, Eva; Wohlfarth, Maria; Lippach, Gregor; Rauh, Manfred; Schneider, Holm; Doetsch, Joerg; Nuesken, Kai-Dietrich (Endocrinology, 2016)
Leptin availability in perinatal life critically affects metabolic programming. We tested the hypothesis that uteroplacental insufficiency and intrauterine stress affect perinatal leptin availability in rat offspring. Pregnant rats underwent bilateral uterine vessel ligation (LIG; n = 14), sham operation (SOP; n = 12), or no operation (controls, n = 14). Fetal livers (n = 180), placentas (n = 180), and maternal blood were obtained 4 hours (gestational day [E] 19), 24 hours (E20), and 72 hours (E22) after surgery. In the offspring, we took blood samples on E22 (n = 44), postnatal day (P) 1 (n = 29), P2 (n = 16), P7 (n = 30), and P12 (n = 30). Circulating leptin (ELISA) was significantly reduced in LIG (E22, P1, P2) and SOP offspring (E22). Postnatal leptin surge was delayed in LIG but was accelerated in SOP offspring. Placental leptin gene expression (quantitative RT-PCR) was reduced in LIG (E19, E20, E22) and SOP (E20, E22). Hepatic leptin receptor (Lepr-a, mediating leptin degradation) gene expression was increased in LIG fetuses (E20, E22) only. Surprisingly, hypoxia-inducible factors (Hif; Western blot) were unaltered in placentas and were reduced in the livers of LIG (Hif1a, E20; Hif2a, E19, E22) and SOP (Hif2a, E19) fetuses. Gene expression of prolyl hydroxylase 3, a factor expressed under hypoxic conditions contributing to Hif degradation, was increased in livers of LIG (E19, E20, E22) and SOP (E19) fetuses and in placentas of LIG and SOP (E19). In summary, reduced placental leptin production, increased fetal leptin degradation, and persistent perinatal hypoleptinemia are present in intrauterine growth restriction offspring, especially after uteroplacental insufficiency, and may contribute to perinatal programming of leptin resistance and adiposity in later life.
EVALuna2:33880

Reference Interval Estimation from Mixed Distributions using Truncation Points and the Kolmogorov-Smirnov Distance (kosmic) - Zierk, Jakob; Arzideh, Farhad; Kapsner, Lorenz; Prokosch, Hans-Ulrich; Metzler, Markus; Rauh, Manfred (Scientific Reports, 2020)
Appropriate reference intervals are essential when using laboratory test results to guide medical decisions. Conventional approaches for the establishment of reference intervals rely on large samples from healthy and homogenous reference populations. However, this approach is associated with substantial financial and logistic challenges, subject to ethical restrictions in children, and limited in older individuals due to the high prevalence of chronic morbidities and medication. We implemented an indirect method for reference interval estimation, which uses mixed physiological and abnormal test results from clinical information systems, to overcome these restrictions. The algorithm minimizes the difference between an estimated parametrical distribution and a truncated part of the observed distribution, specifically, the Kolmogorov-Smirnov-distance between a hypothetical Gaussian distribution and the observed distribution of test results after Box-Cox-transformation. Simulations of common laboratory tests with increasing proportions of abnormal test results show reliable reference interval estimations even in challenging simulation scenarios, when <20% test results are abnormal. Additionally, reference intervals generated using samples from a university hospital’s laboratory information system, with a gradually increasing proportion of abnormal test results remained stable, even if samples from units with a substantial prevalence of pathologies were included. A high-performance open-source C++ implementation is available at https://gitlab.miracum.org/kosmic.
CRIS-Team Scopus Importer:2020-02-14

Reliability of prenatal detection of X-linked hypohidrotic ectodermal dysplasia by tooth germ sonography - Hammersen, Johanna; Wohlfart, Sigrun; Goecke, Tamme W.; Köninger, Angela; Stepan, Holger; Gallinat, Ralph; Morris, Susan; Bücher, Katharina; Clarke, Angus; Wünsche, Stephanie; Beckmann, Matthias; Schneider, Holm; et al. (Prenatal Diagnosis, 2019)
Objective: In X-linked hypohidrotic ectodermal dysplasia (XLHED), dysfunction of ectodysplasin A1 (EDA1) due to EDA mutations results in malformation of hair, teeth, and sweat glands. Hypohidrosis, which can cause life-threatening hyperthermia, is amenable to intrauterine therapy with recombinant EDA1. This study aimed at evaluating tooth germ sonography as a noninvasive means to identify affected fetuses in pregnant carrier women. Methods: Sonography, performed at 10 study sites between gestational weeks 18 and 28, led to the diagnosis of XLHED if fewer than six tooth germs were detected in mandible or maxilla. The assessment was verified postnatally by EDA sequencing and/or clinical findings. Estimated fetal weights and postnatal weight gain of boys with XLHED were assessed using appropriate growth charts. Results: In 19 of 38 sonographic examinations (23 male and 13 female fetuses), XLHED was detected prenatally. The prenatal diagnosis proved to be correct in 37 cases; one affected male fetus was missed. Specificity and positive predictive value were both 100%. Tooth counts obtained by clinical examination corresponded well with findings on panoramic radiographs. We observed no weight deficits of subjects with XLHED in utero but occasionally during infancy. Conclusion: Tooth germ sonography is highly specific and reliable in detecting XLHED prenatally.
CRIS-Team Scopus Importer:2019-08-27

Renal Chemerin Expression is Induced in Models of Hypertensive Nephropathy and Glomerulonephritis and Correlates with Markers of Inflammation and Fibrosis - Mocker, Alexander; Hilgers, Karl Friedrich; Cordasic, Nada; Wachtveitl, Rainer; Menendez-Castro, Carlos; Wölfle, Joachim; Hartner, Andrea; Fahlbusch, Fabian (International Journal of Molecular Sciences, 2019)
Chemerin and its receptor, chemokine-like receptor 1 (CmklR1), are associated with chemotaxis, inflammation, and endothelial function, especially in metabolic syndrome, coronary heart disease, and hypertension. In humans, circulating chemerin levels and renal function show an inverse relation. So far, little is known about the potential role of chemerin in hypertensive nephropathy and renal inflammation. Therefore, we determined systemic and renal chemerin levels in 2-kidney-1-clip (2k1c) hypertensive and Thy1.1 nephritic rats, respectively, to explore the correlation between chemerin and markers of renal inflammation and fibrosis. Immunohistochemistry revealed a model-specific induction of chemerin expression at the corresponding site of renal damage (tubular vs. glomerular). In both models, renal expression of chemerin (RT-PCR, Western blot) was increased and correlated positively with markers of inflammation and fibrosis. In contrast, circulating chemerin levels remained unchanged. Taken together, these findings demonstrate that renal chemerin expression is associated with processes of inflammation and fibrosis-related to renal damage. However, its use as circulating biomarker of renal inflammation seems to be limited in our rat models.
CRIS-Team Scopus Importer:2019-12-24
Keywords: 2-kidney-1-clip; 2k1c; chemerin; CmklR1; renal fibrosis; renal inflammation; renal injury; renovascular hypertension; Thy1.1 nephritis

Report from the HarmoSter study: Different LC-MS/MS androstenedione, DHEAS and testosterone methods compare well; however, unifying calibration is a double-edged sword - Fanelli, Flaminia; Peitzsch, Mirko; Bruce, Stephen; Cantù, Marco; Temchenko, Anastasia; Mezzullo, Marco; Lindner, Johanna M.; Hawley, James M.; Ackermans, Mariette T.; Van Den Ouweland, Jody; Köppl, Daniel; Nardi, Elena; et al. (Clinical Chemistry and Laboratory Medicine, 2024)
Current LC-MS/MS applications for circulating androgen measurements are technically diverse. Previously, variable results have been reported for testosterone. Data are scarce for androstenedione and absent for DHEAS. We assessed the agreement of androstenedione, DHEAS and testosterone LC-MS/MS measurements among nine European centers and explored benefits of calibration system unification. Androgens were measured twice by laboratory-specific procedures in 78 patient samples and in EQA materials. Results were obtained by in-house and external calibration. Intra- and inter-laboratory performances were valued. Intra-laboratory CVs ranged between 4.2-13.2 » % for androstenedione, 1.6-10.8 » % for DHEAS, and 4.3-8.7 » % and 2.6-7.1 » % for female and male testosterone, respectively. Bias and trueness in EQA materials were within ±20 » %. Median inter-laboratory CV with in-house vs. external calibration were 12.0 vs. 9.6 » % for androstenedione (p<0.001), 7.2 vs. 4.9 » % for DHEAS (p<0.001), 6.4 vs. 7.6 » % for female testosterone (p<0.001) and 6.8 and 7.4 » % for male testosterone (p=0.111). Median bias vs. all laboratory median with in-house and external calibration were -13.3 to 20.5 » % and -4.9 to 18.7 » % for androstenedione, -10.9 to 4.8 » % and -3.4 to 3.5 » % for DHEAS, -2.7 to 6.5 % and -11.3 to 6.6 » % for testosterone in females, and -7.0 to 8.5 » % and -7.5 to 11.8 » % for testosterone in males, respectively. Methods showed high intra-laboratory precision but variable bias and trueness. Inter-laboratory agreement was remarkably good. Calibration system unification improved agreement in androstenedione and DHEAS, but not in testosterone measurements. Multiple components, such as commutability of calibrators and EQA materials and internal standard choices, likely contribute to inter-laboratory variability.
CRIS-Team Scopus Importer:2024-01-26
Keywords: androstenedione; dehydroepiandrosterone-sulfate; harmonization; inter-laboratory performance; liquid chromatography-tandem mass spectrometry; testosterone

Reproductive decision-making by women with X-linked hypohidrotic ectodermal dysplasia - Leo, B.; Schneider, Holm; Hammersen, J. (Journal of the European Academy of Dermatology and Venereology, 2022)
Background: In X-linked hypohidrotic ectodermal dysplasia (XLHED), ectodysplasin A1 (EDA1) deficiency results in malformation of hair, teeth and sweat glands. Lack of sweating which can cause life-threatening hyperthermia is amenable to intrauterine therapy with recombinant EDA1. Objectives: This study aimed at evaluating reproductive decision-making by women with XLHED and at clarifying the potential impact of a prenatal treatment option. Methods: In a retrospective cross-sectional analysis, a 75-item questionnaire filled in by 50 women with XLHED (age 19–49 years) was assessed. Results: Sixteen women (32%) prevented pregnancies because of the risk to pass on XLHED; 15 considered assisted reproduction for the same reason. Twelve women had a history of miscarriage, stillbirth or abortion, and three women reported on previous abortion of affected fetuses. When imagining to be pregnant, all except one showed interest in prenatal diagnosis of XLHED and in the possibility of treatment before birth. In 13 out of 50 women (26%), XLHED if detected prenatally would have impact on the continuation of pregnancy. Among 35 mothers of at least one affected child, XLHED had rarely been diagnosed during the first pregnancy (17%) but regularly during subsequent pregnancies (77%). Becoming aware of the condition before birth had caused a moral conflict for 50% of these women. Subjects with an affected child less frequently considered assisted reproduction to prevent XLHED (P < 0.05). In 69% of the women who reported an effect of XLHED on family planning, a prenatal treatment option for this disease would influence their decision-making. Conclusions: Many pregnant XLHED carriers who seek prenatal diagnosis experience moral conflicts. A prenatal treatment option would have strong impact on reproductive decisions, underlining the importance of adequate professional counselling.
CRIS-Team Scopus Importer:2022-06-17

Resection of dominant fusiform gyrus is associated with decline of naming function when temporal lobe epilepsy manifests after the age of five: A voxel-based lesion-symptom mapping study - Reindl, Caroline; Allgäuer, Andrea; Kleiser, Benedict; Onugoren, Müjgan Dogan; Lang, Johannes; Welte, Tamara; Stritzelberger, Jenny; Winder, Klemens; Schwarz, Michael; Gollwitzer, Stephanie; Trollmann, Regina; Rösch, Julie; et al. (NeuroImage: Clinical, 2022)
Objective: To determine patients’ characteristics and regions in the temporal lobe where resections lead to a decline in picture naming. Methods: 311 patients with left hemispheric dominance for language were included who underwent epilepsy surgery at the Epilepsy Center of Erlangen and whose picture naming scores (Boston Naming Test, BNT) were available preoperatively and 6-months postoperatively. Surgical lesions were mapped to an averaged template based on preoperative and postoperative MRI using voxel-based lesion-symptom mapping (VBLSM). Postoperative brain shifts were corrected. The relationship between lesioned brain areas and the presence of a postoperative naming decline was examined voxel-wise while controlling for effects of overall lesion size at first in the total cohort and then restricted to temporal lobe resections. Results: In VBLSM in the total sample, a decline in BNT score was significantly related to left temporal surgery. When only considering patients with left temporal lobe resections (n = 121), 40 (33.1%) significantly worsened in BNT postoperatively. VBLSM including all patients with left temporal resections generated no significant results within the temporal lobe. However, naming decline of patients with epilepsy onset after 5 years of age was significantly associated with resections in the left inferior temporal (extent of BNT decline range: 10.8− 14.4%) and fusiform gyrus (decline range: 12.1−18.4%). Significance: Resections in the posterior part of the dominant fusiform and inferior temporal gyrus was associated with a risk of deterioration in naming performance at six months after surgery in patients with epilepsy onset after 5 years of age but not with earlier epilepsy onset.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Basal temporal language area; Epilepsy surgery; Gyrus fusiformis; Lesion localization; Naming; Neuropsychological outcome

Re-sequencing of candidate genes FOXF1, HSPA6, HAAO, and KYNU in 522 individuals with VATER/VACTERL, VACTER/VACTERL-like association, and isolated anorectal malformation - Thiem, Corina E.; Stegmann, Jil D.; Hilger, Alina C.; Waffenschmidt, Lea; Bendixen, Charlotte; Köllges, Ricarda; Schmiedeke, Eberhard; Schäfer, Frank Mattias; Lacher, Martin; Kosch, Ferdinand; Grasshoff-Derr, Sabine; Kabs, Carmen; et al. (Birth Defects Research, 2022)
Background: The acronym VATER/VACTERL association describes the combination of at least three component features (CFs): vertebral defects (V), anorectal malformations (ARM) (A), cardiac defects (C), tracheoesophageal fistula with or without esophageal atresia (TE), renal malformations (R), and limb defects (L). Individuals presenting two CFs have been termed VATER/VACTERL-like. Recently, FOXF1, HSPA6, HAAO, KYNU, TRAP1, and ZIC3 have been proposed as candidate genes for VATER/VACTERL, VATER/VACTERL-like, and ARM. Re-sequencing studies identified disease-causing variants in TRAP1 and ZIC3, the contribution of other genes was not independently investigated. One affected variant carrier in FOXF1 was previously identified. Here we re-sequenced FOXF1, HSPA6, HAAO, and KYNU in 522 affected individuals. Methods: Using molecular inversion probe (MIP) technology, re-sequencing was performed in 63 individuals with VATER/VACTERL association, 313 with VATER/VACTERL-like association, and 146 with ARM. All individuals were of European ethnicity. Variant filtering considered variants with a minor allele frequency (MAF) ≤0.01 for putative recessive disease-genes HSPA6, HAAO, and KYNU. For the putative dominant disease-gene FOXF1 we considered variants with a MAF ≤0.0001. In silico prediction tools were used for further prioritization. Results: Only two variants in FOXF1 in two independently affected individuals [c.443G>T, p.(Cys148Phe); c.850T>C, p.(Tyr284His)] passed our filter criteria. One individual presented with ARM, the second presented with TE and C comprising atrial and ventricular septal defects. Sanger sequencing confirmed both variants but also their inheritance from the healthy mother. Conclusion: Our analysis suggests that FOXF1, HSPA6, HAAO and KYNU do not play a major role in the formation of VACTER/VACTERL phenotypes or ARM.
CRIS-Team Scopus Importer:2022-04-15
Keywords: anorectal malformation; birth defects; candidate gene; penetrance; variants

Response monitoring of infant acute myeloid leukemia treatment by quantification of the tumor specific MLL-FNBP1 fusion gene - Krumbholz, Manuela; Jung, Ronny; Bradtke, Jutta; Reinhardt, Dirk; Stachel, Daniel; Metzler, Markus (Leukemia & Lymphoma, 2015)
EVALuna2:18906

Results from an international multicenter trial evaluating the ease-of-use of and preference for a newly developed disposable injection pen for the treatment of growth hormone deficiency in treatment-naïve children and adults - Pleil, Andreas M.; Darendeliler, Feyza; Dörr, Helmuth-Günther; Hutchinson, Katherine; Wollmann, Hartmut A. (Medical Devices : Evidence and Research, 2014)
Previous research has reported that ease of use of and preference for a delivery device are associated with greater patient compliance - an important factor in achieving optimal therapeutic results. The objective of this study was to assess the ease-of-use of a new disposable pen (GoQuick(®), Pfizer, Inc.) versus the current reusable pen (GENOTROPIN Pen(®), Pfizer, Inc.) to inject a daily dose of recombinant DNA origin human growth hormone, Genotropin(®) (somatropin) in standard practice. In this randomized, crossover, multicenter, multinational, open-label study, ease-of-use of and preference for the two pens were assessed in three treatment-naïve populations: 1) parents of very young children; 2) parent-child dyads; and 3) adults via use of a validated self-report Injection Pen Assessment Questionnaire (IPAQ) after 2 months of at-home-use experience. The primary endpoint was the proportion of participants who reported the new disposable pen to be no different from or easier to use than the current reusable pen. Safety was also assessed and reported according to local legal requirements. Of the 120 screened patients, 119 were included in the ease-of-use analysis and all were included in the safety analyses. In all, 67.2% found the new somatropin disposable pen to be no different from or easier to use than the reusable pen (95% confidence interval: 58.8-75.7). Most adverse events were mild or moderate. No deaths or device- or treatment-related serious adverse events were reported. These results suggest that improvements made to the reusable somatropin pen are tangible and recognizable to treatment-naïve patients and their caregivers, child-caregiver dyads, and adults, and may positively impact continued compliance with therapy.ClinicalTrials.gov identifier: NCT01112865.
EVALuna2:18887

Results of a multicenter, randomized trial examining a new transition model for post-kidney transplant adolescents - Kreuzer, Martin; Prüfe, Jenny; Dierks, Marie Luise; Müther, Silvia; Bethe, Dirk; Büscher, Anja; Heindl-Rusai, Krisztina; Hollenbach, Sabine; Hoppe, Bernd; John-Kroegel, Ulrike; Kanzelmeyer, Nele Kirsten; Klaus, Günter; et al. (Scientific Reports, 2025)
Allograft loss after pediatric kidney transplantation (KTx) is highest in adolescents and young adults. Non-adherence and Health Care Transition (HCT) are important factors, but others also contribute. In the TransNephro study patients were randomized 1:1. The intervention group was included in the Berlin Transition Program (BTP) and incorporated a central case manager, a communication app, and joined transition rounds for one year before and one year after transfer. Primary endpoint was the coefficient of variation (CoV) of the trough level of the calcineurin inhibitor as a surrogate marker for medication adherence associated with graft loss. Least square (LS) mean differences and corresponding 95% confidence intervals (CIs) were estimated using an analysis of covariance (ANCOVA) model. We assessed 220 patients for eligibility. 49 patients were randomized to the intervention group and 53 to the control group. We analyzed 84 patients in the modified intention-to-treat analysis (38 intervention, 46 controls) and 60 in the per protocol analysis (25 intervention, 35 controls). We found no difference in CoV. We saw low numbers of graft-related events and observed no differences with respect to quality of life. BTP did not improve adherence and other outcome parameters. Non-adherent patients may have decided not to participate, whilst adherence of participants was already good at study start. It is therefore achallenge to design future multicenter trials on HCT that include multiple interventions. Trial registration: ISRCTN22988897, 24/04/2014, https://doi.org/10.1186/ISRCTN22988897.
CRIS-Team Scopus Importer:2025-05-02

RHABDOID TUMOR PREDISPOSITION SYNDROME (RTPS) - FINDING EVIDENCE BY SYSTEMATIC ANALYSES - Nemes, Karolina; Bens, Susanne; Johann, Pascal D.; Steinbuegl, Mona; Gruhle, Miriam; Kachanov, Denis; Teleshova, Margarita; Hauser, Peter; Simon, Thorsten; Tippelt, Stephan; Eberl, Wolfgang; Woessmann, Wilhelm; et al. (NEURO-ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-09-02

Risk Factor Analysis for Long-Term Graft Survival Following Pediatric Kidney Transplantation: The Importance of Pretransplantation Time on Dialysis and Donor/Recipient Age Difference - Marcou, Marios; Galiano, Matthias; Tzschoppe, Anja; Sauerstein, Katja; Wach, Sven; Taubert, Helge; Wullich, Bernd; Hirsch-Koch, Karin; Apel, Hendrik (Journal of Clinical Medicine, 2023)
Recognizing risk factors that may negatively affect long-term graft survival following pediatric kidney transplantation is a key element in the decision-making process during organ allocation. We retrospectively reassessed all cases of pediatric kidney transplantation performed in our center in the last 20 years with the aim of determining baseline characteristics that could be identified as prognostic risk factors for long-term graft survival. Between 2001 and 2020, a total of 91 kidney transplantations in children under the age of 18 years were undertaken in our center. Early graft failure was observed in six of the 91 patients (7%). The median follow-up of the remaining 85 children was 100 months, and the overall kidney graft survival rates at 5, 10, 15 and 20 years were 85.2%, 71.4%, 46.0% and 30.6%, respectively. Small children with a body surface area of <1 m2 were significantly associated with better long-term graft survival outcomes, while adolescents aged more than twelve years showed poorer graft survival rates than younger children. Body surface area of the recipient of ≥1 m2, pretransplantation duration of the recipient on dialysis ≥18 months, hemodialysis prior to transplantation and donor/recipient age difference of ≥25 years were significantly associated with poorer long-term graft survival.
CRIS-Team Scopus Importer:2023-12-08
Keywords: age difference; children; graft survival; kidney transplantation; renal dialysis

Risk factors for mixed chimerism in children with hemophagocytic lymphohistiocytosis after reduced toxicity conditioning - Wustrau, Katharina; Greil, Johann; Sykora, Karl-Walter; Albert, Michael H.; Burkhardt, Birgit; Lang, Peter; Meisel, Roland; Woessmann, Wilhelm; Beier, Rita; Schulz, Ansgar; Bader, Peter; Chada, Martin; et al. (Pediatric Blood & Cancer, 2020)
Background Reduced toxicity conditioning for hematopoietic stem cell transplantation of patients with hemophagocyticlymphohistiocytosis (HLH) results in favorable survival, however at the expense of relevant rates of mixed chimerism. Factors predisposing to mixed chimerism remain to be determined. Procedure Patients with primary HLH transplanted 2009-2016 after treosulfan- or melphalan-based conditioning regimens were analyzed in a retrospective multicenter study for survival, engraftment, chimerism, and adverse events. Mixed chimerism was considered substantial if < 25% donor chimerism occurred and/or if secondary cell therapy was administered. Donor type, graft source, type of alkylating agent, type of serotherapy, and remission status were analyzed as potential risk factors in a multivariable logistic regression model. Results Among 60 patients, engraftment was achieved in 95%, and the five-year estimated overall survival rate was 75%. Prevalence of any recipient chimerism was 48%. Substantial recipient chimerism was recorded in 32% of patients. Secondary post-HSCT cell therapy was administered in 30% of patients. A human leukocyte antigen (HLA)-mismatched donor (< 10/10) was the only significant risk factor for the occurrence of substantial recipient chimerism (P = 0.01; odds ratio, 5.8; CI 95%, 1.5-26.3). Conclusion The use of an HLA-matched donor is the most important factor to avoid substantial recipient chimerism following treosulfan -or melphalan-based conditioning in primary HLH.
CRIS-Team WoS Importer:2020-07-17

Risk of behavioral disturbances in pediatric patients with epilepsy and mild to moderate cognitive impairment: A cross-sectional study - Schader, Carla; Schmidlechner, Tristan; Cornell, Sonia; Gerstl, Lucia; Trollmann, Regina; Borggraefe, Ingo (Epileptic Disorders, 2024)
Objective: The aim of the study was to assess whether children and adolescents with epilepsy are at higher risk of behavioral disturbances when they have concomitant cognitive disturbances. Methods: Behavioral scores were generated using the Child Behavior Checklist (CBCL). Cognitive evaluation was applied by using different age appropriate versions of the Wechsler Intelligence Scale. CBCL scores (total, externalizing, internalizing) were compared between patients with and without intellectual disability (IQ score < 70 and ≥70, respectively). Results: 144 (10.2 mean age, 6.0–17.9 range) patients were recruited for the study. Patients with mild to moderate intellectual disability (full-scale intelligence quotient (FSIQ) < 70) were not at higher risk of behavioral disturbances (total CBCL score ≥ 63) than patients without cognitive impairment. The mean total CBCL score was 62.0 ± 10.6 (range 42.0–83.5, 95% CI 57.9–62.0) and 59.3 ± 10.3 (range 38.0–80.0, CI 57.4–61.2) for patients with FSIQ < 70 and ≥70, respectively. There was no correlation between FSIQ and total CBCL scores. These findings were true for all IQ subcategories. Significance: Behavioral disturbances among children and adolescents with epilepsy occur despite the presence or absence of intellectual dysfunction with respect to full-scale IQ.
CRIS-Team Scopus Importer:2024-07-19
Keywords: behavior; cognition; epilepsy; neuropsychology; risk

RNA sequencing reveals induction of specific renal inflammatory pathways in a rat model of malignant hypertension - Menendez-Castro, Carlos; Cordasic, Nada; Fahlbusch, Fabian; Ekici, Arif Bülent; Kirchner, Philipp; Daniel, Christoph; Amann, Kerstin Ute; Velkeen, Roland; Wölfle, Joachim; Schiffer, Mario; Hartner, Andrea; Hilgers, Karl Friedrich (Journal of Molecular Medicine, 2021)
Abstract: In malignant hypertension, far more severe kidney injury occurs than in the “benign” form of the disease. The role of high blood pressure and the renin–angiotensin–aldosterone system is well recognized, but the pathogenesis of the renal injury of malignant hypertension (MH) remains incompletely understood. Using the rat model of two-kidney, one-clip renovascular hypertension in which some but not all animals develop MH, we performed a transcriptomic analysis of gene expression by RNA sequencing to identify transcriptional changes in the kidney cortex specific for MH. Differential gene expression was assessed in three groups: MH, non-malignant hypertension (NMH), and normotensive, sham-operated controls. To distinguish MH from NMH, we considered two factors: weight loss and typical renovascular lesions. Mean blood pressure measured intraarterially was elevated in MH (220 ± 6.5 mmHg) as well as in NMH (192 ± 6.4 mmHg), compared to controls (119 ± 1.7 mmHg, p < 0.05). Eight hundred eighty-six genes were exclusively regulated in MH only. Principal component analysis revealed a separated clustering of the three groups. The data pointed to an upregulation of many inflammatory mechanisms in MH including pathways which previously attracted relatively little attention in the setting of hypertensive kidney injury: Transcripts from all three complement activation pathways were upregulated in MH compared to NMH but not in NMH compared with controls; immunohistochemistry confirmed complement deposition in MH exclusively. The expression of chemokines attracting neutrophil granulocytes (CXCL6) and infiltration of myeloperoxidase-positive cells were increased only in MH rats. The data suggest that these pathways, especially complement deposition, may contribute to kidney injury under MH. Key messages: The most severe hypertension-induced kidney injury occurs in malignant hypertension.In a rat model of malignant hypertension, we assessed transcriptional responses in the kidney exposed to high blood pressure. A broad stimulation of inflammatory mechanisms was observed, but a few specific pathways were activated only in the malignant form of the disease, notably activation of the complement cascades.Complement inhibitors may alleviate the thrombotic microangiopathy of malignant hypertension even in the absence of primary complement abnormalities.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Complement activation; Inflammation; Kidney injury; Malignant hypertension; RNA-Seq; Two-kidney one-clip renovascular hypertension (2K1C)

Role of TGF-β in anti-rhinovirus immune responses in asthmatic patients - Bielor, Carina; Sopel, Nina; Maier, Anja; Blau, Ashley; Sharma, Himanshu; Vuorinen, Tytti; Kross, Bettina; Mittler, Susanne; Graser, Anna; Mousset, Stephanie; Melichar, Volker O.; Kiefer, Alexander; et al. (Journal of Allergy and Clinical Immunology, 2017)
EVALuna2:32796

Routine Surveillance of SARS-CoV-2 Serostatus in Pediatrics Allows Monitoring of Humoral Response - Wachter, Felix; Knieling, Ferdinand; Raming, Roman; Simon, David; Wölfle, Joachim; Hörning, André; Neubert, Antje; Rauh, Manfred; Regensburger, Adrian (Microorganisms, 2023)
The occurrence of SARS-CoV-2 infections during the pandemic was mainly based on PCR testing of symptomatic patients. However, with new variants, vaccinations, and the changing of the clinical disease severity, knowledge about general immunity is elusive. For public health systems, timely knowledge of these conditions is essential, but it is particularly scarce for the pediatric population. Therefore, in this study, we wanted to investigate the spike and nucleocapsid seroprevalence in pediatric patients using routine residual blood tests collected during the pandemic. This prospective observational study was conducted over seven one-month periods. Herein, the latest four time periods (November 2021, January 2022, March 2022, and May 2022) are depicted. Each patient of a tertiary-care center in Germany was anonymized after collection of clinical diagnosis (ICD-10) and then routinely tested for the respective spike and nucleocapsid SARS-CoV-2 antibody titer. A total of 3235 blood samples from four time periods were included. Spike seroprevalence rose from 37.6% to 51.9% to 70.5% to 85.1% and nucleocapsid seroprevalence from 11.6% to 17.0% to 36.7% to 58.1% in May 2022. In detail, significant changes in seroprevalence between age groups but not between sex or diagnosis groups were found. Quantitative measures revealed rising spike and constant nucleocapsid antibody levels over the pandemic with a half-life of 102 days for spike and 45 days for nucleocapsid antibodies. Routine laboratory assessment of SARS-CoV-2 in residual blood specimens of pediatric hospitals enables monitoring of the seroprevalence and may allow inferences about general immunity in this cohort.
EVALuna2:547467
Keywords: COVID-19; pediatrics; seroprevalence; SARS-CoV-2; Omicron; surveillance

Rubella vaccine–induced granulomas are a novel phenotype with incomplete penetrance of genetic defects in cytotoxicity - Groß, Miriam; Speckmann, Carsten; May, Annette; Gajardo-Carrasco, Tania; Wustrau, Katharina; Maier, Sarah Lena; Panning, Marcus; Huzly, Daniela; Agaimy, Abbas; Bryceson, Yenan T.; Choo, Sharon; Chow, C. W.; et al. (Journal of Allergy and Clinical Immunology, 2021)
Background: Rubella virus–induced granulomas have been described in patients with various inborn errors of immunity. Most defects impair T-cell immunity, suggesting a critical role of T cells in rubella elimination. However, the molecular mechanism of virus control remains elusive. Objective: This study sought to understand the defective effector mechanism allowing rubella vaccine virus persistence in granulomas. Methods: Starting from an index case with Griscelli syndrome type 2 and rubella skin granulomas, this study combined an international survey with a literature search to identify patients with cytotoxicity defects and granuloma. The investigators performed rubella virus immunohistochemistry and PCR and T-cell migration assays. Results: This study identified 21 patients with various genetically confirmed cytotoxicity defects, who presented with skin and visceral granulomas. Rubella virus was demonstrated in all 12 accessible biopsies. Granuloma onset was typically before 2 years of age and lesions persisted from months to years. Granulomas were particularly frequent in MUNC13-4 and RAB27A deficiency, where 50% of patients at risk were affected. Although these proteins have also been implicated in lymphocyte migration, 3-dimensional migration assays revealed no evidence of impaired migration of patient T cells. Notably, patients showed no evidence of reduced control of concomitantly given measles, mumps, or varicella live-attenuated vaccine or severe infections with other viruses. Conclusions: This study identified lymphocyte cytotoxicity as a key effector mechanism for control of rubella vaccine virus, without evidence for its need in control of live measles, mumps, or varicella vaccines. Rubella vaccine–induced granulomas are a novel phenotype with incomplete penetrance of genetic disorders of cytotoxicity.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Cytotoxicity; granuloma; Griscelli syndrome type 2; hemophagocytic lymphohistiocytosis; live vaccine; primary immunodeficiency; rubella virus

Safety and effectiveness of pediatric growth hormone therapy: Results from the full cohort in KIGS - Maghnie, Mohamad; Ranke, Michael B.; Geffner, Mitchell E.; Vlachopapadopoulou, Elpis; Dörr, Helmuth-Günther; Wikland, Kerstin Albertsson; Ibanez, Lourdes; Carlsson, Martin; Cutfield, Wayne; Rooman, Raoul; Gomez, Roy; Wajnrajch, Michael P.; et al. (HORMONE RESEARCH IN PAEDIATRICS, 2021)
CRIS-Team WoS Importer:2021-10-08

Safety and immunogenicity of Fc-EDA, a recombinant ectodysplasin A1 replacement protein, in human subjects - Körber, Iris; Klein, Ophir D.; Morhart, Patrick; Faschingbauer, Florian; Grange, Dorothy K.; Clarke, Angus; Bodemer, Christine; Maitz, Silvia; Huttner, Kenneth; Kirby, Neil; Durand, Caroline; Schneider, Holm (British Journal of Clinical Pharmacology, 2020)
In X-linked hypohidrotic ectodermal dysplasia, the most frequent ectodermal dysplasia, an inherited deficiency of the signalling protein ectodysplasin A1 (EDA1) impairs the development of the skin and its appendages, various eccrine glands, and dentition. The severe hypohidrosis common to X-linked hypohidrotic ectodermal dysplasia patients may lead to life-threatening hyperthermia, especially during hot weather or febrile illness. Fc-EDA, an EDA1 replacement protein known to prevent the disease in newborn animals, was tested in 2 clinical trials (human adults and neonates) and additionally administered under compassionate use to 3 infants in utero. The data support the safety of Fc-EDA and efficacy if applied prenatally. Anti-drug antibodies were detected after intravenous administration in adult males and nonpregnant females, but not in pregnant women when Fc-EDA was delivered intra-amniotically. Most importantly, there was no detectable immune response to the investigational drug in neonates treated by intravenous infusions and in infants who had received Fc-EDA in utero. In conclusion, the safety profile of this drug encourages further development of prenatal EDA1 replacement therapy.
CRIS-Team Scopus Importer:2020-05-02
Keywords: drug safety; ectodermal dysplasia; ectodysplasin A; immunogenicity; prenatal therapy; protein replacement

SARS-CoV-2-Infektion in der Schwangerschaft und Auftreten von angeborenen Fehlbildungen – Besteht ein Zusammenhang? Auswertung von 8032 Schwangerschaften aus dem CRONOS-Register - Hofbauer, Anna; Schneider, Holm; Kehl, Sven; Reutter, Heiko Martin; Pecks, Ulrich; Andresen, Kristin; Morhart, Patrick (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Background Based on single case reports, the COVID-19 Related Obstetric and Neonatal Outcome Study (CRONOS) registry, sponsored by the German Society for Perinatal Medicine (DGPM), investigated the likelihood that SARS-CoV-2 infections of the mother in (early) pregnancy cause embryopathies and/or fetopathies. Material/Methods The CRONOS registry enrolled a total of 8032 women with confirmed SARS-CoV-2 infection during pregnancy at more than 130 participating hospitals from April 2020 to February 2023. Both maternal and fetal data were documented and the anonymized multicenter data were analyzed. Results Of 7142 fully documented pregnancies (including postnatal data), 140 showed congenital malformations. 8.57% of the mothers had had a SARS-CoV-2-infection in the 1st trimester and 36.43% in the 2nd trimester. In 66 cases with congenital malformations (47.14%), the malformation was only detected after the diagnosis of a maternal SARS-CoV-2 infection. The overall prevalence of congenital malformations in this cohort was 1.96%, compared to a prevalence of 2.39% reported in the EUROCAT (European network of population-based registries for the epidemiological surveillance of congenital anomalies) pre-pandemic registry between 2017-2019. Discussion Our multicenter data argue against a link between maternal SARS-CoV-2 infection in early pregnancy and congenital malformation.
CRIS-Team Scopus Importer:2024-02-23
Keywords: Coronavirus; COVID-19; CRONOS-registry; embryopathy; fetopathy; malformations

Schilddrüsenfunktionsstörungen in der Schwangerschaft - Hamza, Amr; Schlembach, Dietmar; Schild, Ralf Lothar; Groten, Tanja; Wölfle, Joachim; Battefeld, Wilgard; Kehl, Sven; Schneider, Michael (gynäkologische praxis, 2024)
With the onset of pregnancy, TSH values fall then rise with ongoing gestation. A TSH screening should be performed in the first trimester under certain indications. Furthermore, the TPO-Ab status should be determined when the TSH levels exceeds 2.5 mU/l as it might lower threshold of a levothyroxine (LT4) substitution. Subclinical hypothyroidism is associated with an increased risk of miscarriage, preterm birth but not an increased risk of preeclampsia, fetal growth restriction or adverse neonatal neurocognitive outcomes and may not require a supplementation especially with negative TPO-Ab. However, the overt hypothyroidism requires LT4 administration. A manifest hyperthyroidism necessitates treatment adjustments before and with the onset pregnancy. Propylthiouracil is recommended in the first trimester and replaced by with thiamazole in the second trimester. A thorough birth plan with neonatological management should be planned. In cases of a fetal hyperthyroidism, a vertical treatment should be introduced in perinatal centres with a specialized experience. Regarding birth management, a detailed intra- and postnatal management plan, including a specialized paediatric care, is necessary. Fetal hyperthyroidism should be ruled out prenatally upon taking thyrostatic agents during the first trimester. Intrauterine therapies for fetal hyper- and hypothyroidism should only be carried out after careful consideration in centres with a therapeutic expertise. In complex cases, the birth should occur in a prenatal centre with paediatric personal that have the necessary expertise.
CRIS-Team Scopus Importer:2024-08-23
Keywords: hyperthyroidism; hypothyroidism; thyroid disease; TSH

Sclerosing epithelioid fibrosarcoma of the kidney: clinicopathologic and molecular study of a rare neoplasm at a novel location - Ohlmann, Carsten-Henning; Brecht, Ines B.; Junker, Kerstin; Van Der Zee, Jill A.; Nistor, Adriana; Bohle, Rainer M.; Stöckle, Michael; Metzler, Markus; Hartmann, Arndt; Agaimy, Abbas (Annals of Diagnostic Pathology, 2015)
Sclerosing epithelioid fibrosarcoma (SEF) is a rare fibrosarcoma variant with specific histomorphology and consistent translocation (EWSR1-CREB3L1/2). To date, 110 cases have been reported; only 15 originated within the abdomen. With only 2 cases reported parallel to our study and one case briefly mentioned in a previous series, primary renal SEF is exceptionally rare but might be underrecognized. We herein describe 2 cases affecting a 23-year-old woman and a 43-year-old man. Tumor size was 22 and 4.2 cm, respectively. Patient 1 developed skeletal and multiple pulmonary metastases. She died of disease 82 months later, despite aggressive multimodality therapy. Patient 2 has no evidence of recurrence or metastasis (8 months after surgery). Histologic examination showed similar appearance with monotonous bland medium-sized epithelioid cells with rounded slightly vesicular nuclei and clear cytoplasm imparting a carcinoma-like appearance set within a highly sclerotic hyaline fibrous stroma. The tumor cells were arranged in nests, single cell cords, trabeculae, or solid sheets with frequent entrapment of renal tubules and glomeruli. Immunohistochemistry showed strong expression of vimentin, bcl2, CD99, and MUC4, whereas cytokeratin and other markers were negative. Fluorescence in situ hybridization showed a translocation involving the EWSR1 gene locus in case 2. Molecular analysis in case 1 was not successful due to poor signal quality. To our knowledge, this is the second report documenting primary renal SEF. Awareness of this entity would help avoid misinterpretation as clear cell carcinoma, sclerosing perivascular epithelioid cell tumor, Xp.11 translocation carcinoma, and other more frequent neoplasms at this site.
EVALuna2:6701

Second International Conference on a classification of ectodermal dysplasias: development of a multiaxis model - Salinas, Carlos F.; Irvine, Alan D.; Itin, Peter H.; Di Giovanna, John J.; Schneider, Holm; Clarke, Angus J.; Mcgovern, Laura Sternesky; Fete, Mary (American Journal of Medical Genetics Part A, 2014)
Ectodermal dysplasias (EDs) comprise a large clinically and etiologically heterogeneous group of genetic disorders characterized by abnormalities in tissues derived from the embryonic ectoderm. Controversy exists over which syndromes should be classified as EDs and which should be excluded from the classification. The challenge will be to balance comprehensiveness within the classification with usability and accessibility so that the benefits truly serve the needs of researchers, health-care providers, and ultimately the individuals and families directly affected by EDs. The overarching goal of the Second International Conference was to develop a consensus on EDs classifications, with the ultimate goal of creating a system that integrates clinical and molecular knowledge, using an interactive Internet-based database that clinicians, researchers, and laymen can use. The Conference, brought together a group of experts from around the world, including a diverse health-care providers, researchers, patient advocate representatives, and administrators. The Conference was modeled after the 2008 conference, with plenary sessions, scientific updates, and small group discussions. Based on the present clinical knowledge, new molecular advances and both coupled with new bioinformatics developments, the participants agree to develop a multi-axis system approach for the classification of EDs. The multi-axis approach will include a clinical/phenotype axis, a gene-based axis, and a functional/pathways axis. The significance of the conference outcomes includes, a new classification approach that will foster a better understanding of EDs, open new fields of research and develop a nosologic approach that may have broad implications for classifying other hereditary conditions.
EVALuna2:18896

Seizure-induced neuronal apoptosis is related to dysregulation of the RNA-edited GluR2 subunit in the developing mouse brain - Jung, Susan; Ballheimer, Yili Elisabeth; Brackmann, Florian; Zoglauer, Daniel; Geppert, Carol-Immanuel; Hartmann, Arndt; Trollmann, Regina (Brain Research, 2020)
Ca2+-permeable AMPA receptors (AMPAR) which crucially modify maturational programs of the developing brain are involved in seizure-induced glutamate excitotoxicity and apoptosis. Regulatory effects on AMPAR subunit composition and RNA-editing in the developing brain and their significance as therapeutic targets are not well understood. Here, we analyzed acute effects of recurrent pilocarpine-induced neonatal seizures on age- and region-specific expression of AMPAR subunits and adenosine deaminases (ADAR) in the developing mouse brain (P10). After recurrent seizure activity and regeneration periods of 6–72 h cerebral mRNA levels of GluR (glutamate receptor subunit) 1, GluR2, GluR3, and GluR4 were unaffected compared to controls. However, ratio of GluR2 and GluR4 to pooled GluR1-4 mRNA concentration significantly decreased in seizure-exposed brains in comparison to controls. After a regeneration period of 24–72 h ADAR1 and ADAR2 mRNA expression was significantly lower in seizure-exposed brains than in those of controls. This was confirmed at the protein level in the hippocampal CA3 region. We observed a regionally increased apoptosis (TUNEL+ and CC3+ cells) in the hippocampus, parietal cortex and subventricular zone of seizure-exposed brains in comparison to controls. Together, present in vivo data demonstrate the maturational age-specific, functional role of RNA-edited GluR2 in seizure-induced excitotoxicity in the developing mouse brain. In response to recurrent seizure activity, we observed reduced expression of GluR2 and the GluR2 mRNA-editing enzymes ADAR1 and ADAR2 accompanied by increased apoptosis in a region-specific manner. Thus, AMPA receptor subtype-specific mRNA editing is assessed as a promising target of novel neuroprotective treatment strategies in consideration of age-related developmental mechanisms.
CRIS-Team Scopus Importer:2020-03-17
Keywords: ADAR; Adenosine deaminases; Apoptosis; Brain injury; Experimental seizure model; Neonatal brain; Neurodegeneration; Neuroprotection; Pilocarpine; RNA editing

Seizure management and prescription patterns of anticonvulsants in Dravet syndrome: A multicenter cohort study from Germany and review of literature - Schubert-Bast, Susanne; Wolff, Markus; Wiemer-Kruel, Adelheid; von Spiczak, Sarah; Trollmann, Regina; Reif, Philipp S.; Pritchard, Clive; Polster, Tilman; Neubauer, Bernd A.; Mayer, Thomas; Macdonald, Daniel; Kurlemann, Gerhard; et al. (Epilepsy & Behavior, 2019)
Objective: The aim of this study was to describe the treatment pattern of patients with Dravet syndrome (DS) in Germany with routine antiepileptic drugs (AEDs) and emergency medication, and to review the literature of real-world evidence on medicine utilization of patients with DS in Europe. Methods: Patient use of routine AEDs and emergency medications over 3–6 months was analyzed from a 2018 multicenter survey of 93 caregivers of patients with DS throughout Germany. Results were contextualized in a review of real-world evidence on medicine utilization of patients with DS in Europe. Results: The variety of medications and the most frequent combinations routinely used by patients with DS (AEDs and others) are described. Patients use a large number of pharmaceutical treatments to manage seizures. The five most commonly used AEDs were sodium valproate (66% of the patients; mean daily dose: 660 mg; 24.5 mg per kg bodyweight), bromide (44%; 1462 mg; 51.2 mg per kg), clobazam (41%; 10.4 mg; 0.32 mg per kg), stiripentol (35%; 797 mg; 27.6 mg per kg), and topiramate (24%; 107 mg; 3.5 mg per kg). Ninety percent had reported using emergency medications in the last 3 months;, with the most common medications being Buccolam (40%, an oromucosal form of midazolam) and diazepam (20%, mostly rectal application). No discernable relationships between current medication and age or seizure frequency were observed. Significance: This is the first comprehensive report of routine AEDs and emergency medication use in a large sample of patients with DS in Germany over a period of 3–6 months and shows that despite the most common AED combinations being in line with clinical guidelines/best practice, there is no discernable impact of best treatment on seizure frequency. We find a higher use of bromide in Germany compared with other real-world evidence in Europe.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Antiepileptic drugs; Benzodiazepines; Epilepsy; Severe myoclonic epilepsy of infants

Selecting A Digitization Device for Bone Marrow Aspirate Smears - Kock, Farina; Pontones, Martina; Ghete, Tabita; Metzler, Markus; Höfener, Henning (Laboratory Investigation, 2025)
The digitization of histologic specimens has become increasingly common within the last years; however, digitization of cytologic slides has its own challenges and there is little guidance on the optimal use of digitization devices for cytopathology. For the morphologic analysis of cells in, for example, bone marrow aspirate smears, different studies have used a variety of scanner setups and there is no direct comparison between those. This makes it nontrivial to choose an optimal scanner setup. This work pragmatically analyzes different whole-slide image scanners but also cost-effective light microscope solutions and identifies important aspects for the digitization of cytopathological samples. We aimed to share our experience in selecting a digitization device for generating a bone marrow aspirate data set.
CRIS-Team Scopus Importer:2025-03-28
Keywords: bone marrow aspirate smear; cytology; digitization; light microscope; whole-slide image scanner

Sex chromosome DSD individuals with mosaic 45,X0 and aberrant Y chromosomes in 46,XY cells: distinct gender phenotypes and germ cell tumour risks§ - Vogt, Peter H.; Besikoglu, Banu; Bettendorf, Markus; Frank-Herrmann, Petra; Zimmer, Jutta; Bender, Urike; Knauer-Fischer, Sabine; Choukair, Daniela; Sinn, Peter; Dörr, Helmuth-Günther; Wölfle, Joachim; Heidemann, Peter H.; et al. (Systems Biology in Reproductive Medicine, 2022)
“Differences of Sexual Development (DSD),” individuals with rearranged Y chromosome breaks in their 46,XY cells are reported with male and female gender phenotypes and differences in germ cell tumour (GCT) risk. This raised the question of whether male or female gender and GCT risk depends on the site of the break and/or rearrangement of the individual´s Y chromosome. In this paper, we report molecular mapping of the breakpoint on the aberrant Y chromosome of 22 DSD individuals with a 45,X/46,XY karyotype reared with a different gender. Their Y chromosome breaks are found at different sites on the long and short Y arms. Our data indicate that gender rearing is, neither dependent on the site of Y breakage, nor on the amount of 45,X0 cells in the individuals' leukocytes. Most prominent are secondary rearrangements of the Y chromosome breaks forming di-centric Y-structures (“dic-Y”). Duplications of the short Y arm and the proximal part of the long Y arm are the results. A putative GCT risk has been analysed with immunohistochemical experiments on some dysgenetic gonadal tissue sections. With specific antibodies for OCT3/4 expression, we marked the pluripotent germ cell fraction being potential tumour precursor cells. With specific antibodies for DDX3Y, TSPY, and UTY we analyzed their putative Gonadoblastoma Y (GBY) tumour susceptibility function in the same specimen. We conclude GBY expression is only diagnostic for GCT development in the aberrant germ cells of these DSD individuals when strong OCT3/4 expression has marked their pluripotency.
CRIS-Team Scopus Importer:2022-05-27
Keywords: 45X/46XY mosaic DSD; di-centric Y chromosome; Germ cell tumour risk; OCT3/4 expression GBY expression

Sex differences in long-term kidney fibrosis following neonatal nephron loss during ongoing nephrogenesis - Menendez-Castro, Carlos; Cordasic, Nada; Fahlbusch, Fabian; Wölfle, Joachim; Hilgers, Karl Friedrich; Hartner, Andrea (Molecular and Cellular Pediatrics, 2023)
Background: Clinical studies suggest that female sex plays a protective role in the development and progression of kidney disease. Recent experimental studies indicate that in male rats early nephron loss under ongoing nephrogenesis is accompanied by severe long-term sequelae. In humans, nephron formation occurs mainly in the third trimester, ceasing with 36 weeks of gestation. Due to perinatal complications, preterm infants delivered during this vulnerable period may undergo acute nephron loss. In rats nephrogenesis persists until postnatal day 10, reflecting the situation of human preterms with persisting nephrogenesis. In our animal model of neonatal uninephrectomy, female and male rats were uninephrectomized at day 1 of life. Hypothesizing sex-dependent differences, long-term renal outcome was assessed after 1 year. Results: In both sexes, neonatal uninephrectomy was not followed by arterial hypertension at 1 year of age. Compensatory weight gain and glomerular hypertrophy of the remaining kidney occurred in uninephrectomized female and male animals. Selected markers of interstitial inflammation and fibrosis were regulated sex-dependently. The expression of monocyte chemoattractant protein-1 was increased in females, while tubulointerstitial infiltration by M1 macrophages was significantly higher in males after neonatal uninephrectomy. Neonatally uninephrectomized male rats had more glomerulosclerosis and podocyte damage compared to females, which was assessed by a semiquantitative score and desmin staining. RT-PCR revealed that after neonatal uninephrectomy in the remaining contralateral kidney of female rats the expression of candidate genes of renal development and function, i.e., wt-1, nephrin, synaptopodin, gdnf, and itga8 was higher than in males. Conclusions: Based on these observations we conclude that female sex is protective in the long-term response of the kidney to acute nephron loss under active nephrogenesis.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Kidney fibrosis; Neonatal nephron loss; Neonatal uninephrectomy; Nephrogenesis; Sex differences

Shedding light on pediatric diseases: multispectral optoacoustic tomography at the doorway to clinical applications. - Regensburger, Adrian; Wagner, Alexandra; Claussen, Jing; Waldner, Maximilian; Knieling, Ferdinand (Molecular and Cellular Pediatrics, 2020)
Optoacoustic imaging (OAI), or photoacoustic imaging (PAI), has fundamentally influenced basic science by providing high-resolution visualization of biological mechanisms. With the introduction of multispectral optoacoustic tomography (MSOT), these technologies have now moved closer to clinical applications. MSOT utilizes short-pulsed near-infrared laser light to induce thermoelastic expansion in targeted tissues. This results in acoustic pressure waves, which are used to resolve specific endo- and exogenous chromophores. Especially in the pediatric population, this non-invasive imaging approach might hold fundamental advantages compared to conventional cross-sectional imaging modalities. As this technology allows the visualization of quantitative molecular tissue composition at high spatial resolution non-invasively in sufficient penetration depth, it paves the way to personalized medicine in pediatric diseases.
EVALuna2:383218

Short Children with CHARGE Syndrome: Do They Benefit from Growth Hormone Therapy? - Dörr, Helmuth-Günther; Boguszewski, Margaret; Dahlgren, Jovanna; Dunger, David; Geffner, Mitchell E.; Hokken-Koelega, Anita C.; Lindberg, Anders; Polak, Michel; Rooman, Raoul (Hormone Research in Paediatrics, 2015)
The aim of this study was to evaluate the response to recombinant growth hormone (GH) treatment in short children with CHARGE syndrome.We identified 51 children (28 boys and 23 girls) in KIGS (Pfizer International Growth Database). The median chronological age was 7.6 years at the start of GH therapy and 13.2 years at the latest visit. Evaluation for GH deficiency (n = 33) was based on the following: peak GH level 7.3 ?g/l and IGF-I level -2.01 standard deviation score (SDS). Sixteen subjects (9 boys) were followed longitudinally for 2 years.Birth length (median SDS, -0.47) and weight (-0.97) were slightly reduced. At the start of GH therapy, height was -3.6 SDS, BMI -0.7 SDS, and the GH dose was 0.26 mg/kg/week. At the latest visit after 2.7 years of GH therapy, height had increased to -2.2 SDS and BMI to -0.5 SDS. In the longitudinal group, height increased from -3.72 SDS at the start of GH therapy to -2.92 SDS after 1 year to -2.37 SDS after 2 years of therapy (start - 2 years: p < 0.05), height velocity increased from -1.69 to 2.98 to 0.95 SDS, and BMI and GH dose (mg/kg/week) remained almost unchanged.Our data show a positive effect of conventional doses of GH on short-term growth velocity for the longitudinal as well as for the total group, without any safety issues.
EVALuna2:18915

Short-term adverse effects of testosterone used for priming in prepubertal boys before growth hormone stimulation test - Albrecht, Andrea; Penger, Theresa; Marx, Martin; Hirsch, Karin; Dörr, Helmuth-Günther (Journal of Pediatric Endocrinology & Metabolism, 2018)
BACKGROUND: Despite the fact that priming with sex steroids in prepubertal children before growth hormone (GH) provocative tests is recommended, there is an ongoing controversial discussion about the appropriate age of the children, the drug used for priming, the dose and the period between priming and the GH test. Interestingly, there is no discussion on the safety of this procedure. To date, only little data have been available on the possible side effects of priming with testosterone. METHODS: We analyzed the outcome in 188 short-statured prepubertal boys who had been primed with testosterone enanthate (n=136: 50 mg; n=51: 125 mg, and accidentally one boy with 250 mg) 7 days prior to the GH test. Serum testosterone levels were measured on the day of the GH test in 99 boys. RESULTS: Overall, only five boys developed adverse side effects. Two boys (dose 125 mg) showed severe low-flow priapism and had to undergo decompression of the corpora cavernosa. One boy suffered from self-limiting priapism and testicular pain (dose 50 mg). Two patients reported testicular pain (each dose 50 mg). The single patient with 250 mg testosterone did not show any adverse effects. The total side effect rate was 2.7%. The serum testosterone levels of the boys with side effects were not different from the testosterone levels of the boys without any side effects. CONCLUSIONS: Parents and patients should be informed about the possible side effects of priming with testosterone such as priapism and testicular pain. However, the overall side effect rate is low. We found no correlation between the outcome and the testosterone dose used and/or the level of serum testosterone.
EVALuna2:35502

Short-term response of metabolic hormones to coronary artery bypass surgery - Nemeth, Adam; Cziraki, Attila; Sulyok, Endre; Horvath, Ivan Gabor; Alotti, Nasri; Rauh, Manfred; Rascher, Wolfgang; Szabados, Sandor (Advances in Medical Sciences, 2014)
To explore the response pattern of plasma adipokine and ghrelin levels to coronary artery bypass graft (CABG) surgery in patients with (on-pump) and without (off-pump) cardiopulmonary bypass (CPB).Sixteen consecutive patients (age: 62 ± 10 years, male: 10) with obstructive coronary artery disease (CAD) who underwent elective CABG surgery with CPB and intraoperative GIK infusion were selected for on-pump group and 19 CAD patients (age: 63 ± 10 years, male: 16) were included in the off-pump group. Blood samples were taken before, during and after surgery. Intraoperative samples were withdrawn simultaneously for peripheral vein and sinus coronarius (SC). Plasma adipokine concentrations were measured by ELISA, those of ghrelin by RIA kits.In response to surgical intervention there was an early, transient fall in plasma levels of adiponectin (p<0.0001) and resistin (p=0.002) followed by an increase to approach their initial values. Plasma ghrelin also increased (p=0.045), this increase, however, was confined to the period of GIK supported CPB. Plasma insulin (p=0.003) and resistin (p=0.009) was significantly higher in the peripheral vein than in SC. The perioperative hormone profile of patients without CPB (off-pump) proved to be comparable to that of on-pump patients in spite of the insulin administration and greater oxidative and inflammatory stress.Adipose tissue-derived factors appear to mediate the metabolic and vascular changes that occur in patients with CABG surgery. Epicardial adipose tissue is unlikely to have major contribution to the development of CAD as adipokines are not elevated in SC independent of the mode of intervention.
EVALuna2:18893

Short-term safety results from compassionate use of risdiplam in patients with spinal muscular atrophy in Germany - Hahn, Andreas; Guenther, Rene; Ludolph, Albert; Schwartz, Oliver; Trollmann, Regina; Weydt, Patrick; Weiler, Markus; Neuland, Kathrin; Schwaderer, Martin Sebastian; Hagenacker, Tim (Orphanet Journal of Rare Diseases, 2022)
Background The oral, selective SMN2-splicing modifier risdiplam obtained European approval in March 2021 for the treatment of patients >= 2 months old with a clinical diagnosis of 5q-associated spinal muscular atrophy (SMA) 1/2/3 or with 1-4 SMN2 gene copies. For the preceding 12 months, this compassionate use program (CUP) made risdiplam available to patients with SMA1/2 in Germany who could not receive any approved SMA therapy. Patients and methods Patients with SMA1/2, aged >= 2 months at enrollment, could be included if they were not eligible for, no longer responsive to, or not able to tolerate nusinersen or not able to receive onasemnogene abeparvovec. Oral risdiplam dosing ranged from 0.2 mg/kg to 5 mg depending on age and weight. All treatment decisions were made by the attending physicians, who were required to report all adverse events (AEs). Results Between March 12, 2020 and March 30, 2021, 36 patients with SMA1 and 98 patients with SMA2 were enrolled, with 31 patients and 80 patients receiving >= 1 risdiplam dose, respectively. The median (range) age was 10.5 (3-52) years in the SMA1 cohort, and 26.5 (3-60) years in the SMA2 cohort. 22.2% of patients with SMA1 and 48.0% with SMA2 were treatment-naive. Most patients were not eligible/could not continue to receive nusinersen due to scoliosis/safety risk (SMA1: 75.0%; SMA2: 96.9%), risks associated with sedation (77.8%; 63.3%), or loss of efficacy (30.6%; 12.2%). Safety data were generally in line with the safety profile of risdiplam in ongoing clinical studies. Gastrointestinal disorders were the most common AEs. For patients with SMA1, 30 AEs were reported in 13 cases with 2 serious AEs in 1 patient. For SMA2, 100 AEs were documented in 31 case reports, including 8 serious AEs in 2 patients. Conclusions We present the first real-world safety data of risdiplam in patients with SMA in Germany. Our observations indicated no new safety signals under real-world conditions. Real-world SMA1/2 populations comprise considerable numbers of patients who are not eligible for gene therapy and cannot tolerate or have failed nusinersen treatment. This medical need may be addressed by oral risdiplam.
CRIS-Team WoS Importer:2022-07-29

SIADH as a Rare Complication of Foramen Magnum Stenosis in an Infant With Achondroplasia. - Cebeci, Ayse Nurcan; Hébert, Steven; Reutter, Heiko Martin; Rompel, Oliver; Wölfle, Joachim (JCEM Case Reports, 2024)
Achondroplasia is the most common skeletal dysplasia and is associated with serious complications such as foramen magnum stenosis (FMS). This case report describes an infant with achondroplasia who presented with a syndrome of inappropriate antidiuretic hormone secretion (SIADH), secondary to significant FMS and myelocompression. A 2-month-old boy with prenatally diagnosed achondroplasia was referred due to disordered breathing and altered consciousness. On admission, apathy, hypotonus, and hypothermia with typical features of achondroplasia were noticed. Laboratory investigations revealed severe hyponatremia and hypochloridaemia with normal glucose and urea levels. The diagnosis of SIADH was made based on low serum osmolality in the presence of high urine osmolality, along with an elevated copeptin level. An emergency computerized tomography showed a high-grade stenosis at the cranio-cervical junction; subsequent magnetic resonance imaging demonstrated myelocompression. The patient underwent decompression surgery the next day; serum osmolality increased after the operation. Spontaneous breathing after extubation was sufficient whereas tetraplegia persisted despite intensive physiotherapy. Clinicians should be aware of SIADH as a presenting sign of FMS in children with achondroplasia. Further discussion is warranted regarding improving parental education and timing of screening recommendations.
EVALuna2:582017

SIADH as presenting feature of foramen magnum stenosis in a 2-month-old infant with achondroplasia (ACH): case report and discussion on management of infants with ACH in order to reduce the risk of serious complications - Cebeci, Ayse Nurcan; Hébert, Steven; Reutter, Heiko Martin; Wölfle, Joachim (HORMONE RESEARCH IN PAEDIATRICS, 2022)
CRIS-Team WoS Importer:2022-10-07

Sickle cell disease in Germany: Results from a national registry - Kunz, Joachim B.; Lobitz, Stephan; Grosse, Regine; Oevermann, Lena; Hakimeh, Dani; Jarisch, Andrea; Cario, Holger; Beier, Rita; Schenk, Daniela; Schneider, Dominik; Gross-Wieltsch, Ute; Prokop, Aram; et al. (Pediatric Blood & Cancer, 2019)
Background Limited data on the prevalence and medical care of sickle cell disease (SCD) in Germany are available. Here, we make use of a patient registry to characterize the burden of disease and the treatment modalities for patients with SCD in Germany. Procedure A nationwide German registry for patients with SCD documents basic data on diagnosis and patient history retrospectively at the time of registration. A prospective annual documentation provides more details on complications and treatment of SCD. For the current analyses, data of 439 patients were available. Results Most patients had homozygous SCD (HbSS 75.1%, HbS/beta-thalassemia 13.2%, and HbSC 11.3%). The median age at diagnosis was 1.9 years (interquartile range, 0.6-4.4 years), most patients were diagnosed when characteristic symptoms occurred. Sepsis and stroke had affected 3.2% and 4.2% of patients, respectively. During the first year of observation, 48.3% of patients were admitted to a hospital and 10.1% required intensive care. Prophylactic penicillin was prescribed to 95.6% of patients with homozygous SCD or HbS/beta thalassemia below the age of six and hydroxycarbamide to 90.4% of patients above the age of two years. At least one annual transcranial Doppler ultrasound was documented for 74.8% of patients between 2 and 18 years. Conclusion With an estimated number of at least 2000, the prevalence of SCD in Germany remains low. Prospectively, we expect that the quality of care for children with SCD will be further improved by an earlier diagnosis after the anticipated introduction of a newborn screening program for SCD.
CRIS-Team WoS Importer:2020-01-07

Side Effects and Sequelae of Treatment for Chronic Myeloid Leukemia in Childhood and Adolescence - Suttorp, Meinolf; Metzler, Markus (Springer International Publishing, 2020)
Targeted therapy by tyrosine kinase inhibitors (TKIs) has dramatically improved survival rates in CML. Today stem cell transplantation is no longer the first-line treatment also in children. However, in the majority of patients, TKIs probably have to be administered over decades to control instead of eradicating completely the malignant cell clone. Thus, CML nowadays has to be regarded in sensu stricto as “chronic” which is in sharp contrast to the other pediatric malignancies dealt with in the context of this book. Lifelong TKI administration requires assessment of any side or “late” effect as a possible “untargeted consequence of a targeted treatment, " which represents a novelty in pediatric oncology. Systematic investigations on TKI late effects in adults are missing, and the cumulative toxicity of ongoing exposure in a growing organism with regard to young and old adulthood is presently hard to be judged on. Side effects so far observed include longitudinal growth impairment, disturbed osseous metabolism, endocrine alterations (hyperparathyroidism, low vitamin D, low growth hormone, altered thyroid metabolism, blood glucose level, impaired fertility), and cardiovascular side effects. Any change in laboratory findings or reported health problems should as causative agent take TKIs into consideration. Most TKIs are substrates and inhibitors of cytochrome P450. If patients are treated with polypharmacy because of TKI side effects or other underlying diseases, drug-drug interactions are always a significant safety concern. While men wanting to become fathers can safely remain on imatinib, women of childbearing potential must be advised on the teratogenic potential of all TKIs. Thus, proper contraception should start early in teenagers. Future strategies including new drugs or vaccination targeting specifically at CML stem cells are currently being explored. First results look promising; however, it seems not unlikely that side effects and late effects may also be associated with these new approaches.
CRIS-Team Scopus Importer:2024-12-16

Significant advantages for first line treatment with TNF-alpha inhibitors in pediatric patients with inflammatory bowel disease – Data from the multicenter CEDATA-GPGE registry study - Claßen, Merle; de Laffolie, Jan; Claßen, Martin; Schnell, Alexander; Sohrabi, Keywan; Hörning, André (Frontiers in Pediatrics, 2022)
Background and aims: In recent years, biological agents, such as anti-TNF-α blockers, have been introduced and have shown efficacy in pediatric patients with inflammatory bowel disease (IBD). Here, the prescription mode differentiated into a first/second line application, and efficacy and side effects are evaluated beginning from 2004 until today. Methods: Statistical analyses of the prospective and ongoing CEDATA multicenter registry data from the Society of Pediatric Gastroenterology and Nutrition (GPGE) were performed for patients receiving a biological agent at least once during the period from June 2004 until November 2020 (n = 487). The analyzed parameters were patient demographics, disease extent and behavior, prior or concurrent therapies, duration and outcome of biological therapy, disease-associated complications, drug-related complications, laboratory parameters and treatment response as determined by the Physician’s Global Assessment. Results: Crohn’s disease (CD) was present in 71.5% of patients, and 52% were boys. Patients showed high disease activity when receiving a first-line TNF-α blocker. After 2016, patients who failed to respond to anti-TNF-α induction therapy were treated with off-label biologics (vedolizumab 4.3% and ustekinumab 2.1%). Propensity score matching indicated that patients with CD and higher disease activity benefitted significantly more from early anti-TNF-α therapy. This assessment was based on a clinical evaluation and lab parameters related to inflammation compared to delayed second-line treatment. Additionally, first-line treatment resulted in less treatment failure and fewer extraintestinal manifestations during TNF-α blockade. Conclusion: First-line treatment with anti-TNF-α drugs is effective and safe. An earlier start significantly reduces the risk of treatment failure and is associated with fewer extraintestinal manifestations during longitudinal follow-up.
CRIS-Team Scopus Importer:2022-11-04
Keywords: anti-TNF-α inhibitor therapy; Crohn’s disease; first-line therapy; pediatric inflammatory bowel disease (IBD); ulcerative colitis

Sleep-Disordered Breathing in Children with Prader-Willi Syndrome in Relation to Growth Hormone Therapy Onset - Zimmermann, Maja; Laemmer, Constanze; Wölfle, Joachim; Fimmers, Rolf; Gohlke, Bettina (Hormone Research in Paediatrics, 2020)
Objective: The aim of this study was to consider sleep apnea in Prader-Willi syndrome (PWS) children depending on age at growth hormone (GH) therapy onset. Study Design: We analyzed longitudinally cardiorespiratory polygraphy of 62 PWS children (aged 0-2.5 years at baseline). Twenty-one children (Group A) started GH-therapy during and 41 children (Group B) after their first year of life. Data were acquired before, at 3 and 6 months, then 1.2, 2.2, and 3.2 years after GH onset. Outcomes were determined with the obstructive apnea hypopnea index (OAHI), central apnea index (CAI), oxygen desaturation index (ODI), and by measuring obstructive sleep apnea (OSA) and peripheral blood oxygen saturation (SpO2). Results: We observed no significant differences in OAHI, CAI, ODI, and SpO2 depending on treatment onset. At baseline, 5/21 patients (23.8%) in Group A versus 15/41 patients (36.6%) in Group B showed pathological sleep apnea (OAHI ≥1.5). Pathological OSA increased significantly in Group A during the first 3 months of therapy but dropped below baseline after 1 year in both groups. ODI changed during GH therapy in both groups (from 4.0 to 2.6 in Group A, and 3.6 to 1.6 in Group B; baseline to 3.2 years; p < 0.05). Conclusions: OSA in PWS children appears to develop independently of treatment onset. Treatment may therefore safely be initiated early but should be accompanied by regular sleep analysis.
CRIS-Team Scopus Importer:2020-07-10

Sleep quality, anxiety, symptoms of depression, and caregiver burden among those caring for patients with Dravet syndrome: a prospective multicenter study in Germany - Maltseva, Margarita; Schubert-Bast, Susanne; Zöllner, Johann Philipp; Bast, Thomas; Mayer, Thomas; von Spiczak, Sarah; Ruf, Susanne; Trollmann, Regina; Wolff, Markus; Hornemann, Frauke; Klotz, Kerstin A.; Jacobs, Julia; et al. (Orphanet Journal of Rare Diseases, 2023)
Background: This study measured sleep quality among caregivers of patients with Dravet syndrome (DS) and assessed the impacts of mental health problems and caregiver burden on sleep quality. Methods: This multicenter, cross-sectional study of patients with DS and their caregivers throughout Germany consisted of a questionnaire and a prospective 4-week diary querying disease characteristics, demographic data, living conditions, nocturnal supervision, and caregivers’ work situations. Sleep quality was assessed using the Pittsburgh Sleeping Quality Index (PSQI). The Hospital Anxiety and Depression Scale (HADS) and the Burden Scale for Family Caregivers (BSFC) were used to measure anxiety, symptoms of depression, and caregiver burden. Results: Our analysis included 108 questionnaires and 82 four-week diaries. Patients with DS were 49.1% male (n = 53), with a mean age of 13.5 ± 10.0 years. Caregivers were 92.6% (n = 100) female, with a mean age of 44.7 ± 10.6 years. The overall mean PSQI score was 8.7 ± 3.5, with 76.9% of participants (n = 83) scoring 6 or higher, indicating abnormal sleep quality. The HADS for anxiety and depression had overall mean scores of 9.3 ± 4.3 and 7.9 ± 3.7, respectively; 61.8% and 50.9% of participants scored above the cutoff value of 8 for anxiety and depression, respectively. Statistical analyses revealed caregiver anxiety levels and patients’ sleep disturbances as major factors influencing PSQI scores. The overall mean BSFC score of 41.7 ± 11.7 indicates a moderate burden, with 45.3% of caregivers scoring 42 or higher. Conclusions: Sleep quality is severely affected among caregivers of patients with DS, correlating with anxiety, comorbidities, and patients’ sleep disturbances. A holistic therapeutic approach should be implemented for patients with DS and their caregivers, focusing on the sleep quality and mental health of caregivers. Trial registration: German Clinical Trials Register (DRKS), DRKS00016967. Registered 27 May 2019, http://www.drks.de/DRKS00016967
CRIS-Team Scopus Importer:2023-05-12
Keywords: Encephalopathy; Epilepsy; Quality of life; Seizure

Social inequalities in the participation and activity of children and adolescents with leukemia, brain tumors, and sarcomas (SUPATEEN): a protocol for a multicenter longitudinal prospective observational study - Roick, Julia; Berner, Reinhard; Bernig, Toralf; Erdlenbruch, Bernhard; Escherich, Gabriele; Faber, Jörg; Klein, Christoph; Bochennek, Konrad; Kratz, Christian; Kühr, Joachim; Längler, Alfred; Lode, Holger N.; et al. (BMC Pediatrics, 2020)
BACKGROUND: About 2000 children and adolescents under the age of 18 are diagnosed with cancer each year in Germany. Because of current medical treatment methods, a high survival rate can be reached for many types of the disease. Nevertheless, patients face a number of long-term effects related to the treatment. As a result, physical and psychological consequences have increasingly become the focus of research in recent years. Social dimensions of health have received little attention in health services research in oncology so far. Yet, there are no robust results that allow an estimation of whether and to what extent the disease and treatment impair the participation of children and adolescents and which factors mediate this effect. Social participation is of great importance especially because interactions with peers and experiences in different areas of life are essential for the development of children and adolescents. METHODS: Data are collected in a longitudinal, prospective, observational multicenter study. For this purpose, all patients and their parents who are being treated for cancer in one of the participating clinics throughout Germany will be interviewed within the first month after diagnosis (t1), after completion of intensive treatment (t2) and half a year after the end of intensive treatment (t3) using standardized questionnaires. Analysis will be done by descriptive and multivariate methods. DISCUSSION: The results can be used to identify children and adolescents in high-risk situations at an early stage in order to be able to initiate interventions tailored to the needs. Such tailored interventions will finally reduce the risk of impairments in the participation of children and adolescents and increase quality of life. TRIAL REGISTRATION: ClinicalTrials.gov: NCT04101123.
CRIS-Team Scopus Importer:2020-02-11
Keywords: Brain tumors; Cancer; Children and adolescents; Leukemia; Patient reported outcomes; Sarcomas; Social participation

SOCIO-ECONOMIC IMPACT OF DRAVET SYNDROME IN GERMANY: A REAL-WORLD STUDY - Irwin, J.; Strzelczyk, A.; Kalski, M.; Bast, T.; Wiemer-Kruel, A.; Bettendorf, U.; Kieslich, M.; Kluger, G.; Kurlemann, G.; Mayer, T.; Neubauer, B. A.; Polster, T.; et al. (VALUE IN HEALTH, 2018)
CRIS-Team WoS Importer:2019-03-15

Somatic variant profiling in chronic phase pediatric chronic myeloid leukemia. - Behrens, Yvonne Lisa; Gaschler, Laura; Nienhold, Ronny; Reinkens, Thea; Schirmer, Elke; Knöβ, Sabine; Strasser, Renate; Sembill, Stephanie; Wotschofsky, Zofia; Suttorp, Meinolf; Krumbholz, Manuela; Schlegelberger, Brigitte; et al. (Haematologica, 2024)
EVALuna2:546999

Spectrum, Applicability and Diagnostic Capacity of Contrast-Enhanced Ultrasound in Pediatric Patients and Young Adults after Intravenous Application - A Retrospective Trial - Knieling, Ferdinand; Strobel, Deike; Rompel, O.; Zapke, M.; Menendez-Castro, C.; Woelfel, M.; Schulz, J.; Rascher, Wolfgang; Juengert, J. (Ultraschall in der Medizin, 2016)
Purpose: To investigate the spectrum, applicability and diagnostic capacity of intravenous contrast-enhanced ultrasound imaging (CEUS) in a pediatric population. Materials and Methods: From 08/2005 to 11/2015, n = 40 pediatric patients and young adults from 0 - 26 years (Ø 11.4 ± 7.5) and 3.0 - 85.3 kg (Ø 40.8 ± 25.6) with n = 55 investigations received n = 79 IV applications of ultrasound contrast agent (UCA). UCA dose and side effects were documented. Scanned organs were the liver (n = 42), spleen (n = 9), kidney (n = 3), and testis (n = 1). Histology, surgery or reference imaging was compared to CEUS and clinical follow-up. Results: The UCA dose < 20 kg was 0.4 ± 0.3 ml, (0.05 ± 0.02 ml/kg) and > 20 kg was 1.0 ± 0.4 ml (p< 0.0001) (0.02 ± 0.01 ml/kg, p< 0.0001). Adverse effects occurred in 2/79 applications (2.5 %). Agreement CEUS/gold standard resulted in 32/34 investigations. For liver diagnostics (gold standard: MRI, CT, histology, serology), n = 11 malignant and n = 15 benign focal liver lesions were included. The specificity was 100 % (95 % CI: 0.77 - 1.00), the sensitivity was 82 % (95 % CI: 0.48 - 0.98), the positive predictive value was 100 % (95 % CI: 0.69 - 1.00) and the negative predictive value was 88 % (95 % CI: 0.62 - 0.98, p< 0.0001). In n = 2 reference imaging misdiagnosed and CEUS was in accordance with clinical follow-up. All splenic/renal lesions were diagnosed correctly. In n = 1 an insufficient testicular perfusion was ruled out. The observation time was 30.4 ± 30.5 months. Conclusion: CEUS is a well-tolerated and diagnostically equivalent modality in pediatric care, providing fundamental advantages compared to currently approved imaging modalities for these age groups.
EVALuna2:14718

Spontaneous postnatal growth is reduced in children with CHARGE syndrome - Dörr, Helmuth-Günther; Madeja, Julia; Junghans, Claudia (Acta Paediatrica, 2015)
There is a scarcity of data on postnatal growth in children with CHARGE syndrome, a genetic disorder. This study analysed spontaneous growth and weight in German children with CHARGE from birth to the age of 6 years.This was a retrospective analysis of 19 children, nine females and 10 males, using data from child health records. Standard deviation scores (SDS) were calculated based on Swiss references.The median birthweight was 2950 g (-0.78 SDS), and the birth length was 49 cm (-0.5 SDS). There was a significant loss of median body length, at around 4 weeks of age from -0.5 to -2.3 SDS (p < 0.05). At 1 year, the median length was -2.6 SDS and it remained low until 5 years of age when the lowest value was found to be -2.8 SDS. There was a significant increase in median body mass index (BMI) from -1.15 SDS at 1 year to -0.15 SDS at 5 years (p < 0.01).Children with CHARGE syndrome displayed almost normal length and weight data at birth, with just one of the 19 infants having below average length for gestational age. However, postnatal growth was retarded during infancy and childhood, and the increase in BMI-SDS did not correlate with growth.
EVALuna2:18914

Stammzellen aus Nabelschnurblut - ein besonderes Gut: Informationen für eine fachärztliche Beratung der Schwangeren - Goecke, Tamme W.; Jud, Sebastian; Weisbach, Volker Günter; Bender, A. W.; Schneider, Holm (Geburtshilfe und Frauenheilkunde, 2010)
CRIS-Team Scopus Importer:2020-07-01

Strong hypoxia reduces leptin synthesis in purified primary human trophoblasts - Nuesken, E.; Herrmann, Y.; Wohlfarth, M.; Goecke, Tamme W.; Appel, S.; Schneider, Holm; Doetsch, J.; Nuesken, K. D. (Placenta, 2015)
Introduction Oxygen availability severely affects placental function. During placental hypoxia, stabilization of hypoxia inducible factors (HIFs) affects transcription, and leptin gene expression concomitantly increases in vivo and in vitro. However, a causal relationship is uncertain.
CRIS-Team Scopus Importer:2020-07-01
Keywords: Hypoxia; Leptin/leptin receptor; Placenta; Trophoblast

Surprising prenatal toxicity of epidermal lipoxygenase-3 - Vierling, F.; Dick, Angela; Wahlbuhl, Mandy; Krieg, P.; Henke, Christine; Ruebner, M.; Schneider, Holm (Placenta, 2014)
Metabolites of the epidermal lipoxygenase-3 (eLOX-3) are involved in various metabolic pathways. Most unexpectedly, intra-amniotic delivery of eLOX-3 to mice at gestational day 14.5, both via an adenoviral vector and as recombinant protein, resulted in fetal growth restriction and intrauterine death. Periodic acid-Schiff staining and RT-PCR analysis of placentae from fetuses exposed to eLOX-3 indicated a lack of glycogen trophoblasts in the junctional zone. Placenta-specific gene expression was altered. Thus, the observed prenatal toxicity of eLOX-3 could be due to a strong effect on placental development.
EVALuna2:17431

Surveillance of Acute SARS-CoV-2 Infections in Elementary Schools and Daycare Facilities in Bavaria, Germany (09/2020-03/2021) - Kern, Anna; Kuhlmann, Pia H.; Matl, Stefan; Ege, Markus; Maison, Nicole; Eckert, Jana; Von Both, Ulrich; Behrends, Uta; Anger, Melanie; Fruehwald, Michael C.; Gerstlauer, Michael; Wölfle, Joachim; et al. (Frontiers in Pediatrics, 2022)
IntroductionHere we report our results of a multi-center, open cohort study ("COVID-Kids-Bavaria") investigating the distribution of acute SARS-CoV-2 infections among children and staff in 99 daycare facilities and 48 elementary schools in Bavaria, Germany. Materials and MethodsOverall, 2,568 children (1,337 school children, 1,231 preschool children) and 1,288 adults (466 teachers, 822 daycare staff) consented to participate in the study and were randomly tested in three consecutive phases (September/October 2020, November/December 2020, March 2021). In total, 7,062 throat swabs were analyzed for SARS-CoV-2 by commercial RT-PCR kits. ResultsIn phase I, only one daycare worker tested positive. In phase II, SARS-CoV-2 was detected in three daycare workers, two preschool children, and seven school children. In phase III, no sample tested positive. This corresponds to a positive test rate of 0.05% in phase I, 0.4% in phase II and 0% in phase III. Correlation of a positive PCR test result with the local-7-day incidence values showed a strong association of a 7-day-incidence of more than 100/100,000 as compared to <100/100,000 (OR = 10.3 [1.5-438], p < 0.005). After phase III, antibody testing was offered to 713 study participants in elementary schools. A seroprevalence rate of 7.7% (students) and 4.5% (teachers) was determined. DiscussionDuring the initial waves of the SARS-CoV-2 pandemic, the risk of a positive SARS-CoV-2 result correlated positively with the local 7-day incidence. Hence, the occurrence of SARS-CoV-2 infections were reflected in schools and daycare facilities. An increased risk of SARS-CoV-2 transmission in the setting of daycare and elementary schooling was unlikely.
CRIS-Team WoS Importer:2022-08-05

Sustained complete molecular remission after imatinib discontinuation in children with chronic myeloid leukemia - Moser, Olga; Krumbholz, Manuela; Thiede, Christian; Tauer, Josephine T.; Janz, Indra; Lauten, Melchior; Dilloo, Dagmar; Metzler, Markus; Suttorp, Meinolf (Pediatric Blood & Cancer, 2014)
Approximately 40% of adults with chronic myeloid leukemia (CML) in prolonged complete molecular response (CMR) remain in CMR after imatinib discontinuation. Corresponding information in children is lacking. Two children with CML in CMR for 48 and 19 months after imatinib discontinuation showed low-level fluctuating disease at RNA transcript and genomic DNA levels. Both patients were low risk according to adult criteria. Since adults with molecular relapse responded to re-introduction of imatinib, we postulated that treatment discontinuation in low risk children might be justified within clinical trials with close monitoring. This may help to minimize exposure to imatinib and its potential side effects.
EVALuna2:18892

Sustained Need for High-Dose Zinc Supplementation in Children With Acrodermatitis Enteropathica - Hammersen, Johanna; Has, Cristina; Galiano, Matthias; Lindner, Martin; Rossi, Rainer; Kohlhase, Juergen; Schneider, Holm (Clinical Pediatrics, 2018)
EVALuna2:34298

Sweating ability and genotype in individuals with X-linked hypohidrotic ectodermal dysplasia - Schneider, Holm; Hammersen, Johanna; Preisler-Adams, Sabine; Huttner, Kenneth; Rascher, Wolfgang; Bohring, Axel (Journal of Medical Genetics, 2011)
Background: X-linked hypohidrotic ectodermal dysplasia (XLHED), the most common type of ectodermal dysplasia, is caused by EDA gene mutations. Reduced sweating contributes substantially to XLHED associated morbidity and mortality. To characterise the genotypeephenotype relationship, sweat gland function was assessed non-invasively in XLHED patients and healthy controls. Subjects and methods: In 36 genotyped XLHED patients and 29 control subjects aged 0e57 years, pilocarpine-induced sweat volume, palmar sweat pore density, and palmar skin conductance before and after stimulation were determined. Results: Among 31 XLHED males, 14 had neither detectable sweat pores nor inducible sweating, 10 showed a few sweat pores but absent sweating, and 7 produced reduced sweat volumes (1e11 ml) as compared with controls (38e93 ml). Two of the low sweating XLHED subjects had normal sweat pore counts. In all 5 heterozygous females, some sweat was detected, but generally less than in female controls. Basal and stimulated skin conductance readings were reduced in 23 of 24 non-sweating, but only in 3 of 12 low-sweating XLHED subjects. There was no correlation between sweat production and number of missing teeth. Conclusions: In contrast to prior reports on nongenotyped hypohidrotic ectodermal dysplasia populations, this study confirmed a consistent, quantifiable defect of sweat gland function in male XLHED subjects as a disease biomarker. Among 26 different EDA genotypes, specific mutations were shown to be consistently associated with anhidrosis, implying that systematic mapping of EDA mutations together with the analysis of objective clinical data may help to distinguish functionally crucial mutations from those allowing residual activity of the gene product.
CRIS-Team Scopus Importer:2020-07-01

Sweating ability of patients with p63-associated syndromes - Ferstl, Paul; Wohlfart, Sigrun; Schneider, Holm (European Journal of Pediatrics, 2018)
Sweating deficiency has been reported to represent a cardinal symptom of ectrodactyly-ectodermal dysplasia-cleft lip/palate syndrome and ankyloblepharon-ectodermal dysplasia-cleft lip/palate syndrome, two rare p63-associated disorders. According to online resources, hypohidrosis may lead to most life-threatening complications in affected patients. Thus, counseling on the prevention of hyperthermia would be indispensable in case of such syndromes, although detailed information on this issue is missing in the literature. We investigated 14 individuals with ectrodactyly-ectodermal dysplasia-cleft lip/palate syndrome (age range 2-48 years) and 9 individuals with ankyloblepharon-ectodermal dysplasia-cleft lip/palate syndrome (0.5-60 years of age) by confocal laser scanning microscopy to determine their palmar sweat duct density and by quantification of pilocarpine-induced sweating. Genotype-phenotype correlations were assessed. In 12 of 23 patients (52%), a normal amount of sweat ducts was detected. These individuals (9 with ectrodactyly-ectodermal dysplasia-cleft lip/palate syndrome, 3 with ankyloblepharon-ectodermal dysplasia-cleft lip/palate syndrome) produced sufficient sweat volumes (≥ 20 μl) in response to pilocarpine. All other patients had clearly reduced sweating ability and fewer sweat glands, but no anhidrosis. Alteration of a specific proline residue (Pro590) of p63 was consistently linked to impaired perspiration.Conclusion: Hypohidrosis in p63-associated syndromes is less common and potentially less severe than previously thought and may be attributable to certain genotypes. What is Known: • Hypohidrosis which has been listed as a cardinal symptom of AEC and EEC syndromes may lead to life-threatening hyperthermia. What is New: • Patients with EEC and AEC syndromes often can sweat normally. • Hypohidrosis seems to be attributed to certain TP63 genotypes.
EVALuna2:35484

Synergistic lethality in chronic myeloid leukemia – targeting oxidative phosphorylation and unfolded protein response effectively complements tyrosine kinase inhibitor treatment - Häselbarth, Lukas; Gamali, Sara; Saul, Domenica; Krumbholz, Manuela; Böttcher-Loschinski, Romy; Böttcher, Martin; Zou, Deyu; Metzler, Markus; Karow, Axel; Mougiakakos, Dimitrios (BMC Cancer, 2023)
Chronic myeloid leukemia (CML) is effectively treated with tyrosine kinase inhibitors (TKIs), targeting the BCR::ABL1 oncoprotein. Still, resistance to therapy, relapse after treatment discontinuation, and side effects remain significant issues of long-term TKI treatment. Preliminary studies have shown that targeting oxidative phosphorylation (oxPhos) and the unfolded protein response (UPR) are promising therapeutic approaches to complement CML treatment. Here, we tested the efficacy of different TKIs, combined with the ATP synthase inhibitor oligomycin and the ER stress inducer thapsigargin in the CML cell lines K562, BV173, and KU812 and found a significant increase in cell death. Both, oligomycin and thapsigargin, triggered the upregulation of the UPR proteins ATF4 and CHOP, which was inhibited by imatinib. We observed comparable effects on cell death when combining TKIs with the ATP synthase inhibitor 8-chloroadenosine (8-Cl-Ado) as a potentially clinically applicable therapeutic agent. Stress-related apoptosis was triggered via a caspase cascade including the cleavage of caspase 3 and the inactivation of poly ADP ribose polymerase 1 (PARP1). The inhibition of PARP by olaparib also increased CML death in combination with TKIs. Our findings suggest a rationale for combining TKIs with 8-Cl-Ado or olaparib for future clinical studies in CML.
CRIS-Team Scopus Importer:2023-12-15
Keywords: 8-chloroadenosine; ATF4; Caspase 3; CML; Olaparib; Oligomycin; Oxidative phosphorylation; PARP; Thapsigargin; TKI; UPR

Synergy of simultaneous activation of cell death pathways of unfolded protein response and of protein synthesis inhibition converges at IRE1a-immunotoxins generate a therapeutic window - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Petkovic, S.; Mellenthin, Lisa; Krumbholz, Manuela; Metzler, Markus; Mackensen, Andreas; Müller, Fabian (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Systematic comparison of donor chimerism in peripheral blood and bone marrow after hematopoietic stem cell transplantation - Bach, Christian; Steffen, M.; Rösler, Wolf; Winkler, Jürgen; Mackensen, Andreas; Stachel, Daniel; Metzler, Markus; Spriewald, B. M. (Blood Cancer Journal, 2017)
EVALuna2:13436

Systematic evaluation of exertional hyperthermia in children and adolescents with hypohidrotic ectodermal dysplasia: An observational study - Hammersen, Johanna E.; Neukam, Valentin; Nüsken, Kai-Dietrich; Schneider, Holm (Pediatric Research, 2011)
To evaluate exertional overheating and the impact of physical exercise on individuals with hypohidrotic ectodermal dysplasia (HED) and to assess protective effects of cooling devices, 13 boys and male adolescents with X-linked HED (XLHED) and age-matched healthy male controls were studied during standardized exercise on a bicycle ergometer at ambient temperatures of 25 and 30°C, without cooling and with evaporative skin cooling devices at 30°C. Body core temperature during and after exercise, heart rate, performance, endurance, and serum lactate were investigated. XLHED subjects experienced a significantly greater rise in body temperature after cycling than healthy controls, and their body temperature remained elevated longer. Maximum heart rates and lactate values did not differ significantly between XLHED and control groups. Application of skin cooling devices led to a clinically relevant attenuation of exertional hyperthermia in XLHED patients, and a previous tendency toward lower performance disappeared. This first systematic study of the effects of physical exercise on HED patients demonstrates a rapid and lasting body temperature increase in XLHED subjects after cycling, posing them at risk of exercise-induced hyperthermia. External evaporative skin cooling attenuates exertional overheating in HED patients and may facilitate their participation in athletic activities and professional life. Copyright © 2011 International Pediatric Research Foundation, Inc.
CRIS-Team Scopus Importer:2020-07-01

Targeted Inhibition of Protein Biosynthesis sensitizes Cancer Cells to IRE1a-mediated Apoptosis as a Consequence of the unfolded protein response - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Parker, S.; Wendland, Kerstin; George, Rebekka; Petkovic, S.; Mellenthin, Lisa; Emmerich, C.; Lutzny-Geier, Gloria; Mackensen, Andreas; Metzler, Markus; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Targeted inhibition of protein synthesis renders cancer cells vulnerable to apoptosis by unfolded protein response - Gsottberger, Franziska; Meier, Christina; Ammon, Anna-Maria; Parker, Scott; Wendland, Kerstin; George, Rebekka; Petkovic, Srdjan; Mellenthin, Lisa; Emmerich, Charlotte; Lutzny-Geier, Gloria; Metzler, Markus; Mackensen, Andreas; et al. (Cell Death & Disease, 2023)
Cellular stress responses including the unfolded protein response (UPR) decide over the fate of an individual cell to ensure survival of the entire organism. During physiologic UPR counter-regulation, protective proteins are upregulated to prevent cell death. A similar strategy induces resistance to UPR in cancer. Therefore, we hypothesized that blocking protein synthesis following induction of UPR substantially enhances drug-induced apoptosis of malignant cells. In line, upregulation of the chaperone BiP was prevented by simultaneous arrest of protein synthesis in B cell malignancies. Cytotoxicity by immunotoxins—approved inhibitors of protein synthesis—was synergistically enhanced in combination with UPR-inducers in seven distinct hematologic and three solid tumor entities in vitro. Synergistic cell death depended on mitochondrial outer membrane permeabilization via BAK/BAX, which correlated with synergistic, IRE1α-dependent reduction of BID, accompanied by an additive fall of MCL-1. The strong synergy was reproduced in vivo against xenograft mouse models of mantle cell lymphoma, Burkitt’s lymphoma, and patient-derived acute lymphoblastic leukemia. In contrast, synergy was absent in blood cells of healthy donors suggesting a tumor-specific vulnerability. Together, these data support clinical evaluation of blocking stress response counter-regulation using inhibitors of protein synthesis as a novel therapeutic strategy.
CRIS-Team Scopus Importer:2023-09-08

Targeted long-read sequencing of the Ewing sarcoma 6p25.1 susceptibility locus identifies germline-somatic interactions with EWSR1-FLI1 binding - Lee, Olivia W.; Rodrigues, Calvin; Lin, Shu Hong; Luo, Wen; Jones, Kristine; Brown, Derek W.; Zhou, Weiyin; Karlins, Eric; Khan, Sairah M.; Baulande, Sylvain; Raynal, Virginie; Surdez, Didier; et al. (American Journal of Human Genetics, 2023)
Ewing sarcoma (EwS) is a rare bone and soft tissue malignancy driven by chromosomal translocations encoding chimeric transcription factors, such as EWSR1-FLI1, that bind GGAA motifs forming novel enhancers that alter nearby expression. We propose that germline microsatellite variation at the 6p25.1 EwS susceptibility locus could impact downstream gene expression and EwS biology. We performed targeted long-read sequencing of EwS blood DNA to characterize variation and genomic features important for EWSR1-FLI1 binding. We identified 50 microsatellite alleles at 6p25.1 and observed that EwS-affected individuals had longer alleles (>135 bp) with more GGAA repeats. The 6p25.1 GGAA microsatellite showed chromatin features of an EWSR1-FLI1 enhancer and regulated expression of RREB1, a transcription factor associated with RAS/MAPK signaling. RREB1 knockdown reduced proliferation and clonogenic potential and reduced expression of cell cycle and DNA replication genes. Our integrative analysis at 6p25.1 details increased binding of longer GGAA microsatellite alleles with acquired EWSR-FLI1 to promote Ewing sarcomagenesis by RREB1-mediated proliferation.
CRIS-Team Scopus Importer:2023-03-17
Keywords: 6p25.1; Ewing sarcoma; EWSR1-FLI1; germline somatic interaction; GGAA microsatellite; GWAS; long-read sequencing; RREB1

Targeting metabolism effectively complements tyrosine kinase inhibitor treatment of chronic myeloid leukemia - Häselbarth, Lukas; Saul, Domenica; Krumbholz, Manuela; Mougiakaos, D.; Metzler, Markus; Karow, A. (KLINISCHE PADIATRIE, 2022)
CRIS-Team WoS Importer:2022-07-08

Targeting Muscular Hemoglobin Content for Classification of Peripheral Arterial Disease by Noninvasive Multispectral Optoacoustic Tomography - Günther, Josefine; Knieling, Ferdinand; Träger, Anna P.; Lang, Werner; Meyer, Alexander; Regensburger, Adrian; Wagner, Alexandra; Trollmann, Regina; Wölfle, Joachim; Klett, Daniel; Uter, Wolfgang; Uder, Michael; et al. (Journal of the American College of Cardiology : Cardiovascular imaging, 2023)
Created from Fastlane, Scopus look-up

T Cell Impairment Is Predictive for a Severe Clinical Course in NEMO Deficiency - Heller, Stephanie; Kölsch, Uwe; Magg, Thomas; Krüger, Renate; Scheuern, Andrea; Schneider, Holm; Eichinger, Anna; Wahn, Volker; Unterwalder, Nadine; Lorenz, Myriam; Schwarz, Klaus; Meisel, Christian; et al. (Journal of Clinical Immunology, 2020)
Purpose: NEMO-deficient patients present with variable degrees of immunodeficiency. Accordingly, treatment ranges from antibiotic prophylaxis and/or IgG-substitution to allogenic hematopoietic stem cell transplantation (HSCT). The correct estimation of the immunodeficiency is essential to avoid over- as well as under-treatment. We compare the immunological phenotype of a NEMO-deficient patient with a newly-described splice site mutation that causes truncation of the NEMO zinc-finger (ZF) domain and a severe clinical course with the immunological phenotype of three NEMO-deficient patients with missense mutations and milder clinical courses and all previously published patients. Methods: Lymphocyte subsets, proliferation, and intracellular NEMO-expression were assessed by FACS. NF-κB signal transduction was determined by measuring IκBα-degradation and the production of cytokines upon stimulation with TNF-α, IL-1β, and TLR-agonists in immortalized fibroblasts and whole blood, respectively. Results: The patient with truncated ZF-domain of NEMO showed low levels of IgM and IgG, reduced class-switched memory B cells, almost complete skewing towards naïve CD45RA+ T cells, impaired T cell proliferation as well as cytokine production upon stimulation with TNF-α, IL-1β, and TLR-agonists. He suffered from severe infections (sepsis, pneumonia, osteomyelitis) during infancy. In contrast, three patients with missense mutations in IKBKG presented neither skewing of T cells towards naïvety nor impaired T cell proliferation. They are stable on prophylactic IgG-substitution or even off any prophylactic treatment. Conclusion: The loss of the ZF-domain and the impaired T cell proliferation accompanied by almost complete persistence of naïve T cells despite severe infections are suggestive for a profound immunodeficiency. Allogenic HSCT should be considered early for these patients before chronic sequelae occur.
CRIS-Team Scopus Importer:2020-02-04
Keywords: CD45RA; immunological phenotype; NEMO deficiency; Primary immunodeficiency; T cell deficiency

Temporal evolution and differential patterns of cellular reconstitution after therapy for childhood cancers - Hofmann, Gina; Zierk, Jakob; Sobik, Bettina; Wotschofsky, Zofia; Sembill, Stephanie; Krumbholz, Manuela; Metzler, Markus; Karow, Axel (Scientific Reports, 2023)
The cellular reconstitution after childhood cancer therapy is associated with the risk of infection and efficacy of revaccination. Many studies have described the reconstitution after stem cell transplantation (SCT). The recovery after cancer treatment in children who have not undergone SCT has mainly been investigated in acute lymphoblastic leukemia (ALL), less for solid tumors. Here, we have examined the temporal evolution of total leukocyte, neutrophil and lymphocyte counts as surrogate parameters for the post-therapeutic immune recovery in a cohort of n = 52 patients with ALL in comparison to n = 58 patients with Hodgkin’s disease (HD) and n = 22 patients with Ewing sarcoma (ES). Patients with ALL showed an efficient increase in blood counts reaching the age-adjusted lower limits of normal between 4 and 5 months after the end of maintenance therapy. The two groups of patients with HD and ES exhibited a comparably delayed recovery of total leukocytes due to a protracted post-therapeutic lymphopenia which was most pronounced in patients with HD after irradiation. Overall, we observed a clearly more efficient resurgence of total lymphocyte counts in patients aged below 12 years compared to patients aged 12 to 18 years. Our results underline that the kinetics of cellular reconstitution after therapy for HD and ES differ significantly from ALL and depend on treatment regimens and modalities as well as on patient age. This suggests a need for disease, treatment, and age specific recommendations concerning the duration of infection prophylaxis and the timing of revaccination.
CRIS-Team Scopus Importer:2023-03-24

Tetrasomy of SCN2A associated with refractory neonatal epileptic encephalopathy - Krumbiegel, Mandy; Trollmann, Regina; Mammadova, Dilbar; Schnell, Alexander; Kraus, Cornelia; Ekici, Arif Bülent; Reis, André; Zweier, Christiane (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

The age of the bone marrow microenvironment influences B-cell acute lymphoblastic leukemia progression via CXCR5-CXCL13 - Zanetti, Costanza; Kumar, Rahul; Ender, Joscha; Godavarthy, Parimala S.; Hartmann, Mark; Hey, Joschka; Breuer, Kersten; Weissenberger, Eva S.; Minciacchi, Valentina R.; Karantanou, Christina; Gu, Zhaohui; Roberts, Kathryn G.; et al. (Blood, 2021)
B-cell acute lymphoblastic leukemia (B-ALL) occurs most commonly in children, whereas chronic myeloid leukemia is more frequent in adults. The myeloid bias of hematopoiesis in elderly individuals has been considered causative, but the age of the bone marrow microenvironment (BMM) may be contributory. Using various murine models of B-ALL in young vs old mice, we recapitulated B-ALL preponderance in children vs adults. We showed differential effects of young vs old BM macrophages on B-ALL cell function. Molecular profiling using RNA- and ATAC-sequencing revealed pronounced differences in young vs old BMM-derived macrophages and enrichment for gene sets associated with inflammation. In concordance with the role of C-X-C motif chemokine (CXCL) 13 for disease-associated B-cell chemoattraction, we found CXCL13 to be highly expressed in young macrophages on a translational compared with a transcriptional level. Inhibition of CXCL13 in BM macrophages impaired leukemia cell migration and decreased the proliferation of cocultured B-ALL cells, whereas recombinant CXCL13 increased pAKT and B-ALL cell expansion. Pretreatment of B-ALL–initiating cells with CXCL13 accelerated B-ALL progression. Deficiency of Cxcr5, the receptor for CXCL13, on B-ALL–initiating cells prolonged murine survival, whereas high expression of CXCR5 in pediatric B-ALL may predict central nervous system relapse. CXCL13 staining was increased in bone sections from pediatric compared with adult patients with B-ALL. Taken together, our study shows that the age of the BMM and, in particular, BM macrophages influence the leukemia phenotype. The CXCR5-CXCL13 axis may act as prognostic marker and an attractive novel target for the treatment of B-ALL.
CRIS-Team Scopus Importer:2021-11-19

The age of the bone marrow microenvironment influences B-cell acute lymphoblastic leukemia progression via CXCR5-CXCL13. - Zanetti, Costanza; Kumar, Rahul; Ender, Joscha; Godavarthy, Parimala S.; Hartmann, Mark; Hey, Joschka; Breuer, Kersten; Weissenberger, Eva S.; Minciacchi, Valentina R.; Karantanou, Christina; Gu, Zhaohui; Roberts, Kathryn G.; et al. (Blood, 2021)
B-cell acute lymphoblastic leukemia (B-ALL) occurs most commonly in children, whereas chronic myeloid leukemia is more frequent in adults. The myeloid bias of hematopoiesis in elderly individuals has been considered causative, but the age of the bone marrow microenvironment (BMM) may be contributory. Using various murine models of B-ALL in young vs old mice, we recapitulated B-ALL preponderance in children vs adults. We showed differential effects of young vs old BM macrophages on B-ALL cell function. Molecular profiling using RNA- and ATAC-sequencing revealed pronounced differences in young vs old BMM-derived macrophages and enrichment for gene sets associated with inflammation. In concordance with the role of C-X-C motif chemokine (CXCL) 13 for disease-associated B-cell chemoattraction, we found CXCL13 to be highly expressed in young macrophages on a translational compared with a transcriptional level. Inhibition of CXCL13 in BM macrophages impaired leukemia cell migration and decreased the proliferation of cocultured B-ALL cells, whereas recombinant CXCL13 increased pAKT and B-ALL cell expansion. Pretreatment of B-ALL-initiating cells with CXCL13 accelerated B-ALL progression. Deficiency of Cxcr5, the receptor for CXCL13, on B-ALL-initiating cells prolonged murine survival, whereas high expression of CXCR5 in pediatric B-ALL may predict central nervous system relapse. CXCL13 staining was increased in bone sections from pediatric compared with adult patients with B-ALL. Taken together, our study shows that the age of the BMM and, in particular, BM macrophages influence the leukemia phenotype. The CXCR5-CXCL13 axis may act as prognostic marker and an attractive novel target for the treatment of B-ALL.
EVALuna2:490620

The components of arginine and methylarginine metabolism are indicative of altered kidney function in intrauterine growth-restricted neonates - Kleinebenne, Lina; Röhrig, Waldemar; Ebach, Fabian; Reutter, Heiko Martin; Pankraz, Alexander; Heuchel, Katharina Monika; Müller, Andreas; Hilger, Alina (Journal of Hypertension, 2024)
Background: Intrauterine fetal growth restriction (IUGR) affects up to 10% of all pregnancies. Severe IUGR is associated with impaired kidney development, reduced nephron endowment, and chronic kidney disease later in life. Currently, no early predictive biomarker exists for detecting altered kidney function in neonates with IUGR. Because nephrons produce key enzymes for the metabolism of arginine and methylarginine components, we quantified and compared the concentrations of arginine and methylarginine metabolites between IUGR and non-IUGR neonates to identify potential biomarkers for the early detection of altered kidney function in IUGR neonates. Methods: Seventy-one IUGR and 123 non IUGR neonates were examined. Serum and Urine samples were obtained between 30 h and 5 days of life and between 5 and 70 days of life. Serum concentrations of creatinine, urea, symmetric and asymmetric-dimethylarginine metabolites (SDGV, SDMA, ADGV, and ADMA), guanidino-2-oxo-caproic acid (GOCA), citrulline, homocitrulline, arginine, and homoarginine were quantified using LC-MS/MS and standard clinical laboratory methods. Datasets were compared by Mann - Whitney - Wilcoxon or Chi-square tests for continuous and discrete parameters. P values were corrected for multiple comparisons using the Bonferroni method. Results: After Bonferroni correction, we found that serum creatinine, urea, SDGV, ADGV, and GOCA levels were significantly lower in neonates with IUGR. Consequently, the ratios of SDGV/SDMA, ADGV/ADMA, and GOCA/homoarginine were significantly lower in IUGR neonates. Conclusion: Our study suggests that arginine and methylarginine are possible early biomarkers for detecting altered kidney function in IUGR neonates.
CRIS-Team Scopus Importer:2024-09-06
Keywords: ADMA; AGXT2; arginine metabolites; glomerular filtration rate; homoarginine; IUGR; kidney function; SDMA

The Cytogenetic Landscape of Pediatric Chronic Myeloid Leukemia Diagnosed in Chronic Phase - Karow, Axel; Göhring, Gudrun; Sembill, Stephanie; Lutterloh, Friederike; Neuhaus, Fina; Callies, Sara; Schirmer, Elke; Wotschofsky, Zofia; Roche-Lancaster, Oisin; Suttorp, Meinolf; Krumbholz, Manuela; Metzler, Markus (Cancers, 2022)
Philadelphia chromosome-positive chronic myeloid leukemia (CML) is cytogenetically characterized by the classic translocation t(9;22)(q34;q11), whereas additional non-Philadelphia aberrations (nPhAs) have been studied extensively in adult patients with CML, knowledge on nPhAs in pediatric patients with CML is still sparse. Here, we have determined nPhAs in a cohort of 161 patients younger than 18 years diagnosed with chronic phase CML and consecutively enrolled in the German national CML-PAED-II registry. In 150 cases (93%), an informative cytogenetic analysis had been performed at diagnosis. In total, 21 individuals (13%) showed nPhAs. Of these, 12 (8%) had a variant translocation, 4 (3%) additional chromosomal aberrations (ACAs) and 5 (3%) harbored a complex karyotype. Chromosome 15 was recurrently involved in variant translocations. No significant impact of the cytogenetic subgroup on the time point of cytogenetic response was observed. Patients with a complex karyotype showed an inferior molecular response compared to patients carrying the classic translocation t(9;22)(q34;q11), variant translocations or ACAs. No significant differences in the probability of progression-free survival and overall survival was found between patients with nPhAs and patients with the classic Philadelphia translocation only. Our results highlight the distinct biology of pediatric CML and underline the need for joint international efforts to acquire more data on the disease pathogenesis in this age group.
CRIS-Team Scopus Importer:2022-04-08
Keywords: additional chromosomal aberrations; chronic myeloid leukemia; complex karyotype; cytogenetic response; molecular response; pediatric chronic myeloid leukemia; Philadelphia chromo-some; tyrosine kinase inhibitor treatment; variant translocations

The EDELIFE clinical trial, the first investigation of a signalling molecule to treat in utero a human developmental genetic disorder - Schneider, Holm; Hadj-Rabia, Smail; Faschingbauer, Florian; Bodemer, Christine; Grange, Dorothy K.; Guillén-Navarro, Encarna; Tadini, Gianluca; Clarke, Angus (European Journal of Human Genetics, 2024)

The ENCCA-WP7/EuroSarc/EEC/PROVABES/EURAMOS 3rd European Bone Sarcoma Networking Meeting/Joint Workshop of EU Bone Sarcoma Translational Research Networks; Vienna, Austria, September 24-25, 2015. Workshop Report - Kager, Leo; Whelan, Jeremy; Dirksen, Uta; Hassan, Bass; Anninga, Jakob; Bennister, Lindsey; Bovee, Judith V. M. G.; Brennan, Bernadette; Broto, Javier M.; Brugieres, Laurence; Cleton-Jansen, Anne-Marie; Copland, Christopher; et al. (Clinical Sarcoma Research, 2016)
This report summarizes the results of the 3rd Joint ENCCA-WP7, EuroSarc, EEC, PROVABES, and EURAMOS European Bone Sarcoma Network Meeting, which was held at the Children's Cancer Research Institute in Vienna, Austria on September 24-25, 2015. The joint bone sarcoma network meetings bring together European bone sarcoma researchers to present and discuss current knowledge on bone sarcoma biology, genetics, immunology, as well as results from preclinical investigations and clinical trials, to generate novel hypotheses for collaborative biological and clinical investigations. The ultimate goal is to further improve therapy and outcome in patients with bone sarcomas.
EVALuna2:34002

The EU paediatric regulation: still a large discrepancy between therapeutic needs and approved paediatric investigation plans - Wimmer, Stefan; Rascher, Wolfgang; Mccarthy, Suzanne; Neubert, Antje (Paediatric Drugs, 2014)
Prior to the implementation of the EU Paediatric Regulation, the European Medicines Agency (EMA) defined unmet paediatric needs for active substances already available on the market. Seven years after the Paediatric Regulation came into force, we investigated the extent to which previously identified needs have led to programmes for generating evidence necessary for the regulatory approval of medicines for managing childhood conditions.The websites of the EMA and the European Commission Community Research and Development Information Service (CORDIS) were systematically screened to identify active substances from the assessment of paediatric needs, off-patent priority list, agreed Paediatric Investigation Plans (PIP) and 7th Framework Programme (FP7) projects related to paediatric medicines.A total of 357 active substances with paediatric needs were identified by June 2013. 511 PIPs were agreed by the Paediatric Committee at the EMA (PDCO), including 51 (14.3 %) PIPs for a previously identified need. Amongst those, 21 were off-patent at the time of the PIP approval, 15 of which received funding from the European Commission's FP7. According to the assessment of paediatric needs, evidence is particularly needed for active substances treating cardiovascular diseases (n = 61), cancer (n = 40) and in the field of anaesthesiology (n = 38). Whereas oncology drugs (n = 66) were frequently represented in PIPs, drugs for cardiovascular diseases (n = 39) and anaesthesiology (n = 3) rarely were.Most PIPs are attributable to marketing authorisations of new active substances, whereas off-patent drugs which are commonly used off-label remain unstudied to a large extent. More effort including ongoing research funding is essential to further regularise and standardise paediatric pharmacotherapy.
EVALuna2:18901

The genomic architecture of bladder exstrophy epispadias complex - Beaman, Glenda M.; Cervellione, Raimondo M.; Keene, David; Reutter, Heiko Martin; Newman, William G. (Genes, 2021)
The bladder exstrophy–epispadias complex (BEEC) is an abdominal midline malformation comprising a spectrum of congenital genitourinary abnormalities of the abdominal wall, pelvis, urinary tract, genitalia, anus, and spine. The vast majority of BEEC cases are classified as non-syndromic and the etiology of this malformation is still unknown. This review presents the current knowledge on this multifactorial disorder, including phenotypic and anatomical characterization, epidemiology, proposed developmental mechanisms, existing animal models, and implicated genetic and environmental components.
CRIS-Team Scopus Importer:2021-08-13
Keywords: BEEC; Bladder exstrophy; Cloacal exstrophy; Epispadias

The German National Registry of Primary Immunodeficiencies (2012-2017) - El-Helou, Sabine M.; Biegner, Anika-Kerstin; Bode, Sebastian; Ehl, Stephan R.; Heeg, Maximilian; Maccari, Maria E.; Ritterbusch, Henrike; Speckmann, Carsten; Rusch, Stephan; Scheible, Raphael; Warnatz, Klaus; Atschekzei, Faranaz; et al. (Frontiers in Immunology, 2019)
Introduction: The German PID-NET registry was founded in 2009, serving as the first national registry of patients with primary immunodeficiencies (PID) in Germany. It is part of the European Society for Immunodeficiencies (ESID) registry. The primary purpose of the registry is to gather data on the epidemiology, diagnostic delay, diagnosis, and treatment of PIDs.
CRIS-Team WoS Importer:2019-08-06

The Influence of the Age of the Bone Marrow Microenvironment on Leukaemia Progression - Zanetti, Costanza; Ender, Joscha; Hartmann, Mark; Hey, Joschka; Godavarthy, Parimala Sonika; Weissenberger, Eva; Kumar, Rahul; Metzler, Markus; Gu, Zhaohui; Roberts, Kathryn G.; Filmann, Natalie; Bloomfield, Clara D.; et al. (BLOOD, 2019)
CRIS-Team WoS Importer:2021-10-18

The Multiple Sclerosis Inventory of Cognition for Adolescents (MUSICADO): A brief screening instrument to assess cognitive dysfunction, fatigue and loss of health-related quality of life in pediatric-onset multiple sclerosis - Storm van's Gravesande, K.; Calabrese, P.; Blaschek, A.; Rostásy, K.; Huppke, P.; Rothe, L.; Mall, V.; Kessler, J.; Kalbe, E.; Kraus, V.; Dornfeld, E.; Elpers, C.; et al. (European Journal of Paediatric Neurology, 2019)
Objective: Screening for cognitive impairment (CI), fatigue and also Health-related quality of life (HRQoL) in patients with pediatric-onset multiple sclerosis (POMS) is of utmost importance in clinical practice. The aim of this study was to establish a new and validated pediatric screening tool “MUSICADO” that is easy to use and time economical. Methods: 106 patients with POMS aged 12–18 years and 210 healthy controls (HCs) stratified for age and education underwent neuropsychological testing including a screening test “Multiple Sclerosis Inventory of Cognition” for adults and 8 standardized cognitive tests and established scales to assess fatigue and HRQoL. Results: The phonemic verbal fluency task (RWT “s-words”), the Trail Making Test A (TMT-A), and the Digit Span Forward discriminated significantly between patients and HCs (p = 0.000, respectively) and showed the highest proportion of test failure in patients (24.5%, 17.9%; 15.1%, respectively). Therefore, they were put together to form the cognitive part of the “MUSICADO”. After applying a scoring algorithm with balanced weighting of the subtests and age and education correction and a cut-off score for impairment, 35.8% of patients were categorized to be cognitively impaired (specificity: 88.6%). Fatigue was detected in 37.1% of the patients (specificity: 94.0%) and loss of HRQoL in 41.8% (specificity 95.7%) with the screening version, respectively. Conclusion: The MUSICADO is a newly designed brief and easy to use screening test to help to early identify CI, fatigue, and loss of HRQoL in patients with POMS as cut scores are provided for all three items. Further studies will have to show its usability in independent samples of patients with POMS.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Cognition; Fatigue; Health-related quality of life; Pediatric-onset multiple sclerosis; Screening instrument

The mutational and phenotypic spectrum of TUBA1A-associated tubulinopathy - Hebebrand, Moritz; Hüffmeier, Ulrike; Trollmann, Regina; Hehr, Ute; Uebe, Steffen; Ekici, Arif Bülent; Kraus, Cornelia; Krumbiegel, Mandy; Reis, André; Thiel, Christian; Popp, Bernt (Orphanet Journal of Rare Diseases, 2019)
BackgroundThe TUBA1A-associated tubulinopathy is clinically heterogeneous with brain malformations, microcephaly, developmental delay and epilepsy being the main clinical features. It is an autosomal dominant disorder mostly caused by de novo variants in TUBA1A.ResultsIn three individuals with developmental delay we identified heterozygous de novo missense variants in TUBA1A using exome sequencing. While the c.1307G>A, p.(Gly436Asp) variant was novel, the two variants c.518C>T, p.(Pro173Leu) and c.641G>A, p.(Arg214His) were previously described. We compared the variable phenotype observed in these individuals with a carefully conducted review of the current literature and identified 166 individuals, 146 born and 20 fetuses with a TUBA1A variant. In 107 cases with available clinical information we standardized the reported phenotypes according to the Human Phenotype Ontology. The most commonly reported features were developmental delay (98%), anomalies of the corpus callosum (96%), microcephaly (76%) and lissencephaly (agyria-pachygyria) (70%), although reporting was incomplete in the different studies. We identified a total of 121 specific variants, including 15 recurrent ones. Missense variants cluster in the C-terminal region around the most commonly affected amino acid position Arg402 (13.3%). In a three-dimensional protein model, 38.6% of all disease-causing variants including those in the C-terminal region are predicted to affect the binding of microtubule-associated proteins or motor proteins. Genotype-phenotype analysis for recurrent variants showed an overrepresentation of certain clinical features. However, individuals with these variants are often reported in the same publication.ConclusionsWith 166 individuals, we present the most comprehensive phenotypic and genotypic standardized synopsis for clinical interpretation of TUBA1A variants. Despite this considerable number, a detailed genotype-phenotype characterization is limited by large inter-study variability in reporting.
CRIS-Team WoS Importer:2019-02-27

The natural history of pediatric Sturge-Weber Syndrome: A multinational cross-sectional study - Disse, Sigrid Claudia; Küpper, Hanna; Bock, Annette; Korenke, Georg Christoph; Ramantani, Georgia; Weidner, Birgit; Preisel, Martin; Trollmann, Regina; Wiemer-Kruel, Adelheid; Brockmann, Knut; Schroeder, Simone; Meyer, Sascha (European Journal of Paediatric Neurology, 2025)
Background: Sturge-Weber Syndrome (SWS) is a capillary-venous malformation which includes the brain (leptomeningeal venous capillary malformation), the eye (choroidal angioma) and the skin (facial portwine birthmark, FPB). Structural epilepsy, glaucoma and FPBs pose therapeutic challenges. Considerable advances include improved neuroimaging, new antiseizure medication (ASM) and progress in epilepsy surgery. Yet, comprehensive data on epidemiology, clinical features, diagnostics, and treatment in contemporary pediatric SWS cohorts is scarce. Methods: We conducted a multinational cross-sectional observational study in Germany, Switzerland and Austria to identify potential patients and build up a comprehensive database containing anonymized patient data. The patients’ guardians and child neurologists filled in detailed questionnaires on histories, clinical features, diagnostic and therapeutic measures. Results: Forty-seven SWS patients from Germany, Switzerland or Austria participated in our survey (111 notifications, i.e. the participation rate was 43 %). Prevalence was 7.37/million in Germany, 4.60/million in Switzerland, 2.61/million in Austria. Severity of skin, eye and brain involvement varied highly. Forty-three patients (91 %) were diagnosed with epilepsy. Median age at first seizure was 6.5 months. Thirty-two percent of the cohort received ASM in monotherapy, fifty-three percent received combination therapy and thirteen percent received no ASM. Eight percent underwent epilepsy surgery. Conclusions: In this European pediatric SWS cohort from a well-established tertiary child neurologist network, the condition was commonly diagnosed within the first year of life. 40 % of the cohort were seizure-free at inclusion; only 8.5 % of the cohort underwent epilepsy surgery. Our findings are concordant with published data from U.S. registries and case series. While our results indicate diagnostic improvement as compared to published studies, epilepsy management in SWS remains a challenge.
CRIS-Team Scopus Importer:2025-02-28
Keywords: ESNEK; Observational study; Pediatric study; Phacomatosis; Sturge-Weber Syndrome

The nuclear receptor constitutive androstane receptor/NR1I3 enhances the profibrotic effects of transforming growth factor β and contributes to the development of experimental dermal fibrosis - Avouac, Jerome; Palumbo-Zerr, Katrin; Ruzehaji, Nadira; Tomcik, Michal; Zerr, Pawel; Dees, Clara; Distler, Alfiya; Beyer, Christian; Schneider, Holm; Distler, Oliver; Schett, Georg; Allanore, Yannick; et al. (Arthritis and Rheumatology, 2014)
Objective Nuclear receptors regulate cell growth, differentiation, and homeostasis. Selective nuclear receptors promote fibroblast activation, which leads to tissue fibrosis, the hallmark of systemic sclerosis (SSc). This study was undertaken to investigate the effects of constitutive androstane receptor (CAR)/NR1I3, an orphan nuclear receptor, on fibroblast activation and experimental dermal fibrosis. Methods CAR expression was quantified by quantitative polymerase chain reaction, Western blotting, immunohistochemistry, and immunofluorescence. CAR expression was modulated by small molecules, small interfering RNA, forced overexpression, and site-directed mutagenesis. The effects of CAR activation were analyzed in cultured fibroblasts, in bleomycin-induced dermal fibrosis, and in mice overexpressing a constitutively active transforming growth factor β (TGFβ) receptor type I (TβRI-CA). Results Up-regulation of CAR was detected in the skin and in dermal fibroblasts in SSc patients. Stimulation of healthy fibroblasts with TGFβ induced the expression of CAR messenger RNA and protein in a Smad-dependent manner. Pharmacologic activation or overexpression of CAR in healthy fibroblasts significantly increased the stimulatory effects of TGFβ on collagen synthesis and myofibroblast differentiation, and amplified the stimulatory effects of TGFβ on COL1A2 transcription activity. Treatment with CAR agonist increased the activation of canonical TGFβ signaling in murine models of SSc and exacerbated bleomycin-induced and TβRI-CA-induced fibrosis with increased dermal thickening, myofibroblast counts, and collagen accumulation. Conclusion Our findings indicate that CAR is up-regulated in SSc and regulates TGFβ signaling. Activation of CAR increases the profibrotic effects of TGFβ in cultured fibroblasts and in different preclinical models of SSc. Thus, inactivation of CAR might be a novel approach to target aberrant TGFβ signaling in SSc and in other fibrotic diseases.
CRIS-Team Scopus Importer:2020-07-01

The ovine cerebral venous system: comparative anatomy, visualization, and implications for translational research - Hoffmann, Anke; Stoffel, Michael H.; Nitzsche, Bjoern; Lobsien, Donald; Seeger, Johannes; Schneider, Holm; Boltze, Johannes (PLoS ONE, 2014)
Cerebrovascular diseases are significant causes of death and disability in humans. Improvements in diagnostic and therapeutic approaches strongly rely on adequate gyrencephalic, large animal models being demanded for translational research. Ovine stroke models may represent a promising approach but are currently limited by insufficient knowledge regarding the venous system of the cerebral angioarchitecture. The present study was intended to provide a comprehensive anatomical analysis of the intracranial venous system in sheep as a reliable basis for the interpretation of experimental results in such ovine models. We used corrosion casts as well as contrast-enhanced magnetic resonance venography to scrutinize blood drainage from the brain. This combined approach yielded detailed and, to some extent, novel findings. In particular, we provide evidence for chordae Willisii and lateral venous lacunae, and report on connections between the dorsal and ventral sinuses in this species. For the first time, we also describe venous confluences in the deep cerebral venous system and an 'anterior condylar confluent' as seen in humans. This report provides a detailed reference for the interpretation of venous diagnostic imaging findings in sheep, including an assessment of structure detectability by in vivo (imaging) versus ex vivo (corrosion cast) visualization methods. Moreover, it features a comprehensive interspecies-comparison of the venous cerebral angioarchitecture in man, rodents, canines and sheep as a relevant large animal model species, and describes possible implications for translational cerebrovascular research.
EVALuna2:18907

The placental mTOR-pathway: correlation with early growth trajectories following intrauterine growth restriction? - Fahlbusch, F. B.; Menendez-Castro, C.; Nögel, Stephanie; Marek, I.; Beckmann, Matthias; Schleussner, E.; Ruebner, M.; Huebner, H.; Dörr, Helmuth-Günther; Schild, R. L.; Doetsch, J.; Rascher, Wolfgang; et al. (Journal of Developmental Origins of Health and Disease, 2015)
Idiopathic intrauterine growth restriction (IUGR) is a result of impaired placental nutrient supply. Newborns with IUGR exhibiting postnatal catch-up growth are of higher risk for cardiovascular and metabolic co-morbidities in adult life. Mammalian target of rapamycin (mTOR) was recently shown to function as a placental nutrient sensor. Thus, we determined possible correlations of members of the placental mTOR signaling cascade with auxologic parameters of postnatal growth. The protein expression and activity of mTOR-pathway signaling components, Akt, AMP-activated protein kinase ?, mTOR, p70S6kinase1 and insulin receptor substrate-1 were analysed via western blotting in IUGR v. matched appropriate-for-gestational age (AGA) placentas. Moreover, mTOR was immunohistochemically stained in placental sections. Data from western blot analyses were correlated with retrospective auxological follow-up data at 1 year of age. We found significant catch-up growth in the 1st year of life in the IUGR group. MTOR and its activated form are immunohistochemically detected in multiple placental compartments. We identified correlations of placental mTOR-pathway signaling components to auxological data at birth and at 1 year of life in IUGR. Analysis of the protein expression and phosphorylation level of mTOR-pathway components in IUGR and AGA placentas postpartum, however, did not reveal pathognomonic changes. Our findings suggest that the level of activated mTOR correlates with early catch-up growth following IUGR. However, the complexity of signals converging at the mTOR nexus and its cellular distribution pattern seem to limit its potential as biomarker in this setting.
EVALuna2:17439

The preleukemic TCF3-PBX1 gene fusion can be generated in utero and is present in ≈0.6% of healthy newborns - Hein, Daniel; Dreisig, Karin; Metzler, Markus; Izraeli, Shai; Schmiegelow, Kjeld; Borkhardt, Arndt; Fischer, Ute (Blood, 2019)
CRIS-Team Scopus Importer:2019-11-12

Therapy with low-dose azacitidine for MDS in children and young adults: a retrospective analysis of the EWOG-MDS study group - Cseh, Annamaria M.; Niemeyer, Charlotte M.; Yoshimi, Ayami; Catala, Albert; Fruehwald, Michael C.; Hasle, Henrik; Van Den Heuvel-Eibrink, Mary M.; Lauten, Melchior; De Moerloose, Barbara; Smith, Owen P.; Bernig, Toralf; Gruhn, Bernd; et al. (British Journal of Haematology, 2016)
Low-dose azacitidine is efficient and safe in the therapy of malignant myeloid disorders in adults but data in children are lacking. We present a retrospective analysis of 24 children and young adults with myelodysplastic syndrome (MDS) who received azacitidine at the time of first diagnosis or relapse after allotransplant (2 children were treated with azacitidine both initially and for relapse). Diagnoses were refractory cytopenia of childhood (N = 4), advanced primary MDS (N = 9) and secondary MDS (N = 11). The median duration of treatment was four cycles. Azacitidine was well tolerated, but cytopenias led to dose reduction in five cases. Treatment was discontinued in one child because of impaired renal function. Sixteen MDS patients were treated with azacitidine at first diagnosis. One complete clinical remission was observed and one child showed complete marrow remission; six children experienced stable disease with haematological improvement. Ten children received azacitidine for relapsed MDS after transplant: of these, seven experienced stable disease for 2-30 cycles (median 3), including one patient with haematological improvement for seven cycles. In summary, azacitidine is effective in some children with MDS and appears to be a non-toxic option in palliative situations to prolong survival.
EVALuna2:33875

The role of de novo variants in formation of human anorectal malformations - Dworschak, Gabriel C.; van Rooij, Iris A.L.M.; Reutter, Heiko Martin (Genes, 2021)
Anorectal malformations (ARM) represent a rare birth defect of the hindgut that occur in approximately 1 in 3000 live births. Around 60% of ARM occur with associated anomalies including defined genetic syndromes and associations with chromosomal aberrations. The etiology of ARM is heterogeneous, with the individual environmental or genetic risk factors remaining unknown for the majority of cases. The occurrence of familial ARM and previous epidemiologic analysis suggest autosomal dominant inheritance in a substantial subset of ARM patients. The implicated mortality and reduced fecundity in patients with ARM would lead to allele loss. However, mutational de novo events among the affected individuals could compensate for the evolutionary pressure. With the implementation of exome sequencing, array-based molecular karyotyping and family-based rare variant analyses, the technologies are available to identify the respective factors. This review discusses the identification of disease-causing variants among individuals with ARM. It highlights the role of mutational de novo events.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Anorectal malformation (ARM); Birth defect; Copy number variation (CNV); De novo; Fecundity; Heritability

The role of de novo variants in patients with congenital diaphragmatic hernia - Bendixen, Charlotte; Reutter, Heiko Martin (Genes, 2021)
The genetic etiology of congenital diaphragmatic hernia (CDH), a common and severe birth defect, is still incompletely understood. Chromosomal aneuploidies, copy number variations (CNVs), and variants in a large panel of CDH-associated genes, both de novo and inherited, have been described. Due to impaired reproductive fitness, especially of syndromic CDH patients, and still significant mortality rates, the contribution of de novo variants to the genetic background of CDH is assumed to be high. This assumption is supported by the relatively low recurrence rate among siblings. Advantages in high-throughput genome-wide genotyping and sequencing methods have recently facilitated the detection of de novo variants in CDH. This review gives an overview of the known de novo disease-causing variants in CDH patients.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Congenital diaphragmatic hernia; De novo variants; Impaired reproductive fitness; Mortality

The Safety of Drug Therapy in Children - Wimmer, Stefan; Neubert, Antje; Rascher, Wolfgang (Deutsches Ärzteblatt international, 2015)
1.7% of children taking medication on an outpatient basis in Germany have at least one adverse drug reaction (ADR). The corresponding figure for hospitalized children is estimated at 10% .This review is based on pertinent literature retrieved by a selective search in PubMed.According to reports submitted to the Drug Commission of the German Medical Association (Arzneimittelkommission der deutschen Ärzteschaft, AkdÄ), serious ADRs can arise, for example, after the administration of dimenhydrinate, ?-adrenergic nose drops, enemas containing phosphate, ACE inhibitors, angiotensin-2-receptor antagonists (sartans), and methylphenidate. The causes of ADRs include overdoses, drug administration despite contraindications, and inadequate monitoring of long-term treatment. Errors can also be made in communication, labeling, and drug administration. The risk of ADRs is especially high in off-label use. Computerized physician order entry systems, individual packaging and labeling of single doses, and the use of bar codes for patient and drug identification can help prevent such errors.The process of drug administration should be optimized through suitable interventions and electronic support, with due consideration of local circumstances. Clinical trials on children should be encouraged as a means of improving drug safety, and additional financial incentives should be created for trials concerning drugs that are off-patent. Physicians and pharmacists should take care to report adverse reactions as they are required to do by professional code, particularly in the case of new drugs, off-label use, or medication errors. A recognized national standard for dosing that can be implemented in computerized physician order entry systems is needed so that evidence-based pediatric dosages can be calculated.
EVALuna2:18938

The second European interdisciplinary Ewing sarcoma research summit–A joint effort to deconstructing the multiple layers of a complex disease - Kovar, Heinrich; Amatruda, James; Brunet, Erika; Burdach, Stefan; Cidre-Aranaz, Florencia; De Alava, Enrique; Dirksen, Uta; Van Der Ent, Wietske; Grohar, Patrick; Grunewald, Thomas G. P.; Helman, Lee; Houghton, Peter; et al. (Oncotarget, 2016)
Despite multimodal treatment, long term outcome for patients with Ewing sarcoma is still poor. The second "European interdisciplinary Ewing sarcoma research summit" assembled a large group of scientific experts in the field to discuss their latest unpublished findings on the way to the identification of novel therapeutic targets and strategies. Ewing sarcoma is characterized by a quiet genome with presence of an EWSR1-ETS gene rearrangement as the only and defining genetic aberration. RNA-sequencing of recently described Ewing-like sarcomas with variant translocations identified them as biologically distinct diseases. Various presentations adressed mechanisms of EWS-ETS fusion protein activities with a focus on EWS-FLI1. Data were presented shedding light on the molecular underpinnings of genetic permissiveness to this disease uncovering interaction of EWS-FLI1 with recently discovered susceptibility loci. Epigenetic context as a consequence of the interaction between the oncoprotein, cell type, developmental stage, and tissue microenvironment emerged as dominant theme in the discussion of the molecular pathogenesis and inter- and intra-tumor heterogeneity of Ewing sarcoma, and the difficulty to generate animal models faithfully recapitulating the human disease. The problem of preclinical development of biologically targeted therapeutics was discussed and promising perspectives were offered from the study of novel in vitro models. Finally, it was concluded that in order to facilitate rapid pre-clinical and clinical development of novel therapies in Ewing sarcoma, the community needs a platform to maintain knowledge of unpublished results, systems and models used in drug testing and to continue the open dialogue initiated at the first two Ewing sarcoma summits.
EVALuna2:33876

The Treatment of Growth Disorders in Childhood and Adolescence. - Wölfle, Joachim; Schnabel, Dirk; Binder, Gerhard (Deutsches Ärzteblatt international, 2024)
BACKGROUND: 3% of all children are unusually short, and 3% are unusually tall. New approaches have broadened the range of therapeutic options in treating growth disorders. METHODS: This review is based on publications retrieved by a selective review of the literature and on the authors' clinical experience. RESULTS: Pituitary growth hormone deficiency is treated with recombinant growth hormone. Long-acting preparations of this type became available recently, but their long-term safety and efficacy are still unknown. Vosoritide, a CNP analogue, has also been approved for the treatment of achondroplasia, and severe primary deficiency of insulin-like growth factor 1 (IGF-1) can be treated with recombinant IGF-1. In the treatment of excessively tall stature, new information on the safety of growth-attenuating treatment and an altered perception of above-average height in society have led to a change in management. CONCLUSION: There are new options for the treatment of rare causes of short stature, while new information on the safety of treatment strategies for excessive tallness have led to a reconsideration of surgical intervention. There is insufficient evidence on the benefits and risks of supraphysiological GH therapy and of newer treatment options for which there are as yet no robust data on adult height. Therefore, before any treatment is provided, physicians should give patients and their families detailed information and discuss their expectations from treatment and the goals that treatment can be expected to achieve.
EVALuna2:549518

The Use of Cannabinoids in Pediatric Palliative Care—A Retrospective Single-Center Analysis - Tagsold, David; Toni, Irmgard; Trollmann, Regina; Wölfle, Joachim; Gravou-Apostolatou, Chara (Children, 2024)
This data analysis aimed to systematically analyze a pediatric patient population with a life-limiting disease who were administered cannabinoids. It was a retrospective single-center analysis of patients under supervision of the specialized outpatient pediatric palliative care (SOPPC) team at the Department of Pediatrics and Adolescent Medicine of the Friedrich-Alexander-Universität Erlangen-Nürnberg (FAU). Thirty-one patients with a primary diagnosis of neuropediatric, oncologic, metabolic, and cardiologic categories were included. The indications we identified were spasticity, pain, restlessness, anxiety, loss of appetite, epilepsy, and paresis. Certain aspects of quality of life were improved for 20 of 31 patients (64.5%). For nine patients (29%), no improvement was detected. No conclusions could be drawn for two patients (6.5%). Adverse events were reported for six of the thirty-one patients (19.4%). These were graded as mild, including symptoms such as restlessness, nausea, and behavioral issues. We detected no clinically relevant interactions with other medications. We collected fundamental data on the use of cannabinoids by pediatric palliative patients. Cannabinoids are now frequently administered in pediatric palliative care. They seem to be safe to use and should be considered an add-on therapy for other drug regimens.
CRIS-Team Scopus Importer:2024-04-26
Keywords: cannabinoids; palliative care; pediatric

Time Tracking of Standard Ultrasound Examinations in Pediatric Hospitals and Pediatric Medical Practices - A Multicenter Study by the Pediatric Section of the German Society of Ultrasound in Medicine (DEGUM) - Regensburger, Adrian; Knieling, Ferdinand; Feldkamp, Axel; Rascher, Wolfgang; Diesch, Katharina; Wölfle, Joachim; Prokosch, Hans-Ulrich; Jüngert, Jörg M. (Ultraschall in der Medizin, 2019)
PURPOSE: Ultrasonography is the primary imaging modality in pediatrics but still lacks sufficient reimbursement in Germany. In this multicenter study, national data for the duration of standard ultrasound in pediatrics were systematically documented in order to specify the actual time required. MATERIALS AND METHODS: N = 10 hospitals (N = 5 university hospitals, N = 5 non-university hospitals) and N = 3 medical practices in Germany recorded the entire process of an ultrasound examination in a special protocol developed by the Pediatric Section of the DEGUM. The duration of each of seven single steps during ultrasonography (from data input to final discussion of the results) of different organ systems was logged. RESULTS: In total, N = 2118 examinations from different organ systems were recorded. N = 10 organ systems were examined frequently (> 30 times). The total duration of an ultrasound examination was statistically significantly longer in hospitals compared to medical practices (median (IQR) 27 min. (18-38) vs. 12 min. (9-17), p < 0.001). The "hands-on" patient time was approximately one half of the total required time in both settings (49.9 % vs. 48.9 %). Ultrasonography of the abdomen and brain lasted longer in university hospitals than in non-university hospitals (p < 0.001, and p = 0.04, respectively). Cooperation and age did not uniformly correlate with the total duration. CONCLUSION: This study provides novel comprehensive national data for the duration of standardized ultrasound examinations of children and adolescents in Germany. These data are essential for a further evaluation of the economic costs and should support better remuneration in the future.
EVALuna2:209480

Time trends towards earlier puberty in boys and girls with type 1 diabetes: Insights from the German Diabetes Prospective Follow-up (DPV) registry, 2000 to 2021 - Gohlke, Bettina; Reschke, Felix; Lanzinger, Stefanie; Boettcher, Claudia; Gemulla, Gitta; Thiele-Schmitz, Susanne; Dunstheimer, Désirée; van den Boom, Louise; Wölfle, Joachim; Holl, R. W. (Diabetes Obesity & Metabolism, 2023)
Aim: To examine the time trends and factors associated with the onset of puberty in children with type 1 diabetes (T1D) using data from the German Diabetes Prospective Follow-up (Diabetes-Patienten-Verlaufsdokumentation [DPV]) registry. Methods: A total of 13 127 children with T1D, aged 6 to 18 years, were included in the analysis. Regression analysis was performed to investigate the relationship between diabetes duration, body mass index (BMI) standard deviation score (SDS), glycated haemoglobin (HbA1c) level, migration background, and the onset of puberty, stratified by sex. Results: Our findings revealed a significant trend towards earlier puberty in both girls and boys with T1D over the observed period (2000 to 2021). Puberty onset in girls (thelarche Tanner stage B2) decreased from 11.48 (11.35-11.65) years in 2000 to 10.93 (10.79-11.08) years in 2021 and gonadarche (Tanner stage G2/testicular volume >3 mL) decreased from 12.62 (12.42-12.82) years in 2000 to 11.98 (11.79-12.16) years in 2021 in boys (both P < 0.001). Longer diabetes duration, higher BMI SDS, and lower HbA1c level were associated with earlier puberty in both sexes (P < 0.001). Conclusions: Our study highlights earlier puberty in children with T1D, influenced by BMI SDS, HbA1c level, and migration background. This has important implications for diabetes management and supporting healthy development. Further research is needed to understand the underlying mechanisms and develop potential interventions for this vulnerable population.
CRIS-Team Scopus Importer:2023-10-20
Keywords: body composition; clinical physiology; cohort study; type 1 diabetes

Timing of first arteriovenous fistula cannulation in children on hemodialysis - Almási-Sperling, Veronika; Galiano, Matthias; Lang, Werner; Rother, Ulrich; Rascher, Wolfgang; Regus, Susanne (Pediatric Nephrology, 2016)
Due to lower complication rates in comparison to central venous catheter (CVC) arteriovenous fistulas (AVFs) are now the preferred hemodialysis access. Recommendations for the first access cannulation range from 6 to 12 weeks, which could lead to temporary or even permanent preference for CVC while awaiting the maturation of the newly created AVF. The aim of this study was to evaluate the influence of first cannulation of AVFs on primary (PP) and secondary (SP) patency rates in children on hemodialysis (HD).This was a retrospective cohort study of 42 pediatric patients with a median age of 14 (range 7-17) years. At the time of surgical AVF creation 21 patients (end-stage renal disease) were still on HD via CVC or peritoneal catheter, while 21 were pre-emptive with initiation of HD expected within a few weeks. All patients received an AVF by the same experienced surgeon between February 1993 and May 2014. Primary failure (PF) was defined as the inability to use the AVF even once due to absent maturation or occlusion within 4 weeks after creation. PP was defined as the interval from time of access placement to any intervention designed to maintain or reestablish patency, to access thrombosis or the time of measurement of patency, while SP was defined as the total lifespan from creation to access abandonment, end of follow-up or loss.Primary failure was observed in six (14.3 %) of 42 AVFs (all radiocephalic fistulas) within the first 10 days after cannulation. Excluding PF, the PP/SP rates at 1, 3, 6, 12, 18 and 24 months were 100/100, 91/99, 86/98, 76/95, 55/85 and 44/77 %, respectively. There was a significant decrease in PP when first cannulation was performed within the first 30 days after creation compared to first cannulation performed after 30 days (p = 0.004). In terms of PP/SP outcome and timing of the first cannulation, there was no significant difference in thee outcome of PP/SP between first cannulation within the first 45 days after creation and that after 45 days (p = 0.091/0.883).The findings suggest that cannulation of AVF within 30 days after surgical creation reduces PP, while SP may be influenced less by time until cannulation. We also found no significant differences in PP after maturing periods of >45 days.
EVALuna2:15275

Transfontanellar Contrast-Enhanced Ultrasound for Monitoring Brain Perfusion During Neonatal Heart Surgery - Knieling, Ferdinand; Rüffer, André; Cesnjevar, Robert; Regensburger, Adrian; Purbojo, Ariawan; Dittrich, Sven; Münch, Frank; Neubert, Antje; Meyer, Sebastian; Strobel, Deike; Rascher, Wolfgang; Wölfle, Joachim; et al. (Circulation: Cardiovascular Imaging, 2020)
CRIS-Team Scopus Importer:2020-03-13

Transfontanellar Contrast-enhanced US for Intraoperative Imaging of Cerebral Perfusion during Neonatal Arterial Switch Operation - Knieling, Ferdinand; Cesnjevar, Robert; Regensburger, Adrian; Wagner, Alexandra; Purbojo, Ariawan; Dittrich, Sven; Münch, Frank; Neubert, Antje; Wölfle, Joachim; Jüngert, Jörg M.; Rüffer, André (Radiology, 2022)
Background Brain injury and subsequent neurodevelopmental disorders are major determinants for later-life outcomes in neonates with transposition of the great arteries (TGA). Purpose To quantitatively assess cerebral perfusion in neonates with TGA undergoing arterial switch operation (ASO) using transfontanellar contrast-enhanced US (T-CEUS). Materials and Methods In a prospective single-center cross-sectional diagnostic study, neonates with TGA scheduled for ASO were recruited from February 2018 to February 2020. Measurements were performed at five time points before, during, and after surgery (T1-T5), and 11 perfusion parameters were derived per cerebral hemisphere. Neonate clinical characteristics, heart rate, mean arterial pressure, central venous pressure, near-infrared spectroscopy, blood gas analyses, ventilation time, time spent in the pediatric intensive care unit, and time in hospital were correlated with imaging parameters. Analysis of variance or a mixed-effects model were used for groupwise comparisons. Results A total of 12 neonates (mean gestational age, 39 6/7 weeks ± 1/7 [SD]) were included and underwent ASO a mean of 6.9 days ± 3.4 after birth. When compared with baseline values, T-CEUS revealed a longer mean time-to-peak (right hemisphere, 4.3 seconds ± 2.1 vs 17 seconds ± 6.4 [P < .001]; left hemisphere, 4.0 seconds ± 2.3 vs 21 seconds ± 8.7 [P < .001]) and rise time (right hemisphere, 3.5 seconds ± 1.7 vs 11 seconds ± 5.1 [P = .002]; left hemisphere, 3.4 seconds ± 2.0 vs 22 seconds ± 7.8 [P = .004]) in both cerebral hemispheres during low-flow cardiopulmonary bypass and hypothermia (T4) for all neonates. Neonate age at surgery negatively correlated with T-CEUS parameters during ASO, as calculated with the area under the flow curve (AUC) during wash-in (R = -0.60, P = .020), washout (R = -0.82, P = .002), and both wash-in and washout (R = -0.79, P = .004). Mean AUC values were lower in neonates older than 7 days compared with younger neonates during wash-in ([87 arbitrary units au ± 77] × 102 vs [270 au ± 164] × 102, P = .049]), washout ([15 au ± 11] × 103 vs [65 au ± 38] × 103, P = .020]) and both wash-in and washout ([24 au ± 18] × 103 vs [92 au ± 53] × 103, P = .023). Conclusion Low-flow hypothermic conditions resulted in reduced cerebral perfusion, as measured with transfontanellar contrast-enhanced US, which inversely correlated with age at surgery. Clinical trial registration no. NCT03215628 © RSNA, 2022 Online supplemental material is available for this article.
CRIS-Team Scopus Importer:2022-07-01

Transition of juvenile patients with neuromuscular disease and respiratory insufficiency Transition bei neuromuskulären Erkrankungen mit chronisch respiratorischer Insuffizienz - Winterholler, M.; Trollmann, Regina (Pneumologe, 2021)
Diseases of the organs responsible for movement, i.e. the motor neurons, the neuromuscular transfer and the muscles themselves, are designated as neuromuscular diseases. Neuromuscular diseases occurring in childhood are either genetically linked or triggered by disorders of the immune system. In total, approximately 0.2–0.5% of all children are affected by neuromuscular diseases, whereby the frequency of individual entities of these always rare diseases greatly varies. The more complex the disease symptoms, the rarer the disease and the more severe the disability is in an adolescent, the more helpful is a meticulous transition from pediatrics to the medical world of adults. Muscle centers and medical centers for adults with intellectual and multiple disabilities are capable of maintaining a multiprofessional treatment concept, when necessary also into adulthood.
CRIS-Team Scopus Importer:2021-02-19
Keywords: Autoimmune disease; Muscular dystrophy; Respiratory muscle weakness; Spinal muscular atrophy; Treatment concept

Transrectal Absorber Guide Raster-Scanning Optoacoustic Mesoscopy for Label-Free In Vivo Assessment of Colitis - Bühler, Adrian; Brown, Emma; Paulus, Lars-Philip; Eckstein, Markus; Thoma, Oana-Maria; Oraiopoulou, Mariam-Eleni; Rother, Ulrich; Hörning, André; Hartmann, Arndt; Neurath, Markus; Wölfle, Joachim; Friedrich, Oliver; et al. (Advanced Science, 2023)
Optoacoustic imaging (OAI) enables microscale imaging of endogenous chromophores such as hemoglobin at significantly higher penetration depths compared to other optical imaging technologies. Raster-scanning optoacoustic mesoscopy (RSOM) has recently been shown to identify superficial microvascular changes associated with human skin pathologies. In animal models, the imaging depth afforded by RSOM can enable entirely new capabilities for noninvasive imaging of vascular structures in the gastrointestinal tract, but exact localization of intra-abdominal organs is still elusive. Herein the development and application of a novel transrectal absorber guide for RSOM (TAG-RSOM) is presented to enable accurate transabdominal localization and assessment of colonic vascular networks in vivo. The potential of TAG-RSOM is demonstrated through application during mild and severe acute colitis in mice. TAG-RSOM enables visualization of transmural vascular networks, with changes in colon wall thickness, blood volume, and OAI signal intensities corresponding to colitis-associated inflammatory changes. These findings suggest TAG-RSOM can provide a novel monitoring tool in preclinical IBD models, refining animal procedures and underlines the capabilities of such technologies to address inflammatory bowel diseases in humans.
CRIS-Team WoS Importer:2023-05-12

Transvascular kidney biopsy in adolescent patients-safe alternative to open procedures - Utsch, Boris; Hoppe, Hanno; Dittrich, Katalin; Amann, Kerstin Ute; Gugger, Mathias; Tschumi, Sibylle; Galiano, Matthias; Plank, Christian Georg; Rascher, Wolfgang; Schmid, Axel; Uder, Michael; Dötsch, Jörg (Clinical Kidney Journal, 2021)
CRIS-Team WoS Importer:2021-05-21

Treatment of Esophageal Atresia in Germany: Analysis of National Hospital Discharge Data From 2016 to 2022 - Ungruh, Max; Hubertus, Jochen; Widenmann, Anke; Kaufmann, Jost; Reutter, Heiko Martin; Busse, Reinhard; Wilms, Miriam; Nimptsch, Ulrike (Journal of Pediatric Surgery, 2024)
Background: Esophageal atresia (EA) is a complex malformation. Multidisciplinary management is necessary, with the operative repair being the most challenging step in the treatment algorithm. The complete care structure for children with EA in Germany has not been analyzed yet. Methods: In the observed period 2016–2022, inpatient EA cases were analyzed 1) during the hospital stay of birth, and 2) during the hospital stay of corrective surgery in patients aged up to 365 days, both based on national hospital discharge data. Patients’ comorbidities, hospital caseload, treatment characteristics (e.g. surgical approach) and outcome parameters were analyzed. Results: 1) 1190 newborn EA cases were treated in 260 hospitals during the perinatal period. 54% had at least one additional malformation, and 16% had a birthweight below 1500 g. In-hospital mortality was 8.4%. 2) 1475 corrective operations for EA were performed in 111 hospitals with a consistent median annual caseload of 2 (P25–P95 1–8) per hospital. At least one indicator for a complicated perioperative course was documented in 63.7% of cases. The use of bronchoscopy was coded in 50% of cases. Median ventilation time during the entire hospital stay was 176 h (P25–P95: 95–1759 h). Conclusions: Newborns with EA are complex and early postoperative complications are common. The care structure is decentralized, and there was no trend towards centralization in the observed period. The low documented use of bronchoscopy is noteworthy. Centralization of the highly complex and schedulable corrective surgery for EA is necessary to evaluate outcomes and might improve the quality of care and resource utilization. Category of the manuscript and type of study: original article, observational cross-sectional study, secondary data analysis.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Caseload; Centralization; Esophageal atresia; Quality of care; Volume-outcome relationship

Treatment of severe traumatic brain injury in German pediatric intensive care units—a survey of current practice - Regensburger, Adrian; Konrad, V.; Trollmann, Regina; Eyüpoglu, Ilker Yasin; Huebner, H.; Zierk, Jakob; Voelkl, T. M. K.; Fahlbusch, F. B. (Childs Nervous System, 2019)
Purpose: German pediatric guidelines for severe traumatic brain injury (TBI) management expired in 2011. Thus, divergent evidence-based institutional protocols are predominantly being followed. We performed a survey of current Pediatric Intensive Care Unit (PICU) management of isolated severe TBI in Germany to reveal potential varying practices. Methods: Seventy German PICUs were invited to join an anonymous online survey from February to May 2017. Twenty-nine participants (41.4%) successfully completed the survey (17 university hospitals and 12 district hospitals). The majority of items were polar (yes/no) or scaled (e.g., never - always). Main topics were imaging, neurosurgery, neuromonitoring, adjuvant therapy, and medication. Severity of TBI was defined via Glasgow Coma Scale. Results: The majority of respondents (93.1%) had internal TBI standards, and patients were mainly administered to interdisciplinary trauma units. The use of advanced neuromonitoring techniques, intracranial hypertension management, and drug treatment differed between PICUs. Routine administration of hypertonic saline in TBI-associated cerebral edema was performed by 3.4%, while it was never an option for 31.0% of the participants. Prophylactic anticonvulsive therapy was restrictively performed. If indicated, the main anticonvulsive drugs used were phenobarbital and levetiracetam. Neuroendocrine follow-up was recommended/performed by 58.6% of the PICUs. Conclusions: This survey provides an overview of the current PICU practices of isolated severe TBI management in Germany and demonstrates a wide instrumental and therapeutical range, revealing an unmet need for the revised national guideline and further (international) clinical trials for the treatment of severe TBI in pediatrics.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Adjuvant therapy; ICP; Neuroimaging; Neuromonitoring

Treatment of Unspecific Back Pain in Children and Adolescents: Results of an Evidence-Based Interdisciplinary Guideline - Frosch, Michael; Leinwather, Stina; Bielack, Stefan; Bloedt, Susanne; Dirksen, Uta; Dobe, Michael; Geiger, Florian; Haefner, Renate; Hoefel, Lea; Huebner-Moehler, Bettina; Von Kalle, Thekla; Lawrenz, Burkhard; et al. (Children, 2022)
Using a structured approach and expert consensus, we developed an evidence-based guideline on the treatment and prevention of non-specific back pain in children and adolescents. A comprehensive and systematic literature search identified relevant guidelines and studies. Based on the findings of this literature search, recommendations on treatment and prevention were formulated and voted on by experts in a structured consensus-building process. Physical therapy (particularly physical activity) and psychotherapy (particularly cognitive behavioral therapy) are recommended for treating pediatric non-specific back pain. Intensive interdisciplinary treatment programs should be provided for chronic and severe pain. Drug therapy should not be applied in children and adolescents. Further research on non-specific back pain in childhood and adolescence is strongly needed to reduce the imbalance between the high burden of non-specific back pain in childhood and adolescence and the low research activity in this field.
CRIS-Team Scopus Importer:2022-04-08
Keywords: adolescents; back pain; children; evidence-based; guideline; prevention; treatment

Trial in Progress: eine multizentrische Open-label Phase IB/ II Studie zur Bestimmung der Dosierung und Sicherheit von Asciminib bei padiatrischen Patienten mit chronischer myeloischer Leukamie in der chronischen Phase (ASC4kids) - Metzler, Markus; Escherich, G.; Reinhardt, D.; Kapoor, S.; Hoch, M.; Descamps, L.; Bayar, M. A.; Ramscar, N.; Hijiya, N. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

TRIM28 haploinsufficiency predisposes to Wilms tumor - Diets, Illja J.; Hoyer, Juliane; Ekici, Arif Bülent; Popp, Bernt; Hoogerbrugge, Nicoline; van Reijmersdal, Simon V.; Bhaskaran, Rajith; Hadjihannas, Michel; Vasileiou, Georgia; Thiel, Christian; Seven, Didem; Uebe, Steffen; et al. (International Journal of Cancer, 2019)
Two percent of patients with Wilms tumors have a positive family history. In many of these cases the genetic cause remains unresolved. By applying germline exome sequencing in two families with two affected individuals with Wilms tumors, we identified truncating mutations in TRIM28. Subsequent mutational screening of germline and tumor DNA of 269 children affected by Wilms tumor was performed, and revealed seven additional individuals with germline truncating mutations, and one individual with a somatic truncating mutation in TRIM28. TRIM28 encodes a complex scaffold protein involved in many different processes, including gene silencing, DNA repair and maintenance of genomic integrity. Expression studies on mRNA and protein level showed reduction of TRIM28, confirming a loss-of-function effect of the mutations identified. The tumors showed an epithelial-type histology that stained negative for TRIM28 by immunohistochemistry. The tumors were bilateral in six patients, and 10/11 tumors are accompanied by perilobar nephrogenic rests. Exome sequencing on eight tumor DNA samples from six individuals showed loss-of-heterozygosity (LOH) of the TRIM28-locus by mitotic recombination in seven tumors, suggesting that TRIM28 functions as a tumor suppressor gene in Wilms tumor development. Additionally, the tumors showed very few mutations in known Wilms tumor driver genes, suggesting that loss of TRIM28 is the main driver of tumorigenesis. In conclusion, we identified heterozygous germline truncating mutations in TRIM28 in 11 children with mainly epithelial-type Wilms tumors, which become homozygous in tumor tissue. These data establish TRIM28 as a novel Wilms tumor predisposition gene, acting as a tumor suppressor gene by LOH.
CRIS-Team Scopus Importer:2019-05-02
Keywords: genetic predisposition; haploinsufficiency; TRIM28; Wilms tumor

Trio Exome Sequencing in VACTERL Association - Ćomić, Jasmina; Tilch, Erik; Riedhammer, Korbinian M.; Brugger, Melanie; Brunet, Theresa; Eyring, Katharina; Vill, Katharina; Redler, Silke; Tasic, Velibor; Schmiedeke, Eberhard; Schäfer, Frank Mattias; Abazi-Emini, Nora; et al. (Kidney International Reports, 2025)
Introduction: Currently, there is only limited data on monogenic causes of vertebral defects, anorectal malformations, cardiac defects, esophageal atresia or tracheoesophageal fistula, renal malformations, and limb defects (VACTERL) association. The aim of this study was to extend the spectrum of disease-causing variants in known genes, to determine the diagnostic yield of monogenic causes, and to identify candidate genes and rare variants by applying comprehensive genetic testing or rare variant burden. Methods: The total cohort comprised 101 affected individuals and their parents. Trio exome sequencing was only performed in 96 individuals and their parents because of DNA quality reasons and case-control gene and pathway burden tests were calculated and evaluated by quantile-quantile plots, principal component analysis plots and family-based association test (FBAT). Results: In 5 of 96 individuals, disease-causing variants in known genes or loci were identified to be associated with the following 4 disorders: Kabuki syndrome, Sotos syndrome, MELAS syndrome, and deletion syndrome encompassing TWIST1. In 91 individuals, no disease-causing variants were found. FBAT showed 14 significant variants, 2 significant genes (LOC645752 and ZNF417), and 8 significant pathways. Conclusion: This study shows that most individuals with VACTERL association do not have known discrete genetic syndromes, implying that pathomechanisms or variants not identifiable by exome sequencing may exist requiring further investigation.
CRIS-Team Scopus Importer:2025-01-31
Keywords: burden test; exome sequencing; mitochondriopathy; VACTERL association; VACTERL-like phenotype; ZNF417

Trophoblast expression dynamics of the tumor suppressor gene gastrokine 2 - Fahlbusch, Fabian B.; Ruebner, Matthias; Hübner, Hanna; Volkert, Gudrun; Bartunik, Hannah; Winterfeld, Ilona; Hartner, Andrea; Menendez-Castro, Carlos; Nögel, Stephanie; Marek, Ines; Wachter, David; Schneider-Stock, Regine; et al. (Histochemistry and Cell Biology, 2015)
Gastrokines (GKNs) were originally described as stomach-specific tumor suppressor genes. Recently, we identified GKN1 in extravillous trophoblasts (EVT) of human placenta. GKN1 treatment reduced the migration of the trophoblast cell line JEG-3. GKN2 is known to inhibit the proliferation, migration and invasion of gastric cancer cells and may interact with GKN1. Recently, GKN2 was detected in the placental yolk sac of mice. We therefore aimed to further characterize placental GKN2 expression. By immunohistochemistry, healthy first-trimester placenta showed ubiquitous staining for GKN2 at its early gestational stage. At later gestational stages, a more differentiated expression pattern in EVT and villous cytotrophoblasts became evident. In healthy third-trimester placenta, only EVT retained strong GKN2 immunoreactivity. In contrast, HELLP placentas showed a tendency of increased levels of GKN2 expression with a more prominent GKN2 staining in their syncytiotrophoblast. Choriocarcinoma cell lines did not express GKN2. Besides its trophoblastic expression, we found human GKN2 in fibrotic villi, in amniotic membrane and umbilical cord. GKN2 co-localized with smooth muscle actin in villous myofibroblasts and with HLA-G and GKN1 in EVT. In the rodent placenta, GKN2 was specifically located in the spongiotrophoblast layer. Thus, the gestational age-dependent and compartment-specific expression pattern of GKN2 points to a role for placental development. The syncytial expression of GKN2 in HELLP placentas might represent a reduced state of functional differentiation of the syncytiotrophoblast. Moreover, the specific GKN2 expression in the rodent spongiotrophoblast layer (equivalent to human EVT) might suggest an important role in EVT physiology.
EVALuna2:6725

Twenty years of newborn screening for congenital adrenal hyperplasia and congenital primary hypothyroidism - experiences from the DGKED/AQUAPE study group for quality improvement in Germany - Hammersen, Johanna; Bettendorf, Markus; Bonfig, Walter; Schoenau, Eckhard; Warncke, Katharina; Eckert, Alexander J.; Fricke-Otto, Susanne; Palm, Katja; Holl, Reinhard W.; Wölfle, Joachim (Medizinische Genetik, 2022)
Congenital primary hypothyroidism (CH) and congenital adrenal hyperplasia (CAH) are targeted by the German and Austrian newborn screening. For both diseases, there are registries for quality improvement, based on standardized observational data from long-term patient follow-up, under the auspices of the DGKED study group. By September 2021, the CH registry HypoDOK includes datasets from 23,348 visits of 1,840 patients, and the CAH registry contains datasets from 36,237 visits of 1,976 patients. Here, we report on the recruitment process, patient characteristics, and research contributions from the registries, and underline that the registries are an important tool to improve patient care and outcomes. Registries for rare conditions should thus be considered as an important public health measure and they should be adequately institutionalized and funded.
CRIS-Team WoS Importer:2022-05-20
Keywords: congenital adrenal hyperplasia; congenital primary hypothyroidism; patient registry; newborn screening; quality management; benchmarking

Ultra-high-frequency ultrasound in patients with spinal muscular atrophy: A retrospective feasibility study - Regensburger, Adrian; Wagner, Anna; Hanslik, Gregor; Schuessler, Stephanie C.; Fahlbusch, Fabian; Wölfle, Joachim; Juengert, Joerg; Trollmann, Regina; Knieling, Ferdinand (Muscle & Nerve, 2020)
CRIS-Team WoS Importer:2020-01-17

Ultrasound Localization Microscopy for the Assessment of Microvascular Circulation in Ischemic Perinatal Stroke - Regensburger, Adrian; Wachter, Felix; Denis, Louise; Mandelbaum, Henriette; Schey, Frauke; Bühler, Adrian; Siebenlist, Gregor; Schwarz, Simone; Schulz-Heise, Susanne; Rompel, Oliver; Trollmann, Regina; Wölfle, Joachim; et al. (Stroke, 2024)
CRIS-Team Scopus Importer:2024-11-15
Keywords: diagnostic imaging; microcirculation; neonate; stroke; ultrasound

Ultrasound Super-Resolution Imaging of Neonatal Cerebral Vascular Reorganization - Schwarz, Simone; Denis, Louise; Nedoschill, Emmanuel; Bühler, Adrian; Danko, Vera; Hilger, Alina; Brevis Nuñez, Francisco; Dürr, Nikola R.; Schlunz-Hendann, Martin; Brassel, Friedhelm; Felderhoff-Müser, Ursula; Reutter, Heiko Martin; et al. (Advanced Science, 2025)
During the first days of neonatal growth, the central nervous system (CNS) develops self-regulatory mechanisms to ensure constant cerebral perfusion. However, this vascular neogenesis takes place at a microscopic scale that cannot be observed with current clinical imaging techniques. Ultrasound localization microscopy (ULM) allows us to observe micro-vessels of the order of a few microns at depths of several centimeters. This can be done using conventional clinical ultrasound scanners and contrast sequences (CEUS). In this study, ULM is used to observe the human microvasculature in neonatal patients undergoing treatment for life-threatening malformations forming direct connections between the cerebral arterial and venous systems. It is observed that neuroendovascular treatment of neonatal arteriovenous malformations causes remodeling and reorganization of the cerebral vasculature by also activating corticomedullary vascular connections. ULM enables us to follow microvascular changes in human neonates with high spatio-temporal resolution. ULM may provide a novel clinical translatable tool, particularly including cerebral imaging in very young patients.
CRIS-Team Scopus Importer:2025-02-14
Keywords: CEUS; microbubbles; super-resolution imaging; ultrasound; ultrasound localization microscopy; Vein of Galen malformation

Umbilical cord blood stem cells: Induction of differentiation into mesenchymal lineages by cell-cell contacts with various mesenchymal cells - Park, Jung; Setter, Viviane; Wixler, Viktor; Schneider, Holm (Tissue Engineering - Part A, 2009)
CD133(+) cells isolated from bone marrow, peripheral blood, or umbilical cord blood (UCB) represent an established source of transplantable hematopoietic progenitors. Further, there is increasing evidence that such CD133(+) cell isolates comprise subpopulations capable of differentiating into several mesenchymal lineages. In this study, we investigated conditions under which mesenchymal differentiation can be induced, particularly the role of cell-cell contacts with mesenchymal cells. A purified, nearly homogeneous CD133(+) population of human UCB cells was expanded by stimulation with platelet-derived growth factor and epidermal growth factor, labeled with the fluorescent marker DiI and cocultivated with rat osteoblasts, C2C12 myoblasts, or rat cardiomyocytes, respectively. In control experiments, the two cell types were separated by microporous membranes to avoid cell-cell contacts. Direct coculture of DiI-labeled UCB cells with the different mesenchymal cell populations resulted in both significant morphological changes and upregulation of lineage-specific markers. Expression of osteocalcin, myosin heavy chain, or α-actinin confirmed differentiation of the UCB cells into an osteoblastic, myoblastic, or cardiomyocytic phenotype, respectively. In contrast, coculture of UCB cells with the respective inducer cells under conditions preventing cell-cell contacts yielded minor, if any, evidence for such differentiation. Our data, thus, indicate that UCB cell expansion in vitro and subsequent direct cell-cell contacts with mesenchymal cells can induce their differentiation into mesenchymal lineages specific to the cell type they are in contact with. This finding has important implications for understanding the homing of adult stem cells and the promise of UCB as a cell source for tissue engineering and regenerative medicine. © 2009, Mary Ann Liebert, Inc.
CRIS-Team Scopus Importer:2020-07-01

Umbilical venous catheter- and peripherally inserted central catheter-associated complications in preterm infants with birth weight < 1250 g: Results from a survey in Austria and Germany Nabelvenenkatheter- und periphere zentrale katheterassoziierte Komplikationen bei Frühgeborenen mit einem Geburtsgewicht < 1250 g: Ergebnisse einer Umfrage in Österreich und Deutschland - Hess, Steffi; Poryo, Martin; Boettger, Ralf; Franz, Axel; Klotz, Daniel; Linnemann, Knud; Ott, Torsten; Poeschl, Johannes; Schroth, Michael; Stein, Anja; Ralser, Elisabeth; Reutter, Heiko Martin; et al. (Wiener Medizinische Wochenschrift, 2022)
Background and objective: Umbilical venous catheters (UVC) and peripherally inserted central catheters (PICC) are commonly used in preterm infants but have been associated with a number of serious complications. We performed a survey in Austria and Germany to assess the use of UVCs and PICCs in preterm infants with a birth weight < 1250 g and associated rates of catheter-related adverse events. Methods: Electronic survey of participating centers of the NeoVitaA trial. Main outcome parameter was the reported rates of UVC- and PICC-associated complications (infection, thrombosis, emboli, organ injury, arrhythmia, dislocation, miscellaneous). Results: In total, 20 neonatal intensive care units (NICU) providing maximal intensive care in Austria and Germany (level I) were contacted, with a senior neonatologist response rate of 12/20 (60%). The reported rates for UVC with a dwell time of 1–10 days were bacterial infection: 4.2 ± 3.4% (range 0–10%); thrombosis: 7.3 ± 7.1% (0–20%); emboli: 0.9 ± 2.0% (0–5%); organ injury: 1.1 ± 1.9% (0–5%); cardiac arrhythmia: 2.2 ± 2.5% (0–5%); and dislocation: 5.4 ± 8.7% (0–30%); and for PICCs with a dwell time of 1–14 days bacterial infection: 15.0 ± 3.4% (range 2.5–30%); thrombosis; 4.3 ± 3.5% (0–10%); emboli: 0.8 ± 1.6% (0–5%); organ injury: 1.5 ± 2.3% (0–5%); cardiac arrhythmia: 1.5 ± 2.3% (0–5%), and dislocation: 8.5 ± 4.6% (0–30%). Conclusion: The catheter-related complication rates reported in this survey differed between UVCs and PICCs and were higher than those reported in the literature. To generate more reliable data on this clinically important issue, we plan to perform a large prospective multicenter randomized controlled trial investigating the non-inferiority of a prolonged UVC dwell time (up to 10 days) against the early change (up to 5 days) to a PICC.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Emboli; Infection; Organ injury; Peripherally inserted central catheter; Survey; Thrombosis; Umbilical venous catheter; Very low birth weight infants

Unbound corneocyte lipid envelopes in 12R-lipoxygenase deficiency support a direct role in lipid-protein crosslinking - Meyer, J. M.; Crumrine, D.; Schneider, Holm; Dick, Angela; Schmuth, M.; Gruber, R.; Radner, F.; Grond, S.; Wakefield, J.; Mauro, T.; Elias, P. (JOURNAL OF INVESTIGATIVE DERMATOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-28

Unbound Corneocyte Lipid Envelopes in 12R-Lipoxygenase Deficiency Support a Specific Role in Lipid-Protein Cross-Linking - Meyer, Jason M.; Crumrine, Debra; Schneider, Holm; Dick, Angela; Schmuth, Matthias; Gruber, Robert; Radner, Franz P.W.; Grond, Susanne; Wakefield, Joan S.; Mauro, Theodora M.; Elias, Peter M. (American Journal of Pathology, 2021)
Loss-of-function mutations in arachidonate lipoxygenase 12B (ALOX12B) are an important cause of autosomal recessive congenital ichthyosis (ARCI). 12R-lipoxygenase (12R-LOX), the protein product of ALOX12B, has been proposed to covalently bind the corneocyte lipid envelope (CLE) to the proteinaceous corneocyte envelope, thereby providing a scaffold for the assembly of barrier-providing, mature lipid lamellae. To test this hypothesis, an in-depth ultrastructural examination of CLEs was performed in ALOX12B−/− human and Alox12b−/− mouse epidermis, extracting samples with pyridine to distinguish covalently attached CLEs from unbound (ie, noncovalently bound) CLEs. ALOX12B−−/− stratum corneum contained abundant pyridine-extractable (ie, unbound) CLEs, compared with normal stratum corneum. These unbound CLEs were associated with defective post-secretory lipid processing, and were specific to 12R-LOX deficiency, because they were not observed with deficiency of the related ARCI-associated proteins, patatin-like phospholipase 1 (Pnpla1) or abhydrolase domain containing 5 (Abhd5). These results suggest that 12R-LOX contributes specifically to CLE–corneocyte envelope cross-linking, which appears to be a prerequisite for post-secretory lipid processing, and provide insights into the pathogenesis of 12R-LOX deficiency in this subtype of ARCI, as well as other conditions that display a defective CLE.
CRIS-Team Scopus Importer:2021-05-07

Under-expression of ?8 integrin aggravates experimental atherosclerosis - Menendez-Castro, Carlos; Cordasic, Nada; Neureiter, Daniel; Amann, Kerstin Ute; Marek, Ines; Volkert, Gudrun; Stintzing, Sebastian; Jahn, Angelika; Rascher, Wolfgang; Hilgers, Karl Friedrich; Hartner, Andrea (Journal of Pathology, 2015)
Integrins play an important role in vascular biology. The ?8 integrin chain attenuates smooth muscle cell migration but its functional role in the development of atherosclerosis is unclear. Therefore, we studied the contribution of ?8 integrin to atherosclerosis and vascular remodelling. We hypothesized that ?8 integrin expression is reduced in atherosclerotic lesions, and that its under-expression leads to a more severe course of atherosclerosis. ?8 Integrin was detected by immunohistochemistry and qPCR and ?8 integrin-deficient mice were used to induce two models of atherosclerotic lesions. First, ligation of the carotid artery led to medial thickening and neointima formation, which was quantified in carotid cross-sections. Second, after crossing into ApoE-deficient mice, the formation of advanced vascular lesions with atherosclerotic plaques was quantified in aortic en face preparations stained with Sudan IV. Parameters of renal physiology and histopathology were assessed: ?8 integrin was detected in the media of human and murine vascular tissue and was down-regulated in arteries with advanced atherosclerotic lesions. In ?8 integrin-deficient mice (?8(-/-) ) as well as ?8(+/-) and ?8(+/+) littermates, carotid artery ligation increased media:lumen ratios in all genotypes, with higher values in ligated ?8(-/-) and ?8(+/-) compared to ligated ?8(+/+) animals. Carotid artery ligation increased smooth muscle cell number in the media of ?8(+/+) mice and, more prominently, of ?8(-/-) or ?8(+/-) mice. On an ApoE(-/-) background, ?8(+/-) and ?8(-/-) mice developed more atherosclerotic plaques than ?8(+/+) mice. ?8 Integrin expression was reduced in ?8(+/-) animals. Renal damage with increased serum creatinine and glomerulosclerosis was detected in ?8(-/-) mice only. Thus, under-expression of ?8 integrin aggravates vascular lesions, while a complete loss of ?8 integrin results in reduced renal mass and additional renal disease in the presence of generalized atherosclerosis. Our data support the hypothesis that integrin ?8?1 has a protective role in arterial remodelling and atherosclerosis. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
EVALuna2:3752

Unexpected phenotypic variability in a family with epilepsy explained by independent segregation of biparental CACNA1A loss-of-function variants - Kraus, Cornelia; Mammadova, Dilbar; Leis, T.; Ekici, Arif Bülent; Thiel, C.; Reis, André; Trollmann, Regina (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Unilateral swelling of the lacrimal gland in a 15-year-old female patient - Berta, A. I.; Naumann-Bartsch, N.; Agaimy, Abbas; Metzler, Markus; Kruse, Friedrich; Holbach, L. (Ophthalmologe, 2013)
EVALuna2:6506

Unraveling the Genetics of Congenital Diaphragmatic Hernia: An Ongoing Challenge - Brosens, Erwin; Peters, Nina C.J.; van Weelden, Kim S.; Bendixen, Charlotte; Brouwer, Rutger W.W.; Sleutels, Frank; Bruggenwirth, Hennie T.; van Ijcken, Wilfred F.J.; Veenma, Danielle C.M.; Otter, Suzan C.M.Cochius Den; Wijnen, Rene M.H.; Eggink, Alex J.; et al. (Frontiers in Pediatrics, 2022)
Congenital diaphragmatic hernia (CDH) is a congenital structural anomaly in which the diaphragm has not developed properly. It may occur either as an isolated anomaly or with additional anomalies. It is thought to be a multifactorial disease in which genetic factors could either substantially contribute to or directly result in the developmental defect. Patients with aneuploidies, pathogenic variants or de novo Copy Number Variations (CNVs) impacting specific genes and loci develop CDH typically in the form of a monogenetic syndrome. These patients often have other associated anatomical malformations. In patients without a known monogenetic syndrome, an increased genetic burden of de novo coding variants contributes to disease development. In early years, genetic evaluation was based on karyotyping and SNP-array. Today, genomes are commonly analyzed with next generation sequencing (NGS) based approaches. While more potential pathogenic variants are being detected, analysis of the data presents a bottleneck—largely due to the lack of full appreciation of the functional consequence and/or relevance of the detected variant. The exact heritability of CDH is still unknown. Damaging de novo alterations are associated with the more severe and complex phenotypes and worse clinical outcome. Phenotypic, genetic—and likely mechanistic—variability hampers individual patient diagnosis, short and long-term morbidity prediction and subsequent care strategies. Detailed phenotyping, clinical follow-up at regular intervals and detailed registries are needed to find associations between long-term morbidity, genetic alterations, and clinical parameters. Since CDH is a relatively rare disorder with only a few recurrent changes large cohorts of patients are needed to identify genetic associations. Retrospective whole genome sequencing of historical patient cohorts using will yield valuable data from which today's patients and parents will profit Trio whole genome sequencing has an excellent potential for future re-analysis and data-sharing increasing the chance to provide a genetic diagnosis and predict clinical prognosis. In this review, we explore the pitfalls and challenges in the analysis and interpretation of genetic information, present what is currently known and what still needs further study, and propose strategies to reap the benefits of genetic screening.
CRIS-Team Scopus Importer:2022-02-25
Keywords: congenital; counseling; development; diaphragm; discordant monozygotic twin; foregut; genetics; hernia

Use of Continuous Glucose Monitoring in Pump Therapy Sensor Augmented Pump or Automated Insulin Delivery in Different Age Groups (0.5 to <26 Years) With Type 1 Diabetes From 2018 to 2021: Analysis of the German/Austrian/Swiss/Luxemburg DPV Registry - van den Boom, Louisa; Auzanneau, Marie; Wölfle, Joachim; Sindichakis, Marina; Herbst, Antje; Meraner, Dagmar; Hake, Kathrin; Klinkert, Christof; Gohlke, Bettina; Holl, Reinhard W. (Journal of diabetes science and technology, 2023)
Aim: Insulin pump, continuous glucose monitoring (CGM), and sensor augmented pump (SAP) technology have evolved continuously leading to the development of automated insulin delivery (AID) systems. Evaluation of the use of diabetes technologies in people with T1D from January 2018 to December 2021. Methods: A patient registry (Diabetes Prospective Follow-up Database [DPV]) was analyzed for use of SAP (insulin pump + CGM ≥90 days, no automated dose adjustment) and AID (HCL or LGS/PLGS). In total 46,043 people with T1D aged 0.5 to <26 years treated in 416 diabetes centers (Germany, Austria, Luxemburg, and Switzerland) were included and stratified into 4 groups A-D according to age. Additionally, TiR and HbA1c were analyzed. Results: From 2018 to 2021, there was a significant increase from 28.7% to 32.9% (sensor augmented pump [SAP]) and 3.5% to 16.6% (AID) across all age groups, with the most frequent use in group A (<7 years, 38.8%-40.2% and 10.3%-28.5%). A similar increase in SAP and AID use was observed in groups B (7 to <11 years) and C (11 to <16 years): B: +15.8 PP, C: +15.9 PP. HbA1c improved significantly in groups C and D (16 to <26 years) (both P <.01). Time in range (TiR) increased in all groups (A: +3 PP; B: +5 PP; C: +5 PP; D: +5 PP; P < 0.01 for each group). Insulin pumps (61.0% versus 53.4% male) and SAP (33.5% versus 28.9% male) are used more frequently in females. Conclusion: In recent years, we found an increasing use of new diabetes technologies and an improvement in metabolic control (TiR) across all age groups.
CRIS-Team Scopus Importer:2023-03-10
Keywords: automated insulin delivery; diabetes patient follow up; hybrid closed loop; sensor augmented pump therapy; type 1 diabetes

Using the existing registry Bestehendes Register nutzen - Holl, Reinhard W.; Wölfle, Joachim (Deutsches Ärzteblatt international, 2021)
CRIS-Team Scopus Importer:2021-08-20

Vaccination With Live Attenuated Vaccines in Four Children With Chronic Myeloid Leukemia While on Imatinib Treatment - Bettoni da Cunha-Riehm, Claudia; Hildebrand, Verena; Nathrath, Michaela; Metzler, Markus; Suttorp, Meinolf (Frontiers in Immunology, 2020)
Chronic myeloid leukemia (CML) in childhood and adolescence is a rare malignancy that can successfully be treated with the tyrosine kinase inhibitor (TKI) imatinib. According to the current experience, treatment is necessary for years and, in the majority of cases, a lifelong approach is required to control the malignant disease. To what extent imatinib causes immunosuppression in different age cohorts is a controversial discussion. According to general medical recommendations, live vaccines are contraindicated in individuals treated with imatinib. However, a recent increase in the number of globally reported cases of measles has been observed and continues to rise. Due to the high contagiousness of the virus, near-perfect vaccination coverage (herd immunity of 93 to 95%) is required to effectively protect against measles resurgence—a scenario that is not realistic in many countries. When four teenagers with CML (median age 13 years, range 12–15) who were enrolled into pediatric trial CML-paed II while on imatinib treatment (median treatment duration 36 months, range 11–84) were identified without protective measles and/or varicella titers, we carefully balanced the risks of a live vaccination under immunosuppressive TKI medication against the benefit of being protected. The patients underwent live vaccination with the live attenuated vaccines M-M-RVAX Pro® and Varivax® simultaneously (Patient #1), Priorix® and Varilix® consecutively (Patient #2), and Priorix® (Patients #3 and #4). While the first three patients were vaccinated while receiving TKI therapy, treatment with imatinib was interrupted in patient #4 for 1 week prior and 2 weeks after vaccination. Patients #1 and #3 reacted with stable long-term seroconversion. In Patient #2, serum titer conversion against measles and varicella could not be demonstrated and thus revaccination with Priorix® and Varilix® was performed 3 years later. However, protective titers did not develop or were lost again. Patient #4 also lost protective titers against measles when assessed 10 months after vaccination, but revaccination resulted in stable seroprotective titers over 12 months after the last vaccination during ongoing imatinib treatment. We conclude that in all patients, the safety of live vaccines could be documented, as no acute or late adverse events were observed. However, in line with observations that memory B-cells are lost under exposure to imatinib, revaccination may become necessary (two out of four patients in this small series lost their seroprotection). Considering that the number of cases is very small, we also suggest some criteria for decision-making regarding live vaccinations of CML patients treated with imatinib.
CRIS-Team Scopus Importer:2020-05-12
Keywords: chronic myeloid leukemia; imatinib; measles; mild immunosuppression; pediatric CML; tyrosine kinase inhibitors; vaccination; varicella

Vaccination with Live Attenuated Virus Vaccines in Four Pediatric Patients with CML While on Imatinib Treatment - Da Cunha-Riehm, Claudia Bettoni; Hildebrand, Verena; Nathrath, Michaela; Metzler, Markus; Suttorp, Meinolf (BLOOD, 2019)
CRIS-Team WoS Importer:2021-10-18

Variable White Matter Atrophy and Intellectual Development in a Family With X-linked Creatine Transporter Deficiency Despite Genotypic Homogeneity - Heussinger, Nicole; Saake, Marc; Mennecke, Angelika; Dörr, Helmuth-Günther; Trollmann, Regina (Pediatric Neurology, 2017)
The X-linked creatine transporter deficiency (CRTD) caused by an SLC6A8 mutation represents the second most common cause of X-linked intellectual disability. The clinical phenotype ranges from mild to severe intellectual disability, epilepsy, short stature, poor language skills, and autism spectrum disorders. The objective of this study was to investigate phenotypic variability in the context of genotype, cerebral creatine concentration, and volumetric analysis in a family with CRTD.The clinical phenotype and manifestations of epilepsy were assessed in a Caucasian family with CRTD. DNA sequencing and creatine metabolism analysis confirmed the diagnosis. Cerebral magnetic resonance imaging (cMRI) with voxel-based morphometry and magnetic resonance spectroscopy was performed in all family members.An SLC6A8 missense mutation (c.1169C>T; p.Pro390Leu, exon 8) was detected in four of five individuals. Both male siblings were hemizygous, the mother and the affected sister heterozygous for the mutation. Structural cMRI was normal, whereas voxel-based morphometry analysis showed reduced white matter volume below the first percentile of the reference population of 290 subjects in the more severely affected boy compared with family members and controls. Normalized creatine concentration differed significantly between the individuals (P < 0.005).There is a broad phenotypic variability in CRTD even in family members with the same mutation. Differences in mental development could be related to atrophy of the subcortical white matter.
EVALuna2:14646

Variants of the ectodysplasin A1 receptor gene underlying homozygous cases of autosomal recessive hypohidrotic ectodermal dysplasia - Wohlfart, Sigrun; Schneider, Holm (Clinical Genetics, 2019)
Hypohidrotic ectodermal dysplasia (HED) is a rare genetic condition resulting from defective development of ectodermal derivatives, such as hair, teeth, and sweat glands. Autosomal recessive (AR) forms of HED may be caused by pathogenic variants of the ectodysplasin A1 receptor (EDAR) gene that encodes a receptor involved in the NF-kappa B signaling pathway. Here, we describe three cases of AR-HED in families of Turkish, Austrian, and German-American origin (with or without known consanguinity). In these cases, two out-of-frame deletions and a pathogenic missense variant of EDAR were found to be disease-causing due to reduced availability of the respective messenger RNA or impaired interaction of the encoded protein with its binding partner leading to diminished signal transduction. The same missense variant, c.1258C>T (p.Arg420Trp), has actually been reported to be restricted to the Icelandic population and to be associated with non-syndromic tooth agenesis but not HED. As our patient has no known relationship to Icelandic individuals and displays a rather severe HED phenotype, we suggest that EDAR-Arg420Trp is a more widespread variant, possibly with variable clinical expressivity.
CRIS-Team WoS Importer:2019-03-06

What Is and Isn’t an Ectodermal Dysplasia? - Peschel, Nicolai; Schneider, Holm (Springer Nature, 2025)
This chapter discusses the classification of ectodermal dysplasias, which has evolved over decades from one based purely on clinical symptoms to one based on molecular changes and signaling pathways. As there are many different disease entities and a broad spectrum of clinical manifestations, a distinctive classification according to the molecular pathways or the cell structures involved is not only useful but has become the gold standard for classifying any group of rare genetic diseases. The general transition from a descriptive clinical to a molecular approach occurred because user-friendly and accessible molecular diagnostic tests are now available in almost every diagnostic laboratory and because the identification of pathogenic gene variants can often quickly objectify a clinical suspicion, allowing better comparability of the different patients seen by healthcare professionals.
CRIS-Team Scopus Importer:2025-05-02
Keywords: Classification; Criteria; Syndromes

X-chromosomal insertions at a recurrent site causing ectodermal dysplasia - Schneider, Holm; Mühle, Christiane (European Journal of Dermatology, 2009)
CRIS-Team Scopus Importer:2020-07-01

X-linked variations in SHROOM4 are implicated in congenital anomalies of the urinary tract and the anorectal, cardiovascular and central nervous systems - Kolvenbach, Caroline M.; Felger, Tim; Schierbaum, Luca; Thiffault, Isabelle; Pastinen, Tomi; Szczepanska, Maria; Zaniew, Marcin; Adamczyk, Piotr; Bayat, Allan; Yilmaz, Oeznur; Lindenberg, Tobias T.; Thiele, Holger; et al. (Journal of Medical Genetics, 2022)
BackgroundSHROOM4 is thought to play an important role in cytoskeletal modification and development of the early nervous system. Previously, single-nucleotide variants (SNVs) or copy number variations (CNVs) in SHROOM4 have been associated with the neurodevelopmental disorder Stocco dos Santos syndrome, but not with congenital anomalies of the urinary tract and the visceral or the cardiovascular system. MethodsHere, exome sequencing and CNV analyses besides expression studies in zebrafish and mouse and knockdown (KD) experiments using a splice blocking morpholino in zebrafish were performed to study the role of SHROOM4 during embryonic development. ResultsIn this study, we identified putative disease-causing SNVs and CNVs in SHROOM4 in six individuals from four families with congenital anomalies of the urinary tract and the anorectal, cardiovascular and central nervous systems (CNS). Embryonic mouse and zebrafish expression studies showed Shroom4 expression in the upper and lower urinary tract, the developing cloaca, the heart and the cerebral CNS. KD studies in zebrafish larvae revealed pronephric cysts, anomalies of the cloaca and the heart, decreased eye-to-head ratio and higher mortality compared with controls. These phenotypes could be rescued by co-injection of human wild-type SHROOM4 mRNA and morpholino. ConclusionThe identified SNVs and CNVs in affected individuals with congenital anomalies of the urinary tract, the anorectal, the cardiovascular and the central nervous systems, and subsequent embryonic mouse and zebrafish studies suggest SHROOM4 as a developmental gene for different organ systems.
CRIS-Team WoS Importer:2022-12-16

Zoledronic Acid Add-on Therapy for Standard-Risk Ewing Sarcoma Patients in the Ewing 2008R1 Trial - Koch, Raphael; Haveman, Lianne; Ladenstein, Ruth; Brichard, Benedicte; Jürgens, Heribert; Cyprova, Sona; van den Berg, Henk; Hassenpflug, Wolf; Raciborska, Anna; Ek, Torben; Baumhoer, Daniel; Egerer, Gerlinde; et al. (Clinical Cancer Research, 2023)
PURPOSE: The phase III, open-label, prospective, multicenter, randomized Ewing 2008R1 trial (EudraCT2008-003658-13) was conducted in 12 countries to evaluate the effect of zoledronic acid (ZOL) maintenance therapy compared with no add-on regarding event-free survival (EFS, primary endpoint) and overall survival (OS) in standard-risk Ewing sarcoma (EWS). PATIENTS AND METHODS: Eligible patients had localized EWS with either good histologic response to induction chemotherapy and/or small tumors (<200 mL). Patients received six cycles of VIDE induction and eight cycles of VAI (male) or eight cycles of VAC (female) consolidation. ZOL treatment started parallel to the sixth consolidation cycle. Randomization was stratified by tumor site (pelvis/other). The two-sided adaptive inverse-normal four-stage design (planned sample size 448 patients, significance level 5%, power 80%) was changed after the first interim analysis using the Müller-Schäfer method. RESULTS: Between April 2010 and November 2018, 284 patients were randomized (142 ZOL/142 no add-on). With a median follow-up of 3.9 years, EFS was not significantly different between ZOL and no add-on group in the adaptive design (HR, 0.74; 95% CI, 0.43-1.28, P = 0.27, intention-to-treat). Three-year EFS rates were 84.0% (95% CI, 77.7%-90.8%) for ZOL vs. 81.7% (95% CI, 75.2%-88.8%) for no add-on. Results were similar in the per-protocol collective. OS was not different between groups. The 3-year OS was 92.8% (95% CI, 88.4%-97.5%) for ZOL and 94.6% (95% CI, 90.9%-98.6%) for no add-on. Noticeable more renal, neurologic, and gastrointestinal toxicities were observed for ZOL (P < 0.05). Severe renal toxicities occurred more often in the ZOL arm (P = 0.003). CONCLUSIONS: In patients with standard-risk localized EWS, there is no additional benefit from maintenance treatment with ZOL.
CRIS-Team Scopus Importer:2023-12-29